A simple power management circuit for microbial fuel cell operation with intermittent electrical load connection - Woodward, Lyne; Tartakovsky, Boris (The Canadian Journal of Chemical Engineering, 2018)
Practical implementation of microbial fuel cell (MFC)‐based power sources requires stable MFC performance regardless of the variations in the composition and quantity of a carbon source (fuel). This study describes a simple power management circuit (PMC) utilizing low and high voltage boundaries for intermittent MFC connection and disconnection to the electrical load. The PMC performance is demonstrated during MFC operation at carbon source‐replete and carbon source‐deplete conditions. In spite of MFC operation at external resistance values significantly below the estimated internal MFC resistance (e.g., 5.5 versus 24.5 Ω, respectively), the proposed PMC optimized MFC performance at all tested influent acetate concentrations, resulting in a volumetric power output of up to 56 mW · L⁻¹. Furthermore, MFC operation with an up‐converter is tested and approaches for optimizing the voltage boundaries are discussed. The robustness and simplicity of the proposed PMC algorithm allows for its implementation in a standalone microprocessor with ultralow energy consumption, which enables MFC application as an autonomous power source.
Keywords: microbial fuel cell; intermittent connection; power management

Liquid-applied air barrier systems for high-rise buildings: code requirements and performance testing - Riahinezhad, Marzieh; Masson, J-F; Lacasse, Michael; Di Lenardo, Bruno; Collins, Peter (Building Envelope Technology Symposium, September 2018, Mississauga, Canada, 2018)
Air barrier systems (ABS) are specified in Canadian codes to minimize the infiltration and exfiltration of air through the building envelope in order to control the risk of condensation. However, since the publication of the Energy Code of Canada in 2014, more attention has been drawn to the importance of an air barrier system to control the loss of energy. Recently, the Canadian Construction Material Centre (CCMC) developed performance criteria for liquid-applied ABS, including installation, barrier, and durability criteria. The CCMC is a recognized body that provides guidance to building officials with respect to the National Building Code of Canada (NBC) and the evaluation and testing of innovative products as alternative solutions meeting the requirements of the NBC. The performance criteria for an ABS will be of interest to air barrier material and air barrier system providers, architects, industry consultants, and contractors.
Keywords: air barrier systems; performance assessment; accelerated aging

Analysis of wall exterior temperature and humidity data to characterise component aging conditions - Riahinezhad, Marzieh; Eve, Augusta; Armstrong, Marianne; Masson, Jean-Francois (Durability and Climate Change: Changing Climatic Loads as May Affect the Durability of Building Materials, Components and Assemblies, Proceedings of CIB/NRC Symposium, 2018)
The study of building materials durability and aging are essential to characterize new products, optimize the performance of buildings and adjust the building code for the climate found in Canada. To understand how the properties of a material change over the span of its service life, accelerated aging is often performed. The prerequisite to effective accelerated aging of building materials used in the building envelope is to have a thorough understanding of the aging conditions in the building envelope. To this effect, temperature and relative humidity data within the envelope of the Canadian Centre for Housing Technology (CCHT) at the National Research Council of Canada was examined. This is an instrumented house with brick cladding for which data was recorded on an hourly basis from 2004 to 2009. The data reported is for a south-facing and east-facing walls, and a south facing roof. The temperature data for the south facing wall was used to determine fluctuations in the high-ends of the average monthly temperatures. The monthly temperatures varied from ‒25 °C to +45°C for the years 2004-2009, from which the normalized average temperature distribution was calculated. The results showed two distinct peaks one at about 0˚C and the other one at 20˚C (Figure 1). These two peaks suggest the bimodal distribution of data for the “hot” months (April to September) and “cold” months (October to March).
Keywords: accelerated aging; building material humidity; material ageing; temperature

Parser combinators for Tigrinya and Oromo morphology - Littell, Patrick; McCoy, Tom; Han, Na-Rae; Rijhwani, Shruti; Sheikh, Zaid; Mortensen, David; Mitamura, Teruko; Levin, Lori (Eleventh International Conference on Language Resources and Evaluation, 2018)
We present rule-based morphological parsers in the Tigrinya and Oromo languages, based on a parser-combinator rather than finite-state paradigm. This paradigm allows rapid development and ease of integration with other systems, although at the cost of non-optimal theoretical efficiency. These parsers produce multiple output representations simultaneously, including lemmatization, morphological segmentation, and an English word-for-word gloss, and we evaluate these representations as input for entity detection and linking and humanitarian need detection.
Keywords: morphology; parsing; Tigrinya; Oromo

Understanding emotions: a dataset of tweets to study interactions between affect categories - Mohammad, Saif M.; Kiritchenko, Svetlana (Eleventh International Conference on Language Resources and Evaluation, 2018)
Human emotions are complex and nuanced. Yet, an overwhelming majority of the work in automatically detecting emotions from text has focused only on classifying text into positive, negative, and neutral classes, and a much smaller amount on classifying text into basic emotion categories such as joy, sadness, and fear. Our goal is to create a single textual dataset that is annotated for many emotion (or affect) dimensions (from both the basic emotion model and the VAD model). For each emotion dimension, we annotate the data for not just coarse classes (such as anger or no anger) but also for fine-grained real-valued scores indicating the intensity of emotion (anger, sadness, valence, etc.). We use Best–Worst Scaling (BWS) to address the limitations of traditional rating scale methods such as inter-and intra-annotator inconsistency by employing comparative annotations. We show that the fine-grained intensity scores thus obtained are reliable (repeat annotations lead to similar scores). We choose Twitter as the source of the textual data we annotate because tweets are self-contained, widely used, public posts, and tend to be rich in emotions. The new dataset is useful for training and testing supervised machine learning algorithms for multi-label emotion classification, emotion intensity regression, detecting valence, detecting ordinal class of intensity of emotion (slightly sad, very angry, etc.), and detecting ordinal class of valence (or sentiment). We make the data available for the recent SemEval-2018 Task 1: Affect in Tweets, which explores these five tasks. The dataset also sheds light on crucial research questions such as: which emotions often present together in tweets?; how do the intensities of the three negative emotions relate to each other?; and how do the intensities of the basic emotions relate to valence?
Keywords: emotion intensity; valence; arousal; dominance; basic emotions; crowdsourcing; sentiment analysis

Word affect intensities - Mohammad, Saif M. (Eleventh International Conference on Language Resources and Evaluation, 2018)
Words often convey affect—emotions, feelings, and attitudes. Further, different words can convey affect to various degrees (intensities). However, existing manually created lexicons for basic emotions (such as anger and fear) indicate only coarse categories of affect association (for example, associated with anger or not associated with anger). Automatic lexicons of affect provide fine degrees of association, but they tend not to be accurate as human-created lexicons. Here, for the first time, we present a manually created affect intensity lexicon with real-valued scores of intensity for four basic emotions: anger, fear, joy, and sadness. (We will subsequently add entries for more emotions such as disgust, anticipation, trust, and surprise.) We refer to this dataset as the NRC Affect Intensity Lexicon, or AIL for short. AIL has entries for close to 6,000 English words. We used a technique called best–worst scaling (BWS) to create the lexicon. BWS improves annotation consistency and obtains reliable fine-grained scores (split-half reliability > 0.91). We also compare the entries in AIL with the entries in the NRC VAD Lexicon, which has valence, arousal, and dominance (VAD) scores for 20K English words. We find that anger, fear, and sadness words, on average, have very similar VAD scores. However, sadness words tend to have slightly lower dominance scores than fear and anger words. The Affect Intensity Lexicon has applications in automatic emotion analysis in a number of domains such as commerce, education, intelligence, and public health. AIL is also useful in the building of natural language generation systems
Keywords: emotion intensity; emotion lexicon; emotion analysis; crowd sourcing; best-worst scaling; sentiment analysis

WikiArt emotions: an annotated dataset of emotions evoked by Art - Mohammad, Saif M.; Kiritchenko, Svetlana (Eleventh International Conference on Language Resources and Evaluation, 2018)
Art is imaginative human creation meant to be appreciated, make people think, and evoke an emotional response. Here for the first time, we create a dataset of more than 4,000 pieces of art (mostly paintings) that has annotations for emotions evoked in the observer. The pieces of art are selected from WikiArt.org's collection for four western styles (Renaissance Art, Post-Renaissance Art, Modern Art, and Contemporary Art). The art is annotated via crowdsourcing for one or more of twenty emotion categories (including neutral). In addition to emotions, the art is also annotated for whether it includes the depiction of a face and how much the observers like the art. The dataset, which we refer to as the {\it WikiArt Emotions Dataset}, can help answer several compelling questions, such as: what makes art evocative, how does art convey different emotions, what attributes of a painting make it well liked, what combinations of categories and emotions evoke strong emotional response, how much does the title of an art impact its emotional response, and what is the extent to which different categories of art evoke consistent emotions in people. We found that fear, happiness, love, and sadness were the dominant emotions that also obtained consistent annotations among the different annotators. We found that the title often impacts the affectual response to art. We show that pieces of art that depict faces draw more consistent emotional responses than those that do not. We also show, for each art category and emotion combination, the average agreements on the emotions evoked and the average art ratings. The WikiArt Emotions dataset also has applications in automatic image processing, as it can be used to develop systems that detect emotions evoked by art, and systems that can transform existing art (or even generate new art) that evokes the desired affectual response.
Keywords: opinion mining/sentiment analysis; emotion recognition/generation

Time-delay signature concealed broadband gain-coupled chaotic laser with fiber random grating induced distributed feedback - Xu, Yanping; Zhang, Liang; Lu, Ping; Mihailov, Steven; Chen, Liang; Bao, Xiaoyi (Optics & Laser Technology, 2018)
A broadband chaotic laser with a flat power spectrum extending up to ∼7.53 GHz is achieved by injecting continuous wave laser light into a chaotic diode laser perturbed by fiber random grating induced distributed feedback, which forms a gain-coupled chaotic laser system. More than triple bandwidth enhancement is realized with appropriate frequency detuning between the master and slave lasers. Unlike normal chaotic lasers, the output from such a broadband chaotic laser is free from time-delay signature, which can be potentially applied for practical random number generations and will find useful applications in the fields of information security and computation systems.
Keywords: lasers; distributed-feedback; semiconductor lasers; instabilities and chaos

Thermal properties of doubly reinforced fiberglass/epoxy composites with graphene nanoplatelets, graphene oxide and reduced-graphene oxide - Rafiee, M.; Nitzsche, F.; Laliberte, J.; Hind, S.; Robitaille, F.; Labrosse, M. R. (Composites Part B: Engineering, 2018)
A novel manufacturing method based on Vacuum Assisted Resin Transfer Molding (VARTM) was devised to incorporate carbon nanoparticles for the enhancement of thermal properties of multiscale laminates. Several graphene-based nanomaterials including graphene oxide (GO), reduced graphene oxide (rGO), graphene nanoplatelets (GNPs) and multi-walled carbon nanotubes (MWCNTs) were used to modify the epoxy matrix and the surface of glass fibers. The thermal, rheological and morphological properties of the resulting glass fiber-reinforced multiscale composites were investigated. The thermal properties of the epoxy/nanoparticle composites were studied through thermal conductivity measurements, differential scanning calorimetry (DSC) and thermo-gravimetric analysis (TGA). The thermal characterization results showed that the introduction of GNPs, GO, rGO, and MWCNTs enhanced thermal conductivity. Compared with the neat epoxy/fiberglass composite control results, improvement in thermal conductivity of fiberglass/epoxy modified with MWCNTs 0.3%, GNPs 1%, GO 2% and rGO 0.042% were 8.8%, 12.6%, 8.2% and 4.1%, respectively. It was concluded that for the same volume fraction of nanoparticles, the thermal conductivity improvement in graphene nanoplatelets-modified composites is more pronounced compared with other nanoparticles. A better dispersion of nanoparticles and a better interfacial interaction between nanoparticles and epoxy are essential in enhancing the thermal conductivity of nanocomposite materials.
Keywords: polymer composites; graphene; thermal properties; thermal conductivity; multiscale composite laminates

Survey of peptide quantification methods and comparison of their reproducibility: a case study using oxytocin - Li, Chensheng; Bhavaraju, Sitaram; Thibeault, Marie-Pier; Melanson, Jeremy; Blomgren, Andreas; Rundlöf, Torgny; Kilpatrick, Eric; Swann, Carolyn J.; Rudd, Timothy; Aubin, Yves; Grant, Kevin; Butt, Margaret; et al. (Journal of Pharmaceutical and Biomedical Analysis, 2018)
USP’s peptide reference standards content is typically determined using an HPLC assay against an external standard for which the purity was determined by a mass balance approach. To explore the use of other analytical methods, the USP Biologics Department conducted a multi-laboratory collaborative study. The study determined the inter-laboratory variability for peptide quantitation using the following methods: HPLC assay, quantitative nuclear magnetic resonance (qNMR) spectroscopy, or amino acid analysis (AAA). The three methods were compared with regard to their suitability for quantitation of the nonapeptide oxytocin. In this study, the HPLC assay method using the same peptide bulk material as the standard showed the lowest inter-lab variability. The coefficient of variation (%CV) was calculated without counting the uncertainty associated with the purity assignment of the standard with mass balance. The proton qNMR method is a direct measurement of the peptide against an internal standard, which is not difficult to perform under common laboratory conditions. Because of the simpler operation and shorter analytical time, qNMR as a primary method for peptide reference standard value assignment deserves further exploration.
Keywords: peptide; quantification; HPLC; NMR; amino acid analysis (AAA)

What color are emergency exit signs? Egress behavior differs from verbal report - Kinateder, Max; Warren, William H.; Schloss, Karen B. (Applied Ergonomics, 2018)
Illuminated emergency exit signs inform building occupants about safe egress routes in emergencies. These exit signs are often found in the presence of other colored signs, which may distract occupants when searching for safe exits. Such distractions can lead to confusing and even harmful outcomes, especially if occupants misinterpret the sign colors, mistaking non-exit signs for exit signs. We studied which colored signs people were most likely to infer were exit signs in a simulated emergency evacuation using virtual reality (VR). Participants were immersed in a virtual room with two doors (left and right), and an illuminated sign with different colored vertical bars above each door. They saw all pairwise combinations of six sign colors across trials. On each trial, a fire alarm sounded, and participants walked to the door that they thought was the exit. We tested two hypotheses: a local exposure hypothesis that color inferences are determined by exit sign colors in the local environment (i.e., red) and a semantic association hypothesis that color inferences are determined by color-concept associations (i.e. green associated with “go” and “safety”). The results challenged the local exposure hypothesis and supported the semantic association hypothesis. Participants predominantly walked toward green signs, even though the exit signs in the local environment—including the building where the experiment took place—were red. However, in a post-experiment survey, most participants reported that exit signs should be red. The results demonstrated a dissociation between the way observers thought they would behave in emergency situations (red = exit) and the way they did behave in simulated emergencies (green = exit). These findings have implications for the design of evacuation systems. Observers, and perhaps designers, do not always anticipate how occupants will behave in emergency situations, which emphasizes the importance of behavioral evaluations for egress safety.
Keywords: emergency exit signs; evacuation; virtual reality; color cognition; visual reasoning

Subtle changes in the combining site of the Chlamydiaceae-specific mAb S25-23 increase the antibody–carbohydrate binding affinity by an order of magnitude - Haji-Ghassemi, Omid; Müller-Loennies, Sven; Brooks, Cory L.; Mackenzie, C. Roger; Caveney, Nathanael; Van Petegem, Filip; Brade, Lore; Kosma, Paul; Brade, Helmut; Evans, Stephen V. (Biochemistry, 2018)
Murine antibodies S25-23, S25-26, and S25-5 derive from a common germ-line origin, and all bind the Chlamydiaceae family-specific epitope αKdo(2→8)αKdo(2→4)αKdo (where Kdo is 3-deoxy-α-d-manno-oct-2-ulosonic acid) with high affinity and specificity. These antibodies recognize the entire trisaccharide antigen in a linkage-dependent manner via a groove composed largely of germ-line residues. Despite sharing identical heavy and light chain genes, S25-23 binds the family-specific epitope with nanomolar affinity, which is an order of magnitude higher than that of S25-26, while S25-5 displays an affinity between those of S25-23 and S25-26. We determined the high-resolution crystal structures of S25-23 and S25-5 antigen binding fragments in complex with a pentasaccharide derived from the LPS of Chlamydia and measured the affinity of S25-5 for chlamydial LPS antigens using isothermal titration microcalorimetry. The 1.75 Å resolution structure of S25-23 shows how subtle conservative mutations Arg(L)-27E to lysine and Ser(H)-56 to threonine lead to an order of magnitude increase in affinity. Importantly, comparison between previous S25-26 structures and the 1.99 and 2.05 Å resolution liganded and unliganded structures of S25-5, respectively, shows how a Ser(L)-27E mutation results in an intermediate affinity due to the reduced enthalpic penalty associated with complex formation that would otherwise be required for arginine in this position. This strategy allows for subtle adjustments in the combining site via affinity maturation that have dramatic consequences for the affinity of an antibody for its antigen.

Reliability assessment of pulsed thermography and ultrasonic testing for impact damage of CFRP panels - Duan, Yuxia; Zhang, Hai; Maldague, Xavier P.V.; Ibarra-Castanedo, Clemente; Servais, Pierre; Genest, Marc; Sfarra, Stefano; Meng, Jianqiao (NDT & E International, 2018)
In order to quantitatively compare the reliability of pulsed thermography and ultrasonic testing techniques, a set of thirty-five Carbon Fiber Reinforced Plastic (CFRP) composite panels with impact damages are inspected by pulsed thermography and ultrasonic C-scan. The comparative experimental results and Probability of Detection (PoD) analysis results are presented. The quantitative comparison shows that pulsed thermography testing has smaller defect size at 90% PoD with 95% confidence level, i.e. a90/95 values than ultrasonic testing for the parameters and setup used in the inspections of these thirty-five CFRP composite panels.
Keywords: thermography; ultrasonic testing; CFRP; impact damage; probability of detection

Real-time random grating sensor array for quasi-distributed sensing based on wavelength-to-time mapping and time-division multiplexing - Liu, Jingxuan; Lu, Ping; Mihailov, Stephen J.; Wang, Muguang; Yao, Jianping (Optics Letters, 2018)
A real-time random grating sensor array for quasi-distributed sensing based on spectral-shaping and wavelength-to-time (SS-WTT) mapping and time-division multiplexing is proposed and experimentally demonstrated. The sensor array consists of multiple random gratings written in a single-mode fiber (SMF) at different physical locations. When the temperature or strain applied to a particular random grating is changed, the central wavelength of the reflection spectrum of the random grating will change, which is converted to the time domain as a time shift based on SS-WTT using a linearly chirped fiber Bragg grating. After detection at a photodetector, an electrical waveform with the time shift information encoded in the random waveform is obtained, which is further compressed by correlation to increase the time resolution. As a demonstration, a real-time quasi-distributed sensing system based on a two-random-grating array is implemented. The results show that the sensing resolutions for temperature and strain are 0.23°C and 2.5 μϵ, respectively, and the accuracies for temperature and strain are 0.11°C and 1.2 μϵ, respectively. Compared with a conventional quasi-distributed sensor, our proposed sensing system has key advantages, including real-time sensing, high-resolution interrogation, and large scalability.

Quantification of natural products in herbal supplements: a combined NMR approach applied on goldenseal - Le, Phuong Mai; Milande, Clément; Martineau, Estelle; Giraudeau, Patrick; Farjon, Jonathan (Journal of Pharmaceutical and Biomedical Analysis, 2018)
Authentication of natural products is of major relevance in the context of manufactured drugs or herbal supplements since such active products generate a lucrative market. The analytical method to identify and quantify valuable natural products is critical for quality control and product assignment of herbal supplements. In this framework, we propose to apply a recently developed quantitative 2D NMR approach called Q QUIPU (Quick QUantItative Perfected and pUre shifted) in combination with 1D 1H NMR capable to access the concentration of three major alkaloids, berberine, β-hydrastine and canadine, in the root extract of goldenseal (Hydrastis canadensis), one of the 20 most popular herbal supplements used worldwide. We highlight the complementarity of 1D and 2D quantitative NMR to accurately assess the amount of alkaloids with different range of concentrations and stability within extracts. In particular, unstable natural products having non-overlapped signals like berberine could only be quantified by sensitive and fast 1D 1H, while overlapped signals of β-hydrastine and low intense ones of canadine could only be quantified with the recent 2D Q QUIPU HSQC. Results obtained from this combined approach have led to a good accuracy (<10%) as compared with coupled UHPLC-MS/UV techniques. This quantitative NMR approach paves the way to numerous applications where the accurate quantification of targeted compounds in complex mixtures is required, for instance in agricultural, food and pharmaceuticals products.
Keywords: herbal supplements; goldenseal (Hydrastine canadensis); alkaloids; quantitative NMR; 1D 1H; 2D Q QUIPU HSQC

Process development for an inducible rituximab-expressing Chinese hamster ovary cell line - Mellahi, Kahina; Cambay, Florian; Brochu, Denis; Gilbert, Michel; Perrier, Michel; Ansorge, Sven; Durocher, Yves; Henry, Olivier (Biotechnology Progress, 2018)
Inducible mammalian expression systems are becoming increasingly available and are not only useful for the production of cytotoxic/cytostatic products, but also confer the unique ability to uncouple the growth and production phases. In this work, we have specifically investigated how the cell culture state at the time of induction influences the cumate‐inducible expression of recombinant rituximab by a GS‐CHO cell line. To this end, cells grown in batch and fed‐batch cultures were induced at increasing cell densities (1 to 10 × 10 6 cells/mL). In batch, the cell specific productivity and the product yield were found to reduce with increasing cell density at induction. A dynamic feeding strategy using a concentrated nutrient solution applied prior and postinduction allowed to significantly increase the integral of viable cells and led to a 3‐fold increase in the volumetric productivity (1.2 g/L). The highest product yields were achieved for intermediate cell densities at induction, as cultures induced during the late exponential phase (10 × 10 6 cells/mL) were associated with a shortened production phase. The final glycosylation patterns remained however similar, irrespective of the cell density at induction. The kinetics of growth and production in a 2 L bioreactor were largely comparable to shake flasks for a similar cell density at induction. The degree of galactosylation was found to decrease over time, but the final glycan distribution at harvest was consistent to that of the shake flasks cultures. Taken together, our results provide useful insights for the rational development of fed‐batch cell culture processes involving inducible CHO cells.

Prediction of acid rock drainage in waste rock piles Part 1: Water film model for geochemical reactions and application to a full-scale case study - Ma, Liang; Huang, Cheng; Liu, Zhong-Sheng; Morin, Kevin A.; Aziz, Mike; Meints, Cody (Journal of Contaminant Hydrology, 2018)
Geochemical reactions taking place at the rock surface and pore water interface, and rapid preferential water flow through waste rock piles are identified as two primary steps for acid rock drainage (ARD) and metal leaching (ML) processes. This paper (Part I) develops a water film model to describe the interactions among sulphide minerals, pore water and oxygen, which considers the reactive surface areas as the primary sites to capture geochemical reactions including sulphide oxidation and neutralization reactions, and also considers acid and metal ion storage in pore water. In addition, the proposed water film model is further coupled with a pile-scale mass transport model to investigate a specific case of the main waste rock pile at the Equity Silver mine, Canada. Overall, the simulated profile of oxygen concentration matches the historical monitoring data. The modeling results revealed potential controlling mechanisms for ARD generation inside the waste rock pile and provided insights into the impact of an engineered cover on the waste rock pile.
Keywords: water film model; geochemical reactions; mass transport; acid rock drainage; waste rock pile; equity silver mine

Pre-clinical translation of second harmonic microscopy of meniscal and articular cartilage using a prototype nonlinear microendoscope - Baskey, Stephen J.; Andreana, Marco; Lanteigne, Eric; Ridsdale, Andrew; Stolow, Albert; Schweitzer, Mark E. (IEEE Journal of Translational Engineering in Health and Medicine, 2018)
Previous studies using nonlinear microscopy have demonstrated that osteoarthritis (OA) is characterized by the gradual replacement of Type II collagen with Type I collagen. The objective of this study was to develop a prototype nonlinear laser scanning microendoscope capable of resolving the structural differences of collagen in various orthopaedically relevant cartilaginous surfaces. The current prototype developed a miniaturized femtosecond laser scanning instrument, mounted on an articulated positioning system, capable of both conventional arthroscopy and second-harmonic laser-scanning microscopy. Its optical system includes a multi-resolution optical system using a gradient index objective lens and a customized multi-purpose fiber optic sheath to maximize the collection of backscattered photons or provide joint capsule illumination. The stability and suitability of the prototype arthroscope to approach and image cartilage were evaluated through preliminary testing on fresh, minimally processed, and partially intact porcine knee joints. Image quality was sufficient to distinguish between hyaline cartilage and fibrocartilage through unique Type I and Type II collagen-specific characteristics. Imaging the meniscus revealed that the system was able to visualize differences in the collagen arrangement between the superficial and lamellar layers. Such detailed in vivo imaging of the cartilage surfaces could obviate the need to perform biopsies for ex vivo histological analysis in the future, and provide an alternative to conventional external imaging to characterize and diagnose progressive and degenerative cartilage diseases such as OA. Moreover, this system is readily customizable and may provide a suitable and modular platform for developing additional tools utilizing femtosecond lasers for tissue cutting within the familiar confines of two or three portal arthroscopy techniques.
Keywords: arthroscopy; cartilage; collagen; diagnostics; histology; microscopy; orthopaedics; osteoarthritis; second harmonic imaging; surgical assist devices

Optimization of production of vesicular stomatitis virus (VSV) in suspension serum-free culture medium at high cell density - Elahi, Seyyed Mehdy; Shen, Chun Fang; Gilbert, Rénald (Journal of Biotechnology, 2018)
During the last decade, oncolytic viruses such as vesicular stomatitis virus (VSV) have gained tremendous popularity as efficient vaccines for infectious diseases as well as for the treatment of cancer. Our laboratory has developed two stable cell lines, 293SF-3F6 (derived from HEK293A cells) and SF-BMAdR cells (a variant of A549 that expresses the E1 region of human adenovirus). These two cell lines were adapted to grow efficiently in suspension culture and in serum-free medium. In this report we evaluated the production of a recombinant VSV expressing the green fluorescent protein (VSV-GFP) in these two stable cell lines. At a relatively low cell density of 500,000 cells per ml, 293SF-3F6 produced 4.6 times more infectious particles than SF-BMAdR cells. There was a positive correlation between volumetric virus titer and cell density up to 2.E + 07 cells/ml. A fed-batch process using an in-house medium and feed was developed to support the growth of 293SF-3F6 cells up to a concentration of 1.E + 07 cells/ml for infection at higher cell density and VSV production at high titer. Shifting the temperature from 37 °C to 34 °C at infection time improved VSV titer up to 3.3 fold. After scaling up the optimal condition from small scale (3 ml) to larger volumes (50 & 200 ml), the maximal volumetric titer obtained using the 293SF-3F6 cells was in average 2.9E + 10 extracellular infectious particles/ml. In conclusion, our data demonstrated that 293SF-3F6 cells, for which a cGMP master cell bank is available, is a performant cell line to scale up VSV production in suspension culture using serum-free medium.
Keywords: oncolytic viruses; Vesicular stomatitis virus (VSV); stable cell line; fed-batch process; suspension culture

Novel electrochemical half-cell design and fabrication for performance analysis of metal-air battery air-cathodes - Zhang, Lei; Zhang, Jiujun (International Journal of Green Energy, 2018)
Metal-air batteries (MABs) are considered promising candidates for sustainable energy storage & conversion applications. Air-cathodes have been identified to be the major challenge towards the commercialization of MAB technology. In development of air-cathodes effectively, a method, or a device is desired for cathode evaluation at operating conditions that are as close as possible to that of an actual battery. In this paper, for diagnosing, evaluating and analyzing the electrochemical performance of MAB air-cathodes, a novel electrochemical half-cell has been designed and fabricated. This half-cell is a three-electrode system, in which the air-cathode is used as the working electrode, a platinum wire with large area as the counter electrode and a saturated calomel electrode (SCE) as the reference electrode. The working electrode is designed to allow the surface of gas diffusion layer to be exposed to the air and the catalyst layer to be exposed to the electrolyte. This half-cell is validated by commercially available and in-house made air cathodes using electrochemical linear scan voltammetry (LSV) method in both neutral and alkaline solutions at various temperatures, enabling the in-situ performance evaluation and analysis of air-cathodes in an environment much closer to that of a primary aqueous metal-air battery while offering a more controlled laboratory environment and economic way for down-selecting and optimizing the air-cathodes.
Keywords: metal-air batteries; oxygen reduction reaction; electrochemical half-cell; air cathodes; half-cell design

Multiclass nonnegative matrix factorization for comprehensive feature pattern discovery - Li, Yifeng; Pan, Youlian; Liu, Ziying (IEEE Transactions on Neural Networks and Learning Systems, 2018)
In this big data era, interpretable machine learning models are strongly demanded for the comprehensive analytics of large-scale multiclass data. Characterizing all features from such data is a key but challenging step to understand the complexity. However, existing feature selection methods do not meet this need. In this paper, to address this problem, we propose a Bayesian multiclass nonnegative matrix factorization (MC-NMF) model with structured sparsity that is able to discover ubiquitous and class-specific features. Variational update rules were derived for efficient decomposition. In order to relieve the need of model selection and stably describe feature patterns, we further propose MC-NMF with stability selection, an ensemble method that collectively detects feature patterns from many runs of MC-NMF using different hyperparameter values and training subsets. We assessed our models on both simulated count data and multitumor ribonucleic acid-seq data. The experiments revealed that our models were able to recover predefined feature patterns from the simulated data and identify biologically meaningful patterns from the pan-cancer data.
Keywords: big data; cancer; feature pattern discovery; multiclass nonnegative matrix factorization (MC-NMF); stability selection

Real-time change point detection using on-line topic models - Wang, Yunli; Goutte, Cyril (Proceedings of the 27th International Conference on Computational Linguistics, 2018)
Detecting changes within an unfolding event in real time from news articles or social media enables to react promptly to serious issues in public safety, public health or natural disasters. In this study, we use on-line Latent Dirichlet Allocation (LDA) to model shifts in topics, and apply on-line change point detection (CPD) algorithms to detect when significant changes happen. We describe an on-line Bayesian change point detection algorithm that we use to detect topic changes from on-line LDA output. Extensive experiments on social media data and news articles show the benefits of on-line LDA versus standard LDA, and of on-line change point detection compared to off-line algorithms. This yields F-scores up to 56% on the detection of significant real-life changes from these document streams.

Highly active and stable ruthenate pyrochlore for enhanced oxygen evolution reaction in acidic medium electrolysis - Feng, Qi; Wang, Qi; Zhang, Zhen; Xiong, Yongyueheng; Li, Hanyi; Yao, Yao; Yuan, Xiao-Zi; Williams, Mark C.; Gu, Meng; Chen, Hong; Li, Hui; Wang, Haijiang (Applied Catalysis B: Environmental, 2018)
Developing active, acid-stable and cost-effective electrocatalysts for oxygen evolution reaction (OER) is a primary challenge to directly produce hydrogen from water electrolysis. IrO2 is the best-known catalyst in acid medium due to its good activity and stability, but it’s too expensive to be used in large amounts. To overcome this economical constraint, the use of low amount of iridium electrocatalyst is required. Recently, ruthenium pyrochlore oxides (A2Ru2O7−δ) as OER catalysts have drawn extensive interests due to reduced content of precious metal relative to RuO2 or IrO2, though their OER catalytic activity still needs to be further improved. In this work, we, for the first time, developed a highly active and stable Y1.85Zn0.15Ru2O7−δ electrocatalyst, the A site doped yttrium ruthenate pyrochlore for OER. The mechanism of A site doped ruthenate pyrochlore improving OER performance is revealed. The partial substitution of Y3+ ions by smaller Zn2+ leads to a formation of oxygen vacancies and mixed valences of Ru (Ru4+ and Ru5+), which, in turn, significantly alter the electronic properties and thus the electrocatalytic activity and electrical conductivity of the developed electrocatalyst for OER. The Y1.85Zn0.15Ru2O7−δ/acetylene black (AB) electrocatalyst exhibits sevenfold higher activity than the IrO2/AB reference catalyst; twofold higher activity than Y2Ru2O7−δ/AB, with a Tafel slope of 36.9 mV dec−1; and higher stability than IrO2/AB in acidic media. Using a home-made proton exchange membrane electrolyser device, a high cell performance is achieved at 25 °C with an electrolysis current density of 0.46 A cm-2, confirming a promising prospect of Y1.85Zn0.15Ru2O7−δ electrocatalyst for practical water electrolysis applications.
Keywords: oxygen evolution reaction; Eelectrocatalyst; water electrolysis; pyrochlore oxides; acid media

High rate CO2 photoreduction using flame annealed TiO2 nanotubes - Kar, Piyush; Zeng, Sheng; Zhang, Yun; Vahidzadeh, Ehsan; Manuel, Ajay; Kisslinger, Ryan; Alam, Kazi M.; Thakur, Ujwal K.; Mahdi, Najia; Kumar, Pawan; Shankar, Karthik (Applied Catalysis B: Environmental, 2018)
The photocatalytic reduction of CO2 into light hydrocarbons using sunlight and water is a challenging reaction involving eight electron transfer steps; nevertheless, it has great potential to address the problem of rising anthropogenic carbon emissions and enable the use of fossil fuels in a sustainable way. Several decades after its first use, TiO2 remains one of the best performing and most durable photocatalysts for CO2 reduction albeit with a poor visible light absorption capacity. We have used flame annealing to improve the response of TiO2 to visible photons and engineered a nanotubular morphology with square-shaped cross-sections in flame-annealed nanotubes. An enhanced CH4 yield was achieved in the photoreduction of CO2 using flame annealed TiO2 nanotubes, and isotope labeled experiments confirmed the reaction products to originate from the CO2 reactant. Flame-annealed TiO2 nanotubes formed in aqueous electrolyte (FANT-aq) yielded 156.5 μmol gcatalyst–1.hr–1 of CH4, which is in the top tier of reported performance values achieved using TiO2 as a stand-alone photocatalyst. This performance resulted because appreciable amounts of CH4 were generated under visible light illumination as well. TiO2 nanotubes exhibited CO2 photoreduction activity up to a wavelength of 620 nm with visible light driven photocatalytic activity peaking at 450 nm for flame annealed TiO2 nanotubes. Isotope labelling studies, using GC–MS and gas-phase FTIR, indicated photoreduction of 13CO2 to 13CH4. The detection of 13CO in the product mixture, and the absence of HCHO and HCOOH provides strong support for the photoreduction proceeding along a carbene pathway. The enhanced CO2 photoreduction performance of FANT-aq is attributed to increased visible light absorption, square morphology, and the presence of rutile as the only crystalline phase with (110) as the dominant plane.
Keywords: solar fuel; carbon dioxide photoreduction; mass spectrometry; FTIR; semiconductor; photocatalysis; FDTD simulations

First quantification of <2 μm clay, <0.2 μm ultrafines and solids wettability in process streams from naphthenic froth treatment plant at commercial mined oil sands operations - Mercier, Patrick H. J.; Tyo, Daniel D.; Zborowski, Andre; Kung, Judy; Patarachao, Bussaraporn; Kingston, David M.; Couillard, Martin; Robertson, Gilles; Mccracken, Thom; Ng, Samson (Fuel, 2018)
For the first time in oil sands industry, the absolute amounts of <2 μm clay and <0.2 μm ultrafine solids were quantified in commercial streams from the naphthenic froth treatment (NFT) process used by mined oil sands operators. The sample suite studied comprised seven representative NFT streams collected at a commercial plant including: one bitumen froth feed (F1), two naphtha-diluted bitumen products (P1, P2) and four tailings (T1, T2, T3, T4). The solids present in each of the seven NFT streams were fractionated quantitatively based on particle size and solids wettability using three original quantitative separation techniques presented here. First, clay-ultrafines (CUF) separation technique allows to fractionate solids into four distinct particle-size fractions: coarser solids (CS), >2 μm; total clays (TC), <2 μm; coarse clays (CC), 0.2–2 μm; and ultrafines (UF), <0.2 μm. Second, toluene/water (T/W) interfacial wettability (WET) fraction separation technique enables separation of solids into four distinct fractions: Hydrophilic Solids (HPS) partitioning into the aqueous phase (carbon <5% w/w); Intermediate Solids (IS) only weakly held at the T/W interface (carbon 6–10% w/w); organic-rich solids (ORS) remaining strongly held at the T/W interface (carbon 15–20% w/w); high speed centrifugation solids (HSCS) remaining dispersed in the bitumen-toluene phase (carbon >20% w/w). And third, toluene/water interfacial total solids (TS) separation permits to isolate all-at-once the entire solids fraction comprised in a given sample. The analytical procedures developed to apply these three techniques are outlined in detail, and compared to two standard methods used in the oil sands industry: Soxhlet-Dean and Stark extraction method and COSIA Unified Fines Method for minus 44 µm material and for Particle Size Distribution (PSD). From quantitative results obtained by CUF, WET and TS techniques and industry standard PSD methods, the following key results arise. Most notably, CUF technique developed here showed >10 wt% ultrafines in samples T4, P1 and P2, whereas industry standard PSD methods (laser diffraction PSD data) did not notice any significant differences between the seven samples. The UF contents per total solids increase in going from froth F1 (∼2.5 wt%) through product P1 (∼9.3 wt%) to product P2 (∼11 wt%). Tailings T4 has the highest proportion of UF (∼12 wt%) amongst the four tailings, and also has the highest amounts of HPS, TC, and CC of any streams. NFT stream T4 therefore likely results from a separation process which selectively removes the smaller hydrophilic solids. The ORS and HSCS proportions per total solids increase in going from froth F1 through product P1 to product P2. For product P2, the ORS and HSCS contents account respectively for ∼70 wt% and ∼10 wt% of the solids contained in this sample. By contrast, as ORS and HSCS increase, the HPS contents decrease correspondingly. This inverse behavior between HPS and ORS + HSCS contents demonstrates the preferential removal of hydrophilic solids by the NFT processes. X-ray diffraction patterns measured for HSCS fractions separated from froth F1 and products P1 and P2 are virtually the same. This suggests that HSCS solids are present in the inlet froth and go through the entire NFT circuit without being affected by any of the different separation unit operations integrated in the NFT process flowsheet.
Keywords: oil sands; bitumen production; naphthenic froth treatment; ultrafines; clays; solids wettability

Failure analysis of adhesively bonded GFRP/aluminum matrix single composite lap joint with cold worked penetrative reinforcements - Fawcett, Andrew; Chen, Xiaohu; Huang, Xiao; Li, Chun (Composites Part B: Engineering, 2018)
A new cold worked, penetrative mechanical reinforcement method was evaluated for its potential to enhance joining between 2024-T3 aluminum matrix and glass fiber reinforced polymer (GFRP) for aerospace and automotive applications. In this study, the aluminum substrate surface was modified using a new cold working process which formed hooks directly from the substrate material. This surface was then treated with grit blast and Sol-Gel surface treatment before it was co-cured to both side of a GFRP, forming a single lap joint for testing. This type of joints was compared to a baseline bonded joint without mechanical reinforcement using the same surface treatment. The joint strength and fatigue performance of these sets of samples were experimentally evaluated under quasi-static and fatigue loading conditions. The bonded joints with penetrative mechanical reinforcements withstood greater peak load and higher strain prior to failure, as compared to non-reinforced bonded joints. Fatigue testing on the other hand showed better performance of non-reinforced joints over the reinforced ones. The failure surfaces of both quasi-static samples and fatigue samples were evaluated using a scanning electron microscope to determine failure mode(s). It was determined that the stress concentration at the base of reinforcements could be the main underlying cause for earlier onset of fatigue failure of reinforced samples.
Keywords: penetrative reinforcement; glass fiber reinforced polymers; compositesHybrid joints

End-user experience with the SCoTSS Compton imager and directional survey spectrometer - Sinclair, Laurel E.; Mccann, Andrew; Saull, Patrick R.B.; Mantifel, Rodger L.; Ouellet, Christian V.O.; Drouin, Pierre-Luc; Macleod, Audrey M.L.; Le Gros, Brian; Summerell, Ian; Hovgaard, Jens H.; Monkhouse, Stephen; Stanescu, Flaviu; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2018)
The Silicon photomultiplier-based Compton Telescope for Safety and Security (SCoTSS) has been developed incorporating end-user requirements into the design process. The end-user group includes those responsible for mobile survey in the event of a radiological or nuclear accident, those responsible for radiation survey support to security operations at major events and at Canadian borders, as well as some of those responsible for Canadian defense applications. The SCoTSS development program has reached a technology readiness level of eight, and we are proceeding with field trials of the instrument in high-fidelity operational environments. Prospective end users have been involved in trial set up and execution, assuring applicability in their mission spaces. SCoTSS has been subject to trials involving hidden sources, heavily shielded sources, imager moving with respect to source, and complicated man-made surroundings. Our operators value high sensitivity for anomaly geolocation and mapping. End users also require an instrument which is capable of direction reconstruction in motion, as well as rapid imaging of a field of view. We have developed a “time to image” measure which allows for quantitative comparison of imagers of fundamentally different technology, where one design may have an advantage in terms of energy resolution and compactness and another design may have an advantage in terms of efficiency and cost effectiveness. We present here the performance of the SCoTSS imager in rapid direction finding. As well, we compare the time to image quantity for the SCoTSS imager and the H3D Polaris-H Quad imager where the data were taken under equivalent conditions. This quantitative measure of imaging performance can allow operators to make an informed choice of the design that meets their needs taking into consideration also weight and size as well as budgetary constraints.
Keywords: compton imaging; compton telescope; scintillator; security; radiation detection

Emerging technologies and learning innovation in the new learning ecosystem - Fournier, Helene; Molyneaux, Heather; Kop, Rita (Information Systems and Technologies to Support Learning, 2018)
This paper highlights a decade of research by the National Research Council in the area of Personal Learning Environments, including MOOCs and learning in networked environments. The value of data analytics, algorithms, and machine learning is explored in more depth, as well as challenges in using personal learning data to automate the learning process, the use of personal learning data in educational data mining (EDM), and important ethics and privacy issues around networked learning environments.
Keywords: personal learning environments; data analytics; algorithms; machine learning; ethics and privacy

Effects of oxidation-resistant coating on creep behavior of modified 9Cr-1Mo steels - Zhang, X. Z.; Wu, X. J.; Liu, R.; Yao, M. X. (Materials Science and Engineering: A, 2018)
Oxidation is a life-limiting factor for material durability. In this study, constant-load creep tests are conducted on modified 9Cr-1Mo steel (F91) with an oxidation-resistant coating, MCrAlY, to evaluate the coating effect on the creep behavior. The creep strain vs. time curves are compared with that of the uncoated material under constant-load conditions. The previously developed deformation-mechanism based true-stress (DMTS) model and the composite stress rule are applied to analyze the creep data for the coated material coupons. This way, the effect of coating and the contributions from material-intrinsic deformation mechanisms, i.e., intragranular dislocation glide and climb, as well as grain boundary sliding, are all delineated quantitatively. The model is shown to describe well the entire creep deformation process consisting of primary, steady-state, and tertiary creep of the F91 with MCrAlY coating.
Keywords: deformation-mechanism based creep model; oxidation-resistant coating; MCrAlYModified 9Cr-1Mo steel

Effect of prior creep strain on high cycle fatigue life of TI 834 - Wu, Xijia; Seo, Dongyi; Head, Marc; Chan, Stephen (Journal of Engineering for Gas Turbines and Power, 2018)
Room-temperature fatigue tests were conducted on Ti 834 with prior creep strains accumulated under constant load at 550 °C and 600 °C, respectively. Microstructural and fractographic examinations on specimens with prior creep strain > 3% revealed the failure process consisting of multiple surface crack nucleation and internal void generation by creep, followed by fatigue crack propagation in coalescence with the internally distributed damage, leading to the final fracture. The amount of prior creep damage increased with creep strain. The fatigue life of Ti 834 was significantly reduced by prior creep straining. The behavior is rationalized with the integrated creep-fatigue theory.

Effect of diesel injection timing on the combustion of natural gas/diesel dual-fuel engine at low-high load and low-high speed conditions - Yousefi, Amin; Guo, Hongsheng; Birouk, Madjid (Fuel, 2018)
Past research has shown that advancing diesel injection timing is a promising approach to decrease the unburned methane and greenhouse gas (GHG) emissions of natural gas/diesel dual-fuel engines at lower engine loads. However, this benefit may not persist under medium to high load-low speed conditions. To explore this, the present paper uses experiments and detailed computational fluid dynamic (CFD) modeling to investigate the impacts of diesel injection timing on the combustion and emissions performance of a heavy-duty natural gas/diesel dual-fuel engine under four different engine load-speed conditions. The results showed that advancing diesel injection timing increases the peak pressure, thermal efficiency, and NOx emissions for all examined engine load-speed conditions. Advancing diesel injection timing also significantly decreases the unburned methane and CO2-equivalent (GHG) emissions of the dual-fuel engine under low load-low speed and medium load-high speed conditions. The concentration of OH and CH4 revealed that the central part of the combustion chamber is the main source of the unburned methane emissions under low load-low speed and medium load-high speed conditions, and advancing diesel injection timing significantly improves the combustion of natural gas-air mixture in this region. However, advancing diesel injection timing slightly increases the unburned methane emissions trapped in the crevice volume. However, this slight increase in the unburned methane emissions in the crevice volume is much lower than its significant decrease in the central region of the combustion chamber. At medium to high load-low speed conditions, there is almost no unburned methane in the central part of the combustion chamber, and the crevice region is considered as the main source of unburned methane emissions. As a result, advancing diesel injection timing does not improve the combustion of natural gas-air mixture in the central part of the combustion chamber but slightly increases the unburned methane trapped in the crevice region. This is the main reason that advancing diesel injection timing slightly increases the unburned methane emissions under medium to high load-low speed conditions. Overall, advancing diesel injection timing significantly increases thermal efficiency and decreases the unburned methane and GHG emissions under low load-low speed and medium load-high speed conditions. It improves the thermal efficiency under medium to high load-low speed conditions, but comes at the expense of increased methane and unchanged GHG emissions.
Keywords: dual-fuel combustion; diesel engine; diesel injection timin; emissions

Current situation of carbon dioxide capture, storage, and enhanced oil recovery in the oil and gas industry - Adu, Emmanuel; Zhang, Yindi; Liu, Dehua (The Canadian Journal of Chemical Engineering, 2018)
Carbon capture and storage (CCS) is an important low‐carbon management technology used to reduce CO2 emissions with the captured anthropogenic CO2 for enhanced oil recovery (EOR). This paper provides an overview and analysis of current issues related to CCS projects and CCS technologies. The paper also assesses risks and costs as well as policy, legal, and regulatory frameworks relevant for CCS and the major countries with CCS deployment. Currently, the few CCS projects in operation are mostly for EOR purposes. However, miscible CO2‐EOR in depleted oil and gas reservoirs appears to be the industry's first choice for CO2 sequestration and increasing oil production. Potential CO2 leakage is a major risk for pipelines and geological storage and a comprehensive monitoring program needs to be developed to ascertain its impact on pipeline material integrity, humans, and the environment. The cost of the CCS chain largely depends on the compression solvent for the synthesis gas or flue gas treatment for separation, heat rate, energy required for capture, capital costs of capture equipment, pipeline diameter, and flow capacity, and the homogeneity and permeability of the geological formations. An effective carbon pricing and cap‐and‐trade system as a part of national carbon policy is needed to achieve the goal of CCS. This paper finally discusses China's carbon capture utilization and storage (CCUS) systems and proposes a new CCUS‐LNG transportation process system for the coastal areas of China. Special attention was focused on CO2 transportation, CCUS‐EOR, and a new CCUS‐LNG process system for China.
Keywords: CCS; enhanced oil recovery; CCUS-LNG; cost; policy

The United States Coast Guard Polar Icebreaker Program: shifting left to ensure success - Hutchison, S.; Simmons, G.; Wang, J.; Millan, J. (The ITEA Journal of Test and Evaluation, 2018)

Model tests of the United States Coast Guard Heavy Polar Icebreaker indicative designs - Wang, Jungyong; Akinturk, Ayhan; Brown, Jeffrey; Muselet, Caroline; Millan, James (OTC Arctic Technology Conference, 2018)
This paper describes the results of model tests carried out in ice and open water conditions to evaluate performance of the United States Coast Guard (USCG) Heavy Polar Icebreaker (HPIB) indicative design. The resistance, propulsion and manoeuvring performance in ice conditions was evaluated at three different ice thicknesses (4, 6 and 8 ft.) with flexural strength 100 psi using two power setups, 36500 HP and 65000 HP. Calm water resistance and propulsion tests were also performed to evaluate open water performance. Models were constructed and tested corresponding to two indicative designs, one with triple shaft propulsion system and the other with one centre shaft and two wing podded propulsors. The present paper describes only the results for the model with triple shaft propulsion system.

Heavy impact test site (HITS) simulations - Gagnon, R; Quinton, B.; Mackay, J. (Proceedings of the 24th IAHR International Symposium on Ice, June 4 to 9, 2018, Vladivostok, Russia, 2018)

Calgary flood mitigation research - Cornett, A.; Knox, P. (Canadian Society for Civil Engineering, 2018)

Assessment of debris issues impacting design of a flood diversion project in a large scale physical model - Knox, P.; Cornett, A.; Provan, M. (2018)

Hydrodynamic analysis of core-loc units via controlled drop tests - Cornett, A. (2018)

Experimental study of velocity deficit and wake due to single and multiple rectangular porous plates in steady flow - Knox, Paul (2018)

A multi-role reconfigurable trainer for naval combat information operators - Emond, Bruno; Kondratova, Irina; Durand, Guillaume; Valdés, Julio (I/ITSEC Papers Online Repository, 2018)
The paper describes our efforts to identify a key set of requirements for a Naval Combat Information Operators training simulation based on a MultiRole Reconfigurable Trainer framework. The project was executed for the Royal Canadian Navy by the National Research Council Canada with the collaboration of Defence Research and Development Canada. The main training issue to be addressed is to augment team training readiness in the transition from individual training to team training. The training domain use case was the acquisition of tactical voice procedures by novice AntiSubmarine Plotting Operators (ASPO), a skill domain particularly suited for a learning-by-doing approach using training simulations. The project explored training technologies that use synthetic teammates to improve the readiness of novice individuals to participate in live team training. The approach we used to achieve this objective included a literature review of key technology areas of interests, training application prototyping, and generation of simulated data of learners’ performance. Each of these aspects of the approach is discussed in the corresponding section. The focus of the literature review was on technologies incorporating synthetic teammates using automatic speech recognition and speech synthesis to capture trainees’ utterances and simulate teammates communication. The section on the training application prototype presents a use case for the verbal tactical procedure which provided the basis to develop the software’s interactive workflows, and, in particular, the construction of a Multi-Role Reconfigurable Trainer prototype. The section on simulated data provides examples of three learning analytics methods applied to a simulated dataset for a group of trainees learning the tactical verbal procedure associated with an initial contact report. Finally, a conclusion reviews the main project results, and identifies possible areas for future research work.

A semi-empirical pod model for USCG icebreaker mackinaw. Part II. The model - Lau, Michael (Proceedings of the 24th IAHR International Symposium on Ice, 2018)
A semi-empirical pod model is developed based on experimental data for the USCGC Mackinaw to predict propulsion forces for the icebreaker driven by twin podded propulsors. The experiments are conducted in straight-ahead motion with the azimuth angle of one of the twin pods steered in a range from 0 to 180o. In this pod model, assumption was made to extend the test data to the full range of 360o azimuth angles and advance coefficients. Since all the tests are carried out in straight ahead motion only with a constant heading, analysis was performed to extend these functions to general cases of arbitrary planar motions. Three pod models were presented with varying degrees of complexity. Model I is the simplest model, applying the nondimensional longitudinal and transverse force coefficients obtained from the straight-ahead motion at known advance coefficient and azimuth angle directly to any motion. In Model II, the influence of geometrical drift angle local to the pods is added to Model I. In Model III, the influence of hull-pod interaction on the geometrical drift angle is added to further refine the model treatment. These models are implemented in the NRC/OCRE-RC’s in-house maneuvering simulation software OSIS-IHI and their validity assessed. The comparison of Model III with comprehensive model test and limited sea trial data shows good agreement. Based on the validation results, it is concluded that the final model (Model III) can be used successfully for motion simulation of pod-driven ships.

A semi-empirical pod model for USCG icebreaker mackinaw. Part I. The empirical data - Lau, Michael (Proceedings of the 24th IAHR International Symposium on Ice, 2018)
A semi-empirical pod model is developed based on experimental data for the USCGC Mackinaw to predict propulsion forces for the icebreaker driven by twin podded propulsors. The experiments are conducted in straight-ahead motion with the azimuth angle of one of the twin pods steered in a range from 0 to 180o. In this pod model, assumption was made to extend the test data to the full range of 360o azimuth angles and advance coefficients. Analysis was then performed to allow these test data for application of any planar motion including turning by considering hull-pod interaction. This is Part I of a two-part paper. In this paper, the results from ice tank tests are presented. These include steering moment generated by the propulsors, thrust and torque of the propellers and the forces exerted on the hull at the location of the connection of the propulsors. The procedure to extend the empirical data to the full range is then presented. The agreement between static and dynamic data and the symmetry of the data is considered.

A physics-based roubble mound stability simulator for armour layers - Latham, John-Paul; Xiang, Jiansheng; Via-Estrem, Lluis; Higuera, P.; Douglas, S.; Nistor, I.; Cornett, Andrew; Logan, S.; Baird, W. F. (Coasts, Marine Structures and Breakwaters 2017: Realising the Potential, 2018)
A decade of research into forward modelling the individual responses of concrete armour units or quarried rock armour in rubble mound structures has had significant breakthroughs in recent years with the inclusion of wave interaction effects. Progress towards providing a physics-based simulator for armour movements is demonstrated including a comparison with equivalent experimentally-measured flume tests for Core-Loc structures conducted in Sogreah’s laboratories in 2009. The authors introduce these advances and discuss the likelihood that coastal engineers will, within the next decade, be using new physics-based simulation tools to supplement their customary design methods and wave tank laboratory testing. In this spotlight, attention falls on a renewed research effort towards experimental validation studies. New experiments are needed to transfer the current proof-of-concept FEMDEM numerical approaches into useable validated tools for coastal engineers.

Extreme wave pressures and loads on a pile-supported wharf deck: influences of air gap and wave direction - Cornett, Andrew (Coastal Engineering 2018: Proceedings of the 36th International Conference, 2018)
Many deck-on-pile structures are located in shallow water depths at elevations low enough to be inundated by large waves during intense storms or tsunami. Many researchers have studied wave-in-deck loads over the past decade using a variety of theoretical, experimental, and numerical methods. Wave-in-deck loads on various pile supported coastal structures such as jetties, piers, wharves and bridges have been studied by Tirindelli et al. (2003), Cuomo et al. (2007, 2009), Murali et al. (2009), and Meng et al. (2010). All these authors analyzed data from scale model tests to investigate the pressures and loads on beam and deck elements subject to wave impact under various conditions. Wavein- deck loads on fixed offshore structures have been studied by Murray et al. (1997), Finnigan et al. (1997), Bea et al. (1999, 2001), Baarholm et al. (2004, 2009), and Raaij et al. (2007). These authors have studied both simplified and realistic deck structures using a mixture of theoretical analysis and model tests. Other researchers, including Kendon et al. (2010), Schellin et al. (2009), Lande et al. (2011) and Wemmenhove et al. (2011) have demonstrated that various CFD methods can be used to simulate the interaction of extreme waves with both simple and more realistic deck structures, and predict wave-in-deck pressures and loads.

Assessment of debris mitigation systems for tidal and river turbines - Cornett, Andrew; Provan, Mitchel; Bear, Michael (International Energy Agency. Ocean Energy Systems, 2018)
The potential for dangerous interactions with floating debris is a leading consideration when evaluating potential sites for deployment of hydrokinetic power systems, yet to date, relatively little research effort has been directed towards developing and proving effective devices and systems for protecting turbines from floating debris. This paper presents and discusses results from a series of 1/10 scale model experiments conducted by the National Research Council, Canada, working in collaboration with New Energy Corp, in which the effectiveness of six different debris barriers was assessed in steady flows up to 3 m/s. This research contributes important new knowledge concerning the performance of debris mitigation systems for use with floating hydrokinetic turbines deployed in rivers, estuaries and coastal waters.
Keywords: river turbines; tidal turbines; debris barrier

Comparison of large woody debris prototypes in a large scale non-flume physical model - Perry, Brian; Rennie, Colin; Cornett, Andrew; Knox, Paul (E3S Web of Conferences, 2018)
Due to excessive rainfall in June of 2013, several rivers located in and near the City of Calgary, Canada experienced significant flooding events. These events caused severe damage to infrastructure throughout the city, precipitating a renewed interest in flood control and mitigation strategies for the area. A major potential strategy involves partial diversion of Elbow River flood water to the proposed Springbank Off-Stream Storage Reservoir. A large scale physical model study was conducted to optimize and validate the design of a portion of the new project. The goals of the physical model were to investigate diversion system behaviors such as flow rates, water levels, sediment transport and, debris accumulation, and optimize the design of new flow control structures to be constructed on the Elbow River. In order to accurately represent the behavior of debris within the system due to flooding, large woody debris created from natural sources was utilized in the physical model and its performance was compared to that of debris of the same size fabricated from pressed cylindrical wood dowels. In addition to comparing the performance of these two debris types, the impact of root wads on debris damming was also investigated. Significant differences in damming behavior was shown to exist between the natural debris and the fabricated debris, while the impact of root wad on damming affected the dam structure and formation. The results of this experiment indicate that natural debris is preferred for studies involving debris accumulation.

Review of bridge design practice for water loads, scour, and ice action: opportunities for climate resilience - Murphy, Enda; Pilechi, Vahid; Barrette, Paul; Khaliq, M. Naveed; Almansour, Husham ([Proceeding: CSCE 2018 Annual Conference], 2018)
An appraisal of historical and recent damage to bridges in Canada and internationally underlines the risks posed by water loads, scour and ice effects. More than 50% of bridge failures in North America are attributed to floods and hydraulic factors, including scour, debris impacts and ice effects. River ice is a unique challenge for bridges in northern climates, with estimates of annual average damages in Canada due to ice jams exceeding $100 million. The rising costs and damages associated with extreme weather events highlight the vulnerabilities of Canadian infrastructure to climate change. Potential changes in exposure to ice and flood hazards (from riverine, pluvial, and coastal sources) pose a threat to the integrity and sustainability of transportation infrastructure, including bridges and overpasses. The Canadian Highway Bridge Design Code contains provisions for evaluating water loads, scour and ice action for new bridges, and refers to the Transportation Association of Canada’s (TAC) Guide to Bridge Hydraulics for additional guidance. However, there are no provisions for evaluating potential climate change impacts on these loads and actions. A review of the current state of bridge design practice for evaluating, mitigating and adapting to water loads, scour, ice action and related climate change impacts was conducted. This included an appraisal of bridge design codes, standards and guidelines in Canada and other countries. The review identified current gaps, emerging best practices, and possible steps towards improving design guidance and the resilience of Canadian bridges and overpasses to water loads, scour, ice action and climate change.

An illustration of acceptable ice conditions for vessel station-keeping operations in pack ice - Sayed, Mohammed; Islam, Shameem; Watson, David; Wright, Brian (The proceedings of the Twenty-Eighth (2018) International Ocean and Polar Engineering Conference Sapporo, Japan, June 10-15, 2018, 2018)
This paper provides an illustration of how to assess acceptable ice conditions for vessel stationkeeping in pack ice. Numerical simulations are used to examine pack ice interaction with a moored/thruster-assisted vessel, including maximum forces and vessel responses. The ice dynamics model utilized for this purpose is based on solving the equations of momentum and a failure criterion. The station-keeping vessel is modeled as a rigid body with three degrees-of-freedom: surge, sway and yaw. Here, ice conditions and vessel characteristics are chosen within a range of values that are relevant to operations on the Grand Banks during seasonal pack ice intrusions. The simulations examine the influence of several variables, including ice coverage, ice thickness, velocity, floe size, peak forces and vessel offsets. The influence of these variables on peak ice forces and key vessel responses is evaluated from an operating envelope point of view.
Keywords: stationkeeping; ice; dynamic positioning; ice forces; mooring; FPSO; numerical simulations

Application of sorptive passive panels for reducing indoor formaldehyde level: effect of environmental conditions - Bahri, Mitra; Kabambi, Jean Leopold; Yakobi-Hancock, Jacqueline; Render, William; So, Stephanie (World Academy of Science, Engineering and Technology (International Journal of Architectural and Environmental Engineering), 2018)
Reducing formaldehyde concentration in residential buildings is an important challenge, especially during the summer. In this study, a ceiling tile was used as a sorptive passive panel for formaldehyde removal. The performance of this passive panel was evaluated under different environmental conditions. The results demonstrated that the removal efficiency is comprised between 40% and 71%. Change in the level of relative humidity (30%, 50%, and 75%) had a slight positive effect on the sorption capacity. However, increase in temperature from 21 °C to 26 °C led to approximately 7% decrease in the average formaldehyde removal performance. GC/MS and HPLC analysis revealed the formation of different by-products at low concentrations under extreme environmental conditions. These findings suggest that the passive panel selected for this study holds the potential to be used for formaldehyde removal under various conditions.
Keywords: Formaldehyde; indoor air quality; passive panel; removal efficiency; sorption

Ice clearing to support near-field operations - Kennedy, Allison; Harris, Trevor; Reid, Veronica (Offshore Technology Conference, 2018)
Ice management is an important consideration for any offshore petroleum operation conducted in an area that could encounter sea ice. Ice management could be performed for a number of reasons: to reduce global ice loads on the installation, to avoid ice interaction with underwater components such as risers or turrets, or to allow for close proximity operations such as loading / offloading, manning / de-manning, or evacuation in the case of an emergency event. The purpose of this project is to provide baseline information relating to ice clearing operations conducted in pack ice conditions. This information includes outcomes of different ice clearing operations in terms of loads on a GBS structure and ice concentration upstream of the GBS structure. It also includes loads measured on the support vessel that is conducting the ice clearing operations for a subset of the clearing techniques considered. To investigate this problem, model testing experiments were conducted in NRC-OCRE's ice tank located in St. John's NL, Canada. These experiments involved systematic testing involving various pack ice conditions representative of the Grand Banks area and two models: a support vessel and a GBS structure. The environmental conditions included: two ice concentrations, two ice piece sizes, and two ice piece drift speeds. Four ice clearing techniques were tested in each condition. The ice clearing techniques included two fixed position tests; where the support vessel was held in place upstream of the GBS using flexible mooring lines and two free running tests; where the support vessel was remotely controlled and maneuvered upstream of the GBS. Results are provided in terms of loads measured on the GBS model with clearing support, loads measured on the support vessel during the fixed ice clearing operations, ice free zones created upstream of the GBS and aft of the support vessel during ice clearing tests, reductions in GBS loads due to ice clearing operations, reductions in ice concentration upstream of the GBS due to ice clearing operations, and a summary of ice events that led to large pack ice loads. The significant factors that influenced each result were also identified. These results complement existing literature relating to physical ice clearing operations by providing the outcomes of systematic testing in different ice conditions which is available in public domain. These results could be used as benchmark values for design or numerical model validation. In addition, they could provide insight to operators, regulators and academia to support informed decision making regarding the level of ice management support required in different operating environments. All dimensions and test results in this paper are provided at full scale value.

Experimental study of the impacts of porous plates on steady flow velocities for hydrokinetic energy resource impact assessment applications - Knox, Paul; Provan, Mitchel; Cornett, Andrew; Murphy, Enda; Cousineau, Julien (Proceedings of the 7th International Conference on the Application of Physical Modelling in Coastal and Port Engineering and Science (Coastlab18), 2018)
In order to take advantage of economies of scale, hydrokinetic energy (HKE) developers typically deploy multiple turbines within rivers or the marine environment in array or farm configurations. Successful planning and design of turbine array deployments requires an understanding of turbine wake hydrodynamics, wake interactions within arrays, and the performance of turbines within array fields, to enable quantification of the extractable power and impacts on the surrounding environment. However, consistent and reliable methods for predicting the power generation capabilities of turbine arrays and the total extractable power from a given site remain elusive. Numerical hydrodynamic models show considerable promise as tools to support hydrokinetic energy resource assessment, turbine array site selection, array design and impact assessment. For example, Computational Fluid Dynamics (CFD) models provide a means to analyse the high frequency motions and complex geometries associated with turbine-fluid interactions at the scale of individual turbines. CFD models can be integrated with numerical models that solve free surface flow equations to study the interactions between turbine arrays and hydrodynamics at coastal region or river reach scales. However, numerical models remain subject to limitations and require calibration and validation to provide confidence in their predictive capabilities, and to quantify uncertainty. This paper presents preliminary work whereby a set of large scale physical models was utilized to document the magnitude and spatial distribution of the velocity deficit at a high resolution upstream, and within the downstream wake, of simplified representations of cross-flow turbines modelled as porous rectangular plates. Subsequent phases of the research will include using this experimental data to calibrate and validate a CFD model of the porous plates, and conducting scale model experiments using more realistic, moving cross-flow hydrokinetic turbines to support improvements in CFD modelling techniques for HKE applications.
Keywords: marine renewable energy; physical modelling; hydrokinetic energy turbines

Assessment of debris issues impacting design of a flood diversion project in a large scale physical model - Knox, Paul (2018)

Experimental study of velocity deficit and wake due to single and multiple rectangular porous plates in steady flow - Provan, Mitchel; Knox, Paul; Cornett, Andrew; Cousineau, Julien (Proceedings of the Marine Energy Technology Symposium 2018, 2018)

Thickness and freeboard statistics of Arctic multi-year ice in late summer: three, recent drilling campaigns - Johnston, M. E. (Cold Regions Science and Technology, 2018)
This paper targets three, diverse audiences: persons calculating ice loads on structures, persons navigating ice-covered waters, and persons using remotely sensed data to estimate ice thickness. The most extensive set of drilling measurements to have been made on thick multi-year ice since the 1980s is presented based upon 22 floes sampled in some of the most remote regions in the world from years 2007 to 2011. Thickness and freeboard measurements from more than 600 drill-holes indicated that mean thicknesses and standard deviations of floes in Nares Strait, the Canadian Arctic Archipelago (CAA) and the Beaufort Sea ranged from 3.4 ± 1.3 m to 14.7 ± 3.8 m. Approximately 23% of the floes had an average thickness of 10 m or more, making them comparable to the 8 to 12 m thick hummock that caused the highest loads ever measured on the offshore structure Molikpaq. The continued presence of thick multi-year ice shows that, although the modal thickness of thermodynamically grown old ice has decreased, driving forces continue to create deformed multi-year ice. The overall thickness distribution of thermodynamically grown and mechanically deformed multi-year ice is lognormally distributed in all of the examined geographic regions. Probability of exceedance curves were used to address underestimated probabilities in the tail. Assessment of first order autocorrelation coefficients showed that drill hole measurements were statistically independent for ~85% of the 100 to 200 m long transects. Linear regressions of freeboard versus thickness had less predictive skill at the point-scale (R² of 0.57, 10 m spacing) than averages at the transect-scale (R² of 0.78, ~100 m) and floe-scale (R² of 0.88, up to ~1 km). The anomalously high freeboard of some drill holes, transects and floes has a number of plausible explanations including loose ice blocks on the underside of relatively level floes, ice blocks in the keel of deformed floes, elevated blocks on the top surface of relatively level ice without a keel, and/or the low density of the elevated and submerged portions of multi-year ice.
Keywords: multi-year ice; thickness; freeboard; draft; deformed ice; statistics

2D hydraulic model study of the Ayia Napa Marina breakwater - Provan, Mitchel; Knox, Paul; Wesson, Mauricio (Proceedings of the 7th International Conference on the Application of Physical Modelling in Coastal and Port Engineering and Science (Coastlab18), 2018)
"A two-dimensional hydraulic model study at a geometric scale of 1:42.2 was conducted to support the design of a breakwater for the Ayia Napa Marina in Cyprus. A scaled model of the Ayia Napa Marina breakwater and an idealized foreshore at the project site were constructed and used to assess the performance of the breakwater. The model breakwater was exposed to scaled reproductions of the design wave conditions forecast for the site. The physical model provided a good simulation of the important hydrodynamic processes influencing armour layer stability and overtopping, including nearshore wave transformation, wave breaking, wave run-up and interstitial flows through the armour and filter layers. The performance of two different cross-sections was determined by observing the stability of the armour layer and amount of overtopping following exposure to a series of irregular wave conditions and elevated water levels representing design storms. Each tests series generated reliable information with respect to the interaction of the extreme design waves with the foreshore and the breakwater (wave breaking, run-up and overtopping) and the response of the breakwater to this forcing (stability of the armour and overtopping discharge). This information was used to refine the breakwater design for the Ayia Napa Marina in Cyprus."
Keywords: coastal engineering; physical modelling; overtopping; marina; tetrapods

The subsea Drake pipeline: a challenging case study to check design effectiveness against drifting ice action - Barrette, Paul; Barker, Anne; Gardin, Enzo (OTC Arctic Technology Conference, 2018)
The Drake pipeline is located offshore Melville Island, in the Canadian High Arctic. It was built on-site in 1977-78 and connected to a natural gas production well, which operated for only a few months. The well was plugged in 1995 and the pipeline was abandoned. The pipeline extends from the shoreline to the wellhead located about one kilometer offshore to a water depth of 55 meters. It is buried at the shoreline crossing, to a target depth of 1.5 meters below sea bottom. A system to generate a frozen soil shield was also devised for further protection against drifting ice. Also, a berm made from ice and gravel was built at the water line. Field investigations could prove highly instructive to assess the state of the structure, and provide guidelines for design of future pipelines in high risks areas. However, significant technical and logistical challenges would face that venture, namely a ‘no physical contact’ (with the pipeline) restriction from the property owner, which leads to difficulty in understanding what has occurred to the pipeline beneath the soil, and a propensity for the region to be covered with a very thick ice cover.

Physical modeling supporting design and construction of low crested breakwater for the Ayia Napa Marina, Cyprus - Wesson, Mauricio; Provan, Mitchel; Cox, Jack; Knox, Paul (Book of Abstracts: 34th PIANC World Congress, 7 to 11 of May 2018, Panama: Connecting Maritime hubs globally, 2018)
SmithGroupJJR undertook the design a new marina and accompanying land development at Ayia Napa, Cyprus. The marina features a 600-slip mega-yacht harbour framed by a large shoreline protection scheme comprised of wave absorbing block walls, revetments, breakwaters, and pocket beaches. Significant upland development, including two, 25-story towers and residential villas are also included in the design, with some of the new development near the sheltering breakwater. An innovative onekilometer long, low-crested breakwater with tetrapod armor and a wide rock berm was designed to protect the harbor and land development. One of the primary design goals was maintaining a crest height low enough to provide the villa owners and marina users with unobstructed views of the sea. Therefore, a key element in the design was to limit the amount of wave overtopping that could pass over the low crested structure and potentially threaten the villas, yachts, cars and people on the lee side of the breakwater. The maximum overtopping flow rate was of interest rather than the mean time-averaged flowrate, since the maximum flow rate is more closely linked to risks to people and property. A physical model study of a revised breakwater design was carried out at the National Research Council of Canada (NRC). A two-dimensional physical model of an idealized foreshore at the project site was constructed at a geometric scale of 1:42.2 in a 63m long by 1.22m wide wave flume. Scale models of two breakwater cross-sections (one in shallow water, the other in deeper water), due to the variable bathymetry, were constructed and exposed to scaled reproductions of the design-wave conditions forecast for the site. The physical model provided a good simulation of the important hydrodynamic processes influencing the stability and overtopping of the tetrapod armor layer, including nearshore wave transformation, wave breaking, wave run-up, and interstitial flows through the armor and filter layers. The Ayia Napa breakwater is currently under construction, with approximately 50% of the breakwater constructed to date and completion expected by April 2019. Breakwater construction has been closely supervised, assuring that it meets the conditions specified by the design and observed in the physical model. The innovative double berm, low crested design approach of the Ayia Napa Marina breakwater provides a casebook example of how to achieve a harmonic, high-performance breakwater integrated with its landscape and environmental context, as well as highlighting the value of using a physical model to deal with design changes that arise during construction.
Keywords: coastal engineering; physical modelling; overtopping; marina; tetrapods

Risks to marine pipelines from drifting ice: gathering the evidence - Barrette, Paul; Mcgonigal, David; Pike, Kenton (2018 ASME International Conference on Ocean, Offshore and Arctic Engineering (Pipelines, Risers, and Subsea Systems), 2018)
Marine pipelines in ice-prone waters are exposed to a number of environmental threats that do not exist in warmer waters. Of particular concern is the damage from ice features such as pressure ridges that drift into shallow areas. The ice keel comes in contact with the seabed and, as the ice feature keeps drifting, it may gouge the seabed to some depth and for considerable distances. Trenching and burial are seen as the best means of protecting these structures, but adequate depth relies on adequate knowledge of these events. This is obtained in various ways. Actual, real-scale events provide valuable information. Seabed mapping allows an appreciation of gouging activity in the target sector. Physical experiments can generate a nearly complete picture of these events, and can be used to validate numerical models. A description is presented of an abandoned marine pipeline in Northern Canada, which represents a rare test case scenario. Plans to conduct field investigations on that pipeline are being considered.
Keywords: undersea pipelines; ice

Development of an interactive, web-based decision support system to facilitate marine renewable energy site selection - Ferguson, Sean; Cousineau, Julien (Ocean Energy Systems, 2018)
The authors present recent progress in the development of the British Columbia Marine Energy Resource Atlas (hereafter referred to as the “Atlas”). The Atlas is a web-based geospatial decision support system and was developed to assist marine renewable energy stakeholders with preliminary site selection and feasibility investigations in the rivers and coastal waters of British Columbia, Canada. The Atlas offers a clean and simple interface through which users are able to interact with the underlying geospatial data and customize investigations to fit their specific design and development criteria. The Atlas represents a uniquely flexible and accessible decision support system that can be operated online via a web browser and does not require any specialized geographic information system software. Furthermore, the Atlas is the first marine renewable energy decision support system to offer support for tidal, wave, and river hydrokinetic resources under a common system and interface.
Keywords: marine renewable energy; atlas; decision support system; multi-criteria decision analysis; GIS

Predicting ice thickness for engineering applications - Frederking, Robert (24th IAHR International Symposium on Ice, 2018)
Many engineering problems require an estimate of ice thickness, either the maximum likely thickness or the thickness at some time during the winter. This can be for estimating ice forces on an offshore structure in the sea or a bridge pier in a river. Operation of icebreaking ships requires knowledge of ice thickness to establish the viability of transit to northern ports. Similarly, over-ice transportation on seas, lakes or rives depends on a knowledge of ice thickness. At some locations historical records can be used to estimate ice thicknesses, but with changing climate historical records have limited applicability. Having means for predicting ice growth during a winter is a helpful tool. In high Arctic regions it is assumed the primary factors affecting ice growth are air temperature and snow depth. Assessment of the equations against data from Arctic weather stations indicates that the incorporation of snow depth in terms of a mean annual snow depth is a simple means for improving their predictive capability. Modified equations including mean annual snow depth and freezing degree days as input parameters are proposed and tested against available data at two locations in the Canadian High Arctic; Resolute Bay in a marine coastal environment and Baker lake in an inland freshwater lake. These modified prediction equations are proposed for general application in the Arctic.

Web-based geospatial decision support system to facilitate marine renewable energy site selection in British Columbia, Canada - Ferguson, Sean; Cousineau, Julien (National Hydropower Association, 2018)
The authors present the British Columbia Marine Energy Resource Atlas (hereafter referred to as “the Atlas”), a web-based geospatial decision support system (DSS) to facilitate preliminary marine renewable energy (MRE) site selection and feasibility investigations within the rivers and coastal waters of Canada’s westernmost province. The Atlas was developed such that users are able to interact with the underlying datasets that drive the hotspot delineation. As such, the Atlas is an effective tool to quickly investigate multiple case-scenarios with different resource, socio-economic, and environmental criteria. Furthermore, the Atlas is the first MRE DSS to offer support for tidal, wave, and river hydrokinetic resources under a common system and interface.

Field and numerical investigations of the morpho-hydrodynamic processes of the tidal inlet at Shippagan Gully, New Brunswick, Canada - Provan, Mitchel; Logan, Seth; Nistor, Ioan; Cornett, Andrew; Drouin, Alain (Coastal Engineering Journal, 2018)
This paper presents the result of a multiyear study consisting of field measurements and numerical modeling of a highly dynamic tidal inlet located on the west side of the Gulf of Saint Lawrence near Le Goulet, New Brunswick, Canada. Due to a lack of human intervention in the past few decades, natural processes have taken hold of this tidal inlet and large volumes of sediment have been deposited within the inlet. The Shippagan Gully inlet transects the Acadian Peninsula and is therefore subject to tidal forcing from both ends. An appreciable phase lag present in the two open ocean boundaries results in ebb flows through Shippagan Gully, which regularly exceed 2 m/s, to be twice as strong as the flood flows. This flow imbalance along with a long history of human intervention has created a complex and highly dynamic tidal inlet. The purpose of the study was to develop a numerical model of the hydrodynamic and morphological processes that occur at Shippagan Gully and to use the model to assess alternative engineering measures that could be implemented to promote a safe and navigable channel through the inlet.
Keywords: sediment transport; tidal inlet; morphology; numerical modeling; coastal structures

3D physical modelling and revetment design for the Billy Bishop Toronto City Airport extension - Baker, Scott; Cornett, Andrew; Glodowski, Chris (Real Property Institute of Canada, 2018)
As part of a planned development for Billy Bishop Toronto City Airport, new land reclamation and related marine works are required to extend both ends of the main runway. Wave conditions at the eastern end of the runway are relatively mild, as the site is sheltered inside Toronto Harbour. However, the western runway extension will be directly exposed to strong winds, energetic wave conditions, high water levels, and winter ice conditions on Lake Ontario. An engineered revetment is required to prevent erosion, preserve stability, and protect the exposed western reclamation from attack by waves and ice. The design challenge was compounded by the requirement to minimize the frequency and extent of wave run-up and overtopping during storms to avoid frequent inundation of the runway. At the same time, the crest elevation of the perimeter revetment was limited by several requirements for safe operations at the airport. A large-scale 3D physical modelling study was crucial to develop, test, and optimize the design of the perimeter revetment and for costing the marine works. In order to accommodate the stringent design requirements, several innovative revetment design concepts (featuring lower crest elevations, milder slopes, thicker filter layers, and thicker armour layers than normally seen in conventional designs) were tested in a wide range of harsh wave, wind, and water level conditions. Once the development is approved, the longer runway will allow for expanded operations from Billy Bishop Airport, with the ability to reach destinations anywhere across North America. This will greatly benefit the citizens of Toronto and boost the local economy. The longer runway will also improve safety by reducing the risk of runway excursion.

Altitude scaling of thermal ice protection systems in running wet operation - Orchard, D. M.; Addy, H. E.; Wright, W. B.; Tsao, J. (Journal of Aircraft, 2018)
A study into the effects of altitude on an aircraft thermal Ice Protection System (IPS) performance has been conducted by the National Research Council Canada (NRC) in collaboration with the NASA Glenn Icing Branch. The study included tests of an airfoil model, with a heated-air IPS, installed in the NRC’s Altitude Icing Wind Tunnel (AIWT) at altitude and ground level conditions. Two scaling strategies were employed based on Reynolds number and Weber number approaches that were combined with matching the ratio of water loading and evaporative rates. The Reynolds number scaled conditions resulted in greater mass of accreted ice that formed further back from the leading edge while the Weber number approach provided a close matches to reference altitude conditions in terms of both ice mass, location and shape.

Aerodynamic characteristics of generic ice shells - Raeesi, Arash; Mctavish, Sean; D'Auteuil, Annick (Journal of Wind Engineering and Industrial Aerodynamics, 2018)
Freezing rain and wet snow can cause ice to accumulate on the surface of bridge cables. Subsequently, a rise in temperature and wind can cause ice to shed from the surface of cables. Several instances of ice and wet snow shedding from bridge cables have been observed in Canada. Environmental predictive models have been proposed to predict the ice shedding behaviour and its trajectory from bridge cables. The current study aims at measuring the aerodynamic force and moment coefficients of generic ice fragments detached from a bridge cable as a priori for a subsequent ice trajectory model. Nine representative generic, ice shells were selected to represent different aspect ratios, curvatures, ice thicknesses, and external ice surface conditions. Aerodynamic forces and moments were measured for each of the ice shell models in turbulent flow for a wide range of orientations. The use of a curved shape as opposed to a flat plate resulted in a significant difference in the aerodynamic coefficients. It was found that the aspect ratio was the most important geometric factor in determining the aerodynamic forces and moments on the curved models. The findings of this study will be implemented in future ice trajectory models.
Keywords: bridge cable; ice accretion; ice fragment; ice trajectory model; ice shell aerodynamics; wind tunnel

A targeted bivalent androgen receptor binding compound for prostate cancer therapy - Chowdhury, Shafinaz; Beitel, Lenore K.; Lumbroso, Rose; Purisima, Enrico O.; Paliouras, Miltiadis; Trifiro, Mark (Hormones and Cancer, 2018)
The androgen-directed treatment of prostate cancer (PCa) is fraught with the recurrent profile of failed treatment due to drug resistance and must be addressed if we are to provide an effective therapeutic option. The most singular difficulty in the treatment of PCa is the failure to respond to classical androgen withdrawal or androgen blockade therapy, which often develops as the malignancy incurs genetic alterations and gain-of-function somatic mutations in the androgen receptor (AR). Physical cellular damaging therapeutic agents, such as radiation or activatable heat-generating transducers would circumvent classical “anti-functional” biological resistance, but to become ultimately effective would require directed application modalities. To this end, we have developed a novel AR-directed therapeutic agent by creating bivalent androgen hormone-AF-2 compounds that bind with high affinity to AR within cells. Here, we used molecular modeling and synthetic chemistry to create a number of compounds by conjugating 5α-dihydrotestosterone (DHT) to various AF-2 motif sequence peptides, through the use of a glycine and other spacer linkers. Our data indicates these compounds will bind to the AR in vitro and that altering the AF-2 peptide composition of the compound does indeed improve affinity for the AR. We also show that many of these bivalent compounds can readily pass through the plasma membrane and effectively compete against androgens alone.
Keywords: androgen receptor; prostate cancer; androgen; bivalent compound; af-2 domain; therapeutics; molecular dynamics simulation

A systematic numerical study of the laminar burning velocity of iso-octane/syngas/air mixtures - Xu, Huanhuan; Liu, Fengshan; Sun, Shaozeng; Meng, Shun; Zhao, Yijun (Chemical Engineering Science, 2018)
The laminar burning velocities of iso-octane/syngas/air mixtures were numerically investigated using a detailed reaction mechanism over a wide range of equivalence ratio (0.4–1.4) at atmospheric and elevated pressure at an initial temperature of 423 K. The mole fraction of syngas in the fuel mixture was varied from the entire range of 0 (pure iso-octane) to 1 (pure syngas). To take into account the large variations of syngas compositions, the following three syngas compositions are considered: 75%H2-25%CO, 50%H2-50%CO, and 25%H2-75%CO by volume. The results show that the laminar burning velocity of iso-octane/syngas/air mixtures increases with the content of syngas, especially for higher H2 content in syngas and rich mixtures. The enhanced burning velocity is attributed to the chemical effects of H2 in syngas. The burning velocity correlates linearly with the level of syngas dilution of the fuel mixture, regardless of how the syngas dilution ratio is defined when the dilution level is low. The linear correlation remains over a wide range of syngas dilution when the dilution ration is defined as that introduced by Yu et al. (1986). H2 addition and CO addition affect the radical pool differently and H is found to be a kinetics indicator for the burning velocity of iso-octane/syngas/air mixtures under the current conditions. Detailed sensitivity and pathway analysis was also conducted to identify reactions that significantly affect the burning velocity of iso-octane/syngas/air mixtures and to illustrate the kinetics interactions between H2, CO, and iso-octane in iso-octane/syngas/air mixtures.
Keywords: Laminar burning velocity; Iso-octane; Syngas; Pathway analysis

A comparison study on forming limit prediction methods for hot stamping of 7075 aluminum sheet - Wang, Ning; Ilinich, Andrey; Chen, Minghe; Luckey, George; D'amours, Guillaume (International Journal of Mechanical Sciences, 2018)
This paper provides an experimental and theoretical study of AA7075 hot forming limits. The limits were measured in a wide range of temperature and strain rates using Nakazima test. Elevated temperature tensile testing was performed to capture the constitutive behavior. Two flow models have been calibrated using the tensile data, the Misiołek model and a continuum damage mechanics (CDM) model. Two theoretical forming limit predictions methods have been investigated, the Marciniak–Kaczynski (M–K) method and a method based on CDM. In the M–K model, the constitutive behavior was modeled by the von Mises yield with the Misiołek flow model. The strain rate sensitivity of the groove section was taken into consideration. The CDM forming limit prediction method utilized the corresponding flow model and a simplified plane stress CDM model. Parameters in the constitutive models and the forming limit prediction models were expressed as functions of temperature and strain rate. Both methods accurately predicted the AA7075 forming limits in the hot stamping temperature range and strain rate range.
Keywords: AA7075; hot forming limit prediction; continuous damage model; M–K model

A comparison of microbial fuel cell and microbial electrolysis cell biosensors for real-time environmental monitoring - Adekunle, Ademola; Raghavan, Vijaya; Tartakovsky, Boris (Bioelectrochemistry, 2018)
This study compares the biosensing performance of a microbial fuel cell (MFC) and a microbial electrolysis cell (MEC). Initial tests provided a qualitative comparison of MFC and MEC currents after the anode compartment liquid (anolyte) was spiked with acetate, or sulphates of NH4+, Na+, Mg2+, Fe2+, or a fertilizer solution. Current measurements showed that the MFC sensor had a faster response time, higher sensitivity, and faster recovery time after the spike. Following the spike tests, the MFC and MEC were operated in a continuous flow mode at several influent concentrations of acetate, and sulphates of NH4+, Na+, and Fe2+. The continuous flow tests confirmed the better performance of the MFC sensor, which was selected for further experiments. Two MFC sensors were used for real-time (on-line) COD measurements of brewery wastewater. Regression analysis showed a strong correlation between the MFC power output and COD concentrations in the anode compartment with a coefficient of determination (R2) of 0.97. Overall, results of this study suggest that an MFC-based sensor can be successfully used as a simple and cost-efficient real-time monitoring tool.
Keywords: Biosensor; Environmental monitoring; MFC; MEC; Pollutant detection; Real-time measurements

Environment-friendly, durable, electro-conductive, and highly transparent heaters based on silver nanowire functionalized keratin nanofiber textiles - Lee, Chil-Hyoung; Yun, Yong Ju; Cho, Hyunjin; Lee, Kyu Seung; Park, Mira; Kim, Hak Yong; Son, Dong Ick (Journal of Materials Chemistry C, 2018)
We demonstrate the fabrication of highly transparent, electro-conductive, durable, and eco-friendly nanofiber (NF) textiles based on keratin using highly conductive silver nanowire (Ag NW) networks on transparent nano-fibrous substrates for multifunctional, high-performance flexible heaters. These NF-based textiles, including keratin, have a high transparency of more than 89% in the visible area, making them very useful for manufacturing transparent wearable electronics. The Ag NW networks on the nanofibers provide a low sheet resistance of 25 Ω sq−1, with a maximum optical transparency of 85% and superior flexibility with mechanical durability up to 1000 cycles of bending and release. Flexible and transparent wearable electronic devices, such as heaters, with an exceptionally high mechanical stability and foldability with negligible changes in electrical conductivity have been successfully fabricated by using this simple method. Also, transparent conductive NFs based on keratin are a promising wearable electronic material for a wide range of high performance, low cost, biocompatible and wearable electronics applications. This study successfully demonstrates a flexible heater based on transparent conductive NFs with a wide operating temperature up to 65.75 °C, a good recovery time of about 10 s and low power consumption (0.38 W) for wearable electronics applications.

β-SnSb for sodium ion battery anodes: phase transformations responsible for enhanced cycling stability revealed by in situ TEM - Xie, Hezhen; Tan, Xuehai; Luber, Erik J.; Olsen, Brian C.; Kalisvaart, W. Peter; Jungjohann, Katherine L.; Mitlin, David; Buriak, Jillian M. (ACS Energy Letters, 2018)
β-SnSb is known to be a highly stable anode for sodium ion batteries during cycling, but its sodiation–desodiation alloying reactions are poorly understood. Combining in situ TEM with electroanalytical methods, we demonstrate that β-SnSb forms Na3Sb and Na15Sn4 in sequence upon sodiation and re-forms as β-SnSb upon desodiation. The negative enthalpy of mixing for Sn and Sb is sufficient to cause sequentially deposited bilayers of Sn/Sb to transform into β-SnSb, resulting in comparable cycling stability. The good cycling stability of β-SnSb results from the complex two-phase amorphous–nanocrystalline microstructure in the partially charged–discharged states, as well as the intrinsic mechanical toughness of the β phase. Per the in situ TEM results, the sequential phase transformation shows minimal fracturing of the β-SnSb, indicating facile buffering of stresses. Extensively cycled specimens eventually show crystalline Sn phase segregation, which may be the source of the ultimate capacity fade in the alloy and bilayers.

Wavefront control architecture and expected performance for the TMT Planetary Systems Imager - Guyon, Olivier; Mazin, Benjamin A.; Fitzgerald, Michael P.; Mawet, Dimitri; Marois, Christian; Skemer, Andy; Lozi, Julien; Males, Jared; Schmidt, Dirk; Schreiber, Laura; Close, Laird M. (Adaptive Optics Systems VI, 2018)
The Planetary Systems Imager (PSI) is a modular instrument optimized for direct imaging and characterization of exoplanet and disks with the Thirty Meter Telescope (TMT). PSI will operate across a wide wavelength range (≈0.6 - 5μm) to image exoplanets and circumstellar disks in both reflected light and thermal emission. Thanks to the TMT’s large collecting area, PSI will have the sensitivity to directly image and spectrally characterize large gaseous planets with unprecedented sensitivity. PSI will also be capable of imaging rocky planets in the habitable zones of the nearest M-type stars in reflected light and search for biomarkers in their atmospheres. Imaging habitable planets in reflected light is PSI’s most challenging goal, requiring high contrast imaging (HCI) capabilities well beyond what current instruments achieve. This science goal drives PSI’s wavefront sensing and control requirements and defines the corresponding architecture discussed in this paper. We show that PSI must deliver 1e-5 image contrast ≈15 mas separation at λ ≈ 1μm-1.5μm, and that a conventional extreme-AO architecture relying on a single high speed wavefront sensor (WFS) is not sufficient to meet this requirement. We propose a wavefront control architecture relying on both visible light (λ < 1.1 μm) sensing to optimize sensitivity, and near-IR (λ > 1.1 μm) sensors to address wavefront chromaticity terms and provide high contrast imaging capability. We show that this combination will enable speckle halo suppression at the < 1e-5 raw contrast level in near-IR, allowing detection and spectroscopic characterization of potentially habitable exoplanets orbiting nearby M-type stars.
Keywords: exoplanets; high Contrast Imaging; adaptive Optics; coronagraphy

Flight measurement of medium category wake vortex characteristics - Brown, Anthony P. (2018 Atmospheric and Space Environments Conference, 2018)
In 2017, the NRC undertook biofuel contrail flight research, using Air Canada A320/A321 jet transport aircraft as the contrail generators. In measuring the full contrail cross-section, the NRC CT-133 research aircraft additionally measured the wake vortex characteristics of the aircraft types, Medium Category jet transports. The vortex cores tended to be large, compared to the wingspan, and thus more laterally proximate. Long-wave instability was relatively small wavelength. Short-wave mutual instabilities between vortices exhibited strong excitation of axial vortex velocity components. Cross-plane (orthogonal to the vortex axes) contour plots of vortex parameters, particularly quasi-vorticity, elucidated vortex structural detail. EDR contours were maxima at vortex core edges, some vortex cores were vented, core edges were warm, and core centres cool. Surprisingly perhaps the Brunt-Vaisala frequency contours exhibited stratified, rotating structures to the vortices, delineating Rossby-style spiral structures.
Keywords: atmospheric and space; environments

Winter roads and climate adaptation: prospective solutions through R&D - Barrette, Paul D.; Charlebois, Lawrence (TAC 2018: Innovation and Technology: Evolving Transportation - 2018 Conference and Exhibition of the Transportation Association of Canada, 2018)
In Canada, the total length of the winter road network is estimated at 10,000 km. These are roads that are usable only in the winter. Nature controls the state of a winter road’s foundation – natural ground and ice surfaces – which needs to be trafficable and able to support the vehicles’ weight. These surfaces are particularly sensitive to climate change. A large number of adaptation measures were developed over the years, which can be applied at the planning, construction and maintenance stages, and for traffic management. We have reached a stage where increasing our fundamental knowledge base is required. This can be done through research and development (R&D). Avenues of investigation include a field tool to characterize winter roads in a more systematic fashion, by combining physical information (e.g. road grades, cross-slopes, width, over-land vs over-water ratio) with all operational and logistical data (e.g. opening and closure dates, nature of goods transported) into an interactive database. This could be used for capacity and multimodal planning, as well as to guide priorities on road realignment and incremental replacement (partial or complete) by all-weather road segments. Several outstanding questions regarding the bearing capacity and deformational behavior of floating ice roads could also be addressed. Topics that need to be investigated include: ice cover strength, how long a vehicle can be parked on the ice, how cracking patterns affect ice integrity, and the investigation of known procedures, techniques and technologies to reinforce an ice cover.

Estimation of sea ice parameters from sea ice model with assimilated ice concentration and SST - Prasad, Siva; Zakharov, Igor; Mcguire, Peter; Power, Desmond; Richard, Martin (The Cryosphere, 2018)
A multi-category numerical sea ice model CICE was used along with data assimilation to derive sea ice parameters in the region of Baffin Bay and Labrador Sea. The assimilation of ice concentration was performed using the data derived from the Advanced Microwave Scanning Radiometer (AMSR-E and AMSR2). The model uses a mixed-layer slab ocean parameterization to compute the sea surface temperature (SST) and thereby to compute the freezing and melting potential of ice. The data from Advanced Very High Resolution Radiometer (AVHRR-only optimum interpolation analysis) were used to assimilate SST. The modelled ice parameters including concentration, ice thickness, freeboard and keel depth were compared with parameters estimated from remote-sensing data. The ice thickness estimated from the model was compared with the measurements derived from Soil Moisture Ocean Salinity – Microwave Imaging Radiometer using Aperture Synthesis (SMOS–MIRAS). The model freeboard estimates were compared with the freeboard measurements derived from CryoSat2. The ice concentration, thickness and freeboard estimates from the model assimilated with both ice concentration and SST were found to be within the uncertainty in the observation except during March. The model-estimated draft was compared with the measurements from an upward-looking sonar (ULS) deployed in the Labrador Sea (near Makkovik Bank). The difference between modelled draft and ULS measurements estimated from the model was found to be within 10 cm. The keel depth measurements from the ULS instruments were compared to the estimates from the model to retrieve a relationship between the ridge height and keel depth.

Transient gene expression in suspension HEK293-EBNA1 cells - L’Abbé, Denis; Bisson, Louis; Gervais, Christian; Grazzini, Eric; Durocher, Yves (Recombinant Protein Expression in Mammalian Cells, 2018)
Transient gene expression in human embryo kidney 293 (HEK293) cells is an established approach for the rapid production of large amounts of recombinant proteins (r-proteins). Milligram to gram quantities of r-proteins can be typically obtained within less than 10 days following transfection. In this chapter, we describe a simple and robust transfection process of suspension-growing human embryo kidney 293 cells using two commercially available serum-free media and polyethylenimine as the transfection reagent. This chapter provides examples for the production and purification of a his-tagged recombinant protein and two monoclonal antibodies.
Keywords: transfection; 293-6E; polyethylenimine; deacylated PEI; recombinant protein; suspension culture; IMAC; protein-A; antibody; serum-free medium

Transfection of difficult-to-transfect rat primary cortical neurons with magnetic nanoparticles - Jin, Wuyang; Lin, Donghai; Nguyen, Anh H.; Abdelrasoul, Gaser N.; Chen, Jian; Mar, Arthur; Qian, Feng; Fang, Qiang; Kovalchuk, Igor; Wang, Yutian; Chen, Jie (Journal of Biomedical Nanotechnology, 2018)
The efficient cell transfection method is vital for various biomedical applications, such as the CRISPR-Cas9 technique. Current cell transfection methods, including lipofectamine, calcium phosphate co-precipitation, nucleofection, and viral infection are not equally efficient for various cells and have their disadvantages. In this study, a magnetic nanoparticle (MNP)-based method was introduced for delivering both FITC dye and a functional EGFP gene into easy-to-transfect HEK cells and difficult-to-transfect rat primary cortical neurons. The transfection efficacy could be controlled in both time-dependent and magnetic strength-dependent manner. This cell transfection method could have substantial potential for targeted drug delivery.
Keywords: Enhanced Green Fluorescent Protein (EGFP); fluorescein isothiocyanate (FITC); magnetic nanoparticles; primary cortical neurons; transfection

Evaluation of pack ice pressure approaches and engineering implications for offshore structure design - Charlebois, Lawrence; Frederking, Robert; Timco, G.W.; Watson, David; Richard, Martin (Cold Regions Science and Technology, 2018)
A probabilistic model for ice forces on a caisson platform in the Beaufort Sea was used to evaluate two different approaches for describing pack ice pressure. The ridge-building equation in the ISO Arctic offshore structures standard was compared to a more recently derived exceedance curve (EC) approach. The results indicated that the EC approach yielded a wider range of pack ice pressures compared to ISO estimates; however, when these results were used to determine the ultimate ice force on the platform, the effect of the pack ice approach selected was minimal. The influence of floe size in affecting the pack ice pressure did not yield agreement amongst several data sets examined. Furthermore, the influence of adfreeze was examined but no definite relationship was quantified. The paper discusses the engineering implications of these results in the context of offshore structure design. When evaluating the ice loads at a candidate site for offshore development, relevant information on floe size distribution and pack ice thickness, concentration, and movement are required in order to assess the influence of pack ice pressure on design calculations.
Keywords: pack ice; offshore structures; ice loads; ice engineering; ice pressure

The transcriptional landscape of polyploid wheat - Ramírez-González, R. H.; Borrill, P.; Lang, D.; Harrington, S. A.; Brinton, J.; Venturini, L.; Davey, M.; Jacobs, J.; Van Ex, F.; Pasha, A.; Khedikar, Y.; Robinson, S. J.; et al. (Science, 2018)
INTRODUCTION: Polyploidy, arising from whole-genome duplication or interspecific hybridization, is ubiquitous across the plant and fungal kingdoms. The presence of highly related genes in polyploids, referred to as homoeologs, has been proposed to confer adaptive plasticity—for example, through neofunctionalization of duplicated genes or tissue-specific expression. This plasticity has facilitated the domestication and adaptation of major polyploid crops (e.g., wheat, cotton, and coffee). However, despite its likely importance, we have a limited understanding of the effect of polyploidy on gene expression and the extent to which homoeologs are similar or different in their expression patterns across development and tissues. RATIONALE: Bread wheat is a polyploid derived from the hybridizations between three distinct diploid species and is an informative system for analyzing the effects of recent polyploidy on gene expression. Understanding the coordination of homoeologs and identifying the mechanisms associated with these processes should help define strategies to improve trait biology in a crop that provides more than 20% of the protein and caloric intake of humans. RESULTS: Here we leverage 850 wheat RNA-sequencing samples, alongside the annotated genome, to determine the similarities and differences between homoeolog expression across a range of tissues, developmental stages, and cultivars. On average, ~30% of wheat homoeolog triads (composed of A, B, and D genome copies) showed nonbalanced expression patterns, with higher or lower expression from a single homoeolog with respect to the other two. These differences between homoeologs were associated with epigenetic changes affecting DNA methylation and histone modifications. Although nonbalanced homoeolog expression could be partially predicted by expression in diploid ancestors, large changes in relative homoeolog expression were observed owing to polyploidization. Our results suggest that the transposable elements in promoters relate more closely to the variation in the relative expression of homoeologs across tissues than to a ubiquitous effect across all tissues. We found that homoeologs with the highest inter-tissue variation had promoters with more frequent transposable element insertions and more varied cis-regulatory elements than homoeologs that were stable across tissues. We also identified expression asymmetry along wheat chromosomes. Homoeologs with the largest inter-tissue, inter-cultivar, and coding sequence variation were most often located in the highly recombinogenic distal ends of chromosomes. These transcriptionally dynamic homoeologs are under more relaxed selection pressure, potentially representing the first steps toward functional innovation through neo- or subfunctionalization. We generated tissue- and stress-specific coexpression networks that reveal extensive coordination of homoeolog expression throughout development. These networks, alongside detailed gene expression atlases (www.wheat-expression.com and http://bar.utoronto.ca), lay the groundwork to identify candidate genes influencing agronomic traits in wheat. CONCLUSION: This study provides detailed insights into the transcriptional landscape of bread wheat, an evolutionarily young polyploid. Our work shows that homoeolog expression patterns in bread wheat have been shaped by polyploidy and are associated with both epigenetic modifications and variation in transposable elements within promoters of homoeologous genes. The extensive datasets and analyses presented here provide a framework that can help researchers and breeders develop strategies to improve crops by manipulating individual or multiple homoeologs to modulate trait responses.

The SCUBA-2 Cosmology Legacy Survey: the EGS deep field. II. Morphological transformation and multiwavelength properties of faint submillimetre galaxies - Zavala, J. A.; Aretxaga, I.; Dunlop, J. S.; Michałowski, M. J.; Hughes, D. H.; Bourne, N.; Chapin, E.; Cowley, W.; Farrah, D.; Lacey, C.; Targett, T.; Van der werf, P. (Monthly Notices of the Royal Astronomical Society, 2018)
We present a multiwavelength analysis of galaxies selected at 450 and 850 μm from the deepest SCUBA-2 observations in the Extended Groth Strip (EGS) field, which have an average depth of σ450 = 1.9 and σ850 = 0.46 mJy beam− 1 over ∼70 arcmin2. The final sample comprises 95 sources: 56 (59 per cent) are detected at both wavelengths, 31 (33 per cent) are detected only at 850 μm, and 8 (8 per cent) are detected only at 450 μm. We identify counterparts for 75 per cent of the whole sample. The redshift distributions of the 450 and 850 μm samples peak at different redshifts with median values of z¯=1.66±0.18 and z¯=2.30±0.20⁠, respectively. However, the two populations have similar IR luminosities, SFRs, and stellar masses, with mean values of 1.5 ± 0.2 × 1012 L⊙, 150 ± 20 M⊙ yr−1, and 9.0 ± 0.6 × 1010 M⊙, respectively. This places most of our sources (≳85 per cent) on the high-mass end of the main sequence of star-forming galaxies. Exploring the IR excess versus UV-slope (IRX-β) relation we find that the most luminous galaxies are consistent with the Meurer law, while the less luminous galaxies lie below this relation. Using the results of a two-dimensional modelling of the HSTH160-band imaging, we derive a median Sérsic index of n=1.4+0.3−0.1 and a median half-light radius of r1/2 = 4.8 ± 0.4 kpc. Based on a visual-like classification in the same band, we find that the dominant component for most of the galaxies at all redshifts is a disc-like structure, although there is a transition from irregular discs to discs with a spheroidal component at z ∼ 1.4, which morphologically supports the scenario of SMGs as progenitors of massive elliptical galaxies.
Keywords: galaxies: evolution; galaxies: high redshift; galaxies: star formation; submillimetre: galaxies

The Mycobacterium tuberculosis complex has a pathway for the biosynthesis of 4‐formamido‐4,6‐dideoxy‐d‐glucose - Brown, Haley A.; Vinogradov, Evgeny; Gilbert, Michel; Holden, Hazel M. (Protein Science, 2018)
Recent studies have demonstrated that the O‐antigens of some pathogenic bacteria such as Brucella abortus, Francisella tularensis, and Campylobacter jejuni contain quite unusual N‐formylated sugars (3‐formamido‐3,6‐dideoxy‐d‐glucose or 4‐formamido‐4,6‐dideoxy‐d‐glucose). Typically, four enzymes are required for the formation of such sugars: a thymidylyltransferase, a 4,6‐dehydratase, a pyridoxal 5'‐phosphate or PLP‐dependent aminotransferase, and an N‐formyltransferase. To date, there have been no published reports of N‐formylated sugars associated with Mycobacterium tuberculosis. A recent investigation from our laboratories, however, has demonstrated that one gene product from M. tuberculosis, Rv3404c, functions as a sugar N‐formyltransferase. Given that M. tuberculosis produces l‐rhamnose, both a thymidylyltransferase (Rv0334) and a 4,6‐dehydratase (Rv3464) required for its formation have been identified. Thus, there is one remaining enzyme needed for the production of an N‐formylated sugar in M. tuberculosis, namely a PLP‐dependent aminotransferase. Here we demonstrate that the M. tuberculosis rv3402c gene encodes such an enzyme. Our data prove that M. tuberculosis contains all of the enzymatic activities required for the formation of dTDP‐4‐formamido‐4,6‐dideoxy‐d‐glucose. Indeed, the rv3402c gene product likely contributes to virulence or persistence during infection, though its temporal expression and location remain to be determined.
Keywords: aminotransferase; dTDP-4-amino-4,6-dideoxy-D-glucose; Mycobacterium tuberculosis; pyridoxal 5’-phosphate; Rv3402c

MICHI: a thermal-infrared instrument for the TMT - Packham, Christopher; Honda, Mitsuhiko; Chun, Mark; Sakon, Itsuki; Richter, Matthew; Okamoto, Yoshiko; Kataza, Hirokazu; Marois, Christian; Meyer, Michael; Puravankara, Manoj; Birkby, Jayne; Crossfield, Ian; et al. (Ground-based and Airborne Instrumentation for Astronomy VII, 2018)
With the imminent launch of the JWST, the field of thermal-infrared (TIR) astronomy will enjoy a revolution. It is easy to imagine that all areas of infrared (IR) astronomy will be greatly advanced, but perhaps impossible to conceive of the new vistas that will be opened. To allow both follow-up JWST observations and a continuance of work started on the ground-based 8m’s, we continue to plan the science cases and instrument design for a TIR imager and spectrometer for early operation on the TMT. We present the current status of our science cases and the instrumentation plans, harnessing expertise across the TMT partnership. This instrument will be proposed by the MICHI team as a second-generation instrument in any upcoming calls for proposals.
Keywords: Infrared; mid-infrared; thermal infrared; imaging; spectroscopy; high spectral resolution; adaptive optics; polarimetry

The GeMS/GSAOI Galactic Globular Cluster Survey (G4CS). I. A pilot study of the stellar populations in NGC 2298 and NGC 3201 - Monty, Stephanie; Puzia, Thomas H.; Miller, Bryan W.; Carrasco, Eleazar R.; Simunovic, Mirko; Schirmer, Mischa; Stetson, Peter B.; Cassisi, Santi; Venn, Kim A.; Dotter, Aaron; Goudfrooij, Paul; Perina, Sibilla; et al. (The Astrophysical Journal, 2018)
We present the first results from the GeMS/GSAOI Galactic Globular Cluster Survey (G4CS) of the Milky Way globular clusters NGC 3201 and NGC 2298. Using the Gemini South Adaptive Optics Imager (GSAOI), in tandem with the Gemini Multi-conjugate adaptive optics System (GeMS) on the 8.1 m Gemini-South telescope, we collected deep near-IR observations of both clusters, resolving their constituent stellar populations down to K s sime 21 Vega mag. Point-spread function (PSF) photometry was performed on the data using spatially variable PSFs to generate JHK s photometric catalogs for both clusters. These catalogs were combined with Hubble Space Telescope (HST) data to augment the photometric wavelength coverage, yielding catalogs that span the near-UV to near-IR. We then applied 0.14 mas yr−1 accurate proper-motion cleaning and differential-reddening corrections and chose to anchor our isochrones using the lower main-sequence knee and the main-sequence turnoff prior to age determination. As a result of the data quality, we found that the K s versus F606W − K s and F336W versus F336W − K s color–magnitude diagrams were the most diagnostically powerful. We used these two color combinations to derive the stellar population ages, distances, and reddening values for both clusters. Following isochrone fitting using three different isochrone sets, we derived best-fit absolute ages of 12.2 ± 0.5 Gyr and 13.2 ± 0.4 Gyr for NGC 3201 and NGC 2298, respectively. This was done using a weighted average over the two aforementioned color combinations, following a pseudo-χ 2 determination of the best-fit isochrone set. Our derived parameters are in good agreement with recent age determinations of the two clusters, with our constraints on the ages being or ranking among the most statistically robust.

The extraordinary linear polarisation structure of the Southern Centaurus a lobe revealed by ASKAP - Anderson, Craig; Heald, George; O’Sullivan, Shane; Bunton, John; Carretti, Ettore; Chippendale, Aaron; Collier, Jordan; Farnes, Jamie; Gaensler, Bryan; Harvey-Smith, Lisa; Koribalski, Bärbel; Landecker, Tom; et al. (Galaxies, 2018)
We present observations of linear polarisation in the southern radio lobe of Centaurus A, conducted during commissioning of the Australian Square Kilometre Array Pathfinder (ASKAP) telescope. We used 16 antennas to observe a 30 square degree region in a single 12-h pointing over a 240 MHz band centred on 913 MHz. Our observations achieve an angular resolution of 26×33 arcseconds (480 parsecs), a maximum recoverable angular scale of 30 arcminutes, and a full-band sensitivity of 85 μ Jy beam −1 . The resulting maps of polarisation and Faraday rotation are amongst the most detailed ever made for radio lobes, with order 10 5 resolution elements covering the source. We describe several as-yet unreported observational features of the lobe, including its detailed peak Faraday depth structure, and intricate networks of depolarised filaments. These results demonstrate the exciting capabilities of ASKAP for widefield radio polarimetry.
Keywords: magnetic fields; faraday tomography; magnetic turbulence; AGN

The direct and accurate determination of major elements Ca, K, Mg and Na in water by HR-ICPMS - Nadeau, Kenny; Mester, Zoltán; Yang, Lu (Scientific Reports, 2018)
A direct, accurate and precise method is reported for major elements Ca, K, Mg and Na measurements in river and drinking water using a high resolution ICP-MS. Double isotope dilution calibration was used for the determination of Mg whereas the combined standard addition and internal standardization (Sc) was used for Ca, K and Na measurements. The method is validated by analysis fresh water SLRS-5, SLRS-6 and SRM1640a with satisfactory results characterized by high precisions of 0.055% to 0.66% RSD (or 0.29–1.8% relative combined uncertainty) for all four analytes, superior to those reported in earlier studies. As noted, use of internal standard Sc has significantly (3–33 times) improved measurement precisions for Ca, K and Na compared to standard addition calibration alone. The proposed method was applied for the determination of major elements Ca, K, Mg and Na in a candidate drinking water CRM AQUA-1. Values of 1.908 ± 0.007 µg g−1, 8.27 ± 0.14 µg g−1, 0.660 ± 0.010 µg g−1 and 13.76 ± 0.05 µg g−1 (u, k = 1) were obtained for Mg, Ca, K and Na in AQUA-1 drinking water, respectively.

Tank car sloshing on rail transportation safety under various loading, track and in-train force conditions - Huang, Wei; Liu, Yan (2018 Joint Rail Conference : April 18-20, 2018, Pittsburgh, Pennsylvania, USA, 2018)
Analytical work was conducted to study if movement of liquid in a tank car (or sloshing) could contribute in any way to derailments of trains carrying dangerous goods liquids. A liquid sloshing model was developed for railway tank car with formulas generated based on available finite element analysis data. An empty tank car dynamics simulation model validated with measured data was used as the base model to implement the liquid sloshing model. Hundreds of thousands of dynamics simulations were conducted for the tank car with liquid cargo at various fill ratios and with equivalent solid (i.e., rigid) cargo on more than 1000 measured curves. The results show that under some conditions tank car sloshing could increase the risk of derailment. The detrimental effect of tank car sloshing on rail safety increases with the increase of outage, trailing tonnage, grade, car length difference, curvature, train speed and track geometry irregularities. Quantitative risk analysis could be improved by considering the effects of tank car sloshing on derailment risk. The findings can be used by regulators and the railroads to improve train marshalling practice and risk mapping of railway networks.
Keywords: safety; rail transportation; sloshing; trains; railway tank cars

Sulfated archaeol glycolipids: comparison with other immunological adjuvants in mice - Akache, Bassel; Stark, Felicity C.; Jia, Yimei; Deschatelets, Lise; Dudani, Renu; Harrison, Blair A.; Agbayani, Gerard; Williams, Dean; Jamshidi, Mohammad P.; Krishnan, Lakshmi; Mccluskie, Michael J.; Murthy, Ashlesh K. (PLOS ONE, 2018)
Archaeosomes are liposomes traditionally comprised of total polar lipids (TPL) or semi-synthetic glycerolipids of ether-linked isoprenoid phytanyl cores with varied glyco- and amino-head groups. As adjuvants, they induce robust, long-lasting humoral and cell-mediated immune responses and enhance protection in murine models of infectious disease and cancer. Traditional total polar lipid (TPL) archaeosome formulations are relatively complex and first generation semi-synthetic archaeosomes involve many synthetic steps to arrive at the final desired glycolipid composition. We have developed a novel archaeosome formulation comprising a sulfated disaccharide group covalently linked to the free sn-1 hydroxyl backbone of an archaeal core lipid (sulfated S-lactosylarchaeol, SLA) that can be more readily synthesized yet retains strong immunostimulatory activity for induction of cell-mediated immunity following systemic immunization. Herein, we have evaluated the immunostimulatory effects of SLA archaeosomes when used as adjuvant with ovalbumin (OVA) and hepatitis B surface antigen (HBsAg) and compared this to various other adjuvants including TLR3/4/9 agonists, oil-in-water and water-in-oil emulsions and aluminum hydroxide. Overall, we found that semi-synthetic sulfated glycolipid archaeosomes induce strong Ag-specific IgG titers and CD8 T cells to both antigens. In addition, they induce the expression of a number of cytokines/chemokines including IL-6, G-CSF, KC & MIP-2. SLA archaeosome formulations demonstrated strong adjuvant activity, superior to many of the other tested adjuvants.

Suppression of dry-band arcing erosion by silica filler in silicone rubber composites - Kone, Daouda; Cisse, Ladji; Ghunem, Refat A.; Hadjadj, Yazid; El-Hag, Ayman H.; Bangash, Kashif N. (2018 IEEE Conference on Electrical Insulation and Dielectric Phenomena (CEIDP), 2018)
The following topics are dealt with: electric breakdown; permittivity; filled polymers; partial discharges; space charge; transformer oil; ageing; power cable insulation; nanocomposites; power transformer insulation.
Keywords: erosion resistance; inert char; volume and size of silica filler; critical test voltage; The Inclined Plane Test

A novel miniature inverted-flame burner for the generation of soot nanoparticles - Kazemimanesh, Mohsen; Moallemi, Alireza; Thomson, Kevin; Smallwood, Greg; Lobo, Prem; Olfert, Jason S. (Aerosol Science and Technology, 2018)
Lab-scale soot nanoparticle generators are used by the aerosol research community to study the properties of soot over a broad range of particle size distributions, and number and mass concentrations. In this study, a novel miniature inverted-flame burner is presented and its emitted soot particles were characterized. The burner consisted of two co-annular tubes for fuel and co-flow air and the flame was enclosed by the latter. The fuel used was ethylene. A scanning mobility particle sizer (SMPS) and an aerodynamic aerosol classifier (AAC) were used to measure mobility and aerodynamic size distribution of soot particles, respectively. Particle morphology was studied using transmission electron microscopy (TEM). The elemental carbon (EC) and organic carbon (OC) content of the soot were measured using thermal-optical analysis (TOA). The burner produced soot particles with mobility diameter range of 66–270 nm, aerodynamic diameter range of 56–140 nm, and total concentration range of 2 × 10⁵–1 × 10⁷ cm⁻³. TEM images showed that most soot particles were sub-micron soot aggregates. Some soot superaggregates, typically larger than 2 µm in length, were observed and their abundance increased with ethylene flow rate. TOA showed that the concentration of EC in the generated soot increased with ethylene flow rate, and the soot was observed to have high EC fraction at high ethylene flow rates. The miniature inverted-flame burner was demonstrated to produce soot nanoparticles over a range of concentrations and sizes with high EC content, making it a practical device to study soot nanoparticle properties in different applications.

Subwavelength grating metamaterial engineering: a new tool for silicon photonics - Ortega-Moñux, A.; Luque-González, J. M.; Sánchez-Postigo, A.; Halir, R.; Wangüemert-Pérez, J. G.; Molina-Fernández, I.; Cheben, Pavel; Schmid, Jens H.; Xu, Dan-Xia; Soler-Penades, J.; Nedeljkovic, M.; Mashanovich, G. Z.; et al. (Advanced Photonics 2018 (BGPP, IPR, NP, NOMA, Sensors, Networks, SPPCom, SOF), 2018)
Subwavelength gratings (SWGs) are periodic structures with a pitch smaller than half the wavelength of the propagating light, so they behave as an equivalent homogeneous birefringent metamaterial. SWGs have found innumerable applications in the field of integrated optics over the past ten years, most of them implemented in the Silicon-on-Insulator platform (SOI). In this talk we will summarize some of our recent contributions in the development of SWG waveguide devices for near and mid-infrared wavelengths.

Sub-MHz ultrasonic sensor using fiber laser based on random fiber grating - Zhang, Liang; Xu, Yanping; Gu, Lijuan; Mihailov, Stephen; Lu, Ping; Chen, Liang; Bao, Xiaoyi (26th International Conference on Optical Fiber Sensors, 2018)
An intensity-modulated fiber laser sensor incorporating distributed feedback from a random fiber grating is experimentally investigated for the detection of multiple sub-MHz ultrasonic continuous waves with minimum frequency spacing of 3 Hz.

Structure dissection of zebrafish progranulins identifies a well-folded granulin/epithelin module protein with pro-cell survival activities - Wang, Ping; Chitramuthu, Babykumari; Bateman, Andrew; Bennett, Hugh P.J.; Xu, Ping; Ni, Feng (Protein Science, 2018)
The ancient and pluripotent progranulins contain multiple repeats of a cysteine‐rich sequence motif of ∼60 amino acids, called the granulin/epithelin module (GEM) with a prototypic structure of four β‐hairpins zipped together by six inter‐hairpin disulfide bonds. Prevalence of this disulfide‐enforced structure is assessed here by an expression screening of 19 unique GEM sequences of the four progranulins in the zebrafish genome, progranulins 1, 2, A and B. While a majority of the expressed GEM peptides did not exhibit uniquely folded conformations, module AaE from progranulin A and AbB from progranulin B were found to fold into the protopypic 4‐hairpin structure along with disulfide formation. Module AaE has the most‐rigid three‐dimensional structure with all four β‐hairpins defined using high‐resolution (H–15N) NMR spectroscopy, including 492 inter‐proton nuclear Overhauser effects, 23 3J(HN,Hα) coupling constants, 22 hydrogen bonds as well as 45 residual dipolar coupling constants. Three‐dimensional structure of AaE and the partially folded AbB re‐iterate the conformational stability of the N‐terminal stack of two beta‐hairpins and varying degrees of structural flexibility for the C‐terminal half of the 4‐hairpin global fold of the GEM repeat. A cell‐based assay demonstrated a functional activity for the zebrafish granulin AaE in promoting the survival of neuronal cells, similarly to what has been found for the corresponding granulin E module in human progranulin. Finally, this work highlights the remaining challenges in structure‐activity studies of proteins containing the GEM repeats, due to the apparent prevalence of structural disorder in GEM motifs despite potentially a high density of intramolecular disulfide bonds.
Keywords: 3D structure; granulin/epithelin module; progranulin; zebrafish; hairpin stack fold; NMRspectroscopy

SPIRou @CFHT: integration and performance of the cryogenic near infra-red spectrograph unit - Carmona, Andres; Micheau, Yoan; Parès, Laurent; Thibault, Simon; Vallée, Philippe; Donati, Jean-François; Kouach, Driss; Lacombe, Marielle; Challita, Zalpha; Reshetov, Vladimir; Baratchart, Sébastien; Barrick, Gregory A.; et al. (Ground-based and Airborne Instrumentation for Astronomy VII, 2018)
SPIRou is an innovative near infra-red echelle spectropolarimeter and a high-precision velocimeter for the 3.6 m Canada-France-Hawaii Telescope (CFHT – Mauna Kea, Hawaii). This new generation instrument aims at detecting planetary worlds and Earth-like planets of nearby red dwarfs, in habitable zone, and studying the role of the stellar magnetic field during the process of low-mass stars / planets formation. The cryogenic spectrograph unit, cooled down at 80 K, is a fiber fed double-pass cross dispersed echelle spectrograph which works in the 0.98-2.40 μm wavelength range, allowing the coverage of the YJHK bands in a single exposure. Among the key parameters, a long-term thermal stability better than 2 mK, a relative radial velocity better than 1 m.s -1 and a spectral resolution of 70K are required. After ~ 1 year of assembly, integration and tests at IRAP/OMP (Toulouse, France) during 2016/2017, SPIRou was then shipped to Hawaii and completely re-integrated at CFHT during February 2018. A full instrument first light was performed on 24th of April 2018. The technical commissioning / science validation phase is in progress until June 2018, before opening to the science community. In this paper, we describe the work performed on integration and test of the opto-mechanical assemblies composing the spectrograph unit, firstly in-lab, in Toulouse and then on site, at CFHT. A review of the performances obtained in-lab (in 2017) and during the first on-sky results (in 2018) is also presented.
Keywords: spectropolarimeter; velocimeter; near infra-red; cryogenic échelle spectrograph; exoplanets; low mass dwarfs; magnetic field; CFHT

Spall strength measurements in EPON 828 epoxy and an epoxy/carbon nanotube composite - Pepper, Jonathan E.; Huneault, Justin; Rahmat, Meysam; Petel, Oren E. (AIP Conference Proceedings; 1979, 2018)
Polymer nanocomposites are seeing more frequent use in armor applications. The role of the microstructure on the performance of these materials under dynamic tensile loading is of particular interest. In the present study, plate impact experiments were conducted in order to observe the dynamic response of a neat epoxy (EPON 828) and an epoxy/carbon nanotube composite. The objective was to examine the effect of nano-scale particle inclusions on the spall strength of the composite. The material response was resolved with the combined use of shock pins and a multi-channel photonic Doppler velocimeter. The addition of raw carbon nanotubes (CNT) to epoxy resulted in a composite material with lower spall strengths compared to strengths measured for neat epoxy at elevated shock stresses. Tensile strain rate was found to have the greatest effect on spall strength. Recovered composite fragments were imaged with a scanning electron microscope. Instances of nanotube pull-out were identified on internal fracture surfaces. The low spall strengths of the epoxy/CNT composite were attributed to an increase in the density of potential nucleation sites for spallation caused by presence of the nanotubes in the matrix.

Source substitution method for obtaining the power transmission from vibrating sources in buildings - Höllerab, Christoph; Gibbs, Barry M. (Applied Acoustics, 2018)
This paper describes a method analogous to the airborne sound source substitution method, to estimate the vibrational power injected by a structure-borne sound source into the supporting building element. The injected vibrational power is required for prediction of the structure-borne sound pressure from vibrating equipment in buildings. The paper focuses on high-mobility sources connected to low-mobility receivers, a situation which is commonly encountered in heavyweight construction. The mobility mismatch simplifies the transformation of laboratory measurement data to prediction of transmitted power in-situ. Three case studies were performed. In the first study, the power injected by a simple test source into a resiliently supported aluminium plate was determined using direct and indirect methods. Source substitution was investigated with different calibration options: steady-state excitation, transient excitation, and spatial averaging. The source power could be determined within 4 dB, compared with direct measurements of the injected power. In the second study, the power injected by a second source into a concrete transmission suite floor was determined. The third study was of a combined heating and power unit on a masonry wall. In this study, a reference sound pressure level in a receiver room was calculated and compared with a criterion curve for the assessment of low-frequency noise complaints. The case studies demonstrate that structure-borne sound source substitution is a promising development of the reception plate method. While the latter can be used if a free reception plate is available, the former circumvents problems of determining the transmitted power into coupled plates and therefore has application to real building conditions. The use of the instrumented hammer for the calibration and the use of spatial averaging significantly simplify the method.
Keywords: source powerIndirect methods; structure-borne sound sources; building acoustics; measurement techniques; reception plate; substitution method

Beneficial effect of Fe addition on the catalytic activity of electrodeposited MnOx films in the water oxidation reaction - Coller Pascuzzi, Marco Etzi; Selinger, Elizabeth; Sacco, Adriano; Castellino, Micaela; Rivolo, Paola; Hernández, Simelys; Lopinski, Gregory; Tamblyn, Isaac; Nasi, Roberto; Esposito, Serena; Manzoli, Maela; Bonelli, Barbara; et al. (Electrochimica Acta, 2018)
We report on a fast and simple protocol for the electrodeposition of Fe-MnOx films used as catalysts for the water oxidation (WO) reaction at neutral pH, and showing the beneficial effect of iron in terms of both activity and stability of the catalyst. While most electrodeposited MnOx WO catalysts are obtained starting from Mn(II) precursors, the proposed protocol consists in the galvanostatic cathodic deposition of Fe-MnOx onto conductive FTO glasses, using KMnO4 and Fe(NO₃)₃ as Mn and Fe precursors, respectively. In the absence of Fe, the Tafel slope drastically increases from 103 to 270 mV dec⁻¹ when passing from low to high overpotentials. The slope change, instead, is progressively reduced when the Fe precursor is added to the deposition solution and a constant slope of 105 mV dec⁻¹ is obtained in the whole overpotential range with an optimal Fe concentration of 1.00 mM, Accordingly, Electrochemical Impedance Spectroscopy (EIS) shows that Fe addition improves both charge transfer and transport properties of the electrodeposited films. In particular, a five-fold decrease in charge transfer resistance at the catalyst/electrolyte interface was observed, suggesting a more facile oxygen evolving kinetics for Fe containing samples. Furthermore, the lower the iron content, the lower the film stability, as pointed out by chronopotentiometric measurements, and confimed by FESEM analysis and EIS as measured both before and after water electrolysis experiments. To establish structure activity relationships, an extended characterization of the electrodeposited films was carried out by means of Raman Microscopy, Transmission Electron Microscopy, UV–vis and X-ray Photoelectron Spectroscopies. The ensemble of the characterization results suggests that Fe³⁺ ions are actually incorporated within the electrodeposited film, with limited effects on the final Fe-MnOx structure, consisting in a defective MnO₂ birnessite-type structure with significant fraction of surface Mn³⁺ species.
Keywords: Manganese oxides; Electrocatalysis; Oxygen evolution reaction; Water electrolysis; Iron addition

Temperature induced lipid membrane restructuring and changes in nanomechanics - Bhojoo, Urvi; Chen, Maohui; Zou, Shan (Biochimica et Biophysica Acta (BBA) - Biomembranes, 2018)
The naturally occurring milk sphingomyelin is of particular interest owing to its complex composition and involvement in the formation of the milk fat globule membrane (MFGM). Knowledge of membrane organization and nanomechanical stability has proved to be crucial in understanding their properties and functions. In this work, two model membrane systems composed of 1, 2 dioleoyl-sn-glycero-3-phosphocholine (DOPC), egg sphingomyelin (egg-SM) and cholesterol, and DOPC, milk sphingomyelin (milk-SM) and cholesterol were exposed to both RT and 10 °C. The morphological and nanomechanical changes were investigated using atomic force microscopy (AFM) imaging and force mapping below RT using a designed liquid cell with temperature-control. In both systems, the size and shape of SM/Chol-enriched liquid ordered domains (Lo) and DOPC-enriched liquid disordered phase (Ld) were monitored at controlled temperatures. AFM based force-mapping showed that rupture forces were consistently higher for Lo domains than Ld phases and were decreased for Ld with decreasing temperature while an increase in breakthrough force was observed in Lo domains. More interestingly, dynamic changes and defect formations in the hydrated lipid bilayers were mostly detected at low temperature, suggesting a rearrangement of lipid molecules to relieve additional tension introduced upon cooling. Noteworthy, in these model membrane systems, tension-driven defects generally heal on reheating the sample. The results of this work bring new insights to low temperature induced membrane structural reorganization and mechanical stability changes which will bring us one step closer to understand more complex systems such as the MFGM.
Keywords: Supported lipid bilayers; Atomic force microscopy; Force mapping; Low temperature; Force indentation; Milk lipids; Sphingomyelin; Cholesterol

SKA telescope manager: a status update - Chaudhuri, Subhrojyoti R.; Di carlo, Matteo; Le Roux, Gerhard; Natarajan, Swaminathan; Wadadekar, Yogesh; Ramanujam, Niruj M.; Kodikar, Jitendra; Sathe, Vinod; Patil, Mangesh; Khanvilkar, Amruta; Dange, Aditya; Trivedi, Vatsal; et al. (Software and Cyberinfrastructure for Astronomy V, 2018)
The international Square Kilometre Array (SKA) project to build two radio interferometers is approaching the end of its design phase, and gearing up for the beginning of formal construction. A key part of this distributed Observatory is the overall software control system: the Telescope Manager (TM). The two telescopes, a Low frequency dipole array to be located in Western Australia (SKA-Low) and a Mid-frequency dish array to be located in South Africa (SKA-Mid) will be operated as a single Observatory, with its global headquarters (GHQ) based in the United Kingdom at Jodrell Bank. When complete it will be the most powerful radio observatory in the world. The TM software must combine the observatory operations based at the GHQ with the monitor and control operations of each telescope, covering the range of domains from proposal submission to the coordination and monitoring of the subsystems that make up each telescope. It must also monitor itself and provide a reliable operating platform. This paper will provide an update on the design status of TM, covering the make-up of the consortium delivering the design, a brief description of the key challenges and the top level architecture, and its software development plans for tackling the construction phase of the project. It will also briefly describe the consortium’s response to the SKA Project’s decision in the second half of 2016 to adopt the processes set out by the Software Engineering Institute (SEI) for system architecture design and documentation, including a re-evaluation of its deliverables, documentation and approach to internal reviews.
Keywords: radio astronomy; interferometry; software architecture; project management

Size and surface effects of silicon nanocrystals in graphene aerogel composite anodes for lithium ion batteries - Aghajamali, Maryam; Xie, Hezhen; Javadi, Morteza; Kalisvaart, W. Peter; Buriak, Jillian M.; Veinot, Jonathan G. C. (Chemistry of Materials, 2018)
Silicon is recognized as a promising anode material for high-performance lithium ion batteries due to its high theoretical specific capacity and elemental abundance. Challenges related to the low electrical conductivity of Si and large volume changes during the lithiation/delithiation cycles, as well as the low rate of lithium diffusion in silicon anodes, hinder practical applications. To provide fundamental insights into these issues, silicon nanocrystal/graphene aerogel nanocomposites were synthesized by combining undecanoic acid-functionalized silicon nanocrystals of various sizes (SiX-COOH, where X represents the nanocrystal diameter of 3, 5, 8, and 15 nm) with conductive mesoporous graphene aerogels (GAs). The silicon nanocrystals are evenly dispersed throughout the graphene aerogel as shown by energy-dispersive X-ray (EDX) mapping. In terms of electrochemical performance, SiX-COOH/GA nanocomposites demonstrated a clear dependence on the size of the embedded silicon nanocrystals, with the composites comprising the larger silicon nanocrystals showing a higher initial capacity but accompanied by rapid decay of capacity retention over 100 cycles. To study the effect of thermal processing on the electrochemical performance, SiX-COOH/GA nanocomposites were annealed at 600 °C to yield annealed SiX/GA nanocomposites. The annealed nanocomposite composed of the smallest silicon nanocrystals, Si3/GA, exhibits a stable specific capacity of ∼1100 mAh/g and capacity retention of over 90% after 500 cycles when tested at a current density of 400 mA/g.

Single channel continuous wave doppler radar for differentiating types of human activity - Valdes, Julio J.; Baird, Zachary; Rajan, Sreeraman; Bolic, Miodrag (2018 International Joint Conference on Neural Networks (IJCNN), 2018)
In real life applications, it is crucial to monitor the different kinds of human activity without interfering with their regular occupations. Contactless physiological monitoring using radars is a valuable tool, but typically it is performed when the human subjects are immobile. This paper analyzes single channel Continuous Wave (CW) Doppler radar signals in relation to three levels of human activity: i) Sedentary and still, ii) Sedentary and moving and iii) Walking. A combination of computational intelligence techniques (GammaTest, neural networks, random forest and genetic algorithms) was used for assessing the predictive ability of 43 features derived from the radar return signal, as well as of subsets of them, which were composed of highly predictive attributes. It is shown that with about one half the number of attributes it is possible to achieve high levels of classification accuracy, in some cases improving false negative ratios. While several attributes were completely irrelevant and noisy, others were required by discriminating each of the classes. There are attributes required by certain classes in particular and there are others associated to the distinction of classes with subtle differences.
Keywords: GammaTest; genetic algorithms; extreme learning machines; random forest; multilayer perceptron; feature selection

Shifting the limits in wheat research and breeding using a fully annotated reference genome - Appels, Rudi; Eversole, Kellye; Stein, Nils; Feuillet, Catherine; Keller, Beat; Rogers, Jane; Pozniak, Curtis J.; Choulet, Frédéric; Distelfeld, Assaf; Poland, Jesse; Ronen, Gil; Sharpe, Andrew G.; et al. (Science, 2018)
INTRODUCTION: Wheat (Triticum aestivum L.) is the most widely cultivated crop on Earth, contributing about a fifth of the total calories consumed by humans. Consequently, wheat yields and production affect the global economy, and failed harvests can lead to social unrest. Breeders continuously strive to develop improved varieties by fine-tuning genetically complex yield and end-use quality parameters while maintaining stable yields and adapting the crop to regionally specific biotic and abiotic stresses. RATIONALE: Breeding efforts are limited by insufficient knowledge and understanding of wheat biology and the molecular basis of central agronomic traits. To meet the demands of human population growth, there is an urgent need for wheat research and breeding to accelerate genetic gain as well as to increase and protect wheat yield and quality traits. In other plant and animal species, access to a fully annotated and ordered genome sequence, including regulatory sequences and genome-diversity information, has promoted the development of systematic and more time-efficient approaches for the selection and understanding of important traits. Wheat has lagged behind, primarily owing to the challenges of assembling a genome that is more than five times as large as the human genome, polyploid, and complex, containing more than 85% repetitive DNA. To provide a foundation for improvement through molecular breeding, in 2005, the International Wheat Genome Sequencing Consortium set out to deliver a high-quality annotated reference genome sequence of bread wheat. RESULTS: An annotated reference sequence representing the hexaploid bread wheat genome in the form of 21 chromosome-like sequence assemblies has now been delivered, giving access to 107,891 high-confidence genes, including their genomic context of regulatory sequences. This assembly enabled the discovery of tissue- and developmental stage–related gene coexpression networks using a transcriptome atlas representing all stages of wheat development. The dynamics of change in complex gene families involved in environmental adaptation and end-use quality were revealed at subgenome resolution and contextualized to known agronomic single-gene or quantitative trait loci. Aspects of the future value of the annotated assembly for molecular breeding and research were exemplarily illustrated by resolving the genetic basis of a quantitative trait locus conferring resistance to abiotic stress and insect damage as well as by serving as the basis for genome editing of the flowering-time trait. CONCLUSION: This annotated reference sequence of wheat is a resource that can now drive disruptive innovation in wheat improvement, as this community resource establishes the foundation for accelerating wheat research and application through improved understanding of wheat biology and genomics-assisted breeding. Importantly, the bioinformatics capacity developed for model-organism genomes will facilitate a better understanding of the wheat genome as a result of the high-quality chromosome-based genome assembly. By necessity, breeders work with the genome at the whole chromosome level, as each new cross involves the modification of genome-wide gene networks that control the expression of complex traits such as yield. With the annotated and ordered reference genome sequence in place, researchers and breeders can now easily access sequence-level information to precisely define the necessary changes in the genomes for breeding programs. This will be realized through the implementation of new DNA marker platforms and targeted breeding technologies, including genome editing.

Sherlock: capturing probe requests for automatic presence detection - Oliveira, Luiz; Henrique, Joao; Schneider, Daniel; De Souza, Jano; Rodriques, Sergio; Sherr, Weiming (2018 IEEE 22nd International Conference on Computer Supported Cooperative Work in Design ((CSCWD)), 2018)
The ubiquity of smartphones creates great opportunities for participatory sensing, where people can implicitly contribute observations about their local environments through sensors such as cameras and accelerometers. The collected data can then be aggregated and used to benefit the crowd in some way. In this paper, we report on the current development of Sherlock, a device capable of automatically detecting the presence of people in localities through evidences left by smartphones called probe requests, without any user intervention. To validate the proposed mechanism implemented in the device, we performed an experiment with ten participants in six rounds where it was possible to automatically detect 41 presence events, of which 66% could be detected within less than 30s. The implicit crowdsourcing mechanism behind this approach may allow real-time monitoring of people flows in public environments, which can enable, among other things, energy systems to be automatically orchestrated according to demand, reducing associated costs.

Stamping of high performance thermoplastic composite intrusion beams - Trudel-Boucher, D; Champagne, M. F. (IOP Conference Series: Materials Science and Engineering, 2018)
In this study, an experimental investigation was performed to evaluate the potential of thermoplastic composites to be used for the fabrication of an automotive intrusion beam using the composite stamping process. To assess the potential of this technology, mechanical properties of several high performance thermoplastic composite materials were first evaluated on coupons. Due to their higher load and displacement at failure, the most promising materials for the fabrication of a composite intrusion beam were found to be glass fibre/polypropylene (GF/PP) and carbon fibre/polyamide 66 (CF/PA66) laminates. Then, stamped intrusion beams were manufactured from these composites using three different stacking sequences. The beams were later tested under three-point flexural loading. For all components, failure occurred at the attachment points. However, higher properties were obtained for ± 45 laminates for which shear-out failure could be avoided. From the load-displacement curves obtained, it can nevertheless be concluded that stamping of thermoplastic composites is promising for the fabrication of intrusion beams, but that further development will be required to avoid failure at the attachment points.

Review and comparison of ASTM and ISO standards on sound transmission in buildings - Höller, Christoph (INTER-NOISE 2018: 47th International Congress and Exposition on Noise Control Engineering: Impact of Noise Control Engineering, 2018)
Many of the commonly used measurement methods in room and building acoustics are standardized in international standards published by ASTM International or the International Standardization Organization (ISO). This paper will provide an overview of the ASTM standards on sound transmission in buildings (developed by ASTM committee E33.03) and their ISO counterparts (developed by ISO/TC 43/SC 2), highlighting similarities and notable differences. The need for ASTM standards equivalent to the ISO 12354 series for estimating the acoustic performance of buildings from the performance of elements is discussed. For laboratory sound insulation tests, the analysis is carried further. Based on a large database of sound insulation tests conducted at the National Research Council Canada, the single-number ratings for airborne sound insulation of walls and floors are compared.
Keywords: laboratory measurement; single-number rating; sound insulation; standards

Reliable parameter extraction of asymmetric GaN-based heterojunction field effect transistors - Du, Xuekun; Dhar, Sagar K.; Jarndal, Anwar; Storey, Craig; Helaoui, Mohamed; Wingar, Simon; Jiang you, Chang; Cai, Jingye; Ghannouchi, Fadhel M. (2018 13th European Microwave Integrated Circuits Conference (EuMIC), 2018)
A novel reliable small signal model parameter extraction of asymmetric GaN-based Heterojunction Field Effect Transistors (HFETs) is proposed in this paper. An efficient systematic searching procedure based on pinch-off and cold weak-forward S-parameters has been developed to consider the asymmetric structure of GaN HFETs and find the optimal values of the gate and drain pad capacitances Cpg and Cpd. Considering that the depletion region extension is varied with the gate bias voltage V gs slightly even below pinch-off voltage, the obtained initial values of the extracted parameters are optimized by artificial bee colony (ABC) algorithm to improve the reliability of parameter extraction. The developed parameter extraction method shows excellent accuracy and reliability. The proposed procedure can be extended to asymmetric GaN devices with various process technologies. The developed approach has been validated by an asymmetric 0.15 μm GaN HFET over a wide range of bias conditions and frequencies.

Recent progress in advanced electrode materials, separators and electrolytes for lithium batteries - Zhang, Hailin; Zhao, Hongbin; Khan, Muhammad Arif; Zou, Wenwen; Xu, Jiaqiang; Zhang, Lei; Zhang, Jiujun (Journal of Materials Chemistry A, 2018)
Lithium-ion batteries (LIBs) possess several advantages over other types of viable practical batteries, including higher operating voltages, higher energy densities, longer cycle lives, lower rates of self-discharge and less environmental pollution. Therefore, LIBs have been widely and successfully applied in portable electronic devices and industrial fields. However, the rapidly increasing demands of new energy vehicles have also quickly increased the performance requirements of LIBs, including the need for higher power densities, greater capacity densities and better safety. As battery designs gradually standardize, improvements in LIB performances mainly depend on the technical progress in key electrode materials such as positive and negative electrode materials, separators and electrolytes. For LIB performances to meet the rising requirements, many studies on the structural characteristics and morphology modifications of electrode/separator/electrolyte materials with different synthesis methods have been conducted. In this review, recent progress of LIBs is reviewed with a focus on positive electrode materials, negative electrode materials, separators and electrolytes in terms of energy density, power density, life-cycle and safety. To accelerate the research and development and to overcome the challenges of LIB technology and application, several possible research directions are also discussed to further improve LIB performances.

Recent advances in mass spectrometry imaging for multiomics application in neurology - Xu, Guang; Li, Jianjun (Journal of Comparative Neurology, 2018)
Mass spectrometry imaging (MSI) has emerged as a powerful tool for multiomics study in neurology. MSI combines the multichannel (m/z) measurement capability of mass spectrometers with a surface sampling process that allows for rapid probing and mapping of the characterized intact proteins, proteolytic digested peptides, released glycans, phospholipids, glycolipids, and small metabolites in brain tissues. The present review is focused on the application of MSI to the study of proteomics, glycomics, peptidomics, metabolomics, and lipidomics in mouse brain tissues.
Keywords: mass spectrometry; mouse brain; proteomics; metabolomics; glycomics; lipidomics

Real-time large-scale fusion of high resolution 3D scans with details preservation - Sekkati, Hicham; Boisvert, Jonathan; Godin, Guy; Borgeat, Louis (2018 15th Conference on Computer and Robot Vision (CRV), 2018)
This paper presents a real-time 3D shape fusion system that faithfully integrates very high resolution 3D scans with the goal of maximizing details preservation. The system fully maps complex shapes while allowing free movement similarly to dense SLAM systems in robotics where sensor fusion techniques map large environments. We propose a novel framework to integrate shapes into a volume with fine details preservation of the reconstructed shape which is an important aspect in many applications, especially for industrial inspection. The truncated signed distance function is generalized with a global variational scheme that controls edge preservation and leads to updating cumulative rules adapted for GPU implementation. The framework also embeds a map deformation method to online deform the shape and correct the system trajectory drift at few microns accuracy. Results are presented from the integrated system on two mechanical objects which illustrate the benefits of the proposed approach.
Keywords: RGB-D; real-time fusion; large-scale 3D scans; volumetric representation; dense SLAM; GPU

Random fiber gratings fabricated using Fs-IR laser for distributed temperature sensor application - Lu, Ping; Mihailov, Stephen J.; Coulas, David; Ding, Huimin; Bao, Xiaoyi (26th International Conference on Optical Fiber Sensors, 2018)
By using the plane-by-plane grating inscription method with a fs-IR laser, random fiber gratings were fabricated in SMF-28 fiber with different phase shifts between different planes for temperature sensing. With the well-defined bandwidth of the enhanced backscattering, the random grating based distributed temperature sensing system shows high accuracy of temperature measurement and low laser-induced loss.

Radiative transfer calculations of the diffuse ionized gas in disc galaxies with cosmic ray feedback - Vandenbroucke, Bert; Wood, Kenneth; Girichidis, Philipp; Hill, Alex S.; Peters, Thomas (Monthly Notices of the Royal Astronomical Society, 2018)
The large vertical scale heights of the diffuse ionized gas (DIG) in disc galaxies are challenging to model, as hydrodynamical models including only thermal feedback seem to be unable to support gas at these heights. In this paper, we use a three-dimensional Monte Carlo radiation transfer code to post-process disc simulations of the Simulating the Life-Cycle of Molecular Clouds project that include feedback by cosmic rays. We show that the more extended discs in simulations including cosmic ray feedback naturally lead to larger scale heights for the DIG which are more in line with observed scale heights. We also show that including a fiducial cosmic ray heating term in our model can help to increase the temperature as a function of disc scale height, but fails to reproduce observed DIG nitrogen and sulphur forbidden line intensities. We show that, to reproduce these line emissions, we require a heating mechanism that affects gas over a larger density range than is achieved by cosmic ray heating, which can be achieved by fine tuning the total luminosity of ionizing sources to get an appropriate ionizing spectrum as a function of scale height. This result sheds a new light on the relation between forbidden line emissions and temperature profiles for realistic DIG gas distributions.
Keywords: radiative transfer; methods: numerical; cosmic rays; galaxies: ISM; galaxies: structure

Purity assignment for peptide certified reference materials by combining qNMR and LC-MS/MS amino acid analysis results: application to angiotensin II - Melanson, Jeremy E.; Thibeault, Marie-Pier; Stocks, Bradley B.; Leek, Donald M.; Mcrae, Garnet; Meija, Juris (Analytical and Bioanalytical Chemistry, 2018)
The purity value assignment of metrologically traceable peptide reference standards requires specialized primary methods. Conventionally, amino acid analysis by isotope dilution tandem mass spectrometry (LC-MS/MS) following peptide hydrolysis is employed as a reference method. By contrast, quantitative nuclear magnetic resonance (qNMR) spectroscopy allows for quantitation of intact peptides, thus eliminating potential bias due to hydrolysis. Both methods are susceptible to interference from related peptide impurities, which need to be accurately measured and accounted for. The mass balance approach has also been employed for peptide purity measurements, whereby the purity is defined by the sum of the mass fraction of all impurities identified. Ideally, results from these three orthogonal methods can be combined for final purity assignment of peptide reference standards. Here we report a novel strategy for correcting both LC-MS/MS and 1H-qNMR results for related peptide impurities and combining results from both methods using a Bayesian statistical approach using mass balance results as prior knowledge. The mass balance method relied on a validated 19F-qNMR method to measure the trifluoroacetic acid (TFA) counter-ion, considered an impurity in this case at nearly 25% by mass. Using a candidate certified reference material (CRM) for angiotensin II, excellent agreement was achieved with the three methods. The final purity value assignment of the candidate CRM was 691 ± 9 mg/g (k = 2).
Keywords: amino acids/peptides; reference materials; qNMR; isotope dilution; Bayesian analysis

ProPOSE: direct exhaustive protein–protein docking with side chain flexibility - Hogues, Hervé; Gaudreault, Francis; Corbeil, Christopher R.; Deprez, Christophe; Sulea, Traian; Purisima, Enrico O. (Journal of Chemical Theory and Computation, 2018)
Despite decades of development, protein–protein docking remains a largely unsolved problem. The main difficulties are the immense space spanned by the translational and rotational degrees of freedom and the prediction of the conformational changes of proteins upon binding. FFT is generally the preferred method to exhaustively explore the translation-rotation space at a fine grid resolution, albeit with the trade-off of approximating force fields with correlation functions. This work presents a direct search alternative that samples the states in Cartesian space at the same resolution and computational cost as standard FFT methods. Operating in real space allows the use of standard force field functional forms used in typical non-FFT methods as well as the implementation of strategies for focused exploration of conformational flexibility. Currently, a few misplaced side chains can cause docking programs to fail. This work specifically addresses the problem of side chain rearrangements upon complex formation. Based on the observation that most side chains retain their unbound conformation upon binding, each rigidly docked pose is initially scored ignoring up to a limited number of side chain overlaps which are resolved in subsequent repacking and minimization steps. On test systems where side chains are altered and backbones held in their bound state, this implementation provides significantly better native pose recovery and higher quality (lower RMSD) predictions when compared with five of the most popular docking programs. The method is implemented in the software program ProPOSE (Protein Pose Optimization by Systematic Enumeration).

Progress in light emission from silicon and germanium nanostructures - Lockwood, David J. (ECS Transactions, 2018)
Light emission from silicon and germanium nanostructures has been of great interest for some time now owing to the need for silicon-based light sources for applications in silicon optoelectronics and photonics. Both silicon and germanium possess indirect band gaps, which makes them very inefficient light emitters. Band gap engineering employing quantum wells, wires, or dots has been proposed as one way to overcome this limitation and, in the past, Si/Ge, Si/SiO2, or Si/SiGe-alloy thin-multilayer nanostructures grown on Si have been produced on this principle, and although light emission with greatly improved efficiency has been obtained at low temperatures the emission at room temperature is still very weak, because of exciton dissociation. Recent advances in band gap engineering technology have resulted in the development of new systems incorporating one-, two-, and three-dimensionally confined Si-Ge nanostructures that produce bright light in the near infrared. Here, the novel optical properties of recently-investigated various such nanostructures are reviewed.

Production of particulate brown carbon during atmospheric aging of residential wood-burning emissions - Kumar, Nivedita K.; Corbin, Joel C.; Bruns, Emily A.; Massabó, Dario; Slowik, Jay G.; Drinovec, Luka; Močnik, Griša; Prati, Paolo; Vlachou, Athanasia; Baltensperger, Urs; Gysel, Martin; El-haddad, Imad; et al. (Atmospheric Chemistry and Physics, 2018)
We investigate the optical properties of light-absorbing organic carbon (brown carbon) from domestic wood combustion as a function of simulated atmospheric aging. At shorter wavelengths (370–470 nm), light absorption by brown carbon from primary organic aerosol (POA) and secondary organic aerosol (SOA) formed during aging was around 10 % and 20 %, respectively, of the total aerosol absorption (brown carbon plus black carbon). The mass absorption cross section (MAC) determined for black carbon (BC, 13.7 m2 g−1 at 370 nm, with geometric standard deviation GSD =1.1) was consistent with that recommended by Bond et al. (2006). The corresponding MAC of POA (5.5 m2 g−1; GSD =1.2) was higher than that of SOA (2.4 m2 g−1; GSD =1.3) at 370 nm. However, SOA presents a substantial mass fraction, with a measured average SOA ∕ POA mass ratio after aging of ∼5 and therefore contributes significantly to the overall light absorption, highlighting the importance of wood-combustion SOA as a source of atmospheric brown carbon. The wavelength dependence of POA and SOA light absorption between 370 and 660 nm is well described with absorption Ångström exponents of 4.6 and 5.6, respectively. UV-visible absorbance measurements of water and methanol-extracted OA were also performed, showing that the majority of the light-absorbing OA is water insoluble even after aging.

Production of domoic acid from large-scale cultures of pseudo-nitzschia multiseries: a feasibility study - Lewis, Nancy I.; Bates, Stephen S.; Quilliam, Michael A. (Harmful Algae, 2018)
The commercial demand for domoic acid (DA), the phycotoxin responsible for Amnesic Shellfish Poisoning, is currently met by extraction from a diminishing supply of stockpiled contaminated mussels (Mytilus edulis). As this supply becomes scarce, a more reliable source is needed. Purification of the toxin from an algal source would be easier and more economical than from shellfish tissue if algal growth and yield of toxin were maximized. This project was initiated to determine if DA could be produced using large-scale semi-continuous algal cultures, which should reduce labour and shorten the time required for biomass production. Pseudo-nitzschia multiseries was grown in 300-L fibreglass photobioreactors called a Brite-Box™. The effect of temperature and nutrient depletion on the yield of DA by P. multiseries was examined. A decline in maximum cell number without a substantial increase in cellular DA was associated with increased temperature. Maximum total cellular DA (8.8 pg cell−1) was achieved at 20 °C. Semi-continuous culture of P. multiseries is accompanied by increasing amounts of DA lost to the medium. The process was deemed to be feasible for growing P. multiseries but methods to recover this extracellular DA are necessary for this process to be economical.
Keywords: diatom; domoic acid; photobioreactor; pseudo-nitzschia

Printed sensors for building management - Zhang, Zhiyi; Ding, Heping; Alem, Salima; Griffin, Ryan; Tao, Ye; Xiao, Gaozhi; Pardasani, Ajit; Xu, Henry; Arsenault, Chantal; Newsham, Guy (2018 International Flexible Electronics Technology Conference (IFETC), 2018)
A high density wireless environmental sensor network has great potential to provide enhanced control options to building automation systems to reduce energy consumption and thus GHG emissions. In this work, we have developed light sensors and temperature sensors with solar energy harvesting and wireless communication capability for the application. The hybrid sensors are built by integrating printed sensing elements with EnOcean's technology that provides solar energy harvesting and wireless transmission functions. The light sensing and temperature sensing elements were printed on flexible PET films using organic photosensitive materials and particle-filled polymer inks developed by our team. The resulting hybrid sensors were tested and shown to meet design specifications. The light sensors have been installed in a full-scale office test bed for demonstrating efficient light control.
Keywords: printable electronics; sensors; energy harvest; wireless; building automation systems (key words)

Printed flexible FE memory array testing system - Chang, Shoude; Zhang, Yanguang; Aich, Badrou Reda; Tao, Ye (2018 7th Electronic System-Integration Technology Conference (ESTC), 2018)
In this paper, a compact testing system is developed to read/write a printed flexible FE (Ferroelectric) memory arrays and evaluate individual FE capacitors. Novel technologies, to the best of our knowledge, for random cell accessing, reading/writing,and analyzing are achieved. This compact system (both hardware and software) is controlled by LabVIEW program installed in a Laptop,and is essentially multi-functional and programmable. This system is designed for writing/reading FE memory cells, individually or in batch, as well as analyzing and displaying FE memory.
Keywords: printed electronics; flexible electronics; nonvolatileFE memory; ferroelectric memory read and write

Preclinical quantitative in-vivo assessment of skin tissue vascularity in radiation-induced fibrosis with optical coherence tomography - Demidov, Valentin; Zhao, Xiao; Demidova, Olga; Pang, Hilary Y. M.; Flueraru, Costel; Liu, Fei-Fei; Vitkin, I. Alex (Journal of Biomedical Optics, 2018)
Radiation therapy (RT) is widely and effectively used for cancer treatment but can also cause deleterious side effects, such as a late-toxicity complication called radiation-induced fibrosis (RIF). Accurate diagnosis of RIF requires analysis of histological sections to assess extracellular matrix infiltration. This is invasive, prone to sampling limitations, and thus rarely used; instead, current practice relies on subjective clinical surrogates, including visual observation, palpation, and patient symptomatology questionnaires. This preclinical study demonstrates that functional optical coherence tomography (OCT) is a useful tool for objective noninvasive in-vivo assessment and quantification of fibrosis-associated microvascular changes in tissue. Data were collected from murine hind limbs 6 months after 40-Gy single-dose irradiation and compared with nonirradiated contralateral tissues of the same animals. OCT-derived vascular density and average vessel diameter metrics were compared to quantitative vascular analysis of stained histological slides. Results indicate that RIF manifests significant microvascular changes at this time point posttreatment. Abnormal microvascular changes visualized by OCT in this preclinical setting suggest the potential of this label-free high-resolution noninvasive functional imaging methodology for RIF diagnosis and assessment in the context of clinical RT.
Keywords: optical coherence tomography; speckle variance optical coherence tomography; radiotherapy; radiation-induced fibrosis; microcirculation; cancer treatment

Potential environmental impact of nanoenergetics - Perreault, Nancy N. (European Chemical Bulletin, 2018)
Nanoenergetics has the potential to become the next generation of explosives and propellants. Nano-explosives often show better performances in terms of energy release, ignition and mechanical properties compared to their bulk counterparts. In addition to monomolecular explosives such as nano-TNT and nano-RDX, diverse energetic nanocomposites have been developed, including the nanometer-sized versions of conventional thermites (nanothermites) and those using carbon-based nanomaterials (e.g., fullerenes and carbon nanotubes). While the unique characteristics of nanomaterials allow groundbreaking applications, they also result in distinct environmental fate, transport and toxicity. The high surface to volume ratio and reactivity of nanomaterials make them highly dynamic in environmental systems. Once released in the environment, nanoenergetic chemicals will undergo transportation and transformation processes including dissolution, aggregation, adsorption, photolysis and biotransformation, which will also affect their persistence and bioavailability. This review was conducted to better understand the potential environmental fate and ecological impact of the use of nanoenergetics.
Keywords: nanomaterial; nanothermite; environmental fate; nanotoxicity

Performance of pre-1970s squat reinforced concrete shear walls - Cortés-Puentes, W. L.; Palermo, D. (Canadian Journal of Civil Engineering = Revue canadienne de génie civil, 2018)
The seismic performance of pre-1970s squat reinforced concrete shear walls is assessed with the capacity spectrum method to expose structural deficiencies that arise due to current estimates of seismic demands. The walls are 1/3 scale models of a prototype building, designed and detailed in accordance with the 1965 edition of the National Building Code of Canada (NBCC-1965) for four locations, two in high seismic zones in western Canada and two in moderate seismic zones in eastern Canada. Seismic demands for different drifts are evaluated against the spectral capacities of the walls to determine the performance. The seismic demands are based on uniform hazard spectra specified by the NBCC-2015. The calculated effective damping and the spectral capacity of the walls are determined from the force–displacement envelopes of the reverse cyclic responses of the shear walls. In addition, spectral capacities based on experimental and numerical results are used to study the effect of axial load and low-strength reinforcing steel on the performance of the shear walls.
Keywords: performance-based design; conception fondée sur la performance; seismic assessment; évaluation sismique; squat shear walls; mur de contreventement trapu (« squat shear wall »); reinforced concrete; béton armé; pre-1970s shear walls; murs de contreventement pré 1970

Perceptual assessment of environmental stability modulates postural sway - Cooper, Natalia; Cant, Iain; White, Mark D.; Meyer, Georg F.; Cropper, Simon J. (PLOS ONE, 2018)
We actively maintain postural equilibrium in everyday life, and, although we are unaware of the underlying processing, there is increasing evidence for cortical involvement in this postural control. Converging evidence shows that we make appropriate use of ‘postural anchors’, for example static objects in the environment, to stabilise our posture. Visually evoked postural responses (VEPR) that are caused when we counteract the illusory perception of self-motion in space (vection) are modulated in the presence of postural anchors and therefore provide a convenient behavioural measure. The aim of this study is to evaluate the factors influencing visual appraisal of the suitability of postural anchors. We are specifically interested in the effect of perceived ‘reality’ in VR the expected ‘stability’ of visual anchors. To explore the effect of ‘reality’ we introduced an accommodation-vergence conflict. We show that VEPR are appropriately modulated only when virtual visual ‘anchors’ are rendered such that vergence and accommodation cues are consistent. In a second experiment we directly test whether cognitive assessment of the likely stability of real perceptual anchors (we contrast a ‘teapot on a stand’ and a ‘helium balloon’) affects VEPR. We show that the perceived positional stability of environmental anchors modulate postural responses. Our results confirm previous findings showing that postural sway is modulated by the configuration of the environment and further show that an assessment of the stability and reality of the environment plays an important role in this process. On this basis we propose design guidelines for VR systems, in particular we argue that accommodation-vergence conflicts should be minimised and that high quality motion tracking and rendering are essential for high fidelity VR.

Oxford nanopore sequencing enables rapid discovery of single-domain antibodies from phage display libraries - Lowden, Michael J.; Henry, Kevin A. (BioTechniques, 2018)
Antibody (Ab) repertoire sequencing using high-throughput massively parallel technologies has contributed substantially to the understanding of Ab responses following infection, vaccination and autoimmunity. Because individual B-cell receptors are recombined and diversified somatically, genomic comparisons are limited, and distinguishing rare variants from sequencing errors is a major challenge. Oxford Nanopore Technologies’ MinION is a highly portable and cost-effective third-generation sequencing instrument, but has not been used for Ab repertoire sequencing due to its high error rate (approximately 1/10 bases). Here, we applied nanopore sequencing to single-domain Ab (sdAb) repertoires and phage-displayed sdAb libraries. We show that despite low overall data fidelity, sdAb sequences could be reconstructed above a frequency threshold (∼100 copies); however, distinguishing clonal sdAb variants was not always possible. The data quality was sufficient to enable rapid identification of antigen-specific sdAb sequences enriched during panning of phage display libraries, obviating the need for screening single clones.
Keywords: antibody; nanopore sequencing; next-generation DNA sequencing; phage display; single-domain antibody; VHH

Optimizing the electrical conductivity of screen printed silver conductive tracks by post treatment - Sun, Haixiang; Xiao, Gaozhi George; Lang, Stephen; Zhang, Zhiyi; Tao, Ye (2018 International Flexible Electronics Technology Conference (IFETC), 2018)
Screen printed silver conductive tracks have been used or are being explored for applications in membrane switches, solar cells, radio frequency identification (RFID) antennas, diabetic testing strips, sensors etc. For many of these applications, optimizing the electric conductivity of the printed tracks is crucial. It has been noticed that the electric conductivity of the printed conductive tracks are highly dependent on the post-processing conditions. However, the understanding of the effect is limited. In this paper, preliminary study results show that ambient temperature drying followed by heat treatment offers the lowest resistance (highest conductance) for printed conductive tracks.

OH 18 cm observations of the intermediate-velocity molecular cloud G211+63 - Smith, Allison J.; Magnani, Loris; Gonzalez, Louis; Robishaw, Timothy (Monthly Notices of the Royal Astronomical Society, 2018)
We detected OH 18 cm main line emission from 5 of 7 positions in the intermediate-velocity molecular cloud (IVMC) G211+63. These are the first detections of hydroxyl in IVMCs. Our OH detections at AV levels ranging from 0.24 to 0.27 mag reinforce the notion that these lines can efficiently trace diffuse, low-extinction molecular gas. N(OH) is derived for a range of excitation temperatures (5–30 K) and likely falls between 1 and 16 × 1013cm−2⁠. The corresponding N(H2) values are consistent both with estimates derived from E(B − V) and CO data. Estimates of the cloud mass from the OH data range from 26 to 820 M⊙ for distances from 100 to 400 pc and Tex from 5 to 10 K. These values are 3–20 times less than the virial mass of the cloud. It is likely IVMCs resemble high-latitude clouds in this respect. If so, they are transient structures breaking up on time-scales of ∼106yr⁠.
Keywords: ISM: clouds; ISM: molecules

Neutralization of Clostridium difficile toxin B with VHH-Fc fusions targeting the delivery and CROPs domains - Hussack, Greg; Ryan, Shannon; Van Faassen, Henk; Rossotti, Martin; Mackenzie, C. Roger; Tanha, Jamshid (PLOS ONE, 2018)
An increasing number of antibody-based therapies are being considered for controlling bacterial infections, including Clostridium difficile by targeting toxins A and B. In an effort to develop novel C. difficile immunotherapeutics, we previously isolated several single-domain antibodies (VHHs) capable of toxin A neutralization through recognition of the extreme C-terminal combined repetitive oligopeptides (CROPs) domain, but failed at identifying neutralizing VHHs that bound a similar region on toxin B. Here we report the isolation of a panel of 29 VHHs targeting at least seven unique epitopes on a toxin B immunogen composed of a portion of the central delivery domain and the entire CROPs domain. Despite monovalent affinities as high as KD = 70 pM, none of the VHHs tested were capable of toxin B neutralization; however, modest toxin B inhibition was observed with VHH-VHH dimers and to a much greater extent with VHH-Fc fusions, reaching the neutralizing potency of the recently approved anti-toxin B monoclonal antibody bezlotoxumab in in vitro assays. Epitope binning revealed that several VHH-Fcs bound toxin B at sites distinct from the region recognized by bezlotoxumab, while other VHH-Fcs partially competed with bezlotoxumab for toxin binding. Therefore, the VHHs described here are effective at toxin B neutralization when formatted as bivalent VHH-Fc fusions by targeting toxin B at regions both similar and distinct from the bezlotoxumab binding site.

Near-infrared pyramid wavefront sensor for Keck adaptive optics: opto-mechanical design - Wizinowich, Peter L.; Vandenberg, Adam; Taheri, Mojtaba; Wallace, James K.; Chun, Mark R.; Bond, Charlotte Z.; Jacobson, Shane M.; Lilley, Scott J.; Mawet, Dimitri; Delorme, Jacques-Robert; Jovanovic, Nemanja; Schmidt, Dirk; et al. (Adaptive Optics Systems VI, 2018)
A near-infrared, high order pyramid wavefront sensor will be implemented on the Keck telescope, with the aim of providing high resolution adaptive optics correction for the study of exoplanets around M-type stars and planet formation in obscured star forming regions. The pyramid wavefront sensor is designed to support adaptive optics correction of the light to an imaging vortex coronagraph and to a fiber injection unit that will feed a spectrograph. We present the opto-mechanical design of the near-infrared pyramid wavefront sensor, the optical performance, and the alignment strategy. The challenges of designing the assembly, as well as a fiber injection unit, to fit into the limited available space on the Keck adaptive optics bench, will also be discussed.
Keywords: AO; KPIC; near-infrared pyramid wavefront sensor

Multisite multivariate disaggregation of climate parameters using multiplicative random cascades - Gaur, Abhishek; Lacasse, Michael (Urban Climate, 2018)
The Multiplicative Random Cascade (MRC) disaggregation model has been extensively used to disaggregate precipitation in many regions across the globe. In this study, it is adapted to disaggregate a range of climate variables (CV) relevant for hygrothermal modelling of building envelopes. This generalized MRC-G model is further improved by explicitly modelling the cross-correlation structure between CVs in the MRC-G-CV model. A thorough evaluation of MRC, MRC-G, and MRC-G-CV models is performed for five Canadian cities: Ottawa, Vancouver, Calgary, St. Johns, and Winnipeg. Results indicate that the MRC model is able to simulate grid-level statistics with >90% accuracy. Grid-level extreme magnitudes and spatial cross-correlation structures are also well simulated. Error magnitudes associated with hourly predictions indicate superior performance of the models in respect to thermal variables, followed by wind variables, and then moisture related variables. Finally, the performance of MRC-G model towards modelling cross-correlation among CVs is found to improve by >50% in terms of energy distance by explicitly modelling these relationships in the MRC-G-CV model. Results indicate that the MRC model variants demonstrated in this study have the potential to facilitate effective hygrothermal performance evaluation of building envelopes at locations where observational sub-daily climate records are unavailable.
Keywords: disaggregation; precipitation; wind; temperature; multiple random cascade; hygrothermal simulations

MSE FiTS: the ultimate multi-fiber optic transmission system - Erickson, Darren; Crampton, David; Pawluczyk, Rafal; Fournier, Paul; Venn, Kim A.; Hall, Patrick; Bradley, Colin; Mcconnachie, Alan W.; Pazder, John; Jahandar, Farbod; Kielty, Collin; Monty, Stephanie; et al. (Ground-based and Airborne Instrumentation for Astronomy VII, 2018)
The Maunakea Spectroscopic Explorer (MSE) is a next-generation observatory, designed to provide highly multiplexed, multi-object spectroscopy over a wide field of view. The observatory will consist of (1) a telescope with an 11.25 m aperture, (2) a 1.5 square-degree science field of view, (3) fibre optic positioning and transmission systems, and (4) a suite of low (R=3000), moderate (R=6000) and high resolution (R=40,000) spectrographs. The Fibre Transmission System (FiTS) consists of 4332 optical fibres, designed to transmit the light from the telescope prime focus to the dedicated spectrographs. The ambitious science goals of MSE require the Fibre Transmission System to deliver performance well beyond the current state of the art for multi-fibre systems, e.g., the sensitivity to observe magnitude 24 objects (@ SNR=2) over a very broad wavelength range (0.37 – 1.8 μm) while achieving relative spectrophotometric accuracy of < 3% and radial velocity precision of 20 km/s (@ SNR=5). This paper details the design of the FiTS fibre system. It places FiTS into context with existing and planned spectroscopic facilities, such as Subaru/PFS, KPNO/DESI, ESO/4MOST and Gemini/GRACES. The results and lessons learned from GRACES are particularly applicable, since FiTS and GRACES share many team members, including industrial partner FiberTech Optica (Kitchener, ON). The FiTS system consists of 57 identical fibre cables. These cables have been designed to be modular, facilitating efficient construction and automated acceptance testing. Each cable consists of 76 fibres, including 57 fibres feeding light to the low and moderate resolution spectrographs and 19 fibres feeding the high-resolution spectrographs. Thus, the MSE/FiTS consists of 4332 fibres in total. Novel construction techniques utilizing continuous high-NA (f/2) fibres, pioneered by FiberTech Optica, are outlined and test results showing < 5% focal ratio degradation (FRD) in V-band are presented. The effect on FRD from varying the input f/# is also shown. Where test data is unavailable, system error budgets have been created to assess design choices on options such as fibre material, anti-reflection coatings, and fibre-optic connectors.
Keywords: wide-field; multi-object spectrograph; multiplex,; fibre optic cable; FRD; MSE

Monitor and control for the SKA1 CSP Mid.CBF utilizing the Stratix-10 FPGA equipped with HPS - Del Rizzo, David A.; Garstin, Mark A. B.; Guzman, Juan C.; Ibsen, Jorge (Software and Cyberinfrastructure for Astronomy V, 2018)
We present design considerations and a prototyping progress report for a low-level monitor and control communication system designed to operate on the Stratix-10 System on a Chip (SoC) Field Programmable Gate Array (FPGA) equipped with a Hard Processor System (HPS). The goal of this activity is to allow remote clients to use high level communication protocols (ie. TANGO) to access IP blocks within a Stratix-10 FPGA chip by taking advantage of very low latency communication between HPS and the FPGA fabric, eliminating the need to implement Ethernet protocols within the FPGA logic.
Keywords: SKA; CSP; Stratix; FPGA; HPS; kernel; TANGO; correlator

Metrology challenges for characterization of cellulose nanocrystals - Johnston, L. J. (International Conference on Nanotechnology for Renewable Materials 2018. Volume 2, 2018)
Keywords: X ray scattering; block copolymers; incidence small-angle

Modification of cellulose nanocrystals for compostable food packaging - Bosnick, K.; Benhalima, A.; Chapleau, N.; Champagne, M. (TechConnect Briefs 2018: Advanced Materials. Volume 1, 2018)
Polylactide (PLA) suffers from deficiencies compared with petroleum-derived materials that limit its immediate adoption as a food packaging material, which may be addressed through compounding with cellulose nanocrystals (CNC). In this work, compatibilized CNC particles are blended with PLA and cast into packaging films to assess their potential for improving food packaging related properties. As a control, the compatibilized CNC particles are also cast in polyethylene (PE). An acetylation reaction and surfactant modification are employed to compatibilize the CNC particles for melt processing with PE and PLA matrices. High quality films are produced with indications of improved mechanical and promising oxygen-barrier results. Further progress will require detailed microstrucrural characterization of the composites to understand the degree of dispersion and thermal degradation, as well as the effect on the host polymer crystallinity.
Keywords: barrier; cellulose; composite; nanocrystal; packaging

Modelling of future flood risk across Canada due to climate change - Gaur, Ayushi; Gaur, Abhishek; Simonovic, Slobodan P. (Risk Analysis XI, 2018)
Climate change has induced changes in key climate variables and hydrological cycles across Canada. With continuous emission of greenhouse gases, this trend is expected to continue over the 21st century and beyond. In this study, a macro-scaled hydrodynamic model is used to simulate 25 km resolution daily streamflow across Canada for historical (1961–2005) and future (2061–2100) timelines. Future projections from 21 General Climate Models (GCMs) following four Representative Concentration Pathways (RCPs) are used for analysis. Changes in the frequency and magnitude of historical 100-year and 250-year return period flood events and month of occurrence of peak flow are analyzed. Results obtained from uncertainty analysis for both return period flood events found that flood frequency will increase in most of northern Canada, southern Ontario, southern British Columbia, northern Alberta, Manitoba and Saskatchewan. However, northern British Columbia, northern Ontario, Manitoba and north-eastern Quebec will be facing a decrease in flood frequency. Aggregated results indicate early summertime extreme flows in the regions such as Alberta, Saskatchewan, Manitoba, Quebec, southern Ontario and some parts of Nunavut and Yukon territories, whereas the British Columbia region is mostly projected with increases in wintertime flooding. The projected flood hazard changes at 100 most populous Canadian cities and flow regulation infrastructure (FRI) are used to quantify future changes in flood risk. Results indicate that 40–60% of Canada’s 100 most populated cities including many prominent cities such as Toronto and Montreal are high at risk of increased riverine flooding under climate change. Among the 1,072 FRIs analyzed, 45–60% of them can be expected to experience increases in flood magnitudes in the future whereas 25–60% of them can be expected to experience changes in flood timing.
Keywords: climate change; Canada; flooding frequency; catchment based macroscale floodplain model; uncertainty

Microstructure and thermomechanical fatigue behavior of directionally solidified Ni-based superalloys in OP condition - Seo, Dongyi; Seo, Seong-moon; Yoo, Young-Soo; Kim, Daejin (ASME Turbo Expo 2018: Turbomachinery Technical Conference and Exposition. Volume 6: Ceramics; Controls, Diagnostics, and Instrumentation; Education; Manufacturing Materials and Metallurgy, 2018)
Two directionally solidified (DS) Ni-base superalloys, one with the GTD-111 composition and the other with a modified composition derived by numerical simulation, were produced using the Bridgman method. Solution and aging heat treatments were applied to the DS alloys to produce the desired microstructures. Thermomechanical fatigue (TMF) tests were conducted under fully reversed mechanical strain (R = −1) in the temperature range of 538–927°C in laboratory air. The tests were performed under the out-of-phase (OP) loading condition at the mechanical strain range of 0.8–1.5% with multiple specimens tested at each test condition to confirm the trend in fatigue lives. In general, the OP-TMF lives of the DS alloys depended on the applied mechanical strain range as well as the microstructural features of the alloys. By analyzing the fracture surface and longitudinal section of the tested specimens, the TMF lives of the DS alloys tested at mechanical strain ranges lower than 1.5% were found to be primarily affected by the coarse carbides formed in the interdendritic regions. In this study, the main damage mechanism of each alloy under the OP-TMF condition was elucidated in terms of its microstructural features, and recommendations were made to control the microstructures of the DS alloys to achieve enhanced TMF resistance.

Meta-omics survey of [NiFe]-hydrogenase genes fails to capture drastic variations in H2-oxidation activity measured in three soils exposed to H2 - Khdhiri, Mondher; Piché-Choquette, Sarah; Tremblay, Julien; Tringe, Susannah G.; Constant, Philippe (Soil Biology and Biochemistry, 2018)
Inferences on soil biogeochemical processes based on metagenomic profiles is a challenging task due to enormous diversity of soil microbes and the fragile linkage between gene abundance and functioning. Here we used the biological sink of H2 as a case study to test the hypothesis that [NiFe]-hydrogenase gene distribution and expression profiles explain variations in H2 oxidation rate measured in soil collected in poplar monoculture, larch plantation and farmland. Shotgun metagenomic and metatranscriptomic analyses of soil samples exposed to elevated or low H2 concentration led to the identification of 45 genes encoding the large subunit of [NiFe]-hydrogenases belonging to 8 distinct phyla. Our results indicate that despite significant sequencing effort, retrieved hydrogenase sequences are not in themselves adequate surrogates of H2 oxidation activity in these soils. In fact, land-use exerted a greater influence than H2 exposure on both hydrogenase gene distribution and expression though expression of certain genes responded to H2. We argue that approaches relying on PCR/RT-PCR amplicon sequencing or quantification combined with physicochemical parameters are currently the best option to infer the activity of H2-oxidizing bacteria and probably other specialist functional guilds with similar population size in soil.
Keywords: metagenomic; metatranscriptomics; biogeochemistry; microbial ecology; H2 oxidation activities

Meat spoilage sensing devices - Bosnick, K.; Tay, L.-L.; Bruce, J.; Smith, B.; Zhang, H.; Shwartz, C. (TechConnect briefs 2018: Advanced Materials. Vol. 3 Biotech, Biomaterials and Biomedical, 2018)
The safety, sustainability, and profitability of the food industry will remain a key societal challenge in the decades ahead. When meat begins to degrade, the protein decomposes and releases biogenic amines. Early detection of these volatile amines therefore provides a means to sense the onset of meat spoilage. In this work, Pd-decorated ZnO nanomaterials deposited on interdigitated electrode substrates are found to show an excellent chemiresistive response to methyl amine in air with concentrations as low as 25 ppm and with operating temperatures as low as 150 °C. These results suggest that a similar chemiresistive response to biogenic amines may be possible. Surface enhanced Raman scattering is shown to be an excellent tool for sensing biogenic amines, largely due to the chemical interactions between the amine group and the Au/Ag nanoparticles, as well as the effect of the diamine on the aggregation of the nanoparticles.
Keywords: amine; chemiresistor; food safety; sers; spoilage

Maunakea spectroscopic explorer advancing from conceptual design - Szeto, Kei; Murowinski, Richard; Mcconnachie, Alan; Hill, Alexis; Flagey, Nicolas; Mignot, Shan; Simons, Doug; Bauman, Steven; Gilmozzi, Roberto; Marshall, Heather K.; Spyromilio, Jason (Ground-based and Airborne Telescopes VII, 2018)
The Maunakea Spectroscopic Explorer (MSE) project has completed its Conceptual Design Phase. This paper is a status report of the MSE project regarding its technical and programmatic progress. The technical status includes its conceptual design and system performance, and highlights findings and recommendations from the System and various subsystems design reviews. The programmatic status includes the project organization and management plan for the Preliminary Design Phase. In addition, this paper provides the latest information related to the permitting process for Maunakea construction.
Keywords: observatories; telescopes; spectrographs; astronomy; spectroscopy; calibration; multiplexing

Maunakea spectroscopic explorer (MSE): implementing systems engineering methodology for the development of a new facility - Hill, Alexis; Mignot, Shan; Szeto, Kei; Flagey, Nicolas; Murowinski, Richard; McConnachie, Alan W.; Hervieu, Calum; Edgar, Mick; Gillingham, Peter; Angeli, George Z.; Dierickx, Philippe (Modeling, Systems Engineering, and Project Management for Astronomy VIII, 2018)
Maunakea Spectroscopic Explorer will be a 10-m class highly multiplexed survey telescope, including a segmented primary mirror and robotic fiber positioners at the prime focus. MSE will replace the Canada France Hawaii Telescope (CFHT) on the summit of Mauna Kea, Hawaii. The multiplexing includes an array of over four thousand fibers feeding banks of spectrographs several tens of meters away. We present an overview of the requirements flow-down for MSE, from Science Requirements Document to Observatory Requirements Document. We have developed the system performance budgets, along with updating the budget architecture of our evolving project. We have also identified the links between subsystems and system budgets (and subsequently science requirements) and included system budget that are unique to MSE as a fiber-fed facility. All of this has led to a set of Observatory Requirements that is fully consistent with the Science Requirements.
Keywords: requirement; system budget; SNR; noise; throughput; image quality; injection efficiency; observing efficiency

Machine learning-based sensor data modeling methods for power transformer PHM - Li, Anyi; Yang, Xiaohui; Dong, Huanyu; Xie, Zihao; Yang, Chunsheng (Sensors, 2018)
An emerging prognostic and health management (PHM) technology has recently attracted a great deal of attention from academies, industries, and governments. The need for higher equipment availability and lower maintenance cost is driving the development and integration of prognostic and health management systems. PHM models depend on the smart sensors and data generated from sensors. This paper proposed a machine learning-based methods for developing PHM models from sensor data to perform fault diagnostic for transformer systems in a smart grid. In particular, we apply the Cuckoo Search (CS) algorithm to optimize the Back-propagation (BP) neural network in order to build high performance fault diagnostics models. The models were developed using sensor data called dissolved gas data in oil of the power transformer. We validated the models using real sensor data collected from power transformers in China. The results demonstrate that the developed meta heuristic algorithm for optimizing the parameters of the neural network is effective and useful; and machine learning-based models significantly improved the performance and accuracy of fault diagnosis/detection for power transformer PHM.
Keywords: machine learning; effective cuckoo search; BP neural network; IEC-three ratio method; power transformer PHM; fault diagnosis

Low loss grating coupled optical interfaces for large volume fabrication with deep ultraviolet optical lithography - Alonso-Ramos, Carlos; Guerber, Sylvain; Pérez-Galacho, Diego; Vakarin, Vladyslav; Le Roux, Xavier; Marcaud, Guillaume; Cassan, Eric; Marris-Morini, Delphine; Cheben, Pavel; Boeuf, Frédéric; Baudot, Charles; Vivien, Laurent; et al. (Silicon Photonics: From Fundamental Research to Manufacturing, 2018)
Optical input/output interfaces between silicon-on-insulator (SOI) waveguides and optical fibers, allowing robust, costeffective and low-loss coupling of light, are fundamental functional elements in the library of silicon photonic devices. Surface grating couplers are particularly desirable as they allow wafer-scale device testing, yield improved alignment tolerances, and are compatible with state-of-the-art integration and packaging technologies. While several factors jointly contribute to the coupler performance, the grating directionality is a critical parameter for high-efficiency fiber-chip coupling. To address this issue, conventional coupler designs typically call upon comparatively complex architectures to improve light coupling efficiency. Increasing the intrinsic directionality of the grating by exploiting the blazing effects is another promising solution. In this paper, we report on our recent advances in development of low-loss grating couplers that afford excellent directionality, close to the theoretical limit of 100%. In particular, we demonstrate, by theory and experiments, several implementations of blazed grating couplers with layout features that are compatible with deepultraviolet (deep-UV) optical lithography. Devices can be advantageously implemented on various photonic platforms, including industry-specific and the offerings of publicly accessible foundries. The first experimental realizations of uniform deep-UV-compatible couplers yield losses of -2.7 dB at 1.55-µm and a 3-dB bandwidth of 62 nm. A subwavelength-index-engineered impedance matching transition is used to reduce back-reflections down to -20 dB.
Keywords: diffraction gratings; fiber couplers; silicon; optical design; deep ultraviolet; reflectivity; optical lithography; interfaces; waveguides; etching

Low-frequency vibration-assisted drilling of hybrid CFRP/Ti6Al4V stacked material - Hussein, R.; Sadek, A.; Elbestawi, M. A.; Attia, M. H. (The International Journal of Advanced Manufacturing Technology, 2018)
The drilling of carbon fiber-reinforced polymers (CFRP) and Ti6Al4V alloy stacked materials play a significant role in the aerospace industry’s ability to achieve improved machinability and assembly. Conventional drilling has resulted in various challenges such as CFRP delamination, unacceptable hole accuracy, and high tool wear. In addition, high cutting temperatures and poor chip evacuation mechanisms were also identified as important difficulties necessitating the drilling of each material separately. Low-frequency vibration-assisted drilling (LF-VAD) promises a high potential for overcoming these challenges. The primary objective of this study was to investigate the effect of machining parameters (cutting speed, feed rate, modulation amplitude, and modulation frequency) on the LF-VAD stacked drilling of CFRP/Ti6Al4V. The effect of applying a 2.5-cycle/rev frequency modulation to a wide range of machining parameters is reported, and the results are discussed. The variables considered included cutting speed, feed rate, and modulation amplitude. The results show up to a 56% reduction in cutting temperature, as well as a change in chip morphology. The effects on hole quality and surface roughness are also presented.
Keywords: vibration-assisted drilling; low-frequency vibration-assisted drilling; CFRP/Ti6Al4V; stacked material; advanced machining

Low-dimensional spaces for relating sensor signals with internal data structure in a propulsion system - Cheung, Catherine; Kilfoyle, Nicolle; Valdés, Julio; Sehgal, Srishti; Chavez, Richard Salas (Advances in Science, Technology and Engineering Systems Journal, 2018)
Advances in technology have enabled the installation of an increasing number of sensors in various mechanical systems allowing for more detailed equipment health monitoring capabilities. It is hoped the sensor data will enable development of predictive tools to prevent system failures. This work describes continued analysis of sensor data surrounding a seizure of a turbocharger within a propulsion system. The objective of the analysis was to characterize and distinguish healthy and failed states of the turbocharger. The analysis approach included mapping of multi-dimensional sensor data to a low-dimensional space using various linear and nonlinear techniques in order to highlight and visualize the underlying structure of the information. To provide some physical insight into the structure of the low-dimensional representation, the transformation plots were analyzed from the perspective of several engine signals. By overlaying operating ranges of individual sensor signals, certain regions of the mappings could be associated with distinct operational states of the engine, and several anomalies could be related to various points in the turbocharger seizure. Although the failed points did not map to an obvious outlier location in the transformations, incorporating expert domain knowledge with the data mining tools significantly enhanced the insight derived from the sensor data.
Keywords: condition indicators; failure prediction; intrinsic dimension; low-dimensional spaces

Local normal and tangential ice forces on the R. V. Polarstern - Frederking, R. (The Proceedings of the Twenty-eighth (2018) International Ocean and Polar Engineering Conference: Sapporo, Japan, June 10-15, 2018, 2018)
The forebody of the Research Vessel Polarstern was instrumented to measure normal and tangential ice forces on two 1-m 2 areas, one mid-bow and the other on the shoulder of the hull. Simultaneous time series records of the normal and tangential ice forces on both areas were used to examine the nature of ice friction on the hull. The friction coefficient varied inversely with the magnitude of the normal force and depended on whether the normal force was increasing or decreasing. The data allowed the more detailed examination of the apparent relation between normal and transvers forces. Friction coefficients averaged 0.5 for normal forces less than 100 kN, but deceased to values in the range 0.05 to 0.15 for normal forces greater than 500 kN.

Linking MRO to prognosis based health management through physics-of-failures understanding - Patnaik, Prakash; Wu, Xijia (ASME Turbo Expo 2018: Turbomachinery Technical Conference and Exposition. Volume 6: Ceramics; Controls, Diagnostics, and Instrumentation; Education; Manufacturing Materials and Metallurgy, 2018)
Traditional engine maintenance, repair and overhaul (MRO) are geared toward fixed schedules. However, with online condition monitoring, assessments and prognosis, it is required that MRO be adaptive to the life consumption with respect to the actual usage of the engine to realize the benefit of prognosis. Shifting to this new paradigm, there are several challenges: 1. How exactly the life is consumed in components under complex usage profiles that may involve a combination of low and high cycle fatigue, thermomechanical fatigue and creep, for regular usage (aside from incidents)? 2. What are the physical failure mechanism(s) in components under the above conditions, the understanding of which may help to select the most appropriate detection, repair and replacement (including material insertion) strategy, for life renewal/extension and cost reduction? 3. Understanding the limitations of repairs for the particular failure mechanism. To overcome these challenges, one needs physics-based material failure models that can reflect the true failure mechanisms on the component level under actual (complex) usage profiles. Conventional, empirical test-data correlations for isolated conditions fall short of this requirement because pure fatigue and pure creep are not experienced by real components in service. In addition, to ensure the repaired component’s structural integrity, the material database would have to be comprehensive enough to cover the effect of intrinsic repair defects and microstructures that are not present in the original component material. While models and data are integral parts of digital twins, it is proposed that physics-based models are needed to cover the entire application domain continuously. This paper will introduce a physics-based method of life consumption evaluation and discussion through past experience in line with the development of Digital Twin concepts for sustainment.

Linear and nonlinear stability of Soret-Dufour Lapwood convection near double codimension-2 points - Attia, Abbes; Mamou, Mahmoud; Benissaad, Smail; Ouazaa, Nabil (Heat Transfer-Asian Research, 2018)
In this study, the Dufour and Soret effects on natural double‐diffusion convection in a horizontal porous layer was studied numerically using FORTRAN 90 programming and analytically near various convection onset thresholds. The porous layer was subject to a uniform heat and mass fluxes on the horizontal walls while the vertical walls were impermeable and adiabatic. The Darcy model along with the Boussinesq approximation was assumed in the problem formulation. The governing parameters of the problem are the thermal Rayleigh number, RT, the buoyancy ratio, N, the Lewis number, Le, the aspect ratio of the cavity, A, and the Dufour, Du, and Soret, Sr, numbers. For a shallow enclosure, the analytical solution was derived assuming zero convection wave number, which is valid near and above criticality. The onset of subcritical, supercritical and oscillatory convection was investigated. Two linear and nonlinear codimension‐2 points were found to exist. Whether the system was subject to constant fluxes and heat and solute, regardless of the aspect ratio of the layer, the subcritical convection behavior remained the same with similarity in the thresholds expressions for subcritical bifurcation.
Keywords: double diffusion; Lapwood convection; linear codimension‐2 points; Soret and Dufour effects

Isolation and characterization of camelid single-domain antibodies against HER2 - Hussack, Greg; Raphael, Shalini; Lowden, Michael J.; Henry, Kevin A. (BMC Research Notes, 2018)
Objective: To isolate and characterize novel high-affinity llama single-domain antibodies against human HER2. Results: We immunized a llama with human HER2, constructed a phage-displayed VHH library from the lymphocytes of the animal, and isolated six unique HER2-specific VHHs by panning. All six VHHs were unique at the amino acid level and were clonally unrelated, as reflected by their distinct CDR3 lengths. All six VHHs recognized recombinant human HER2 ectodomain with monovalent affinities ranging from 1 to 51 nM, had comparable affinities for cynomolgus monkey HER2, and bound HER2+ SKOV3 cells by flow cytometry. Three of the VHHs recognized recombinant murine HER2 with no loss of affinity compared with human and cynomolgus monkey HER2. The VHHs recognized three major epitopes on HER2 (including one conserved across the human, simian and murine orthologues), all of which were distinct from that of trastuzumab. These VHHs may be useful in the design of modular cancer immunotherapeutics.
Keywords: single-domain antibody; VHH; HER2; cancer

Inspection of aircraft engine components using induction thermography - Genest, Marc; Li, Gang (2018 IEEE Canadian Conference on Electrical & Computer Engineering (CCECE), 2018)
Induction thermography technique is assessed experimentally on aircraft engine parts with fatigue cracks using a three-loop coil. Results show that induction thermography can detect cracks in engine parts, with inspection time of less than 1 s. Coating surface to increase the part emissivity improved the signal to noise ratio but was not necessary for the crack detection. Despite high local heat gradient resulting from the parts' edges, cracks were still detectable. This edge effect introduced more challenges to detect short cracks. Relatively, longer cracks were easier to detect. The optimal observation time, in the experiments, was between 0.1 s and 0.25 s. Inspection of the engine disc with complex geometry was feasible using the induction thermography technique. However, in this case only some of the cracks were detected. Similar findings were also obtained from the 3D multiphysics finite element modelling.
Keywords: induction thermography; engine components; nondestructive evaluation; multiphysics modelling

Insight into the chromophore of rhodopsin and its Meta-II photointermediate by 19F solid-state NMR and chemical shift tensor calculations - Brinkmann, Andreas; Sternberg, Ulrich; Bovee-Geurts, Petra H. M.; Fernández Fernández, Isabelle; Lugtenburg, Johan; Kentgens, Arno P. M.; Degrip, Willem J. (Physical Chemistry Chemical Physics, 2018)
19F nuclei are useful labels in solid-state NMR studies, since their chemical shift and tensor elements are very sensitive to the electrostatic and space-filling properties of their local environment. In this study we have exploited a fluorine substituent, strategically placed at the C-12-position of 11-cis retinal, the chromophore of visual rhodopsins. This label was used to explore the local environment of the chromophore in the ground state of bovine rhodopsin and its active photo-intermediate Meta II. In addition, the chemical shift and tensor elements of the chromophore in the free state in a membrane environment and the bound state in the protein were determined. Upon binding of the chromophore into rhodopsin and Meta II, the isotropic chemical shift changes in the opposite direction by +9.7 and −8.4 ppm, respectively. An unusually large isotropic shift difference of 35.9 ppm was observed between rhodopsin and Meta II. This partly originates in the light-triggered 11-cis to all-trans isomerization of the chromophore. The other part reflects the local conformational rearrangements in the chromophore and the binding pocket. These NMR data were correlated with the available X-ray structures of rhodopsin and Meta II using bond polarization theory. For this purpose hydrogen atoms have to be inserted and hereto a family of structures were derived that best correlated with the well-established 13C chemical shifts. Based upon these structures, a 12-F derivative was obtained that best corresponded with the experimentally determined 19F chemical shifts and tensor elements. The combined data indicate strong changes in the local environment of the C-12 position and a substantially different interaction pattern with the protein in Meta II as compared to rhodopsin.

Injector tip temperature and combustion performance of a natural gas-diesel dual fuel engine at medium and high load conditions - Guo, Hongsheng; Liko, Brian (ASME 2018 Internal Combustion Engine Division Fall Technical Conference. Volume 1: Large Bore Engines, Fuels, Advanced Combustion, 2018)
Diesel engines have been widely used due to the higher reliability and superior fuel conversion efficiency. However, they still generate significant amount of carbon dioxide (CO2) and particulate matter (PM) emissions. Natural gas is a low carbon and clean fuel that generates less CO2 and PM emissions than diesel during combustion. Replacing diesel by natural gas in internal combustion engines help reduce both CO2 and PM emissions. Natural gas – diesel dual fuel combustion is a practical and efficient way to replace diesel by natural gas in internal combustion engines. One concern for dual fuel combustion engines is the diesel injector tip temperature increase with increasing natural gas fraction. This paper reports an experimental investigation on the diesel injector tip temperature variation and combustion performance of a natural gas – diesel dual fuel engine at medium and high load conditions. The natural gas fraction was changed from zero to 90% in the experiment. The results suggest that the injector tip temperature increased with increasing natural gas fraction at a given diesel injection timing or with advancing the diesel injection timing at a given natural gas fraction. However, the injector tip temperature never exceeded 250 °C in the whole experimental range. The effect of natural gas fraction on combustion performance depended on engine load and diesel injection timing.
Keywords: temperature; combustion; fuels; engines; stress; ejectors; diesel

Infrared thermography for inspection of aramid and ultra-high-molecular-weight polyethylene armour systems - Genest, Marc; Ouellet, Simon; Williams, Kevin; De Vries, Jaap; Burleigh, Douglas (Thermosense: Thermal Infrared Applications XL, 2018)
Non-Destructive Evaluation (NDE) trials were performed on aramid and ultra-high molecular-weight polyethylene (UHMWPE) based armor systems. Pulsed thermography, continuous heating, and lock-in thermography were investigated for various types of damage. It is shown that the infrared thermography results vary significantly based on the material and thickness of the armor system, and only certain types of damage can be confidently identified. While the pulsed thermography performed in reflection mode was the fastest and provided the strongest indication signal for some types of damage, deeper damage on thicker armor system needed to be performed in transmission mode. Due to inherent material properties variations in these armor systems, the infrared images were affected by non-uniformity. In addition, due to low thermal conductivity, the inspections were sporadically affected by non-uniform heating. Approaches are presented to address the non-uniform heating issue affecting the inspection of those low thermal conductivity materials.
Keywords: thermography; inspection; nondestructive evaluation; infrared imaging

Influence of the Femtosecond Laser Induced Loss on the Type II Phase-Shifted FBG Passband - Grobnic, Dan; Hnatovsky, Cyril; Mihailov, Stephen J. (Advanced Photonics 2018 (BGPP, IPR, NP, NOMA, Sensors, Networks, SPPCom, SOF), 2018)
During the inscription of Type II Bragg gratings a certain amount of optical loss is induced in the fiber. For Type II phase-shifted gratings, this broadband loss imposes strong restrictions on the grating passband.

Individual pathways in the formation of magic-size clusters and conventional quantum dots - Zhang, Jing; Hao, Xiaoyu; Rowell, Nelson; Kreouzis, Theo; Han, Shuo; Fan, Hongsong; Zhang, Chunchun; Hu, Changwei; Zhang, Meng; Yu, Kui (The Journal of Physical Chemistry Letters, 2018)
The formation relationship between colloidal magic-size clusters (MSCs) and conventional quantum dots (QDs) has not been well established. Here, we report our systematic study on their formation pathways, using cadmium sulfide (CdS) as a model system. Two Cd precursors were prepared from CdO with branched 2-methyloctadecanoic acid (C16H33CH(CH3)–COOH) and linear oleic acid (C16H31CH2–COOH), reacting with elemental S powder in 1-octadecene (ODE). We show that the presence of MSC-311 (exhibiting a sharp absorption peaking at 311 nm) is regulated by the growth of conventional QDs. We demonstrate that MSC-311 cannot directly convert into conventional QDs but to its immediate precursor (IP-311), which is transparent in optical absorption (>310 nm). We propose that there are two individual pathways for the formation of MSCs and conventional QDs, linked by an intrinsic pathway from MSCs to IPs to fragments to QDs. The present study introduces new avenues to precisely control their formation.

In situ synchrotron X-ray diffraction analysis of phase transformation in epitaxial metastable hcp nickel thin films, prepared via plasma-enhanced atomic layer deposition - Motamedi, Pouyan; Bosnick, Ken; Cadien, Ken; Hogan, James D. (Advanced Materials Interfaces, 2018)
Ultrathin metal films have a wide variety of applications, especially in microelectronics. A key method to deposit these films is plasma‐enhanced atomic layer deposition (PEALD), which is known for its ability to deposit thin films conformally and at relatively low temperatures. Building on the recent work, an improved recipe is reported on for the development of nickel PEALD technology, through which fully epitaxial nickel thin films are deposited. The effect of continuous heating on the phase structure and agglomeration in the metastable thin films is investigated in this paper. The variations of the phase structure are monitored via in situ synchrotron X‐ray diffraction, as well as optical roughness analysis. The temperature windows for phase transformation and particle formation are determined. It is noted that, after the hcp‐to‐fcc transformation and particle coalescence processes are complete, the particles reshape to acquire the thermodynamically stable shapes dictated by the Wulff theorem. Additionally, a crystallographic orientation relationship between the fcc particles and the sapphire substrate is observed, i.e., Ni (111)||Sapphire(002).

Immunotoxicity and genotoxicity of single-walled carbon nanotubes co-exposed with cadmium in the freshwater mussel, Elliptio complanata - Revel, Messika; Fournier, Michel; Robidoux, Pierre Yves (Environmental Toxicology and Pharmacology, 2018)
Potential immunotoxicity and genotoxicity of as-produced and purified single walled carbon nanotubes (SWCNT, 500 μg Lˉ¹) with or without cadmium (20 μg Lˉ¹) was investigated in hemocytes of the freshwater mussel, Elliptio complanata. Our results showed a decrease in hemocyte viability after 3, and 8 days of exposure and an increase of hemocyte phagocytic efficiency for organisms exposed to Cd. No modification of the cyclo-oxygenase (COX) activity was measured. An increase in DNA damage was measured after 1 day of exposure to Cd and a potentiating effect of combined exposures was observed.
Keywords: DNA damage; SWCNT; interaction; cadmium; mussels

Immunological functions and evolutionary emergence of heavy-chain antibodies - Brooks, Cory L.; Rossotti, Martin A.; Henry, Kevin A. (Trends in Immunology, 2018)
Homodimeric antibodies devoid of light chains have evolved multiple times through convergent evolution, yet their specific immunological functions remain poorly understood. We survey the molecular and structural features of these antibodies, their immunological functions in host defense, and reflect on the long-standing question of the evolutionary forces driving their emergence.
Keywords: heavy chain-only antibody; single-domain antibody; VHHVNAR; comparative immunology; evolutionary immunology

Identification and structure elucidation of janthitrems A and D from Penicillium janthinellum and determination of the tremorgenic and anti-insect activity of janthitrems A and B - Babu, Jacob V.; Popay, Alison J.; Miles, Christopher O.; Wilkins, Alistair L.; Di Menna, Margaret E.; Finch, Sarah C. (Journal of Agricultural and Food Chemistry, 2018)
New compounds, 11,12-epoxyjanthitrem B (1) and 11,12-epoxyjanthitrem C (4), were isolated from Penicillium janthinellum and given the trivial names janthitrem A and janthitrem D, respectively. The known compounds janthitrem B (2) and janthitrem C (3) were also isolated, and NMR assignments were made for all four compounds. This showed that the previously published NMR assignments for 3 needed considerable revision. 1 and 2 were used as model compounds for the more complex, and highly unstable, epoxyjanthitrems that have been isolated from perennial ryegrass infected with the AR37 endophyte and which contain an epoxide group analogous to that of 1. Both 1 and 2 induced tremors in mice and reduced weight gain and food consumption of porina (Wiseana cervinata) larvae, although 1 showed greater potency. This shows the importance of the epoxy group and suggests that epoxyjanthitrems are likely to be involved in the observed effects of the AR37 endophyte on livestock and insects.
Keywords: AR37; endophyte; epoxyjanthitrem; janthitrem; Penicillium janthinellum; porina; tremorgen

IC 4499 revised: spectro-photometric evidence of small light-element variations - Dalessandro, E.; Lardo, C.; Cadelano, M.; Saracino, S.; Bastian, N.; Mucciarelli, A.; Salaris, M.; Stetson, P.; Pancino, E. (Astronomy & Astrophysics, 2018)
It has been suggested that IC 4499 is one of the very few old globulars to not host multiple populations with light-element variations. To follow-up on this very interesting result, here we have made use of accurate HST photometry and FLAMES at VLT high-resolution spectroscopy to investigate in more detail the stellar population properties of this system. We find that the red giant branch of the cluster is clearly bimodal in near-UV-optical colour-magnitude diagrams, thus suggesting that IC 4499 is actually composed by two sub-populations of stars with different nitrogen abundances. This represents the first detection of multiple populations in IC 4499. Consistently, we also find that one star out of six is Na-rich to some extent, while we do not detect any evidence of intrinsic spread in both Mg and O. The number ratio between stars with normal and enriched nitrogen is in good agreement with the number ratio – mass trend observed in Galactic globular clusters. Also, as typically found in other systems, nitrogen rich stars are more centrally concentrated than normal stars, although this result cannot be considered conclusive because of the limited field of view covered by our observations (∼1rh). On the contrary, we observe that both the RGB UV colour spread, which is a proxy of N variations, and Na abundance variations, are significantly smaller than those observed in Milky Way globular clusters with mass and metallicity comparable to IC 4499. The modest N and Na spreads observed in this system can be tentatively connected to the fact that IC 4499 likely formed in a disrupted dwarf galaxy orbiting the Milky Way, as previously proposed based on its orbit.
Keywords: globular clusters: general; globular clusters: individual: IC 4499; Hertzsprung-Russell and C-M diagrams; techniques: photometric; stars: abundances; techniques: spectroscopic

Hybrid graphene ribbon/carbon electrodes for high‐performance energy storage - Farquhar, Anna K.; Supur, Mustafa; Smith, Scott R.; Dyck, Colin; Mccreery, Richard L. (Advanced Energy Materials, 2018)
The utility of supercapacitors for both fixed and portable energy storage would be greatly enhanced if their energy density could be increased while maintaining their high power density, fast charging time, and low cost. This study describes a simple, solution‐phase, scalable modification of carbon materials by a covalently bonded “brush” of hydrogen‐terminated graphene ribbons (GRs) with layer thicknesses of 2–20 nm, resulting in a 20–100 times increase in the areal capacitance of the unmodified electrode surface. On a flat sp2 carbon surface modified by GRs, the capacitance exceeds 1200 µF cm−2 in 0.1 m H2SO4 due to a distinct type of pseudocapacitance during constant current charge/discharge cycling. Modification of high surface area carbon black electrodes with GRs yields capacitances of 950–1890 F g−1, power densities >40 W g−1, and minimal change in capacitance during 1500 charge/discharge cycles at 20 A g−1. A capacitance of 1890 F g−1 affords an energy density of 318 Wh kg−1 operating at 1.1 V and 590 Wh kg−1 at 1.5 V. The projected energy density of a hybrid GR/carbon supercapacitor greatly exceeds the current 10 Wh kg−1 for commercial supercapacitors and approaches that of lithium ion batteries.
Keywords: carbon black; diazonium reduction; graphene ribbon; renewable energy; supercapacitors

How to optimize materials and devices via design of experiments and machine learning: demonstration using organic photovoltaics - Cao, Bing; Adutwum, Lawrence A.; Oliynyk, Anton O.; Luber, Erik J.; Olsen, Brian C.; Mar, Arthur; Buriak, Jillian M. (ACS Nano, 2018)
Most discoveries in materials science have been made empirically, typically through one-variable-at-a-time (Edisonian) experimentation. The characteristics of materials-based systems are, however, neither simple nor uncorrelated. In a device such as an organic photovoltaic, for example, the level of complexity is high due to the sheer number of components and processing conditions, and thus, changing one variable can have multiple unforeseen effects due to their interconnectivity. Design of Experiments (DoE) is ideally suited for such multivariable analyses: by planning one’s experiments as per the principles of DoE, one can test and optimize several variables simultaneously, thus accelerating the process of discovery and optimization while saving time and precious laboratory resources. When combined with machine learning, the consideration of one’s data in this manner provides a different perspective for optimization and discovery, akin to climbing out of a narrow valley of serial (one-variable-at-a-time) experimentation, to a mountain ridge with a 360° view in all directions.

High-yield production of human Dicer by transfection of human HEK293-EBNA1 cells grown in suspension - Bouvette, Jonathan; Korkut, Dursun nizam; Fouillen, Aurélien; Amellah, Soumiya; Nanci, Antonio; Durocher, Yves; Omichinski, James G.; Legault, Pascale (BMC Biotechnology, 2018)
Background: Dicer is a 219-kDa protein that plays key roles in gene regulation, particularly as the ribonuclease III enzyme responsible for cleaving precursor miRNA substrates. Its enzymatic activity is highly regulated by protein factors, and this regulation can impact on the levels of miRNAs and modulate the behavior of a cell. To better understand the underlying mechanisms of regulation, detailed enzymatic and structural characterization of Dicer are needed. However, these types of studies generally require several milligrams of recombinant protein, and efficient preparation of such quantities of pure human Dicer remains a challenge. To prepare large quantities of human Dicer, we have optimized transfection in HEK293-6E cells grown in suspension and streamlined a purification procedure. Results: Transfection conditions were first optimized to achieve expression levels between 10 and 18 mg of recombinant Dicer per liter of culture. A three-step purification protocol was then developed that yields 4–9 mg of purified Dicer per liter of culture in a single day. From SEC-MALS/RI analysis and negative stain TEM, we confirmed that the purified protein is monomerically pure ( ≥ 98%) and folds with the characteristic L-shape geometry. Using an electrophoretic mobility shift assay, a dissociation constant (Kd) of 5 nM was measured for Dicer binding to pre-let-7a-1, in agreement with previous reports. However, when probing the cleavage activity of Dicer for pre-let-7a-1, we measured kcat (7.2 ± 0.5 min− 1) and KM (1.2 ± 0.3 μM) values that are much higher than previously reported due to experimental conditions that better respect the steady-state assumption. Conclusions: The expression and purification protocols described here provide high yields of monomerically pure and active human Dicer. Cleavage studies of a pre-let-7 substrate with this purified Dicer reveal higher kcat and KM values than previously reported and support the current view that conformational changes are associated with substrate binding. Large quantities of highly pure Dicer will be valuable for future biochemical, biophysical and structural investigations of this key protein of the miRNA pathway.
Keywords: human HEK293-EBNA1 cells; mammalian cell suspension culture; dicer expression; dicer purification; pre-miRNA; pre-let-7; dicer binding; dicer cleavage assay

High-speed and high-resolution interrogation of a strain and temperature random grating sensor - Deng, Hong; Lu, Ping; Mihailov, Stephen J.; Yao, Jianping (Journal of Lightwave Technology, 2018)
High-speed and high-resolution interrogation of a random fiber grating sensor based on spectral shaping and wavelength-to-time (SS-WTT) mapping, and pulse compression for simultaneous measurement of strain and temperature is proposed and demonstrated. In the proposed system, an ultrashort pulse is spectrum shaped by a high-birefringence (Hi-Bi) random grating (HBRG) to generate two orthogonally polarized spectra with a wavelength difference determined by the birefringence of the HBRG, which are then fed to a dispersive optical loop in which a linearly chirped fiber Bragg grating (LCFBG) is incorporated, to perform linear WTT mapping, to generate two temporally separated optical pulses, which are converted to two random electrical waveforms at a photodetector). Random pulse compression is then performed to increase the interrogation resolution. By measuring the time shifts of the temporally compressed pulses, the strain and temperature information is retrieved. An experiment is performed. The experimental results show that the proposed random grating sensor and its interrogation system can provide a strain and temperature resolution of 7.1 με and 0.79 °C at an ultrahigh speed of 20 MHz.
Keywords: fiber Bragg grating; interrogation; sensor; linearly chirped fiber Bragg grating

High-accuracy roundness measurements at NRC - Aldous, C.; Leroux, I. D.; Eves, B. J. (Measurement Science and Technology, 2018)
An uncertainty budget for measuring the roundness of high-quality parts using the reversal method has been developed. A systematic source of uncertainty due to the non-linear nature of the and operators has been experimentally verified and a simple method to remove the bias developed. The dominant source of uncertainty for the measurement of high-quality parts is the difficulty of realizing the correct measurand when the form of the part varies along the rotation axis. Example uncertainty budgets for both a steel ring and a glass hemisphere are presented. The expanded uncertainty (k  =  2) for the out-of-roundness of the hemisphere is 4.0 nm.

High temperature characterization and material model calibration for hot stamping of AA7075 aluminium sheet - Amours, G. D.; Ilinich, A. (IOP Conference Series: Materials Science and Engineering, 2018)
This paper presents an overview of the elevated temperature characterization of AA7075 aluminium sheet and calibration of a custom material model implemented in LS-DYNA. The plasticity characterization was performed by isothermal tensile testing while formability characterization was performed via isothermal Nakazima testing in a wide range of temperatures and strain rates. A special heat treatment path representative of the hot stamping was developed and applied in both series of tests. The material model included Hill'48 yield with a non-associated flow rule and phenomenological damage model similar to GISSMO but extended to cover non-isothermal conditions.

Mechanisms of the immune response cause by cationic and anionic surface functionalized cellulose nanocrystals using cell-based assays - Despres, Hannah W.; Sabra, Adham; Anderson, Phil; Hemraz, Usha D.; Boluk, Yaman; Sunasee, Rajesh; Ckless, Karina (Toxicology in Vitro, 2018)
The interest in functionalized cellulose nanocrystals (CNCs) for multiple biomedical application has been increasing in recent years. CNCs are suitable to functionalization with an array of polymers, generating chemically related nanomaterials with different morphologies, surface charges that can affect bioreactivity, including immune response. In this study, we sought to understand the mechanistic differences regarding immunological responses evoked by functionalized CNCs and whether surface charges play a role in this effect. We investigated the effect of a cationic, CNCs-poly(APMA), and an anionic, CNCs-poly(NIPAAm) derivatives on the secretion of inflammatory cytokines, mitochondria-derived ROS and mitochondrial function and antioxidant response as well as on endoplasmic reticulum (ER) stress, in human and murine inflammatory cells. The cationic CNCs-poly(APMA) evoked a more robust immunological response in murine cell line, while the anionic CNCs-poly(NIPAAm) showed a significant NLRP3 inflammasome-dependent and independent immunological response in human monocytes. Moreover, CNCs-poly(NIPAAm) induced greater formation of acidic vesicular organelles, mitochondrial ROS in non-stimulated cells while CNCs-poly(APMA) mainly affected mitochondrial function by decreasing the intracellular ATP. The differences on the biological responses may be related to the surface charges of CNCs, and their likely interactions with intra and extracellular biomolecules.
Keywords: cellulose nanocrystals; surface charge; nanomaterials; immunogenicity; reactive oxygen species; NLRP3 inflammasome

A lavender ABC transporter confers resistance to monoterpene toxicity in yeast - Demissie, Zerihun A.; Tarnowycz, Mike; Adal, Ayelign M.; Sarker, Lukman S.; Mahmoud, Soheil S. (Planta, 2018)
The interest in functionalized cellulose nanocrystals (CNCs) for multiple biomedical application has been increasing in recent years. CNCs are suitable to functionalization with an array of polymers, generating chemically related nanomaterials with different morphologies, surface charges that can affect bioreactivity, including immune response. In this study, we sought to understand the mechanistic differences regarding immunological responses evoked by functionalized CNCs and whether surface charges play a role in this effect. We investigated the effect of a cationic, CNCs-poly(APMA), and an anionic, CNCs-poly(NIPAAm) derivatives on the secretion of inflammatory cytokines, mitochondria-derived ROS and mitochondrial function and antioxidant response as well as on endoplasmic reticulum (ER) stress, in human and murine inflammatory cells. The cationic CNCs-poly(APMA) evoked a more robust immunological response in murine cell line, while the anionic CNCs-poly(NIPAAm) showed a significant NLRP3 inflammasome-dependent and independent immunological response in human monocytes. Moreover, CNCs-poly(NIPAAm) induced greater formation of acidic vesicular organelles, mitochondrial ROS in non-stimulated cells while CNCs-poly(APMA) mainly affected mitochondrial function by decreasing the intracellular ATP. The differences on the biological responses may be related to the surface charges of CNCs, and their likely interactions with intra and extracellular biomolecules.
Keywords: Cellulose nanocrystals; surface charge; Nanomaterials; immunogenicity; reactive oxygen species; NLRP3 inflammasome

MeioCapture: an efficient method for staging and isolation of meiocytes in the prophase I sub-stages of meiosis in wheat - Shunmugam, Arun S. K.; Bollina, Venkatesh; Dukowic-Schulze, Stefanie; Bhowmik, Pankaj K.; Ambrose, Chris; Higgins, James D.; Pozniak, Curtis; Sharpe, Andrew G.; Rozwadowski, Kevin; Kagale, Sateesh (BMC Plant Biology, 2018)
Background: Molecular analysis of meiosis has been hindered by difficulties in isolating high purity subpopulations of sporogenous cells representing the succeeding stages of meiosis. Isolation of purified male meiocytes from defined meiotic stages is crucial in discovering meiosis specific genes and associated regulatory networks. Results: We describe an optimized method termed MeioCapture for simultaneous isolation of uncontaminated male meiocytes from wheat (Triticum spp.), specifically from the pre-meiotic G2 and the five sub-stages of meiotic prophase I. The MeioCapture protocol builds on the traditional anther squash technique and the capillary collection method, and involves extrusion of intact sporogenous archesporial columns (SACs) containing meiocytes. This improved method exploits the natural meiotic synchrony between anthers of the same floret, the correlation between the length of anthers and meiotic stage, and the occurrence of meiocytes in intact SACs largely free of somatic cells. The main advantage of MeioCapture, compared to previous methods, is that it allows simultaneous collection of meiocytes from different sub-stages of prophase I at a very high level of purity, through correlation of stages with anther sizes. A detailed description is provided for all steps, including the collection of tissue, isolation and size sorting of anthers, extrusion of intact SACs, and staging of meiocytes. Precautions for individual steps throughout the procedure are also provided to facilitate efficient isolation of pure meiocytes. The proof-of-concept was successfully established in wheat, and a light microscopic atlas of meiosis, encompassing all stages from pre-meiosis to telophase II, was developed. Conclusion: The MeioCapture method provides an essential technique to study the molecular basis of chromosome pairing and exchange of genetic information in wheat, leading to strategies for manipulating meiotic recombination frequencies. The method also provides a foundation for similar studies in other crop species.
Erratum published in volume 19, article 178, May 2, 2019. DOI: 10.1186/s12870-019-1780-4
Keywords: meiosis; meiocytes; sporogenous archesporial column; wheat; cytogenetics; meiotic prophase; functional genomics

Genetic diversity and population structure of synthetic hexaploid-derived wheat (Triticum aestivum L.) accessions - Gordon, Emily; Kaviani, Mina; Kagale, Sateesh; Payne, Thomas; Navabi, Alireza (Genetic Resources and Crop Evolution, 2018)
A comprehensive understanding of the population structure and genetic diversity of potential germplasm is necessary for making breeding decisions and to fully interpret marker-trait associations. The purpose of this study was to examine the genetic diversity and population structure of a panel of 194 synthetic hexaploid-derived wheat (SHW; Triticum aestivum L.) accessions using 6904 polymorphic single nucleotide polymorphism (SNP) markers. Ancestry-based dissimilarity indices and marker-based genetic distances were positively correlated (r = 0.67). The variation in the primary synthetic parent in the pedigrees accounted for 4.52%, while the degree of the synthetic contribution accounted for only 1.06% of variation in the genetic distance. In addition, variation in the Aegilops tauschii Coss. (syn. Aegilops squarrosa auct. non L.) accession and T. turgidum accession used in the initial cross accounted for 3.48% and 2.75% of the variation in genetic distance, respectively. Using a model-based population structure approach, seven sub-populations were identified in the panel. Results of the model-based population structure analysis was for the most part in agreement with the distance-based clustering using unweighted pair group method with arithmetic mean (UPGMA) of the genetic distance or ancestry data and the principle component analysis of relatedness. We conclude that using a model-based approach provides a more statistically robust estimation of population structure. Results of this study, while highlighting the potential contribution of introgressed genome in the panel, provide the foundation for employing this panel in genome-wide association studies.
Keywords: synthetic hexaploid derived wheat; genetic diversity; population structure; Triticum and Aegilops tauschii

Headspace in-tube microextraction and GC-ICP-MS determination of mercury species in petroleum hydrocarbons - Gajdosechova, Zuzana; Pagliano, Enea; Zborowski, Andre; Mester, Zoltan (Energy & Fuels, 2018)
Characterization of mercury contamination in petroleum hydrocarbons (PHs) is necessary in order to assess the risk of corrosion of the processing infrastructure and to assess the level of human exposure to Hg-containing substances. Here we present an accurate and sensitive method for determination of Hg species in PHs by headspace sampling with a possibility of on-line pre-concentration using in-tube extraction (ITEX) combined with gas chromatography–inductively coupled plasma mass spectrometry (GC-ICP-MS) analysis. Mercury species were first extracted from the PHs matrix into an aqueous phase via dithizone chelation and subsequently converted with sodium tetrapropyl borate into volatile derivatives which could be sampled from the headspace prior to GC-ICP-MS analysis. For concentrations in the ng kg–1 range, the on-line ITEX method was applied, whereas the μg kg–1 range was accessible by static headspace. Quantitation of Hg species was carried out by a double isotope dilution method, with quantitative recoveries of methylmercury (MeHg, average 101 ± 5%) and inorganic mercury (InHg, average 97 ± 7%) by direct headspace injection. Average recoveries of Hg spikes after on-line ITEX pre-concentration were 95 ± 3% for MeHg and 98 ± 8% for InHg. The detection limits for MeHg and InHg were 428 and 46 ng kg–1 when measured by static headspace, and 2.4 ng kg–1 and 1.7 ng kg–1 by on-line ITEX pre-concentration. The accuracy of the pre-concentration method was demonstrated by analysis of a crude oil standard reference material (NIST 2722) certified for InHg.

Gut bacterial microbiota and its resistome rapidly recover to basal state levels after short-term amoxicillin-clavulanic acid treatment in healthy adults - Macpherson, Chad W.; Mathieu, Olivier; Tremblay, Julien; Champagne, Julie; Nantel, André; Girard, Stéphanie-Anne; Tompkins, Thomas A. (Scientific Reports, 2018)
Clinical effects of antimicrobials and probiotics in combination have been reported, however, little is known about their impact on gut microbiota and its resistome. In this study 16S rRNA gene amplicon, shotgun metagenomics sequencing and antibiotic resistance (ABR) microarray were used on fecal samples of 70 healthy participants, taken at four time points in probiotic (Lactobacillus rhamnosus R0011 and Lactobacillus helveticus R0052) and placebo groups to profile the gut bacterial microbiota and its resistome following administration of amoxicillin-clavulanic acid for one week. Significant shifts in microbiota family composition caused by the antimicrobial in both groups that included decreases in the proportion of Lachnospiraceae, Coriobacteriaceae and unidentified Clostridiales; and notable increases for the proportion of Enterobacteriaceae, Bacteroidaceae and Porphyromonadaceae compared to baseline levels. Resistome showed a corresponding enrichment of ABR genes compared to baseline from such classes as aminoglycosides and beta-lactams that were linked, by in silico inference, to the enrichment of the family Enterobacteriaceae. Despite perturbations caused by short-term antibiotic treatment, both gut microbiota and resistome showed prompt recovery to baseline levels one week after cessation of the antimicrobial. This rapid recovery may be explained by the hypothesis of community resilience.

Gramillin A and B: cyclic lipopeptides identified as the nonribosomal biosynthetic products of Fusarium graminearum - Bahadoor, Adilah; Brauer, Elizabeth K.; Bosnich, Whynn; Schneiderman, Danielle; Johnston, Anne; Aubin, Yves; Blackwell, Barbara; Melanson, Jeremy E.; Harris, Linda J. (Journal of the American Chemical Society, 2018)
The virulence and broad host range of Fusarium graminearum is associated with its ability to secrete an arsenal of phytotoxic secondary metabolites, including the regulated mycotoxins belonging to the deoxynivalenol family. The TRI genes responsible for the biosynthesis of deoxynivalenol and related compounds are usually expressed during fungal infection. However, the F. graminearum genome harbors an array of unexplored biosynthetic gene clusters that are also co-induced with the TRI genes, including the nonribosomal peptide synthetase 8 (NRPS8) gene cluster. Here, we identify two bicyclic lipopeptides, gramillin A (1) and B (2), as the biosynthetic end products of NRPS8. Structural elucidation by high-resolution LC-MS and NMR, including 1H-15N-13C HNCO and HNCA on isotopically enriched compounds, revealed that the gramillins possess a fused bicyclic structure with ring closure of the main peptide macrocycle occurring via an anhydride bond. Through targeted gene disruption, we characterized the GRA1 biosynthetic gene and its transcription factor GRA2 in the NRPS8 gene cluster. Further, we show that the gramillins are produced in planta on maize silks, promoting fungal virulence on maize but have no discernible effect on wheat head infection. Leaf infiltration of the gramillins induces cell death in maize, but not in wheat. Our results show that F. graminearum deploys the gramillins as a virulence agent in maize, but not in wheat, thus displaying host-specific adaptation.

Graphene: epoxy composites for anti-corrosion coatings - Bosnick, K.; Benhalima, A.; Chapleau, N.; Tefashe, U. M.; Bergren, A. J.; Yang, Q.; Champagne, M. (TechConnect Briefs 2018: Advanced Materials. Volume 1, 2018)
The use of epoxy (EP) coatings for the protection of steel infrastructure from corrosion is a dominant technology in modern industrial settings. Improvement of this technology by compounding with graphene materials is explored. Composite coatings are produced on steel substrates using graphite nanoplatelets (GNP), more exfoliated graphene materials (MEG), and graphene oxide (GO). The anti-corrosion (AC) performance of the coatings is evaluated by salt-fog corrosion (SFC) testing and electrochemical (EC) methods. GO is found to be an excellent candidate as an AC barrier filler in EP coatings by both SFC and EC testing, clearly outperforming the neat EP. MEG also shows potential as an AC filler by the SFC tests, but performed poorly in the EC tests, possibly due to processing issues at the concentration investigated. GNP is found to show relatively less benefit as an AC filler in EP, compared with the more exfoliated GO and MEG fillers.
Keywords: anti-corrosion; coating; composite; epoxy; graphene

Galvanic corrosion risk assessment of bolt materials in contact with ASTM A1010 steel bridges - Ebrahimi, N.; Zhang, J.; Baldock, B.; Lai, D. (Corrosion Conference and Expo 2018, 2018)
This study has evaluated the galvanic coupling corrosion risk between connection bolt materials with ASTM A1010 structural steel, which has recently emerged for the construction of more corrosion-resistant bridges than weathering steel bridges. Use of A1010 steels containing 10.5% Cr is intended to extend the service life of steel bridges without frequent maintenance requirements caused by corrosion, particularly in regions under severe chloride exposures such as due to heavy use of de-icing salts and in marine environments. The greater corrosion resistance of A1010 steel with a more positive corrosion potential does, however, impose a risk of galvanic corrosion with the connection bolts in direct electrical contact. Here, the galvanic corrosion between A1010 steel and galvanized ASTM A325 Type I bolt was compared to that between weathering steel and galvanized ASTM A325 Type I bolt, as well as that between A1010 steel and ASTM A320 B8 class 2 and A193 B6 stainless steel bolts. A comprehensive experimental investigation measured galvanic coupling current and potential for samples in cells of aerated salt solution, and the galvanic corrosion risk ranking was validated by visual examinations of bolted steel plates exposed to a salt spray testing chamber. The galvanic corrosion risk of using B8 class 2 bolts with A1010 steel was found to be much lower than using galvanized A325 bolts, but B6 bolt material itself experienced severe crevice and pitting corrosion in both simulated salt solution and salt spray testing.
Keywords: A325 galvanized bolts; ASTM A1010 steel; bridge; galvanic coupling corrosion; stainless steel bolts

Future changes in flood hazards across Canada under a changing Climate - Gaur, Ayushi; Gaur, Abhishek; Simonovic, Slobodan (Water, 2018)
Climate change has induced considerable changes in the dynamics of key hydro-climatic variables across Canada, including floods. In this study, runoff projections made by 21 General Climate Models (GCMs) under four Representative Concentration Pathways (RCPs) are used to generate 25 km resolution streamflow estimates across Canada for historical (1961–2005) and future (2061–2100) time-periods. These estimates are used to calculate future projected changes in flood magnitudes and timings across Canada. Results obtained indicate that flood frequencies in the northernmost regions of Canada, and south-western Ontario can be expected to increase in the future. As an example, the historical 100-year return period events in these regions are expected to become 10–60 year return period events. On the other hand, northern prairies and north-central Ontario can be expected to experience decreases in flooding frequencies in future. The historical 100-year return period flood events in these regions are expected to become 160–200 year return period events in future. Furthermore, prairies, parts of Quebec, Ontario, Nunavut, and Yukon territories can be expected to experience earlier snowmelt-driven floods in the future. The results from this study will help decision-makers to effectively manage and design municipal and civil infrastructure in Canada under a changing climate.
Keywords: climate change; flooding frequency; catchment based macroscale floodplain model; uncertainty

Fully printed parallel plate capacitance humidity sensors - Chen, Mickey; Zhang, Zhiyi; Ding, Heping; Lang, Stephen; Tao, Ye; Chu, Ta-Ya; Xiao, Gaozhi; Graddage, Neil; Ton, Kevin (2018 International Flexible Electronics Technology Conference (IFETC), 2018)
Printed humidity sensors on flexible substrates has potential to be low cost platform. A novel capacitance-humidity sensor was screen printed with silver electrodes and cellulose acetate butyrate (CAB) as the dielectric on flexible polyethylene terephthalate (PET) substrate. The parallel plate design achieves capacitance between 400-500pF at ambient conditions. This study found that the sensor exhibits superior linearity from 10-70%RH with R2 of 0.9975, and acceptable linearity between 10-85% with R2 of 0.9779 with <10s response times.
Keywords: humidity sensor; capacitance; printed electronics; parallel plate

Freshwater fish habitat complexity mapping using above and underwater structure-from-motion photogrammetry - Kalacska, Margaret; Lucanus, Oliver; Sousa, Leandro; Vieira, Thiago; Arroyo-Mora, Juan (Remote Sensing, 2018)
Substrate complexity is strongly related to biodiversity in aquatic habitats. We illustrate a novel framework, based on Structure-from-Motion photogrammetry (SfM) and Multi-View Stereo (MVS) photogrammetry, to quantify habitat complexity in freshwater ecosystems from Unmanned Aerial Vehicle (UAV) and underwater photography. We analysed sites in the Xingu river basin, Brazil, to reconstruct the 3D structure of the substrate and identify and map habitat classes important for maintaining fish assemblage biodiversity. From the digital models we calculated habitat complexity metrics including rugosity, slope and 3D fractal dimension. The UAV based SfM-MVS products were generated at a ground sampling distance (GSD) of 1.20–2.38 cm while the underwater photography produced a GSD of 1 mm. Our results show how these products provide spatially explicit complexity metrics, which are more comprehensive than conventional arbitrary cross sections. Shallow neural network classification of SfM-MVS products of substrate exposed in the dry season resulted in high accuracies across classes. UAV and underwater SfM-MVS is robust for quantifying freshwater habitat classes and complexity and should be chosen whenever possible over conventional methods (e.g., chain-and-tape) because of the repeatability, scalability and multi-dimensional nature of the products. The SfM-MVS products can be used to identify high priority freshwater sectors for conservation, species occurrences and diversity studies to provide a broader indication for overall fish species diversity and provide repeatability for monitoring change over time.
Keywords: Brazil; fractal dimension; neural network; river; rugosity; UAV; underwater; Xingu river

Fluorescence‐based real time monitoring and diagnostics of recombinant Pichia pastoris cultivations in a bioreactor - Karakach, Tobias K.; Dachon, Aurore; Choi, Jerome; Miguez, Carlos; Masson, Luke; Tartakovsky, Boris (Biotechnology Progress, 2018)
This study describes the application of the multivariate curve resolution (MCR) analysis technique for real‐time analysis of culture fluorescence during recombinant Pichia pastoris cultivation in a bioreactor. Fluorescence spectra were acquired with an on‐line dual excitation wavelength fluorometer and then used to develop a real time MCR‐based bioprocess monitoring and diagnostics tool. Initial bioreactor experiments using two similar recombinant antibody secreting P. pastoris cell lines showed significant differences in protein production. To distinguish between the contributions of operating conditions and the specific cell line's genetic composition to the observed differences in protein production, the bioreactor experiments were repeated and accompanied by real time MCR analysis. The tests demonstrated high sensitivity of MCR‐derived “pure concentration” profiles to growth as well as to initial conditions, thus enabling real‐time cultivation process trend diagnostics and fault detection.
Keywords: multivariate curve resolution; fluorescence; on‐line diagnostics; monitoring; bioreactor

Flocculation performance of anionic starch in oil sand tailings - Zhao, Nana; Al Bitar, Hani; Zhu, Yunyin; Xu, Yuming; Shi, Zhiqing (Water Science and Technology, 2018)
A series of carboxymethyl starches (CMSs), with various degrees of substitution from 0.1 to 0.79, were synthesized and selected as a model to study the feasibility of using natural polymers as flocculants for oil sand tailings treatment. The flocculation performance of modified CMS in kaolin clay suspensions and oil sand tailings was evaluated in terms of settling rate, solids content, capillary suction time, and specific resistance to filtration of the sediment phase. It was found that the synthesized CMS effectively accelerates settling of kaolin suspensions and oil sand fine tailings, thus demonstrating the feasibility of this application.
Keywords: carboxymethyl starch; dewatering; flocculants; oil sand tailings; settling rate

Exponential family restricted boltzmann machines and annealed importance sampling - Li, Yifeng; Zhu, Xiaodan (2018 International Joint Conference on Neural Networks (IJCNN), 2018)
In this paper, we investigate restricted Boltzmann machines (RBMs) from the exponential family perspective, en-abling the visible units to follow any suitable distributions from the exponential family. We derive a unified view to compute the free energy function for exponential family RBMs (exp-RBMs). Based on that, annealed important sampling (AIS) is generalized to the entire exponential family, allowing for estimating the log-partition function and log-likelihood. Our experiments on a document processing task demonstrate that the generalized free energy functions and AIS estimation perform well in helping capture useful knowledge from the data; the estimated log-partition functions are stable. The appropriate instances of exp-RBMs can generate novel and meaningful samples and can be applied to classification tasks.
Keywords: deep learning; generative model; exponential family; restricted Boltzmann machine; annealed importance sampling

Experimental and theoretical investigation of a multimode cooling scheme using multiple electromagnetically-induced-transparency resonances - Scharnhorst, Nils; Cerrillo, Javier; Kramer, Johannes; Leroux, Ian D.; Wübbena, Jannes B.; Retzker, Alex; Schmidt, Piet O. (Physical Review A, 2018)
We introduce and demonstrate double-bright electromagnetically-induced-transparency (D-EIT) cooling as an extension to EIT cooling. By involving an additional ground state, two bright states can be shifted individually into resonance for cooling of motional modes of frequencies that may be separated by more than the width of a single EIT cooling resonance. This allows three-dimensional ground-state cooling of a 40Ca+ ion trapped in a linear Paul trap with a single cooling pulse. Measured cooling rates and steady-state mean motional quantum numbers for this D-EIT cooling are compared with those of standard EIT cooling as well as concatenated standard EIT cooling pulses for multimode cooling. Experimental results are compared to full-density matrix calculations. We observe a failure of the theoretical description within the Lamb-Dicke regime that can be overcome by a time-dependent rate theory. Limitations of the different cooling techniques and possible extensions to multi-ion crystals are discussed.

Evaluation of a high-resolution numerical weather prediction model's simulated clouds using observations from CloudSat, GOES-13 and in situ aircraft - Qu, Zhipeng; Barker, Howard W.; Korolev, Alexei V.; Milbrandt, Jason A.; Heckman, Ivan; Bélair, Stéphane; Leroyer, Sylvie; Vaillancourt, Paul A.; Wolde, Mengistu; Schwarzenböck, Alfons; Leroy, Delphine; Strapp, J. Walter; et al. (Quarterly Journal of the Royal Meteorological Society, 2018)
This study aimed to assess tropical cloud properties predicted by Environment and Climate Change Canada's Global Environmental Multiscale (GEM) model when run with the Milbrandt–Yau double‐moment cloud microphysical scheme and one‐way nesting that culminated at a (∼300 km)2 inner domain with 0.25 km horizontal grid spacing. The assessment utilized satellite and in situ data collected during the High Ice Water Content (HIWC) and High Altitude Ice Crystals (HAIC) projects for a mesoscale convective system on 16 May 2015 over French Guiana. Data from CloudSat's cloud‐profiling radar and GOES‐13's imager were compared to data either simulated directly by GEM or produced by operating on GEM's cloud data with both the CFMIP (Cloud Feedback Model Intercomparison Project) Observation Simulator Package (COSP) instrument simulator and a three‐dimensional Monte Carlo solar radiative transfer model. In situ observations were made from research aircraft – Canada's National Research Council Convair‐580 and the French SAFIRE Falcon‐20 – whose flight paths were aligned with CloudSat's ground‐track. Spatial and temporal shifts of clouds simulated by GEM compared well to GOES‐13 imagery. There are, however, differences between simulated and observed amounts of high and low cloud. While GEM did well at predicting ranges of ice‐water content (IWC) near 11 km altitude (Falcon‐20), it produces too much graupel and snow near 7 km (Convair‐580). This produced large differences between CloudSat's and COSP‐generated radar reflectivities and two‐way attenuations. On the other hand, CloudSat's inferred values of IWC agree well with in situ samples at both altitudes. Generally, GEM's visible reflectances exceeded GOES‐13's on account of having produced too much low‐level liquid cloud. It is expected that GEM's disproportioning of cloud hydrometeors will improve once it includes a better representation of secondary ice production.
Keywords: clouds; field campaigns; mesoscale; microphysics; numerical methods and NWP; remote sensing; severe weather; Tropics

Engineered nanomaterials and human health: Part 2. Applications and nanotoxicology (IUPAC Technical Report) - Gubala, Vladimir; Johnston, Linda J.; Krug, Harald F.; Moore, Colin J.; Ober, Christopher K.; Schwenk, Michael; Vert, Michel (Pure and Applied Chemistry, 2018)
Research on engineered nanomaterials (ENM) has progressed rapidly from the very early stages of studying their unique, size-dependent physicochemical properties and commercial exploration to the development of products that influence our everyday lives. We have previously reviewed various methods for synthesis, surface functionalization, and analytical characterization of ENM in a publication titled ‘Engineered Nanomaterials: Preparation, Functionalization and Characterization’. In this second, inter-linked document, we first provide an overview of important applications of ENM in products relevant to human healthcare and consumer goods, such as food, textiles, and cosmetics. We then highlight the challenges for the design and development of new ENM for bio-applications, particularly in the rapidly developing nanomedicine sector. The second part of this document is dedicated to nanotoxicology studies of ENM in consumer products. We describe the various biological targets where toxicity may occur, summarize the four nanotoxicology principles, and discuss the need for careful consideration of the biodistribution, degradation, and elimination routes of nanosized materials before they can be safely used. Finally, we review expert opinions on the risk, regulation, and ethical aspects of using engineered nanomaterials in applications that may have direct or indirect impact on human health or our environment.
Keywords: anomaterial; nanomedicine; nanoparticle; nano-products; nano-toxicology; regulation

Engineered nanomaterials and human health: Part 1. Preparation, functionalization and characterization (IUPAC Technical Report) - Gubala, Vladimir; Johnston, Linda J.; Liu, Ziwei; Krug, Harald; Moore, Colin J.; Ober, Christopher K.; Schwenk, Michael; Vert, Michel (Pure and Applied Chemistry, 2018)
Nanotechnology is a rapidly evolving field, as evidenced by the large number of publications on the synthesis, characterization, and biological/environmental effects of new nano-sized materials. The unique, size-dependent properties of nanomaterials have been exploited in a diverse range of applications and in many examples of nano-enabled consumer products. In this account we focus on Engineered Nanomaterials (ENM), a class of deliberately designed and constructed nano-sized materials. Due to the large volume of publications, we separated the preparation and characterisation of ENM from applications and toxicity into two interconnected documents. Part 1 summarizes nanomaterial terminology and provides an overview of the best practices for their preparation, surface functionalization, and analytical characterization. Part 2 (this issue, Pure Appl. Chem. 2018; 90(8): 1325–1356) focuses on ENM that are used in products that are expected to come in close contact with consumers. It reviews nanomaterials used in therapeutics, diagnostics, and consumer goods and summarizes current nanotoxicology challenges and the current state of nanomaterial regulation, providing insight on the growing public debate on whether the environmental and social costs of nanotechnology outweigh its potential benefits.
Keywords: nanomaterial; nanoparticle; nanoscale; nano-toxicology

Emerging technologies for delivery of biotherapeutics and gene therapy across the blood–brain barrier - Stanimirovic, Danica B.; Sandhu, Jagdeep K.; Costain, Will J. (BioDrugs, 2018)
Antibody, immuno- and gene therapies developed for neurological indications face a delivery challenge posed by various anatomical and physiological barriers within the central nervous system (CNS); most notably, the blood–brain barrier (BBB). Emerging delivery technologies for biotherapeutics have focused on trans-cellular pathways across the BBB utilizing receptor-mediated transcytosis (RMT). ‘Traditionally’ targeted RMT receptors, transferrin receptor (TfR) and insulin receptor (IR), are ubiquitously expressed and pose numerous translational challenges during development, including species differences and safety risks. Recent advances in antibody engineering technologies and discoveries of RMT targets and BBB-crossing antibodies that are more BBB-selective have combined to create a new preclinical pipeline of BBB-crossing biotherapeutics with improved efficacy and safety. Novel BBB-selective RMT targets and carrier antibodies have exposed additional opportunities for re-targeting gene delivery vectors or nanocarriers for more efficient brain delivery. Emergence and refinement of core technologies of genetic engineering and editing as well as biomanufacturing of viral vectors and cell-derived products have de-risked the path to the development of systemic gene therapy approaches for the CNS. In particular, brain-tropic viral vectors and extracellular vesicles have recently expanded the repertoire of brain delivery strategies for biotherapeutics. Whereas protein biotherapeutics and bispecific antibodies enabled for BBB transcytosis are rapidly heading towards clinical trials, systemic gene therapy approaches for CNS will likely remain in research phase for the foreseeable future. The promise and limitations of these emerging cross-BBB delivery technologies are further discussed in this article.

Effect of venting range hood flow rate on size-resolved ultrafine particle concentrations from gas stove cooking - Sun, Liu; Wallace, Lance A.; Dobbin, Nina A.; You, Hongyu; Kulka, Ryan; Shin, Tim; St-Jean, Melissa; Aubin, Daniel; Singer, Brett C. (Aerosol Science and Technology, 2018)
Cooking is the main source of ultrafine particles (UFP) in homes. This study investigated the effect of venting range hood flow rate on size-resolved UFP concentrations from gas stove cooking. The same cooking protocol was conducted 60 times using three venting range hoods operated at six flow rates in twin research houses. Size-resolved particle (10–420 nm) concentrations were monitored using a NanoScan scanning mobility particle sizer (SMPS) from 15 min before cooking to 3 h after the cooking had stopped. Cooking increased the background total UFP number concentrations to 1.3 × 103 particles/cm3 on average, with a mean exposure-relevant source strength of 1.8 × 1012 particles/min. Total particle peak reductions ranged from 25% at the lowest fan flow rate of 36 L/s to 98% at the highest rate of 146 L/s. During the operation of a venting range hood, particle removal by deposition was less significant compared to the increasing air exchange rate driven by exhaust ventilation. Exposure to total particles due to cooking varied from 0.9 to 5.8 × 104 particles/cm3·h, 3 h after cooking ended. Compared to the 36 L/s range hood, higher flow rates of 120 and 146 L/s reduced the first-hour post-cooking exposure by 76% and 85%, respectively.

Effect of the heating rate on the stability of the three-phase interstellar medium - Hill, Alex S.; Mac Low, Mordecai-Mark; Gatto, Andrea; Ibáñez-Mejía, Juan C. (The Astrophysical Journal, 2018)
We investigate the impact of the far-UV (FUV) heating rate on the stability of the three-phase interstellar medium using three-dimensional simulations of a 1 kpc^2, vertically extended domain. The FUV heating rate sets the range of thermal pressures across which the cold (~10^2 K) and warm (~10^4 K) neutral media (CNM and WNM) can coexist in equilibrium. Even absent a variable star formation rate regulating the FUV heating rate, the gas physics keeps the pressure in the two-phase regime: because radiative heating and cooling processes happen on shorter timescales than sound wave propagation, turbulent compressions tend to keep the interstellar medium within the CNM–WNM pressure regime over a wide range of heating rates. The thermal pressure is set primarily by the heating rate with little influence from the hydrostatics. The vertical velocity dispersion adjusts as needed to provide hydrostatic support given the thermal pressure: when the turbulent pressure {p}δ^2z is calculated over scales ≳500pc, the thermal plus turbulent pressure approximately equals the weight of the gas. The warm gas volume filling fraction is $0.2<fw<0.8 over a factor of less than three in heating rate, with fw near unity at higher heating rates and near zero at lower heating rates. We suggest that cosmological simulations that do not resolve the CNM should maintain an interstellar thermal pressure within the two-phase regime.

Effect of swirl ratio on NG/diesel dual-fuel combustion at low to high engine load conditions - Yousefi, Amin; Guo, Hongsheng; Birouk, Madjid (Applied Energy, 2018)
Recent regulation on pollutant and greenhouse gas (GHG) emissions has exerted great pressure on diesel engine industries which generate significant amount of GHG and pollutants. The concept of lean burn pilot ignited natural gas/diesel dual-fuel (NDDF) combustion is considered as one of the most suitable engine platforms to meet emissions and fuel economy regulations over a short to medium term. However, a major challenge is the slightly lower fuel efficiency and high level of methane (CH4) and carbon monoxide (CO) emissions, especially under low to medium engine load conditions. This paper numerically investigates the influence of swirl ratio on the combustion performance and emissions of a NDDF engine under low to high load conditions. The results at low load-low speed condition and retarded injection timing of 14 crank angle degrees before top dead center (BTDC) suggest that increasing swirl ratio from 0.5 to 1.5 significantly improves fuel efficiency and CH4 and CO emissions. However, under the same engine load-speed condition but at advanced injection timing of 30 crank angle degrees BTDC, increasing swirl ratio deteriorates the fuel efficiency and CH4 and CO emissions. Under a medium load-high speed condition, swirl ratio significantly improves diffusion combustion and turbulent flame propagation of natural gas. The results show that OH radical propagates more rapidly in the azimuthal direction when increasing the swirl ratio from 0.5 to 1.5. Further increase in the swirl ratio causes the peak pressure to exceed the limit (160 bar). At high load-low speed condition, increasing the swirl ratio significantly improves diesel diffusion and flame propagation of natural gas, which consequently enhances fuel efficiency. Under this engine load-speed condition, OH radical distribution shows that the combustion progresses rapidly within each jet in both the azimuthal and radial directions. Considering fuel efficiency and emissions, a swirl ratio of 1.5 is found to be the optimum. Overall, it is concluded that swirl motion may provide better mixture preparation, diesel diffusion, and natural gas flame propagation. However, this benefit may not persist under very high swirl ratio (swirl ratio > 1.5) due to higher heat losses.
Keywords: dual-fuel combustion; diesel engine; NG/diesel; swirl ratio; emissions

Effect of small molecule additives in the prenucleation stage of semiconductor CdSe quantum dots - Liu, Yuanyuan; Willis, Maureen; Rowell, Nelson; Luo, Wenzhi; Fan, Hongsong; Han, Shuo; Yu, Kui (The Journal of Physical Chemistry Letters, 2018)
For the addition of small molecules in the prenucleation stage of colloidal CdSe conventional quantum dots (QDs), there is insufficient knowledge regarding what are advantageous circumstances. Here, we present a study about such addition. When CH3COOH or Zn(OOCCH3)2 is added in the prenucleation stage (at 120 °C) of a reaction consisting of cadmium myristate (Cd(OOC(CH2)12CH3)2, Cd(MA)2 made from CdO) and Se powder in 1-octadecene (ODE), CdSe magic-size clusters (MSCs) exhibiting a single sharp absorption doublet at 433/460 nm are synthesized in a single-ensemble form (around 220 °C). We demonstrate that such small molecule addition suppresses the nucleation and growth of QDs and thus directs a competitive process to the formation of MSCs. The present study provides insight into the individual but linked pathways to forming CdSe QDs and MSCs and introduces new avenues to improve the production of MSCs through the addition of small molecules in the prenucleation stage.

Effect of prior creep strain on high cycle fatigue life of Ti 834 - Wu, Xijia; Seo, Dongyi; Head, Marc; Chan, Stephen (ASME Turbo Expo 2018: Turbomachinery Technical Conference and Exposition. Volume 6: Ceramics; Controls, Diagnostics, and Instrumentation; Education; Manufacturing Materials and Metallurgy, 2018)
Room-temperature fatigue tests were conducted on Ti 834 with prior creep strains accumulated under constant load at 550°C and 600°C, respectively. Microstructural and fractographic examinations on specimens with prior creep strain > 3% revealed the failure process consisting of multiple surface crack nucleation and internal void generation by creep, followed by fatigue crack propagation in coalescence with the internally distributed damage, leading to the final fracture. The amount of prior creep damage increased with creep strain. The fatigue life of Ti 834 was significantly reduced by prior creep straining. The behavior is rationalized with the integrated creep-fatigue theory.
Keywords: creep; high cycle fatigue

Dynamic mechanical characterization of boron nitride nanotube-epoxy nanocomposites - Rahmat, Meysam; Naftel, Alex; Ashrafi, Behnam; Jakubinek, Michael B.; Martinez-Rubi, Yadienka; Simard, Benoit (Polymer Composites, 2018)
Quasi‐static and dynamic performances of an epoxy adhesive with and without Boron nitride nanotubes (BNNTs) are studied here. This article investigates the thin film shear and bulk tensile properties of EPON 828/Epikure 3223. In addition to the neat epoxy material, specimens with 1 and 2 wt% concentrations of BNNTs were also tested. Double‐lap shear tests were performed at strain rates ranging from 4.0 × 10−4 to 3.7 × 103 s−1 and it was found that neither the incorporation of BNNTs nor increasing the strain rate had a substantial effect on the shear properties of the thin adhesive layer. However, bulk tensile properties were seen to be sensitive to changes in strain rate. An increase in the strain rate from 5.5 × 10−4 to 1.2 × 102 s−1 increased the tensile strength and Young's modulus by 39 and 113%, respectively; while the failure strain decreased by 49%. Additionally, the BNNT‐modified tensile specimens demonstrated up to 7% increase in tensile strength, up to a 16% increase in modulus, and a 9% decrease in the strain at failure. These results along with electron micrographs showed that due to pull‐out and bridging mechanisms of the nano‐reinforcements, the BNNTs are more effective in normal stress dominant applications, as opposed to shear stress.

Development of an optimization tool for calibrating crack growth material models - Bombardier, Yan (Materials Performance and Characterization, 2018)
Crack growth models are typically calibrated using experimental data prior to conducting damage tolerance analyses of aircraft structures. This process can be trivial for crack growth models that only have a few fitting parameters. However, other models, such as the FASTRAN crack growth equation with the analytical crack-closure model, include several model parameters that make calibration challenging. To simplify the calibration process and improve the accuracy of crack growth simulations, an automated crack growth model optimization tool was developed. This tool also aims at improving the robustness of crack growth models by reducing their dependency on loading spectra and specimen geometries. To achieve this, numerical optimization is used to minimize the discrepancy between experimental data and analytical crack growth. To demonstrate this approach, material model parameters were calibrated for P-3/CP-140 aircraft applications using the FASTRAN crack growth equation with the analytical crack-closure model. The optimization tool was found to be very effective at fitting crack growth simulation results to experimental data by changing the values of selected parameters. It was, however, observed that the automated calibration process could find multiple sets of FASTRAN parameter values that provide equivalent correlations with experimental data. In an attempt to develop a more robust material model, multiple test configurations with different geometries and loading spectra were used to determine an optimal trade-off model that maximizes the correlation for multiple test configurations. The conducted tests demonstrated that this approach is viable and could be used to improve the robustness of crack growth simulations.

Quantification and stability determination of surface amine groups on silica nanoparticles using solution NMR - Kunc, Filip; Balhara, Vinod; Brinkmann, Andreas; Sun, Ying; Leek, Donald M.; Johnston, Linda J. (Analytical Chemistry, 2018)
Surface chemistry is a critical factor for determining the behavior of a nanomaterial after incorporation in composites, devices, and biomedical products, and is also important for nanotoxicology studies. We have developed an optimized protocol for dissolution of aminated silicas and determination of functional-group contents by quantitative ¹H NMR (qNMR) analysis of the released amines. A number of variables were optimized for the dissolution protocol, including the base concentration, mass of silica, time, temperature, and method of sample agitation, in order to achieve adequate NMR signals for quantification. The protocol was tested using nanoparticles from a single commercial supplier with sizes ranging from 20 to 120 nm that were functionalized with 3-aminopropyl groups. Interestingly the batch-to-batch variability for some sizes of these aminated silicas was as high as 50%. Amine contents measured by a ninhydrin colorimetric assay were typically ∼20% lower than those measured by qNMR, consistent with measurement of only ninhydrin-reagent accessible amines. The dissolution–qNMR protocol was compatible with aminated silicas from other commercial suppliers, and in these cases, an even larger variability in surface coverage was observed. Silica nanoparticles with longer-chain amines and variable amine loadings were synthesized to demonstrate the ability to quantify amines with more complex structures and to assess the limit of quantification for the dissolution–qNMR method. Finally, the stability of the aminated nanoparticles was examined. Loss of 3-aminopropyl groups occurred in water at room temperature and was significantly more rapid at higher temperatures. Amine loss increased with increasing surface coverage and was slower for long-chain amines, consistent with studies of amine stability on planar silica. Overall, this work highlights the importance of developing methods for quantifying surface functionalization, particularly given the variability in surface coverage for commercial samples, and for ensuring that the amine group is stable under its usage conditions.

Development of a material model for AA7075 aluminium hot stamping - D’amours, G.; Ilinich, A. (Journal of Physics: Conference Series, 2018)
This paper presents the development and validation of a material model for finite element analysis of aluminium hot stamping. It is based on Hill'48 yield function with a non-associated flow rule and isotropic, temperature and rate sensitive hardening. The model also includes phenomenological damage treatment which was developed for plastic instability and fracture prediction in non-isothermal conditions. A special attention was given to the calibration of thermal conductance. Validation was performed with a series of cross die hot stamping tests with in-situ temperature measurements.

Energy performance based anomaly detection in non-residential buildings using symbolic aggregate approximation - Ashouri, Araz; Hu, Yitian; Newsham, Guy R.; Shen, Weiming (2018 IEEE 14th International Conference on Automation Science and Engineering (CASE), 2018)
Building system faults in commercial and office buildings can result in a reduced occupant comfort and increased utility bills. Energy performance-based anomaly detection helps operators efficiently identify faults. In this work, a data-driven method for anomaly detection is presented. Using a symbolic aggregate method, the weekly energy demand profiles are statistically quantised and labeled to determine normal and abnormal building behaviours. A case study with three federal office buildings has been conducted to demonstrate the proposed method. The resulting technology provides building operators with easily-interpreted and actionable information for optimised building performance.
Keywords: fault detection and diagnosis; building energy management; energy auditing; data analysis; electricity demand

Developing the ngDVA 15m composite reflector concept - Lacy, Gordon E.; Islam, Mohammad N.; Gilmozzi, Roberto; Marshall, Heather K.; Spyromilio, Jason (Ground-based and Airborne Telescopes VII, 2018)
The Next Generation Very Large Array (ngVLA) project to replace the VLA telescope in New Mexico is just beginning. As a part of the initial Community Studies phase, we have contributed the concept design of a 15m feed-low wheel and track design. This telescope, the Next Generation Dish Verification Antenna 15m (ngDVA-15) follows on from the DVA-1 and DVA-2 antennas developed at the Dominion Radio Astrophysical Observatory (DRAO) between 2012 and the present day. This paper will concentrate on the design and optimization process for the ngDVA-15 back-up structure. Topology and free-size optimization were used to develop the initial design concepts. Both methods helped to steer the back-up structure in the initial design phase, but ultimately engineering intuition also played a role. Topology optimization can lead directly to useful solutions in some cases but hardware and software limitations still limit the physical size of the model. Also, topological routines cannot yet correctly model truss-type networks with no moment transfer at the joints, and optimizing structures with only gravitational loads proved to be challenging for the current generation of optimization routines. Size optimization was also used once the design was sufficiently refined. The initial stage of design involved minimization of reflector surface deflections under gravitational loads only. FEA modelling of surface deflections together with in-house developed fitting algorithms were used to determine primary surface accuracy. Surface accuracies of better than 80 microns RMS were achieved which met the initial design goal for telescope operation at 120GHz.
Keywords: reflectors; composites; carbon; telescopes; metals; finite element methods; chemical elements

Determination of the isotopic composition of osmium using MC-ICPMS - Zhu, Zuhao; Meija, Juris; Tong, Shuoyun; Zheng, Airong; Zhou, Lian; Yang, Lu (Analytical Chemistry, 2018)
Despite its widespread applications in geology, all osmium isotope ratio measurements are either uncalibrated or rely on the veracity of the uncalibrated 1937 Nier values by adopting them as normalizing constants typically in conjunction with an exponential mass bias correction model. In this study, isotope ratios of osmium were determined in six commercial osmium materials, including the DROsS standard and a new NRC isotopic osmium reference material OSIS-1, by MC-ICPMS. We use a previously optimized and validated regression mass bias correction model to correct instrumental isotope fractionation effects which does not rely either on Nier’s values or on a strictly mass-dependent behavior of the isotopes. Deviations from mass-dependent fractionation (mass independent fractionation) were observed for osmium isotopes in MC-ICPMS with the most dramatic effect occurring for 187Os, wherein, on average, close to half-percent bias in the isotope ratio 187Os/188Os was observed as a result of imposing Russell’s law.

Determination of sulfur and sulfate half-ester content in cellulose nanocrystals: an interlaboratory comparison - Johnston, Linda J.; Jakubek, Zygmunt J.; Beck, Stephanie; Araki, Jun; Cranston, Emily D.; Danumah, Christophe; Fox, Douglas; Li, Haifeng; Wang, Jun; Mester, Zoltan; Moores, Audrey; Murphy, Karen; et al. (Metrologia, 2018)
Charged functional groups on the surface of cellulose nanocrystals (CNCs) are important for controlling the colloidal stability of suspensions and the interaction of the material with its environment. Quantification of surface groups is therefore an important metric for reproducible production of this nanomaterial. Here we report the results of an interlaboratory comparison (ILC) with twelve participants piloted by National Research Council Canada (NRC) that evaluated two methods for determining the sulfur content for an NRC reference material (CNCD-1) produced from CNCs extracted by sulfuric acid hydrolysis of wood pulp. Inductively coupled plasma-optical emission spectroscopy (ICP-OES) was used to measure the total sulfur content of CNCs after microwave assisted digestion in strong acid. Conductometric titration quantified the negatively charged sulfate half-ester groups on the CNC surface after dialysis and protonation using ion exchange resin. The data was analyzed with an ASTM method that employs h and k statistics to identify data sets for which the laboratory mean or standard deviation show excessive variation from the overall mean or standard deviation and the NIST consensus builder (NICOB) engine using the DerSimonian–Laird meta-analysis to determine a consensus estimate of the mean and its associated measurement uncertainty. The consensus estimates  ±  uncertainty for total sulfur and sulfate half ester content were (8771  ±  94) mg kg−1 and (252.0  ±  8.2) mmol kg−1, respectively. Neither approach identified any outliers in the data sets and the consensus estimates were in agreement with values obtained during certification of the reference material. The results confirmed that the difference between the sulfur content measured by conductometric titration and ICP-OES is larger than the combined 95% expanded uncertainties. The higher sulfur content measured by ICP-OES may reflect the presence of sulfur impurities that are not detected by titration. Overall the ILC provides validation for the protocols for the two methods and indicates that both are reasonably tolerant of small variations from the protocol. A more reliable method of assessing the titration endpoint and a quality control (QC) sample were identified as potential improvements to reduce variability for the conductometric titration.

Definition of the mole (IUPAC Recommendation 2017) - Marquardt, Roberto; Meija, Juris; Mester, Zoltán; Towns, Marcy; Weir, Ron; Davis, Richard; Stohner, Jürgen (Pure and Applied Chemistry, 2018)
In 2011 the General Conference on Weights and Measures (CGPM) noted the intention of the International Committee for Weights and Measures (CIPM) to revise the entire International System of Units (SI) by linking all seven base units to seven fundamental physical constants. Of particular interest to chemists, new definitions for the kilogram and the mole have been proposed. A recent IUPAC Technical Report discussed these new definitions in relation to immediate consequences for the chemical community. This IUPAC Recommendation on the preferred definition of the mole follows from this Technical Report. It supports a definition of the mole based on a specified number of elementary entities, in contrast to the present 1971 definition.
Keywords: Avogadro constant; Avogadro number; definition; IUPAC Physical and Biophysical Chemistry Division; mole; SI

Cysteinyl leukotrienes C4 AND D4Downregulate human mast cell expression of toll-like receptors 1 through 7 - Karpov, V.; Ilarraza, R.; Catalli, A.; Kulka, M. (Journal of Biological Regulators and Homeostatic Agents, 2018)
Cysteinyl leukotrienes (CysLT) are potent inflammatory lipid molecules that mediate some of the pathophysiological responses associated with asthma such as bronchoconstriction, vasodilation and increased microvascular permeability. As a result, CysLT receptor antagonists (LRA), such as montelukast, have been used to effectively treat patients with asthma. We have recently shown that mast cells are necessary modulators of innate immune responses to bacterial infection and an important component of this innate immune response may involve the production of CysLT. However, the effect of LRA on innate immune receptors, particularly on allergic effector cells, is unknown. This study determined the effect of CysLT on toll-like receptor (TLR) expression by the human mast cell line LAD2. Real-time PCR analysis determined that LTC4, LTD4 and LTE4 downregulated mRNA expression of several TLR. Specifically in human CD34+-derived human mast cells (HuMC), LTC4 inhibited expression of TLR1, 2, 4, 5, 6 and 7 while LTD4 inhibited expression of TLR1-7. Montelukast blocked LTC4-mediated downregulation of all TLR, suggesting that these effects were mediated by activation of the CysLT1 receptor (CysLT1R). Flow cytometry analysis confirmed that LTC4 downregulated surface expression of TLR2 which was blocked by montelukast. These data show that CysLT can modulate human mast cell expression of TLR and that montelukast may be beneficial for innate immune responses mediated by mast cells.

Corona discharge electrospray ionization of formate-containing solutions enables in-source reduction of disulfide bonds - Stocks, Bradley B.; Melanson, Jeremy E. (Analytical and Bioanalytical Chemistry, 2018)
Disulfide bonds are critical linkages for maintaining protein structure and enzyme activity. These linkages, however, can limit peptide sequencing efforts by mass spectrometry (MS) and often require chemical reduction and alkylation. Under such conditions, information regarding cysteine connectivity is lost. Online partial disulfide reduction within the electrospray (ESI) source has recently been established as a means to identify complex cysteine linkage patterns in a liquid chromatography-MS experiment without the need for sample pre-treatment. Corona discharge (CD) is invoked as the causative factor of this in-source reduction (ISR); however, evidence remains largely circumstantial. In this study, we demonstrate that instrumental factors—nebulizing gas, ESI capillary material, organic solvent content, ESI spray needle-to-MS distance—all modulate the degree of reduction observed for the single disulfide in oxytocin, further implicating CD in ISR. Rigorous analysis of solution conditions, however, reveals that corona discharge alone can induce only minor disulfide reduction. We establish that CD-ESI of peptide solutions containing formic acid or its conjugate base results in a dramatic increase in disulfide reduction. It is also determined that ISR is exacerbated at low pH for complex peptides containing multiple disulfide bonds and possessing higher-order structure, as well as for a small protein. Overall, our results demonstrate that ESI of formate/formic acid–containing solutions under corona discharge conditions facilitates disulfide ISR, likely by a similar reduction pathway measured in γ-radiolysis studies nearly three decades ago.
Keywords: disulfide bond; in-source reduction; formate; corona discharge; electrospray ionization

Cooperation in publicly funded reference material production - Emteborg, Håkan; Florian, Doris; Choquette, Steven; Ellison, Stephen L. R.; Fernandes-Whaley, Maria; Mackay, Lindsey; McCarron, Pearse; Panne, Ulrich; Sander, Sylvia G.; Kim, Sook-Kyung; Held, Andrea; Linsinger, Thomas; et al. (Accreditation and Quality Assurance, 2018)
The meeting was organised by the European Commission’s Joint Research Centre and held at the JRC-Geel site on 22–23 February 2018. It was a follow-up of a similar meeting held in 2009. The objective of the meeting was to exchange information about ongoing publicly funded reference material (RM) production, identify areas of interest for future specific RMs, including certified reference material (CRM) developments, investigate potential areas of collaboration, and to identify areas which may be of a lower importance in the future for a specific RM producer. The benefit of exchanging such information is to avoid duplication of efforts in RM production, make better use of public funds by potentially matching competencies, and to address problems that are common to publicly funded RM producers. Attendees included representatives of the following organisations: Bundesanstalt für Materialforschung und –prüfung (BAM), Germany; IAEA Environment Laboratories, Monaco; the Joint Research Centre (JRC), Belgium (formerly IRMM); the Korea Research Institute of Standards and Science (KRISS), South Korea; LGC, UK, the National Institute of Standards and Technology (NIST), USA; the National Measurement Institute of Australia (NMIA), Australia; the National Metrology Institute of South Africa (NMISA), South Africa; and the National Research Council Canada (NRCC), Canada. National Metrology Institute of Japan (NMIJ), Japan, and National Institute of Metrology (NIM), China, were invited but declined or were unable to attend. The remaining nine attendees participated physically or via videoconference. The full group of eleven RM producers corresponds to the major publicly funded RM producers according to the activity reports of the International Standards Organisation’s committee on reference materials (ISO-REMCO).

Contrail flight data for a variety of jet fuels - Brown, Anthony P.; Bastian, Matthew; Canteenwalla, Pervez (2018 Atmospheric and Space Environments Conference, 2018)
In 2017/18, the NRC undertook biofuel contrail flight research from a number of jet transport aircraft and jet fuels, including petroleum JetA1, JP-5, HEFA and ethanol-derived ATJ biofuels. The flight contrail data, consisting of derived ice particle number, size, spherical mass, and the FSSP-100 optical properties of effective size, extinction coefficient, optical depth and laterally-integrated optical depth, was obtained and compared for JetA1, JP-5 and biofuels (43% HEFA-SPK blend with Jet A1 and 92% ethanol-derived ATJ-SPK blend with aromatics). Contrail conditions covered sublimating to persistent. Contrail properties were compared with aerosol and non-volatile particulate emissions, and with previous soot modeling of young contrails. Results showed progressive reductions in persistent contrail ice particle number with biofuel blend percentage, almost log-linear reductions with non-volatile aerosol emissions, a slight increase in ice particle size with 92% ATJ-SPK. The lateral integrands of optical depth showed 30-50% reductions for the 92% blend ATJ-SPK, compared to Jet A1.

Construction of high-density linkage maps for mapping quantitative trait loci for multiple traits in field pea (Pisum sativum L.) - Gali, Krishna K.; Liu, Yong; Sindhu, Anoop; Diapari, Marwan; Shunmugam, Arun S. K.; Arganosa, Gene; Daba, Ketema; Caron, Carolyn; Lachagari, Reddy V. B.; Tar’an, Bunyamin; Warkentin, Thomas D. (BMC Plant Biology, 2018)
Background: The objective of this research was to map quantitative trait loci (QTLs) of multiple traits of breeding importance in pea (Pisum sativum L.). Three recombinant inbred line (RIL) populations, PR-02 (Orb x CDC Striker), PR-07 (Carerra x CDC Striker) and PR-15 (1–2347-144 x CDC Meadow) were phenotyped for agronomic and seed quality traits under field conditions over multiple environments in Saskatchewan, Canada. The mapping populations were genotyped using genotyping-by-sequencing (GBS) method for simultaneous single nucleotide polymorphism (SNP) discovery and construction of high-density linkage maps. Results: After filtering for read depth, segregation distortion, and missing values, 2234, 3389 and 3541 single nucleotide polymorphism (SNP) markers identified by GBS in PR-02, PR-07 and PR-15, respectively, were used for construction of genetic linkage maps. Genetic linkage groups were assigned by anchoring to SNP markers previously positioned on these linkage maps. PR-02, PR-07 and PR-15 genetic maps represented 527, 675 and 609 non-redundant loci, and cover map distances of 951.9, 1008.8 and 914.2 cM, respectively. Based on phenotyping of the three mapping populations in multiple environments, 375 QTLs were identified for important traits including days to flowering, days to maturity, lodging resistance, Mycosphaerella blight resistance, seed weight, grain yield, acid and neutral detergent fiber concentration, seed starch concentration, seed shape, seed dimpling, and concentration of seed iron, selenium and zinc. Of all the QTLs identified, the most significant in terms of explained percentage of maximum phenotypic variance (PVmax) and occurrence in multiple environments were the QTLs for days to flowering (PVmax = 47.9%), plant height (PVmax = 65.1%), lodging resistance (PVmax = 35.3%), grain yield (PVmax = 54.2%), seed iron concentration (PVmax = 27.4%), and seed zinc concentration (PVmax = 43.2%). Conclusion: We have identified highly significant and reproducible QTLs for several agronomic and seed quality traits of breeding importance in pea. The QTLs identified will be the basis for fine mapping candidate genes, while some of the markers linked to the highly significant QTLs are useful for immediate breeding applications.
Keywords: pea; Pisum sativum L; quantitative trait loci

Commissioning of a high speed rolling-element bearing rig: preliminary results - Dadouche, A.; Kerrouche, R.; Boukraa, S. (73rd Society of Tribologists and Lubrication Engineers Annual Meeting and Exhibition 2018, 2018)
Rolling element bearings represent critical components in rotating machinery especially aircraft engines and accessory gearboxes. They are required to operate reliably under high temperature and speed conditions well over 3 million DN (bearing bore in millimeter x shaft speed in rpm) where hybrid technology is being investigated by numerous engine manufacturers. As a result, there has been an enormous amount of work done in the field over the last five decades where different test rigs have been built for that purpose. For instance, Holmes tested ball bearings with a 125 mm bore at speeds up to 24 krpm (3.0 MDN) to determine skidding characteristics. Similarly, in their experimental work, Bamberger et al. studied the effect of speed and load on the performance operation of a 120 mm bore angular contact ball bearing. They found that significant skidding occurred at the highest speed of 25 krpm. This paper describes the operation of a high-speed bearing rig instrumented with state-of-the-art sensors to study performance characteristics of rolling-element bearings operating at extreme conditions. A typical aircraft engine roller bearing was used during the commissioning phase of the rig. Preliminary results of the main bearing characteristics under controlled operating conditions are presented.
Keywords: rolling bearings:cylindrical roller bearings; engines:gas/jet turbines; friction:hydrodynamic friction

Coherent storage and manipulation of broadband photons via dynamically controlled Autler–Townes splitting - Saglamyurek, Erhan; Hrushevskyi, Taras; Rastogi, Anindya; Heshami, Khabat; Leblanc, Lindsay J. (Nature Photonics, 2018)
Photonic quantum information technologies rely on quantum memory for long-lived storage and coherent manipulation of short pulses of non-classical light. The optical quantum memories explored over the past two decades are based on various coherent light–matter interaction schemes, but despite impressive progress, practical memories featuring efficient, broadband and long-lived operation remain elusive, due to the technical demands and inherent limitations of the established schemes. Here, we introduce a technique for high-speed quantum memory and manipulation that overcomes these obstacles. This scheme relies on dynamically controlled absorption of light via the ‘Autler–Townes effect’, which mediates reversible transfer between photonic coherence and the collective ground-state coherence of the storage medium. We experimentally demonstrate proof-of-concept storage and signal processing capabilities of our protocol in a laser-cooled gas of rubidium atoms, including storage of nanoseconds-long single-photon-level laser pulses for up to a microsecond. This approach opens up new avenues in quantum optics, with immediate applications on atomic and solid-state platforms.

Charge-spin correlation in van der Waals Antiferromagnet NiPS3 - Kim, So Yeun; Kim, Tae Yun; Sandilands, Luke J.; Sinn, Soobin; Lee, Min-Cheol; Son, Jaeseok; Lee, Sungmin; Choi, Ki-Young; Kim, Wondong; Park, Byeong-Gyu; Jeon, C.; Kim, Hyeong-Do; et al. (Physical Review Letters, 2018)
Strong charge-spin coupling is found in a layered transition-metal trichalcogenide NiPS3, a van der Waals antiferromagnet, from studies of the electronic structure using several experimental and theoretical tools: spectroscopic ellipsometry, x-ray absorption, photoemission spectroscopy, and density functional calculations. NiPS3 displays an anomalous shift in the optical spectral weight at the magnetic ordering temperature, reflecting strong coupling between the electronic and magnetic structures. X-ray absorption, photoemission, and optical spectra support a self-doped ground state in NiPS3. Our work demonstrates that layered transition-metal trichalcogenide magnets are useful candidates for the study of correlated-electron physics in two-dimensional magnetic materials.

Characterization of concentrated aqueous CNC suspensions by static multiple light scattering: equivalent particle size and suspension stability - Jakubek, Z. J.; Mazloumi, M.; Johnston, L. J. (International Conference on Nanotechnology for Renewable Materials 2018. Volume 1, 2018)

Dispersion, stability and size measurements for cellulose nanocrystals by static multiple light scattering - Mazloumi, Mahyar; Johnston, Linda J.; Jakubek, Zygmunt J. (Cellulose, 2018)
Static multiple light scattering (SMLS) is used to provide qualitative information on cellulose nanocrystal (CNC) suspensions as a function of the methods used to disperse the dry CNCs and, in some cases, to estimate the equivalent size for primary particles and their aggregates. The methods were validated by measuring the mean diameter of several sizes and concentrations of silica particles which are approximately monodisperse and spherical, both of which significantly simplify the analysis of SMLS data. The results indicate that uncertainty in the silica density contributes to differences between the estimated SMLS diameters and those determined by dynamic light scattering. Suspension stability, sedimentation kinetics, and particle size as a function of dispersion method were evaluated for CNC suspensions by measuring the intensity profiles of light transmitted through the sample as a function of time, and applying sedimentation or light scattering theories. The results demonstrate that SMLS is a useful method for monitoring CNC dispersion for samples that are too concentrated to study by DLS. The sedimentation analysis provides qualitative information on the presence and size (equivalent diameter) of CNC aggregates/agglomerates and evidence for formation of a stable phase that forms during concurrent sedimentation and dispersion of CNC aggregates for unsonicated suspensions and is hypothesized to be a gel phase.
Keywords: cellulose nanocrystals; dispersion; static multiple light scattering

CCAT-Prime: science with an ultra-widefield submillimeter observatory on Cerro Chajnantor - Stacey, Gordon J.; Battaglia, Nicholas; Bertoldi, Frank; Fich, Michel; Haynes, Martha P.; Herter, Terry L.; Magnelli, Benjamin; Niemack, Michael D.; Nikola, Thomas; Parshley, Stephen C.; Riechers, Dominik A.; Viero, Marco; et al. (Ground-based and Airborne Telescopes VII, 2018)
We present the detailed science case, and brief descriptions of the telescope design, site, and first light instrument plans for a new ultra-wide field submillimeter observatory, CCAT-prime, that we are constructing at a 5600 m elevation site on Cerro Chajnantor in northern Chile. Our science goals are to study star and galaxy formation from the epoch of reionization to the present, investigate the growth of structure in the Universe, improve the precision of B-mode CMB measurements, and investigate the interstellar medium and star formation in the Galaxy and nearby galaxies through spectroscopic, polarimetric, and broadband surveys at wavelengths from 200 m to 2 mm. These goals are realized with our two first light instruments, a large field-of-view (FoV) bolometer-based imager called Prime-Cam (that has both camera and an imaging spectrometer modules), and a multi-beam submillimeter heterodyne spectrometer, CHAI. CCAT-prime will have very high surface accuracy and very low system emissivity, so that combined with its wide FoV at the unsurpassed CCAT site our telescope/instrumentation combination is ideally suited to pursue this science. The CCAT-prime telescope is being designed and built by Vertex Antennentechnik GmbH. We expect to achieve first light in the spring of 2021.

Cascaded Mach–Zehnder architectures for photonic integrated delay lines - Waqas, Abi; Melati, Daniele; Melloni, Andrea (IEEE Photonics Technology Letters, 2018)
A continuously tunable integrated optical delay line architecture with large bandwidth and bandwidth-delay product is proposed and demonstrated. The non-resonant delay line is based on cascaded Mach-Zehnder interferometers with tunable couplers. The device is operated with a single control signal and outperforms the common ring-resonator-based delay lines in terms of bandwidth-delay product. A device with a delay tuning range of 124 ps is experimentally demonstrated over a transmission bandwidth of 4.5 GHz.

Carbon nanotubes and related nanomaterials: critical advances and challenges for synthesis toward mainstream commercial applications - Rao, Rahul; Pint, Cary L.; Islam, Ahmad E.; Weatherup, Robert S.; Hofmann, Stephan; Meshot, Eric R.; Wu, Fanqi; Zhou, Chongwu; Dee, Nicholas; Amama, Placidus B.; Carpena-Nuñez, Jennifer; Shi, Wenbo; et al. (ACS Nano, 2018)
Advances in the synthesis and scalable manufacturing of single-walled carbon nanotubes (SWCNTs) remain critical to realizing many important commercial applications. Here we review recent breakthroughs in the synthesis of SWCNTs and highlight key ongoing research areas and challenges. A few key applications that capitalize on the properties of SWCNTs are also reviewed with respect to the recent synthesis breakthroughs and ways in which synthesis science can enable advances in these applications. While the primary focus of this review is on the science framework of SWCNT growth, we draw connections to mechanisms underlying the synthesis of other 1D and 2D materials such as boron nitride nanotubes and graphene.
Keywords: 2D materials; boron nitride nanotubes; carbon nanotubes; chirality control; CVD; graphene; helicity; synthesis

Capturing elusive polymorphs of curcumin: a structural characterization and computational study - Matlinska, Maria A.; Wasylishen, Roderick E.; Bernard, Guy M.; Terskikh, Victor V.; Brinkmann, Andreas; Michaelis, Vladimir K. (Crystal Growth & Design, 2018)
Curcumin, a compound derived from the herb turmeric, has gained considerable attention because of its purported pharmacological activity, but its poor water solubility and low bioavailability impedes its therapeutic potential. In addition to the frequently studied curcumin polymorph, referred to as form I, another polymorph with enhanced water solubility, referred to as form II, or red curcumin, has also been reported. We discuss experimental challenges in isolating the red curcumin polymorph. In the course of our studies, we were unable to obtain a third reported polymorph, form III. We redetermined crystal structures of forms I and II of curcumin and present 13C and 1H solid-state nuclear magnetic resonance (NMR) spectra for these two forms, as well as 13C–1H two-dimensional heteronuclear correlation (HETCOR) data. The experimental 1H and 13C nuclear magnetic resonance (NMR) chemical shifts are compared with GIPAW density functional theory values computed using CASTEP. Our research illustrates the utility of NMR spectroscopy in characterization of polymorphism in bulk samples.

Canadian seismic design provisions for CLT structures - Popovski, M.; McFadden, J. B. W. (WCTE 2018: World Conference on Timber Engineering, 2018)
Although Cross-laminated timber (CLT) has been used as a product and a structural system for over 20 years around the world, the codification of CLT is lagging behind which presents a challenge for the design community. Driven by the popularity of CLT in residential and non-residential applications in Canada, design provisions for CLT have been implemented in the 2014 edition of CSA O86 Update No. 1 published in 2016, the Canadian Standard for Engineering Design in Wood. These design provisions for CLT are among the first such guidelines implemented in any code or design standard in the world. This paper summarizes the main aspects of the provisions that are related to seismic design of CLT structures in platform type application. As seismic design provisions for CLT structures are currently being developed in Europe, New Zealand, Japan and the US, the paper will be of great interest to researchers, designers and code officials in this field.
Keywords: capacity based design; CLT; CLT diaphragms; CLT shearwalls; seismic design of CLT structures

Birefringent π-phase-shifted fiber bragg gratings for sensing at 1000 °C fabricated using an infrared femtosecond laser and a phase mask - Hnatovsky, Cyril; Grobnic, Dan; Mihailov, Stephen J. (Journal of Lightwave Technology, 2018)
Birefringent π-phase-shifted Bragg gratings for multi-parameter sensing at temperatures ~1000 °C are written inside a standard single mode silica optical fiber (SMF-28) with infrared femtosecond pulses and a special phase mask one half of which is shifted with respect to the other by 5/4 of the mask period. The birefringence is caused by the presence of light-induced sub-wavelength periodic planar nanostructures in the fiber core, whose orientation is controlled by the laser polarization, and is maximized when the laser pulse polarization is aligned perpendicular to the fiber core. The birefringence can reach ~4.2 × 10 -4 at room temperature at the 1.5 × 10 -4 level after 100 h annealing at 1000 °C. Erasure and rewriting of the planar nanostructures inside fiber Bragg gratings by changing the laser pulse polarization is demonstrated.
Keywords: birefringence; femtosecond laser; fiber Bragg gratings; laser material processing; phase mask; phase shift

Bi-functional air electrode fabrication, performance and stability evaluation - Zhang, Xinge; Tsay, Ken; Qu, Wei; Fahlman, Jason (Journal of Energy Storage, 2018)
Perovskite Sm0.5Sr0.5CoO3-δ (SSC) based bifunctional (BF) air electrodes were fabricated by dry fibrillation mixing, wet tape processing and hot plate pressing method using Vulcan XC-72 carbon black as conductive support, polytetrafluoroethylene as binder and Ni exmet (or Ni foam) as current collector. The BF air electrodes exhibited encouraging performance and cycle-ability. Under the test condition of room temperature (20–22 °C), 6 M KOH and 50 mA/cm2, the obtained oxygen evolution reaction (OER) potential was around 0.67 V and oxygen reduction reaction (ORR) potential was around −0.20 V vs. Hg/HgO reference electrode. Number of cycle of 2 h (approximately) duration reached over 180 cycles at 20 mA/cm2 using a copper exmet as negative Zn electrode substrate. The Zn air battery prototype showed coulombic efficiency and energy efficiency around 95–98% and 50–52%, respectively. It was found that using Ni-foam reinforced BF air electrode structure further improved the stability of the electrode, especially for the OER. Performance degradation of approximately 1.5% and 15% were observed for the OER and the ORR, respectively over a test period of 300 h. The electrode performance degradation was explained due to KOH wetting-through the backing layer causing electrode flooding. Active SSC material de-binding and carbon support oxidation were also observed in this study.
Keywords: Zn air battery; rechargeable; bifunctional; air electrode; SSE; energy storage

Bicyclic eremophilane-type petasite sesquiterpenes potentiate peroxisome proliferator–activated receptor γ activator–mediated inhibition of dendritic cells - Arizmendi, Narcy; Hou, Chenjie; Guo, Fujiang; Li, Yiming; Kulka, Marianna (International Journal of Immunopathology and Pharmacology, 2018)
Dendritic cell (DC) activation induces expression of co-stimulatory surface molecules, as well as migration into secondary lymphoid organs, where they activate naïve T-cells. A family of plant derivatives, eremophilane-type petasite sesquiterpenes, can regulate the immune system through DC targeting due to their anti-inflammatory effects. Peroxisome proliferator–activated receptor gamma (PPARγ) is involved in inhibition of inflammatory responses and induction of DCs to acquire a mucosal phenotype. Since mucosal DCs are central in innate immune responses, we hypothesized that eremophilane-type petasite sesquiterpenes exerted their anti-inflammatory effects by inhibiting DC maturation and activation through PPARγ. This study assessed the bicyclic eremophilane-type petasite sesquiterpene compounds Fukinone and 10βH-8α,12-Epidioxyeremophil-7(11)-en-8β-ol (ZYFDC21 and ZYFDC22) in the maturation and activation of mouse DC. We measured surface expression of co-stimulatory molecules by flow cytometry and cell-free supernatant cytokine production upon lipopolysaccharide stimulation by enzyme-linked immunosorbent assays (ELISAs) in the presence or absence of PPARγ agonists. DCs were generated from C57BL/6 mice bone marrow cells and harvested. Cells were exposed to bicyclic eremophilane-type petasite sesquiterpenes ZYFDC21 or ZYFDC22 in the presence or absence of synthetic PPARγ agonists (GW1929 and TGZ) or the natural PPARγ ligand 15d-PGJ2, followed by overnight activation with LPS. We observed differences in the upregulation of surface expression of CD86, along with TNF, IL-6, and IL-12p70 released by DCs stimulated with LPS, when using combinations of bicyclic eremophilane-type petasite sesquiterpenes ZYFDC21 or ZYFDC22, and PPARγ agonists, in particular the PPARγ ligand 15d-PGJ2. Our results indicate that bicyclic eremophilane-type petasite sesquiterpenes ZYFDC21 or ZYFDC22 inhibit maturation and activation of DC, and this activity is augmented upon PPARγ activation.
Keywords: inflammation; peroxisome proliferator–activated receptor gamma; plant derivatives; transcription factor

Automated fatigue testing device for assessing performance of sealant jointing products - Miyauchi, Hiroyuki; Lacasse, Michael A.; Ito, Akihiko; Yamada, Hitoshi (Durability of Building and Construction Sealants and Adhesives: 6th Volume, 2018)
A description of the sealant jointing product test device is given herein that includes information on its operation and results from its use in subjecting sealant products to fatigue resistance tests. In the first instance, a novel benchtop sealant test device was developed that permits assessing the expected long-term performance of joint sealant products. This sealant test device can be used to conduct bench-scale testing indoors in a laboratory setting or outdoors whereby sealant products are exposed to weathering effects while undergoing movement. The device also includes a load cell that permits monitoring the load imposed on the products while undergoing movement; thus, changes in the resistance to movement can be monitored over time. Cyclic movement programs can be run once input to the device, and the rate of movement can be set at predetermined levels. In a subsequent development stage, the durability of sealed joints was verified with the use of the testing device. The effect of the curing condition and stress relaxation of sealants during joint movement were continuously monitored over the course of a daily cycle or a 12-s cycle of compression-tension with the device's load cell. Results showed that over the curing period the sealant joint was damaged, as evident from changes in the cross-section of the sealed joint and reduction in stress of the jointing product. It is likely that this would influence the fatigue resistance of the sealed joint. In addition, in respect to the stress relaxation of sealants, the rate of decrease in the compressive load compared with the initial load is larger than that of the decrease on tensile load; as such, to properly evaluate the fatigue resistance of sealed joints, it is desirable to carry out a program of cyclic joint movement.
Keywords: cyclic movement; durability; fatigue resistance; long-term performance; sealant; sealant curing; sealed joints; stress relaxation; test device

Automated dynamic inspection using active infrared thermography - Usamentiaga, Ruben; Mokhtari, Yacine; Ibarra-Castanedo, Clemente; Klein, Matthieu; Genest, Marc; Maldague, Xavier (IEEE Transactions on Industrial Informatics, 2018)
Active thermography is a proven technology used in a wide variety of applications. In the most common approach using a static configuration, the elements involved in the inspection do not move. This presents serious drawbacks when it is applied to the inspection of large products and machines. An alternative approach is the dynamic inspection, which enables the inspection of large and complex products with better resolution, but it is also extremely challenging as data reconstruction is necessary. This work analyzes two methods for dynamic inspection using active infrared thermography: the thermal photocopier and the line scan. Automatic robust methods are proposed to calculate the temperature-time history, producing a pseudostatic sequence that can be further processed using advanced data processing algorithms to improve defect detection. Results demonstrate the robustness of the proposed methods and the ability to inspect large products with excellent results.
Keywords: Active thermography; dynamic inspection; line scan; thermal photocopier

Athermal echelle grating filter in silicon-on-insulator using a temperature-synchronized input - Melati, Daniele; Verly, Pierre G.; Delâge, André; Cheben, Pavel; Schmid, Jens H.; Janz, Siegfried; Xu, Dan-Xia (Optics Express, 2018)
Athermal design of integrated photonic devices can reduce the need for active temperature stabilization and consequently the energy required to operate photonic integrated circuits. For silicon photonic filters such as AWGs which employ wire or ridge waveguides, temperature insensitivity can be achieved using cladding materials with negative thermo-optic coefficients. On the other hand, in echelle grating filters the inteference takes place in the slab free-propagation region, and therefore the modal overlap with the cladding is small, rendering this method ineffective. In this work we present an approach to design an athermal echelle grating filter exploiting a temperature-synchronized Mach-Zehnder interferometer as input. This reduces the spectral shift over a temperature range of 20 K to less than ±45 pm compared to the 1.6 nm shift for the same echelle grating with a conventional waveguide input. Furthermore, the proposed design relies exclusively on a standard fabrication process for silicon-on-insulator photonic devices and exhibits a good tolerance to fabrication uncertainties.

Assessing MS-based quantitation strategies for low-level impurities in peptide reference materials: application to angiotensin II - Stocks, Bradley B.; Thibeault, Marie-Pier; Meija, Juris; Melanson, Jeremy E. (Analytical and Bioanalytical Chemistry, 2018)
Identification and quantitation of related impurities is vital in obtaining corrected purity values for peptide certified reference materials. The sensitivity and selectivity of high-resolution mass spectrometry (MS) renders it an indispensable technique in this arena. Typical quantitation efforts involve constructing external calibration curves, although analysis of dilute peptide solutions can be complicated by analyte adsorption to vial walls, instrument tubing, etc. The standard addition method alleviates many concerns associated with this sample loss as the calibrant solutions more closely match the matrix of the samples. Yet, both strategies require acquisition of synthetic impurity peptide standards. Label-free proteomics relies on electrospray ionization (ESI)-MS signals to quantify identical peptides across multiple samples; however, peptides of differing sequence can exhibit widely disparate ESI-MS responses. This study explores the use of peak area ratios to quantitate sequence-related peptide impurities in an angiotensin II candidate certified reference material. Using synthetic standards of five abundant substances, impurity mass fractions calculated via the relative response method are in reasonable agreement with those determined from standard addition experiments, whereas external calibration measurements frequently overestimate impurity amounts. For a synthetic peptide and its related sequence impurities, the relative response method can expedite analysis and lower expenditures, and in some cases improve data quality.
Keywords: peptide; reference material; quantitation; impurities; high-resolution mass spectrometry

Application of a hygroscopicity tandem differential mobility analyzer for characterizing PM emissions in exhaust plumes from an aircraft engine burning conventional and alternative fuels - Trueblood, Max B.; Lobo, Prem; Hagen, Donald E.; Achterberg, Steven C.; Liu, Wenyan; Whitefield, Philip D. (Atmospheric Chemistry and Physics, 2018)
In the last several decades, significant efforts have been directed toward better understanding the gaseous and particulate matter (PM) emissions from aircraft gas turbine engines. However, limited information is available on the hygroscopic properties of aircraft engine PM emissions which play an important role in the water absorption, airborne lifetime, obscuring effect, and detrimental health effects of these particles. This paper reports the description and detailed lab-based performance evaluation of a robust hygroscopicity tandem differential mobility analyzer (HTDMA) in terms of hygroscopic properties such as growth factor (GF) and the hygroscopicity parameter (κ). The HTDMA system was subsequently deployed during the Alternative Aviation Fuel EXperiment (AAFEX) II field campaign to measure the hygroscopic properties of aircraft engine PM emissions in the exhaust plumes from a CFM56-2C1 engine burning several types of fuels. The fuels used were conventional JP-8, tallow-based hydroprocessed esters and fatty acids (HEFA), Fischer–Tropsch, a blend of HEFA and JP-8, and Fischer–Tropsch doped with tetrahydrothiophene (an organosulfur compound). It was observed that GF and κ increased with fuel sulfur content and engine thrust condition, and decreased with increasing dry particle diameter. The highest GF and κ values were found in the smallest particles, typically those with diameters of 10 nm.

Antimicrobial peptide LL-37 and its truncated forms, GI-20 and GF-17, exert spermicidal effects and microbicidal activity against Neisseria gonorrhoeae - Kiattiburut, Wongsakorn; Zhi, Ruina; Lee, Seung Gee; Foo, Alexander C.; Hickling, Duane R.; Keillor, Jeffrey W.; Goto, Natalie K.; Li, Weihua; Conlan, Wayne; Angel, Jonathan B.; Wang, Guangshun; Tanphaichitr, Nongnuj (Human Reproduction, 2018)
Do the truncated LL-37 peptides, GI-20 and GF-17, have spermicidal activity and microbicidal effects on the sexually transmitted infection (STI) pathogen Neisseria gonorrhoeae with equivalent potency to LL-37? GI-20 and GF-17 exhibited spermicidal effects on both mouse and human sperm as well as microbicidal action on N. gonorrhoeae with the same efficacy as LL-37.
Keywords: spermicide; antimicrobial peptide; LL-37; GI-20; GF-17; microbicide; Neisseria gonorrhoeae; Lactobacillus crispatus; sperm-fertilizing ability; vaginal contraceptive

Antigen recognition by single-domain antibodies: structural latitudes and constraints - Henry, Kevin A.; Mackenzie, C. Roger (mAbs, 2018)
Single-domain antibodies (sdAbs), the autonomous variable domains of heavy chain-only antibodies produced naturally by camelid ungulates and cartilaginous fishes, have evolved to bind antigen using only three complementarity-determining region (CDR) loops rather than the six present in conventional VH:VL antibodies. It has been suggested, based on limited evidence, that sdAbs may adopt paratope structures that predispose them to preferential recognition of recessed protein epitopes, but poor or non-recognition of protuberant epitopes and small molecules. Here, we comprehensively surveyed the evidence in support of this hypothesis. We found some support for a global structural difference in the paratope shapes of sdAbs compared with those of conventional antibodies: sdAb paratopes have smaller molecular surface areas and diameters, more commonly have non-canonical CDR1 and CDR2 structures, and have elongated CDR3 length distributions, but have similar amino acid compositions and are no more extended (interatomic distance measured from CDR base to tip) than conventional antibody paratopes. Comparison of X-ray crystal structures of sdAbs and conventional antibodies in complex with cognate antigens showed that sdAbs and conventional antibodies bury similar solvent-exposed surface areas on proteins and form similar types of non-covalent interactions, although these are more concentrated in the compact sdAb paratope. Thus, sdAbs likely have privileged access to distinct antigenic regions on proteins, but only owing to their small molecular size and not to general differences in molecular recognition mechanism. The evidence surrounding the purported inability of sdAbs to bind small molecules was less clear. The available data provide a structural framework for understanding the evolutionary emergence and function of autonomous heavy chain-only antibodies.
gold access
Keywords: single-domain antibody; VHH; VNAR; molecular recognition; antibody:antigen interaction; paratope; epitope

An investigation of the mechanisms causing large-amplitude wind-induced vibrations in stay cables using unsteady surface pressure measurements - Mctavish, Sean; Raeesi, Arash; D'Auteuil, Annick; Yamauchi, Kunihiro; Sato, Hiroshi (Journal of Wind Engineering and Industrial Aerodynamics, 2018)
Dry galloping has been observed on in-service bridges and has been reproduced in several wind tunnel experiments of inclined stay cables. In certain cases, the large-amplitude vibrations caused by dry galloping could not be mitigated with damping levels specified by the Post Tensioning Institute (PTI). Wind tunnel investigations were conducted for IHI Corporation on a 1:1 scale sectional model of an inclined bridge stay cable in the 3 m × 6 m Wind Tunnel at the National Research Council Canada in 2015. The purpose of the investigation was to reproduce large amplitude cable galloping, which had been observed at an existing cable-stayed bridge in Japan. The experiment was designed to investigate the influence of different damping levels and the ability of a 5 mm-diameter helical fillet to mitigate dry cable vibrations. The current work identified several important factors that contributed to dry galloping and large-amplitude cable motions. It was shown that the physical mechanisms leading to the onset of large-amplitude motion in the critical and supercritical Reynolds number regimes are distinct. In the critical Reynolds number regime, the drop in drag, increase in lift, and fluctuations in the laminar separation bubbles along the cable destabilize the low pressure lobes, allowing the changes in pressure along the cable to become synchronized with the cable motion in a highly-correlated manner. This type of galloping could not be mitigated with damping greater than that required by the PTI. At high Reynolds numbers, the boundary layer state changed and was associated with the upstream movement of the separation point and an asymmetric pressure distribution, Kármán vortex shedding re-emerged and appeared to combine with low-frequency variations to induce large-amplitude motion. The large-amplitude motion at high Reynolds numbers could be mitigated with additional damping.
Keywords: stay cable; dry galloping; wind-induced vibration; damping; wind tunnel

Accurate semantic textual similarity for cleaning noisy parallel corpora using semantic machine translation evaluation metric: the NRC supervised submissions to the Parallel Corpus Filtering task - Lo, Chi-Kiu; Simard, Michel; Stewart, Darlene; Larkin, Samuel; Goutte, Cyril; Littell, Patrick (Third Conference on Machine Translation (WMT 18) Shared Task Papers, 2018)
We present our semantic textual similarity approach in filtering a noisy web crawled parallel corpus using YiSi—a novel semantic machine translation evaluation metric. The systems mainly based on this supervised approach perform well in the WMT18 Parallel Corpus Filtering shared task (4th place in 100-millionword evaluation, 8th place in 10-million-word evaluation, and 6th place overall, out of 48 submissions). In fact, our best performing system—NRC-yisi-bicov is one of the only four submissions ranked top 10 in both evaluations. Our submitted systems also include some initial filtering steps for scaling down the size of the test corpus and a final redundancy removal step for better semantic and token coverage of the filtered corpus. In this paper, we also describe our unsuccessful attempt in automatically synthesizing a noisy parallel development corpus for tuning the weights to combine different parallelism and fluency features.

Measuring sentence parallelism using Mahalanobis distances: the NRC unsupervised submissions to the WMT18 Parallel Corpus Filtering shared task - Littell, Patrick; Larkin, Samuel; Stewart, Darlene; Simard, Michel; Goutte, Cyril; Lo, Chi-Kiu (Third Conference on Machine Translation (WMT 18) Shared Task Papers, 2018)
The WMT18 shared task on parallel corpus filtering (Koehn et al., 2018b) challenged teams to score sentence pairs from a large high recall, low-precision web-scraped parallel corpus (Koehn et al., 2018a). Participants could use existing sample corpora (e.g. past WMT data) as a supervisory signal to learn what a “clean” corpus looks like. However, in lower resource situations it often happens that the target corpus of the language is the only sample of parallel text in that language. We therefore made several unsupervised entries, setting ourselves an additional constraint that we not utilize the additional clean parallel corpora. One such entry fairly consistently scored in the top ten systems in the 100M-word conditions, and for one task—translating the European Medicines Agency corpus (Tiedemann, 2009)—scored among the best systems even in the 10M-word conditions.

An improved secondary reflector for DVA-2 radio telescope: a case study on application of structural optimization technique - Islam, Mohammad N.; Lacy, Gordon E. (Ground-based and Airborne Telescopes VII, 2018)
Dish Verification Antennae (DVA)–1 demonstrates excellent performance at L-band and can operate reasonably up to 10 GHz. However, with recent technological advances, there is a push towards the development of high frequency radio telescopes up to Q-Band and more. As an attempt to demonstrate the capabilities of the composite radio telescopes at higher frequency range (up to Q-Band), a DVA–2 is currently under construction. In this article the authors will elaborate the design path towards the improved carbon based secondary dish support structure (SDSS) for the DVA–2. In DVA–1, the secondary support structure was directly connected to the secondary reflector at four points. At various gravity loads, it is observed in finite element analysis (FEA) that the distortion from the feed platform and adjacent structures are directly transferred into the secondary rim and eventually on to the surface. To separate the effects, a ring made out of carbon composite was placed between the support structure and the secondary reflector. To investigate the size of the ring and especially the layup of the composite, a topology optimization and free-size optimization was performed. A further improvement was achieved by carefully investigating the deformations in the ring and locally stiffening the connection points of the landing tubes on the ring. All these changes in the SDSS resulted in a 96% reduction in RMS residual error for the worst case condition at 15° elevation angle. A combination of careful analyses and application of optimization techniques was paramount to achieve 50GHz performance.
Keywords: DVA-2; secondary dish; residual error; structural optimization

An examination of the besetting of the MV Berge Atlantic - Browne, T.; Fowler, C. D.; Kubat, I.; Watson, D.; Sayed, M. (28th International Ocean and Polar Engineering Conference, ISOPE 2018; Sapporo; Japan; 10 June 2018 through 15 June 2018, 2018)
A detailed account of the besetting and break-out of the MV Berge Atlantic in the Gulf of St. Lawrence in 2014 is presented. Field observations indicate that besetting occurred with the absence of significant ice pressure, and may have been triggered by ice ridging. An ice dynamics model was used to reproduce the evolution of ice conditions in the vicinity of the beset vessel. The results show that appropriate initialization of ridge distribution is needed for accurate evaluation of the risk of besetting.
Keywords: besetting; ice dynamics model; ice pressure; sea ice ridging

An ALMA 3 mm continuum census of Westerlund 1 - Fenech, D. M.; Clark, J. S.; Prinja, R. K.; Dougherty, S.; Najarro, F.; Negueruela, I.; Richards, A.; Ritchie, B. W.; Andrews, H. (Astronomy & Astrophysics, 2018)
Massive stars play an important role in both cluster and galactic evolution and the rate at which they lose mass is a key driver of both their own evolution and their interaction with the environment up to and including their terminal SNe explosions. Young massive clusters provide an ideal opportunity to study a co-eval population of massive stars, where both their individual properties and the interaction with their environment can be studied in detail. We aim to study the constituent stars of the Galactic cluster Westerlund 1 in order to determine mass-loss rates for the diverse post-main sequence population of massive stars. To accomplish this we made 3mm continuum observations with the Atacama Large Millimetre/submillimetre Array. We detected emission from 50 stars in Westerlund 1, comprising all 21 Wolf-Rayets within the field of view, plus eight cool and 21 OB super-/hypergiants. Emission nebulae were associated with a number of the cool hypergiants while, unexpectedly, a number of hot stars also appear spatially resolved. We were able to measure the mass-loss rates for a unique population of massive post-main sequence stars at every stage of evolution, confirming a significant increase as stars transitioned from OB supergiant to WR states via LBV and/or cool hypergiant phases. Fortuitously, the range of spectral types exhibited by the OB supergiants provides a critical test of radiatively-driven wind theory and in particular the reality of the bi-stability jump. The extreme mass-loss rate inferred for the interacting binary Wd1-9 in comparison to other cluster members confirmed the key role binarity plays in massive stellar evolution. The presence of compact nebulae around a number of OB and WR stars is unexpected; by analogy to the cool super-/hypergiants we attribute this to confinement and sculpting of the stellar wind via interaction with the intra-cluster medium/wind. Given the morphologies of core collapse SNe depend on the nature of the pre-explosion circumstellar environment, if this hypothesis is correct then the properties of the explosion depend not just on the progenitor, but also the environment in which it is located.
Keywords: stars: evolution; open clusters and associations: individual: Westerlund 1; submillimeter: stars

An accurate TMT-based approach to quantify and model lysine susceptibility to conjugation via N-hydroxysuccinimide esters in a monoclonal antibody - Hill, Jennifer J.; Tremblay, Tammy-Lynn; Corbeil, Christopher R.; Purisima, Enrico O.; Sulea, Traian (Scientific Reports, 2018)
Conjugation of small molecules to proteins through N-hydroxysuccinimide (NHS) esters results in a random distribution of small molecules on lysine residues and the protein N-terminus. While mass spectrometry methods have improved characterization of these protein conjugates, it remains a challenge to quantify the occupancy at individual sites of conjugation. Here, we present a method using Tandem Mass Tags (TMT) that enabled the accurate and sensitive quantification of occupancy at individual conjugation sites in the NIST monoclonal antibody. At conjugation levels relevant to antibody drug conjugates in the clinic, site occupancy data was obtained for 37 individual sites, with average site occupancy data across 2 adjacent lysines obtained for an additional 12 sites. Thus, altogether, a measure of site occupancy was obtained for 98% of the available primary amines. We further showed that removal of the Fc-glycan on the NIST mAb increased conjugation at two specific sites in the heavy chain, demonstrating the utility of this method to identify changes in the susceptibility of individual sites to conjugation. This improved site occupancy data allowed calibration of a bi-parametric linear model for predicting the susceptibility of individual lysines to conjugation from 3D-structure based on their solvent exposures and ionization constants. Trained against the experimental data for lysines from the Fab fragment, the model provided accurate predictions of occupancies at lysine sites from the Fc region and the protein N-terminus (R2 = 0.76). This predictive model will enable improved engineering of antibodies for optimal labeling with fluorophores, toxins, or crosslinkers.

Advanced metal-organic frameworks (MOFs) and their derived electrode materials for supercapacitors - Du, Wei; Bai, Yue-Ling; Xu, Jiaqiang; Zhao, Hongbin; Zhang, Lei; Li, Xifei; Zhang, Jiujun (Journal of Power Sources, 2018)
Metal-organic frameworks (MOFs) and their derivatives are promising electrodes materials because of their various modular and controllable structures as well as their high specific surface areas and large internal pore volume. This review elaborates the recent advances in MOFs and MOF-derived materials for supercapacitor applications. Derivatives based on several typical MOFs are discussed with a focus on material synthesis strategies and corresponding supercapacitor performances if applied as electrode materials. Challenges and opportunities in MOFs-derived materials as supercapacitors are also highlighted, and further research directions are proposed to facilitate research and development in this area.
Keywords: metal organic frameworks; supercapacitors; electrode materials; material composition

Adenosine activates Gαs proteins and inhibits C3a-induced activation of human mast cells - Arizmendi, Narcy; Kulka, Marianna (Biochemical Pharmacology, 2018)
Anaphylatoxin C3a and adenosine receptors (AR) are implicated in the inflammatory process associated with allergic rhinitis and asthma by modifying mast cell (MC) responses. Possible interactions between these G-protein coupled receptor (GPCR) pathways in MCs have not yet been demonstrated. LAD2 human MC were stimulated with C3a in the presence or absence of AR agonists and antagonists and their adhesion, chemotaxis and mediator release were measured. The pan-specific AR agonist, 5′-N-Ethylcarboxamidoadenosine (NECA) inhibited C3a-induced LAD2 cell migration, adhesion, degranulation, production of CCL2, and ERK1/2 phosphorylation. The selective A2A receptor agonist CGS 21680 inhibited C3a-mediated degranulation, while the A2B and A3 receptor agonists BAY 60-6583 and IB-MECA, respectively, had no effect. Moreover, an A2A receptor antagonist SCH 58261 blocked the inhibitory effect of NECA on C3a-induced degranulation, suggesting that inhibition of degranulation was mediated through the A2A receptor. NECA increased intracellular cAMP in C3a-activated mast cells, suggesting that Gαs protein signals are required for adenosine-induced inhibition of C3a-mediated human mast cell activation. The adenylyl cyclase inhibitor SQ 22536 attenuated the inhibitory effect of NECA on C3a-activated degranulation, and the A2A agonist CSG 21680 potentiated the inhibition of mast cell activation mediated by the A2A receptor. Our results suggest that adenosine inhibits C3a-mediated activation of human mast cells, possibly through a Gαs protein-dependent pathway.
Keywords: allergic inflammation; adenosine; adenosine receptors; complement; G proteins; mast cells

AC-DC difference of a thermal tansfer standard measured with a pulse-driven Josephson voltage standard - Granger, G.; Flowers-Jacobs, N. E.; Rufenacht, A. (2018 Conference on Precision Electromagnetic Measurements (CPEM 2018), 2018)
An upgraded pulse-driven AC Josephson voltage standard system at the National Research Council Canada allows the generation of quantum-accurate root-mean-square voltages up to 1 V at frequencies down to 10 Hz. The system is used to determine the AC-DC difference of a commercial thermal transfer standard, and an uncertainty budget is presented. Such quantum voltage systems could replace aging multi-junction thermal converters.
Keywords: Josephson arbitratey waveform synthesizers; Josephson voltage standards; pulse-driven thermal transfer standards; thermal converters

A surface plasmon resonance based inhibition immunoassay for measurement of steroid hormones - Cao, Yong; Mcdermott, Mark T. (Analytical Biochemistry, 2018)
Quantitative measurement of small-molecule metabolites is now emerging as an effective way to link the metabolite profile to disease state. Surface plasmon resonance (SPR) is a sensing platform that has demonstrated applicability for a large range of biomolecules. However, direct detection of small molecules with SPR challenges the refractive index based detection mechanism. Herein, we utilized an indirect detection format and developed an inhibition immunoassay for the quantitative measurement of 17β-estradiol (E2) using SPR. One competitor, BSA-E2 conjugate, was immobilized to the SPR chip via the reaction between the primary amino group of the conjugate and the succinimide group (NHS) introduced by the formation of a thiol-NHS monolayer on gold surface. Free E2 molecules compete with BSA-E2 on chip surface for binding sites provided by a monoclonal anti-E2 antibody. It was found the binding affinity of the antibody to BSA-E2 conjugate increases with decreasing surface coverage of BSA-E2 conjugate. Under optimal conditions, a sigmoidal calibration curve with a negative slope and a dynamic range from 10 pM to 2 nM was generated. The detection limit of the immunoassay is estimated to be 0.3 pM. Moreover, the immunoassay exhibits high specificity for E2 detection using estrone (E1) as a potential interference.
Keywords: surface plasmon resonance; inhibition immunoassay; small-molecule metabolites; hormones 17β-estradiol; label-free; 17β-estradiol

A sequence-component-based power-flow analysis for unbalanced droop-controlled hybrid AC/DC microgrids - Allam, Mahmoud A.; Said, Amr; Kazerani, Mehrdad (IEEE Transactions on Sustainable Energy, 2018)
This paper proposes a generalized and efficient power-flow algorithm for islanded hybrid ac/dc microgrids. The algorithm considers the microgrid operational aspects, i.e., absence of a slack bus, unbalanced ac subgrid, droop-controlled ac and dc voltages and ac frequency, and coupling between the ac frequency and dc voltage through interlinking converters (ICs). To attain high computational efficiency, the algorithm adopts three features. First, it models the ac subgrid elements in sequence components, thereby dividing the subgrid's set of equations into three smaller sets for faster parallel solution. This approach also accurately represents the different types of ac distributed generators (DGs). Second, the algorithm sequentially solves for the power-flow variables of the ac and dc subgrids, thus reducing number of equations to be solved simultaneously, once again for further computational cost alleviation. Third, the algorithm implements the quadratically-convergent Newton-Raphson technique to solve the decoupled sets of equations. The proposed algorithm is validated through comparisons with time-domain simulations, in MATLAB/Simulink, for test hybrid ac/dc microgrids of different configurations. Moreover, three case studies are introduced to examine the proposed algorithm's effectiveness in solving large-scale microgrids, to investigate its limits-enforcement capabilities, and to evaluate its performance as compared to conventional methods.
Keywords: Droop; islanded; hybrid ac/dc microgrids; power-flow; sequence components

A priori bond-valence and bond-length calculations in rock-forming minerals - Gagné, Olivier Charles; Mercier, Patrick H. J.; Hawthorne, Frank Christopher (Acta Crystallographica Section B Structural Science, Crystal Engineering and Materials, 2018)
Within the framework of the bond-valence model, one may write equations describing the valence-sum rule and the loop rule in terms of the constituent bond valences. These are collectively called the network equations, and can be solved for a specific bond topology to calculate its a priori bond valences. A priori bond valences are the ideal values of bond strengths intrinsic to a given bond topology that depend strictly on the formal valences of the ion at each site in the structure, and the bond-topological characteristics of the structure (i.e. the ion connectivity). The a priori bond valences are calculated for selected rock-forming minerals, beginning with a simple example (magnesiochromite, = 1.379 bits per atom) and progressing through a series of gradually more complex minerals (grossular, diopside, forsterite, fluoro-phlogopite, phlogopite, fluoro-tremolite, tremolite, albite) to finish with epidote (= 4.187 bits per atom). The effects of weak bonds (hydrogen bonds, long Na+—O2− bonds) on the calculation of a priori bond valences and bond lengths are examined. For the selected set of minerals, a priori and observed bond valences and bond lengths scatter closely about the 1:1 line with an average deviation of 0.04 v.u. and 0.048 Å and maximum deviations of 0.16 v.u. and 0.620 Å. The scatter of the corresponding a priori and observed bond lengths is strongly a function of the Lewis acidity of the constituent cation. For cations of high Lewis acidity, the range of differences between the a priori and observed bond lengths is small, whereas for cations of low Lewis acidity, the range of differences between the a priori and observed bond lengths is large. These calculations allow assessment of the strain in a crystal structure and provide a way to examine the effect of bond topology on variation in observed bond lengths for the same ion-pair in different bond topologies.
Keywords: bond valence; bond length; network equations; Lewis acidity; structural strain

A novel dynamic power routing scheme to maximize loadability of islanded hybrid AC/DC microgrids under unbalanced AC loading - Allam, Mahmoud A.; Hamad, Amr A.; Kazerani, Mehrdad; El-saadany, Ehab F. (IEEE Transactions on Smart Grid, 2018)
This paper proposes a novel dynamic power routing (DPR) scheme for hybrid ac/dc microgrids operating in islanded mode, where unlike in grid-connected microgrids, local generation adequacy is crucial for proper system operation. The unbalanced nature of ac distribution networks limits the microgrid loadability in the sense that loads must be shed from heavily loaded phases, even if the connected distributed generators (DGs) have not reached their total three-phase capacity limits. The main challenge is to exploit the available resources by routing the power between the ac subgrid phases, thereby minimizing load shedding. The proposed method utilizes the interlinking converters between the ac and dc sides of hybrid ac/dc microgrids to provide this functionality. A supervisory controller implements a DPR-based optimal power flow (OPF) algorithm to allow full loadability of the islanded network. The formulated OPF problem is solved analytically using an interior point method that has proved to be computationally cost-effective. Many case studies are conducted to address the unbalance problem and to validate the effectiveness of the proposed strategy against conventional methods, which are based solely on optimal DG droop settings.

A new realization of SI for organic chemical measurement: NIST PS1 primary standard for quantitative NMR (Benzoic Acid) - Nelson, M. A.; Waters, J. F.; Toman, B.; Lang, B. E.; Rück, A.; Breitruck, K.; Obkircher, M.; Windust, A.; Lippa, K. A. (Analytical Chemistry, 2018)
Metrological traceability to common references supports the comparability of chemical measurement results produced by different analysts, at various times, and at separate places. Ideally, these references are realizations of base units of the International System of Units (SI). ISO/IEC 17025 (Clause 6.5) states that traceability of measurement results is a necessary attribute of analytical laboratory competence, and as such, has become compulsory in many industries, especially clinical diagnostics and healthcare. Historically, claims of traceability for organic chemical measurements have relied on calibration chains anchored on unique reference materials with linkage to the SI that is tenuous at best. A first-of-its-kind National Institute of Standards and Technology (NIST) reference material, ultrapure and extensively characterized PS1 Benzoic Acid Primary Standard for quantitative NMR (qNMR), serves as a definitive, primary reference (calibrant) that assuredly links the qNMR spectroscopy technique to SI units. As qNMR itself is a favorable method for accurate, direct characterization of chemical reference materials, PS1 is a standard for developing other traceable standards and is intended to establish traceability for the measurement of thousands of organic chemical species. NIST PS1 will play a critical role in directly promoting accuracy and worldwide comparability of measurement results produced by the chemical measurement community, supporting the soundness of clinical diagnostics, food safety and labeling, forensic investigation, drug development, biomedical research, and chemical manufacturing. Confidence in this link to the SI was established through (i) unambiguous identification of chemical structure; (ii) determinations of isotopic composition and molecular weight; (iii) evaluation of the respective molecular amount by multiple primary measurement procedures, including qNMR and coulometry; and (iv) rigorous evaluation of measurement uncertainty using state-of-the-art statistical methods and measurement models.

A flight study of unsteady aerodynamic loading induced by wake vortex encounter - Brown, Anthony P. (2018 Atmospheric and Space Environments Conference, 2018)
The NRC CT-133 research jet has been installed with a wing glove on the mid-span of the port wing. The wing glove has been installed with pressure transducers, for the measurement of unsteady surface pressures. In flight test, the wing glove has been applied to low-speed stalling and high-speed Mach buffet manoeuvres. The wing glove has been applied to the measurement of unsteady lifting loads during wake vortex encounters (WVE), and appeared to faithfully represent surface flow conditions representative of the loading state experienced by the overall aircraft. In particular local Mach Number on the glove achieved 1.4, without the occurrence of significant shock-induced boundary layer separation (nor, buffet by the overall aircraft), evidential of an increase in the lifting capability of a wing section, under the energizing effect of wake vortex interaction with the wing boundary layer.

A comparison of strong and weak coupling schemes for computational aeroelasticity in OpenFOAM - Seraj, Sabet; Fereidooni, Amin; Grewal, Anant (ASME 2018 5th Joint US-European Fluids Engineering Division Summer Meeting. Volume 1: Flow Manipulation and Active Control; Bio-Inspired Fluid Mechanics; Boundary Layer and High-Speed Flows; Fluids Engineering Education; Transport Phenomena in Energy Conversion and Mixing; Turbulent Flows; Vortex Dynamics; DNS/LES and Hybrid RANS/LES Methods; Fluid Structure Interaction; Fluid Dynamics of Wind Energy; Bubble, Droplet, and Aerosol Dynamics, 2018)
Two coupling schemes for fluid-structure interaction using the OpenFOAM structural solver sixDoF Rigid Body Motion are developed. The first scheme is developed by modifying the baseline leapfrog weak coupling scheme to minimize the lag between the fluid and structural solvers. The second is a strong coupling scheme based on the Crank-Nicolson method. The two newly implemented schemes and the baseline are compared through the aeroelastic simulation of a NACA 64A010 airfoil and the Benchmark Supercritical Wing. The aeroelastic solutions obtained using the newly implemented schemes exhibit significantly lower sensitivity to changes in time step size compared to the baseline weak coupling scheme. The modified weak coupling and strong coupling schemes perform comparably for the cases studied.

A comparative study of enhanced infrared image processing for foreign object detection in lightweight composite honeycomb structures - Zhang, Hai; Sfarra, Stefano; Genest, Marc; Ibarra-Castanedo, Clemente; Duan, Yuxia; Fernandes, Henrique; Avdelidis, Nicolas P.; Maldague, Xavier P. V. (International Journal of Thermophysics, 2018)
The interest toward lightweight composites in the aeronautical industry grows year by year. The challenge is the identification and characterization of defects by using an integration of different techniques. The use of the infrared thermography (IRT) method for the inspection of lightweight composites is poorly documented in the open literature, due to the low heat diffusion through the honeycomb cores. In this study, IRT was used to retrieve the unknown positions of internal inserted objects in three different lightweight composite structures, by using three new thermal image processing integration methods. The corresponding post-processed results were compared against the traditional principal component thermography and pulsed phase thermography image processing techniques. The comparison showed that the integrated signal smoothing processing enhanced the image quality compared to the established techniques. Then, a thermal-physical analysis corresponding to the experimental results was conducted, in order to explain the experimental results. Finally, the advantages and disadvantages of the different presented methods when applied on the different lightweight composite structures were summarized.
Keywords: composite; honeycomb; infrared; lightweight; NDT

A collaborative PHY-aided technique for end-to-end IoT device authentication - Hao, Peng; Wang, Xianbin; Shen, Weiming (IEEE Access, 2018)
Nowadays, Internet of Things (IoT) devices are rapidly proliferating to support a vast number of end-to-end (E2E) services and applications, which require reliable device authentication for E2E data security. However, most low-cost IoT end devices with limited computing resources have difficulties in executing the increasingly complicated cryptographic security protocols, resulting in increased vulnerability of the virtual authentication credentials to malicious cryptanalysis. An attacker possessing compromised credentials could be deemed legitimate by the conventional cryptography-based authentication. Although inherently robust to upper-layer unauthorized cryptanalysis, the device-to-device physical-layer (PHY) authentication is practically difficult to be applied to the E2E IoT scenario and to be integrated with the existing, well-established cryptography primitives without any conflict. This paper proposes an enhanced E2E IoT device authentication that achieves seamless integration of PHY security into traditional asymmetric cryptography-based authentication schemes. Exploiting the collaboration of several intermediate nodes (e.g., edge gateway, access point, and full-function device), multiple radio-frequency features of an IoT device can be estimated, quantized, and used in the proposed PHY identity-based cryptography for key protection. A closed-form expression of the generated PHY entropy is derived for measuring the security enhancement. The evaluation results of our cross-layer authentication demonstrate an elevated resistance to various computation-based impersonation attacks. Furthermore, the proposed method does not impose any extra implementation overhead on resource-constrained IoT devices.

A catalogue of dense cores and young stellar objects in the Lupus complex based on Herschel Gould Belt Survey observations - Benedettini, M.; Pezzuto, S.; Schisano, E.; André, P.; Könyves, V.; Men’shchikov, A.; Ladjelate, B.; Di Francesco, J.; Elia, D.; Arzoumanian, D.; Louvet, F.; Palmeirim, P.; et al. (Astronomy & Astrophysics, 2018)
Context. How the diffuse medium of molecular clouds condenses in dense cores and how many of these cores will evolve in protostars is still a poorly understood step of the star formation process. Much progress is being made in this field, thanks to the extensive imaging of star-forming regions carried out with the Herschel Space Observatory. Aims. The Herschel Gould Belt Survey key project mapped the bulk of nearby star-forming molecular clouds in five far-infrared bands with the aim of compiling complete census of prestellar cores and young, embedded protostars. From the complete sample of prestellar cores, we aim at defining the core mass function and studying its relationship with the stellar initial mass function. Young stellar objects (YSOs) with a residual circumstellar envelope are also detected. Methods. In this paper, we present the catalogue of the dense cores and YSOs/protostars extracted from the Herschel maps of the Lupus I, III, and IV molecular clouds. The physical properties of the detected objects were derived by fitting their spectral energy distributions. Results. A total of 532 dense cores, out of which 103 are presumably prestellar in nature, and 38 YSOs/protostars have been detected in the three clouds. Almost all the prestellar cores are associated with filaments against only about one third of the unbound cores and YSOs/protostars. Prestellar core candidates are found even in filaments that are on average thermally subcritical and over a background column density lower than that measured in other star-forming regions so far. The core mass function of the prestellar cores peaks between 0.2 and 0.3 M⊙, and it is compatible with the log-normal shape found in other regions. Herschel data reveal several, previously undetected, protostars and new candidates of Class 0 and Class II with transitional disks. We estimate the evolutionary status of the YSOs/protostars using two independent indicators: the α index and the fitting of the spectral energy distribution from near- to far-infrared wavelengths. For 70% of the objects, the evolutionary stages derived with the two methods are in agreement. Conclusions. Lupus is confirmed to be a very low-mass star-forming region, in terms of both the prestellar condensations and the diffuse medium. Noticeably, in the Lupus clouds we have found star formation activity associated with interstellar medium at low column density, usually quiescent in other (more massive) star-forming regions.
Keywords: clouds; ISM: individual objects: Lupus complex (except planetary nebulae); stars: formation; submillimeter: ISM

A bibliometric analysis of observatory publications for the period 2012-2016 - Crabtree, Dennis R.; Peck, Alison B.; Benn, Chris R.; Seaman, Robert L. (Observatory Operations: Strategies, Processes, and Systems VII, 2018)
This paper is a biennial update on the productivity and impact of observatory publications. The primary scientific output of a telescope is the collection of papers published in refereed journals based on data from that telescope. A telescope's productivity is measured by the number of papers published, while its scientific impact is the sum of each individual paper’s impact as measured quantitatively by the number of citations that the paper receives. The period covered by this paper ifor the years between 2012 and 2016.

A bibliometric analysis of observatory publications 2011-2015 - Crabtree, Dennis; Lesteven, S.; Kern, B.; D’abrusco, R.; Dorch, B. (EPJ Web of Conferences, 2018)
Bibliometrics are increasingly used as metrics to measure the performance of individuals, institutions and countries. Refereed publications are the primary output of modern observatories. In this paper, I use bibliometric techniques to examine the performance of astronomical observatories.

The impact of processing on the cytotoxicity of graphene oxide - Gies, Valerie; Lopinski, Gregory; Augustine, Jerry; Cheung, Timothy; Kodra, Oltion; Zou, Shan (Nanoscale Advances, 2018)
In-house prepared graphene oxide (GO) was processed via base washing, sonication, cleaning and combinations of these processing techniques to evaluate the impact on the flake morphology, composition and cytotoxicity of the material. The flakes of unprocessed GO were relatively planar, but upon base washing, the flakes became textured exhibiting many folds and creases observed by AFM. In addition to the pronounced effect on the topography, base washing increased the C/O ratio and increased the cytotoxicity of GO on all four cell lines studied determined via the WST-8 assay. Sonicating the unprocessed and base washed samples resulted in smaller flakes with a similar topography; the base washed flakes lost the texture previously observed upon sonication. The sonicated samples were more toxic than the unprocessed sample, attributed to the smaller flake size, but were interestingly less toxic than the base washed, unsonicated sample despite the base washed unsonicated sample having a larger flake size. This unexpected finding was confirmed by a second analyst using the same, and a different source of GO and resulted in the conclusion that the morphology of GO greatly impacts the cytotoxicity. Cleaning the GO reduced the amount of nitrogen and sulfur impurities in the sample but had no significant impact on the cytotoxicity of the material. It was observed that nutrient depletion via nanomaterial adsorption was not the route of cytotoxicity for the GO samples studied.

The Planck constant for the definition and realization of the kilogram - Wood, Barry; Bettin, Horst (Annalen der Physik, 2018)
On May 20, 2019 the values of the Planck, h, and Avogadro, NA, constants will be fixed, revising our measurement system, the International System of Units (SI), and providing a new way to get mass traceability. While the famous energy relations mc² and hf may remind many that the Planck constant is indeed related to mass, it is less recognized how this is also true for the Avogadro constant. These concepts are reviewed in the context of the upcoming revision of the SI. How the fixed values were chosen and how mass traceability will be maintained with the smallest uncertainty are also discussed.
yes
Keywords: Kibble balance; kilogram; Planck constant; revised SI; X-ray crstal density method

Frequency accuracy measurements for the microwave generator used in the Programmable Josephson Voltage Standard at NRC - Gertsvolf, M.; Granger, G. (2018 Conference on Precision Electromagnetic Measurements (CPEM 2018), 2018)
Standard frequency and time techniques are used to characterize the frequency accuracy of the commercial microwave generator used in the Programmable Josephson Voltage Standard at National Research Council Canada. Tests are also performed to verify the frequency resolution of the generator.
Keywords: frequency and time; frequency accuracy; phase offset; frequency resolution; microwave generator; Programmable Josephson Voltage Standard

NRC TimeLinkTM - Bernard, John; Charbonneau, Andre; Hoger, Bill; Pham, Hai; Gertsvolf, Marina (National Research Council Canada, 2018)
We present a system and service for traceable time dissemination of UTC(NRC) to users across Canada. The time synchronization is based on the GPS common-view method and we achieve uncertainties of nanoseconds, long holdover times and performance monitoring for jamming detection.
Keywords: traceable time; remote time dissemination

Calibration of gigahertz microwave generator for the programmable Josephson voltage standard at NRC - Gertsvolf, M.; Granger, G. (IEEE Transactions on Instrumentation and Measurement, 2018)
A frequency calibration method is developed to characterize the frequency accuracy of the commercial microwave generator (MWG) used in the programmable Josephson voltage standard at the National Research Council Canada. The approach allows the evaluation of the MWG performance at 9.2 and 18.4 GHz with fractional frequency uncertainty at 10¹⁴. The method also validates the MWG frequency resolution and setting accuracy from millihertz to megahertz to gigahertz.
yes
Keywords: Calibration; frequency measurement; microwave measurement; voltage measurement

Remote calibration of time from NTP servers - Douglas, Rob; Charbonneau, André; Gertsvolf, Marina (Metrologia, 2018)
The Network Time Protocol (NTP), is used for time synchronization in most networked equipment. Seen as capable of 50 ms accuracy or better, it lacks calibration for metrological traceability to its reference, Coordinated Universal Time (UTC). In response to client requests for traceability, the National Research Council (NRC) has begun to monitor NTP servers and document their traceability. We use an NTP calibrator at NRC to measure the time offset of a remote client's NTP server with respect to UTC(NRC). Standard NTP methods and systems are utilized, even for the NTP calibrator in the NRC Time Laboratory. The service aims at broad applicability rather than low uncertainty and can provide traceability to any networked computer that is configured as an NTP server. As with any calibration service, measurement results and the associated uncertainties are reported for each monitored NTP server for quality system records and auditing purposes, and we also make available near-real-time results and alerts.
Keywords: Network Time Protocol; traceability; remote calibration

Three certified sugar reference materials for carbon isotope delta measurements - Chartrand, Michelle M. G.; Meija, Juris; Kumkrong, Paramee; Mester, Zoltan (Rapid Communications in Mass Spectrometry, 2018)
For isotope delta analysis, it is preferable to have at least two matrix‐matched reference materials whose isotope delta values encompass those of the samples to be analyzed. The National Research Council Canada (NRC) has developed three sugar Certified Reference Materials (CRMs), BEET‐1 (beet sugar), GALT‐1 (galactose), and FRUT‐1 (fructose), to be collectively used for carbon isotope delta measurements in sugars, and other organic materials.

1 V AC-DC difference of a thermal transfer standard measured with a pulsed Josephson standard unloaded by a transconductance amplifier - Granger, G.; Budovsky, I. (2018 Conference on Precision Electromagnetic Measurements (CPEM 2018), 2018)
A transconductance amplifier (TCA) with a negative admittance has been used in parallel with a commercial thermal transfer standard (TTS) to unload the voltage source, a pulse-driven AC Josephson Voltage Standard (also known as Josephson Arbitrary Waveform Synthesizer or JAWS). AC-DC difference measurements at 1 V and at frequencies from 10 Hz to 10 kHz show excellent agreement with the values obtained by a conventional method. Expanded uncertainties between 0.28 µV/V and 0.39 µV/V (k=2), depending on the frequency, have been achieved.
Keywords: AC-DC difference; Josephson Arbitrary Waveform Synthesizer; Josephson Voltage Standard; pulsedriven; thermal transfer standard; transconductance amplifier

Investigation of cold spray on polymers by single particle impact experiments - Che, Hanqing; Vo, Phuong; Yue, Stephen (Journal of Thermal Spray Technology, 2018)
Cold spray has been proven to be a viable method for metallization of polymers and polymer composites, although it has been reported that the mechanism of cold spray on polymeric substrates is different from the mechanism on metallic substrates. In this work, single copper particle impact experiments were performed on polymeric substrates as well as mild steel. Two gas temperatures were selected for each polymer substrate, with one leading to a particle temperature above the glass transition temperature when reaching the substrate and the other below. The particle–substrate interactions on different substrates were analyzed. Based on the results, the mechanism of cold spray on polymeric substrates is discussed and compared to that on metallic substrates.
Keywords: cold spray; metallization of polymers; polymeric substrate; single particle impact

Design and physical model studies of innovative living breakwaters - Baker, Scott; Brashear, Pippa; Tschirky, Paul; Marrone, Joseph; Larson, Max (Proceedings of 36th Conference on Coastal Engineering, Baltimore, Maryland, 2018, 2018)
This paper describes two separate but closely related physical models conducted to support the detailed design of the Living Breakwaters project located in Raritan Bay, New York. One study focused on optimizing and verifying the breakwater design elements to ensure they were well adapted to typical and extreme conditions, while the second study focused on verifying the overall performance of multiple living breakwaters in terms of wave attenuation and impacts on nearshore wave-induced circulation. These investigations generated a large quantity of valuable information concerning the design and performance of the breakwaters that will be used to optimize and support the final design and obtain the necessary permits required for construction.
Keywords: rubble-mound breakwater; living breakwater; physical modeling

Kawenn´on:nis: the Wordmaker for Kanyen'k´eha - Kazantseva, Anna; Maracle, Owennatekha Brian; Maracle, Ronkwe’tiyóhstha Josiah; Pine, Aidan (Proceedings of the Workshop on Computational Modeling of Polysynthetic Languages, 2018)
In this paper we describe preliminary work on Kawenn´on:nis, a verb conjugator for Kanyen'k´eha (Ohsweken dialect). The project is the result of a collaboration between Onkwawenna Kentyohkwa Kanyen'k´eha immersion school and the Canadian National Research Council’s Indigenous Language Technology lab. The purpose of Kawenn´on:nis is to build on the educational successes of the Onkwawenna Kentyohkwa school and develop a tool that assists students in learning how to conjugate verbs in Kanyen'k´eha; a skill that is essential to mastering the language. Kawenn´on:nis is implemented with both web and mobile front-ends that communicate with an application programming interface that in turn communicates with a symbolic language model implemented as a finite state transducer. Eventually, it will serve as a foundation for several other applications for both Kanyen'k´eha and other Iroquoian languages.

Scalable collaborative filtering based on splitting-merging clustering algorithm - Belacel, Nabil; Durand, Guillaume; Leger, Serge; Bouchard, Cajetan (Agents and Artificial Intelligence, 2018)
Recommender systems apply information filtering technologies to identify a set of items that could be of interest to a user. Collaborative filtering (CF) is one of the most well-known successful filtering techniques in recommender systems and has been widely applied. However the usual CF techniques face issues that limit their application, especially in dealing with highly sparse and large-scale data. For instance, CF algorithms using the k-Nearest Neighbor approach are very efficient in filtering interesting items to users but in the same time they require a very expensive computation and grow non-linearly with the number of users and items in a database. To address this scalability issues, some researchers propose to use clustering methods. K-means is among the well-known clustering algorithms but has the shortcomings of dependency on the number of the clusters and on the initial centroids, which lead to inaccurate recommendations and increase computation time. In this paper, we will show by comparing with K-means based approaches how a clustering algorithm called K-means+ that considers the statistical nature of data can improve the performances of recommendation with reasonable computation time. The results presented that predictions of substantially better quality are obtained with the proposed K-means+ method. These results also provide significant evidences that the proposed Splitting-Merging clustering based CF is more scalable than the conventional one.
Keywords: recommender systems; collaborative filtering; information filtering; clustering; splitting-merging clustering

The infrared imaging spectrograph (IRIS) for TMT: electronics-cable architecture - Trapp, A. C.; Larkin, James; Magnone, Ken; Greffe, Timothee; Hardy, Tim; Dunn, Jennifer; Chisholm, Eric; Johnson, Chris; Suzuki, Ryuji (Ground-based and Airborne Instrumentation for Astronomy VII, 2018)
The InfraRed Imaging Spectrograph (IRIS) is a first-light instrument for the Thirty Meter Telescope (TMT). It combines a diffraction limited imager and an integral field spectrograph. This paper focuses on the electrical system of IRIS. With an instrument of the size and complexity of IRIS we face several electrical challenges. Many of the major controllers must be located directly on the cryostat to reduce cable lengths, and others require multiple bulkheads and must pass through a large cable wrap. Cooling and vibration due to the rotation of the instrument are also major challenges. We will present our selection of cables and connectors for both room temperature and cryogenic environments, packaging in the various cabinets and enclosures, and techniques for complex bulkheads including for large detectors at the cryostat wall.
Keywords: ELT: TMT; TMT: IRIS; cable architecture; electronics diagrams

Integrated transcriptome and hormone profiling highlight the role of multiple phytohormone pathways in wheat resistance against fusarium head blight - Wang, Lipu; Li, Qiang; Liu, Ziying; Surendra, Anu; Pan, Youlian; Li, Yifeng; Zaharia, L. Irina; Ouellet, Thérèse; Fobert, Pierre R. (PLOS ONE, 2018)
Fusarium head blight (FHB or scab) caused by Fusarium spp. is a destructive disease of wheat. Since the most effective sources of FHB resistance are typically associated with unfavorable agronomic traits, breeding commercial cultivars that combine desired agronomic traits and a high level of FHB resistance remains a considerable challenge. A better understanding of the molecular mechanisms governing FHB resistance will help to design more efficient and precise breeding strategies. Here, multiple molecular tools and assays were deployed to compare the resistant variety Sumai3 with three regionally adapted Canadian cultivars. Macroscopic and microscopic disease evaluation established the relative level of Type II FHB resistance of the four varieties and revealed that the F. graminearum infection process displayed substantial temporal differences among organs. The rachis was found to play a critical role in preventing F. graminearum spread within spikes. Large-scale, organ-specific RNA-seq at different times after F. graminearum infection demonstrated that diverse defense mechanisms were expressed faster and more intensely in the spikelet of resistant varieties. The roles of plant hormones during the interaction of wheat with F. graminearum was inferred based on the transcriptomic data obtained and the quantification of the major plant hormones. Salicylic acid and jasmonic acid were found to play predominantly positive roles in FHB resistance, whereas auxin and ABA were associated with susceptibility, and ethylene appeared to play a dual role during the interaction with F graminearum.

[INVITED] Subwavelength structures for silicon photonics biosensing - Wangüemert-Pérez, J. Gonzalo; Hadij-Elhouati, Abdelfettah; Sánchez-Postigo, Alejandro; Leuermann, Jonas; Xu, Dan-Xia; Cheben, Pavel; Ortega-Moñux, Alejandro; Halir, Robert; Molina-Fernández, Íñigo (Optics & Laser Technology, 2018)
Silicon photonic biosensors hold the potential for highly accurate, yet low cost point-of-care devices. Maximizing the sensitivity of the sensing chips while reducing the complexity and cost of the read-out system is pivotal to realize this potential. Here we present an extensive analysis, both from a practical and a theoretical perspective, of current biosensors, and analyze how subwavelength structures can be exploited to enhance their sensitivity. This study is not restricted just to the near-infrared band as we also determine the sensing capabilities of the suspended silicon waveguides with subwavelength metamaterial cladding working in the mid-infrared range. These waveguides have been recently proposed to cover the full transparency window of silicon ( λ<~8.5 μm), where the fingerprint spectral region of many molecules takes place and so a plethora of evanescent field absorption-based applications will be developed in the near future.
Keywords: subwavelength waveguides; silicon photonics; biosensors; coherent multi-port sensing architecture

Geospatial data for developing nutrient SPARROW models for the Midcontinental region of Canada and the United States - Vouk, Ivana; Burcher, Richard S.; Johnston, Craig M.; Jenkinson, R. Wayne; Saad, David A.; Gaiot, John S.; Benoy, Glenn A.; Robertson, Dale M.; Laitta, Michael (Technical Report (National Research Council Canada. Ocean, Coastal and River Engineering); OCRE-TR-2018-014, 2018)
Through the International Watersheds Initiative of the International Joint Commission (IJC), the Spatially-Referenced Regressions on Watershed attributes (SPARROW) model developed by the U.S. Geological Survey (USGS) is being applied to the Great Lakes, Rainy River – Lake of the Woods and Red-Assiniboine basins. The objective of this binational application of the SPARROW model is to better understand and quantify the sources of phosphorus (P) and nitrogen (N) that contribute to regional water quality issues like algal blooms and eutrophication in Lake Erie and other parts of the Great Lakes, as well as Lake of the Woods. Led by the IJC, a team of researchers from the National Research Council of Canada – Ocean, Coastal and River Engineering Research Centre, USGS, and IJC are extending the SPARROW modelling work previously completed for the Red-Assiniboine basin and the U.S. portions of the Great Lakes, Ohio, Upper Mississippi, and Souris-Red-Rainy river basins to cover all of the Great Lakes, Rainy River – Lake of the Woods and Red-Assiniboine basins. The current effort is termed the Midcontinent SPARROW modelling study. This report describes the data used to develop the Midcontinent SPARROW models, specifically the sources of original data, assembling the data, and the processing and harmonization required between the U.S. and Canada data needed to produce these models. Details provided include the: • development of a digital stream network and related catchments – most significantly in the Canadian regions of the Great Lakes and Rainy River – Lake of the Woods basins where these data were not available to create a seamless binational network across the model domain; • calculation of variables to aid in the determination of in-stream and in-reservoir decay of P and N; • quantification of Canadian diversions within the Midcontinental region (i.e., Lake St. Joseph, Long Lake and the Ogoki Reservoir); • development of binational input nutrient sources considered for model development (i.e., land cover, inorganic farm fertilizer, manure, atmospheric deposition, point source pollution from wastewater treatment plants and contribution from non-modelled watersheds); and • development of delivery variables considered to be most predominant (i.e., temperature, precipitation and ensuing runoff, soil permeability and clay content, slope of the catchments, and tile drainage). The majority of the geospatial data collection and processing was required for Canadian datasets because many of the U.S. datasets were already assembled for previous SPARROW model applications in the U.S. The task of harmonizing data between the U.S. and Canada was important to ensure consistency of the datasets used in the models. The harmonized digital stream network, delineated catchments and input data for each catchment (i.e., source and delivery variables), created for the Midcontinent SPARROW models, are available for download at url https://doi.org/10.4224/300.0001
This publication describes the development of this dataset : (2018) Binational dataset used to develop nutrient SPARROW models for the Midcontinental region of Canada and the United States. National Research Council Canada
Cette publication décrit le développement de l'ensemble de données suivant : (2018) Binational dataset used to develop nutrient SPARROW models for the Midcontinental region of Canada and the United States. National Research Council Canada

Bioinformatics identification of drug gene modules: application to clear cell carcinoma of the ovary - Tchagang, Alain B. (2018 40th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC), 2018)
Targeted therapy is a treatment that targets the cancer's specific genes, proteins, or the tissue environment that contributes to cancer growth and survival. Identification of therapeutics targets is a very challenging problem in bioinformatics. An integrative and iterative approach for the identification of drug-gene modules (i.e., groups of genes and drugs such that genes in the same module may regulate each other and are targets of some of the drugs in the same module) is developed. Application to clear cell carcinoma of the ovary data reveals several drug-gene modules and a target network that may play important roles in treating this disease.

Direct mineralogical imaging of economic ore and rock samples with multi-modal nonlinear optical microscopy - Kao, Mung-Chung; Pegoraro, Adrian F.; Kingston, David M.; Stolow, Albert; Kuo, Wen-Chuan; Mercier, Patrick H. J.; Gogoi, Ankur; Kao, Fu-Jen; Ridsdale, Andrew (Scientific Reports, 2018)
Multi-modal nonlinear optical (NLO) microscopy, including stimulated Raman scattering (SRS) and second harmonic generation (SHG), was used to directly image mineralogical features of economic ore and rock samples. In SRS/SHG imaging, ore samples generally require minimal preparation and may be rapidly imaged, even in their wet state. 3D structural details, at submicron resolution, are revealed tens of microns deep within samples. Standard mineral imaging based on scanning electron microscopy (SEM), with elemental analysis via energy dispersive X-Ray spectroscopy, was used to independently validate the mineral composition of the samples. Spatially-resolved SRS from dominant Raman-resonant bands precisely maps the locations of specific minerals contained within the samples. SHG imaging reveals locally non-centrosymmetric structures, such as quartz grains. Competing absorption and nonlinear scattering processes, however, can reduce contrast in SRS imaging. Importantly, the correlation between standard electron microscopy and multi-modal NLO optical microscopy shows that the latter offers rapid image contrast based on the mineral content of the sample.

SNAP RTM: a cost-effective compression RTM variant to manufacture composite component for transportation applications - Khoun, Loleï; Trudeau, Paul (Society of Plastics Engineers. Automotive Division, 2018)
The Corporate Fuel Average Efficiency (CAFÉ) regulation requires average fuel consumption of cars to increase from 37.8 mpg (6.2 L/100 km) to 54.5 mpg (4.3 L/100 km) by 2025. One solution to help reach this target is vehicle lightweighting. As a reference, a 10% reduction in vehicle weight can result in a 5 – 8% reduction of fuel consumption. Among the lightweight material alternatives, fibre reinforced composite materials are believed to enable car body-weight reductions of 25% to 50%, weight reduction that cannot be obtained with lightweight metals alone. From an industrial point of view, process cycle time and cost are the main barriers to a wider use of fibre reinforced composites in mass produced vehicles, as current high performance composite manufacturing processes do not meet the 2 to 5 minutes cycle time desired by the transportation industry for the production of large series components. In order to benefit from the performance of advanced composites needed to achieve significant reductions in vehicle weight, it is then necessary to develop rapid and cost-effective processing techniques adapted to these materials. In recent years, material suppliers have been reducing the cure time required for thermoset resins that have helped to shorten cycle times targeted by the automotive industry. Among the manufacturing technologies available to produce high performance composites parts, liquid moulding technologies appear to have some potential to successfully introduce those rapid cure resin systems at faster production rates. In this study, a cost effective variant of the Compression-RTM process has been developed to manufacture high performance composite plaques. The injection and compression parameters were studied and compared to traditional RTM moulding: cycle time, part quality and part mechanical performance. Results validated the use of low cost / low pressure injection equipment combined with a static mix head and innovative tool design to manufacture composite plaques within cycle times targeted by the transportation industry.

Performance assessment of protective thermal spray coatings for lightweight Al brake rotor disks - Poirier, Dominique; Legoux, Jean-Gabriel; Irissou, Eric; Gallant, Danick; Jiang, Jimmy; Potter, Tim; Boileau, James (Journal of Thermal Spray Technology, 2018)
This paper presents the results of a study to evaluate stainless steel thermal spray coatings on aluminum-based substrates. Coating wear, corrosion, and thermal cycling resistance were evaluated using pin-on-disk, cyclic corrosion, and a custom laser-based heating system, respectively, for 300-series stainless steel coatings deposited by arc-sprayed and cold-sprayed systems. Arc spray coatings were found to have equivalent wear and frictional performance as compared to gray cast iron (wear rates of 0.730-1.524 versus 1.294 × 10−5 mm3/m, COF of 0.35-0.36 versus 0.36). However, arc spray coating exhibited low adhesion (~ 30 MPa) and early spalling under thermal cycling conditions, i.e., < 600 cycles, as well as corrosion and delamination. The cold-sprayed coatings were found to have high corrosion and thermal cycling resistance, i.e., above 10,000 cycles. However, cold-sprayed coatings exhibited wear rates higher than those of the cast iron (cold spray wear rates of 4.774 × 10−5 mm3/m). A duplex coating composed of a cold-sprayed bond coat and an arc-sprayed top coat was created and showed good wear properties under simulated extreme braking conditions. The results from this study show that stainless steel coatings on aluminum substrates could be viable substitute for the cast iron in future brake rotors.
Keywords: automotive applications; cold spray; corrosion; cyclic heating; wear

Influence of substrate characteristics on single Ti splat bonding to ceramic substrates by cold spray - Imbriglio, Sara I.; Brodusch, Nicolas; Aghasibeig, Maniya; Gauvin, Raynald; Chromik, Richard R. (Journal of Thermal Spray Technology, 2018)
The cold spray technique may be used to fabricate metal matrix composites and to metallize ceramics. Both applications involve the creation of metal/ceramic interfaces, which are well researched for other processes but not nearly as much for cold spray. Here, the effect of ceramic substrate composition and surface roughness on adhesion strength of metallic splats is investigated. Splat adhesion testing was performed on Ti splats deposited on Al2O3 substrates with varying average reduced peak height roughness (Rpk) values. Ti splats sprayed onto Al2O3 with the lowest surface roughness had a higher bond strength (305 ± 87 MPa) than splats deposited on the higher surface roughness Al2O3 (237 ± 47 MPa). Failed interfaces revealed that the bonding mechanism for substrates with higher surface roughness is predominantly mechanical interlocking. Adhesion to the Al2O3 substrate with low surface roughness is predominantly along the periphery of the particle where jetting occurs. Splat adhesion testing was also performed on Ti splats deposited on SiC. Ti splats had a significantly higher bond strength to all Al2O3 substrates than to SiC. Posttest observations of SiC substrates showed little evidence of bonding. Several rebounded or detached splats left traces of Ti along the periphery of the impacted particle.
Keywords: adhesion; alumina; cold spray; interface; silicon carbide; titanium

A large scale study of blast effects from a structural reactive material solid under explosive loading - Zhang, Fan; Yoshinaka, Akio; Gauthier, Maxime; Cojocaru, Cristian V.; Ripley, Robert C. (JHU WSE Energetics Research Group, 2018)
A structural reactive material (SRM) is made by consolidating a mixture of micro- or nanometric reactive metals and metal compounds to the theoretical maximum density (TMD). A SRM can thus possess a higher energy density, relying on various exothermic reactions, and higher mechanical strength and heat resistance than that of conventional CHNO explosives. Small scale studies of a SRM solid have made progresses specifically to explore it as an energy source for air blast through reaction of fine SRM fragments under explosive loading. These subscale studies comprised a large number of experiments, whereby explosives were encased in a thick-walled SRM solid cylindrical shell with diameters ranging from 40 mm to 100 mm and explosive masses from 100 g to 1.2 kg, using different formulations to provide a variety of detonation pressures and resulting in a SRM casing-to-explosive mass ratio up to M/C = 1.8 [1]. These studies laid the foundation for the next stage of developments, including basic SRM solid explosion characterization, material properties of a SRM solid, and its dynamic fine fragmentation mechanisms and fragment reaction mechanisms.
Keywords: structural reactive material; reactive material; intermetallics; thermite; metal Combustion; blast; reactive fragment

Meshfree numerical simulation of hybrid friction stir welding with adhesive bonding - Fraser, Kirk; Nadeau, F.; Noormohammed, Saleema; Kiss, Laszlo; St-Georges, L. (Proceedings of the 12th International Symposium on FSW, 2018)
As interest for lightweight vehicles continues to increase, there has been significant progress in the development of hybrid joining approaches. A process that has been gaining interest is friction stir welding combined with adhesive bonding (FSW-AB). In the FSW-AB process, a lap joint is prepared with an uncured adhesive over the entire overlap region. Following the application of the adhesive, the FSW process is performed. Using this hybrid method can lead to improved joint strength as well as increased fatigue resistance. Furthermore, the adhesive acts as a sealant and protect the FSW joint from corrosion. Certainly the method is attractive; however, there are joint design aspects that must be considered such as the thermal degradation of the adhesive and the effect of the adhesive transport in the friction stir weld zone. In this work, a meshfree coupled thermo-mechanical simulation of the FSW-AB process is performed using SPHriction-3D. The set of continuum mechanics equations describing the physics of the FSW-AB process are cast into an amenable set of algebraic equations using a weak-strong form approach called smoothed particle hydrodynamics (SPH). This approach uses a Lagrangian frame of reference, making it ideal for predicting the movement and thermal history of the adhesive layer during the FSW process. Experimental results along with adhesive degradation profiles and infrared spectroscopy are compared to the simulation results. The article will focus on details of the meshfree simulation method as well as comparison between the simulation and experimental results. We will show that the numerical model is able to predict the extent and location of the adhesive degradation. Ultimately, the developed simulation approach is a powerful design tool for advanced hybrid joining methods such as the FSW-AB process.
Keywords: friction stir welding; adhesive bonding; meshfree simulation; coupled thermo-mechanic; SPHriction-3D

Development of a phenomenological equation to predict tool wear in friction stir welding by steel grades in Al/Steel lap joining - Tremblay, F.; Nadeau, F.; St-Georges, L. (Proceedings of the 12th International Symposium on FSW, 2018)
Since its introduction in the industry, the amount of structures being joined by friction stir welding (FSW) are in progression. Even if low-melting point materials such as aluminium or magnesium represents the highest number of applications, this method can also successfully join materials with different melting point as in the case of aluminium to steel. As lightweigthing structures gained ground in the last few years and will still continue to grow, joining processes combining aluminium to steel effectively need to be developed further. When it comes down to join aluminium to steel, the most common configuration is lap joint which the FSW pin enters into the bottom sheet substrate, thus the steel material. In order to have a FSW tool that lasts a sufficient amount of time, the material needs to sustain high stresses and temperatures and still be affordable, such as WC-based tools. The wear rate of the tool used during the process needs to be known and understood as it dictates the applicability of the FSW method depending of the application. As an example, the sub-frame assembly of the Honda Accord 2013 is joined using aluminium to steel FSW lap joining. Be able to predict when the tool reaches a point where it is no longer effective to produce a sound weld can certainly help to evaluate tool life. Actually, a few papers have produced a series of equations or processes that can predict material losses but they are constraints at the application designed for and will be presented further. This study will assess FSW tool life prediction upon different material configurations, mainly steel grades as it impacts greatly the wear behavior of the tool.

BlowView software to simulate blow molding processes - Benrabah, Z. (ITB 2018: Plastic Powertrain Part 2018, 2018)
BlowView is an engineering 2.5D finite element simulation software, developed at NRC, dedicated to simulate a conventional extrusion blow molding, twin-sheet extrusion blow molding, suction blow molding, stretch blow molding and thermoforming processes. This versatile blow molding simulation software is highly automated, flexible and user-friendly, yet allows users in-depth analysis capabilities for a wide range of materials, including warpage, optimization and permeability. The latest functionalities and capabilities of the software will be highlighted on blow molded automotive parts.

Cold spraying of mixed Sn-Al powders onto carbon fibre reinforced polymers - Liberati, Andre; Che, Hanqing; Yue, Stephen; Vo, Phuong (Proceedings of International Thermal Spray Conference 2018, 2018)
Pure metal coatings have successfully been cold sprayed on Carbon Fibre Reinforced Polymers (CFRPs) in previous studies at McGill University. As a means to improve coating conductivity for lightning-strike protection (LSP) purposes, coatings with mixed elements were tested. The studied coatings were based on a mix of tin powder and aluminum, a metal commonly used in the aerospace industry for its lightweight properties. The different coatings were characterized and compared to results on pure tin coatings. The deposition efficiency (DE) and the conductivity were measured for different conditions and compared to those of pure tin coatings. Based on the results, mixing tin and aluminium powders is discussed and various mechanisms related to cold spraying mixed powders on polymers are explored.

Investigation of cold spray on polymers by single particle impact experiments - Che, Hanqing; Vo, Phuong; Yue, Stephen ([Proceedings of International Thermal Spray Conference 2018], 2018)
Cold spray has been proved a viable method for metallization of polymers and polymer composites. It has been reported that the mechanism of cold spray on polymeric substrates is different from the conventional mechanism on metallic substrates (i.e. adiabatic shear instability). In this work, single particle impact experiments were performed on polymeric substrates as well as mild steel. The particle-substrate interactions on different substrates were analyzed. Based on the results, the mechanism of cold spray on polymeric substrates is discussed and compared to that on metallic substrates.
Keywords: cold spray; metallization of polymers; polymeric substrate; single particle impact

Effects of feedstock mixing composition on the cold sprayability of bimodal size 316L/Fe powder mixtures - Chu, Xin; Che, Hanqing; Yue, Stephen; Vo, Phuong (Proceedings of International Thermal Spray Conference 2018, 2018)
In this study, a 43 μm 316L stainless steel and a 23 μm commercial purity Fe feedstocks were used. The following coatings were made by cold spray: single component 316L, Fe, and their binary composites with nominal compositions of 20 wt.% Fe (20Fe), 50 wt.% Fe (50Fe) and 80 wt.% Fe (80Fe). The coatings were characterized (microstructure, flattening ratio, composition) and the cold sprayability metrics (DE, porosity, bond strength) were analyzed. Results show that the single component 316L coating has a much better DE and bond strength, and a slightly lower porosity as compared with the Fe coating. Whereas all the composite coatings have the similar bond strength. Moreover, the 20Fe coating features the highest porosity and the lowest DE; 50Fe coating features the lowest porosity; and the 80Fe coating features the highest DE. To indicate the feedstock mixture composition, in addition to the routine approach such as weight or volume fraction, the particle number ratio of the large/small components, which is defined as the ratio of the numbers of the component particles in a mixture estimated by the mean particle size, was calculated. Using this metric, the effects of the feedstock mixing composition on the cold sprayability of bimodal size 316L/Fe powder mixtures can be better explained.

Fire safety of CLT buildings in Canada - Su, Joseph (Wood and Fiber Science, 2018)
This article provides an overview of the code requirements pertinent to large cross-laminated timber (CLT) buildings and the methods for meeting the requirements in Canada. Canadian building codes are objective-based. Compliance with the code is achieved by directly applying the acceptable solutions up to certain prescriptive building sizes (height and area) or by developing alternative solutions beyond the height and area limits. The fire safety design for a CLT building larger than the prescriptive limit must demonstrate that the building will achieve at least the minimum level of performance afforded by noncombustible construction in limiting the structural involvement in fire and contribution to the growth and spread of fire during the time required for occupant evacuation and emergency responses.
Keywords: cross-laminated timber; building fire safety and protection; fire resistance; performance based design; alternative solution

Fire safety challenges of tall wood buildings. Phase 2: Task 2 & 3: cross laminated - Su, Joseph; Lafrance, Pier-Simon; Hoehler, Matthew; Bundy, Matthew (National Research Council Canada. Construction, 2018)
The Fire Protection Research Foundation (FPRF) initiated the project “Fire Safety Challenges of Tall Wood Buildings - Phase 2” to address the need for evaluating the contribution of mass timber elements to compartment fires. In part, this is linked to the concern that timber elements in tall wood buildings could increase the fire load, affect the fire growth rate, and potentially compromise fire protection systems in buildings, all of which could result in more severe conditions for occupants and responding fire fighters and increase the threat of damage to the property and adjacent properties. This project aimed to quantify the contribution of cross laminated timber (CLT) building elements to compartment fires, and to characterize the fire protection of the CLT structural elements using physical barrier (e.g., gypsum board) for delaying or preventing their involvement in the fire.
Keywords: tall wood buildings; fire safety; tall timber; cross laminated timber; CLT; compartment fire; fire test

Demand control of baseboard heaters: lessons learned from 50-home pilot study - Pardasani, Ajit; Veitch, Jennifer A.; Newsham, Guy R.; Hu, Yitian; Cormier, Terrance; Hull, Sonya (Proceedings: IEEE Canada Electrical Power and Energy Conference (EPEC 2018), 2018)
This paper presents results from a pilot study in 50 occupied homes in Fredericton, New Brunswick, Canada to evaluate a demand response (DR) strategy applied to residential electric baseboard heating loads. The underlying principle is based on storing electricity as thermal energy in the building envelope and household contents before the grid peak demand period, and then discharging that stored energy to maintain conditions for thermal comfort during the peak period. During January and February 2016, a total of 13 DR interventions were executed. This field test showed that a load shift up to a maximum of 3.4 kW, with an average of 1.4 kW, per household was possible for the first hour, depending on the outdoor temperature. We observed a large variation in load shift between homes, partly depending on the thermostat set-point profiles, building and occupant characteristics. The approach holds significant potential for shifting peak loads in locations where electricity is a major source of energy for space heating.
Keywords: demand response; electrical thermal storage; load shift; space heating; smart thermostats

Enhanced anti-metastatic bioactivity of an IGF-TRAP re-engineered to improve physicochemical properties - Vaniotis, George; Moffett, Serge; Sulea, Traian; Wang, Ni; Elahi, S. Mehdy; Lessard, Etienne; Baardsnes, Jason; Perrino, Stephanie; Durocher, Yves; Frystyk, Jan; Massie, Bernard; Brodt, Pnina (Scientific Reports, 2018)
The insulin-like growth factor (IGF) axis has been implicated in the progression of malignant disease and identified as a clinically important therapeutic target. Several IGF-1 receptor (IGF-1R) targeting drugs including humanized monoclonal antibodies have advanced to phase II/III clinical trials, but to date, have not progressed to clinical use, due, at least in part, to interference with insulin receptor signalling. We previously reported on the production of a soluble fusion protein consisting of the extracellular domain of human IGF-1R fused to the Fc portion of human IgG1 (first generation IGF-TRAP) that bound human IGF-1 and IGF-2 with a 3 log higher affinity than insulin. We showed that the IGF-TRAP had potent anti-cancer activity in several pre-clinical models of aggressive carcinomas. Here we report on the re-engineering of the IGF-TRAP with the aim of improving physicochemical properties and suitability for clinical applications. We show that cysteine-serine substitutions in the Fc hinge region of IGF-TRAP eliminated high-molecular-weight oligomerized species, while a further addition of a flexible linker, not only improved the pharmacokinetic profile, but also enhanced the therapeutic profile of the IGF-TRAP, as evaluated in an experimental colon carcinoma metastasis model. Dose-response profiles of the modified IGF-TRAPs correlated with their bio-availability profiles, as measured by the IGF kinase-receptor-activation (KIRA) assay, providing a novel, surrogate biomarker for drug efficacy. This study provides a compelling example of structure-based re-engineering of Fc-fusion-based biologics for better manufacturability that also significantly improved pharmacological parameters. It identifies the re-engineered IGF-TRAP as a potent anti-cancer therapeutic.

Numerical modelling of complex parison and sheet formation in blow molding processes using BlowView Software - Bardetti, Anna; Benrabah, Zohir; Atsbha, Haile (ANTEC 2018 Conference Proceedings, 2018)
BlowView is an engineering 2.5D finite element simulation software, developed at NRC, dedicated to simulate conventional extrusion blow molding, twin-sheet extrusion blow molding, stretch blow molding and thermoforming processes. This versatile blow molding simulation software is highly automated, flexible and user-friendly, yet allows users in-depth analysis capabilities for a wide range of materials, including optimization and permeability. Extrusion blow molding, and twin-sheet extrusion blow molding, are extensively used in manufacturing automotive plastic fuel tanks (PFT). These processes consist of three main phases: parison/sheet formation, inflation and part cooling and solidification. The parison/sheet formation is the most critical stage, as the final dimensions and mechanical performance of the PFT is directly related to the initial extrudate shape, which often requires the use of advanced die shaping technologies such as: Vertical Wall Distribution System (VWDS), Partial Wall Distribution System (PWDS), Die Slide Motion (DSM), and/or a combination of all three. These technologies are all available in the BlowView software, and can be handled simultaniously and synchronized with the machine programming points. In order to predict the extrusion with sag and swell, BlowView uses a hybrid approach that couples fluid mechanics to represent the die flow, with solid mechanics to represent the parison/sheet behavior outside the die, and a phenomenological swell model to capture the die geometry effect. This approach permits avoiding instability issues encountered by traditional fluid mechanics, especially at high Weissenberg numbers. After extrusion, the parison/sheet inflation is predicted tacking into account all mold components and their respective position and displacements. The modelling capabilities of NRC’s BlowView software will be presented based on using an industrial case study of a PFT. Permeability and optimization results will be also illustrated.

Investigation on the fatigue fracture characteristics between friction-stir welded aluminium overlap joints with different alloys and tools - Gariépy, Alexandre; Nadeau, François; Gambou-Bosca, Axel; Grégoire, Hélène (Proceedings of the 12th International Symposium on FSW, 2018)
In this study, overlap FSW joints were prepared using various aluminium alloys and tool shapes and tested in single-lap shear fatigue. Such configurations could be used in automotive applications. While all tests resulted in fracture by crack propagation through the upper sheet, performance differences appeared between alloys and tools. The objective is to understand the different fatigue strengths for a subset of aluminium alloys (5083SPF and 7075-T6) and tools (MX Triflute ® and Flared Whisk Triflute ®). The fatigue failure modes are investigated using a combination of experimental and numerical methods to establish process-microstructure-properties correlations, highlight key differences for the subset of alloys and tools under study, and identify favourable factors for fatigue performance.
Keywords: overlap joint; aluminium alloys; tool shape; fatigue

Towards a parallel multiphysics model for phase change in enclosed geometries - Blais, Bruno; Ilinca, Florin (Parallel CFD, 2018)
We present a novel finite element model for the simulation of free surfaces flows of fluids undergoing phase change (melting or freezing) in enclosed geometries. The modeling complexities arising from the modeling of phase change are discussed and the extended stabilized finite element approach chosen to tackle this issue is presented. The proposed model is first verified on simplified geometry before it is applied to the study of phase change in complex 3D geometries using unstructured meshes.
Keywords: stabilized finite element method; free surface flows; melting and freezing; adaptive domain decomposition; natural convection

Cold spray additive manufacturing fabrication of hard and soft magnetic materials - Lamarre, Jean-Michel; Bernier, Fabrice (ASM International, 2018)
Manufacturing increasingly complex parts featuring advanced functionalities while reducing costs is a challenge for all industries. Automotive electric motor fabrication is no exception as high performance magnetic materials need to be shaped and installed into complex assemblies. Current fabrication procedures severely limit the design flexibility as magnetic materials are typically difficult to machine and manipulate. In this work, we will describe the use of cold spray additive manufacturing for the low-cost direct shaping of hard and soft magnetic materials on electric motor parts without the need for additional assembly steps. Combination of sprayed soft and hard magnetic materials opens up the possibilities for innovative designs leading to performance gain and cost savings. The role of the process parameters such as the gas temperature as well as the powder composition, size distribution and morphology on the magnetic properties is discussed. The use of robot toolpath programming necessary to spray on motor parts is illustrated by different examples of complex shape prototypes. Use of soft and hard magnetic materials for the realization of motor prototypes is shown, thus demonstrating the feasibility of using cold spray additive manufacturing as an effective technology to fabricate motor parts.

Numerical simulation of shrinkage and warpage deformation of an intermittent-extrusion blow molded part: validation case study - Benrabah, Z.; Bardetti, A.; Ilinca, F.; Ward, G. (ANTECH 2018 Conference Proceedings, 2018)
Intermittent extrusion blow molding is increasingly being used in polymer forming processes for the production of complex thermoplastic industrial parts with short cycle times. During this process residual stresses caused by inhomogeneous cooling and relaxation of polymer chains, often result in shrinkage and warpage of the final part. One challenging quality requirement of industrial blow molded parts is geometric tolerances. Therefore part deformation, due to cooling and solidification, needs to be controlled and optimized according to specific design criteria. In particular, the complex design shapes of plastic fuel tank (PFT) shells exacerbate these challenges which need to be resolved upfront, in the early stages of product development and tool design. Consequently, the development of an accurate simulation tool, well suited for industrial applications, to predict thermoplastic part deformations due to cooling and solidification, has become essential for part designers to help achieve an efficient production with minimum manufacturing cost. The aim of this work is to present the latest advancements in predicting the shrinkage and warpage deformation of a curved PFT, designed for agricultural machinery, using NRC’s BlowView software. This case study validation considers the entire blow molding stages (i.e., polymer flow in the die, parison formation, inflation, and finally in and out of mold cooling during part solidification). The simulation results, in terms of thickness distribution and displacements, are compared to an actual scanned part using the best fit technique in order to exemplify the accuracy and reliability of the modelling approach.

A preliminary study on text mining operator logbooks to develop a fault-frequency model - Gunay, H Burak; Yang, Chunsheng; Shi, Zixiao; Shen, Weiming; Huchuk, Brent (ASHRAE transactions, 2018)
Textual data in operator logbooks represent an untapped opportunity to retrieve information about the maintenance routines of HVAC equipment and control infrastructure. This paper presents a case study in which seven years' worth of work order logs from 44 buildings on a university campus were analyzed. After extracting HVAC-related terms such as fan, AHU, VAV, stuck, and leak from custom operator descriptions, the apriori algorithm was used to derive association rules that define the coexistence tendencies of the terms in a work order (e.g., coexistence of the terms radiator and leak). Based on this analysis, a preliminary HVAC work order frequency model was put forward. The results indicate that the annual work order intensity per 1000 m2 (10,764 ft2) was about 4. More than 70% of the HVAC-related work orders were issued to address zone-level problems. Among the AHU-level work orders issued for a physical subcomponent, more than 90% were related to fans. Future work is planned to analyze the HVAC-related work order patterns with numeric data from automation and controls networks.
Keywords: buildings; energy efficiency; operations; optimization

Data analytics to improve building performance: a critical review - Burak gunay, H.; Shen, Weiming; Newsham, Guy (Automation in Construction, 2018)
The data inherent in building automation systems, computerized maintenance management systems, security and access control systems, and IT networks represent an untapped opportunity to improve the operation and maintenance (O&M) of buildings. This paper reports the findings of a critical review of the literature regarding the use of data analytics in building O&M applications, and a two-day stakeholder's workshop titled Big Data in Building Operations. Building on the discussions at the workshop and the literature survey, the current state of the O&M related decision-making process was identified: the data availability in existing buildings was discussed; the challenges related with accessing and processing these datasets were examined; and emerging sensing technologies were presented. Further, the research fields applying data analytics in O&M were introduced, the barriers to their widespread use in practice were discussed, future work recommendations were developed; and the need for semantic models of O&M data and comprehensive open O&M datasets was identified for the development and assessment of data analytics-driven energy and comfort management algorithms.
Keywords: building operation and maintenance; data analytics; building automation systems; computerized maintenance management systems

Three-dimensional numerical model development for the investigation of the gas jet wiping process on the flow behaviors near the galvanizing bath surface - Yu, K. R.; Ilinca, F.; Blais, B.; Goodwin, F. E. (2018 AISTech Conference Proceedings, 2018)
In continuous galvanizing bath operations, the thickness and the uniformity of the zinc coating are strongly influenced by the gas jet wiping process which aims to remove the excess liquid zinc adhered to the steel strip as it emerges from the bath. This work describes the development process of a three-dimensional numerical model which aims to consider the moving strip, the turbulent jet, and their complex interactions with the falling excess liquid zinc. Such model would be highly valuable to advance the fundamental understanding of the complex flow behaviors near the bath surface.
Keywords: gas jet wiping; continuous galvanizing bath; numerical modeling

Microstructural characterization and room-temperature erosion behavior of as-deposited SPS, EB-PVD and APS YSZ-based TBCs - Lima, Rogerio S.; Guerreiro, Bruno M. H.; Aghasibeig, Maniya (Journal of Thermal Spray Technology, 2018)
The erosion behavior at room temperature of as-deposited suspension plasma spray (SPS), electron beam physical vapor deposition (EB-PVD) and air plasma spray (APS) ZrO2-Y2O3 (YSZ)-based TBCs was investigated. All coatings were deposited on Inconel 625 alloy coupons. The same APS CoNiCrAlY bond coat was employed for all SPS and APS TBCs. The erodent material was 50-µm alumina, and the impact angles were 15° and 90°. A total of 4 different types of SPS YSZ-based TBCs were tested, which consisted of two distinct columnar-segmented and two distinct columnar-grown microstructures. The EB-PVD and APS YSZ TBCs were employed as benchmarks. The erosion performance of the different TBCs in this study was ranked based on the coating volume loss after wear testing. The TBC microstructures and phase compositions were evaluated via scanning electron microscopy and X-ray diffraction. The erosion mechanisms of the different TBCs were compared by analyzing the cross-sectional and top surface microstructures of the as-deposited and eroded TBCs. These are released results from the Surftec Industrial R&D Group of the National Research Council of Canada.
Keywords: APS; EB-PVD; erosion; SPS; TBC; YSZ

Development of protective thermal spray coatings for lightweight Al brake rotor discs - Poirier, Dominique; Legoux, Jean-Gabriel; Irissou, Eric; Gallant, Danick; Jiang, Jimmy (The Conference, 2018)
This paper reports on the performance evaluation of stainless steel (SS) thermal spray coatings aimed at shielding lightweight aluminum (Al) brake rotor disks from excessive heat and providing an adequate tribological surface in contact with brake pads. Coating wear, corrosion and heat resistance performances were evaluated using pin-on-disk, cyclic corrosion tests and thermal cycling using a custom laser rig, respectively. Arc spray optimized coatings displayed lower or equivalent wear rates when compared with the baseline gray cast iron disks, with similar frictional behavior. However, arc spray coating exhibited low adhesion which limits the maximum coating thicknesses achievable and leads to early coating spalling after about 1000 thermal cycles. Arc sprayed coatings also corroded and delaminated under corrosion tests. Optimized cold spray coatings present high corrosion resistance and could resist above 10,000 thermal cycles without spalling. However, cold spray coatings exhibit wear rates at least 4 times those of the cast iron. Taking advantage of both types of coatings, it was found that the production of a duplex coating made of a cold spray bond coat and an arc spray top coat could meet the requirements for protecting Al disks, with near 50% weight reduction.

Camelid single-domain antibodies raised by DNA immunization are potent inhibitors of EGFR signaling - Rossotti, Martin A.; Henry, Kevin A.; Van Faassen, Henk; Tanha, Jamshid; Callaghan, Deborah; Hussack, Greg; Arbabi-Ghahroudi, Mehdi; Mackenzie, C. Roger (Biochemical Journal, 2018)
Upregulation of epidermal growth factor receptor (EGFR) is a hallmark of many solid tumors, and inhibition of EGFR signaling by small molecules and antibodies has clear clinical benefit. Here, we report the isolation and functional characterization of novel camelid single-domain antibodies (sdAbs or VHHs) directed against human EGFR. The source of these VHHs was a llama immunized with cDNA encoding human EGFR ectodomain alone (no protein or cell boost), which is notable in that genetic immunization of large, outbred animals is generally poorly effective. The VHHs targeted multiple sites on the receptor's surface with high affinity ( KD range: 1-40 nM), including one epitope overlapping that of cetuximab, several epitopes conserved in the cynomolgus EGFR orthologue, and at least one epitope conserved in the mouse EGFR orthologue. Interestingly, despite their generation against human EGFR expressed from cDNA by llama cells in vivo (presumably in native conformation), the VHHs exhibited wide epitope-dependent variation in their apparent affinities for native EGFR displayed on tumor cell lines. As fusions to human IgG1 Fc, one of the VHH-Fcs inhibited EGFR signaling induced by EGF binding with a potency similar to that of cetuximab (IC50: ~30 nM). Thus, DNA immunization elicited high-affinity, functional sdAbs that were vastly superior to those previously isolated by our group through protein immunization.
Keywords: antibody; single-domain antibody; VHH; EGFR; cancer; DNA immunization

Untargeted high resolution mass spectrometry approaches for identifying novel microcystins - Miles, C. O.; Beach, D. G; Wright, E. J.; Foss, A. J.; Uhlig, S.; Samdal, I. A.; Sandvik, M.; Van Nieuwenhove, I. Ine; Lovberg, K. E. (Abstract Book: 18th International Conference on Harmful Algae, from Ecosystems to Socio-Ecosystems, 2018)
Microcystins (MCs) are a group of hepatotoxic heptapeptides that inhibit protein phosphatases, and are produced by many species of cyanobacteria. Most MCs contain the unusual β-amino acid “Adda5 ”, γ-linked D-Glu6, and N-methyldehydroalanine (Mdha 7) at positions 5–7, with more than 250 different microcystin congeners having been reported in the literature, and with new congeners being discovered regularly. In addition to methods capable of measuring total MCs or targeting known congeners, improved methods are needed for identifying new candidate MCs , to ensure the safety of recreational and drinking waters. Untargeted high resolution mass spectrometry (HRMS) methods allows for simultaneous analysis of a tens of thousands of known and unknown chemicals in complex biological or environmental samples. Typically, identification of novel MCs involves only LC–MS/MS analysis in positive ionization mode with detection of a characteristic fragment from Adda5 at m/z 135.0804. However, some MCs contain modified Addamoieties, or are otherwise modified to change the MS/MS conditions under which this fragment is generated, and are not readily detected in this manner. We have recently shown that thiol-derivatization of the Mdha7/Dha7 group in MCs is a highly effective method for identifying even trace amounts of novel MCs in complex matrices by LC–MS. Here, we present a new approach using metabolomics software for semi-automated detection of novel MCs based on mercaptoethanol derivatization, together with accurate mass detection of precursor and characteristic product ions in negative and positive ionization modes. Taken together, this approach targets any molecules containing Adda5, D-Glu6 or Mdha7/Dha7, one or more of which is present in every microcystin reported to date. Furthermore, it is these three residues that are in closest contact with the catalytic centre of protein phosphatases, and which appear to be most important for toxicity. HRMS methods using data independent acquisition scan modes were particularly well suited for this purpose, allowing for simultaneous acquisition of MS/MS data on all compounds detected. This type of data is also well suited to retrospective analysis of newly discovered MCs from previously acquired data. The application of microcystin immunoaffinity columns containing antibodies with broad specificity to the whole family of MCs (presentation by Samdal et al.) further enhances the utility of this metabolomics workflow. We demonstrate the power of the combination of these novel approaches with the identification of numerous novel MCs in field and culture samples as well as a blue-green algal matrix reference material.

Effect of hardening heat treatment on the mechanical properties of a 17-4PH stainless steel foam - Gauthier, Maxime; Katz, Aurélien; Maison, Antoine; Cojocaru, Cristian V.; Bernier, Fabrice (MRS Advances, 2018)
This paper presents the results of a study on the impact of a precipitation hardening treatment on the mechanical properties of 17-4PH stainless steel open-cell foams produced using a powder-metallurgy-based process patented by the National Research Council Canada (NRC). Pre-alloyed powder was used to manufacture stainless steel (SS) foams with either medium or high porosity by changing the nature of the organic binder used to process the porous materials. Some of these were kept in the as-sintered state, while others were submitted to the H900 precipitation hardening treatment frequently prescribed for 17-4PH stainless steels. Metallurgical and physical characterization was carried out on the resulting materials, along with mechanical testing at the micro (indentation testing) and macro (compressive testing) scales. It was found that the Medium-Porosity Foams (MPF) and High-Porosity Foams (HPF) had very different morphologies, the HPFs having a delicate porous structure featuring thin sintered walls with many openings (a.k.a. windows) between the main cells, while the MPFs exhibited much thicker walls with few windows connecting the larger pores. As expected from these foam morphologies, the mechanical properties of MPFs were much higher than those of the more porous and delicate HPF materials. For both foam types, the average mechanical properties were improved by the H900 treatment. A comparison with compressive properties of 17-4PH foams taken from the literature resulted in reasonable agreement. However, the large scatter observed on the average compressive properties of the NRC foams and the slightly different structure/composition of the literature materials mean that any comparison between these porous alloys must be interpreted with caution.
Keywords: metal; foam

Effects of atmospheric CO₂ level on the metabolic response of resistant and susceptible wheat to Fusarium graminearum infection - Cuperlovic-Culf, Miroslava; Vaughan, Martha; Vermillion, Karl; Surendra, Anu; Teresi, Jennifer; Mccormick, Susan (Molecular Plant-Microbe Interactions, 2018)
Rising atmospheric CO₂ concentration and associated climate changes are thought to have contributed to the steady increase of Fusarium head blight (FHB) on wheat. However, our understanding of precisely how elevated CO₂ influences the defense response of wheat against Fusarium graminearum (Fg) remains limited. In this study, we evaluated the metabolic profiles of susceptible (Norm) and moderately resistant (Alsen) spring wheat in response to whole-head inoculation with two deoxynivalenol (DON) producing Fg isolates (DON⁺) Fg isolates (9F1 and Gz3639), and a DON deficient (DON⁻) Fg isolate (Gzt40) at ambient (400ppm) and elevated (800ppm) CO₂ concentrations. The effects of elevated CO₂ were dependent on both the Fg strain and the wheat variety, but metabolic differences in the host can explain the observed changes in Fg biomass and DON accumulation. The complexity of abiotic and biotic stress interactions make it difficult to determine if the observed metabolic changes in wheat are a result of CO₂ induced changes in the host, the pathogen, or a combination of both. However, the effects of elevated CO₂ were not dependent on DON production. Finally, we identified several metabolic biomarkers for wheat that can reliably predict FHB resistance or susceptibility even as atmospheric CO₂ levels rise.

Small-molecule allosteric triggers of Clostridium difficile toxin B auto-proteolysis as a therapeutic strategy - Ivarsson, Mattias E.; Durantie, Estelle; Huberli, Corina; Huwiler, Samuel; Hegde, Chrismita; Friedman, Jillian; Altamura, Fernando; Lu, Jun; Verdu, Elena F.; Bercik, Premysl; Logan, Susan M.; Chen, Wangxue; et al. (Cell Chemical Biology, 2018)
Clostridium difficile causes increasing numbers of life-threatening intestinal infections. Symptoms associated with C. difficile infection (CDI) are mediated by secreted protein toxins, whose virulence is modulated by intracellular auto-proteolysis following allosteric activation of their protease domains by inositol hexakisphosphate (IP6). Here, we explore the possibility of inactivating the C. difficile toxin B (TcdB) by triggering its auto-proteolysis in the gut lumen prior to cell uptake using gain-of-function small molecules. We anticipated that high calcium concentrations typically found in the gut would strongly chelate IP6, precluding it from pre-emptively inducing toxin auto-proteolysis if administered exogenously. We therefore designed IP6 analogs with reduced susceptibility to complexation by calcium, which maintained allosteric activity at physiological calcium concentrations. We found that oral administration of IP6 analogs attenuated inflammation and promoted survival in mouse models of CDI. Our data provide impetus to further develop small-molecule allosteric triggers of toxin auto-proteolysis as a therapeutic strategy.
Keywords: Clostridium difficile; bacterial toxins; small-molecule drug; allosteric modulator; inositol phosphate; non-antibiotic strategy

Detection of thermal strain in steel rails with BOTDA - Gu, Lijuan; Zhang, Liang; Bao, Xiaoyi; Zhang, Merrina; Zhang, Chengxian; Dong, Yongkang (Applied Sciences, 2018)
Rail transportation is one of the most important and efficient forms of transportation. Large thermal strain can develop in the rail steel due to extreme climatic conditions resulting in safety related issues. We carried out a thermal-strain monitoring test on the rail specimen over a large temperature range from -40 ∘ C to +50 ∘ C using a Brillouin optical time-domain analyzer (BOTDA) for the first time, to the best of our knowledge. Two jacketed fibers and small-diameter carbon/polyimide-coating single-mode fiber were used for the purpose of investigating the jacket effect of thermal-strain detection on the rail. Although a nonlinear response to the temperature of the loose jacketed fiber was found, it was applicable for thermal strain monitoring when glued on the surface of the rail sample. The measured thermal strain in the rail specimen was validated by the results obtained by the strain gauge. The thermally induced strain from the large rail specimen was found to have suppressed the nonlinear impact of the fiber jacket.
Keywords: brillouin optical time domain analyzer; thermal strain; fiber jacket

Genetic analysis of resistance to stripe rust in durum wheat (Triticum turgidum L. var. durum) - Lin, Xue; N’diaye, Amidou; Walkowiak, Sean; Nilsen, Kirby T.; Cory, Aron T.; Haile, Jemanesh; Kutcher, Hadley R.; Ammar, Karim; Loladze, Alexander; Huerta-Espino, Julio; Clarke, John M.; Ruan, Yuefeng; et al. (PLOS ONE, 2018)
Stripe rust, caused by the fungal pathogen Puccinia striiformis Westend. f. sp. tritici Eriks, is an important disease of bread wheat (Triticum aestivum L.) worldwide and there is an indication that it may also become a serious disease of durum wheat (T. turgidum L. var. durum). Therefore, we investigated the genetic architecture underlying resistance to stripe rust in adapted durum wheat germplasm. Wheat infection assays were conducted under controlled conditions in Canada and under field conditions in Mexico. Disease assessments were performed on a population of 155 doubled haploid (DH) lines derived from the cross of Kofa (susceptible) and W9262-260D3 (moderately resistant) and on a breeding panel that consisted of 92 diverse cultivars and breeding lines. Both populations were genotyped using the 90K single-nucleotide polymorphism (SNP) iSelect assay. In the DH population, QTL for stripe rust resistance were identified on chromosome 7B (LOD 6.87–11.47) and chromosome 5B (LOD 3.88–9.17). The QTL for stripe rust resistance on chromosome 7B was supported in the breeding panel. Both QTL were anchored to the genome sequence of wild emmer wheat, which identified gene candidates involved in disease resistance. Exome capture sequencing identified variation in the candidate genes between Kofa and W9262-260D3. These genetic insights will be useful in durum breeding to enhance resistance to stripe rust.

Track research: longitudinal rail stress management gap analysis research report (phase 1) - Zhang, Merrina; Roghani, Alireza; Barker, Christian (National Research Council Canada. Automotive and Surface Transportation, 2018)
Rail steel is produced in fixed lengths of between 12 to 120 m. To build track, rails can be joined either mechanically with joint bars and bolts or by welding the sections together as continuously welded rail (CWR). The general industry view is that CWR is preferred for main track construction as it eliminates discontinuities in track support. However, with this type of track construction, the rail steel is fixed in place and not free to expand or contract with changes in temperature. This results in thermally induced stresses in the rail (compressive when hot, and tensile when cold), which can be extremely large and contribute to rail breaks during cold weather conditions, and rail buckles under hot weather conditions. Although North American railways have operated with CWR since the 1950s, there is insufficient information on how rail behaves under stress, how longitudinal stress changes over time, how stress impacts the interaction between track and trains during operations, what exact stress condition(s) would cause broken rail or track buckling, nor how effective are current stress management practices. A literature review of thirty-three technical documents revealed a recurring theme of the difficulty in quantifying the level of stress being experienced by rails in CWR construction. Three potentially game changing technologies for longitudinal rail stress measurement were identified, including frictional strain sensing, X-ray diffraction and fibre optic sensing. These are commercial technologies already used in industries including oil and gas, construction, geotechnical and mining. A way forward is also proposed to test and validate the technologies, and deploy those suitable for the rail operating environment.

Simplified finite element model for evaluation of ultimate capacity of corrosion-damaged reinforced concrete beam-columns - Mohammed, A.; Almansour, H.; Martín-Pérez, B. (International Journal of Advanced Structural Engineering, 2018)
A simplified nonlinear finite element analysis (NLFEA) based on enhanced inspection, material testing, and nonlinear sectional analysis is introduced as part of a semi-quantitative assessment approach of aged beam-columns. The focus is on the evaluation of the structural performance and residual capacities of slab-on-girder bridge columns subjected to combined external loads and reinforcement corrosion. NLFEA takes into account different levels of geometrical, material, and bond damage due to reinforcement corrosion. At each load step of the nonlinear analysis process, NLFEA establishes the instantaneous stiffness of the structure through effective transfer of the instantaneous axial and flexural rigidities from the sectional level to the element level. The model adopts a displacement field tuning convergence approach that involves single or multiple correction phases satisfying the equilibrium and any user-defined displacement tolerance. The efficiency and accuracy of the proposed NLFEA is verified by comparison with test and analytical results from previous studies conducted on undamaged and corrosion-damaged structural elements. NLFEA proves to have high numerical stability and fast convergence, establishing its adoptability in large structural analysis/assessment frameworks. For corrosion-damaged beamcolumns, it is found that critical design sections do not necessarily remain critical for the structural evaluation.
Keywords: nonlinear finite element analysis; reinforcement corrosion; RC bridge column; semi-quantitative assessment framework; displacement field tuning convergence

Durability and climate change: changing climatic loads as may affect the durability of building materials, components and assemblies, proceedings of CIB/NRC symposium - Lacasse, Michael A. (CIB Publication; no. 414, 2018)
Keywords: building elements; building envelope; deterioration resistance; durability design; environmental separation; guideline; heat; air and moisture transfer; hygrothermal modelling; hygrothermal response

Mid-infrared suspended waveguide platform and building blocks - Sanchez-Postigo, Alejandro; Wangüemert-Pérez, Juan Gonzalo; Soler Penades, Jordi; Ortega-Moñux, Alejandro; Nedeljkovic, Milos; Halir, Robert; El Mokhtari Mimum, Faysal; Xu Cheng, Yolanda; Qu, Zhibo; Khokhar, Ali; Osman, Ahmed; Cao, Wei; et al. (IET Optoelectronics, 2018)

Expected observing efficiency of the Maunakea Spectroscopic Explorer (MSE) - Flagey, Nicolas; Mcconnachie, Alan W.; Szeto, Kei; Mahoney, Billy; Ho, Kevin; Hill, Alexis; Hervieu, Calum; Peck, Alison B.; Benn, Chris R.; Seaman, Robert L. (Observatory Operations: Strategies, Processes, and Systems VII, 2018)
The Maunakea Spectroscopic Explorer (MSE) will obtain millions of spectra each year in the optical to near-infrared, at low (R ≃ 3; 000) to high (R ≃ 40; 000) spectral resolution by observing <4,000 spectra per pointing via a highly multiplexed fiber-fed system. Key science programs for MSE include black hole reverberation mapping, stellar population analysis of faint galaxies at high redshift, and sub-km/s velocity accuracy for stellar astrophysics. One key metric of the success of MSE will be its survey speed, i.e. how many spectra of good signal-to-noise ratio will MSE be able to obtain every night and every year. This is defined at the higher level by the observing efficiency of the observatory and should be at least 80%, as indicated in the Science Requirements. In this paper we present the observing efficiency budget developed for MSE based on historical data at the Canada-France-Hawaii Telescope and other Maunakea Observatories. We describe the typical sequence of events at night to help us compute the observing efficiency and how we envision to optimize it to meet the science requirements.

A specific demetalation of Fe–N4 catalytic sites in the micropores of NC_Ar + NH3 is at the origin of the initial activity loss of the highly active Fe/N/C catalyst used for the reduction of oxygen in PEM fuel cells - Chenitz, Régis; Kramm, Ulrike I.; Lefèvre, Michel; Glibin, Vassili; Zhang, Gaixia; Sun, Shuhui; Dodelet, Jean-Pol (Energy & Environmental Science, 2018)
In this study, we explored the behavior of NC_Ar + NH3, an initially highly active catalyst for oxygen electroreduction, in H2/air fuel cells from 0.8 to 0.2 V at 80 °C and 25 °C, in order to find the causes of its instability. We discovered that the decay of the current density always involves the superposition of fast and slow first order kinetics, for which half-lives were obtained. The half-life of the fast decay was practically the same at all potentials and temperatures with a value of around 138 ± 55 min, while the half-life of the slow decay greatly varied from a minimum of ≈2400 min (40 h) to infinity. From the adsorption–desorption isotherm of NC_Ar + NH3, it was deduced that the Fe/N/C carbonaceous catalyst is characterized by interconnected open-end slit-shaped micropores, in which water (with dissolved H+ and O2) quickly flows in the fuel cells if their width is ≥0.7 nm as it has no interaction with the hydrophobic walls of the micropores. The driving force of this quick water flow is the humidified air streaming through the working cathode. Fe–N4-like active sites are thermodynamically stable in stagnant acidic conditions, but according to the Le Chatelier principle, they demetalate in the flux of water running into the micropores. This specific demetalation is the cause of the initial loss of ORR activity of NC_Ar + NH3 catalysts assigned to the fast current decay in fuel cells.

Titanium dioxide: material for a sustainable environment - Yang, Dongfang (InTech, 2018)
Titanium dioxide is currently being used in many industrial products. It provides unique photocatalytic properties for water splitting and purification, bacterial inactivation, and organics degradation. It has also been widely used as the photoanode for dye-sensitized solar cells and coatings for self-cleaning surfaces, biomedical implants, and nanomedicine. This book covers various aspects of titanium dioxide nanomaterials including their unique one-dimensional, two-dimensional, mesoporous, and hierarchical nanostructures and their synthetic methods such as sol-gel, hydrothermal, anodic oxidation, and electrophoretic deposition, as well as its key applications in environmental and energy sectors. Through these 24 chapters written by experts from the international scientific community, readers will have access to a comprehensive overview of the recent research and development findings on the titanium dioxide nanomaterials.

Detection of vascular plaque from optical coherence tomography images using hidden Markov random field based segmentation - Prakash, Ammu; Hewko, Mark; Sowa, Michael; Sherif, Sherif (Optics and the Brain part of OSA Biophotonics Congress: Biomedical Optics: 3-6 April 2018, Hollywood, Florida, United States, 2018)
We implemented a method to detect vascular plaque from optical coherence tomography images using hidden Markov random field based segmentation. We validated our segmentation results using both histology and photographic images of vascular plaque samples.

MixUp as locally linear out-of-manifold regularization - Guo, Hongyu; Mao, Yongyi; Zhang, Richong (Computer Science, 2018)
MixUp, a data augmentation approach through mixing random samples, has been shown to be able to significantly improve the predictive accuracy of the current art of deep neural networks. The power of MixUp, however, is mostly established empirically and its working and effectiveness have not been explained in any depth. In this paper, we develop a theoretical understanding for MixUp as a form of out-of-manifold regularization, which constrains the model on the input space beyond the data manifold. This analytical study also enables us to identify MixUp's limitation caused by manifold intrusion, where synthetic samples collide with real examples of the manifold. Such intrusion gives rise to over regularization and thereby under-fitting. To address this issue, we further propose a novel regularizer, where mixing policies are adaptively learned from the data and a manifold intrusion loss is embraced as to avoid collision with the data manifold. We empirically show, using several benchmark datasets, our regularizer's effectiveness in terms of over regularization avoiding and accuracy improvement upon current art of deep classification models and MixUp.

The potential for ‘next-generation’, microalgae-based feed ingredients for salmonid aquaculture in context of the blue revolution - Tibbetts, Sean Michael (Microalgal Biotechnology, 2018)
Microalgae-based ingredients have potential to ensure continued growth of salmonid aquaculture for global sustainable food security in the blue economy. Algal biorefineries must valorize the entire crop to grow profitable microalgae-based economies. With massive growth and demand for novel sustainable ingredients, farmed salmonid feed sectors are highly promising areas to focus on. Microalgae-based ingredients for salmonid feeds may have market advantages in terms of lower input costs, aerial footprint, wastewater remediation benefits and carbon credits for industrial CO2 conversion. A handful of microalgae-based ingredients have been proposed as candidates to supply well-balanced nutrients and immunostimulatory compounds. However, technical gaps exist and need addressing before the industry could economically incorporate microalgae-based ingredients into commercial feeds. Current knowledge on comprehensive biochemical composition is incomplete, highly heterogeneous, and information on their nutritional value is scattered and/or inconsistent. The aim of this chapter is to consolidate relatively fragmented data on biochemical composition and nutritional value of microalgae-based ingredients focusing on farmed salmonid feeds. Presented are discussions on the potential for such ‘next-generation’ ingredients, opportunities/challenges for their use and a compendium of studies evaluating their performance in feeds for economically relevant farmed salmonids, including rainbow trout (Oncorhynchus mykiss), Arctic charr (Salvelinus alpinus) and Atlantic salmon (Salmo salar).
Keywords: microalgae; salmonids; aquaculture feeds; composition; nutritional value

Targeted capture of cpn60 gene fragments for PCR-independent microbial community profiling - Dumonceaux, Tim; Dumonceaux, Tim; Links, Matthew; Town, Jennifer; Hill, Janet; Hemmingsen, Sean (Protocol Exchange, 2018)
This protocol describes the laboratory steps required to capture cpn60 gene fragments from microbial community DNA obtained from an environment of interest. This approach facilitates the determination of the taxonomic composition of a sample, providing information that spans all Domains of life (Bacteria, Eukarya, and Archaea). This method is independent of amplification biases associated with PCR, and provides a microbial community profile that is consistent with that generated using whole community shotgun sequencing, with substantially less sequencing effort required for the same community coverage. The protocol involves shearing the whole community genomic DNA by sonication, adding Illumina index primers, then hybridizing the sheared DNA to biotinylated RNA probes that correspond to the entire cpn60 reference database. Hybrids are selected using magnetic streptavidin beads, washed, and sequenced using an Illumina MiSeq platform. The protocol involves approximately five hours of hands-on time per sample over two days, along with a 24 hour hybridization step. In this protocol we describe the major changes we have implemented using the manufacturer’s recommendations as a starting point. We also provide tips and expected results.
Keywords: microbial community profiling; cpn60; metagenomics; sequence capture; Illumina sequencing

Arabidopsis UBC13 differentially regulates two programmed cell death pathways in responses to pathogen and low-temperature stress - Wang, Lipu; Wen, Rui; Wang, Jinghe; Xiang, Daoquan; Wang, Qian; Zang, Yuepeng; Wang, Zheng; Huang, Shuai; Li, Xin; Datla, Raju; Fobert, Pierre R.; Wang, Hong; et al. (New Phytologist, 2018)
-UBC13 is required for Lys63‐linked polyubiquitination and innate immune responses in mammals, but its functions in plant immunity remain to be defined. -Here we used genetic and pathological methods to evaluate roles of Arabidopsis UBC13 in response to pathogens and environmental stresses. -Loss of UBC13 failed to activate the expression of numerous cold‐responsive genes and resulted in hypersensitivity to low‐temperature stress, indicating that UBC13 is involved in plant response to low‐temperature stress. Furthermore, the ubc13 mutant displayed low‐temperature‐induced and salicylic acid‐dependent lesion mimic phenotypes. Unlike typical lesion mimic mutants, ubc13 did not enhance disease resistance against virulent bacterial and fungal pathogens, but diminished hypersensitive response and compromised effector‐triggered immunity against avirulent bacterial pathogens. UBC13 differently regulates two types of programmed cell death in response to low temperature and pathogen. The lesion mimic phenotype in the ubc13 mutant is partially dependent on SNC1. UBC13 interacts with an F‐box protein CPR1 that regulates the homeostasis of SNC1. However, the SNC1 protein level was not altered in the ubc13 mutant, implying that UBC13 is not involved in CPR1‐regulated SNC1 protein degradation. -Taken together, our results revealed that UBC13 is a key regulator in plant response to low temperature and pathogens.
Keywords: arabidopsis thaliana; cell death; disease resistance; low-temperature stress; ubiquitination

Extraction of cobalt and nickel from a pyrrhotite rich tailings sample via bioleaching - Cameron, R.; Yu, B.; Baxter, C.; Plugatyr, A.; Lastra, R.; Dal-Cin, M.; Mercier, P. H. J.; Perreault, N. (Extraction 2018: Proceedings of the First Global Conference on Extractive Metallurgy, 2018)
The growing use and acceptance of electric vehicles (EV), as evidenced by the record sales of over 750 thousand vehicles in 2016 and a current global EV stock of 2 million vehicles, is putting pressure on sourcing raw materials such as cobalt, and to a lesser extent, nickel. Global supply is poorly diversified, with 50–60% of global cobalt production sourced solely from the Democratic Republic of Congo (DRC). One potential source for cobalt and nickel are low-grade nickeliferous pyrrhotite tailings, of which 50–100 million tonnes are present in the Sudbury area alone. This paper presents the extraction of cobalt and nickel from this material using a combination of flotation and bioleaching technologies. The findings of a high-level techno-economic analysis of the proposed processing flowsheet are presented.
Keywords: pyrrhotite; tailings reprocessing; cobalt; nickel; flotation; bioleaching; techno-economic analysis

Evolution of two types of CdTe magic-size clusters from a single induction period sample - Luan, Chaoran; Gökçinar, Ömür Ö; Rowell, Nelson; Kreouzis, Theo; Han, Shuo; Zhang, Meng; Fan, Hongsong; Yu, Kui (The Journal of Physical Chemistry Letters, 2018)
There are two types of colloidal semiconductor nanocrystals (NCs) that exhibit band gap absorption that is relatively sharp compared to conventional quantum dots (QDs). One type displays an absorption doublet, while the other displays an absorption singlet. Here, we report the evolution of the two types of NCs at room temperature from a single CdTe sample extracted during the induction period (IP) prior to nucleation and growth of conventional QDs. The resulting NCs exhibit band gap absorption peaking at ∼371 nm and are magic-size clusters (MSCs), labeled as dMSC-371 and sMSC-371 for the doublet and singlet cases, respectively. We demonstrate that dMSC-371 (with another peak at ∼350 nm) evolves when the sample is incubated. When the sample is dispersed without incubation into a toluene and octylamine mixture, dMSC-371 or sMSC-371 grows depending on the amine amount. We propose that dMSC-371 and sMSC-371 are a pair of polymorphs (with identical CdTe core compositions). The present study brings insight into the formation relationship between dMSCs and sMSCs.

Measurement science for enhanced cannabis testing - Melanson, J. E.; Mcrae, G; Le, P. M.; Bates, J (Thieme Open, 2018)
Advancements in measurement science are vital in assuring the quality and safety of Canada's rapidly expanding cannabis industry. Reports of high variability in results between testing laboratories, in addition to several medical cannabis recalls, have highlighted the need for standards in cannabis testing. The National Research Council, as Canada's National Metrology Institute, is addressing this challenge through the promotion of documentary standards for cannabis testing methods and the development of cannabis certified reference materials (CRMs). These standards will ensure accuracy and consistency of testing results, assist licensed cannabis producers in achieving regulatory requirements, and ultimately promote confidence in the regulated cannabis industry. This presentation will highlight recent advancements in metrology in support of the cannabis industry. Specifically, a liquid chromatography – tandem mass spectrometry (LC-MS/MS) method for cannabinoids will be described, which is being proposed as a candidate ASTM International standard method. A pesticide method using liquid chromatography – high resolution mass spectrometry (LC-HRMS) will also be discussed. The presentation will also highlight progress on the development of a cannabis CRM (NRC MARI-1) to be certified for major cannabinoids and select contaminants. The production and certification will discussed, including the establishment of SI-traceability through the purity assignment of cannabinoid standards by quantitative nuclear magnetic resonance spectroscopy (qNMR). The availability of a cannabis CRM will facilitate method validation for cannabis testing laboratories and allow laboratories to assess their entire method, from extraction to analysis.

Determination of aluminium phosphide (AlP) in fumigants by ICP OES - Santos, E. J. Dos; Zagonel, G. F.; Herrmann, A. B.; Fantin, E. B.; Sturgeon, R. E. (Analytical Methods, 2018)
A method for determination of aluminium phosphide (AlP) in fumigants by inductively coupled plasma optical emission spectrometry (ICP OES) is presented. An 8 hour hydrolysis in water achieved complete decomposition of AlP with the released PH3 being absorbed in a medium of KMnO4/H2SO4. The solution was treated with NH2OH.HCl to reduce the excess MnO4- and the PO4-3 so formed was quantitated as P by ICP OES based on external calibration using the P(I) 213.618 nm emission line. A detection limit (3s, n=10) of 0.26 g/100 g AlP and LOQ (10s, n=10) of 0.85 g/100g AlP were realized. Ten commercial samples of fumigants were analysed, providing results in agreement with specifications of ~ 55-60 g/100g and concordant with values generated by the spectrophotometric method, as evidenced by a paired t-test (95% confidence limit).This simple procedure has been adopted by the Institute of Technology of Paraná - TECPAR (Curitiba, Brazil).

Emission from strained germanium nanocrystals - Rowell, Nelson L.; Lockwood, David J. (ECS Transactions, 2018)
We analyse the intense photoluminescence (PL) observed at energies from 600 to 1500 meV for many molecular beam epitaxy grown Si1-xGex epitaxial layers. We show that the unexplained broad PL peak is due to self-assembled Ge nanocrystals (NCs) within the SiGe layers. The NCs are assumed lattice matched to the SiGe in the vertical, growth direction. As the Ge-fraction in the SiGe layer increases, the vertical strain in the NCs changes from compressive to tensile at x ~ 0.36, lowering the NC band gap (BG) below that of bulk Ge. We analyse PL results for 64 samples exhibiting this broad PL peak by examining how it follows the strained Ge BG for x from 0.05 to 0.53. The PL is resolvable as two narrower peaks separated by the TO phonon energy for Ge. Strain and confinement shifted NC bound exciton energies calculated numerically agree well with the measured ones.

Wideband Ge-Rich SiGe polarization-insensitive waveguides for mid-infrared free-space communications - Vakarin, Vladyslav; Ramírez, Joan; Frigerio, Jacopo; Liu, Qiankun; Ballabio, Andrea; Le Roux, Xavier; Alonso-Ramos, Carlos; Isella, Giovanni; Cheben, Pavel; N. Ye, Winnie; Vivien, Laurent; Marris-Morini, Delphine (Applied Sciences, 2018)
The recent development of quantum cascade lasers, with room-temperature emission in the mid-infrared range, opened new opportunities for the implementation of ultra-wideband communication systems. Specifically, the mid-infrared atmospheric transparency windows, comprising wavelengths between 3–5 µm and 8–14 µm, have great potential for free-space communications, as they provide a wide unregulated spectrum with low Mie and Rayleigh scattering and reduced background noise. Despite the great efforts devoted to the development of mid-infrared sources and detectors, little attention is dedicated to the management of polarization for signal processing. In this work, we used Ge-rich SiGe alloys to build a wideband and polarization-insensitive mid-infrared photonic platform. We showed that the gradual index change in the SiGe alloys enabled the design of waveguides with remarkably low birefringence, below 2 × 10−4, over ultra-wide wavelength ranges within both atmospheric transparency windows, near wavelengths of 3.5 µm and 9 µm. We also report on the design of a polarization-independent multimode interference device achieving efficient power splitting in an unprecedented 4.5-µm bandwidth at around 10-µm wavelength. The ultra-wideband polarization-insensitive building blocks presented here pave the way for the development of high-performance on-chip photonic circuits for next-generation mid-infrared free-space communication systems.
Keywords: photonic integrated circuits; mid-infrared; polarization-insensitive

Ignition of quantum cascade lasers in a state of oscillating electric field domains - Winge, David O.; Dupont, Emmanuel; Wacker, Andreas (Physical Review A, 2018)
Quantum cascade lasers (QCLs) are generally designed to avoid negative differential conductivity (NDC) in the vicinity of the operation point in order to prevent instabilities. We demonstrate that the threshold condition is possible under an inhomogeneous distribution of the electric field (domains) and leads to lasing at an operation point with a voltage bias normally attributed to the NDC region. For our example, a terahertz QCL operating up to the current maximum temperature of 199 K, the theoretical findings agree well with the experimental observations. In particular, we experimentally observe self-sustained oscillations with GHz frequency before and after threshold. These are attributed to traveling domains by our simulations. Overcoming the design paradigm to avoid NDC may allow for the further optimization of QCLs with less dissipation from stabilizing background currents.

High density genetic mapping of Fusarium head blight resistance QTL in tetraploid wheat - Sari, Ehsan; Berraies, Samia; Knox, Ron E.; Singh, Asheesh K.; Ruan, Yuefeng; Cuthbert, Richard D.; Pozniak, Curtis J.; Henriquez, Maria Antonia; Kumar, Santosh; Burt, Andrew J.; N’diaye, Amidou; Konkin, David J.; et al. (PLOS ONE, 2018)
Breeding for Fusarium head blight (FHB) resistance in durum wheat is complicated by the quantitative trait expression and narrow genetic diversity of available resources. High-density mapping of the FHB resistance quantitative trait loci (QTL), evaluation of their co-localization with plant height and maturity QTL and the interaction among the identified QTL are the objectives of this study. Two doubled haploid (DH) populations, one developed from crosses between Triticum turgidum ssp. durum lines DT707 and DT696 and the other between T. turgidum ssp. durum cv. Strongfield and T. turgidum ssp. carthlicum cv. Blackbird were genotyped using the 90K Infinium iSelect chip and evaluated phenotypically at multiple field FHB nurseries over years. A moderate broad-sense heritability indicated a genotype-by-environment interaction for the expression of FHB resistance in both populations. Resistance QTL were identified for the DT707 × DT696 population on chromosomes 1B, 2B, 5A (two loci) and 7A and for the Strongfield × Blackbird population on chromosomes 1A, 2A, 2B, 3A, 6A, 6B and 7B with the QTL on chromosome 1A and those on chromosome 5A being more consistently expressed over environments. FHB resistance co-located with plant height and maturity QTL on chromosome 5A and with a maturity QTL on chromosome 7A for the DT707 × DT696 population. Resistance also co-located with plant height QTL on chromosomes 2A and 3A and with maturity QTL on chromosomes 1A and 7B for the Strongfield × Blackbird population. Additive × additive interactions were identified, for example between the two FHB resistance QTL on chromosome 5A for the DT707 × DT696 population and the FHB resistance QTL on chromosomes 1A and 7B for the Strongfield × Blackbird population. Application of the Single Nucleotide Polymorphic (SNP) markers associated with FHB resistance QTL identified in this study will accelerate combining genes from the two populations.

Novel type II Bragg grating structures in silica fibers using femtosecond lasers and phase masks - Mihailov, Stephen; Hnatovsky, Cyril; Grobnic, Dan (Journal of Lightwave Technology, 2018)
This review paper presents recent developments on the fabrication of novel thermally stable Type II fiber Bragg grating structures using femtosecond lasers and the phase mask technique. By manipulating the inscription beam and phase mask designs, exotic grating structures, such as ultrashort gratings < 100 μm in length, Fabry-Perot structures or π-phase shifted structures can be created that are stable at high temperatures. These novel structures can also be created directly through protective polymer coatings such as polyimide, thus simplifying their manufacture.
Keywords: phase shift; phase mask; femtosecond laser; fiber Bragg gratings

High-temperature stable π-phase-shifted fiber Bragg gratings inscribed using infrared femtosecond pulses and a phase mask - Hnatovsky, Cyril; Grobnic, Dan; Mihailov, Stephen J. (Optics Express, 2018)
Type II π-phase-shifted Bragg gratings stable up to ~1000°C are written inside a standard single mode silica optical fiber (SMF-28) with infrared femtosecond pulses and a special phase mask. Inscription through the protective polyimide fiber coating is also demonstrated. The birefringence of the Bragg gratings and, as a result, the polarization dependence of their spectra are strongly affected by the femtosecond laser polarization. Using optimized writing conditions, the full width at half maximum of the π-phase-shifted passband feature can be ~30 pm in transmission, while the polarization-dependent shift of its central wavelength can be less than 8 pm, for a 7 mm long grating structure. This makes such gratings a unique tool for high-resolution measurements of temperature, load and vibration in extreme temperature environments.

Tilted subwavelength gratings: controlling anisotropy in metamaterial nanophotonic waveguides - Luque-González, José Manuel; Herrero-Bermello, Alaine; Ortega-Moñux, Alejandro; Molina-Fernández, Íñigo; Velasco, Aitor V.; Cheben, Pavel; Schmid, Jens H.; Wang, Shurui; Halir, Robert (Optics Letters, 2018)
Subwavelength grating (SWG) structures are an essential tool in silicon photonics, enabling the synthesis of metamaterials with a controllable refractive index. Here we propose, for the first time to the best of our knowledge, tilting the grating elements to gain control over the anisotropy of the metamaterial. Rigorous finite difference time domain simulations demonstrate that a 45° tilt results in an effective index variation on the fundamental TE mode of 0.23 refractive index units, whereas the change in the TM mode is 20 times smaller. Our simulation predictions are corroborated by experimental results. We furthermore propose an accurate theoretical model for designing tilted SWG structures based on rotated uniaxial crystals that is functional over a wide wavelength range and for both the fundamental and higher order modes. The proposed control over anisotropy opens promising venues in polarization management devices and transformation optics in silicon photonics.

Inkjet-printed unipolar n-type transistors on polymer substrates based on dicyanomethylene-substituted diketopyrrolopyrrole quinoidal compounds - Lu, Jianping; Dadvand, Afshin; Chu, Ta-Ya; Movileanu, Raluca; Baribeau, Jean-Marc; Ding, Jianfu; Tao, Ye (Organic Electronics, 2018)
The development of printable and air-stable unipolar n-type semiconductors remains a critical issue in the field of organic electronics in view of n-type transistors being indispensable components in the manufacture of low-power-consumption complementary (CMOS type) integrated circuits. In this work, we report on two dicyanomethylene-substituted diketopyrrolopyrrole derivatives with different alkyl side chains (DCM-DPP-C13 and DCM-DPP-C16) for n-type transistors. Compared with DCM-DPP-C16, the side chain branching point in DCM-DPP-C13 was moved further away from the conjugated backbone. Both materials showed promising electron mobility above 0.1 cm2/VS in air with remarkably low threshold voltages (−3 V – 2 V) on spin-coated bottom-contact bottom-gated devices on silicon substrates. Contrary to our original expectation, the average electron mobility of DCM-DPP-C16 (0.2 cm2/VS) was higher than that of DCM-DPP-C13 (0.12 cm2/VS) due to the bigger crystalline domains in the thin film of the former compound. We investigated the inkjet printability of these two compounds as well, and bottom-contact top-gated transistors were successfully fabricated on flexible PET substrates. Widely used Cytop was employed as the gate dielectric. Ag gate electrodes were readily inkjet printed on the gate dielectric by using a thin layer of Nafion as an adhesion promoter. DCM-DPP-C16 demonstrated an excellent inkjet-ability with good uniformity and reproducibility. An average electron mobility around 0.1 cm2/VS was achieved in air. This is an important step toward the fabrication of large-area organic CMOS logic circuits with low cost.

Simulation of behaviour of an energy storage device during installation process in lake Ontario - Zaman, M. Hasanat; Akinturk, Ayhan; Mcgillis, Andrew (ASME 2018 37th International Conference on Ocean, Offshore and Arctic Engineering. Volume 3: Structures, Safety, and Reliability, 2018)
A model of a compressed air energy storage unit is tested for tow-out and installation in the Ocean, Coastal & River Engineering (OCRE) Portfolio of the National Research Council of Canada (NRC). The proposed prototype accumulator is a cylinder of 36 m in diameter and 12 m in height, which will be installed at the bottom of Lake Ontario at about 60 m water depth. The model of the accumulator with scale 1:21.5 was fabricated at the Design and Fabrication Unit of NRC. Appropriate ballast systems were designed and applied for the tow out, installations and release mechanism tests. The model scale test was conducted to examine the hydrodynamic behavior of the accumulator during tow-out and set down operations. NRC’s Towing Tank and Offshore Engineering Basin test facilities were used for the tasks. In this paper only the installation case of the accumulator is reported and discussed. Relevant numerical simulations are also carried out. Comparisons of the numerical results with the experimental results show good agreement for the compared cases.
Keywords: simulation; energy storage; lakes

Interaction of Nomadic Bergy bits with an offshore gravity based structure in waves - Seo, Dong Cheol; Zaman, M. Hasanat; Akinturk, Ayhan (ASME 2018 37th International Conference on Ocean, Offshore and Arctic Engineering. Volume 7A: Ocean Engineering, 2018)
Offshore oil and gas operations are being conducted in harsh environments such as offshore fields around Newfoundland and Labrador. The platforms used in these fields may be exposed to additional risks due the presence of drifting ice pieces in various sizes. To avoid a dangerous collision with a large floating ice, ice management and risk mitigation plans are required firstly. In case of smaller ice pieces (or bergy bits), if they collide with an offshore platform, the combined load of bergy bits and waves may be larger than the typical design wave loads. Hence, it is necessary to predict how these bergy bits may interact with a platform in a given sea state to estimate the combined load for developing a reliable design. In this paper, dynamic interaction between a moving bergy bit and a fixed offshore platform is simulated using CFD (Computation Fluid Dynamics) method. Trajectories and velocities of ice are simulated and compared to understand the hydrodynamic interaction by applying a series of different wave conditions such as wave period, height and relative incident peak location. The simulation outcomes show the importance and possibilities to apply it to the design process of such structures in the ocean.
Keywords: gravity (force); waves; ocean engineering

Epoxy resin nanocomposites with hydroxyl (OH) and amino (NH2) functionalized boron nitride nanotubes - Guan, Jingwen; Ashrafi, Behnam; Martinez-Rubi, Yadienka; Jakubinek, Michael B.; Rahmat, Meysam; Kim, Keun Su; Simard, Benoit (Nanocomposites, 2018)
Hydroxyl (OH) and amino (NH2) functionalized boron nitride nanotubes (f-BNNTs) were integrated into an epoxy resin (Epon828) to achieve improved mechanical properties. While raw BNNT-composites yielded the largest values for Young’s modulus and appeared to be well mixed, f-BNNTs were found to provide a superior combination of mechanical properties yielding improvements in strain at failure, tensile strength and toughness that were not observed using raw BNNTs. In particular, an increase of 21% in Young’s modulus is observed with 5 wt% of f-BNNT, and increases of 12, 21, and 49% are observed in tensile strength, failure strain, and toughness, respectively, with 2 wt% f-BNNT while a 34% increase in fracture toughness is observed with 3 wt% f-BNNT.
Keywords: boron nitride nanotubes (BNNTs); epoxy resin; nanocomposite; functionalization; mechanical properties

Quantum metrology with photoelectrons. Volume 2: Applications and advances - Hockett, Paul (IOP Publishing, 2018)
Since the turn of the century, the increasing availability of photoelectron imaging experiments, along with the increasing sophistication of experimental techniques, and the availability of computational resources for analysis and numerics, has allowed for significant developments in such photoelectron metrology. Quantum Metrology with Photoelectrons, Volume 2: Applications and advances discusses the fundamental concepts along with recent and emerging applications. Volume 2 explores the applications and development of quantum metrology schemes based on photoelectron measurements. The author begins with a brief historical background on 'complete' photoionization experiments, followed by the details of state reconstruction methodologies from experimental measurements. Three specific applications of quantum metrology schemes are discussed in detail. In addition, the book provides advances, future directions, and an outlook including (ongoing) work to generalise these schemes and extend them to dynamical many-body systems. Volume 2 will be of interest to readers wishing to see the (sometimes messy) details of state reconstruction from photoelectron measurements as well as explore the future prospects for this class of metrology.

Quantum metrology with photoelectrons. Volume 1: Foundations - Hockett, Paul (IOP Publishing, 2018)
Since the turn of the century, the increasing availability of photoelectron imaging experiments, along with the increasing sophistication of experimental techniques, and the availability of computational resources for analysis and numerics, has allowed for significant developments in such photoelectron metrology. Quantum Metrology with Photoelectrons, Volume 1: Foundations discusses the fundamental concepts along with recent and emerging applications.

pH-switchable water-soluble boron nitride nanotubes - Guan, Jingwen; Kim, Keun Su; Jakubinek, Michael B.; Simard, Benoit (ChemistrySelect, 2018)
The first example of aqueous solutions of boron nitride nanotubes (BNNTs) with switchable stability and without use of surfactants is demonstrated. The as‐produced boron nitride nanotubes are both purified and solubilized through an environmentally friendly and scalable approach using water extraction and liquid bromine treatment. This treatment effectively removes elemental boron particles and excess bromine reacts with BNNTs, inducing B−N bond cleavage on the BNNT surface to yield hydroxyl (OH) and amino (NH2) functionalized BNNTs. The resulting functionalized BNNTs form stable aqueous solutions around neutral pH (4 < pH < 8), but readily precipitate in other pH ranges. This switchable solubility is explained in terms of the capability of the functional groups (OH and NH2) to form hydrogen‐bonding networks in water. Further, the solubility differences in selected polar organic solvents have been utilized to prepare functionalized BNNTs with higher purity.

Multi-scale impedance model for supercapacitor porous electrodes: theoretical prediction and experimental validation - Huang, Qiu-An; Li, Yu; Tsay, Keh-Chyun; Sun, Chunwen; Yang, Changping; Zhang, Lei; Zhang, Jiujun (Journal of Power Sources, 2018)
In this paper, a multi-scale impedance model is developed for evaluating the charge storage capacity and ion-transfer rate of supercapacitor porous electrodes. This model can be used to theoretically understand the contributions of the intra-particle pore at nano-scale, the inter-particle pore at micron-scale, and the porous electrode at millimeter-scale to the performance of supercapacitor. Then, impedance spectrum characteristics of porous electrodes are screened via numerical simulation based on the developed multi-scale impedance model, especially for different electrode thicknesses and various faradaic processes with different time constants. Subsequently, seven supercapacitor samples, four of them with electrode thicknesses of 60, 100, 180, and 370 μm respectively, and three of them with different types of current collectors (nickel, carbon-coated stainless-steel, and stainless-steel), are fabricated and characterized to validate the developed model. The fitting results and residuals of the measured impedance data validate the linear relationship of the scaled equivalent resistance of electrolyte v. s. electrode thickness and the scaled characteristic time constant v. s. the square of electrode thickness. The validated multi-scale impedance model might offer an effective method to rationally balance or optimize charge storage and charge transfer via morphology design for porous electrodes.
Keywords: porous electrode; multi-scale impedance model; De Levie's equation; charge storage; ion transport

Performance of fine and ultra-fine lead-free powders for solder paste applications - Nobari, Amir H.; St-Laurent, Sylvain; Thomas, Yannig; Bouchemit, Arslane; Lesperance, Gilles (2018 IEEE 68th Electronic Components and Technology Conference (ECTC), 2018)
The continuing demand for smaller and lighter electronic products has driven the use of miniature components. The assembly of these miniature components requires fine solder joints; and, finer solder joints require advanced solder pastes with finer particle sizes. In general, there are four key characteristics for any powder: purity, particle size distribution, surface oxide, and morphology. However, a complete understanding of the effect of key solder powder characteristics on the paste properties is still not achieved. This understanding becomes much more important when new solder pastes with finer powder size (Type 5, 6, 7, and 8) are developed for advanced applications in semiconductor packaging. In this work, SAC305 (Sn-3Ag-0.5Cu) powders is produced with a proprietary atomizing technology, particularly effective in producing solder powder ranging from 1 to 25 μm. Powder characteristics considered are particle size distribution and powder oxidation. The surface oxide layer is characterized using Auger Electron Spectroscopy and Transmission Electron Microscopy and characterization of the surface oxide layer is presented for powders with various particle size distributions. The relation between surface oxide thickness and reflow performance is described. Finally, a powder treatment will be shown to be required to improve the robustness of solder paste in certain conditions. The influence of the powder treatment on the reflow performance of solder paste will be discussed. The results and knowledge obtained by the systematic study presented in this paper can be applied to design new and advanced solder pastes with fine powders.

Structure of the LPS O-chain from Fusobacterium nucleatum strain ATCC 23726 containing a novel 5,7-diamino-3,5,7,9-tetradeoxy-l-gluco-non-2-ulosonic acid presumably having the d-glycero-l-gluco configuration - Vinogradov, Evgeny; St Michael, Frank; Cox, Andrew D. (Carbohydrate Research, 2018)
Fusobacterium nucleatum is an anaerobic bacterium found in the human mouth where it causes periodontitis. It was also found in colorectal cancer tissues and is linked with pregnancy complications, including pre-term and still births. Cell surface structures of the bacterium could be implicated in pathogenesis. Here we report the following structure of the lipopolysaccharide O-chain of a spontaneous streptomycin resistant (SmR) mutant of F. nucleatum strain ATCC 23726: -4-β-Non5Am7Ac-4-β-d-GlcNAcyl3NFoAN-3-β-d-FucNAc4N- where GlcNAcyl3NFoAN indicates 2,3-diamino-2,3-dideoxyglucuronic acid amide with Fo at N-3 being formyl and Acyl at N-2 being propanoyl (∼70%) or butanoyl (∼30%); Non5Am7Ac indicates 7-acetamido-5-acetimidoylamino-3,5,7,9-tetradeoxy-l-gluco-non-2-ulosonic acid presumably having the d-glycero-l-gluco configuration. To our knowledge, no l-gluco isomer of higher sugars of this class as well as no N-propanoyl or N-butanoyl group have so far been found in bacterial polysaccharides.
Keywords: Fusobacterium nucleatum; lipopolysaccharide; NMR spectroscopy; polysaccharide; structure; non-2-ulosonic acid

Challenges, mitigation strategies and perspectives in development of zinc-electrode materials and fabrication for rechargeable zinc–air batteries - Yi, Jin; Liang, Pengcheng; Liu, Xiaoyu; Wu, Kai; Liu, Yuyu; Wang, Yonggang; Xia, Yongyao; Zhang, Jiujun (Energy & Environmental Science, 2018)
As a promising energy storage device, rechargeable zinc-air battery (RZAB) has drawn increasing attention because of its high energy density, cost-effectiveness, high safety, rich abundance of zinc, as well as environmental benignity. However, the widespread application of RZABs still face considerable challenges derived from zinc-electrodes, electrolytes, and air-electrodes. In this paper, a specific attention is given to RZAB zinc-electrode materials and fabrication with focus on the fundamental understanding of zinc-electrode reaction mechanisms, technical challenges, mitigation strategies, and perspectives. Particularly, the approaches to overcome the challenges are also presented and analyzed for facilitating the further reserach and development of RZABs.

A case study of triggered star formation in Cygnus X - Deb, Soumen; Kothes, Roland; Rosolowsky, Erik (Monthly Notices of the Royal Astronomical Society, 2018)
Radiative feedback from massive stars can potentially trigger star formation in the surrounding molecular gas. Inspired by the case of radiatively driven implosion in M16 or Eagle Nebula, we analyse a similar case of star formation observed in the Cygnus X region. We present new James Clerk Maxwell Telescope observations of 13CO(3−2) and C18O(3−2) molecular lines of a cometary feature located at 50 pc north of the Cyg OB2 complex that was previously identified in 12CO(3−2) mapping. These data are combined with archival H α, infrared, and radio continuum emission data, from which we measure the mass to be 110 M⊙. We identify Cyg OB2 as the ionizing source. We measure the properties of two highly energetic molecular outflows and the photoionized rim. From this analysis, we argue the external gas pressure and gravitational energy dominate the internal pressure. The force balance along with previous simulation results and a close comparison with the case of Eagle Nebula favours a triggering scenario.
Keywords: stars: formation; ISM: jets and outflows; open clusters and associations: individual: Cyg OB2

New insights into the nature of transition disks from a complete disk survey of the Lupus star-forming region - Marel, Nienke Van Der; Williams, Jonathan P.; Ansdell, M.; Manara, Carlo F.; Miotello, Anna; Tazzari, Marco; Testi, Leonardo; Hogerheijde, Michiel; Bruderer, Simon; Terwisga, Sierk E. Van; Dishoeck, Ewine F. Van (The Astrophysical Journal, 2018)
Transition disks with large dust cavities around young stars are promising targets for studying planet formation. Previous studies have revealed the presence of gas cavities inside the dust cavities hinting at recently formed, giant planets. However, many of these studies are biased towards the brightest disks in the nearby star forming regions, and it is not possible to derive reliable statistics that can be compared with exoplanet populations. We present the analysis of 11 transition disks with large cavities (>20 AU radius) from a complete disk survey of the Lupus star forming region, using ALMA Band 7 observations at 0.3" (22-30 AU radius) resolution of the 345 GHz continuum, 13CO and C18O 3-2 observations and the Spectral Energy Distribution of each source. Gas and dust surface density profiles are derived using the physical-chemical modeling code DALI. This is the first study of transition disks of large cavities within a complete disk survey within a star forming region. The dust cavity sizes range from 20-90 AU radius and in three cases, a gas cavity is resolved as well. The deep drops in gas density and large dust cavity sizes are consistent with clearing by giant planets. The fraction of transition disks with large cavities in Lupus is ~11%, which is inconsistent with exoplanet population studies of giant planets at wide orbits. Furthermore, we present a hypothesis of an evolutionary path for large massive disks evolving into transition disks with large cavities.
Keywords: astrochemistry; ISM: molecules; protoplanetary disks; stars: formation

Organophosphorus pesticide in sapodilla (Manilkara zapota) fruit - Alcântara, Daniel; Paz, Mario; Rodrigues, Tigressa; Fernandes, Tatiana; Barbosa, Pablo; Loiola, Adonay; Grinberg, Patricia; Zocolo, Guilherme; De Brito, Edy; Do Nascimento, Ronaldo (Journal of the Brazilian Chemical Society, 2018)
A method based on QuEChERS (quick, easy, cheap, effective, rugged, and safe) extraction and gas chromatography-mass spectrometry (GC-MS) detection was described for the pesticides dichlorvos, disulfoton, ethoprophos, parathion methyl, fenchlorphos, chlorpyrifos, azinphos methyl and prothiofos in sapodilla. For all compounds studies, it was observed a strong matrix effect showing the need to use matrix matched calibration strategy. Method was validated, and good linearity (R > 0.99) was obtained for all pesticides studied with limits of detection (LODs) and quantification (LOQs) ranging from 0.01 to 0.06 mg kg-1 and 0.03 to 0.2 mg kg-1, respectively. Recovery studies were performed at different levels (0.08, 0.10, 0.14, 0.20, 0.35 and 1.17 mg kg-1) and showed good results (between 70 and 120% with relative standard deviation (RSD) < 20%). A statistical test was applied to the coefficients of the analytical curves obtained in the sapodilla matrix. Analyses of commercial samples showed chlorpyrifos were detected in about 70 and 33% for fruit and pulps samples, respectively. It should be noted that chlorpyrifos is not permitted in sapodilla crops by ANVISA and EC guidelines.
Keywords: QuEChERS; validation; matrix effect; GC-MS

Indoor air pollution - Pluschke, Peter; Schleibinger, Hans (The Handbook of Environmental Chemistry; no. 64, 2018)
This second edition offers a comprehensive overview of the priority indoor air pollutants, such as volatile organic compounds, indoor particles and fibres, combustion products and other chemical agents that may affect health. It includes updated reviews with a focus on emission processes and on the large variety of volatile organic pollutants. It also introduces new topics, such as reflections on the shift in human health from infection-related diseases to chronic illnesses and the significance of indoor chemical exposure. The authors provide insights into different cultural settings and their consequences for indoor air quality. Further, the book briefly discusses building certification as a market-oriented tool to improve energy efficiency and indoor air quality in the building sector. It appeals to public health specialists; scientists; graduate students in the field of environmental sciences; decision makers in government, regulatory bodies and the construction industry; and facility managers.

Using building performance simulation for fault impact evaluation - Shi, Zixiao; O'Brien, William (The Conference, 2018)
Automated building fault detection and diagnostics (AFDD) has become a valuable tool to maintain the efficiency of high-performance buildings. Still, when faults are detected or diagnosed, they are often presented to the building operators as-is with little explanation of their potential impacts. This could lead to higher workload and knowledge requirement for the operators to assess the situation and schedule maintenance tasks. One approach to aid the building operators' decision-making process is to provide quantitative impact metrics for faults. Metrics such as energy, thermal comfort, and cost can be simulated using building performance simulation (BPS) software or data-driven models. While BPS has been used in fault detection research as well as advanced control algorithms, little work has done to introduce BPS to fault evaluation and fault management applications. This paper proposes a standardized procedure to use BPS to evaluate diagnosed faults in building systems by quantifying symptoms caused by faults, and then translate these symptoms to BPS inputs. This research tries to tackle the challenges of uncertainties caused by parameter estimation and providing strategies to symptoms that cannot be directly translated to a BPS input. The proposed method can be generalized to be integrated with existing FDD tools or future FDD research.
Keywords: building performance simulation; fault detection and diagnostics; fault evaluation; building energy management

Development of a distributed building fault detection, diagnostic, and evaluation system - Shi, Zixiao; O’Brien, William; Gunay, H. Burak (ASHRAE Transactions, 2018)
This paper introduces a distributed system for building fault detection, diagnostic, and evaluation (FDDE). The design of the distributed system aims to address computation and network limitations on a common commercial building automation system (BAS). This system also aims to be adaptable to different fault detection and fault diagnostics algorithms developed by other researchers. The fault evaluation aspect of the system provides quantitative impact metrics of the potential faults to the building operators. Probabilistic representations of faults and symptoms are used, and a continuous symptom severity value is developed to provide more granularity over the abnormal operation information. The proposed method is then tested with five fault cases simulated in EnergyPlus. Results show reduced false positive rate and enhanced fault belief when using a dynamic Bayesian network (DBN) over the conventional event-based Bayesian network (BN) used in fault diagnostics. Fault evaluation based on continuous symptom severity provides a reasonable quantitative reference for building operators to make informed decisions. This system will be further expanded with more fault detection algorithms and tested inside real buildings, and a framework will be made available for other researchers to develop upon.

Satellite-based InSAR monitoring of highway bridges: validation case study on the north channel bridge in Ontario, Canada - Cusson, Daniel; Trischuk, Ken; Hébert, Daniel; Hewus, Glenn; Gara, Matthew; Ghuman, Parwant (Transportation Research Record: Journal of the Transportation Research Board, 2018)
A space-borne bridge displacement monitoring technology was demonstrated on a major highway bridge in Cornwall (Ontario, Canada) over a 15-month period. Two major challenges had to be overcome and solutions were identified and implemented. The first challenge related to the proper selection and analysis of satellite imagery to optimize the number and signal quality of point targets on the bridge for adequate movement detection and analysis. The second challenge was the comparison and validation of independent sets of data having different measurement methods, reference baselines, and distributions in space and time. The key findings include: (i) the regression analysis of interferometric synthetic aperture radar (InSAR) data from the satellite produced the best coherence when fitted against the following three independent variables: height, ambient temperature, and time; (ii) the bridge railings appeared to be excellent natural reflectors with their sharp edges and regular spacing along the bridge, showing a return of over 3,000 clear point targets to the satellite; (iii) the InSAR displacement thermal sensitivity data was found to compare very well to numerical modeling thermal data. The results show great promise and value in applying satellite-based technology for the remote monitoring of highway and railway bridges to alert engineers of excessive movement and, in turn, will help optimize preventive maintenance management, extend structural lifespan, minimize traffic disruptions due to late repair, and ensure structural integrity.

Abstract A189: identification of antibody-drug conjugate targets using curated public data, in-house glycoproteomics, and a surrogate in vitro ADC assay - Hill, Jennifer J.; Fauteux, François; Tremblay, Tammy-Lynn; Jaramillo, Maria (Molecular Cancer Therapeutics, 2018)
Antibody-drug conjugates (ADCs) are a promising approach for cancer therapy, combining the specificity of an antibody with the potency of small-molecule toxins. To identify cellular targets for the development of new ADCs, we have set out to identify proteins that (1) are expressed on the cell surface; (2) have high specificity for tumors, with relatively low expression on normal tissues; and (3) can internalize into the tumor cell by a mechanism that enables the delivery and activation of sufficient amounts of toxin to kill cancer cells. Here at the NRC, we have built a pipeline to identify new ADC targets, incorporating public gene expression data mining and glycoproteomic profiling, followed by in vitro screening through a surrogate ADC assay. Public data enable the analysis of large numbers of human tumors and normal tissues, providing a population-based estimate of gene expression. Through curation of the Gene Expression Omnibus, we have built a microarray database that contains >26,000 tumor samples and >8,800 normal samples, all on the Affymetrix HGU133 Plus 2.0 platform. We have also collected RNA-seq data for >5,000 normal samples from the GTEx database, and 6,900 tumor samples from The Cancer Genome Atlas. These samples cover a broad range of tissues: blood, bone marrow, brain, breast, colon, heart, kidney, liver, lung, muscle, ovary, pancreas, prostate, skin, stomach, and uterus. To identify candidates for ADC development, we first classify tumors into subtypes through consensus clustering followed by a Monte Carlo implementation of our iterative ensemble classification methods. Next, we perform differential gene expression analysis between normal tissues and known or novel cancer subtypes. In one example, we have identified 50 breast cancer targets, 7 of which have already been developed as ADCs to the clinical trial stage by others, demonstrating the validity and promise of this approach (Fauteux et al., 2016). Glycoproteomics data are typically derived from small numbers of samples, making a population-based analysis less informative. Therefore, we have integrated glycoproteomic data into our target selection pipeline in two ways. First, glycoproteomics has been used to profile the cell surface of 11 tumor cell lines. Using an approach with high specificity for cell-surface glycoproteins, over 200 cell-surface proteins have been identified for each cell line. This data enables the selection of targets that are amenable to our in vitro functional assay for ADC activity, based on expression in our screen-adapted cell lines. Glycoproteomics has also been used to identify and prioritize targets upregulated during hypoxia or epithelial-mesenchymal transition, two important aspects of tumor biology. For example, cellular glycoproteins from four pancreatic cell lines were profiled under normoxic and hypoxic conditions, identifying >70 proteins upregulated under hypoxic conditions. These glycoproteomic datasets, in conjunction with the public data analysis, are being used to identify promising ADC targets. Based on these target selection methods, we are currently producing and screening thousands of NRC monoclonal and single-domain antibodies generated against a variety of cancer-associated cell surface targets and screening them for ADC activity, in vitro and in vivo.

Abnormality detection in mammography using deep convolutional neural networks - Xi, Pengcheng; Shu, Chang; Goubran, Rafik (2018 IEEE International Symposium on Medical Measurements and Applications (MeMeA), 2018)
Breast cancer is the most common cancer in women worldwide. The most common screening technology is mammography. To reduce the cost and workload of radiologists, we propose a computer aided detection approach for classifying and localizing calcifications and masses in mammogram images. To improve on conventional approaches, we apply deep convolutional neural networks (CNN) for automatic feature learning and classifier building. In computer-aided mammography, deep CNN classifiers cannot be trained directly on full mammogram images because of the loss of image details from resizing at input layers. Instead, our classifiers are trained on labelled image patches and then adapted to work on full mammogram images for localizing the abnormalities. State-of-the-art deep convolutional neural networks are compared on their performance of classifying the abnormalities. Experimental results indicate that VGGNet receives the best overall accuracy at 92.53% in classifications. For localizing abnormalities, ResNet is selected for computing class activation maps because it is ready to be deployed without structural change or further training. Our approach demonstrates that deep convolutional neural network classifiers have remarkable localization capabilities despite no supervision on the location of abnormalities is provided.

Data-driven modeling for energy consumption estimation - Yang, Chunsheng; Cheng, Qiangqiang; Lai, Pinhua; Liu, Jie; Guo, Hongyu (Exergy for A Better Environment and Improved Sustainability 2, 2018)
Energy consumption estimation for building energy management systems (BEMS) is one of the key factors in the success of energy saving measures in modern building operation, either residential buildings or commercial buildings. It provides a foundation for building owners to optimize not only the energy usage but also the operation to respond to the demand signals from smart grid. However, modeling energy consumption in traditional physical modeling techniques remains a challenge. To address this issue, we present a data mining-based methodology, as an alternative, for developing data-driven models to estimate energy consumption for BEMSs. Following the methodology, we developed data-driven models for estimating energy consumption for a chiller and a supply fan in an air handling unit (AHU) by using historic building operation data and weather forecast information. The models were evaluated with unseen data. The experimental results demonstrated that the data-driven models can estimate energy consumption for BEMS with promising accuracy.
Keywords: Building energy management systems (BEMS); data-driven modeling; Air handling unit (AHU); machine learning algorithms; demand response systems

A review of the role of explanations for user acceptance in black box systems - Vinson, Norman G.; Molyneaux, Heather; Lapointe, Jean-Francois (The Conference, 2018)
The opacity of black box AI systems’ decision-making has led to calls to modify these systems so they can provide explanations for their decisions. In this article we discuss what these explanations should address and what their nature should be in order to meet the concerns that have been raised and to prove satisfactory to users.

Enter the matrix: factorization uncovers knowledge from omics - Stein-O’brien, Genevieve L.; Arora, Raman; Culhane, Aedin C.; Favorov, Alexander V.; Garmire, Lana X.; Greene, Casey S.; Goff, Loyal A.; Li, Yifeng; Ngom, Aloune; Ochs, Michael F.; Xu, Yanxun; Fertig, Elana J. (Trends in Genetics, 2018)
Omics data contain signals from the molecular, physical, and kinetic inter- and intracellular interactions that control biological systems. Matrix factorization (MF) techniques can reveal low-dimensional structure from high-dimensional data that reflect these interactions. These techniques can uncover new biological knowledge from diverse high-throughput omics data in applications ranging from pathway discovery to timecourse analysis. We review exemplary applications of MF for systems-level analyses. We discuss appropriate applications of these methods, their limitations, and focus on the analysis of results to facilitate optimal biological interpretation. The inference of biologically relevant features with MF enables discovery from high-throughput data beyond the limits of current biological knowledge – answering questions from high-dimensional data that we have not yet thought to ask.
Keywords: genomics; unsupervised learning; matrix factorization; dimension reduction; single cell; deconvolution

Transcriptome dynamics associated with resistance and susceptibility against fusarium head blight in four wheat genotypes - Pan, Youlian; Liu, Ziying; Rocheleau, Hélène; Fauteux, François; Wang, Yunli; Mccartney, Curt; Ouellet, Thérèse (BMC Genomics, 2018)
Background: Fusarium head blight (FHB) of wheat in North America is caused mostly by the fungal pathogen Fusarium graminearum (Fg). Upon exposure to Fg, wheat initiates a series of cellular responses involving massive transcriptional reprogramming. In this study, we analyzed transcriptomics data of four wheat genotypes (Nyubai, Wuhan 1, HC374, and Shaw), at 2 and 4 days post inoculation (dpi) with Fg, using RNA-seq technology. Results: A total of 37,772 differentially expressed genes (DEGs) were identified, 28,961 from wheat and 8811 from the pathogen. The susceptible genotype Shaw exhibited the highest number of host and pathogen DEGs, including 2270 DEGs associating with FHB susceptibility. Protein serine/threonine kinases and LRR-RK were associated with susceptibility at 2 dpi, while several ethylene-responsive, WRKY, Myb, bZIP and NAC-domain containing transcription factors were associated with susceptibility at 4 dpi. In the three resistant genotypes, 220 DEGs were associated with resistance. Glutathione S-transferase (GST), membrane proteins and distinct LRR-RKs were associated with FHB resistance across the three genotypes. Genes with unique, high up-regulation by Fg in Wuhan 1 were mostly transiently expressed at 2 dpi, while many defense-associated genes were up-regulated at both 2 and 4 dpi in Nyubai; the majority of unique genes up-regulated in HC374 were detected at 4 dpi only. In the pathogen, most genes showed increased expression between 2 and 4 dpi in all genotypes, with stronger levels in the susceptible host; however two pectate lyases and a hydrolase were expressed higher at 2 dpi, and acetyltransferase activity was highly enriched at 4 dpi. Conclusions: There was an early up-regulation of LRR-RKs, different between susceptible and resistant genotypes; subsequently, distinct sets of genes associated with defense response were up-regulated. Differences in expression profiles among the resistant genotypes indicate genotype-specific defense mechanisms. This study also shows a greater resemblance in transcriptomics of HC374 to Nyubai, consistent with their sharing of two FHB resistance QTLs on 3BS and 5AS, compared to Wuhan 1 which carries one QTL on 2DL in common with HC374.
Keywords: fusarium head blight; differentially expressed genes; rna-seq; triticum aestivum; fusarium graminearum; pathogenesis; plant defense

Chemical derivatization strategy for extending the identification of MHC class I immunopeptides - Chen, Rui; Fauteux, Francois; Foote, Simon; Stupak, Jacek; Tremblay, Tammy-Lynn; Gurnani, Komal; Fulton, Kelly M.; Weeratna, Risini D.; Twine, Susan M.; Li, Jianjun (Analytical Chemistry, 2018)
Neoantigen-based therapeutic vaccines have a high potential impact on tumor eradication and patient survival. Mass spectrometry (MS)-based immunopeptidomics has the capacity to identify tumor-associated epitopes and pinpoint mutation-bearing major histocompatibility complex (MHC)-binding peptides. This approach presents several challenges, including the identification of low-abundance peptides. In addition, MHC peptides have much lower MS/MS identification rates than tryptic peptides due to their shorter sequence and lack of basic amino acid at C-termini. In this study, we report the development and application of a novel chemical derivatization strategy that combines the analysis of native, dimethylated, and alkylamidated peptides by liquid chromatography–tandem mass spectrometry (LC–MS/MS) to expand the coverage of the MHC peptidome. The results revealed that dimethylation increases hydrophobicity and ionization efficiency of MHC class I peptides, while alkylamidation significantly improves the fragmentation by producing more y-ions during MS/MS fragmentation. Thus, the combination of dimethylation and alkylamidation enabled the identification of peptides that could not be identified from the analysis of their native form. Using this strategy, we identified 3148 unique MHC I peptides from HCT 116 cell lines, compared to only 1388 peptides identified in their native form. Among these, 10 mutation-bearing peptides were identified with high confidence, indicating that this chemical derivatization strategy is a promising approach for neoantigen discovery in clinical applications.

Beyond k-NN: combining cluster analysis and classification for recommender systems - Alabdulrahman, Rabaa; Viktor, Herna; Paquet, Eric (Proceedings of the 10th International Joint Conference on Knowledge Discovery, Knowledge Engineering and Knowledge Management, 2018)
Recommendation systems have a wide application in e-business and have been successful in guiding users in their online purchases. The use of data mining techniques, to aid recommendation systems in their goal to learn the correct user profiles, is an active area of research. In most recent works, recommendations are obtained by applying a supervised learning method, notably the k-nearest neighbour (k-NN) algorithm. However, classification algorithms require a class label, and in many applications, such labels are not available, leading to extensive domain expert labelling. In addition, recommendation systems suffer from a data sparsity problem, i.e. the number of items purchased by a customer is typically a small subset of all ĉvailable products. One solution to overcome the labelling and data sparsity problems is to apply cluster analysis techniques prior to classification. Cluster analysis allows one to learn the natural groupings, i.e. similar customer profiles. In this paper, we s tudy the value of applying cluster analysis techniques to customer ratings prior to applying classification models. Our HCC-Learn framework combines content-based analysis in the cluster analysis stage, with collaborative filtering in the recommending stage. Our experimental results show the value of combining cluster analysis and classification against two real-world data sets.
Keywords: recommendation systems; hybrid model; data sparsity; cluster analysis; classification; learning

Editorial: Computational linguistics and literature - Szpakowicz, Stan; Feldman, Anna; Kazantseva, Anna (Frontiers in Digital Humanities, 2018)
Computational Linguistics—or, more technically, Natural Language Processing—has made great strides in the past several years. Machine learning (ML) is the technology of choice; deep learning, in particular, has pushed the envelope. These methods work best in narrow domains, given vast amounts of data and asked for information rather than for interpretation. Literary data are not limited by topic, and they are hardly ever plentiful enough. That is why work on such data has been, as yet, on the periphery of research and development in Computational Linguistics. This Research Topic aims to bring the processing of literary data to the attention of a broader audience.

Abstract 746: development of novel formats of anti-AXL ADCs - Jaramillo, Maria L.; Banville, Myriam; Robert, Alma; Meury, Luc; Acchione, Maurizio; Marcil, Anne; Gadoury, Christine; Wu, Cunle; Fortin, Yves; Henry, Kevin; Schrag, Joseph; Tu, The-Minh; et al. (Cancer Research, 2018)
AXL is a member of the Tyro3- AXL -Mer (TAM) receptor tyrosine kinase subfamily which has been associated with several cellular functions including growth, migration, aggregation, and anti-inflammation (Li Y et al., 2009) via activation through its ligand, Gas6. Originally identified as an oncogene in chronic myelogenous leukemia, expression of Axl has been reported to be upregulated in a variety of cancers including breast, gastric, prostate, ovarian, and lung. AXL expression has been shown to be negatively associated with patient survival and implicated in epithelial-to-mesenchymal transition, a process closely linked with invasive motility and metastasis of malignant cells. Several recent studies have reported that AXL is overexpressed during resistance to chemotherapy and other molecularly targeted therapies, as well as during hypoxia (Schoumacher M et al 2017). Consequently, Axl is promising therapeutic target for development into ADCs for the first or second line treatment of cancer. At the National Research Council (NRC) of Canada, we have selected mouse monoclonal (mAbs) or llama derived single domain antibodies (sdAbs) that are selective for the extracellular domain of human Axl and which have been shown to be internalized into Axl expressing cells for antibody drug conjugate (ADC) development using a surrogate ADC screen. These antibodies were also characterized based on their binding domains and ability to compete with Gas6, the extracellular ligand for Axl. A panel of Axl-specific ADCs was subsequently directly conjugated to maytansine, the microtubule disrupting agent through a noncleavable linker. Axl-DM1 ADCs were shown to efficiently induce cytotoxicity in vitro, in Axl expressing cells including breast (MDA-MB 231), lung (NCI-H292) and ovarian (SKOV3) cell lines with sub nM potencies achieved with both sdAb and conventional mAb-based ADCs. When tested in vivo using ovarian (SKOV3) and breast cancer (MDA-MB 231) xenograft models, Axl-DM1 ADCs were shown to have potent anti-tumor activity. Biparatopic antibodies (i.e. those which target two non-overlapping epitopes) directed against HER2 have been previously shown to induce target clustering and promote robust internalization, lysosomal trafficking, and degradation (LI JY et al 2016). Since these properties are important in the mechanism of action of ADCs, we have further tested anti-Axl antibodies in various configurations and have identified potent biparatopic antibodies for further development into ADCs.

Product deterioration based demand forecasting and service supply model for MRO service chain - Li, Ling; Liu, Min; Shen, Weiming; Cheng, Guoqing (IEEE Transactions on Engineering Management, 2018)
As one kind of product service supply chains, maintenance, repair, and overhaul (MRO) service chain manages the physical industrial products and the related MRO services, and performs MRO service supply activities depending on demand planning and operational measures. The spare part and service demands in MRO service chain are typically uncertain because of product deterioration and random failure. The existing works mainly focus on providing the best possible modeling of demand characteristics (such as price, service level, and stock level) without aiming at demand generation process itself. We try to leverage the stochastic process based product deterioration model to characterize the generation of such uncertain demands, and then develop a predictive and proactive service policy. In our model, geometric process is combined with Gamma process and stochastic monotonicity of geometric process is utilized to quantify product's accelerated deterioration. Based on the developed accelerated deterioration model, the uncertain demands in MRO service chain can be forecasted, and the analytic expression of two-dimensional joint policy involving the scheduled service plan (inspection interval) and the stochastic service plan (replacement time) is derived. Model demonstration on MRO service management of continuous caster illustrates the feasibility and practicality of the proposed method.

Non-noble iron group (Fe, Co, Ni)-based oxide electrocatalysts for aqueous zinc–air batteries: recent progress, challenges, and perspectives - Yi, Jin; Liu, Xiaoyu; Liang, Pengcheng; Wu, Kai; Xu, Jie; Liu, Yuyu; Zhang, Jiujun (Organometallics, 2018)
With the increasing energy demand, energy conversion and storage technology has garnered intense attention. As one of the competitive electrochemical energy technologies, the zinc–air battery (ZAB) has been considered to be a promising candidate due to its advantages, including low cost and environmental friendliness. To overcome its technical challenges of low activity and stability of ZAB air electrode electrocatalysts, substantial efforts have been made to develop highly active and stable materials for improving the performance. In this paper, a comprehensive review of one type of the ZAB electrocatalyst, that is, iron group (Fe, Co, Ni)-based oxides, is provided. The discussion will be concentrated on the recent progress and challenges associated with this type of electrocatalyst as well as corresponding perspectives.

Multiconjugate adaptive optics simulator for the Thirty Meter Telescope: design, implementation, and results - Mieda, Etsuko; Veran, Jean-Pierre; Rosensteiner, Matthias; Turri, Paolo; Andersen, David; Herriot, Glen; Lardiere, Olivier; Spano, Paolo (Journal of Astronomical Telescopes, Instruments, and Systems, 2018)
We present a multiconjugate adaptive optics (MCAO) system simulator bench, Herzberg NFIRAOS Optical Simulator (HeNOS). HeNOS is developed to validate the performance of the MCAO system for the Thirty Meter Telescope, as well as to demonstrate techniques critical for future AO developments. We focus on describing the derivations of parameters that scale the 30-m telescope AO system down to a bench experiment and explain how these parameters are practically implemented on an optical bench. While referring to other papers for details of AO technique developments using HeNOS, we introduce the functionality of HeNOS, in particular, three different single-conjugate AO modes that HeNOS currently offers: a laser guide star AO with a Shack–Hartmann wavefront sensor, a natural guide star AO with a pyramid wavefront sensor, and a laser guide star AO with a sodium spot elongation on the Shack–Hartmann corrected by a truth wavefront sensing on a natural guide star. Laser tomography AO and ultimate MCAO are being prepared to be implemented in the near future.
Keywords: adaptive optics; astronomy; wavefront sensors; Thirty Meter Telescope; pyramid wavefront sensors

The JCMT Gould Belt Survey: SCUBA-2 data reduction methods and Gaussian source recovery analysis - Kirk, Helen; Hatchell, Jennifer; Johnstone, Doug; Berry, David; Jenness, Tim; Buckle, Jane; Mairs, Steve; Rosolowsky, Erik; Francesco, James Di; Sadavoy, Sarah; J. Currie, Malcolm; Broekhoven-Fiene, Hannah; et al. (The Astrophysical Journal Supplement Series, 2018)
The James Clerk Maxwell Telescope (JCMT) Gould Belt Survey (GBS) was one of the first legacy surveys with the JCMT in Hawaii, mapping 47 deg2 of nearby (<500 pc) molecular clouds in dust continuum emission at 850 and 450 μm, as well as a more limited area in lines of various CO isotopologues. While molecular clouds and the material that forms stars have structures on many size scales, their larger-scale structures are difficult to observe reliably in the submillimeter regime using ground-based facilities. In this paper, we quantify the extent to which three subsequent data reduction methods employed by the JCMT GBS accurately recover emission structures of various size scales, in particular, dense cores, which are the focus of many GBS science goals. With our current best data reduction procedure, we expect to recover 100% of structures with Gaussian σ sizes of ≤30'' and intensity peaks of at least five times the local noise for isolated peaks of emission. The measured sizes and peak fluxes of these compact structures are reliable (within 15% of the input values), but source recovery and reliability both decrease significantly for larger emission structures and fainter peaks. Additional factors such as source crowding have not been tested in our analysis. The most recent JCMT GBS data release includes pointing corrections, and we demonstrate that these tend to decrease the sizes and increase the peak intensities of compact sources in our data set, mostly at a low level (several percent), but occasionally with notable improvement.
Keywords: dust, extinction; ISM: structure; stars: formation; submillimeter: ISM

A critical review on isotopic fractionation correction methods for accurate isotope amount ratio measurements by MC-ICP-MS - Yang, Lu; Tong, Shuoyun; Zhou, Lian; Hu, Zhaochu; Mester, Zoltán; Meija, Juris (Journal of Analytical Atomic Spectrometry, 2018)
Multicollector inductively coupled plasma mass spectrometry (MC-ICP-MS) is a powerful research tool for obtaining accurate and precise isotope amount ratios in a wide range of applications. Compared to thermal ionization mass spectrometry (TIMS), MC-ICP-MS suffers from much larger isotopic fractionation/mass bias. In addition to the commonly believed mass-dependent fractionation (MDF) phenomenon, recognition and reporting of mass-independent fractionation (MIF) within MC-ICP-MS itself has proliferated in the last decade. Traditional isotopic fractionation correction models, such as the widely used exponential and Russell laws, were designed to account for the mass-dependent fractionation as a function of nuclide mass. The latest findings of MIF within MC-ICP-MS itself have a significant impact on the choice of these isotopic fractionation correction models, as the use of mass-dependent models to correct for instrumental bias for isotopes which display mass-independent fractionation would result in biased isotope amount ratios. This review focuses on the latest developments related to isotopic fractionation and its correction models for MC-ICP-MS, and the implications of MIF within MC-ICP-MS on several popular mass bias correction models for obtaining accurate isotope amount ratios by MC-ICP-MS are discussed in detail.

Transmission infrared spectroscopy for rapid quantification of fat, protein, and lactose concentrations in human milk - Elsohaby, Ibrahim; Mcclure, J. Trenton; Riley, Christopher B.; Bryanton, Janet; Bigsby, Kathryn; Shaw, R. Anthony (Journal of Perinatology, 2018)
Objective: To develop partial least squares regression (PLSR) calibration models in combination with transmission infrared (TIR) spectroscopy for rapid and optimal quantification of human milk macronutrient concentrations. Study design: Human milk samples (n = 306) were characterized simultaneously by reference chemical analytical methods and TIR spectroscopy. Reference macronutrient concentrations were linked to pre-processed spectra and divided into two (training and test) sets. PLSR was used to develop trial calibration models using training set, and the test set was used to assess the accuracy of the trial analytical methods. Results: For the methods selected as optimal, the concordance correlation coefficients between reference and TIR-based methods were 0.93 for fat, 0.96 for protein, and 0.52 for lactose. The Bland-Altman plots showed no evidence of systematic bias between TIR and reference methods. Conclusions: TIR spectroscopy provides the basis for accurate and rapid quantification of human milk fat and protein concentrations but is less accurate for measuring lactose concentration.

The S-layer protein of a Clostridium difficile SLCT-11 strain displays a complex glycan required for normal cell growth and morphology - Richards, Emma; Bouché, Laura; Panico, Maria; Arbeloa, Ana; Vinogradov, Evgeny; Morris, Howard; Wren, Brendan; Logan, Susan M.; Dell, Anne; Fairweather, Neil F. (Journal of Biological Chemistry, 2018)
Clostridium difficile is a bacterial pathogen that causes major health challenges worldwide. It has a well-characterized surface (S)-layer, a para-crystalline proteinaceous layer surrounding the cell wall. In many bacterial and archaeal species, the S-layer is glycosylated, but no such modifications have been demonstrated in C. difficile. Here, we show that a C. difficilestrain of S-layer cassette type 11, Ox247, has a complex glycan attached via an O-linkage to Thr-38 of the S-layer low-molecular-weight subunit. Using mass spectrometry and NMR, we fully characterized this glycan. We present evidence that it is composed of three domains: (i) a core peptide–linked tetrasaccharide with the sequence -4-α-Rha-3-α-Rha-3-α-Rha-3-β-Gal-peptide, (ii) a repeating pentasaccharide with the sequence -4-β-Rha-4-α-Glc-3-β-Rha-4-(α-Rib-3-)β-Rha-, and (iii) a non-reducing end–terminal 2,3 cyclophosphoryl-rhamnose attached to a ribose-branched sub-terminal rhamnose residue. The Ox247 genome contains a 24 kb locus containing genes for synthesis and protein attachment of this glycan. Mutations in genes within this locus altered or completely abrogated formation of this glycan, and their phenotypes suggested that this S-layer modification may affect sporulation, cell length, and biofilm formation of C. difficile. In summary, our findings indicate that the S-layer protein of SLCT-11 strains displays a complex glycan and suggest that this glycan is required for C. difficilesporulation and control of cell shape, a discovery with implications for the development of antimicrobials targeting the S-layer.
Keywords: Clostridium difficile; surface layer; virulence; mass spectrometry (MS); microbiology; genetics; glycoprotein structure; uclear magnetic resonance (NMR)

Evaluation of phenospectral dynamics with Sentinel-2A using a bottom-up approach in a northern ombrotrophic peatland - Arroyo-Mora, J. P.; Kalacska, M.; Soffer, R.; Ifimov, G.; Leblanc, G.; Schaaf, E. S.; Lucanus, O. (Remote Sensing of Environment, 2018)
Peatlands cover very large extents in northern regions and play a significant role in the global carbon cycle by functioning as a carbon sink. Large-scale satellite based monitoring systems, such as the Sentinel-2 Multispectral Instrument (MSI), are necessary to improve our understanding of how these ecosystems respond to climate change by providing verifiable land products. For instance, satellite-based land product validation approaches can benefit from airborne hyperspectral imagery and in-situ data, which provide higher spatial and spectral resolution baselines, ideal for measuring vegetation changes (e.g. phenology, LAI) at local scales. Here, we assessed the short-term phenospectral dynamics (spectral changes indicated by specific spectral features as a function of phenology) of five ombrotrophic peatland vegetation physiognomies over four dates at the Mer Bleue bog in Canada. We took advantage of a unique remote sensing data acquisition campaign aiming to validate Sentinel-2A land products, and analyzed three spatially and spectrally distinctive datasets (i.e. field spectra, VISNIR airborne hyperspectral imagery (HSI) and Sentinel-2A imagery) over the first half of the 2016 growing season. By implementing a bottom-up approach, first we assessed the airborne HSI's capability to detect phenological changes as compared to in-situ acquired field spectroscopy measurements in a 10 ha area at Mer Bleue and evaluated the spectral features characteristic of these phenological changes. Second, over the entire Mer Bleue area (28,000 ha), we compared a series of four Sentinel-2A images to four airborne HSI mosaics (spatially and spectrally resampled to Sentinel-2A) to assess the utility of Sentinel-2A for detecting small spectral variations due to phenological changes (i.e. greening). In addition, for this second comparison, three spectral vegetation indices were derived from the Sentinel-2A images and the airborne HSI mosaics. The spectral comparisons between the airborne HSI and the field spectroscopy data revealed clear phenological changes from the airborne HSI. For instance, a closer agreement between reflectance measured by the field spectrometer and the airborne HSI spectral response was found in the visible region (450–680 nm). A greater difference however, was consistently seen in the near-infrared region (681–866 nm) across the four dates. Narrow spectral features in three regions of the visible range (global minima, red absorption, green peak), indicating changes in vegetation colour, were consistent for both datasets and with expected phenological patterns at Mer Bleue. At the landscape level, Sentinel-2A mirrored the spectral changes depicted by the resampled HSI data. However, band level, pair-wise comparisons showed significant differences (p < 0.001) in reflectance for each band, with Sentinel-2A exhibiting higher reflectance values than the HSI for the first three dates. Only for the last date (June 23rd) did the airborne HSI have higher reflectance values or no significant difference with the Sentinel-2A data. Overall, our three datasets captured the short-term phenological changes at Mer Bleue and have provided promising results in terms of using the Sentinel-2A MSI sensor to monitor these changes at the landscape level.
Keywords: sentinel-2 MSI; mer Bleue; phenospectral; spectroscopy; airborne hyperspectral; CASI; multi-datasets; bog; land product validation

Data and systems for medication-related text classification and concept normalization from Twitter: insights from the Social Media Mining for Health (SMM4H)-2017 shared task - Sarker, Abeed; Belousov, Maksim; Friedrichs, Jasper; Hakala, Kai; Kiritchenko, Svetlana; Mehryary, Farrokh; Han, Sifei; Tran, Tung; Rios, Anthony; Kavuluru, Ramakanth; De Bruijn, Berry; Ginter, Filip; et al. (Journal of the American Medical Informatics Association, 2018)
Objective: We executed the Social Media Mining for Health (SMM4H) 2017 shared tasks to enable the community-driven development and large-scale evaluation of automatic text processing methods for the classification and normalization of health-related text from social media. An additional objective was to publicly release manually annotated data. Materials and Methods: We organized 3 independent subtasks: automatic classification of self-reports of 1) adverse drug reactions (ADRs) and 2) medication consumption, from medication-mentioning tweets, and 3) normalization of ADR expressions. Training data consisted of 15 717 annotated tweets for (1), 10 260 for (2), and 6650 ADR phrases and identifiers for (3); and exhibited typical properties of social-media-based health-related texts. Systems were evaluated using 9961, 7513, and 2500 instances for the 3 subtasks, respectively. We evaluated performances of classes of methods and ensembles of system combinations following the shared tasks. Results: Among 55 system runs, the best system scores for the 3 subtasks were 0.435 (ADR class F1-score) for subtask-1, 0.693 (micro-averaged F1-score over two classes) for subtask-2, and 88.5% (accuracy) for subtask-3. Ensembles of system combinations obtained best scores of 0.476, 0.702, and 88.7%, outperforming individual systems. Discussion: Among individual systems, support vector machines and convolutional neural networks showed high performance. Performance gains achieved by ensembles of system combinations suggest that such strategies may be suitable for operational systems relying on difficult text classification tasks (eg, subtask-1). Conclusions: Data imbalance and lack of context remain challenges for natural language processing of social media text. Annotated data from the shared task have been made available as reference standards for future studies (http://dx.doi.org/10.17632/rxwfb3tysd.1).
gold access
Keywords: social media; text mining; natural language processing; pharmacovigilance; machine learning

A multi-parent faba bean (Vicia faba L.) population for future genomic studies - Khazaei, Hamid; Stoddard, Frederick L.; Purves, Randy W.; Vandenberg, Albert (Plant Genetic Resources: Characterization and Utilization, 2018)
Faba bean (Vicia faba L.) is a valuable grain legume and a staple protein crop in many countries. Its large and complex genome requires novel approaches for its genetic dissection. Here we introduce a multi-parent population developed from four founders (ILB 938/2, Disco/2, IG 114476 and IG 132238). The selection of parental lines was based on geographic (Colombia, France, Bangladesh and China), genetic and phenotypic diversity. The parental lines were inbred and then genotyped using 875 single nucleotide polymorphism (SNP) markers. Based on molecular data, the parents had high homozygosity and high genetic distance among them. The population segregates for several important traits such as seed morphology, seed chemistry, phenology, plant architecture, drought response, yield and its components, and resistance to Botrytis fabae. The population was checked for unbiased segregation in each generation by observing simply inherited Mendelian traits such as stipule spot pigmentation (SSP) and flower colour at different generations. All 1200 four-way cross F1 plants had pigmented flowers and stipule spots. The segregation ratios for white flower colour (single gene, zt2) fit 7:1, 13:3 and 25:7 at F2, F3 and F4 generations, respectively, and the segregation ratio of SSP (two recessive unlinked genes, ssp1 and ssp2) fit 49:15 and 169:87 at the F2 and F3 generations, respectively, demonstrating unbiased generation advance. We will subject the F5 generation of this population to a high-throughput SNP array and make it available for further phenotyping and genotyping.
Keywords: faba bean; multi-parent population; phenotyping; pigmentation

A guide creating SAE AS5562 ice crystal, mixed phase and rain conditions in a wind tunnel environment - Clark, Catherine; Orchard, David M.; Chevrette, Gislain (2018 Atmospheric and Space Environments Conference, 2018)
In response to the requirements set out in SAE AS5562, the National Research Council Canada has invested significant effort in expanding the Altitude Icing Wind Tunnel operating envelope to provide ice crystal, mixed phase and rain conditions in the test section. These environments are challenging to create as they require fundamentally different mechanical systems and calibration instrumentation than those for classic supercooled liquid droplet environments. This document offers guidance on the creation of these conditions in a closed-circuit, temperature-controlled wind tunnel environment based on the experiences at the NRC Altitude Icing Wind Tunnel. The discussion includes droplet size and water content measurement techniques, variables to consider during calibration, and challenges that still need to be addressed.

Application of the hot stamping process to aluminum alloy structural components - Samuel, Ehab (Light Metals 2018, 2018)
It has long been accepted that one primary way to achieve vehicle lightweighting is to incorporate aluminum alloys wherever possible. As such, panel-type components have since been produced using these alloys. Structural components, however, still present a challenge for the aluminum hot forming field. In order to help bridge this knowledge gap, the National Research Council Canada (NRC) explored the applicability of subjecting two heat-treatable aluminum alloys, namely a medium strength 6082 and a high strength 7021, to a rapid hot forming process, notably hot stamping, in order to simultaneously form and quench a part destined for structural applications. A full-scale structural part was hot stamped in ~30 s, which is in very good agreement with the time constraints reported in the literature. Differential scanning calorimetry was used to optimize blank soaking conditions. Finally, artificial aging tests were carried out to restore the T6-temper strength of the initial as-received sheet.
Keywords: aluminum alloys; vehicle lightweighting; structural components; hot forming; hot stamping

Sex-disaggregated systematics in Canadian time allocation committee telescope proposal reviews - Spekkens, Kristine; Cofie, Nicholas; Crabtree, Dennis R.; Peck, Alison B.; Benn, Chris R.; Seaman, Robert L. (Observatory Operations: Strategies, Processes, and Systems VII, 2018)
Recent studies have shown that the proposal peer review processes employed by a variety of organizations to allocate astronomical telescope time produce outcomes that are systematically biased depending on whether proposal's principal investigator (PI) is a man or a woman. Using Canada-France-Hawaii Telescope (CFHT) and Gemini Observatory proposal statistics from Canada over 10 recent proposal cycles, we assess whether or not the mean proposal scores assigned by the National Research Council's (NRC's) Canadian Time Allocation Committee (CanTAC) also correlate significantly with PI sex. Classical t-tests, bootstrap and jackknife replications show that proposals submitted by women were rated significantly worse than those submitted by men. We subdivide the data in order to investigate sex-disaggregated statistics in relation to PI career stage (faculty vs. non-faculty), telescope requested, scientific review panel, observing semester, and the PhD year of faculty PIs. Consistent with the bivariate results, a multivariate regression analysis controlling for other covariates confirmed that PI sex is the only significant predictor of proposal rating scores for the sample as a whole, although differences emerge for proposals submitted by faculty and non-faculty PIs. While further research is needed to explain our results, it is possible that implicit social cognition is at work. NRC and CanTAC have taken steps to mitigate this possibility by altering proposal author lists in order to conceal the PI's identity among co-investigators. We recommend that the impact of this measure on mitigating bias in future observing semesters be quantitatively assessed using statistical techniques such as those employed here.

Effects of aerodynamic blockage on stagnation collection efficiency in a wind tunnel icing environment - Clark, Catherine (2018 Atmospheric and Space Environments Conference, 2018)
A multi-phase research program in the National Research Council of Canada’s Altitude Icing Wind Tunnel was completed over the course of two years investigating the effects of aerodynamic blockage on the ice accumulation at the leading edge of airfoils. This work has particular application to the testing of unmanned aerial vehicles in icing conditions; the wing sections for these vehicles are often tested at full-scale and create significant aerodynamic blockage in the test section. It has been observed that for large models, the ice accumulation at the stagnation point does not match theoretical predictions based on the empty tunnel calibration. Using NACA 0012 and NACA 4412 airfoil models, a correlation has been established that suggests aerodynamic blockage increases the stagnation point collection efficiency when the droplet Reynolds number is less than 100. The experimental test program covered a range of droplet sizes, liquid water contents and airspeeds typically observed when testing airfoils in the NRC icing wind tunnel.

Ice crystal icing physics study using a NACA 0012 airfoil at the National Research Council of Canada’s Research Altitude Test Facility - Struk, Peter M.; King, Michael C.; Bartkus, Tadas P.; Tsao, Jen-Ching; Fuleki, Dan; Neuteboom, Martin; Chalmers, Jennifer (2018 Atmospheric and Space Environments Conference, 2018)
This paper presents results from a study of the fundamental physics of ice-crystal ice accretion using a NACA 0012 airfoil at the National Research Council of Canada (NRC) Research Altitude Test Facility in August 2017. These tests were a continuation of work which began in 2010 as part of a joint collaboration between NASA and NRC. The research seeks to generate icing conditions representative of those that occur inside a jet engine when ingesting ice crystals. In this test, an airfoil was exposed to mixed-phase icing conditions and the resulting ice accretions were recorded and analyzed. This paper details the specific objectives, procedures, and measurements which included the aero-thermal and cloud measurements. The objectives were built upon observations and hypothesis generated from several previous test campaigns regarding mixed-phase ice-crystal icing. The specific objectives included (A) ice accretions under different wet-bulb temperatures, (B) investigations of steady-state ice shapes previously reported in the literature, (C) total water content variations in search of a threshold for accretion, and (D) probe characterization related to measuring melt fraction which is important to characterize the mixed-phase condition. The resulting ice accretions and conditions leading to such accretions are intended to help extend NASA’s predictive ice-accretion codes to include conditions occurring in engine ice-crystal icing.

Characterization of an engine icing tunnel and comparison to liquid water content from an evaporation model - Davison, Craig R.; Macleod, James D. (2018 Atmospheric and Space Environments Conference, 2018)
The National Research Council Canada (NRC) operates several engine icing facilities. This paper discusses recent improvements to an intermediate size engine icing tunnel and describes the characterisation of the liquid water content (LWC) provided by the spray mast. The measured values are compared to the LWC predicted by the NRC evaporation model, which is used to control the tunnel cloud conditions.

Experimental investigations of the NASA common research semi-span model in the NRC 5-ft trisonic wind tunnel - Broughton, Cabot A.; Benmeddour, Ali; Mebarki, Youssef; Rivers, Melissa B. (2018 Aerodynamic Measurement Technology and Ground Testing Conference, 2018)
An experimental aerodynamic investigation of the 2.7 percent scale NASA Common Research Model (CRM) in a semispan configuration was conducted in the National Research Council, Canada (NRC) 5-Ft. Trisonic Wind Tunnel. Data were obtained at a chord Reynolds number of 5 million for five model configurations. Model forces and moments, wing surface pressures and wing bending and twist were obtained in the current investigation. No semispan support corrections were made to the data published in this paper. Comparison of the data acquired in the semispan investigation are made with the published wall interference corrected data from the NASA fullspan tests conducted at both the NASA National Transonic Facility and 11-Ft. Transonic Wind Tunnel Facility. Comparison of the force and moment data in an absolute sense is made for the Wing-Body (WB) configuration while most of the remaining configurations are compared with the fullspan data in an incremental sense using the WB configuration as the baseline. For the WB configuration, the angle of attack and pitching moment coefficient as a function of lift coefficient were found to be within 0.1° and 0.01 of the fullspan data, respectively. However, the measured semispan drag coefficient was significantly higher compared with the fullspan data. The incremental effects of the nacelle/pylon to the WB on all force and moment coefficients were found to be consistent with the fullspan tests within the estimated experimental uncertainty. The incremental and absolute pitching moment effects of the horizontal stabilizer in the semispan test were found to be significantly different compared to the fullspan experiments. However, assessment of the biases or limitations of the semispan support interference on the aerodynamic characteristics of a fuselage mounted horizontal tail plane are not yet clearly understood as the reference fullspan data contain the blade sting support interference.

Development of a small modular multi-stage axial compressor for ice crystal icing research - Currie, Thomas C. (2018 Atmospheric and Space Environments Conference, 2018)
This paper describes a Small Modular Axial Compressor Rig (SMACR) being developed by the National Research Council of Canada (NRC) for use in research into ice crystal icing (ICI) of jet engine compressors. This compressor will allow a variety of effects that cannot be simulated with static rigs, such as those used in previous ICI research at NRC, to be investigated. These include particle fragmentation, centrifuging and melting by the heat of compression. The paper describes the design of a single stage that can be replicated to obtain a multi-stage compressor by simply changing the rotor and stator and other minor hardware items. The modularity is achieved by using an independent high speed electric motor for each stage and mounting the (overhung) rotor directly on the motor output shaft. Preliminary test results are presented for the modular drive assembly combined with the 1st stage rotor and stator for sea level pressure and lower pressures of ~69kPa and 47kPa obtained by testing in a purpose-built low pressure (LP) plenum. These results show that the 1st stage can deliver the target power of approximately 15kW at rotational speeds over 30000RPM, which should be sufficient for fragmentation studies. Simulation results for ice particle melting in the compressor with 2 and 3 stages and fully glaciated inlet conditions show that 2 stages will be able to produce a discharge melt ratio (MR) above the lower end of the “plateau” for ICI, at least at the lowest targeted operating pressure of 34.5kPa (5psia) where low melting will result from high evaporative cooling. An additional (3rd) stage will likely be required to produce an MR approaching the upper end of the plateau at these conditions.

Supporting trust and engagement in personalized learning - Kondratova, Irina; Molyneaux, Heather; Fournier, Helene (Learning and Collaboration Technologies. Learning and Teaching, 2018)
This paper discusses the benefits and challenges associated with supporting learner trust and engagement in personalized learning. Personalized learning refers to instruction in which the pace of learning and the instructional approach are optimized for the needs of each learner. Quality of personalization depends on information collected from the learner and stored in a personal profile. The authors elaborate on research and design solutions to support privacy, trust and engagement in the context of the Learning and Performance Support (LPSS) program at the National Research Council of Canada. The paper builds on earlier work by the authors related to learning personalization, trust and privacy, and on the results of user surveys and usability studies of the LPSS system related to trust, privacy and user engagement.
Keywords: human-computer interfaces; technology support for collaboration and learning; personalization; trust; digital ethics; learner engagement

Off-axis point spread function characterization in laser guide star adaptive optics systems - Beltramo-Martin, O.; Correia, C. M.; Mieda, E.; Neichel, B.; Fusco, T.; Witzel, G.; Lu, J. R.; Véran, J-P (Monthly Notices of the Royal Astronomical Society, 2018)
Adaptive optics (AO) restore the angular resolution of ground-based telescopes, but at the cost of delivering a time- and space-varying point spread function (PSF) with a complex shape. PSF knowledge is crucial for breaking existing limits on the measured accuracy of photometry and astrometry in science observations. In this paper, we concentrate our analyses of the anisoplanatism signature only on to the PSF. For large-field observations (20 arcmin) with single-conjugated AO, PSFs are strongly elongated due to anisoplanatism that manifests itself as three different terms for laser guide star (LGS) systems: angular, focal and tilt anisoplanatism. First, we propose a generalized model that relies on a point-wise decomposition of the phase and encompasses the non-stationarity of LGS systems. We demonstrate that it is more accurate and less computationally demanding than existing models: it agrees with end-to-end physical-optics simulations to within 0.1 per cent of PSF measurables, such as the Strehl ratio, FWHM and the fraction of variance unexplained (FVU). Secondly, we study off-axis PSF modelling with respect to the C2n(h) Cn2(h) profile (heights and fractional weights). For 10-mclass telescopes, PSF morphology is estimated at the 1  per cent level as long as we model the atmosphere with at least seven layers, whose heights and weights are known with precisions of 200 m and 10 per cent, respectively. As a verification test, we used the Canada’s National Research Council – Herzberg NFIRAOS Optical Simulator (HeNOS) testbed data, featuring four lasers. We highlight the capability of retrieving off-axis PSF characteristics within 10 per cent of the FVU, which complies with the expected range from the sensitivity analysis. Our new off-axis PSF modelling method lays the groundwork for testing on-sky in the near future.
Keywords: atmospheric effects; instrumentation: adaptive optics; methods: analytical; methods: data analysis

Combustion performance and unburned hydrocarbon emissions of a natural gas–diesel dual fuel engine at a low load condition - Guo, Hongsheng; Liko, Brian; Luque, Luis; Littlejohns, Jennifer (Journal of Engineering for Gas Turbines and Power, 2018)
The combustion of natural gas reduces fuel cost and generates less emissions of carbon dioxide and particulate matter (PM) than diesel and gasoline. Replacing diesel by natural gas in internal combustion engines is of great interest for transportation and stationary power generation. Dual fuel combustion is an efficient way to burn natural gas in internal combustion engines. In natural gas–diesel dual fuel engines, unburned hydrocarbon emissions increase with increasing natural gas fraction. Many studies have been conducted to improve the performance of natural gas–diesel dual fuel engines and reported the performance of combustion and emissions of regulated pollutants and total unburned hydrocarbon at various engine operating strategies. However, little has been reported on the emissions of different unburned hydrocarbon components. In this paper, an experimental investigation was conducted to investigate the combustion performance and emissions of various unburned hydrocarbon components, including methane, ethane, ethylene, acetylene, propylene, formaldehyde, acetaldehyde, and benzaldehyde, at a low engine load condition. The operating conditions, such as engine speed, load, intake temperature, and pressure, were well controlled during the experiment. The combustion and emissions performance of pure diesel and natural gas–diesel dual fuel combustion were compared. The effect of diesel injection timing was analyzed. The results show that appropriately advancing diesel injection timing to form a homogeneous charge compression ignition (HCCI)-like combustion is beneficial to natural gas–diesel dual fuel combustion at low load conditions. The emissions of different unburned hydrocarbon components changed in dual fuel combustion, with emissions of some unburned hydrocarbon components being primarily due to the combustion of natural gas, while those of others being more related to diesel combustion.

Important factors affecting the gouging abrasion resistance of materials - (Jimmy) Jiang, Jiaren; Xie, Yongsong; Qian, Weimin; Hall, Robert (Minerals Engineering, 2018)
Gouging abrasion occurs in many processes in comminution where large and hard abrasives such as rocks/ores are handled with high contact or impact stresses. In the past decade or so, the National Research Council Canada has systematically investigated the gouging abrasion performance of a wide range of materials per the ASTM G81 standard testing method using a jaw crusher. Materials evaluated include carbon and low alloy steels, high alloy tool steels, austenitic manganese steel, white cast irons, austempered ductile irons, chromium carbide and tungsten carbide overlays. In this paper, the main test results are summarized and the key properties/characteristics that are conducive to enhancing materials’ gouging abrasion resistance are discussed.
Keywords: gouging abrasion; jaw crusher; abrasion resistance; ASTM G81 standard

Understanding of nafion membrane additive behaviors in proton exchange membrane fuel cell conditioning - Zhao, Nana; Xie, Zhong; Shi, Zhiqing (Journal of Electrochemical Energy Conversion and Storage, 2018)
Durability and cost are the two major factors limiting the large-scale implementation of fuel cell technology for use in commercial, residential, or transportation applications. The conditioning cost is usually negligible for making proton exchange membrane fuel cells (PEMFCs) at R&D or demo stage with several tens of stacks each year. However, with industry's focus shifting from component development to commercial high-volume manufacturing, the conditioning process requires significant additional capital investments and operating costs, thus becomes one of the bottlenecks for PEMFC manufacturing, particularly at a high production volume (>1000 stack/year). To understand the mechanisms behind PEMFC conditioning, and to potentially reduce conditioning time or even to eliminate the conditioning process, the conditioning behaviors of commercial Nafion™ XL100 and Nafion® NRE 211 membranes were studied. The potential effects of the membrane additive on fuel cell conditioning were diagnosed using in situ electrochemical impedance spectroscopy (EIS). It was found that the membrane additive led to the significant variation of the charge transfer resistance in EIS during conditioning, which affected the conditioning behavior of the membrane electrode assembly (MEA).

Zika virus crosses an in vitro human blood brain barrier model - Alimonti, Judie B.; Ribecco-Lutkiewicz, Maria; Sodja, Caroline; Jezierski, Anna; Stanimirovic, Danica B.; Liu, Qing; Haqqani, Arsalan S.; Conlan, Wayne; Bani-Yaghoub, Mahmud (Fluids and Barriers of the CNS, 2018)
Zika virus (ZIKV) is a flavivirus that is highly neurotropic causing congenital abnormalities and neurological damage to the central nervous systems (CNS). In this study, we used a human induced pluripotent stem cell (iPSC)-derived blood brain barrier (BBB) model to demonstrate that ZIKV can infect brain endothelial cells (i-BECs) without compromising the BBB barrier integrity or permeability. Although no disruption to the BBB was observed post-infection, ZIKV particles were released on the abluminal side of the BBB model and infected underlying iPSC-derived neural progenitor cells (i-NPs). AXL, a putative ZIKV cellular entry receptor, was also highly expressed in ZIKV-susceptible i-BEC and i-NPs. This iPSC-derived BBB model can help elucidate the mechanism by which ZIKV can infect BECs, cross the BBB and gain access to the CNS.
Keywords: Zika virus; brain endothelial cells; blood–brain barrier model; iPSC; AXL; neural progenitors

Why model evacuee decision-making? - Gwynne, S. M. V.; Hunt, A. L. E. (Safety Science, 2018)
The purpose of this article is to outline the theoretical and practical benefits of representing the evacuee decision-making process within an agent-based simulation tool. This rationale is important as the development of a comprehensive representation of evacuee decision-making will be expensive, requiring a great deal of time, expertise and effort. However, the theoretical and practical benefits are such that this effort is considered warranted. In previous work, Gwynne et al. demonstrated advances in the representation of evacuee performance and the potential for representing evacuee decision-making. Here, we show that realising this potential is critical to progressing future analysis and, in turn, the field. The paper concludes the following: • Current understanding of evacuee performance suggests a decision-making process often in response to a complex, ambiguous and dynamic environment. This process connects the conditions experienced by an agent and the actions taken. Representing this is important if we are interested in what evacuees do and when they do it. • Agent-based models have the potential to represent evacuees, their decision-making process, their subsequent actions and the resultant interactions between agents and entities in their environment. • Generative Social Science (GSS) employs ABM (agent-based models) to produce subject matter insights using retrodiction and prediction. These approaches will help us enhance our subject matter understanding and the computational tools available to quantify evacuee performance, in turn aiding theoretical and practical efforts. The specific benefits of this approach to our understanding and quantification of evacuee performance are described in this paper, which include the expansion of the explanatory value of the tools available and the refinement of theoretical explanations of evacuee behaviour.
Keywords: egress modeling; evacuee behaviour; decision-making process

Where is OH and does it trace the dark molecular gas (DMG)? - Li, Di; Tang, Ningyu; Nguyen, Hiep; Dawson, J. R.; Heiles, Carl; Xu, Duo; Pan, Zhichen; Goldsmith, Paul F.; Gibson, Steven J.; Murray, Claire E.; Robishaw, Tim; Mcclure-Griffiths, N. M.; et al. (The Astrophysical Journal Supplement Series, 2018)
Hydroxyl (OH) is expected to be abundant in diffuse interstellar molecular gas because it forms along with H2 under similar conditions and forms within a similar extinction range. We have analyzed absorption measurements of OH at 1665 MHz and 1667 MHz toward 44 extragalactic continuum sources, together with the J = 1–0 transitions of 12CO, 13CO, and C18O, and the J = 2–1 transition of 12CO...

Ultra-narrow linewidth quantum dot coherent comb lasers with self-injection feedback locking - Lu, Z. G.; Liu, J. R.; Poole, P. J.; Song, C. Y.; Chang, S. D. (Optics Express, 2018)
We have used an external cavity self-injection feedback locking (SIFL) system to simultaneously reduce the optical linewidth of over 39 individual wavelength channels of an InAs/InP quantum dot (QD) coherent comb laser (CCL). Linewidth reduction from a few MHz to less than 200 kHz is observed. Measured phase noise spectra clearly indicate a significant decrease in phase noise in the frequency range above 2 kHz. The RF beating signal between two adjacent channels also shows a substantial reduction in 3-dB linewidth from 10 kHz to 300 Hz with the SIFL system, and a corresponding drop in baseline level (−27 dB to −50 dB).

Ultra-narrow linewidth quantum dot coherent comb lasers - Lu, Z. G.; Liu, J. R.; Poole, P. J.; Song, C. Y.; Chang, S. D. (Optical Fiber Communication Conference, 2018)
We have developed a secondary-cavity self-injection feedback locking system to simultaneously reduce the linewidths of over 39 filtered individual channels of an InAs/InP quantum-dot coherent comb laser from a few MHz to less than 200 kHz.

Ultrafast X-ray spectroscopy of conical intersections - Neville, Simon P.; Chergui, Majed; Stolow, Albert; Schuurman, Michael S. (Physical Review Letters, 2018)
Ongoing developments in ultrafast x-ray sources offer powerful new means of probing the complex nonadiabatically coupled structural and electronic dynamics of photoexcited molecules. These non-Born-Oppenheimer effects are governed by general electronic degeneracies termed conical intersections, which play a key role, analogous to that of a transition state, in the electronic-nuclear dynamics of excited molecules. Using high-level ab initio quantum dynamics simulations, we studied time-resolved x-ray absorption (TRXAS) and photoelectron spectroscopy (TRXPS) of the prototypical unsaturated organic chromophore, ethylene, following excitation to its S2(ππ∗) state. The TRXAS, in particular, is highly sensitive to all aspects of the ensuing dynamics. These x-ray spectroscopies provide a clear signature of the wave packet dynamics near conical intersections, related to charge localization effects driven by the nuclear dynamics. Given the ubiquity of charge localization in excited state dynamics, we believe that ultrafast x-ray spectroscopies offer a unique and powerful route to the direct observation of dynamics around conical intersections.

UV-initiated Si–S, Si–Se, and Si–Te bond formation on Si(111): coverage, mechanism, and electronics - Hu, Minjia; Hauger, Tate C.; Olsen, Brian C.; Luber, Erik J.; Buriak, Jillian M. (The Journal of Physical Chemistry C, 2018)
Diaryl and dialkyl chalcogenide molecules serve as convenient precursors to silicon–chalcogenide bonds, ≡Si–E–R groups, on silicon surfaces, where E = S, Se, and Te. The 254 nm light, coupled with gentle heating to melt and liquefy the chalcogenide precursors for 15 min, enables formation of the resulting silicon–chalcogenide bonds. R groups analyzed comprise a long alkyl chain, octadecyl, and a phenyl group. Quantification of substitution levels of the silicon-hydride on the starting ≡Si(111)–H surface by an organochalcogen was determined by XPS, using the chalcogenide linker atom as the atomic label, where average substitution levels of ∼15% were found for all ≡Si–E–Ph groups. These measured substitution levels were found to agree with 2-dimensional stochastic simulations assuming kinetically irreversible silicon–chalcogen bond formation. Due to the small bond angle about the chalcogen atom, the phenyl rings in the case of ≡Si–E–Ph effectively block otherwise reactive Si–H bonds, leading to the observed lower substitution levels. The linear aliphatic dialkyl disulfide version, ≡Si–S–n-octadecyl, is less limited by steric blocking of surface Si–H groups as is the case with a phenyl group and has a much higher substitution level of ∼29%. The series, ≡Si–S–Ph, ≡Si–Se–Ph, and ≡Si–Te–Ph, was prepared to determine the effect of chalcogenide substitution on the electronics of the silicon, including surface dipoles and work function. The electronics did not change significantly from the starting ≡Si–H surface, which may be due to the low level of substitution that is believed to be caused by steric blocking by the phenyl groups, as well as the relatively similar electronegativities of these elements relative to silicon.

Tutorial: high harmonics from solids and gases - Corkum, Paul (Conference on Lasers and Electro-Optics, 2018)
Experiments and models show that intense light irradiating transparent solids or gases creates a sequence of harmonics extending to photon energies >1 keV in gases and >H29 in solids. The same process creates attosecond pulses.

Triad3a induces the degradation of early necrosome to limit RipK1-dependent cytokine production and necroptosis - Alturki, Norah A.; Mccomb, Scott; Ariana, Ardeshir; Rijal, Dikchha; Korneluk, Robert G.; Sun, Shao-Cong; Alnemri, Emad; Sad, Subash (Cell Death & Disease, 2018)
Understanding the molecular signaling in programmed cell death is vital to a practical understanding of inflammation and immune cell function. Here we identify a previously unrecognized mechanism that functions to downregulate the necrosome, a central signaling complex involved in inflammation and necroptosis. We show that RipK1 associates with RipK3 in an early necrosome, independent of RipK3 phosphorylation and MLKL-induced necroptotic death. We find that formation of the early necrosome activates K48-ubiquitin-dependent proteasomal degradation of RipK1, Caspase-8, and other necrosomal proteins. Our results reveal that the E3-ubiquitin ligase Triad3a promotes this negative feedback loop independently of typical RipK1 ubiquitin editing enzymes, cIAPs, A20, or CYLD. Finally, we show that Triad3a-dependent necrosomal degradation limits necroptosis and production of inflammatory cytokines. These results reveal a new mechanism of shutting off necrosome signaling and may pave the way to new strategies for therapeutic manipulation of inflammatory responses.

Trees, fungi and bacteria: tripartite metatranscriptomics of a root microbiome responding to soil contamination - Gonzalez, E.; Pitre, F. E.; Pagé, A. P.; Marleau, J.; Guidi Nissim, W.; St-Arnaud, M.; Labrecque, M.; Joly, S.; Yergeau, E.; Brereton, N. J. B. (Microbiome, 2018)
Background: One method for rejuvenating land polluted with anthropogenic contaminants is through phytoremediation, the reclamation of land through the cultivation of specific crops. The capacity for phytoremediation crops, such as Salix spp., to tolerate and even flourish in contaminated soils relies on a highly complex and predominantly cryptic interacting community of microbial life. Methods: Here, Illumina HiSeq 2500 sequencing and de novo transcriptome assembly were used to observe gene expression in washed Salix purpurea cv. ‘Fish Creek’ roots from trees pot grown in petroleum hydrocarbon-contaminated or non-contaminated soil. All 189,849 assembled contigs were annotated without a priori assumption as to sequence origin and differential expression was assessed. Results: The 839 contigs differentially expressed (DE) and annotated from S. purpurea revealed substantial increases in transcripts encoding abiotic stress response equipment, such as glutathione S-transferases, in roots of contaminated trees as well as the hallmarks of fungal interaction, such as SWEET2 (Sugars Will Eventually Be Exported Transporter). A total of 8252 DE transcripts were fungal in origin, with contamination conditions resulting in a community shift from Ascomycota to Basidiomycota genera. In response to contamination, 1745 Basidiomycota transcripts increased in abundance (the majority uniquely expressed in contaminated soil) including major monosaccharide transporter MST1, primary cell wall and lamella CAZy enzymes, and an ectomycorrhiza-upregulated exo-β-1,3-glucanase (GH5). Additionally, 639 DE polycistronic transcripts from an uncharacterised Enterobacteriaceae species were uniformly in higher abundance in contamination conditions and comprised a wide spectrum of genes cryptic under laboratory conditions but considered putatively involved in eukaryotic interaction, biofilm formation and dioxygenase hydrocarbon degradation. Conclusions: Fungal gene expression, representing the majority of contigs assembled, suggests out-competition of white rot Ascomycota genera (dominated by Pyronema), a sometimes ectomycorrhizal (ECM) Ascomycota (Tuber) and ECM Basidiomycota (Hebeloma) by a poorly characterised putative ECM Basidiomycota due to contamination. Root and fungal expression involved transcripts encoding carbohydrate/amino acid (C/N) dialogue whereas bacterial gene expression included the apparatus necessary for biofilm interaction and direct reduction of contamination stress, a potential bacterial currency for a role in tripartite mutualism. Unmistakable within the metatranscriptome is the degree to which the landscape of rhizospheric biology, particularly the important but predominantly uncharacterised fungal genetics, is yet to be discovered.
Keywords: metatranscriptomics; microbiome; Salix; rhizosphere; phytoremediation

Trace metals in soot and PM2.5 from heavy-fuel-oil combustion in a marine engine - Corbin, J. C.; Mensah, A. A.; Pieber, S. M.; Orasche, J.; Michalke, B.; Zanatta, M.; Czech, H.; Massabò, D.; Buatier De Mongeot, F.; Mennucci, C.; El Haddad, I.; Kumar, N. K.; et al. (Environmental Science & Technology, 2018)
Heavy fuel oil (HFO) particulate matter (PM) emitted by marine engines is known to contain toxic heavy metals, including vanadium (V) and nickel (Ni). The toxicity of such metals will depend on the their chemical state, size distribution, and mixing state. Using online soot-particle aerosol mass spectrometry (SP-AMS), we quantified the mass of five metals (V, Ni, Fe, Na, and Ba) in HFO-PM soot particles produced by a marine diesel research engine. The in-soot metal concentrations were compared to in-PM2.5 measurements by inductively coupled plasma-optical emission spectroscopy (ICP-OES). We found that <3% of total PM2.5 metals was associated with soot particles, which may still be sufficient to influence in-cylinder soot burnout rates. Since these metals were most likely present as oxides, whereas studies on lower-temperature boilers report a predominance of sulfates, this result implies that the toxicity of HFO PM depends on its combustion conditions. Finally, we observed a 4-to-25-fold enhancement in the ratio V:Ni in soot particles versus PM2.5, indicating an enrichment of V in soot due to its lower nucleation/condensation temperature. As this enrichment mechanism is not dependent on soot formation, V is expected to be generally enriched within smaller HFO-PM particles from marine engines, enhancing its toxicity.

Revealing the role of poly(vinylidene fluoride) binder in Si/graphite composite anode for Li-ion batteries - Zhao, Xiuyun; Niketic, Svetlana; Yim, Chae-Ho; Zhou, Jigang; Wang, Jian; Abu-Lebdeh, Yaser (ACS Omega, 2018)
The conventional polyvinylidene fluoride (PVDF) binder works well with the graphite anode, but when combined with silicon in composites to increase the energy density of Li-ion batteries, it results in severe capacity fade. Herein, by using scanning electron microscopy and energy-dispersive X-ray spectroscopy analyses, we reveal that this failure stems from the loss of connectivity between the silicon (or its agglomerates), graphite, and PVDF binder because of the mechanical stresses experienced during battery cycling. More importantly, we reveal for the first time that the PVDF binder undergoes chemical decomposition during the cycling of not only the composite but also the Si-only or even graphite-only electrodes despite the excellent battery performance of the latter. Through X-ray photoemission electron microscopy and X-ray photoelectron spectroscopy techniques, LiF was identified as the predominant decomposition product. We show that the distribution of LiF in the electrodes due to the differences in the interactions between PVDF and either Si or graphite could correlate with the performance of the battery. This study shows that the most suitable binder for the composite electrode is a polymer with a good chemical interaction with both graphite and silicon.
Keywords: batteries; carbon-based materials; composites; electron microscopy; fluoropolymers; Nanoparticles; physical and chemical processes; spectra; surface structure

Vapor-phase nanopatterning of aminosilanes with electron beam lithography: understanding and minimizing background functionalization - Fetterly, Christopher R.; Olsen, Brian C.; Luber, Erik J.; Buriak, Jillian M. (Langmuir, 2018)
Electron beam lithography (EBL) is a highly precise, serial method for patterning surfaces. Positive tone EBL resists enable patterned exposure of the underlying surface, which can be subsequently functionalized for the application of interest. In the case of widely used native oxide-capped silicon surfaces, coupling an activated silane with electron beam lithography would enable nanoscale chemical patterning of the exposed regions. Aminoalkoxysilanes are extremely useful due to their reactive amino functionality but have seen little attention for nanopatterning silicon surfaces with an EBL resist due to background contamination. In this work, we investigated three commercial positive tone EBL resists, PMMA (950k and 495k) and ZEP520A (57k), as templates for vapor-phase patterning of two commonly used aminoalkoxysilanes, 3-aminopropyltrimethoxysilane (APTMS) and 3-aminopropyldiisopropylethoxysilane (APDIPES). The PMMA resists were susceptible to significant background reaction within unpatterned areas, a problem that was particularly acute with APTMS. On the other hand, with both APTMS and APDIPES exposure, unpatterned regions of silicon covered by the ZEP520A resist emerged pristine, as shown both with SEM images of the surfaces of the underlying silicon and through the lack of electrostatically driven binding of negatively charged gold nanoparticles. The ZEP520A resist allowed for the highly selective deposition of these alkoxyaminosilanes in the exposed areas, leaving the unpatterned areas clean, a claim also supported by contact angle measurements with four probe liquids and X-ray photoelectron spectroscopy (XPS). We investigated the mechanistic reasons for the stark contrast between the PMMA resists and ZEP520A, and it was found that the efficacy of resist removal appeared to be the critical factor in reducing the background functionalization. Differences in the molecular weight of the PMMA resists and the resulting influence on APTMS diffusion through the resist films are unlikely to have a significant impact. Area-selective nanopatterning of 15 nm gold nanoparticles using the ZEP520A resist was demonstrated, with no observable background conjugation noted in the unexposed areas on the silicon surface by SEM.

Toward a rational photocatalyst design: a new formation strategy of co-catalyst/semiconductor heterostructures via in situ exsolution - Sun, Yi-Fei; Yang, Yan-Ling; Chen, Jian; Li, Meng; Zhang, Ya-Qian; Li, Jian-Hui; Hua, Bin; Luo, Jing-Li (Chemical Communications, 2018)
A new “post-growth” approach to implant metal sulfide nanodots (<5 nm) with high population and uniform dispersion into a semiconductor parent matrix was reported. The encapsulation modality of nanodot co-catalysts grants enhanced visible light absorption and photocatalytic performance, which provides another route for hetero-architecture materials design.

Total synthesis of (6R,10R,13R,14R,16R,17R,19S,20R,21R,24S, 25S,28S,30S,32R,33R,34R,36S,37S,39R)‐azaspiracid‐3 reveals non‐identity with the natural product - Kenton, Nathaniel T.; Adu-Ampratwum, Daniel; Okumu, Antony A.; Zhang, Zhigao; Chen, Yong; Nguyen, Son; Xu, Jianyan; Ding, Yue; Mccarron, Pearse; Kilcoyne, Jane; Rise, Frode; Wilkins, Alistair L.; et al. (Angewandte Chemie International Edition, 2018)
A convergent and stereoselective total synthesis of the previously assigned structure of azaspiracid‐3 has been achieved by a late‐stage Nozaki–Hiyama–Kishi coupling to form the C21−C22 bond with the C20 configuration unambiguously established from l‐(+)‐tartaric acid. Postcoupling steps involved oxidation to an ynone, modified Stryker reduction of the alkyne, global deprotection, and oxidation of the resulting C1 primary alcohol to the carboxylic acid. The synthetic product matched naturally occurring azaspiracid‐3 by mass spectrometry, but differed both chromatographically and spectroscopically.

Thermophysical property measurements of tetrabutylphosphonium acetate (TBPAce) ionic semiclathrate hydrate as thermal energy storage medium for general air conditioning systems - Arai, Yuta; Yamauchi, Yuji; Tokutomi, Hiroki; Endo, Fuyuaki; Hotta, Atsushi; Alavi, Saman; Ohmura, Ryo (International Journal of Refrigeration, 2018)
This paper reports the experimental study on measuring the phase equilibrium temperatures and the dissociation heats of ionic semiclathrate hydrate formed with tetrabutylphosphonium acetate (TBPAce) under atmospheric pressure. The phase equilibrium temperature and the dissociation heat measurements were performed in the range of the mass fraction of TBPAce aqueous solution from 0.10 to 0.42. The highest phase equilibrium temperature was 11.0°C at the mass fraction range from 0.35 to 0.39. The largest dissociation heat of pure TBPAce hydrate was 192.0 kJ kg–1 at the mass fraction 0.36. The obtained results indicate that TBPAce hydrate would be suitable for a new thermal energy storage medium for general air conditioning systems.
Keywords: ionic semiclathrate hydrate; tetrabutylphosphonium acetate (TBPAce); thermal energy storage; air conditioning systems; phase equilibrium temperature; dissociation hea; semi-clathrate hydrate ionique; acétate de tétrabutylphosphonium (TBPAce); stockage d’énergie thermique; systèmes de conditionnement d’air; température d’équilibre de phase; dissociation thermique

Theory of Kerr instability amplification - Nesrallah, M.; Vampa, G.; Bart, G.; Corkum, P. B.; Mcdonald, C. R.; Brabec, T. (Optica, 2018)
Evolution of lasers in Kerr nonlinear materials is inextricably linked with unstable behavior. Current research has investigated the growth of optical Kerr instability out of noise, which results in phenomena such as conical emission and filamentation in bulk materials, and modulation instability in optical fibers. Here, we suggest that seeding Kerr instability in dielectrics can be used for wideband optical amplification ranging from the second harmonic of the pump laser to the mid-infrared. Our theoretical feasibility analysis focuses on the infrared. We find that one- to two-cycle pulse amplification by 3–4 orders of magnitude in the wavelength range of 1–14 μm is feasible with currently available laser sources. Final output energies in the range of a few tens of μJ are achievable corresponding to about 0.25% of the pump energy. Such intense ultrashort mid-infrared radiation sources will substantially impact research in nonlinear spectroscopy, strong-field physics, attosecond science, and ultrafast laser electron accelerators.

Theory of complex fluids in the warm dense matter regime and application to an unusual phase transition in liquid carbon - Dharma-Wardana, M. W. C. (Contributions to Plasma Physics, 2018)
Data from recent laser‐shock experiments or from simulations using density functional theory (DFT), molecular dynamics (MD), path integrals etc. that are available for warm dense carbon are compared with the corresponding results predicted using the neutral pseudo‐atom [NPA] method. The NPA results are in good agreement not only with the 3–12 g/cm3 regimes that have been studied via path‐integral Monte Carlo methods but even at low densities and low temperatures where transient covalent bonding dominates ionic correlations. Thus, the “prepeak” due to the C–C bond at ∼1.4 Å and other features found in the pair distribution function g[r] from DFT + MD simulations at 0.86 eV and 3.7 g/cm3 and other densities etc. are recovered accurately in the NPA + HNC (hypernetted‐chain) calculations. The exploration of regimes not covered by previous studies is presented together with evidence of an unusual phase transition of carbon in the liquid state to a vapour, as seen from the loss of ion–ion correlations. An abrupt decrease in the number of free electrons per ion occurs simultaneously. A metallic liquid with strong ionic correlations arising from transient C–C bonds becomes a metallic vapour. This occurs when carbon at the density of ∼1.0 g/cm3 and mean ionization Z = 4 transits abruptly to a disordered mono‐atomic vapour at 7 eV, with Z ≃ 3. The behaviour of the pressure, compressibility and the electrical conductivity as well as physical quantities available from X‐ray Thomson scattering are presented across the tentatively proposed phase transition.

Theoretical and experimental study of ice accretion due to freezing rain on an inclined cylinder - Szilder, Krzysztof (Cold Regions Science and Technology, 2018)
This paper reports on an investigation of ice formation on a cylinder exposed to freezing rain. Freezing rain icing is characterized by supercooled raindrop impingement, with vertical and horizontal velocity components, water flow over the surface driven by aerodynamic and gravity forces, and freezing or shedding of the surface water. In the first part of the paper, a novel, three-dimensional analytical model of ice growth on a cylinder is derived and the results are discussed. This is followed by a discussion of experimental tests in the NRC Altitude Icing Wind Tunnel. The experiments were constrained to horizontal drop impingement, and we encountered difficulties delivering large drops at low speed to the test section. Hence, the experiments were used primarily to validate the NRC morphogenetic ice accretion model. The morphogenetic model is a discrete element, random walk model that emulates the motion and freezing of individual fluid elements on the accretion surface. After validating the numerical methodology against the wind tunnel experiments, the model was used to simulate ice formation under more realistic and general geometrical configurations and environmental conditions.
Keywords: freezing rain; ice accretion; icing

The stellar populations of two ultra-diffuse galaxies from optical and near-infrared photometry - Pandya, Viraj; Romanowsky, Aaron J.; Laine, Seppo; Brodie, Jean P.; Johnson, Benjamin D.; Glaccum, William; Villaume, Alexa; Cuillandre, Jean-Charles; Gwyn, Stephen; Krick, Jessica; Lasker, Ronald; Martín-Navarro, Ignacio; et al. (The Astrophysical Journal, 2018)
We present observational constraints on the stellar populations of two ultra-diffuse galaxies (UDGs) using optical through near-infrared (NIR) spectral energy distribution (SED) fitting. Our analysis is enabled by new Spitzer-IRAC 3.6 and 4.5 μm imaging, archival optical imaging, and the prospector fully Bayesian SED fitting framework. Our sample contains one field UDG (DGSAT I), one Virgo cluster UDG (VCC 1287), and one Virgo cluster dwarf elliptical for comparison (VCC 1122). We find that the optical–NIR colors of the three galaxies are significantly different from each other...
Keywords: galaxies: clusters: general; galaxies: dwarf; galaxies: evolution; galaxies: formation; galaxies: photometry; galaxies: stellar content

The role of amine ligands in governing film morphology and electrical properties of copper films derived from copper formate-based molecular inks - Paquet, Chantal; Lacelle, Thomas; Liu, Xiangyang; Deore, Bhavana; Kell, Arnold J.; Lafrenière, Sylvie; Malenfant, Patrick R. L. (Nanoscale, 2018)
Copper formate complexes with various primary amines, secondary amines and pyridines were prepared, and their decomposition into conductive films was characterized. A comparison of the various complexes reveals that the temperature of thermolysis depends on the number of hydrogen bonds that can be formed between the amine and formate ligands. The particle size resulting from sintering of the copper complexes is shown to depend on the fraction of amine ligand released during the thermolysis reaction. The particle size in turn is shown to govern the electrical properties of the copper films. Correlations between the properties of the amines, such as boiling point and coordination strength, with the morphology and electrical performance of the copper films were established and provide a basis for the molecular design of copper formate molecular inks.

The next generation Virgo Cluster survey (NGVS). XXXII. A search for globular cluster substructures in the Virgo Galaxy Cluster core - Powalka, Mathieu; Puzia, Thomas H.; Lançon, Ariane; Longobardi, Alessia; Peng, Eric W.; Duc, Pierre-Alain; Alamo-Martínez, Karla; Blakeslee, John P.; Côté, Patrick; Cuillandre, Jean-Charles; Durrell, Patrick; Eigenthaler, Paul; et al. (The Astrophysical Journal, 2018)
Substructure in globular cluster (GC) populations around large galaxies is expected in galaxy formation scenarios that involve accretion or merger events, and it has been searched for using direct associations between GCs and structure in the diffuse galaxy light, or with GC kinematics. Here, we present a search for candidate substructures in the GC population around the Virgo cD galaxy M87 through the analysis of the spatial distribution of the GC colors. The study is based on a sample of ~1800 bright GCs with high-quality u, g, r, i, z, K s photometry, selected to ensure a low contamination by foreground stars or background galaxies. The spectral energy distributions of the GCs are associated with formal estimates of age and metallicity, which are representative of its position in a 4D color space relative to standard single stellar population models. Dividing the sample into broad bins based on the relative formal ages, we observe inhomogeneities that reveal signatures of GC substructures. The most significant of these is a spatial overdensity of GCs with relatively young age labels, of diameter ~0fdg1 (~30 kpc), located to the south of M87. The significance of this detection is larger than about 5σ after accounting for estimates of random and systematic errors. Surprisingly, no large Virgo galaxy is present in this area that could potentially host these GCs. But candidate substructures in the M87 halo with equally elusive hosts have been described based on kinematic studies in the past. The number of GC spectra available around M87 is currently insufficient to clarify the nature of the new candidate substructure.

The next generation Virgo Cluster survey (NGVS). XVIII. Measurement and calibration of surface brightness fluctuation distances for bright galaxies in Virgo (and beyond) - Cantiello, Michele; Blakeslee, John P.; Ferrarese, Laura; Côté, Patrick; Roediger, Joel C.; Raimondo, Gabriella; Peng, Eric W.; Gwyn, Stephen; Durrell, Patrick R.; Cuillandre, Jean-Charles (The Astrophysical Journal, 2018)
We describe a program to measure surface brightness fluctuation (SBF) distances to galaxies observed in the Next Generation Virgo Cluster Survey (NGVS), a photometric imaging survey covering 104 deg2 of the Virgo cluster in the u*, g, i, and z bandpasses with the Canada–France–Hawaii Telescope. We describe the selection of the sample galaxies, the procedures for measuring the apparent i-band SBF magnitude m-i, and the calibration of the absolute Mibar as a function of observed stellar population properties. The multiband NGVS data set provides multiple options for calibrating the SBF distances, and we explore various calibrations involving individual color indices as well as combinations of two different colors. Within the color range of the present sample, the two-color calibrations do not significantly improve the scatter with respect to wide-baseline, single-color calibrations involving u*. We adopt the (u*-z) calibration as a reference for the present galaxy sample, with an observed scatter of 0.11 mag. For a few cases that lack good u* photometry, we use an alternative relation based on a combination of (g-i) and (g-z) colors, with only a slightly larger observed scatter of 0.12 mag. The agreement of our measurements with the best existing distance estimates provides confidence that our measurements are accurate. We present a preliminary catalog of distances for 89 galaxies brighter than B T ≈ 13.0 mag within the survey footprint, including members of the background M and W Clouds at roughly twice the distance of the main body of the Virgo cluster. The extension of the present work to fainter and bluer galaxies is in progress.

The molecular attoclock: sub-cycle control of electronic dynamics during H2 double ionization - Hanus, Vaclav; Kangaparambil, Sarayoo; Larimian, Seyedreza; Xie, Xinhua; Schoffler, Markus; Staudte, André; Paulus, Gerhard; Baltuska, Andrius; Kitzler, Markus (High-Brightness Sources and Light-driven Interactions, 2018)
We introduce and employ the molecular attoclock method. This allows us to simultaneously trace the nuclear and electron dynamics during H2 fragmentation, and to CEP-control the two-electron emission dynamics on sub-cycle time scales.

The He2-OCS complex: comparison between theory and experiment - Norooz Oliaee, J.; Moazzen-Ahmadi, N.; Mckellar, A. R. W.; Wang, Xiao-Gang; Carrington, Tucker (Chemical Physics Letters, 2018)
OCS is an ideal probe for quantum solvation effects in cold helium clusters. He2-OCS is the “second step” in going from a single OCS molecule to a large doped superfluid helium cluster. Here assignment of the spectrum of He2-OCS is significantly extended to higher values of J, K, and vt (the low frequency torsional vibration). The observation of a new infrared band, OCS ν1 + ν3, taken together with the known ν1 band, enables assignments to be verified by comparing ground state combination differences. Relatively straightforward scaling of previously calculated theoretical energy levels gives a remarkably good fit to experiment.

The GALEX Ultraviolet Virgo Cluster survey (GUViCS). VII. Brightest cluster galaxy UV upturn and the FUV-NUV color up to redshift 0.35 - Boissier, S.; Cucciati, O.; Boselli, A.; Mei, S.; Ferrarese, L. (Astronomy & Astrophysics, 2018)
Context. At low redshift, early-type galaxies often exhibit a rising flux with decreasing wavelength in the 1000–2500 Å range, called “UV upturn”. The origin of this phenomenon is debated, and its evolution with redshift is poorly constrained. The observed GALEX FUV-NUV color can be used to probe the UV upturn approximately to redshift 0.5. Aim. We provide constraints on the existence of the UV upturn up to redshift ~0.4 in the brightest cluster galaxies (BCG) located behind the Virgo cluster, using data from the GUViCS survey. Methods. We estimate the GALEX far-UV (FUV) and near-UV (NUV) observed magnitudes for BCGs from the maxBCG catalog in the GUViCS fields. We increase the number of nonlocal galaxies identified as BCGs with GALEX photometry from a few tens of galaxies to 166 (64 when restricting this sample to relatively small error bars). We also estimate a central color within a 20 arcsec aperture. By using the r-band luminosity from the maxBCG catalog, we can separate blue FUV-NUV due to recent star formation and candidate upturn cases. We use Lick indices to verify their similarity to redshift 0 upturn cases. Results. We clearly detect a population of blue FUV-NUV BCGs in the redshift range 0.10–0.35, vastly improving the existing constraints at these epochs by increasing the number of galaxies studied, and by exploring a redshift range with no previous data (beyond 0.2), spanning one more Gyr in the past. These galaxies bring new constraints that can help distinguish between assumptions concerning the stellar populations causing the UV upturn phenomenon. The existence of a large number of UV upturns around redshift 0.25 favors the existence of a binary channel among the sources proposed in the literature.
Keywords: ultraviolet: galaxies; galaxies: ellipticals and lenticulars, cD; galaxies: stellar content

The envelope kinematics and a possible disk around the class 0 protostar within BHR7 - Tobin, John J.; Bos, Steven P.; Dunham, Michael M.; Bourke, Tyler L.; Van Der Marel, Nienke (The Astrophysical Journal, 2018)
We present a characterization of the protostar embedded within the BHR7 dark cloud, based on both photometric measurements from the near-infrared to millimeter and interferometric continuum and molecular line observations at millimeter wavelengths. We find that this protostar is a Class 0 system, the youngest class of protostars, measuring its bolometric temperature to be 50.5 K, with a bolometric luminosity of 9.3 L ☉. The near-infrared and Spitzer imaging show a prominent dark lane from dust extinction separating clear bipolar outflow cavities. Observations of 13CO ($J=2→ 1$), C18O ($J=2→ 1$), and other molecular lines with the Submillimeter Array (SMA) exhibit a clear rotation signature on scales <1300 au. The rotation can be traced to an inner radius of ~170 au and the rotation curve is consistent with an R −1 profile, implying that angular momentum is being conserved. Observations of the 1.3 mm dust continuum with the SMA reveal a resolved continuum source, extended in the direction of the dark lane, orthogonal to the outflow. The deconvolved size of the continuum indicates a radius of ~100 au for the continuum source at the assumed distance of 400 pc. The visibility amplitude profile of the continuum emission cannot be reproduced by an envelope alone and needs a compact component. Thus, we posit that the resolved continuum source could be tracing a Keplerian disk in this very young system. If we assume that the continuum radius traces a Keplerian disk (R ~ 120 au) the observed rotation profile is consistent with a protostar mass of 1.0 M ☉.
Keywords: ISM: individual objects (BHR7); ISM: jets and outflows; ISM: molecules; stars: formation; stars: protostars

The effects of substitute multisensory feedback on task performance and the sense of presence in a virtual reality environment - Cooper, Natalia; Milella, Ferdinando; Pinto, Carlo; Cant, Iain; White, Mark; Meyer, Georg; Proulx, Michael J. (PLOS ONE, 2018)
Objective and subjective measures of performance in virtual reality environments increase as more sensory cues are delivered and as simulation fidelity increases. Some cues (colour or sound) are easier to present than others (object weight, vestibular cues) so that substitute cues can be used to enhance informational content in a simulation at the expense of simulation fidelity. This study evaluates how substituting cues in one modality by alternative cues in another modality affects subjective and objective performance measures in a highly immersive virtual reality environment. Participants performed a wheel change in a virtual reality (VR) environment. Auditory, haptic and visual cues, signalling critical events in the simulation, were manipulated in a factorial design. Subjective ratings were recorded via questionnaires. The time taken to complete the task was used as an objective performance measure. The results show that participants performed best and felt an increased sense of immersion and involvement, collectively referred to as ‘presence’, when substitute multimodal sensory feedback was provided. Significant main effects of audio and tactile cues on task performance and on participants' subjective ratings were found. A significant negative relationship was found between the objective (overall completion times) and subjective (ratings of presence) performance measures. We conclude that increasing informational content, even if it disrupts fidelity, enhances performance and user’s overall experience. On this basis we advocate the use of substitute cues in VR environments as an efficient method to enhance performance and user experience.

The benefit of kitchen exhaust fan use after cooking: an experimental assessment - Dobbin, Nina A.; Sun, Liu; Wallace, Lance; Kulka, Ryan; You, Hongyu; Shin, Tim; Aubin, Daniel; St-Jean, Melissa; Singer, Brett C. (Building and Environment, 2018)
Cooking is one of the main sources of indoor air pollutants, and may even exceed the contribution from outdoor sources. This pilot study examines the use of different flow-rate fans during cooking and tests whether continuing to run the fan after cooking significantly improves pollutant removal rates and integrated exposures. Tests were carried out in the Canadian Centre for Housing Technology's twin research houses, in Ottawa, Ontario. We completed the same cooking protocol 60 times on a gas stove, testing 6 different flow rates on three different over-the-range exhaust fans, while continuously measuring UFP, PM2.5, NO2, and NO. The fan was operated during cooking for all tests and then either turned off or left on after cooking for the duration of the three hour test. We estimated decay rates, source emission rates, and integrated exposures to measured pollutants following the cooking test. The results showed that while leaving the fan on after cooking generally increased decay rates, it had a relatively small effect on integrated exposures compared to the effects of fan flow rate and the specific fan used during cooking. For PM2.5, the effect of running an exhaust fan for 15 min after cooking was similar in magnitude to the impact of a 100 cfm increase in the flow rate used while cooking: both were associated with a decrease in 15-min integrated exposure of roughly 3  μg m−3. This suggests that one can partially compensate for a low flow rate exhaust fan by continuing to run the fan after cooking.
Keywords: indoor air quality; cooking; fine particulate matter (PM2.5); ultrafine particles (UFP); nitric oxide; gas stove

Introduction to average Hamiltonian theroy. I. Basics - Brinkmann, Andreas (Concepts in Magnetic Resonance Part A, 2018)
Understanding the dynamics of electron or nuclear spins during a magnetic resonance experiment requires to solve the Schrödinger equation for the spin system considering all contributions to the Hamiltonian from interactions of the spins with each other and their surroundings. In general, this is a difficult task as these interaction terms can be both time-dependent and might not commute with each other. A powerful tool to analytically approximate the time evolution is average Hamiltonian theory, in which a time-​independent effective Hamiltonian is taking the place of the time-dependent Hamiltonian. The effective Hamiltonian is subjected to the Magnus expansion, allowing to calculate the effective Hamiltonian to a certain order. The goal of this paper is to introduce average Hamiltonian theory in a rigorous but educational manner. The application to two composite pulses in NMR spectroscopy is used to demonstrate important aspects of average Hamiltonian theory.
Keywords: NMR; average Hamiltonian theory; effective Hamiltonian; average Hamiltonian; Magnus expansion; composite pulse

Harmonie mitigation of an improved high voltage current source for on-site system calibration of high voltage transformer loss - Said, Amr; So, Eddy; Angelo, Dave (2018 Conference on Precision Electromagnetic Measurements (CPEM 2018), 2018)
This paper proposes an open-loop technique that mitigate the harmonic distortion in high load currents for on site system calibrations of high voltage transformer loss measurement systems. The harmonic distortion induced by the current transconductance amplifier and current injector poses high burden on the feedback current correction loop and thus may compromise the measurement accuracy. Accordingly, a harmonic mitigation technique is introduced through online system identification and open-loop anti-harmonic injection. This methodology significantly reduces the THD in the load current from 0.3% to less than 0.022%.
Keywords: harmonic mitigation; load loss standard; open-loop control

High voltage CT ratio errors dependency on voltage and power factor of the metered load - So, Eddy; Roman, Zoltan (CPEM 2018, 2018)
This paper describes the results of performance cvaluation of ratio errors of a high voltage current transformer (CT) and a high voltage combined current and voltage transformer (CT/VT) with the aim of discovering the behavior of the CT ratio errors at different operating high voltages, different power factor loads on the transmission line in which the CT (or CT part of the CT/VT) was connected and the effects of the VT burden (in case of the CT/VT).
Keywords: current transformer; load; ratio errors; voltage

A high precision multi-ratio three-stage current transformer (CT) for loss measurements of extra high voltage (EHV) three-phase shunt reactors with test voltages up to 1050 kV - So, Eddy So; Verhoeven, Rob; Simmons, Bart; Parks, Harold; Angelo, Dave (CPEM 2018, 2018)
An overvicw of the development and performance of special high prccision multi-ratio three-stage CT and its application for loss measurement of EHV thrcc-phase shunt rcactors with test voltages up to 1050 kV at Royal SMIT Transformcrs arc prcsented and discuss. lt features current ratios of SOOA/I A, 400A/ 1A, 300A/1A, 200A/ IA, and lOOA/lA with ratio crrors of lcss than Sxl0-6 in both magnitude and phase with burdens up to 1.0 Q and at power frcqucncies of 50 Hz - 60 Hz.
Keywords: Extra High Voltage (EHV); multi-ratio; multistage; precision measurements; ratio errors; shunt reactor; three-stage; uncertainty

Re-evaluation of the gravity transfer component of the NRC Kibble balance - Wood, B. M.; Liard, J. O.; Sanchez, C. A. (CPEM 2018, 2018)
We describe a project to re-eval uate the transfer of the absolute determination of the local acceleration due to gravity from a nearby site, to the center of mass of the test mass in the NRC Kibble Ba lance. This re-evaluation includes the Characterization of the sensitivity of a relative gravity meter to the fringing magnetic flux density, as well as the attenuation provided by a simple magnetic shield.
Keywords: gravity measurement; magnetic field; revised SI; watt balance; Planck constant; SI units

Reassessment of the uncertainties of the NRC cryogenic current comparator and quantum hall resistance standard - Sanchez, C. (CPEM 2018, 2018)
This paper describes the main sources of error in the NRC Cryogenic Current Comparator (CCC) and Quantum Hall Resistance Standard (QHR) systems and reports their estimated uncertainty. The CCC type B uncertainty is evaluated to be about 0.26 parts in 109 with the largest contribution being the effect of a noise-induced offset in the Superconducting Quantum Interference Device (SQUID). The uncertainty of the QHR system is estimated at 0.28, with comparable contribution from leakage resistances between the leads and finite dissipation on the QHR sample.
Keywords: cryogenic current comparator; quantum hall resistance; resistance bridge; SQUIDs

The JILA (Parks-Falier) 2010 determination of the Newtonian constant - Falle, J. E.; Parkst, H. V. (CPEM 2018, 2018)
We present here an update of the JILA (Parks Faller) 2010 determination of the Newtonian Constant of gravitation (big G). Due to an A bbe error that was unaccounted for in the initial analysis, we adjust our value of the gravitational constant G from (6.672 34 ± 0.000 14) x 10-11 m3 kg-1 s-2 to (6.672 96 ± 0.000 22) x 10-11 m3 kg-1 s-2. We discuss the source of the error and how it can be avoided in future iterations of this experiment.
Keywords: fundamental constants; measurement techniques; measurement uncertainty; Newtonian gravitational constant; precision measurement

Calibration of electricity meters with digital input - Djokic, Branislav; Parks, Harold (CPEM 2018, 2018)
Ovcr the last dccades, prolifcration of harmon ie producin g loads in the electric power system is noticeable, duc to, in large part , increase of use of many power electronics devices. This tren d contin ues as the role of power electronics in Smart Grid developments is very important. The Smart Grid is also characterized by an ever incrcasing use of intelligent elcctron ic dcviccs (lEDs) for monitoring, control, protection and mctcrin g in digital su bstations. The IEDs, non-convcntiona l instrument transformcrs (NCITs) with digital output, and merging un its (M Us), opcrate with power system voltage and currcnt sa mplcd values (SVs) conforming to IEC 61850-9-2 format. The SVs a rc also used for revenue mctering by non-convcnti onal cncrgy mcters with digital inputs. The paper {discusses 1 invcstigatcs} the performance of c11crgy meters with digital inputs u11der 11011- sinusoidal waveform conditions.
Keywords: digital substation; digital energy meter; digital power source; merging unit; non-conventional instrument transformer; harmonics; calibration; precision measurements

A synchronized current-comparator-based power bridge for calibrating analog merging units - Djokic, Branislav; Parks, Harold (CPEM 2018, 2018)
A synchronized current-comparator-based power bridge for calibrating analog merging units at power frequencies of 60 Hz and 50 Hz is described. Analog merging units take analog signals from instrument transformers, convert them into digital form, pack the sampled values into Ethernet frames conforming to the IEC 61850-9-2 LE specification and stream the frames to other equipment in a digital substation for further processing. Since the sampled values are used for protection and metering, the merging units need to be calibrated. The expanded uncertainties (k=2) of the described calibration system are estimated to be better than 30 11A/A for magnitude and 60 µrad for phase.
Keywords: instrument transformers; merging unit; calibration; power bridge; current comparator; measurement uncertainty

Calibration of AC shunts at frequencies up to 10 kHz using digital sampling - Djokic, Bran Islav; Parks, Harold (CPEM 2018, 2018)
This paper describes a calibration system for AC shunts using digital sampling. It provides bot h ratio errors and phase displacements of a shunt under test with respect to a reference shunt. ln its basic configuration, the calibration system operates at currents of up to 10 A and frequencies of up to IO kHz. The expanded uncertainties (k = 2) of the described calibration system arc estimated to be better than 30 µA/A for magnitude and 30 µrad for phrase at 10 kHz, and lower than these at lower frequencies.
Keywords: AC shunt; current measurement; measurement standards; calibration; measurement uncertainty; current comparator; calculable resistor

Software to determine sphere center from terrestrial laser scanner data per ASTM Standard E3125-17 - Rachakonda, Prem; Muralikrishnan, Bala; Cournoyer, Luc; Sawyer, Daniel (Journal of Research of the National Institute of Standards and Technology, 2018)
Terrestrial laser scanners (TLSs) are instruments that can measure 3D coordinates of objects at high speed using a laser, resulting in high density 3D point cloud data. The Dimensional Metrology Group (DMG) at NIST performed research to support the development of documentary standards within ASTM E57 committee on 3D imaging systems. This led to the publication of the ASTM E3125-2017 standard on point-to-point distance performance evaluation of 3D imaging systems such as TLSs. To ensure that the data from different TLS systems are processed identically, the ASTM E3125- 2017 mandates the use of a common algorithm to determine the center of a sphere from point cloud data. This paper describes this algorithm and software code is provided as a download.
Keywords: 3D point cloud; sphere fitting; terrestrial laser scanner data

Concept to commercialization of an artifact for evaluating three-dimensional imaging systems per ASTM E3125-17 - Muralikrishnan, Bala; Rachakonda, Prem; Lee, Vincent; Shilling, Meghan; Sawyer, Daniel; Cheok, Geraldine; Cournoyer, Luc; Gleason, Joe (Journal of Research of the National Institute of Standards and Technology, 2018)
• The relative-ra nge en-or test is one of several tests described in the ASTM E3 l 25-2017 standard for perfonnance evaluation of sphe1ical coordinate 3D imaging systems such as ten-estrial laser scanners (TLS). • Using a simple planar/plate target requires careful alignment of the targe!at each position of the relative-range en-or test which is labor intensive and time consuming. • We have designed a new artifact, called the plate-sphere target, that allows the realization of the relative-range error tests quickly and efficiently without the need for aligrunent at each position of the test. This new a1tifact significantly reduces the time required to pe1fonn the test, from a malter of hours to less than 30 minutes, thus saving users and manufacturers of TLSs considerable time and money. • The plate-sphere target was conceived at the National lnstitute of Standards and Technology (NIST), improved based on feedback from collaborators at the Nat ional Research Council (NRC) of Canada and TLS manufacturers, and commercialized by Bal-tee lnc.
Keywords: ASTM E3125-l7; laser scanner; plate-sphere aitifact; relative-range e1rnr test

Hybrid weld-bond joining technology of light metal alloys - Noormohammed, Saleema; Nadeau, François; Menini, Richard (The Adhesion Society, 2018)
The biggest challenge faced by transportation industries in structural assembly is the joints’ integrity upon exposure to environmental conditions while maintaining excellent mechanical properties. Combination of mechanical and adhesive joining can provide high joint strengths, increased energy absorption and high fatigue lives. A weld-thru method has been previously employed where the parts to be assembled are friction stir welded (FSW) in the presence of a structural adhesive/sealant between the parts. However, this technology suffers adhesive damage due to weld-induced heat generated locally affecting the joints’ durability and mechanical properties. Also, most adhesive/sealants have Tg below the temperature attained during welding (450 to 500 oC), unable to withstand the weld-induced heat. In this paper, an inverse technology, called flow-in or weld-bond was used to bond Al-Al and Al-steel using a low viscosity epoxy adhesive in combination with FSW and arc welding processes. In this method, the welding step in overlap mode is performed first. The adhesive is applied later through the welded gap via capillary forces. Since welding and adhesive application are independently performed, the adhesive safely fills the gap while maintaining the joints’ integrity. The performance of the weld-bonded joints of pretreated Al and steel alloys as-assembled and after various environmental degradation (international standards) including combinations of heat, humidity, sub-zero temperatures, salt-spray and UV exposure, has been evaluated. The results show tremendous increase (1.7 times) in joint strengths on weld-bonded specimens in comparison to the weld-alone and adhesive-alone specimens with no change even after degradation. A simple surface treatment prior to adhesive application is found to help the joints sustain the salt-spray conditions. The fatigue life of the weld-bonded joints is found to be higher than those prepared using individual techniques.

On-sun testing of a 100-shingled-cell dense receiver array at ∼50 W/cm2 using overlapped single-axis foci - Norman, Richard; Bouzazi, Boussairi; Leveille, Etienne; Siskavich, Brad; Dufault, Jean-Francois; Arenas, Osvaldo; Ares, Richard; Aimez, Vincent; Frechette, Luc G. (14th International Conference on Concentrator Photovoltaic Systems (CPV-14), 2018)
Dish CPV can achieve high concentration at low cost by overlapping the foci of single-axis mirrors into an oblong compound focus, which secondary optics can convert to a rectangular focus with even intensity on its major axis. The resulting focus is suitable for a dense receiver array with rows of cells-in-parallel on the minor axis with the rows themselves in series along the major axis. A dense receiver array was previously proposed in which multiple receiver segments are covered with rows of CPV cells that are shingled to minimize gaps in the photoreceptive surface. Segments are built on thermal-expansion-matched micro-channel cold plates for up to 1000× concentration. Segments share a coolant manifold and a steel housing with cooled secondary mirrors, so a receiver with hundreds of cells can be handled in-field as a unit. The first receiver segments have been built, populated with cells and flash-tested, and the first segment has been installed in a receiver and tested on sun at up to 50 W/cm2 at the focus of a multiple-single-axis-mirror dish.

In silico modelling and of monoclonal antibody fed-batch production in CHO cell - Cuperlovic-Culf, Miroslava (Current Metabolomics, 2018)
Background: Chinese hamster ovary (CHO) cells are highly important host cells in recombinant DNA technology. The rapid ability to conduct experiments in silico, using mathematical models of growing CHO cells, has helped advance the optimization of bioreactor conditions towards higher viable cell concentrations and mAb production. Several kinetic and system level models have been proposed for CHO cells. Results: In this work we have provided a new kinetic model of CHO cell metabolism and have shown its application for the simulation of novel high-throughput metabolomics data for fed-batch production in bioreactors with CHO cells grown using two feeding strategies. RNASeq data from CHO cells was used to guide selection of major metabolic pathways that were included in the kinetic model. The kinetic model includes 37 completely described reactions processing 45 species (metabolites). This model is based on previously published kinetic characteristics for this system and was evaluated against metabolomics data for CHO cells grown under two different feeding regimes. Conclusions: This work provides kinetic model for energy metabolism of CHO cells. Application of the model offers insights into possible causes of different performance of two feeding strategies, thus suggesting possible problems and future optimization routes.
Keywords: metabolomics; metabolic modelling; kinetic modelling; CHO; bioreactor; mAb productio

Silicon and germanium suspended waveguides for the mid-infrared - Osman, A.; Soler-Penades, J.; Sanchez-Postigo, A.; Wu, Y.; Qu, Z.; Wanguemert-Perez, J. G.; Ortega-Monux, A.; Halir, R.; Cheben, P.; Molina-Fernandez, I.; Nedeljkovic, M.; Mashanovich, G. Z. (2018 IEEE Photonics Society Summer Topical Meeting Series (SUM), 2018)
Both silicon and germanium are very interesting materials for mid-infrared applications, particularly sensing, due to their low material losses at long wavelengths. Silicon is low loss up to 8 μm, and germanium up to 15 μm. To fully exploit these long wavelength transmission ranges of Si and Ge, and to build Si and Ge long wavelength photonic circuits, cladding materials need to have the same or larger transmission wavelength ranges than Si or Ge. One solution is to remove a lossy substrate and create Si and Ge suspended structures with air cladding. In the case of SOI, buried oxide can be removed by HF, and for the Ge-on-Si platform, Si substrate can be removed by TMAH. In this paper we report on the fabrication and characterization of suspended Ge waveguides at a wavelength of 3.8 μm, and on Si waveguides operating at a wavelength of 7.7 μm, both of which are the longest reported wavelengths for the two platforms

Hole free phase plate tomography for materials sciences samples - Hayashida, Misa; Cui, Kai; Najarian, Amin Morteza; Mccreery, Richard; Jehanathan, Neerushana; Pawlowicz, Chris; Motoki, Sohei; Kawasaki, Masahiro; Konyuba, Yuji; Malac, Marek (Micron, 2018)
We report, for the first time, the three dimensional reconstruction (3D) of a transistor from a microprocessor chip and roughness of molecular electronic junction obtained by electron tomography with Hole Free Phase Plate (HFPP) imaging. The HFPP appears to enhance contrast between inorganic materials and also increase the visibility of interfaces between different materials. We demonstrate that the degree of enhancement varies depending on material and thickness of the samples using experimental and simulation data.
Keywords: Hole Free Phase Plate (HFPP); electron tomography; transistor Imaging; molecular electronic junction; interface roughness; Transmission electron microscope (TEM)

Carrageenans: new tools for new applications - Genicot, Sabine; Préchoux, Aurélie; Correc, Gaëlle; Kervarec, Nelly; Simon, Gaëlle; Craigie, James S. (Blue Biotechnology, 2018)
Carrageenan is the generic name given to a family of sulfated polysaccharides extracted from some red seaweeds (Rhodophyta). They are made of repeating d‐galactose units linked alternately via α‐1, 3 and β‐1, 4 linkages. Units can have various sulfation patterns and often the α‐d‐galactose moiety is replaced by a 3,6‐anhydro‐α‐d‐galactose moiety. Carrageenans have long been used in the food industry (E407), in drug formulations, and in cosmetic products for their texturizing and gelling properties. Novel applications of carrageenans are moving toward the use of designed poly‐ and oligosaccharides that have specific functionality. In this respect, the use of specific carrageenan‐modifying enzymes is essential. There are two distinctive sets of enzymes: those that desulfate (sulfatases and sulfurylases) and the carrageenan hydrolases, also called carrageenases. These enzymes are used to produce specific oligosaccharides that are gaining in importance as they display biological activities in human health and plant growth and protection. The sulfurylases and sulfatases are able to specifically biochemically convert carrageenans into another carrageenan form. In this chapter, we review all the enzymes that are now available to bioconvert carrageenans, and we also present some of their possible uses. Perspectives of blue technology rely on potent analytical methods for in‐depth studies on the enzymatic modifications. Thus, the three main spectroscopic methods (infrared, nuclear magnetic resonance, and mass spectrometry) used for this purpose are presented.

Modelling dissolved oxygen content in water for ultrasound power measurements - Wu, Lixue (Proceedings of the 25th International Congress on Sound and Vibration, 2018)

Experimental and analytical characterization of alternative aviation fuel sprays under realistic operating conditions - Corber, Andrew; Rizk, Nader; Chishty, Wajid Ali (ASME Turbo Expo 2018: Turbomachinery Technical Conference and Exposition. Volume 4A: Combustion, Fuels, and Emissions, 2018)
The National Jet Fuel Combustion Program (NJFCP) is an initiative, currently being led by the Office of Environment & Energy at the FAA, to streamline the ASTM jet fuels certification process for alternative aviation fuels. In order to accomplish this objective, the program has identified specific applied research tasks in several areas. The National Research Council of Canada (NRC) is contributing to the NJFCP in the areas of sprays and atomization and high altitude engine performance. This paper describes work pertaining to atomization tests using a reference injection system. The work involves characterization of the injection nozzle, comparison of sprays and atomization quality of various conventional and alternative fuels, as well as use of the experimental data to validate spray correlations. The paper also briefly explores the application viability of a new spray diagnostic system that has potential to reduce test time in characterizing sprays. Measurements were made from ambient up to 10 bar pressures in NRC’s High Pressure Spray Facility using optical diagnostics including laser diffraction, phase Doppler anemometry (PDA), LIF/Mie Imaging and laser sheet imaging to assess differences in the atomization characteristics of the test fuels. A total of nine test fluids including six NJFCP fuels and three calibration fluids were used. The experimental data was then used to validate semi-empirical models, developed through years of experience by engine OEMs and modified under NJFCP, for predicting droplet size and distribution. The work offers effective tools for developing advanced fuel injectors, and generating data that can be used to significantly enhance multi-dimensional combustor simulation capabilities.
Keywords: fuels; sprays; aviation

Subwavelength integrated photonics - Cheben, Pavel; Halir, Robert; Schmid, Jens H.; Atwater, Harry A.; Smith, David R. (Nature, 2018)
In the late nineteenth century, Heinrich Hertz demonstrated that the electromagnetic properties of materials are intimately related to their structure at the subwavelength scale by using wire grids with centimetre spacing to manipulate metre-long radio waves. More recently, the availability of nanometre-scale fabrication techniques has inspired scientists to investigate subwavelength-structured metamaterials with engineered optical properties at much shorter wavelengths, in the infrared and visible regions of the spectrum. Here we review how optical metamaterials are expected to enhance the performance of the next generation of integrated photonic devices, and explore some of the challenges encountered in the transition from concept demonstration to viable technology.

Analysis of the uptake, metabolism, and behavioral effects of cannabinoids on zebrafish larvae - Achenbach, John C.; Hill, Jessica; Hui, Joseph P. M.; Morash, Michael G.; Berrue, Fabrice; Ellis, Lee D. (Zebrafish, 2018)
The Cannabis sativa plant contains numerous phytocannabinoids and terpenes with known or potential biological activity. For decades, plant breeders have been breeding the Cannabis plant to control for a desired ratio of the major cannabinoids. A high-throughput in vivo model to understand the relationship between the chemical composition of different strains and their therapeutic potential then becomes of value. Measuring changes in the behavioral patterns of zebrafish larvae is an established model with which to test the biological activity of neuroactive compounds. However, there is currently little information regarding the uptake kinetics and metabolism of compounds by larvae. In this study, we chose to compare the uptake kinetics and metabolism of Δ⁹-tetrahydrocannabinol (THC) and cannabidiol (CBD) alone or in combination with their effects on larval behavior. We have shown that both compounds have distinct behavioral patterns and concentration response profiles. Additionally, the uptake kinetics observed for each compound appears to correlate with the change in behavior observed in the behavioral assays. When combinations of THC and CBD were tested there were shifts in both the behavioral activity and the uptake kinetics of each compound compared with when they were tested alone. Finally, the THC/CBD-derived metabolites detected in the larvae are similar to those found in mammalian systems. This study thus provides a model for further testing of additional cannabinoids and potentially plant extracts.
Keywords: zebrafish; cannabinoid; metabolism; behavior; behaviour; THC; CBD

Profiling of the transcriptomic responses of Clonostachys rosea upon treatment with Fusarium graminearum secretome - Demissie, Zerihun A.; Foote, Simon J.; Tan, Yifang; Loewen, Michele C. (Frontiers in Microbiology, 2018)
Clonostachys rosea strain ACM941 is a fungal bio-control agent patented against the causative agent of Fusarium Head Blight, Fusarium graminearum. Although the molecular details remain enigmatic, previous studies have suggested that C. rosea may secrete F. graminearum growth inhibitors. Further toward this, experiments described herein show that induction of C. rosea cultures by the addition of an aliquot of F. graminearum(Fg)-spent media (including macroconidia), yield C. rosea (Cr)-spent media that elicited higher anti-F. graminearum activity than either control or deoxynivalenol (DON)-induced Cr-spent media. To gain additional insight into the genetic and metabolic factors modulating this interaction, transcriptomic (RNAseq) profiles of C. rosea in response to DON and Fg-spent media treatment, were developed. This analysis revealed 24,112 C. rosea unigenes, of which 5,605 and 6,285 were differentially regulated by DON and F-spent media, respectively. More than half of these unigenes were up-regulated, with annotations, most notably in the Fg-spent media treatment data, suggesting enhancement of polyketide (PK) and non-ribosomal peptide (NRP) secondary metabolite precursor synthesis, and PK/NRP-like synthases. Four ABC transporters were also up-regulated in response to Fg-spent media. Further analysis showed that the PK and NRP-like synthases belong to three gene clusters that also include ABC transporters, and other genes known to tailor secondary metabolite biosynthesis. The RNAseq data was further validated using quantitative RT-qPCR. Taken together, these results show that C. rosea responds to the presence of Fg-spent media (and to a lesser extent, DON-alone) by up-regulating unique aspects of its secondary metabolism-related genetic repertoire. The identities and roles of C. rosea secondary metabolites produced by the targeted gene clusters are now under investigation.

Update on the benefits and mechanisms of action of the bioactive vegetal alkaloid berberine on lipid metabolism and homeostasis - Wang, Yanwen; Zidichouski, Jeffrey A. (Cholesterol, 2018)
Elevation of circulating levels of blood cholesterol, especially LDL cholesterol, and/or the decrease of HDL cholesterol levels have long been recognized as primary risk factors for developing atherosclerosis that leads to cardiovascular and cerebrovascular disease. Hypertriglyceridemia is an independent risk factor that is known to contribute to the development of atherosclerosis. Thus, various interventional efforts aimed at reducing hypercholesterolemia and hypertriglyceridemia have been practiced clinically for decades to reduce morbidity and mortality risk associated with deleterious cardiovascular and cerebrovascular events. As such, many drugs have been developed and clinically used to treat hypocholesteremia and/or hypertriglyceridemia; however, dietary approaches including supplements along with changes in nutrition and lifestyle have become increasingly attractive and acceptable methods used to control borderline or moderately increased levels of blood cholesterol and triacylglycerols. In this regard, the use of a plant/herbal bioactive compound, berberine (BBR), has recently been studied extensively in terms of its efficacy as well as its mechanisms of action and safety as an alternative intervention that beneficially modulates blood lipids. The aim of this review is to provide a comprehensive update on BBR research, new concepts and directions in terms of product development and current challenges, and future prospects of using BBR to manage diseases and complications associated with dyslipidemia.

Laser-induced breakdown spectroscopy of molten matte - Moreau, A.; Hamel, A.; Bouchard, P.; Sabsabi, M. (CIM Journal, 2018)
Laser-induced breakdown spectroscopy (LIBS) is an atomic emission spectroscopy technique suitable for in-situ and in-line measurements during pyrometallurgy. A mobile prototype system was developed to measure elemental compositions of molten metals. An inert gas flows through a tube with one end immersed in molten metal and the gas bubbles out below the melt surface. The LIBS measurement is made through the tube and onto the bubble’s surface. This avoids measuring surface contaminants and slag. This paper presents the simultaneous measurement of Cu, Ni, Fe, Co, and S concentrations in molten matte at 1,125°C.
Keywords: copper; cuivre; laser-induced breakdown spectroscopy (LIBS); spectroscopie des plasma induits par laser (LIBS); matte; matte; nickel; nickel; pyrometallurgy; pyrométallurgie; sensor; capteur

Indigenous language technologies in Canada: assessment, challenges, and successes - Littell, Patrick; Kazantseva, Anna; Kuhn, Roland; Pine, Aidan; Arppe, Antti; Cox, Christopher; Junker, Marie-Odile (Proceedings of the 27th International Conference on Computational Linguistics, 2018)
In this article, we discuss which text, speech, and image technologies have been developed, and would be feasible to develop, for the approximately 60 Indigenous languages spoken in Canada. In particular, we concentrate on technologies that may be feasible to develop for most or all of these languages, not just those that may be feasible for the few most-resourced of these. We assess past achievements and consider future horizons for Indigenous language transliteration, text prediction, spell-checking, approximate search, machine translation, speech recognition, speaker diarization, speech synthesis, optical character recognition, and computer-aided language learning.

Preliminary evaluation of NRC-FCs2 fountain clock at the National Research Council Canada - Beattie, Scott; Jian, Bin; Alcock, John A.; Gertsvolf, Marina; Hendricks, Rich; Handricks, Rich; Szymaniec, Krzysztof; Gibble, Kurt (Proceedings of the 2018 IEEE International Frequency Control Symposium (IFCS), 2018)
At the NRC we are performing the first accuracy evaluation of our newly developed caesium fountain clock, NRC-FCs2. This primary frequency standard operates with a short term stability and upon full evaluation, we expect to achieve a type B uncertainty in fractional frequency below 5x10⁻¹⁶. We will discuss the current status of the evaluation, including several evaluated shifts, as well as the outstanding systematics yet to be fully characterized.
Keywords: Primary frequency standard; microwave; clock; atom cooling and trapping

Testing the role of recollision in N2+ air lasing - Britton, Mathew; Laferrière, Patrick; Ko, Dong Hyuk; Li, Zhengyan; Kong, Fanqi; Brown, Graham; Naumov, Andrei; Zhang, Chunmei; Arissian, Ladan; Corkum, P. B. (Physical Review Letters, 2018)
It has been known for many years that during filamentation of femtosecond light pulses in air, gain is observed on the B to X transition in N+2. While the gain mechanism remains unclear, it has been proposed that recollision, a process that is fundamental to much of strong field science, is critical for establishing gain. We probe this hypothesis by directly comparing the influence of the ellipticity of the pump light on gain in air filaments. Then, we decouple filamentation from gain by measuring the gain in a thin gas jet that we also use for high harmonic generation. The latter allows us to compare the dependence of the gain on the ellipticity of the pump with the dependence of the high harmonic signal on the ellipticity of the fundamental. We find that gain and harmonic generation have very different behavior in both filaments and in the jet. In fact, in a jet we even measure gain with circular polarization. Thus, we establish that recollision does not play a significant role in creating the inversion.

Text-mining building maintenance work orders for component fault frequency - Gunay, H. Burak; Shen, Weiming; Yang, Chunsheng (Building Research & Information, 2018)
Operators’ work order descriptions in computerized maintenance management systems (CMMS) represent an untapped opportunity to benchmark a facility’s maintenance and operation performance. However, it is challenging to carry out analytics on these large and amorphous databases. This paper puts forward a text-mining method to extract information about failure patterns in building systems and components from CMMS databases. The method is executed in three steps. Step 1 is pre-processing to convert work order descriptions into a mathematical form that lends itself to a quantitative lexical analysis. Step 2 is clustering to focus on interesting sections of a CMMS database that contain work orders about failures in building systems and components – rather than less interesting routine maintenance and inspection activities. Step 3 is association rule-mining to identify the coexistence tendencies among the terms of cluster of interest (e.g. coexistence of the terms ‘radiator’ and ‘leak’). This text-mining method is demonstrated by using two data sets. One data set was from a central heating and cooling plant with four boilers and five chillers; the other data set was from a cluster of 44 buildings. The results provide insights into per equipment breakdown of failure events, top system and component-level failure modes, and their occurrence frequencies.
Keywords: building operations; building performance; diagnostics; facilities management; fault detection; HVAC systems; maintenance; operator logbooks; text-mining

Targeted mutagenesis in wheat microspores using CRISPR/Cas9 - Bhowmik, Pankaj; Ellison, Evan; Polley, Brittany; Bollina, Venkatesh; Kulkarni, Manoj; Ghanbarnia, Kaveh; Song, Halim; Gao, Caixia; Voytas, Daniel F.; Kagale, Sateesh (Scientific Reports, 2018)
CRISPR/Cas9 genome editing is a transformative technology that will facilitate the development of crops to meet future demands. However, application of gene editing is hindered by the long life cycle of many crop species and because desired genotypes generally require multiple generations to achieve. Single-celled microspores are haploid cells that can develop into double haploid plants and have been widely used as a breeding tool to generate homozygous plants within a generation. In this study, we combined the CRISPR/Cas9 system with microspore technology and developed an optimized haploid mutagenesis system to induce genetic modifications in the wheat genome. We investigated a number of factors that may affect the delivery of CRISPR/Cas9 reagents into microspores and found that electroporation of a minimum of 75,000 cells using 10–20 µg DNA and a pulsing voltage of 500 V is optimal for microspore transfection using the Neon transfection system. Using multiple Cas9 and sgRNA constructs, we present evidence for the seamless introduction of targeted modifications in an exogenous DsRed gene and two endogenous wheat genes, including TaLox2 and TaUbiL1. This study demonstrates the value and feasibility of combining microspore technology and CRISPR/Cas9-based gene editing for trait discovery and improvement in plants.

Superior performance of Na7V4(P2O7)4PO4 in sodium ion batteries - Fang, Wenying; An, Zhongxun; Xu, Jiaqiang; Zhao, Hongbin; Zhang, Jiujun (RSC Advances, 2018)
A novel synthetic method has been investigated to fabricate a 1D nanostructure Na7V4(P2O7)4PO4. Mixed polyanion materials with a well-defined 3D framework channel can improve the electrochemical performance of sodium reversible insertion/extraction reactions, and can be especially beneficial for high rate performance and cycling capability. It approaches an initial reversible electrochemical capacity of 92.0 mA h g−1 with a high discharge potential over 3.85 V (vs. Na/Na+) and good cycling properties with a capacity retention of 81.4% after 300 cycles at a 0.5C rate in sodium systems. Taking into consideration the superior electrochemical characteristics, the phase-pure composite is considered to have a promising high rate capability as well as being a high capacity electrode material for advanced energy storage applications.

Superhydrophobic and superhydrophilic functionalized surfaces by picosecond laser texturing - Serles, Peter; Nikumb, Suwas; Bordatchev, Evgueni (Journal of Laser Applications, 2018)
The study of laser textured surfaces has been carried out in the pursuit of superhydrophobic and superhydrophilic functional surfaces on stainless steel and silicon carbide substrate materials, respectively. The theoretical aspects of laser texturing a surface were investigated in order to understand how replication of micro- and nanoscale features could be achieved by high intensity picosecond pulsed laser systems. A series of laser parameters, pre-processing, and post-processing steps were developed to achieve contact angles of 152° as well as 0° on stainless steel and silicon carbide substrates, respectively. The substrates were used to demonstrate functional characteristics such as water repellency, self-cleaning, water adhesion, and dispersion of water using micro-capillary forces.
Keywords: superhydrophobic; superhydrophilic; picosecond pulsed laser; surface; functionalization; microfabrication; wettability

Structure of the LPS O-chain from Fusobacterium nucleatum strain MJR 7757 B - Vinogradov, Evgeny; St Michael, Frank; Cox, Andrew D. (Carbohydrate Research, 2018)
Fusobacterium nucleatum is an anaerobic bacterium found in the human mouth where it causes periodontitis. It was also found in colorectal cancer tissues and is linked with pregnancy complications, including pre-term and still births. Cell surface structures of the bacterium could be implicated in pathogenesis. Here we report the following structure of the lipopolysaccharide O-chain of F. nucleatum strain MJR 7757 B:where Lac is (R)-1-carboxyethyl (lactic acid residue); all monosaccharides are in the pyranose form. ManNAc4Lac, analogue of N-acetylmuramic acid, is found for the first time in natural sources.
Keywords: Fusobacterium nucleatum; lipopolysaccharide; NMR spectroscopy; polysaccharide; structure

Progress in nanostructured (Fe or Co)/N/C non-noble metal electrocatalysts for fuel cell oxygen reduction reaction - Zhang, Lei; Wilkinson, David P.; Liu, Yuyu; Zhang, Jiujun (Electrochimica Acta, 2018)
The high cost and limited supply of platinum for Pt-based catalysts in proton exchange membrane fuel cells (PEMFCs) have driven intensive research into the use of non-noble metal catalysts in recent years. As the most promising non-noble metal catalysts for PEMFC oxygen reduction reactions (ORR), metal/N/C class of catalysts has been extensively explored. Earlier efforts (1964–2004) were mainly focused on the exploration of various synthesis routes and the investigation of active site mechanisms. During recent years (2005–2010), great progress in the development of these types of non-noble metal catalysts in real PEMFC environments has been achieved both in terms of catalytic activity and stability. From 2011 to present, several new synthetic approaches have been explored to produce highly dense catalytically active sites decorated within micropores using rationally designed zeolite imidazolate frameworks (ZIFs) and porous organic polymers (POPs). Currently, the most active non-noble metal catalysts are derived using this method and are able to deliver a kinetic volumetric current density of 450 A/cm3 at 0.8 V under fuel cell operating conditions. These results are superior to the US DOE 2020 target of 300 A/cm3. In terms of fuel cell maximum power density, the best non-noble metal catalysts for cathodes can achieve results as high as 0.98 W/cm2 and 0.41 W/cm2 with feeds of pure O2 and air respectively. In terms of stability, some non-noble metal catalysts have remained stable for over 1000 h with only minor degradation under PEMFC conditions. Nonetheless, activity and stability still remain major challenges for non-noble metal catalysts when compared to Pt-based ones in PEMFCs. Improvements in the structure of both catalysts and catalyst layers are urgently needed to realize the activity targets established for automobile fuel cell applications as well as the US DOE Hydrogen and Fuel Cell (H&FC) program. In the long term and the sustainable commercialization of fuel cells, replacing Pt-based catalysts with non-noble metal catalysts is, in the present authors' opinion, the most sustainable solution. Therefore, further intensive research into fundamental studies is critical to uncovering the workings of active site mechanisms. Once controllable design and synthesize of non-noble metal catalysts with high active site densities and utilization can be achieved, the goal of cost-effective, non-noble metal catalysts in automobile fuel cells can become reality.
Keywords: nanostructure; non-noble metal electrocatalyst; oxygen reduction reaction; fuel cell

Resolved millimeter observations of the HR 8799 debris disk - Wilner, David J.; Macgregor, Meredith A.; Andrews, Sean M.; Hughes, A. Meredith; Matthews, Brenda; Su, Kate (The Astrophysical Journal, 2018)
We present 1.3 mm observations of the debris disk surrounding the HR 8799 multi-planet system from the Submillimeter Array to complement archival ALMA observations that spatially filtered away the bulk of the emission. The image morphology at 3".8 (150 au) resolution indicates an optically thin circumstellar belt, which we associate with a population of dust-producing planetesimals within the debris disk. The interferometric visibilities are fit well by an axisymmetric radial power-law model characterized by a broad width, ΔR/R >≈ 1. The belt inclination and orientation parameters are consistent with the planet orbital parameters within the mutual uncertainties. The models constrain the radial location of the inner edge of the belt to Rin = 104(^+8 -12) au. In a simple scenario where the chaotic zone of the outermost planet b truncates the planetesimal distribution, this inner edge location translates into a constraint on the planet b mass of Mpl = 5.8^(+7.9 -3.1) M Jup. This mass estimate is consistent with infrared observations of the planet luminosity and standard hot-start evolutionary models, with the uncertainties allowing for a range of initial conditions. We also present new 9 mm observations of the debris disk from the Very Large Array and determine a millimeter spectral index of 2.41 ± 0.17. This value is typical of debris disks and indicates a power-law index of the grain size distribution q = 3.27 ± 0.10, close to predictions for a classical collisional cascade.

Structural studies of the cell wall polysaccharide from Lactococcus lactis UC509.9 - Vinogradov, Evgeny; Sadovskaya, Irina; Grard, Thierry; Murphy, James; Mahony, Jennifer; Chapot-Chartier, Marie-Pierre; Van Sinderen, Douwe (Carbohydrate Research, 2018)
Lactococcus lactis is the most widely utilised starter bacterial species in dairy fermentations. The L. lactis cell envelope contains polysaccharides, which, among other known functions, serve as bacteriophage receptors. Our previous studies have highlighted the structural diversity of these so-called cell wall polysaccharides (CWPSs) among L. lactis strains that could account for the narrow host range of most lactococcal bacteriophages. In the present work, we studied the CWPS of L. lactis strain UC509.9, an Irish dairy starter strain that is host to the temperate and well-characterized P335-type phage Tuc2009. The UC509.9 CWPS structure was analyzed by methylation, deacetylation/deamination, Smith degradation and 2D NMR spectroscopy. The CWPS consists of a linear backbone composed of a tetrasaccharide repeat unit, partially substituted with a branched phosphorylated oligosaccharide having a common trisaccharide and three non-stoichiometric substitutions.

Structural characteristics and membrane interactions of tandem α-synuclein oligomers - Dong, Chunhua; Hoffmann, Marion; Li, Xi; Wang, Meijing; Garen, Craig R.; Petersen, Nils O.; Woodside, Michael T. (Scientific Reports, 2018)
Pre-fibrillar oligomers of α-synuclein are thought to be pathogenic molecules leading to neurotoxicity associated with Parkinson’s disease and other neurodegenerative disorders. However, small oligomers are difficult to isolate for study. To gain better insight into the properties of small α-synuclein oligomers, we investigated engineered oligomers of specific size (dimers, tetramers, and octamers) linked head-to-tail in tandem, comparing the behavior of the oligomers to monomeric α-synuclein. All oligomeric constructs remained largely disordered in solution, as determined from dynamic light scattering and size-exclusion chromatography. Electron microscopy revealed that each construct could aggregate to form fibrils similar to those formed by monomeric α-synuclein. The interactions with large unilamellar vesicles (LUVs) composed of negatively-charged lipids differed depending on size, with smaller oligomers forming more extensive helical structure as determined by CD spectroscopy. Monitoring the influx of a fluorescence bleaching agent into vesicles showed that larger oligomers were somewhat more effective at degrading vesicular integrity and inducing membrane permeabilization.

Strong-field optoelectronics in solids - Vampa, G.; Hammond, T. J.; Taucer, M.; Ding, Xiaoyan; Ropagnol, X.; Ozaki, T.; Delprat, S.; Chaker, M.; Thiré, N.; Schmidt, B. E.; Légaré, F.; Klug, D. D.; et al. (Nature Photonics, 2018)
Perturbative optical nonlinearities induced by static electric fields have proven useful in visualizing dynamical function in systems including operating circuits, electric and magnetic domain walls, and biological matter, and in controlling light for applications in silicon photonics. Here, we extend field-induced second-harmonic generation to the non-perturbative regime. We demonstrate that static or transient fields up to terahertz (THz) frequencies applied to silicon and ZnO crystals generate even-order high harmonics. Images of the even harmonics confirm that static fields delivered with conventional electronics control the spatial properties of the high-harmonic emission. Extending our methodology to higher-harmonic photon energies paves the way for realizing active optics in the extreme ultraviolet and will allow imaging of operating electronic circuits, of Si-photonic devices and of other functional materials, with higher spatio-temporal resolution than perturbative methods. For THz spectroscopy, our method has the bandwidth to allow measurement of attosecond transients imprinted on THz waveforms.

Stochastic process design kits for photonic circuits based on polynomial chaos augmented macro-modelling - Waqas, Abi; Melati, Daniele; Manfredi, Paolo; Melloni, Andrea (Optics Express, 2018)
Fabrication tolerances can significantly degrade the performance of fabricated photonic circuits and process yield. It is essential to include these stochastic uncertainties in the design phase in order to predict the statistical behaviour of a device before the final fabrication. This paper presents a method to build a novel class of stochastic-based building blocks for the preparation of Process Design Kits for the analysis and design of photonic circuits. The proposed design kits directly store the information on the stochastic behaviour of each building block in the form of a generalized-polynomial-chaos-based augmented macro-model obtained by properly exploiting stochastic collocation and Galerkin methods. Using these macro-models, only a single deterministic simulation is required to compute the stochastic moments of any arbitrary photonic circuit, without the need of running a large number of time-consuming circuit simulations thereby dramatically improving simulation efficiency. The effectiveness of the proposed approach is verified by means of classical photonic circuit examples with multiple uncertain variables.

Steroids limit myocardial edema during Ex vivo perfusion of hearts donated after circulatory death - Sandha, Jaskiran K.; White, Christopher W.; Müller, Alison; Avery, Emma; Thliveris, James; Dixon, Ian M.C.; Arora, Rakesh C.; Tian, Ganghong; Hryshko, Larry V.; Nagendran, Jayan; Freed, Darren H. (The Annals of Thoracic Surgery, 2018)
Background: Normothermic ex vivo heart perfusion (EVHP) has been shown to improve the preservation of hearts donated after circulatory arrest and to facilitate clinical successful transplantation. Steroids are added to the perfusate solution in current clinical EVHP protocols; however, the impact of this approach on donor heart preservation has not been previously investigated. We sought to determine the impact of steroids on the inflammatory response and development of myocardial edema during EVHP. Methods: Thirteen pigs were anesthetized, mechanical ventilation was discontinued, and a hypoxemic cardiac arrest ensued. A 15-minute warm-ischemic standoff period was observed, and then hearts were resuscitated with a cardioplegic solution. Donor hearts were then perfused ex vivo in a normothermic beating state for 6 hours with 500 mg of methylprednisolone (steroid: n = 5) or without (control: n = 8). Results: The addition of steroids to the perfusate solution reduced the generation of proinflammatory cytokines (interleukin-6, -8, -1β, and tumor necrosis factor-α) and the development of myocardial edema during EVHP (percentage of weight gain: control = 26% ± 7% versus steroid = 16% ± 10%, p = 0.049). Electron microscopy suggested less endothelial cell edema in the steroid group (injury score: control = 1.8 ± 0.2 versus steroid = 1.2 ± 0.2, p = 0.06), whereas perfusate troponin-I (control = 11.9 ± 1.9 ng/mL versus steroid = 9.5 ± 2.4 ng/mL, p = 0.448) and myocardial function were comparable between the groups. Conclusions: The addition of methylprednisolone to the perfusion solution minimizes the generation of proinflammatory cytokines and development of myocardial edema during normothermic ex vivo perfusion of hearts donated after circulatory arrest.

Stereochemical definition of the natural product (6R,10R,13R, 14R,16R,17R,19S,20S,21R,24S,25S,28S,30S,32R,33R,34R,36S,37S,39R)‐azaspiracid‐3 by total synthesis and comparative analyses - Kenton, Nathaniel T.; Adu-ampratwum, Daniel; Okumu, Antony A.; Mccarron, Pearse; Kilcoyne, Jane; Rise, Frode; Wilkins, Alistair L.; Miles, Christopher O.; Forsyth, Craig J. (Angewandte Chemie International Edition, 2018)
The previously accepted structure of the marine toxin azaspiracid‐3 is revised based upon an original convergent and stereoselective total synthesis of the natural product. The development of a structural revision hypothesis, its testing, and corroboration are reported. Synthetic (6R,10R,13R,14R,16R,17R,19S,20S,21R,24S,25S,28S,30S,32R, 33R,34R,36S,37S,39R)‐azaspiracid‐3 chromatographically and spectroscopically matched naturally occurring azaspiracid‐3, whereas the previously assigned 20R epimer did not.

Spectrally resolved light extinction enhancement of coated soot particles - Lefevre, G.; Yon, J.; Liu, F.; Coppalle, A. (Atmospheric Environment, 2018)
The aim of the present study is to evaluate experimentally the impact of a non-absorbing coating material on the spectral radiative properties of freshly produced carbonaceous aerosols. Once emitted into the atmosphere, carbonaceous particles are prone to interact with organic chemical compounds to acquire a certain amount of non-absorbing or weakly absorbing coating on their surface. In the present study, oleic acid is used as a surrogate for the coating material and applied to aerosols produced by a miniCAST (soot particles of different chemical and morphological properties) and a spark discharge aerosol generator. A simple analytical model is presented to evaluate the coating thickness. Furthermore, the spectrally resolved extinction cross sections of uncoated and coated particles are determined enabling the evaluation of the mass specific extinction coefficient and the extinction enhancement factor over a wide spectral range (200−1100nm). Influences of the coating thickness and the type of core carbonaceous particles are also discussed.
Keywords: extinction; coated carbonaceous particles; brown carbon; spectral dependence

Sources of variance in BC mass measurements from a small marine engine: influence of the instruments, fuels and loads - Jiang, Yu; Yang, Jiacheng; Gagné, Stéphanie; Chan, Tak W.; Thomson, Kevin; Fofie, Emmanuel; Cary, Robert A.; Rutherford, Dan; Comer, Bryan; Swanson, Jacob; Lin, Yue; Van Rooy, Paul; et al. (Atmospheric Environment, 2018)
Knowledge of black carbon (BC) emission factors from ships is important from human health and environmental perspectives. A study of instruments measuring BC and fuels typically used in marine operation was carried out on a small marine engine. Six analytical methods measured the BC emissions in the exhaust of the marine engine operated at two load points (25% and 75%) while burning one of three fuels: a distillate marine (DMA), a low sulfur, residual marine (RMB-30) and a high-sulfur residual marine (RMG-380). The average emission factors with all instruments increased from 0.08 to 1.88 gBC/kg fuel in going from 25 to 75% load. An analysis of variance (ANOVA) tested BC emissions against instrument, load, and combined fuel properties and showed that both engine load and fuels had a statistically significant impact on BC emission factors. While BC emissions were impacted by the fuels used, none of the fuel properties investigated (sulfur content, viscosity, carbon residue and CCAI) was a primary driver for BC emissions. Of the two residual fuels, RMB-30 with the lower sulfur content, lower viscosity and lower residual carbon, had the highest BC emission factors. BC emission factors determined with the different instruments showed a good correlation with the PAS values with correlation coefficients R2 >0.95. A key finding of this research is the relative BC measured values were mostly independent of load and fuel, except for some instruments in certain fuel and load combinations.
Keywords: black carbon; measurement methods; marine fuels; loads

Sorting of semiconducting single-walled carbon nanotubes in polar solvents with an amphiphilic conjugated polymer provides general guidelines for enrichment - Ouyang, Jianying; Ding, Jianfu; Lefebvre, Jacques; Li, Zhao; Guo, Chang; Kell, Arnold J.; Malenfant, Patrick R. L. (ACS Nano, 2018)
Conjugated polymer extraction (CPE) has been shown to be a highly effective method to isolate high-purity semiconducting single-walled carbon nanotubes (sc-SWCNTs). In both literature reports and industrial manufacturing, this method has enabled enrichment of sc-SWCNTs with high purity (≥99.9%). High selectivity is typically obtained in nonpolar aromatic solvents, yet polar solvents may provide process improvements in terms of yield, purity and efficiency. Using an amphiphilic fluorene-alt-pyridine conjugated copolymer with hydrophilic side chains, we have investigated the enrichment of sc-SWCNTs in polar solvents. Various conditions such as polymer/SWCNT ratio, solvent polarity, solvent dielectric constant as well as polymer solubility and SWCNT dispersibility were explored in order to optimize the purity and yield of the enriched product. Herein, we provide insights on CPE by demonstrating that a conjugated polymer having a hydrophobic backbone and hydrophilic oligo(ethylene oxide) side chains provides near full recovery (95%) of sc-SWCNTs using a multiextraction protocol. High purity is also obtained, and differences in chiral selectivity compared to analogous hydrophobic systems were confirmed by optical absorption and Raman spectroscopy as well as photoluminescence excitation mapping. Taking into consideration the solvent dielectric constant, polarity index as well as polymer solubility and SWCNT dispersibility provides a better understanding of structure–property effects on sc-SWCNT enrichment. The resulting hydrophilic SWCNT dispersions demonstrate long-term colloidal stability, making them suitable for ink formulation and high-performance thin-film transistors fabrication.
Keywords: amphiphilic polymer; enrichment; high-purity semiconducting SWCNT; inkjet printing; polar solvents; poly(fluorene-alt-pyridine); thin-film transistors

Soot production modeling in a laminar coflow ethylene diffusion flame at different Oxygen Indices using a PAH-based sectional model - Jerez, Alejandro; Consalvi, Jean-Louis; Fuentes, Andrés; Liu, Fengshan; Demarco, Rodrigo (Fuel, 2018)
A numerical study is carried out to, first of all, investigate the capability of a Polycyclic Aromatic Hydrocarbon (PAH)-based sectional particle dynamics soot model in the prediction of soot production in laminar coflow ethylene diffusion flames. The effects of different oxygen mole fractions in the oxidizer stream, called Oxygen Index (OI), ranging from 17% to oxygen-enriched conditions up to 33% are investigated. Secondly, the relative importance of species responsible for the increase in both soot formation and oxidation rates with increasing the OI is analyzed. The soot production model considers a detailed description of nucleation via collisions among heavy PAHs, particle aggregation, PAH condensation, surface growth and oxidation through the hydrogen abstraction acetylene addition (HACA) mechanism, and fragmentation of soot aggregates. Model predictions are compared with previously-published experimental data and numerical predictions obtained with a semi-empirical acetylene-based soot production model [Comb. Flame 160: 786–795 (2013)]. Results indicate that the flame structure, soot volume fraction and flame cross-section integrated soot volume fraction predicted by the PAH-based sectional soot model are in good agreement with the experimental data over the entire range of OI considered. The temperature and the concentrations of soot precursors increase with the OI, leading to higher soot nucleation, condensation, surface growth, and oxidation rates. Results show that the PAH-based sectional soot model represents a significant improvement over the semi-empirical acetylene based two-equation soot model studied earlier, especially in conditions far from the normal air conditions (21% of O2). With increasing the OI, the non-dimensional zone of influence does not change for the flame cross-section integrated soot formation rates but increases for the integrated soot oxidation rate. Nucleation occurs just above the burner rim and displays the largest increase in its rate with increasing the OI. Nucleation and condensation are mainly dependent on the concentrations of BGHIF and BAPYR. Condensation is also affected by the increase in the number of aggregates available for collision. Soot formation is mainly dominated by surface growth, through HACA, with a significant influence of soot condensation closer to the burner surface, regardless of the level of OI. The surface growth through HACA is mainly controlled not only by the acetylene concentration and the associated kinetic rate, but also by the specific soot surface area. Oxidation by O2 is found to dominate at the top of the flame, while oxidation by OH is dominant at the middle height of the flame. The oxidation rate by O2 increases more rapidly with increasing the OI than that by OH.
Keywords: laminar diffusion flame; PAH-based soot model; under-oxygenated flames; over-oxygenated flames; numerical modeling

Soil contamination alters the willow root and rhizosphere metatranscriptome and the root–rhizosphere interactome - Yergeau, Etienne; Tremblay, Julien; Joly, Simon; Labrecque, Michel; Maynard, Christine; Pitre, Frederic E.; St-Arnaud, Marc; Greer, Charles W. (The ISME Journal, 2018)
Phytoremediation using willows is thought to be a sustainable alternative to traditional remediation techniques involving excavation, transport, and landfilling. However, the complexity of the interaction between the willow and its associated highly diverse microbial communities makes the optimization of phytoremediation very difficult. Here, we have sequenced the rhizosphere metatranscriptome of four willow species and the plant root metatranscriptome for two willow species growing in petroleum hydrocarbon-contaminated and non-contaminated soils on a former petroleum refinery site. Significant differences in the abundance of transcripts related to different bacterial and fungal taxa were observed between willow species, mostly in contaminated soils. When comparing transcript abundance in contaminated vs. non-contaminated soil for each willow species individually, transcripts for many microbial taxa and functions were significantly more abundant in contaminated rhizosphere soil for Salix eriocephala, S. miyabeana and S. purpurea, in contrast to what was observed in the rhizosphere of S. caprea. This agrees with the previously reported sensitivity of S. caprea to contamination, and the superior tolerance of S. miyabeana and S. purpurea to soil contamination at that site. The root metatranscriptomes of two species were compared and revealed that plants transcripts are mainly influenced by willow species, while microbial transcripts mainly responded to contamination. A comparison of the rhizosphere and root metatranscriptomes in the S. purpurea species revealed a complete reorganization of the linkages between root and rhizosphere pathways when comparing willows growing in contaminated and non-contaminated soils, mainly because of large shifts in the rhizosphere metatranscriptome.

Seeing red in NGC 1978, NGC 55, and NGC 3109 - Davidge, T. J. (The Astrophysical Journal, 2018)
Spectra of the intermediate-age star cluster NGC 1978 and the dwarf irregular galaxies NGC 55 and NGC 3109 are discussed. The spectra were recorded with the Gemini Multi-object Spectrograph on Gemini South and span the 0.7–1.1 μm wavelength interval. Five slit pointings were observed in NGC 1978, and these are used to examine stochastic effects on the integrated red light from an intermediate-age cluster. The removal of either the brightest M giant or the brightest C star from the co-added spectrum has minor effects on the equivalent withs of the Ca triplet. The most robust signature of C stars in the integrated cluster spectrum at these wavelengths is the CN band head near 7900 Å. The equivalent widths of Ca triplet lines in the NGC 1978 spectrum and in the spectra of individual cluster stars are larger than expected for a scaled-solar abundance system. It is suggested that these stars have a lower than expected surface gravity, which might occur if the stars in NGC 1978 have been subject to extra mixing processes, as suggested by Lederer et al. The near-infrared color profile of NGC 1978 is shown to contain a prominent red cusp in the central 10 arcsec, and the suppression of light from this cusp does not affect the depth of the Ca lines in the integrated spectrum. The NGC 55 spectra run parallel to the major axis, and a gradient is found in the strength of the Ca lines, in the sense that the Ca lines weaken with increasing distance from the disk plane. Comparisons with models suggest that the disk light is dominated by stars with ages 1–2 Gyr, in agreement with star-forming histories (SFHs) obtained from the analysis of color–magnitude diagrams (CMDs). The NGC 55 spectra also sample a large star-forming complex. The age of this complex inferred from comparisons with models is broadly consistent with that estimated from a near-infrared CMD of the same region. The CN band head at 7900 Å in this part of NGC 55 is detected, but this is likely a signature of red supergiants (RSGs) rather than C stars. The NGC 3109 observations sample three different parts of that galaxy but have a low signal-to-noise ratio. Comparisons with models suggest that the light from the NGC 3109 disk at red wavelengths is dominated by RSGs with ages of at most a few tens of Myr, in qualitative agreement with SFHs that are based on photometric measurements.
Keywords: galaxies: individual (NGC 55 and NGC 3109); galaxies: stellar content; globular clusters: individual (NGC 1978)

Role of hydrogen in high-yield growth of boron nitride nanotubes at atmospheric pressure by induction thermal plasma - Kim, Keun Su; Couillard, Martin; Shin, Homin; Plunkett, Mark; Ruth, Dean; Kingston, Christopher T.; Simard, Benoit (ACS Nano, 2018)
We recently demonstrated scalable manufacturing of boron nitride nanotubes (BNNTs) directly from hexagonal BN (hBN) powder by using induction thermal plasma, with a high-yield rate approaching 20 g/h. The main finding was that the presence of hydrogen is crucial for the high-yield growth of BNNTs. Here we investigate the detailed role of hydrogen by numerical modeling and in situ optical emission spectroscopy (OES) and reveal that both the thermofluidic fields and chemical pathways are significantly altered by hydrogen in favor of rapid growth of BNNTs. The numerical simulation indicated improved particle heating and quenching rates (∼105 K/s) due to the high thermal conductivity of hydrogen over the temperature range of 3500–4000 K. These are crucial for the complete vaporization of the hBN feedstock and rapid formation of nanosized B droplets for the subsequent BNNT growth. Hydrogen is also found to extend the active BNNT growth zone toward the reactor downstream, maintaining the gas temperature above the B solidification limit (∼2300 K) by releasing the recombination heat of H atoms, which starts at 3800 K. The OES study revealed that H radicals also stabilize B or N radicals from dissociation of the feedstock as BH and NH radicals while suppressing the formation of N2 or N2+ species. Our density functional theory calculations showed that such radicals can provide faster chemical pathways for the formation of BN compared with relatively inert N2.
Keywords: boron nitride nanotubes; density functional theory; hydrogen-catalyzed; induction thermal plasma; optical emission spectroscopy; scalable manufacturing; thermofluid simulation

Revival of the magnetar PSR J1622–4950: observations with MeerKAT, Parkes, XMM-Newton, Swift, Chandra, and NuSTAR - Camilo, F.; Scholz, P.; Serylak, M.; Buchner, S.; Merryfield, M.; Kaspi, V. M.; Archibald, R. F.; Bailes, M.; Jameson, A.; Straten, W. van; Sarkissian, J.; Reynolds, J. E.; et al. (The Astrophysical Journal, 2018)
New radio (MeerKAT and Parkes) and X-ray (XMM-Newton, Swift, Chandra, and NuSTAR) observations of PSR J1622–4950 indicate that the magnetar, in a quiescent state since at least early 2015, reactivated between 2017 March 19 and April 5. The radio flux density, while variable, is approximately 100× larger than during its dormant state. The X-ray flux one month after reactivation was at least 800× larger than during quiescence, and has been decaying exponentially on a 111 ± 19 day timescale. This high-flux state, together with a radio-derived rotational ephemeris, enabled for the first time the detection of X-ray pulsations for this magnetar. At 5%, the 0.3–6 keV pulsed fraction is comparable to the smallest observed for magnetars. The overall pulsar geometry inferred from polarized radio emission appears to be broadly consistent with that determined 6–8 years earlier. However, rotating vector model fits suggest that we are now seeing radio emission from a different location in the magnetosphere than previously. This indicates a novel way in which radio emission from magnetars can differ from that of ordinary pulsars. The torque on the neutron star is varying rapidly and unsteadily, as is common for magnetars following outburst, having changed by a factor of 7 within six months of reactivation.

Revisiting the extended schmidt law: the important role of existing stars in regulating star formation - Shi, Yong; Yan, Lin; Armus, Lee; Gu, Qiusheng; Helou, George; Qiu, Keping; Gwyn, Stephen; Stierwalt, Sabrina; Fang, Min; Chen, Yanmei; Zhou, Luwenjia; Wu, Jingwen; et al. (The Astrophysical Journal, 2018)
Keywords: galaxies: evolution; galaxies: starburst; ISM: atoms; ISM: molecules; stars: formation

Reservoir of diverse adaptive learners and stacking fast hoeffding drift detection methods for evolving data streams - Pesaranghader, Ali; Viktor, Herna; Paquet, Eric (Machine Learning, 2018)
The last decade has seen a surge of interest in adaptive learning algorithms for data stream classification, with applications ranging from predicting ozone level peaks, learning stock market indicators, to detecting computer security violations. In addition, a number of methods have been developed to detect concept drifts in these streams. Consider a scenario where we have a number of classifiers with diverse learning styles and different drift detectors. Intuitively, the current ‘best’ (classifier, detector) pair is application dependent and may change as a result of the stream evolution. Our research builds on this observation. We introduce the Tornado framework that implements a reservoir of diverse classifiers, together with a variety of drift detection algorithms. In our framework, all (classifier, detector) pairs proceed, in parallel, to construct models against the evolving data streams. At any point in time, we select the pair which currently yields the best performance. To this end, we introduce the CAR measure, which is employed to balance classification, adaptation and resource utilization requirements. We further incorporate two novel stacking-based drift detection methods, namely the FHDDMS and FHDDMS add FHDDMSadd approaches. The experimental evaluation confirms that the current ‘best’ (classifier, detector) pair is not only heavily dependent on the characteristics of the stream, but also that this selection evolves as the stream flows. Further, our FHDDMS variants detect concept drifts accurately in a timely fashion while outperforming the state-of-the-art.
Keywords: Data stream mining Online learning Adaptive learning Concept drift Drift detection Classification Hoeffding’s inequality

Research on wheel wear of heavy-haul railway freight car of Chinese Daqin railway - Lyu, Kewei; Shao, Wendong; Huang, Wei (ICRT 2017, 2018)
Direct consequence of wheel/rail interaction of heavy-haul is cause of wheel/rail wear. Cost of railway operation is affected by wheel/rail wear. It is important that investigate the actual situation of wheel/rail wear for heavy haul railway freight cars. Because, only grasp the real condition of wheel wear, is the basic conditions for further the wheel wear problem. It is either verified or negated for reporting issues under investigation through simulation modeling. Reporting issues under investigation are verified based on simulation analysis for heavy-haul railway freight car of Chinese Daqin railway. In order to further improve techno-economics of heavy-haul railway freight transport, put forward the direction of the further development of heavy-haul railway freight car and the suggestion.

Relationship between QTL for grain shape, grain weight, test weight, milling yield, and plant height in the spring wheat cross RL4452/‘AC Domain’ - Cabral, Adrian L.; Jordan, Mark C.; Larson, Gary; Somers, Daryl J.; Humphreys, D. Gavin; Mccartney, Curt A.; Zhang, Aimin (PLOS ONE, 2018)
Kernel morphology characteristics of wheat are complex and quantitatively inherited. A doubled haploid (DH) population of the cross RL4452/‘AC Domain’ was used to study the genetic basis of seed shape. Quantitative trait loci (QTL) analyses were conducted on a total of 18 traits: 14 grain shape traits, flour yield (Fyd), and three agronomic traits (Plant height [Plht], 1000 Grain weight [Gwt], Test weight [Twt]), using data from trial locations at Glenlea, Brandon, and Morden in Manitoba, Canada, between 1999 and 2004. Kernel shape was studied through digital image analysis with an Acurum® grain analyzer. Plht, Gwt, Twt, Fyd, and grain shape QTL were correlated with each other and QTL analysis revealed that QTL for these traits often mapped to the same genetic locations. The most significant QTL for the grain shape traits were located on chromosomes 4B and 4D, each accounting for up to 24.4% and 53.3% of the total phenotypic variation, respectively. In addition, the most significant QTL for Plht, Gwt, and Twt were all detected on chromosome 4D at the Rht-D1 locus. Rht-D1b decreased Plht, Gwt, Twt, and kernel width relative to the Rht-D1a allele. A narrow genetic interval on chromosome 4B contained significant QTL for grain shape, Gwt, and Plht. The ‘AC Domain’ allele reduced Plht, Gwt, kernel length and width traits, but had no detectable effect on Twt. The data indicated that this variation was inconsistent with segregation at Rht-B1. Numerous QTL were identified that control these traits in this population.

Regenerable urchin-like Fe3O4@PDA-Ag hollow microspheres as catalyst and adsorbent for enhanced removal of organic dyes - Cui, Kuixin; Yan, Bin; Xie, Yijun; Qian, Hui; Wang, Xiaogang; Huang, Qingxue; He, Yuehui; Jin, Shengming; Zeng, Hongbo (Journal of Hazardous Materials, 2018)
In this work, novel urchin-like Fe3O4@polydopamine (PDA)-Ag hollow microspheres have been prepared via a facile synthesis method by in situ reduction and growth of Ag nanoparticles on mussel-inspired PDA layers coated on Fe3O4 hollow cores. The catalytic reduction efficiency and adsorption performance of the as-prepared urchin-like Fe3O4@polydopamine (PDA)-Ag hollow microspheres for model organic dyes (i.e., methylene blue and rhodamine B) under varying pH condition have been systematically investigated, which are demonstrated to be significantly enhanced as compared to that of spherical (relatively smooth) solid Fe3O4@PDA-Ag microspheres. The as-prepared urchin-like Fe3O4@PDA-Ag hollow microspheres show high reusability, easy separability, and fast regeneration ability, with no obvious drop in the catalytic and adsorption efficiency after cyclic reuse. The versatile PDA coatings on the urchin-like microspheres allow further surface functionalization for development of multifunctional catalyst and adsorbent materials. This work provides a very useful and facile methodology for synthesizing and tuning the urchin-like morphology of Fe3O4@PDA-Ag microspheres, with great potential applications in catalysis and wastewater treatment.
Keywords: urchin-like Fe3O4@PDA-Ag hollow microspheres; polydopamine; regeneration ability; catalytic reduction; water treatment

Recent advancements in the development of bifunctional electrocatalysts for oxygen electrodes in unitized regenerative fuel cells (URFCs) - Wang, Yan-Jie; Fang, Baizeng; Wang, Xiaomin; Ignaszak, Anna; Liu, Yuyu; Li, Aijun; Zhang, Lei; Zhang, Jiujun (Progress in Materials Science, 2018)
An ever-increasing energy demand has stimulated intense research into electrochemical technologies for both energy storage and conversion such as unitized regenerative fuel cells (URFCs). Due to its high efficiency, low cost, and low environmental impact, the URFC, which combines a polymer electrolyte membrane fuel cell (PEMFC) with a polymer electrolyte water electrolyzer (PEWE), has been regarded as an important energy technology that can offer new opportunities to not only further reduce investment costs but also to open doors to the mass production of domestic applications. Despite this, URFCs still have to be further improved and optimized to reach a level of maturity of both fuel cells and electrolyzers in terms of energy efficiency and long-term performance. Currently, the major challenge of URFC technology has been the insufficient performance of the bifunctional electrocatalyst. Based on the most recent research trends and progresses of bifunctional oxygen catalyst materials, this review will provide a systematic introduction and a comprehensive assessment of various bifunctional oxygen catalysts; their science and technology, including material selection, synthesis, and characterization, as well as their applications in URFCs. This review aims to correlate the physicochemical characteristics of URFCs with the catalytic activity/stability of these materials.
Keywords: unitized regenerative fuel cells; polymer electrolyte fuel cell; polymer electrolyte water electrolyzer; bifunctional electrocatalyst; catalytic activity; stability

Real-time spectral characterization of a photon pair source using a chirped supercontinuum seed - Erskine, Jennifer; England, Duncan; Kupchak, Connor; Sussman, Benjamin (CLEO: QELS_Fundamental Science 2018, 2018)
We perform joint spectral intensity measurements by studying stimulated four wave mixing in a birefringent fiber photon pair source. Seeding the process with a chirped supercontinuum beam, measurements are acquired in as little as 5 s.

Real-time spectral characterization of a photon pair source using a chirped supercontinuum seed - Erskine, Jennifer; England, Duncan; Kupchak, Connor; Sussman, Benjamin (Optics Letters, 2018)
Photon pair sources have wide ranging applications in a variety of quantum photonic experiments and protocols. Many of these protocols require well controlled spectral correlations between the two output photons. However, due to low cross-sections, measuring the joint spectral properties of photon pair sources has historically been a challenging and time-consuming task. Here, we present an approach for the real-time measurement of the joint spectral properties of a fiber-based four wave mixing source. We seed the four wave mixing process using a broadband chirped pulse, studying the stimulated process to extract information regarding the spontaneous process. In addition, we compare stimulated emission measurements with the spontaneous process to confirm the technique’s validity. Joint spectral measurements have taken many hours historically and several minutes with recent techniques. Here, measurements have been demonstrated in 5–30 s depending on resolution, offering substantial improvement. Additional benefits of this approach include flexible resolution, large measurement bandwidth, and reduced experimental overhead.

Real-time monitoring for structural health, public safety, and risk management of mine tailings dams - Hui, Shiqiang (Rob); Charlebois, Lawrence; Sun, Colin (Canadian Journal of Earth Sciences, 2018)
Public awareness of tailings dam failures is increasing in the wake of incidents in Canada and abroad. The present work establishes the current state of practice in mine tailings dam monitoring and provides a summary of the current technical and operational gaps identified through industry and stakeholder engagement. These gaps may be addressed with currently available technologies supplied by commercial instrumentation manufacturers; however, the assumed costs and lack of regulatory demand may serve as barriers to adoption. An integrated approach and diverse suite of technologies is needed to address issues of dam stability, worker and public safety, and environmental protection. Technological applications and limitations are described and design requirements are proposed for an integrated, real-time monitoring system. Socio-economic impacts and loss reduction benefits are considered and the need for industry and regulator participation is emphasized.
Keywords: tailings; dam failure; mine safety; monitoring systems; instrumentation; public safety; stériles; rupture de digue; sécurité des mines; systèmes de surveillance; instrumentation; sécurité publique

realfast: real-time, commensal fast transient surveys with the very large array - Law, C. J.; Bower, G. C.; Burke-Spolaor, S.; Butler, B. J.; Demorest, P.; Halle, A.; Khudikyan, S.; Lazio, T. J. W.; Pokorny, M.; Robnett, J.; Rupen, M. P. (The Astrophysical Journal Supplement Series, 2018)
Radio interferometers have the ability to precisely localize and better characterize the properties of sources. This ability is having a powerful impact on the study of fast radio transients, where a few milliseconds of data is enough to pinpoint a source at cosmological distances. However, recording interferometric data at millisecond cadence produces a terabyte-per-hour data stream that strains networks, computing systems, and archives. This challenge mirrors that of other domains of science, where the science scope is limited by the computational architecture as much as the physical processes at play. Here, we present a solution to this problem in the context of radio transients: realfast, a commensal, fast transient search system at the Jansky Very Large Array. realfast uses a novel architecture to distribute fast-sampled interferometric data to a 32-node, 64-GPU cluster for real-time imaging and transient detection. By detecting transients in situ, we can trigger the recording of data for those rare, brief instants when the event occurs and reduce the recorded data volume by a factor of 1000. This makes it possible to commensally search a data stream that would otherwise be impossible to record. This system will search for millisecond transients in more than 1000 hr of data per year, potentially localizing several Fast Radio Bursts, pulsars, and other sources of impulsive radio emission. We describe the science scope for realfast, the system design, expected outcomes, and ways in which real-time analysis can help in other fields of astrophysics.

Radiation resistant fiber Bragg grating in random air-line fibers for sensing applications in nuclear reactor cores - Zaghloul, Mohamed A.S.; Wang, Mohan; Huang, Sheng; Hnatovsky, Cyril; Grobnic, Dan; Mihailov, Stephen; Li, Ming-Jun; Carpenter, David; Hu, Lin-Wen; Daw, Joshua; Laffont, Guillaume; Nehr, Simon; et al. (Optics Express, 2018)
This paper reports the testing results of radiation resistant fiber Bragg grating (FBG) in random air-line (RAL) fibers in comparison with FBGs in other radiation-hardened fibers. FBGs in RAL fibers were fabricated by 80 fs ultrafast laser pulse using a phase mask approach. The fiber Bragg gratings tests were carried out in the core region of a 6 MW MIT research reactor (MITR) at a steady temperature above 600°C and an average fast neutron (>1 MeV) flux >1.2 × 1014 n/cm2/s. Fifty five-day tests of FBG sensors showed less than 5 dB reduction in FBG peak strength after over 1 × 1020 n/cm2 of accumulated fast neutron dose. The radiation-induced compaction of FBG sensors produced less than 5.5 nm FBG wavelength shift toward shorter wavelength. To test temporal responses of FBG sensors, a number of reactor anomaly events were artificially created to abruptly change reactor power, temperature, and neutron flux over short periods of time. The thermal sensitivity and temporal responses of FBGs were determined at different accumulated doses of neutron flux. Results presented in this paper reveal that temperature-stable Type-II FBGs fabricated in radiation-hardened fibers can survive harsh in-pile conditions. Despite large parameter drift induced by strong nuclear radiation, further engineering and innovation on both optical fibers and fiber devices could lead to useful fiber sensors for various in-pile measurements to improve safety and efficiency of existing and next generation nuclear reactors.

Quantum-beat photoelectron-imaging spectroscopy of Xe in the VUV - Forbes, Ruaridh; Makhija, Varun; Underwood, Jonathan G.; Stolow, Albert; Wilkinson, Iain; Hockett, Paul; Lausten, Rune (Physical Review A, 2018)
Time-resolved pump-probe measurements of Xe, pumped at 133 nm and probed at 266 nm, are presented. The pump pulse prepared a long-lived hyperfine wave packet in the Xe 5p5(2P∘1/2)6s2[1/2]∘ 1 manifold (E=77185cm−1=9.57eV). The wave packet was monitored via single-photon ionization and velocity map photoelectron images were measured. The images provide angle- and time-resolved data which, when obtained over a large time window (900 ps), constitute a precision quantum-beat spectroscopy measurement of the hyperfine state splittings. Additionally, analysis of the full photoelectron image stack provides a quantum-beat imaging modality, in which the Fourier components of the photoelectron images correlated with specific beat components can be obtained. This may also permit the extraction of isotope-resolved photoelectron images in the frequency domain, in cases where nuclear spins (hence beat components) can be uniquely assigned to specific isotopes (as herein), and also provides phase information relating to the ionization dynamics. The information content of both raw and inverted image stacks is investigated, suggesting the utility of the Fourier analysis methodology in cases where images cannot be inverted.

Probing position-dependent diffusion in folding reactions using single-molecule force spectroscopy - Foster, Daniel A. N.; Petrosyan, Rafayel; Pyo, Andrew G.T.; Hoffmann, Armin; Wang, Feng; Woodside, Michael T. (Biophysical Journal, 2018)
Folding of proteins and nucleic acids involves a diffusive search over a multidimensional conformational energy landscape for the minimal-energy structure. When examining the projection of conformational motions onto a one-dimensional reaction coordinate, as done in most experiments, the diffusion coefficient D is generally position dependent. However, it has proven challenging to measure such position-dependence experimentally. We investigated the position-dependence of D in the folding of DNA hairpins as a simple model system in two ways: first, by analyzing the round-trip time to return to a given extension in constant-force extension trajectories measured by force spectroscopy, and second, by analyzing the fall time required to reach a given extension in force jump measurements. These methods yielded conflicting results: the fall time implied a fairly constant D, but the round-trip time implied variations of over an order of magnitude. Comparison of experiments with computational simulations revealed that both methods were strongly affected by experimental artifacts inherent to force spectroscopy measurements, which obscured the intrinsic position-dependence of D. Lastly, we applied Kramers’s theory to the kinetics of hairpins with energy barriers located at different positions along the hairpin stem, as a crude probe of D at different stem positions, and we found that D did not vary much as the barrier was moved along the reaction coordinate. This work underlines the difficulties faced when trying to deduce position-dependent diffusion coefficients from experimental folding trajectories.

Printing silver conductive inks with high resolution and high aspect ratio - Chu, Ta-Ya; Zhang, Zhiyi; Tao, Ye (Advanced Materials Technologies, 2018)
Narrow metal lines with low electrical resistance are essential for many printable electronic devices. Printing metal lines of narrower than 10 µm and with a high thickness‐to‐width aspect ratio is very difficult and remains a technical challenge in printable electronics. In this work, by controlling the ink–substrate interaction and ink drying dynamics, 4.6 µm wide inkjet‐printed silver lines are demonstrated with an aspect ratio of 0.7 and an elliptical cross‐section. The silver lines are obtained by jetting a silver nanoparticle‐based ink onto an SU‐8‐coated polyethylene terephthalate substrate to form well‐defined silver lines, and then heating the lines to transform them into high aspect ratio narrow lines through ink dewetting and receding. The simultaneous dissolution and redistribution of SU‐8 by the ink result in a concave structure, which prevents the lines from bulging and allows the lines to become embedded into the SU‐8 film.

Preclinical longitudinal imaging of tumor microvascular radiobiological response with functional optical coherence tomography - Demidov, Valentin; Maeda, Azusa; Sugita, Mitsuro; Madge, Victoria; Sadanand, Siddharth; Flueraru, Costel; Vitkin, I. Alex (Scientific Reports, 2018)
Radiation therapy (RT) is widely used for cancer treatment, alone or in combination with other therapies. Recent RT advances have revived interest in delivering higher dose in fewer fractions, which may invoke both cellular and microvascular damage mechanisms. Microvasculature may thus be a potentially sensitive functional biomarker of RT early response, especially for such emerging RT treatments. However it is difficult to measure directly and non-invasively, and its time course, dose dependencies, and overall importance in tumor control are unclear. We use functional optical coherence tomography for quantitative longitudinal in vivo imaging in preclinical models of human tumor xenografts subjected to 10, 20 and 30 Gy doses, furnishing a detailed assessment of vascular remodeling following RT. Immediate (minutes to tens of minutes) and early (days to weeks) RT responses of microvascular supply, as well as tumor volume and fluorescence intensity, were quantified and demonstrated robust and complex temporal dose-dependent behaviors. The findings were compared to theoretical models proposed in the literature.

Precision tuning of InAs quantum dot emission wavelength by iterative laser annealing - Dubowski, Jan J.; Stanowski, Radoslaw; Dalacu, Dan; Poole, Philip J. (Optics & Laser Technology, 2018)
Controlling the emission wavelength of quantum dots (QDs) over large surface area wafers is challenging to achieve directly through epitaxial growth methods. We have investigated an innovative post growth laser-based tuning procedure of the emission of self-assembled InAs QDs grown epitaxially on InP (001). A targeted blue shift of the emission is achieved with a series of iterative steps, with photoluminescence diagnostics employed between the steps to monitor the result of intermixing. We demonstrate tuning of the emission wavelength of ensembles of QDs to within approximately ±1 nm, while potentially better precision should be achievable for tuning the emission of individual QDs.
Keywords: InAs quantum dots; quantum dot intermixing; iterative laser annealing; wavelength emission correction; photoluminescence

Potentiometric sensors with chalcogenide glasses as sensitive membranes: a short review - Moreno, Thiago V.; Malacarne, Luis C.; Baesso, Mauro L.; Qu, Wei; Dy, Eben; Xie, Zhong; Fahlman, Jason; Shen, Jun; Astrath, Nelson G. C. (Journal of Non-Crystalline Solids, 2018)
Nowadays there exists a large variety of Ion Selective Electrodes with chalcogenide glasses as sensitive membrane. This short review paper will discuss the development of these sensors for the last almost fifty years. The glass compositions, response modelling, construction methods, parameters evaluation and applications are reviewed. Research breakthroughs and remaining problems on chalcogenide glass Ion Selective Electrodes are discussed.
Keywords: chalcogenide glass membrane; ion selective electrode; sensor calibration

Potential for value-added utilization of bamboo shoot processing waste: recommendations for a biorefinery approach - Lin, Zhen; Chen, Jian; Zhang, Junzeng; Brooks, Marianne Su-Ling (Food and Bioprocess Technology, 2018)
Bamboo shoot processing produces substantial quantities of wastes in China and other parts of the world, with estimates of up to 70% of the harvested bamboo shoots being discarded as waste biomass. The solid waste residues that are generated as processing by-products consist of the outer sheath and basal section of the bamboo shoot, and wastewater is also produced, all of which pose a significant environmental burden. In comparison to the edible bamboo shoot tips, data on the composition of bamboo shoot processing residue (BSPR) are comparatively scarce. The tender shoots are rich in nutrients and bioactive compounds that are associated with health benefits against many chronic and degenerative diseases, and there is potential for these compounds to also be present in BSPR. Therefore, this paper reviews the current literature available on BSPR composition from both English and Chinese journals, for comparison with the tender bamboo shoot. From this information, the potential of using BSPR as a cheap source of valuable nutrients and bioactive compounds for value-added products (e.g., food additives, functional foods, and pharmaceuticals) is discussed. To maximize the value from BSPR and reduce its environmental impact as a waste, a systematic biorefinery approach for waste valorization is recommended.
Keywords: Bamboo shoots; Processing waste; Nutrients; Bioactive compounds; Waste utilization

Photonic generation of pseudo random microwave waveform based on a random fiber grating - Deng, Hong; Lu, Ping; Mihailov, Stephen; Yao, Jianping (Optical Fiber Communication Conference, 2018)

Phosphorus sorption capacity of biochars varies with biochar type and salinity level - Dugdug, Abdelhafid Ahmed; Chang, Scott X.; Ok, Yong Sik; Rajapaksha, Anushka Upamali; Anyia, Anthony (Environmental Science and Pollution Research, 2018)
Biochar is recognized as an effective material for recovering excess nutrients, including phosphorus (P), from aqueous solutions. Practically, that benefits the environment through reducing P losses from biochar-amended soils; however, how salinity influences P sorption by biochar is poorly understood and there has been no direct comparison on P sorption capacity between biochars derived from different feedstock types under non-saline and saline conditions. In this study, biochars derived from wheat straw, hardwood, and willow wood were used to compare P sorption at three levels of electrical conductivity (EC) (0, 4, and 8 dS m−1) to represent a wide range of salinity conditions. Phosphorus sorption by wheat straw and hardwood biochars increased as aqueous solution P concentration increased, with willow wood biochar exhibiting an opposite trend for P sorption. However, the pattern for P sorption became the same as the other biochars after the willow wood biochar was de-ashed with 1 M HCl and 0.05 M HF. Willow wood biochar had the highest P sorption (1.93 mg g−1) followed by hardwood (1.20 mg g−1) and wheat straw biochars (1.06 mg g−1) in a 25 mg L−1 P solution. Although the pH in the equilibrium solution was higher with willow wood biochar (~ 9.5) than with the other two biochars (~ 6.5), solution pH had no or minor effects on P sorption by willow wood biochar. The high sorption rate of P by willow wood biochar could be attributed to the higher concentrations of salt and other elements (i.e., Ca and Mg) in the biochar in comparison to that in wheat straw and hardwood biochars; the EC values were 2.27, 0.53, and 0.27 dS m−1 for willow wood, wheat straw, and hardwood biochars, respectively. A portion of P desorbed from the willow wood biochar; and that desorption increased with the decreasing P concentration in the aqueous solution. Salinity in the aqueous solution influenced P sorption by hardwood and willow wood but not by wheat straw biochar. We conclude that the P sorption capacity of the studied biochars is dependent on the concentration of the soluble element in the biochar, which is dependent on the biochar type, as well as the salinity level in the aqueous solution.
Keywords: biochar; equilibrium solution; feedstock type; salt stress; phosphorus sorption; wheat straw; wood

Perturbing laser field dependent high harmonic phase modulations - Li, Zhengyan; Kong, Fanqi; Brown, Graham; Hammond, T. J.; Ko, Dong-Hyuk; Zhang, Chunmei; Corkum, P. B. (Journal of Physics B: Atomic, Molecular and Optical Physics, 2018)
A perturbing laser pulse modulates and controls the phase of the high harmonic radiation driven by an intense fundamental pulse. Thus, a structured wave front can impress a specific spatial phase onto the generated high harmonic wave front. This modulation procedure leads to all-optical spatial light modulators for VUV or XUV radiation created by high harmonic generation. Here, through theoretical analysis and experiment, we study the correlation between the high harmonic phase modulations and the perturbing laser field amplitude and phase, providing guidelines for practical high harmonic spatial light modulators. In addition, we show that the petahertz optical oscilloscope for measuring electric fields of a perturbing beam is most robust using low order harmonics, far from the cut-off.

Selenium analysis in waters. Part 2: Speciation methods - Leblanc, Kelly L.; Kumkrong, Paramee; Mercier, Patrick H. J.; Mester, Zoltán (Science of The Total Environment, 2018)
In aquatic ecosystems, there is often no correlation between the total concentration of selenium present in the water column and the toxic effects observed in that environment. This is due, in part, to the variation in the bioavailability of different selenium species to organisms at the base of the aquatic food chain. The first part of this review (Kumkrong et al., 2018) discusses regulatory framework and standard methodologies for selenium analysis in waters. In this second article, we are reviewing the state of speciation analysis and importance of speciation data for decision makers in industry and regulators. We look in detail at fractionation methods for speciation, including the popular selective sequential hydride generation. We examine advantages and limitations of these methods, in terms of achievable detection limits and interferences from other matrix species, as well as the potential to over- or under-estimate operationally-defined fractions based on the various conversion steps involved in fractionation processes. Additionally, we discuss methods of discrete speciation (through separation methods), their importance in analyzing individual selenium species, difficulties associated with their implementation, as well as ways to overcome these difficulties. We also provide a brief overview of biological treatment methods for the remediation of selenium-contaminated waters. We discuss the importance of selenium speciation in the application of these methods and their potential to actually increase the bioavailability of selenium despite decreasing its total waterborne concentration.

Selenium analysis in waters. Part 1: Regulations and standard methods - Kumkrong, Paramee; Leblanc, Kelly L.; Mercier, Patrick H.J.; Mester, Zoltán (Science of The Total Environment, 2018)
Selenium is released into the aquatic environment through anthropogenic activities such as agricultural irrigation, coal mining, and metallurgical activities, where it acts as a reproductive toxin with negative effects on predatory fish and water fowl. Waterborne selenium concentrations are closely regulated worldwide, and various standardized methods are implemented by regulatory bodies to allow for the monitoring of selenium concentrations in different types of waters. Here, we discuss worldwide regulations relating to concentration limits of selenium in drinking, natural, and industrial waters. Focusing specifically on North America, we look at some standardized analysis methods and discuss the fact that many of these methods are not adequately sensitive to measure selenium in the concentrations outlined by the associated regulations for natural waters. We look in detail at the limitations of these methods with regards to both detection limits and interfering sample matrix components and establish the need for more sensitive and robust methods of analysis for regulatory compliance. This review is complemented by a second part (LeBlanc et al., 2018) where we discuss the state of selenium speciation analysis and importance of speciation data for decision makers in industry and regulators.

Personalized prediction of genes with tumor-causing somatic mutations based on multi-modal deep Boltzmann machine - Li, Yifeng; Fauteux, François; Zou, Jinfeng; Nantel, André; Pan, Youlian (Neurocomputing, 2018)
When diagnosed at an advanced stage, most cancer patients suffer from treatment failure, recurrences and low survival. Taking advantage of high-throughput sequencing and deep learning techniques, we developed an early cancer monitoring method based on multi-modal deep Boltzmann machine to (1) learn association between matched germline and somatic mutations captured by whole exome sequencing from available samples of cancer patients, and (2) predict patient-specific high-risk genes whose somatic mutations are required to drive normal tissues to a tumor state. Our experiments on a set of breast cancer samples show that our method significantly outperforms the currently used frequency-based method in the personalized prediction of genes carrying critical mutations.
Keywords: cancer diagnosis; whole exome sequencing; deep learning; multi-modal deep Boltzmann machine

Performance of sorption- and photocatalytic oxidation-based indoor passive panel technologies - Zuraimi, M. S.; Magee, R. J.; Won, D. Y.; Nong, G.; Arsenault, C. D.; Yang, W.; So, S.; Nilsson, G.; Abebe, L.; Alliston, C. (Building and Environment, 2018)
Little information is available on the performance of commercially available indoor passive panel technologies (IPPT) based on sorptive and photocatalytic processes. In this paper, we studied 8 sorptive- and 3 photocatalytic oxidation (PCO)-based materials using controlled test chamber experiments. Four reference samples were used as controls. Sorptive-based samples were challenged with toluene and formaldehyde at 100 μg/m3 to determine their removal rates. PCO-based samples were challenged with only toluene at 100 μg/m3 to determine its removal rate and ozone and carbonyl by-product formations. Removal performance variations were wide across all IPPT samples although for every IPPT sample, its removal rate was better than its conventional counterpart. Most sorptive-based IPPT samples were not equally effective in removing toluene and formaldehyde. Painting on IPPT gypsum boards reduced their removal performance down to levels comparable to those of conventional gypsum boards. Toluene removal using PCO-based IPPTs were dependent on light used: only two PCO IPPTs are capable of performing under visible light. All PCO-based IPPTs generate ozone and carbonyls as by-products releasing up to 1.0 mg/h and 3.2 mg/h of ozone and formaldehyde respectively. This is a concern as exposures to ozone and formaldehyde have been known to be associated with negative health outcomes.
Keywords: indoor passive panel technologies; sorption; photocatalytic oxidation; performance; IAQ; VOC

Performance evaluation of phage-displayed synthetic human single-domain antibody libraries: a retrospective analysis - Henry, Kevin A.; Tanha, Jamshid (Journal of Immunological Methods, 2018)
Fully human synthetic single-domain antibodies (sdAbs) are desirable therapeutic molecules but their development is a considerable challenge. Here, using a retrospective analysis of in-house historical data, we examined the parameters that impact the outcome of screening phage-displayed synthetic human sdAb libraries to discover antigen-specific binders. We found no evidence for a differential effect of domain type (VH or VL), library randomization strategy, incorporation of a stabilizing disulfide linkage or sdAb display format (monovalent vs. multivalent) on the probability of obtaining any antigen-binding human sdAbs, instead finding that the success of library screens was primarily related to properties of target antigens, especially molecular mass. The solubility and binding affinity of sdAbs isolated from successful screens depended both on properties of the sdAb libraries (primarily domain type) and the target antigens. Taking attrition of sdAbs with major manufacturability concerns (aggregation; low expression) and sdAbs that do not recognize native cell-surface antigens as independent probabilities, we calculate the overall likelihood of obtaining ≥1 antigen-binding human sdAb from a single library-target screen as ~24%. Successful library-target screens should be expected to yield ~1.3 human sdAbs on average, each with average binding affinity of ~2 μM.

Parametric analysis of thin multifunctional elastomeric optical sheets - Nicholson-Smith, Chloë; Knopf, George K.; Bordatchev, Evgueni (Advanced Optical Technologies, 2018)
Flexible optical sheets are thin large-area polymer light guide structures that can be used to create innovative passive light-harvesting and illumination systems. The optically transparent micro-patterned polymer sheet is designed to be draped over arbitrary surfaces or hung like a curtain. The light guidance sheet is fabricated by bonding two or more micro-patterned layers with different indices of optical refraction. By imprinting micro-optical elements on the constituent layers, it is possible to have portions of the optical sheet act as a light concentrator, near ‘lossless’ transmitter, or diffuser. However, the performance and efficiency of the flexible optical sheet depends on the overall curvature (κ) of the optical sheet and the relative orientation of incident light source. To illustrate this concept, the impact of key design parameters on the controlled guidance of light through a two-layer polydimethylsiloxane (PDMS) concentrator-transmitter-diffuser optical sheet is investigated using ray tracing simulation software. The analysis initially considers a flat (κ=0) PDMS optical sheet exposed to a collimated light source. The impact of sheet curvature (κ>0) on both system efficiency and illumination uniformity is then briefly explored. Critical design guidelines for creating multifunctional monolithic optical sheets are also summarized.

PALFA discovery of a highly relativistic double neutron star binary - Stovall, K.; Freire, P. C. C.; Chatterjee, S.; Demorest, P. B.; Lorimer, D. R.; Mclaughlin, M. A.; Pol, N.; Van Leeuwen, J.; Wharton, R. S.; Allen, B.; Boyce, M.; Brazier, A.; et al. (The Astrophysical Journal, 2018)
We report the discovery and initial follow-up of a double neutron star (DNS) system, PSR J1946+2052, with the Arecibo L-Band Feed Array pulsar (PALFA) survey. PSR J1946+2052 is a 17 ms pulsar in a 1.88 hr, eccentric (e = 0.06) orbit with a gsim1.2 M ⊙ companion. We have used the Jansky Very Large Array to localize PSR J1946+2052 to a precision of 0farcs09 using a new phase binning mode. We have searched multiwavelength catalogs for coincident sources but did not find any counterparts. The improved position enabled a measurement of the spin period derivative of the pulsar (P=9 +- 2 x10 ^(-19)); the small inferred magnetic field strength at the surface (B S = 4 × 109 G) indicates that this pulsar has been recycled. This and the orbital eccentricity lead to the conclusion that PSR J1946+2052 is in a DNS system. Among all known radio pulsars in DNS systems, PSR J1946+2052 has the shortest orbital period and the shortest estimated merger timescale, 46 Myr; at that time it will display the largest spin effects on gravitational-wave waveforms of any such system discovered to date. We have measured the advance of periastron passage for this system, omega = 25.6 +- 0.3 deg yr^(-1), implying a total system mass of only 2.50 ± 0.04 M ⊙, so it is among the lowest-mass DNS systems. This total mass measurement combined with the minimum companion mass constrains the pulsar mass to lesssim1.3 M ⊙.

OSSOS. VIII. The transition between two size distribution slopes in the scattering disk - Lawler, S. M.; Shankman, C.; Kavelaars, J. J.; Alexandersen, M.; Bannister, M. T.; Chen, Ying-Tung; Gladman, B.; Fraser, W. C.; Gwyn, S.; Kaib, N.; Petit, J.-M.; Volk, K. (The Astronomical Journal, 2018)
The scattering trans-Neptunian Objects (TNOs) can be measured to smaller sizes than any other distant small-body population. We use the largest sample yet obtained, 68 discoveries, primarily by the Outer Solar System Origins Survey (OSSOS), to constrain the slope of its luminosity distribution, with sensitivity to much fainter absolute H-magnitudes than previous work. Using the analysis technique in Shankman et al., we confirm that a single slope for the H-distribution is not an accurate representation of the scattering TNOs and Centaurs, and that a break in the distribution is required, in support of previous conclusions. A bright-end slope of α b = 0.9 transitioning to a faint-end slope α f of 0.4–0.5 with a differential number contrast c from 1 (a knee) to 10 (a divot) provides an acceptable match to our data. We find that break magnitudes H b of 7.7 and 8.3, values both previously suggested for dynamically hot Kuiper Belt populations, are equally non-rejectable for a range of α f and c in our statistical analysis. Our preferred divot H-distribution transitions to α f = 0.5 with a divot of contrast c = 3 at H b = 8.3, while our preferred knee H-distribution transitions to α f = 0.4 at H b = 7.7. The intrinsic population of scattering TNOs required to match the OSSOS detections is 3 × 106 for H r < 12, and 9 × 104 for H r < 8.66 (D gsim 100 km), with Centaurs having an intrinsic population two orders of magnitude smaller.

OSSOS. VII. 800+ trans-neptunian objects: the complete data release - Bannister, Michele T.; Gladman, Brett J.; Kavelaars, J. J.; Petit, Jean-Marc; Volk, Kathryn; Chen, Ying-Tung; Alexandersen, Mike; Gwyn, Stephen D. J.; Schwamb, Megan E.; Ashton, Edward; Benecchi, Susan D.; Cabral, Nahuel; et al. (The Astrophysical Journal Supplement Series, 2018)
The Outer Solar System Origins Survey (OSSOS), a wide-field imaging program in 2013–2017 with the Canada–France–Hawaii Telescope, surveyed 155 deg2 of sky to depths of m r = 24.1–25.2. We present 838 outer solar system discoveries that are entirely free of ephemeris bias. This increases the inventory of trans-Neptunian objects (TNOs) with accurately known orbits by nearly 50%. Each minor planet has 20–60 Gaia/Pan-STARRS-calibrated astrometric measurements made over 2–5 oppositions, which allows accurate classification of their orbits within the trans-Neptunian dynamical populations. The populations orbiting in mean-motion resonance with Neptune are key to understanding Neptune's early migration. Our 313 resonant TNOs, including 132 plutinos, triple the available characterized sample and include new occupancy of distant resonances out to semimajor axis a ~ 130 au. OSSOS doubles the known population of the nonresonant Kuiper Belt, providing 436 TNOs in this region, all with exceptionally high-quality orbits of a uncertainty σ a ≤ 0.1%; they show that the belt exists from a gsim 37 au, with a lower perihelion bound of 35 au. We confirm the presence of a concentrated low-inclination a sime 44 au "kernel" population and a dynamically cold population extending beyond the 2:1 resonance. We finely quantify the survey's observational biases. Our survey simulator provides a straightforward way to impose these biases on models of the trans-Neptunian orbit distributions, allowing statistical comparison to the discoveries. The OSSOS TNOs, unprecedented in their orbital precision for the size of the sample, are ideal for testing concepts of the history of giant planet migration in the solar system.

OSSOS. IX. Two objects in Neptune's 9:1 resonance: implications for resonance sticking in the scattering population - Volk, Kathryn; Murray-Clay, Ruth A.; Gladman, Brett J.; Lawler, Samantha M.; Yu, Tze yeung Mathew; Alexandersen, Mike; Bannister, Michele T.; Chen, Ying-Tung; Dawson, Rebekah I.; Greenstreet, Sarah; Gwyn, Stephen D. J.; Kavelaars, J. J.; et al. (The Astronomical Journal, 2018)
We discuss the detection in the Outer Solar System Origins Survey (OSSOS) of two objects in Neptune's distant 9:1 mean motion resonance at semimajor axis a ≈ 130 au. Both objects are securely resonant on 10 Myr timescales, with one securely in the 9:1 resonance's leading asymmetric libration island and the other in either the symmetric or trailing asymmetric island. These objects are the largest semimajor axis objects with secure resonant classifications, and their detection in a carefully characterized survey allows for the first robust resonance population estimate beyond 100 au. The detection of these objects implies a 9:1 resonance population of 1.1 × 104 objects with H r < 8.66 (D gsim 100 km) on similar orbits (95% confidence range of ~(0.4–3) × 104). Integrations over 4 Gyr of an ensemble of clones spanning these objects' orbit-fit uncertainties reveal that they both have median resonance occupation timescales of ~1 Gyr. These timescales are consistent with the hypothesis that these objects originate in the scattering population but became transiently stuck to Neptune's 9:1 resonance within the last ~1 Gyr of solar system evolution. Based on simulations of a model of the current scattering population, we estimate the expected resonance sticking population in the 9:1 resonance to be 1000–4500 objects with H r < 8.66; this is marginally consistent with the OSSOS 9:1 population estimate. We conclude that resonance sticking is a plausible explanation for the observed 9:1 population, but we also discuss the possibility of a primordial 9:1 population, which would have interesting implications for the Kuiper Belt's dynamical history.

Orbital control of photocurrents in large area all-carbon molecular junctions - Morteza najarian, Amin; Bayat, Akhtar; Mccreery, Richard L. (Journal of the American Chemical Society, 2018)
Photocurrents generated by illumination of carbon-based molecular junctions were investigated as diagnostics of how molecular structure and orbital energies control electronic behavior. Oligomers of eight aromatic molecules covalently bonded to an electron-beam deposited carbon surface were formed by electrochemical reduction of diazonium reagents, with layer thicknesses in the range of 5–12 nm. Illumination through either the top or bottom partially transparent electrodes produced both an open circuit potential (OCP) and a photocurrent (PC), and the polarity and spectrum of the photocurrent depended directly on the relative positions of the frontier orbitals and the electrode Fermi level (EF). Electron donors with relatively high HOMO energies yielded positive OCP and PC, and electron acceptors with LUMO energies closer to EF than the HOMO energy produced negative OCP and PC. In all cases, the PC spectrum and the absorption spectrum of the oligomer in the molecular junction had very similar shapes and wavelength maxima. Asymmetry of electronic coupling at the top and bottom electrodes due to differences in bonding and contact area cause an internal potential gradient which controls PC and OCP polarities. The results provide a direct indication of which orbital energies are closest to EF and also indicate that transport in molecular junctions thicker than 5 nm is controlled by the difference in energy of the HOMO and LUMO orbitals.

Automated testing of optical fibres: towards the design of the Maunakea Spectroscopic Explorer Fibre Transmission System - Monty, Stephanie; Jahandar, Farbod; Lee, Jooyoung; Venn, Kim A.; Bradley, Colin; Erickson, Darren; Crampton, David; Nicolov, Victor; Kielty, Collin L.; Mazoukh, Celine; Hall, Patrick; Takami, Hideki; et al. (Ground-based and Airborne Instrumentation for Astronomy VII, 2018)
We present the results of an automated fibre optic test bench constructed at the University of Victoria as part of the Maunakea Spectroscopic Explorer (MSE) Fibre Transmission System (FiTS). In preparation for MSE-FiTS, we have begun characterizing the focal ratio degradation (FRD) of candidate multi-mode fibres with the ultimate goal of testing all 4000 MSE fibres. To achieve this, we have built an optical bench to perform an automated version of the collimated beam test. Herein we present the design of the bench and discuss the automation of components by introducing the Big FiTS Fibre Wrapper (Big FFW), our open-source automation software. We conclude with the results of tests performed using the Big FFW on a sample of candidate fibre, comparing the Big FFW results against those found using manual methods. Our results suggest that the candidate MSE fibre meets the science requirement of < 5% FRD at f /2 and find less than 1% disagreement between both measurement methods.

Subwavelength-grating metamaterial structures for silicon photonic devices - Halir, Robert; Ortega-Moñux, Alejandro; Benedikovic, Daniel; Mashanovich, Goran Z.; Wangüemert-Pérez, J. Gonzalo; Schmid, Jens H.; Molina-Fernández, Íñigo; Cheben, Pavel (Proceedings of the IEEE, 2018)
Segmenting silicon waveguides at the subwavelength scale produce an equivalent homogenous material. The geometry of the waveguide segments provides precise control over modal confinement, effective index, dispersion and birefringence, thereby opening up new approaches to design devices with unprecedented performance. Indeed, with ever-improving lithographic technologies offering sub-100-nm patterning resolution in the silicon photonics platform, many practical devices based on subwavelength structures have been demonstrated in recent years. Subwavelength engineering has thus become an integral design tool in silicon photonics, and both fundamental understanding and novel applications are advancing rapidly. Here, we provide a comprehensive review of the state of the art in this field. We first cover the basics of subwavelength structures, and discuss substrate leakage, fabrication jitter, reduced backscatter, and engineering of material anisotropy. We then review recent applications including broadband waveguide couplers, high-sensitivity evanescent field sensors, low-loss devices for mid-infrared photonics, polarization management structures, spectral filters, and highly efficient fiber-to-chip couplers. We finally discuss the future prospects for subwavelength silicon structures and their impact on advanced device design.
Keywords: Fiber-to-chip coupler; filter; metamaterial; midinfrared; near-infrared; polarization; silicon photonics; sensor; subwavelength grating; waveguide; waveguide coupler

On-chip continuously tunable optical delay line based on cascaded Mach-Zehnder interferometers - Melati, Daniele; Melloni, Andrea (2018 Optical Fiber Communications Conference and Exposition (OFC), 2018)
We propose a novel integrated optical delay line based on cascaded Mach-Zehnder interferometers. It allows a continuous delay tuning, can achieve wideband operation and is experimentally demonstrated with a delay up to 125 ps.

On the learning curve attrition bias in additive factor modeling - Goutte, Cyril; Durand, Guillaume; Léger, Serge (Artificial Intelligence in Education, 2018)
Learning curves are a crucial tool to accurately measure learners skills and give meaningful feedback in intelligent tutoring systems. Here we discuss various ways of building learning curves from empirical data for the Additive Factor model (AFM) and highlight their limitations. We focus on the impact of student attrition, a.k.a. attrition bias. We propose a new way to build learning curves, by combining empirical observations and AFM predictions. We validate this proposition on simulated data, and test it on real datasets.
Keywords: learning curves; attrition bias; additive factor model

Observation of FeGe skyrmions by electron phase microscopy with hole-free phase plate - Kotani, Atsuhiro; Harada, Ken; Malac, Marek; Salomons, Mark; Hayashida, Misa; Mori, Shigeo (AIP Advances, 2018)
We report application of hole-free phase plate (HFPP) to imaging of magnetic skyrmion lattices. Using HFPP imaging, we observed skyrmions in FeGe, and succeeded in obtaining phase contrast images that reflect the sample magnetization distribution. According to the Aharonov-Bohm effect, the electron phase is shifted by the magnetic flux due to sample magnetization. The differential processing of the intensity in a HFPP image allows us to successfully reconstruct the magnetization map of the skyrmion lattice. Furthermore, the calculated phase shift due to the magnetization of the thin film was consistent with that measured by electron holography experiment, which demonstrates that HFPP imaging can be utilized for analysis of magnetic fields and electrostatic potential distribution at the nanoscale.

Niche separation increases with genetic distance among bloom-forming cyanobacteria - Tromas, Nicolas; Taranu, Zofia E.; Martin, Bryan D.; Willis, Amy; Fortin, Nathalie; Greer, Charles W.; Shapiro, B. Jesse (Frontiers in Microbiology, 2018)
Bacterial communities are composed of distinct groups of potentially interacting lineages, each thought to occupy a distinct ecological niche. It remains unclear, however, how quickly niche preference evolves and whether more closely related lineages are more likely to share ecological niches. We addressed these questions by following the dynamics of two bloom-forming cyanobacterial genera over an 8-year time-course in Lake Champlain, Canada, using 16S amplicon sequencing and measurements of several environmental parameters. The two genera, Microcystis (M) and Dolichospermum (D), are frequently observed simultaneously during bloom events and thus have partially overlapping niches. However, the extent of their niche overlap is debated, and it is also unclear to what extent niche partitioning occurs among strains within each genus. To identify strains within each genus, we applied minimum entropy decomposition (MED) to 16S rRNA gene sequences. We confirmed that at a genus level, M and D have different preferences for nitrogen and phosphorus concentrations. Within each genus, we also identified strains differentially associated with temperature, precipitation, and concentrations of nutrients and toxins. In general, niche similarity between strains (as measured by co-occurrence over time) declined with genetic distance. This pattern is consistent with habitat filtering – in which closely related taxa are ecologically similar, and therefore tend to co-occur under similar environmental conditions. In contrast with this general pattern, similarity in certain niche dimensions (notably particulate nitrogen and phosphorus) did not decline linearly with genetic distance, and instead showed a complex polynomial relationship. This observation suggests the importance of processes other than habitat filtering – such as competition between closely related taxa, or convergent trait evolution in distantly related taxa – in shaping particular traits in microbial communities.

New insights about ice friction obtained from crushing-friction tests on smooth and high-roughness surfaces - Gagnon, Robert E. (International Journal of Naval Architecture and Ocean Engineering, 2018)
Ice crushing occurs in many situations that involve a sliding frictional component such as sports involving ice-contact, ice interaction with ship hulls, and ice-on-ice sliding/crushing within glaciers and between interacting sea ice floes. Ice crushing-friction tests were conducted in the lab at −10 °C using a set of acrylic ice-crushing platens that included a flat smooth surface and a variety of high-roughness surfaces with regular arrays of small prominences. The experiments were part of Phase II tests of the Blade Runners technology for reducing ice-induced vibration. Ice was crushed against the platens where the ice movement had both a vertical and a horizontal component. High-speed imaging through the platens was used to observe the ice contact zone as it evolved during the tests. Vertical crushing rates were in the range 10–30 mm/s and the horizontal sliding rates were in the range 4.14–30 mm/s. Three types of freshwater ice were used. Friction coefficients were extraordinarily low and were proportional to the ratio of the tangential sliding rate and the normal crushing rate. For the rough surfaces all of the friction coefficient variation was determined by the fluid dynamics of a slurry that flowed through channels that developed between leeward-facing facets of the prominences and the moving ice. The slurry originated from a highly-lubricating self-generating squeeze film of ice particles and melt located between the encroaching intact ice and the surfaces.
Keywords: ice crushing-friction; highly-lubricating ice-melt slurry; solid–solid fluid interface friction mechanism; surprising low friction on rough surfaces

Near-field imaging for single-shot waveform measurements - Hammond, T. J.; Korobenko, Aleksey; Naumov, A. Yu; Villeneuve, D. M.; Corkum, Paul B.; Ko, Dong Hyuk (Journal of Physics B: Atomic, Molecular and Optical Physics, 2018)
The accurate measurement of ultrashort pulses is necessary to optimize pulse compression for nonlinear optics and strong-field physics. Additionally, field-sensitive time-domain techniques enable measuring femtosecond and sub-femtosecond dynamics. In this paper, we introduce a single-shot measurement to characterize few-cycle fields. This polarization-sensitive time-domain measurement can retrieve the waveform of pulses shorter than two-cycles in duration with a temporal window of hundreds of femtoseconds. We measure how the field changes after propagation through dispersive optics, and we measure the sub-femtosecond phase shift imposed by the nonlinear intensity dependent response of a dielectric. Real-time field measurements will benefit low repetition rate systems used in strong-field physics and attosecond science, while the large temporal window compliments Fourier transform spectroscopy.

Motion compensation for phase-shift structured-light systems based on a total-variation framework - Boisvert, Jonathan; Drouin, Marc-Antoine; Dicaire, Louis-Guy; Picard, Michel; Godin, Guy (2017 International Conference on 3D Vision (3DV), 2018)
Phase-shift profilometry (PSP) is a technique for acquiring non-contact three-dimensional measurements using a projector and a camera. The technique can be used to measure 3D surfaces with high accuracy. However, it can be sensitive to motion because phase images are sequentially captured. We propose a new technique that uses residual phase errors to minimize the influence of motion on the recovered phases (and 3D points). The method minimizes residual phase error with respect to apparent phase offset variations caused by motion. Furthermore, a total variation scheme is used to minimize spatial variations of apparent phase offset variations. We demonstrate the method with different moving objects, and we also study the effect of the magnitude of the motion on the accuracy of the recovered phases. Visual artefacts as well as accuracy loss associated with motion are found to be significantly decreased.
Keywords: motion-Compensation; phase-shift-profilometry; structured-light; 3D-imaging

Modelling and analysis of unsolicited temperature setpoint change requests in office buildings - Gunay, H. Burak; Shen, Weiming; Newsham, Guy; Ashouri, Araz (Building and Environment, 2018)
This paper presents an analysis conducted upon custom temperature setpoint change request data collected from four large office buildings. In three of these buildings, the setpoint changes were executed upon hot and cold complaints; and in the fourth building, the occupants could adjust their setpoints through their thermostats. Using concurrent indoor and outdoor temperature records, multivariate logistic regression models predicting the frequency of custom setpoint change requests were developed. The indoor temperatures that minimize the frequency of thermal complaints or thermostat overrides were determined with these models. It is argued that these temperatures can be used to select building specific default seasonal temperature setpoints. The results indicate that the majority of the setpoint change requests were either to increase the default 22 °C temperature setpoints during the cooling season or to decrease them during the heating season. Custom setpoint change requests were registered 24 times more frequently when occupants were permitted to make temporary thermostat overrides. It was also identified that the operators tend to make greater setpoint changes upon hot and cold complaints than the occupants make through their thermostat overrides.
Keywords: thermal complaints; thermostat use behaviour; occupant behaviour; temperature setpoints

Model for developing trust on US construction projects - Issa, Raja R.A.; Olbina, Svetlana; Zuppa, Dino (Built Environment Project and Asset Management, 2018)
Purpose: The purpose of this paper is to identify the factors found on US construction projects that are perceived by contractors to strengthen or weaken trust between contracting stakeholders and to develop a framework for evaluating these relationships. Design/methodology/approach: A comprehensive framework containing a number of factors (54) that could impact trust on construction projects was first developed. A survey questionnaire was then developed and administered via phone to contractors selected from the Engineering News Record top 400 US construction companies. The survey findings were then used to develop a trust model and case studies were used to validate and revise the trust model. Findings: A trust model is developed that helps large US contractors measure and improve trust with other stakeholders on their projects. Practical implications: Large US contractors are now provided with a tool not previously available to help them measure and improve trust between the different contracting parties on construction projects which can help them decrease project time and costs, and improve project results. Originality/value: The proposed trust model adds a number of different dimensions to the existing trust models found in the literature and as such improves the contractor’s ability to foster and enhance trust on a US construction project.
Keywords: construction; trust; communication; project management; productivity; trust model

Methylammonium cation dynamics in methylammonium lead halide perovskites: a solid-state NMR perspective - Bernard, Guy M.; Wasylishen, Roderick E.; Ratcliffe, Christopher I.; Terskikh, Victor; Wu, Qichao; Buriak, Jillian M.; Hauger, Tate (The Journal of Physical Chemistry A, 2018)
In light of the intense recent interest in the methylammonium lead halides, CH3NH3PbX3 (X = Cl, Br, and I) as sensitizers for photovoltaic cells, the dynamics of the methylammonium (MA) cation in these perovskite salts has been reinvestigated as a function of temperature via 2H, 14N, and 207Pb NMR spectroscopy. In the cubic phase of all three salts, the MA cation undergoes pseudoisotropic tumbling (picosecond time scale). For example, the correlation time, τ2, for the C–N axis of the iodide salt is 0.85 ± 0.30 ps at 330 K. The dynamics of the MA cation are essentially continuous across the cubic ↔ tetragonal phase transition; however, 2H and 14N NMR line shapes indicate that subtle ordering of the MA cation occurs in the tetragonal phase. The temperature dependence of the cation ordering is rationalized using a six-site model, with two equivalent sites along the c-axis and four equivalent sites either perpendicular or approximately perpendicular to this axis. As the cubic ↔ tetragonal phase transition temperature is approached, the six sites are nearly equally populated. Below the tetragonal ↔ orthorhombic phase transition, 2H NMR line shapes indicate that the C–N axis is essentially frozen.

MESAS: measuring the emission of stellar atmospheres at submillimeter/millimeter wavelengths - White, Jacob Aaron; Aufdenberg, Jason; Boley, A. C.; Hauschildt, Peter; Hughes, Meredith; Matthews, Brenda; Wilner, David (The Astrophysical Journal, 2018)
In the early stages of planet formation, small dust grains grow to become millimeter-sized particles in debris disks around stars. These disks can in principle be characterized by their emission at submillimeter and millimeter wavelengths. Determining both the occurrence and abundance of debris in unresolved circumstellar disks of A-type main-sequence stars requires that the stellar photospheric emission be accurately modeled. To better constrain the photospheric emission for such systems, we present observations of Sirius A, an A-type star with no known debris, from the James Clerk Maxwell Telescope, Submillimeter Array, and Jansky Very Large Array at 0.45, 0.85, 0.88, 1.3, 6.7, and 9.0 mm. We use these observations to inform a PHOENIX model of Sirius A's atmosphere. We find the model provides a good match to these data and can be used as a template for the submillimeter/millimeter emission of other early A-type stars where unresolved debris may be present. The observations are part of an ongoing observational campaign entitled Measuring the Emission of Stellar Atmospheres at Submillimeter/millimeter wavelengths.

Mechanical anisotropy of PS/CO2 microcellular foam sheet prepared by foaming extrusion - Reignier, Joël; Gendron, Richard (Journal of Cellular Plastics, 2018)
Microcellular polystyrene foam sheets prepared by extrusion foaming with CO2 as the blowing agent were found to exhibit a significant anisotropy in mechanical behavior which could not be explained solely by the shape anisotropy of the cells and/or the preferential orientation of polystyrene molecules in the machine direction. Surprisingly, samples allowed to fully relax were still found to maintain part of their mechanical anisotropy, which was attributed to the weakness of the cell walls perpendicular to machine direction.
Keywords: microcellular foam; polystyrene; carbon dioxide; mechanical anisotropy; molecular orientation

Low-temperature and atmospheric pressure sample digestion using dielectric barrier discharge - Luo, Yijing; Yang, Yuan; Lin, Yao; Tian, Yunfei; Wu, Li; Yang, Lu; Hou, Xiandeng; Zheng, Chengbin (Analytical Chemistry, 2018)
A new sample digestion method using a double layer and coaxial dielectric barrier discharge (DBD) digestion reactor was developed for the sensitive determination of trace elements in rice samples. All the operation parameters of the DBD microplasma and other digestion conditions were carefully optimized. Three DBD-digestion modes were investigated for real matrix samples, including H2O-DBD-digestion, H2O2-DBD-digestion, and HNO3-DBD-digestion systems. Among the three modes, the H2O-DBD-digestion system provides a suitable digestion of sample without any additional chemicals, achieving environmental friendly sample treatment and eliminating the potential interferences. Under the optimized conditions, limits of detection for Mg, Mn, Zn, Cd, Cr, Co, and As were in the range of 0.01–0.35 ng g–1 by inductively coupled plasma mass spectrometry (ICPMS). The accuracy of the proposed method was checked by analysis of a certified reference material (GBW10043) and spiked samples with satisfactory results (83–113% recoveries).

Low-dimensional spaces for the analysis of sensor network data: identifying behavioural changes in a propulsion system - Cheung, Catherine; Valdes, Julio J.; Rubio, Alejandro Lehman; Chavez, Richard Salas; Bayley, Christopher (2017 IEEE International Symposium on Robotics and Intelligent Sensors (IRIS), 2018)
The amount of sensors installed for equipment health monitoring on board engines, aircraft, and vehicles has increased steadily in the digital age. Developing strategies and capabilities to extract useful information from the tremendous amounts of data collected is a separate challenge that can be used to establish the indicators of system health, a necessary precursor to the implementation of condition based maintenance, that could be explored through the use of data analytics tools and methods. In this work, initial analysis of the sensor data related to a diesel engine system and specifically its turbocharger subsystem was carried out. An incident involving seizure of the turbocharger was captured by the sensor data, and hence analysis of this event provides an opportunity to identify changes in equipment indicators with a known outcome. Several data analysis tools were used, including the transformation of the original highdimensional sensor data to a low-dimensional space. The data analysis is focused on characterizing the healthy and failed states of the turbocharger system and identifying the change in behaviour of the system during that transition.

Long-term performance of a microbial electrolysis cell operated with periodic disconnection of power supply - Hussain, S. A.; Perrier, M.; Tartakovsky, B. (RSC Advances, 2018)
This study describes a new approach for achieving stable long-term performance and maximizing the removal of chemical oxygen demand (COD) in a Microbial Electrolysis Cell (MEC). In the proposed approach, the MEC power supply is periodically disconnected, e.g. at a frequency of 0.1–0.5 Hz and a duty cycle of 90–95%. To evaluate the impact of such periodic power supply disconnection (on/off mode) on MEC performance, experiments were carried out in two flow-through MECs with activated granular carbon electrodes. The on/off operating strategy was applied to one MEC, while the other one was operated at a fixed voltage (control MEC). Long-term on/off operation resulted in progressive increase in COD removal efficiency (from 80% to 90%) and MEC current over time, while the control MEC showed stable but inferior performance. Furthermore, by changing the operating strategies and applying the on/off approach to the control MEC, its COD removal was increased from 78% to 83% and internal resistance decreased. The proposed on/off mode of operation can be used to develop a high-rate MEC-based wastewater treatment system.

Lipofection of plasmid DNA into human mast cell lines using lipid nanoparticles generated by microfluidic mixing - Duguay, Brett A.; Huang, Kate Wei-Chen; Kulka, Marianna (Journal of Leukocyte Biology, 2018)
Mast cells are important immune cells that have significant roles in mediating allergy and asthma. Therefore, studying the molecular mechanisms regulating these and other processes in mast cells is important to elucidate. Methods such as lipofection, transduction, and electroporation are often employed to dissect these mechanisms by disrupting gene expression in mast cell lines. However, as with other leukocytes, human mast cells (HMCs) are often refractory to the delivery of plasmids by lipofection. In this study, we investigated the utility of lipid nanoparticles (LNPs) containing the ionizable cationic lipids 1,2‐dioleoyloxy‐3‐dimethylaminopropane, 1,2‐dioleyloxy‐3‐dimethylaminopropane, or 2,2‐dilinoleyl‐4‐(2‐dimethylaminoethyl)‐[1,3]‐dioxolane for the delivery of plasmid DNA into HMC lines. Herein, we demonstrate for the first time the use of LNPs to achieve significant and reproducible levels of plasmid DNA transfection in HMC‐1.2 and laboratory of allergic diseases 2 (LAD2) cells. These levels reached 53.2% and 16.0% in HMC‐1.2 and LAD2 cells, respectively; and outperformed Lipofectamine 3000 in both cases. Moreover, cell viability in the transfected cells remained above 65% for all LNP conditions tested. Together, these observations illustrate the efficacy of this technique for mast cell researchers and further support the use of LNPs for nucleic acid delivery into leukocytes.

Lighting controls: evolution and revolution - Pandharipande, A; Newsham, G. R. (Lighting Research & Technology, 2018)
The basic function of a lighting system is to provide a defined amount of light to a space according to context-appropriate design criteria while minimising energy use. Lighting control strategies based on occupancy and daylight adaptation have been consistently shown to substantially lower lighting energy use compared to fixed systems, and are now ubiquitous in building energy codes. The adoption of light emitting diodes and the integration of information and communication technologies enable lighting control systems to become smarter with a greater integration of sensing, data processing and connectivity, and to evolve into a platform for both lighting and non-lighting applications. We describe different lighting control strategies and their evolution with a focus on commercial office applications. To illustrate emerging approaches, we then discuss two particular smart lighting systems – a wireless, distributed lighting control system and a power-over-Ethernet, centralised lighting control system, with cloud connectivity. The role that a connected lighting system can play in the overall building eco-system is then discussed, and new applications and services that are enabled are presented. Finally, we discuss the challenges to the market adoption of connected smart lighting systems, and the arising opportunities for researchers and practitioners to realise one more round of high-value returns offered by lighting systems.

Light amplification by seeded Kerr instability - Vampa, G.; Hammond, T. J.; Nesrallah, M.; Naumov, A. Yu.; Corkum, P. B.; Brabec, T. (Science, 2018)
Amplification of femtosecond laser pulses typically requires a lasing medium or a nonlinear crystal. In either case, the chemical properties of the lasing medium or the momentum conservation in the nonlinear crystal constrain the frequency and the bandwidth of the amplified pulses. We demonstrate high gain amplification (greater than 1000) of widely tunable (0.5 to 2.2 micrometers) and short (less than 60 femtosecond) laser pulses, up to intensities of 1 terawatt per square centimeter, by seeding the modulation instability in an Y3Al5O12 crystal pumped by femtosecond near-infrared pulses. Our method avoids constraints related to doping and phase matching and therefore can occur in a wider pool of glasses and crystals even at far-infrared frequencies and for single-cycle pulses. Such amplified pulses are ideal to study strong-field processes in solids and highly excited states in gases.

Large magnetoresistance by Pauli blockade in hydrogenated graphene - Guillemette, J.; Hemsworth, N.; Vlasov, A.; Kirman, J.; Mahvash, F.; Lévesque, P. L.; Siaj, M.; Martel, R.; Gervais, G.; Studenikin, S.; Sachrajda, A.; Szkopek, T. (Physical Review B, 2018)
We report the observation of a giant positive magnetoresistance in millimeter-scale hydrogenated graphene with the magnetic field oriented in the plane of the graphene sheet. A positive magnetoresistance in excess of 200% at a temperature of 300 mK was observed in this configuration, reverting to negative magnetoresistance with the magnetic field oriented normal to the graphene plane. We attribute the observed positive in-plane magnetoresistance to a Pauli blockade of hopping conduction induced by spin polarization. Our Rapid Communication shows that spin polarization in concert with electron-electron interaction can play a dominant role in magnetotransport within an atomic monolayer.

Large built-in fields control the electronic properties of nanoscale molecular devices with dipolar structures - Van Dyck, Colin; Bergren, Adam J. (Advanced Electronic Materials, 2018)
Large area molecular junctions are nanoscale materials made of a molecular layer sandwiched between two metal electrodes. In this study, a fundamental property of these systems is demonstrated: the emergence of a large built‐in field, typically as high as 109 V m−1, and susceptible to appear in any junction possessing an asymmetry. This field originates from permanent dipoles in the contacted molecular layer and is responsible for a large renormalization of the band alignment in the junction. To illustrate this effect, a predictive theoretical characterization of two realistic gold‐thiolate‐based organic layers is carried out. The parameters leading to the emergence of the built‐in field are given and the very large renormalization effect is interpreted in terms of an applied voltage drop. Despite a high significance, this generic feature of molecular junctions has widely been neglected hitherto in the design and interpretation of molecular device characteristics. Built‐in fields provide a powerful way to achieve structure–property relationships in molecular junctions, by taking advantage of dipolar nanometric building blocks.

Landau-Zener-Stückelberg-Majorana interferometry of a single hole - Bogan, Alex; Studenikin, Sergei; Korkusinski, Marek; Gaudreau, Louis; Zawadzki, Piotr; Sachrajda, Andy S.; Tracy, Lisa; Reno, John; Hargett, Terry (Physical Review Letters, 2018)
We perform Landau-Zener-Stückelberg-Majorana (LZSM) spectroscopy on a system with strong spin-orbit interaction (SOI), realized as a single hole confined in a gated double quantum dot. Analogous to electron systems, at a magnetic field B=0 and high modulation frequencies, we observe photon-assisted tunneling between dots, which smoothly evolves into the typical LZSM funnel-shaped interference pattern as the frequency is decreased. In contrast to electrons, the SOI enables an additional, efficient spin-flip interdot tunneling channel, introducing a distinct interference pattern at finite B. Magnetotransport spectra at low-frequency LZSM driving show the two channels to be equally coherent. High-frequency LZSM driving reveals complex photon-assisted tunneling pathways, both spin conserving and spin flip, which form closed loops at critical magnetic fields. In one such loop, an arbitrary hole spin state is inverted, opening the way toward its all-electrical manipulation.

Lack of functional selectin-ligand interactions enhances innate immune resistance to systemic Listeria monocytogenes infection - Agbayani, Gerard; Gurnani, Komal; Zafer, Ahmed; Sad, Subash; Krishnan, Lakshmi (Journal of Leukocyte Biology, 2018)
Selectin‐ligand interactions are important for leukocyte homing and functionality. The roles of selectin‐ligand interactions in modulating immunity to intracellular infections are not completely understood. Mice lacking the expression of fucosyltransferase‐IV and ‐VII (Fucosyltransferase‐IV and ‐VII double knockout, FtDKO) exhibit deficient functionality of selectin‐ligand interactions. We addressed the kinetics of infection and immunity to Listeria monocytogenes (LM), an intracellular pathogen, in FtDKO mice. These mice exhibited enhanced ability to clear infection and increased survival to a lethal dose of LM infection relative to wild‐type (WT) C57BL/6J controls. This was associated with increased levels of neutrophils, monocytes, and dendritic cells (DCs) in the blood and/or infected organs. Adoptive transfer of bone marrow (BM) cells from FtDKO mice to WT mice resulted in enhanced neutrophil numbers and improved clearance of LM bacteria in recipients. In vivo depletion of myeloid innate immune cells, particularly neutrophils, monocytes, macrophages, and DCs, using anti‐Ly‐6G (RB6‐8C5) monoclonal antibody, reduced the ability of FtDKO mice to curtail LM infection. Nevertheless, depletion using anti‐Ly‐6G (1A8) known to exclusively deplete neutrophils did not abrogate increased resistance of FtDKO mice to LM infection, suggesting a role for other myeloid innate immune cells in this model. Examination of BM hematopoietic progenitors through flow cytometry and cell culture colony‐forming unit assay showed increased frequencies of granulocyte‐macrophage progenitors in FtDKO relative to WT mice, Overall, our results indicate that functional selectin ligand deficiency enhances innate immune‐mediated resistance to systemic LM infection despite defective leukocyte migration and lymphocyte homing.

Kuiper belt analogues in nearby M-type planet-host systems - Kennedy, G. M.; Bryden, G.; Ardila, D.; Eiroa, C.; Lestrade, J.-F.; Marshall, J. P.; Matthews, B. C.; Moro-Martin, A.; Wyatt, M. C. (Monthly Notices of the Royal Astronomical Society, 2018)
We present the results of a Herschel survey of 21 late-type stars that host planets discovered by the radial velocity technique. The aims were to discover new discs in these systems and to search for any correlation between planet presence and disc properties. In addition to the known disc around GJ 581, we report the discovery of two new discs, in the GJ 433 and GJ 649 systems. Our sample therefore yields a disc detection rate of 14 per cent, higher than the detection rate of 1.2 per cent among our control sample of DEBRIS M-type stars with 98 per cent confidence. Further analysis however shows that the disc sensitivity in the control sample is about a factor of two lower in fractional luminosity than for our survey, lowering the significance of any correlation between planet presence and disc brightness below 98 per cent. In terms of their specific architectures, the disc around GJ 433 lies at a radius somewhere between 1 and 30 au. The disc around GJ 649 lies somewhere between 6 and 30 au, but is marginally resolved and appears more consistent with an edge-on inclination. In both cases the discs probably lie well beyond where the known planets reside (0.06–1.1 au), but the lack of radial velocity sensitivity at larger separations allows for unseen Saturn–mass planets to orbit out to ∼5 au, and more massive planets beyond 5 au. The layout of these M-type systems appears similar to Sun-like star + disc systems with low-mass planets.
Keywords: circumstellar matter; stars: individual: GJ 433; stars: individual: GJ 649

Kalman filter approach for uncertainty quantification in time-resolved laser-induced incandescence - Hadwin, Paul J.; Sipkens, Timothy A.; Thomson, Kevin A.; Liu, Fengshan; Daun, Kyle J. (Journal of the Optical Society of America A, 2018)
Time-resolved laser-induced incandescence (TiRe-LII) data can be used to infer spatially and temporally resolved volume fractions and primary particle size distributions of soot-laden aerosols, but these estimates are corrupted by measurement noise as well as uncertainties in the spectroscopic and heat transfer submodels used to interpret the data. Estimates of the temperature, concentration, and size distribution of soot primary particles within a sample aerosol are typically made by nonlinear regression of modeled spectral incandescence decay, or effective temperature decay, to experimental data. In this work, we employ nonstationary Bayesian estimation techniques to infer aerosol properties from simulated and experimental LII signals, specifically the extended Kalman filter and Schmidt–Kalman filter. These techniques exploit the time-varying nature of both the measurements and the models, and they reveal how uncertainty in the estimates computed from TiRe-LII data evolves over time. Both techniques perform better when compared with standard deterministic estimates; however, we demonstrate that the Schmidt–Kalman filter produces more realistic uncertainty estimates.

Dynamic model of a municipal wastewater stabilization pond in the arctic - Recio-Garrido, Didac; Kleiner, Yehuda; Colombo, Andrew; Tartakovsky, Boris (Water Research, 2018)
Waste stabilisation ponds (WSPs) are the method of choice for sewage treatment in most arctic communities because they can operate in extreme climate conditions, require a relatively modest investment, are passive and therefore easy and inexpensive to operate and maintain. However, most arctic WSPs are currently limited in their ability to remove carbonaceous biochemical oxygen demand (CBOD), total suspended solids (TSS) and ammonia-nitrogen. An arctic WSP differs from a ‘southern’ WSP in the way it is operated and in the conditions under which it operates. Consequently, existing WSP models cannot be used to gain better understanding of the arctic lagoon performance. This work describes an Arctic-specific WSP model. It accounts for both aerobic and anaerobic degradation pathways of organic materials and considers the periodic nature of WSP operation as well as the partial or complete freeze of the water in the WSP during winter. A uniform, multi-layer (ice, aerobic, anaerobic and sludge) approach was taken in the model development, which simplified and expedited numerical solution of the model, enabling efficient model calibration to available field data.
Keywords: arctic; facultative lagoon; WSP; dynamic model; icecap

Ion-ion dynamic structure factor, acoustic modes, and equation of state of two-temperature warm dense aluminum - Harbour, L.; Förster, G. D.; Dharma-Wardana, M. W. C.; Lewis, Laurent J. (Physical Review E, 2018)
The ion-ion dynamical structure factor and the equation of state of warm dense aluminum in a two-temperature quasiequilibrium state, with the electron temperature higher than the ion temperature, are investigated using molecular-dynamics simulations based on ion-ion pair potentials constructed from a neutral pseudoatom model. Such pair potentials based on density functional theory are parameter-free and depend directly on the electron temperature and indirectly on the ion temperature, enabling efficient computation of two-temperature properties. Comparison with ab initio simulations and with other average-atom calculations for equilibrium aluminum shows good agreement, justifying a study of quasiequilibrium situations. Analyzing the van Hove function, we find that ion-ion correlations vanish in a time significantly smaller than the electron-ion relaxation time so that dynamical properties have a physical meaning for the quasiequilibrium state. A significant increase in the speed of sound is predicted from the modification of the dispersion relation of the ion acoustic mode as the electron temperature is increased. The two-temperature equation of state including the free energy, internal energy, and pressure is also presented.

Investigation of converging and collimated beam instrument geometry on specular gloss measurements - Zwinkels, Joanne C.; Côté, Éric; Morgan, John (Journal of Physics: Conference Series, 2018)
Specular gloss is an important appearance property of a wide variety of manufactured goods. Depending upon the application, e.g. paints, paper, ceramics, etc. different instrument designs and measurement geometries are specified in standard test methods. For a given specular angle, these instrument designs can be broadly classified as converging beam (TAPPI method) and collimated beam (DIN method). In recent comparisons of specular gloss measurements using different glossmeters, very large standard deviations have been reported, well exceeding the manufacturers claims. In this paper, we investigate the effect of instrument beam geometry on gloss measurements. These results indicate that this difference in beam geometry can give the magnitude of gloss differences reported in these comparisons and highlights the importance of educating the user community of best measurement practices and obtaining appropriate traceability for their glossmeters.

Interpreting the ultraviolet absorption in the spectrum of 415 nm-bandgap CdSe magic-size clusters - Zhu, Dikai; Hui, Juan; Rowell, Nelson; Liu, Yuanyuan; Chen, Queena Y.; Steegemans, Tristan; Fan, Hongsong; Zhang, Meng; Yu, Kui (The Journal of Physical Chemistry Letters, 2018)
Colloidal semiconductor magic-size clusters (MSCs), a crucial link between molecular and bulk materials, have attracted attention in the past three decades. However, the identification of their nonbandgap electronic transitions via optical absorption has been challenging due to the possible presence of other-bandgap ensembles in synthetic batches. For CdSe MSC-415, referred to as the optical absorption (1S(e)–1S3/2(h)) in nanometers of wavelength, we report our exploration on the origin of two commonly documented absorption peaks at 381 and 351 nm. We show that the evolution of the two peaks does not synchronize with that of the ∼415 nm peak and seems to be respectively related to the disappearance of MSC-391 and MSC-361. Accordingly, these two peaks detected are probably not due to higher order electronic transitions in MSC-415. The present study shows the necessity of re-evaluating previous experimental results and of developing advanced theoretical models to better understand the quantized energy levels of MSCs.

Interpreting and propagating the uncertainty of the standard atomic weights (IUPAC Technical Report) - Possolo, Antonio; Van Der Veen, Adriaan M. H.; Meija, Juris; Hibbert, D. Brynn (Pure and Applied Chemistry, 2018)
In 2009, the Commission on Isotopic Abundances and Atomic Weights (CIAAW) of the International Union of Pure and Applied Chemistry (IUPAC) introduced the interval notation to express the standard atomic weights of elements whose isotopic composition varies significantly in nature. However, it has become apparent that additional guidance would be helpful on how representative values should be derived from these intervals, and on how the associated uncertainty should be characterized and propagated to cognate quantities, such as relative molecular masses. The assignment of suitable probability distributions to the atomic weight intervals is consistent with the CIAAW’s goal of emphasizing the variability of the atomic weight values in nature. These distributions, however, are not intended to reflect the natural variability of the abundances of the different isotopes in the earth’s crust or in any other environment. Rather, they convey states of knowledge about the elemental composition of “normal” materials generally, or about specific classes of such materials. In the absence of detailed knowledge about the isotopic composition of a material, or when such details may safely be ignored, the probability distribution assigned to the standard atomic weight intervals may be taken as rectangular (or, uniform). This modeling choice is a reasonable and convenient default choice when a representative value of the atomic weight, and associated uncertainty, are needed in calculations involving atomic and relative molecular masses. When information about the provenance of the material, or other information about the isotopic composition needs to be taken into account, then this distribution may be non-uniform. We present several examples of how the probability distribution of an atomic weight or relative molecular mass may be characterized, and also how it may be used to evaluate the associated uncertainty.

Inter-laboratory study for the certification of trace elements in seawater certified reference materials NASS-7 and CASS-6 - Yang, Lu; Nadeau, Kenny; Meija, Juris; Grinberg, Patricia; Pagliano, Enea; Ardini, Francisco; Grotti, Marco; Schlosser, Christian; Streu, Peter; Achterberg, Eric P.; Sohrin, Yoshiki; Minami, Tomoharu; et al. (Analytical and Bioanalytical Chemistry, 2018)
Certification of trace metals in seawater certified reference materials (CRMs) NASS-7 and CASS-6 is described. At the National Research Council Canada (NRC), column separation was performed to remove the seawater matrix prior to the determination of Cd, Cr, Cu, Fe, Pb, Mn, Mo, Ni, U, V, and Zn, whereas As was directly measured in 10-fold diluted seawater samples, and B was directly measured in 200-fold diluted seawater samples. High-resolution inductively coupled plasma mass spectrometry (HR-ICPMS) was used for elemental analyses, with double isotope dilution for the accurate determination of B, Cd, Cr, Cu, Fe, Pb, Mo, Ni, U, and Zn in seawater NASS-7 and CASS-6, and standard addition calibration for As, Co, Mn, and V. In addition, all analytes were measured using standard addition calibration with triple quadrupole (QQQ)-ICPMS to provide a second set of data at NRC. Expert laboratories worldwide were invited to contribute data to the certification of trace metals in NASS-7 and CASS-6. Various analytical methods were employed by participants including column separation, co-precipitation, and simple dilution coupled to ICPMS detection or flow injection analysis coupled to chemiluminescence detection, with use of double isotope dilution calibration, matrix matching external calibration, and standard addition calibration. Results presented in this study show that majority of laboratories have demonstrated their measurement capabilities for the accurate determination of trace metals in seawater. As a result of this comparison, certified/reference values and associated uncertainties were assigned for 14 elements in seawater CRMs NASS-7 and CASS-6, suitable for the validation of methods used for seawater analysis.
Keywords: Dissolved trace metals; Seawater; Certified reference material; Isotope dilution; HR-ICPMS; Flow injection analysis; Standard addition calibration

Intensity-corrected Herschel observations of nearby isolated low-mass clouds - Sadavoy, Sarah I.; Keto, Eric; Bourke, Tyler L.; Dunham, Michael M.; Myers, Philip C.; Stephens, Ian W.; Di Francesco, James; Webb, Kristi; M. Stutz, Amelia; Launhardt, Ralf; J. Tobin, John (The Astrophysical Journal, 2018)
We present intensity-corrected Herschel maps at 100, 160, 250, 350, and 500 μm for 56 isolated low-mass clouds. We determine the zero-point corrections for Herschel Photodetector Array Camera and Spectrometer (PACS) and Spectral Photometric Imaging Receiver (SPIRE) maps from the Herschel Science Archive (HSA) using Planck data. Since these HSA maps are small, we cannot correct them using typical methods. Here we introduce a technique to measure the zero-point corrections for small Herschel maps. We use radial profiles to identify offsets between the observed HSA intensities and the expected intensities from Planck. Most clouds have reliable offset measurements with this technique. In addition, we find that roughly half of the clouds have underestimated HSA-SPIRE intensities in their outer envelopes relative to Planck, even though the HSA-SPIRE maps were previously zero-point corrected. Using our technique, we produce corrected Herschel intensity maps for all 56 clouds and determine their line-of-sight average dust temperatures and optical depths from modified blackbody fits. The clouds have typical temperatures of ~14–20 K and optical depths of ~10−5–10−3. Across the whole sample, we find an anticorrelation between temperature and optical depth. We also find lower temperatures than what was measured in previous Herschel studies, which subtracted out a background level from their intensity maps to circumvent the zero-point correction. Accurate Herschel observations of clouds are key to obtaining accurate density and temperature profiles. To make such future analyses possible, intensity-corrected maps for all 56 clouds are publicly available in the electronic version.
Keywords: dust, extinction; ISM: clouds; ISM: structure; stars: formation; submillimeter: ISM

Intelligent machining: real-time tool condition monitoring and intelligent adaptive control systems - Hassan, M.; Sadek, A.; Attia, M. H.; Thomson, V. (Journal of Machine Engineering, 2018)
Unmanned manufacturing systems has recently gained great interest due to the ever increasing requirements of optimized machining for the realization of the fourth industrial revolution in manufacturing ‘Industry 4.0’. Real-time tool condition monitoring (TCM) and adaptive control (AC) machining system are essential technologies to achieve the required industrial competitive advantage, in terms of reducing cost, increasing productivity, improving quality, and preventing damage to the machined part. New AC systems aim at controlling the process parameters, based on estimating the effects of the sensed real-time machining load on the tool and part integrity. Such an aspect cannot be directly monitored during the machining operation in an industrial environment, which necessitates developing new intelligent model-based process controllers. The new generations of TCM systems target accurate detection of systematic tool wear growth, as well as the prediction of sudden tool failure before damage to the part takes place. This requires applying advanced signal processing techniques to multi-sensor feedback signals, in addition to using ultra-high speed controllers to facilitate robust online decision making within the very short time span (in the order of 10 ms) for high speed machining processes. The development of new generations of Intelligent AC and TCM systems involves developing robust and swift communication of such systems with the CNC machine controller. However, further research is needed to develop the industrial internet of things (IIOT) readiness of such systems, which provides a tremendous potential for increased process reliability, efficiency and sustainability.

Insight towards the role of ceria-based supports for reverse water gas shift reaction over RuFe nanoparticles - Panaritis, Christopher; Edake, Mahesh; Couillard, Martin; Einakchi, Raha; Baranova, Elena A. (Journal of CO2 Utilization, 2018)
Utilization of CO2 through the reverse water gas shift (RWGS) reaction is a promising solution in managing greenhouse gas emissions. Here, we used the RWGS reaction to evaluate the catalytic conversion of CO2 over Ru-Fe nanoparticles supported on samarium-doped ceria (SDC) support. Catalysts of different RuxFe100-x compositions (x = 100, 80, 45, 20, 0 at.%) have been studied under steady-state conditions in a packed bed reactor in the temperature range 300–800 °C to determine their catalytic activity and selectivity towards CO. The metal-support interaction (MSI) effect for SDC was evaluated to determine its promotional behavior for the RWGS reaction. The catalyst was characterized using TEM, TGA, and ICP-ES techniques. Among all investigated catalysts, Ru45Fe55/SDC (2 wt.%) displayed the overall best activity and CO selectivity. A stability test of 100 h at 650 °C confirmed an excellent stability of the Ru45Fe55/SDC catalyst. Overall, the use of Ru45Fe55/SDC (2 wt.%) is a promising catalyst in the utilization of CO2, reaching a maximum CO yield of ∼47.5% at 800 °C and 100% CO selectivity above 500 °C. Furthermore, Ru45Fe55 (2 wt.%) nanoparticles were deposited on un-doped CeO2 and doped ceria: Gd-CeO2, Y2O3-CeO2, as well as yttria-stabilized zirconia (YSZ) and carbon supports. Contrary to carbon support, all catalysts containing oxygen conducting-ceramic supports displayed 100% selectivity to CO at temperatures above 600 °C, which can be attributed to the synergistic relationship between Ru-Fe nanoparticles being promoted through the MSI and thermally induced migration of promoting ionic species (Oδ−) from oxygen conducting ceramics to the nanoparticles.
Keywords: reverse water-gas shift (RWGS); ruthenium; iron; nanoparticles; oxygen conducting ceramic

Infrared spectrum and intermolecular potential energy surface of the CO–O2 dimer - Barclay, A. J.; Mckellar, A. R. W.; Moazzen-Ahmadi, N.; Dawes, Richard; Wang, Xiao-Gang; Carrington, Tucker (Physical Chemistry Chemical Physics, 2018)
Only a few weakly-bound complexes containing the O2 molecule have been characterized by high resolution spectroscopy, no doubt due to the complications added by the oxygen molecule's unpaired electron spin. Here we report an extensive infrared spectrum of CO–O2, observed in the CO fundamental band region using a tunable quantum cascade laser to probe a pulsed supersonic jet expansion. The rotational energy level pattern derived from the spectrum consists of stacks of levels characterized by the total angular momentum, J, and its projection on the intermolecular axis, K. Five such stacks are observed in the ground vibrational state, and ten in the excited state (ν(CO) = 1). They are divided into two groups, with no observed transitions between groups. The groups correspond to different projections of the O2 electron spin, and correlate with the two lowest fine structure states of O2, (N, J) = (1, 0) and (1, 2). The rotational constant of the lowest K = 0 stack implies an effective intermolecular separation of 3.82 Å, but this should be interpreted with caution since it ignores possible effects of electron spin. A new high-level 4-dimensional potential energy surface is developed for CO–O2, and rotational energy levels are calculated for this surface, ignoring electron spin. By comparing calculated and observed levels, it is possible to assign detailed quantum labels to the observed level stacks.

Infrared spectra of C2H4 dimer and trimer - Barclay, A.J.; Esteki, K.; Mckellar, A. R. W.; Moazzen-Ahmadi, N. (Journal of Molecular Spectroscopy, 2018)
Spectra of ethylene dimers and trimers are studied in the ν11 and (for the dimer) ν9 fundamental band regions of C2H4 (≈2990 and 3100 cm−1) using a tunable optical parametric oscillator source to probe a pulsed supersonic slit jet expansion. The deuterated trimer has been observed previously, but this represents the first rotationally resolved spectrum of (C2H4)3. The results support the previously determined cross-shaped (D2d) dimer and barrel-shaped (C3h or C3) trimer structures. However, the dimer spectrum in the ν9 fundamental region of C2H4 is apparently very perturbed and a previous rotational analysis is not well verified.
Keywords: ethylene; spectrum; dimer; trimer; van der waals; infrared; supersonic jet

Influence of primary particle polydispersity and overlapping on soot morphological parameters derived from numerical TEM images - Morán, J.; Cuevas, J.; Liu, F.; Yon, J.; Fuentes, A. (Powder Technology, 2018)
Experimental studies of soot morphology based on analysis of transmission electron microscopy (TEM) images usually neglect the potential effects of primary particle polydispersity and overlapping. In this study, fractal aggregates of different sizes consisting of polydisperse and overlapping primary particles were numerically generated using typical fractal dimension and prefactor relevant to soot. A total of 3600 simulated two-dimensional projections for each primary particle size distribution and level of overlapping considered was produced and analyzed using two TEM image analysis methods commonly used in the literature to evaluate the effects of primary particle polydispersity and overlapping on the recovered morphological parameters of soot. Fairly large deviations in the recovered number of primary particles in aggregates were obtained by both methods considered using the procedure commonly used in the literature. A recommendation was proposed to improve the accuracy of the retrieved number of polydisperse primary particles in an aggregate. We show that the results obtained by using both the Tian et al. (2006) and Brasil et al. (1999) methods can be significantly improved by using the recommended modification for primary particle polydispersity levels commonly encountered in flame soot. Finally, we recommend to use the modified Tian et al. 2006 method for recovering the number of primary particles of aggregates consisting of both polydisperse and overlapped primary particles.
Keywords: polydisperse primary particles; overlapping; fractal aggregates; TEM; image analysis

Influence of preheating and burner geometry on modeling the attachment of laminar coflow CH4/air diffusion flames - Xu, Huanhuan; Liu, Fengshan; Sun, Shaozeng; Zhao, Yijun; Meng, Shun; Tang, Wenbo; Feng, Dongdong; Gu, Mingyan (Combustion and Flame, 2018)
A laminar coflow CH4/air diffusion flame was experimentally and numerically studied to elucidate the mechanism of flame attachment and the importance of preheating, thermal boundary condition at the fuel tube, and burner geometry to the flame attachment location. OH*-chemiluminescence images were captured using an intensified CCD camera. The temperature of the outer surface of fuel tube at 2 mm below the burner exit was measured using a K-type thermocouple. Detailed simulations based on five different burner wall models were conducted to investigate the influence of preheating effect and burner geometry on flame attachment. The conjugate heat transfer between the heat-conducting burner wall and the surrounding gas flows was considered in the overall flame model to account for the preheating effect without or with less ad hoc assumptions for the burner inlet conditions. The effect of different thermal boundary conditions imposed at the fuel tube on the predicted flame attachment location was investigated. Results show that it is paramount to specify the inlet location at a certain distance upstream the burner exit to model the flame attachment phenomenon. This finding can be explained in terms of the direct heating of the fuel and air streams by the flame base or the mixing process between the fuel and air streams associated with the hydrodynamics and diffusion in the vicinity of the burner rim. The thermal boundary condition at the fuel tube only slightly affects the predicted flame attachment location. The fuel decomposition occurs inside the fuel tube mainly due to preheating by the fuel tube wall and the key chemical pyrolysis process was revealed through a detailed kinetics analysis. The efflux of CH4 to the air side over the burner rim was found responsible for the flame attachment under current conditions. The flame base kernel is established around the stoichiometric mixture and its location is controlled by the thermal condition and geometry of the burner wall. The burner geometry influences the position of flame attachment on the outer surface of the fuel tube through the fuel tube heat capacity and the shape.
Keywords: flame attachment; preheating effect; burner geometry; laminar coflow diffusion flame

Influence of powder morphology and microstructure on the cold spray and mechanical properties of Ti6Al4V coatings - Munagala, Venkata Naga Vamsi; Akinyi, Valary; Vo, Phuong; Chromik, Richard R. (Journal of Thermal Spray Technology, 2018)
The powder microstructure and morphology has significant influence on the cold sprayability of Ti6Al4V coatings. Here, we compare the cold sprayability and properties of coatings obtained from Ti6Al4V powders of spherical morphology (SM) manufactured using plasma gas atomization and irregular morphology (IM) manufactured using the Armstrong process. Coatings deposited using IM powders had negligible porosity and better properties compared to coatings deposited using SM powders due to higher particle impact velocities, porous surface morphology and more deformable microstructure. To evaluate the cohesive strength, multi-scale indentation was performed and hardness loss parameter was calculated. Coatings deposited using SM powders exhibited poor cohesive strength compared to coatings deposited using IM powders. Images of the residual indents showed de-bonding and sliding of adjacent splats in the coatings deposited using SM powders irrespective of the load. Coatings deposited using IM powders showed no evidence of de-bonding at low loads. At high loads, splat de-bonding was observed resulting in hardness loss despite negligible porosity. Thus, while the powders from Armstrong process lead to a significant improvement in sprayability and coating properties, further optimization of powder and cold spray process will be required as well as consideration of post-annealing treatments to obtain acceptable cohesive strength.
Keywords: Armstrong; cold spray; nanoindentation; particle morphology; Ti6Al4V; titanium alloys

Induction thermography of steel coupons with cracks - Genest, Marc; Li, Gang (Applied Optics, 2018)
The induction thermography technique was assessed experimentally and numerically on notched steel coupons using two coil configurations: straight line and loop conditions. The coupons had different lengths of fatigue crack varying from zero to 3 mm. The numerical predictions showed that the peak temperature was always located at the crack tip or the notch tip position. The loop coil resulted in higher temperatures than those of the straight line coil. Results showed that the numerical methods effectively supported the application assessment of this nondestructive evaluation (NDE) technique for the steel material, but crack geometry remains a challenge as the exact shape of a natural crack is typically unknown. It is shown that induction thermography can detect a crack as small as 1 mm in the notched steel coupons. Commentary on the application of the NDE technique with the numerical modeling support was provided.

In situ pilot test for bioremediation of energetic compound-contaminated soil at a former military demolition range site - Jugnia, Louis B.; Manno, Dominic; Drouin, Karine; Hendry, Meghan (Environmental Science and Pollution Research, 2018)
Bioremediation was performed in situ at a former military range site to assess the performance of native bacteria in degrading hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) and 2,4-dinitrotoluene (2,4-DNT). The fate of these pollutants in soil and soil pore water was investigated as influenced by waste glycerol amendment to the soil. Following waste glycerol application, there was an accumulation of organic carbon that promoted microbial activity, converting organic carbon into acetate and propionate, which are intermediate compounds in anaerobic processes. This augmentation of anaerobic activity strongly correlated to a noticeable reduction in RDX concentrations in the amended soil. Changes in concentrations of RDX in pore water were similar to those observed in the soil suggesting that RDX leaching from the soil matrix, and treatment with waste glycerol, contributed to the enhanced removal of RDX from the water and soil. This was not the case with 2,4-DNT, which was neither found in pore water nor affected by the waste glycerol treatment. Results from saturated conditions and Synthetic Precipitation Leaching Procedure testing, to investigate the environmental fate of 2,4-DNT, indicated that 2,4-DNT found on site was relatively inert and was likely to remain in its current state on the site.
Keywords: in situ; pilot test; biodegradation; carbon source; waste glycerol; RDX; 2,4-DNT

Improved circuit model fitting of inkjet-printed OTFTs and a proposal for standardized parameter reporting - Griffin, Ryan H.; Shleifman, Denis; Dadvand, Afshin; Graddage, Neil; Chu, Ta-Ya; Tao, Ye (IEEE Transactions on Electron Devices, 2018)
Within the field of organic thin-film transistors (OTFTs), a large variety of materials are available. As a consequence, it may not be possible for one circuit model to accurately replicate the behavior of all OTFT devices. We propose modifications to two popular circuit models in order to better match the characteristics observed in the devices manufactured using our materials system. Using measured data for complementary n- and p-type organic devices, modeling parameters are extracted through optimization. Due to the ubiquitous use of the square-law model to characterize organic devices, modeling parameters are also extracted using this traditional approach. Extracted parameters are then compared and discussed. As there is a clear variation in device parameters based on the model used, a new standardization scheme is proposed which attempts to provide a standardized quality assurance metric, which simplifies the comparison of the reported device parameters. This scheme provides an indication of the goodness of fit between the model being used to describe the device and the extracted modeling parameters.
Keywords: modeling; organic field effect transistor (OFET); organic thin-film transistor (OTFT); parameter extraction; standardization

Impact of low molecular weight acids on oil impregnated paper insulation degradation - Kouassi, Kakou; Fofana, Issouf; Cissé, Ladji; Hadjadj, Yazid; Yapi, Kouba; Diby, K. (Energies, 2018)
Aging of a power transformer’s insulation system produces carboxylic acids. These acids—acetic, formic and levulinic—are absorbed by the paper insulating material, thus accelerating the degradation of the whole insulation system. In this contribution, the effect of these acids on the aging of oil-impregnated paper insulation used in power transformer is reported. A laboratory aging experiment considering different concentrations of these three acids was performed to assess their effect on the insulation system’s degradation. Each acid was individually mixed with virgin oil, and a mixture of acids was also blended with oil. The paper’s degradation was assessed by the degree of polymerization (DPv). It was found that the DPv of paper aged with formic acid decreased much faster in comparison to the other acids.
Keywords: power transformer; oil-paper insulation; carboxylic acids; acetic acid; formic acid; levulinic acid; degree of polymerization

Identification, growth and toxicity assessment of Coolia Meunier (Dinophyceae) from Nova Scotia, Canada - Lewis, Nancy I.; Wolny, Jennifer L.; Achenbach, John Claude; Ellis, Lee; Pitula, Joseph S.; Rafuse, Cheryl; Rosales, Detbra S.; Mccarron, Pearse (Harmful Algae, 2018)
Benthic dinoflagellates of the toxigenic genus Coolia Meunier (Dinophyceae) are known to have a global distribution in both tropical and temperate waters. The type species, C. monotis, has been reported from the Mediterranean Sea, the NE Atlantic and from Rhode Island, USA in the NW Atlantic, whereas other species in the genus have been reported from tropical locations. Coolia cells were observed in algal drift samples collected at seven sites in Nova Scotia, Canada. Clonal isolates were established from four of these locations and identified with light and scanning electron microscopy, then confirmed with genetic sequencing to be C. monotis. This is the first record of this species in Nova Scotia. The isolates were established and incubated at 18 °C under a 14:10 L:D photoperiod with an approximate photon flux density of 50–60 μmol m−2 s−1. Growth experiments using an isolate from Johnston Harbour (CMJH) were carried out at temperatures ranging from 5 to 30 °C under the same photoperiod with an approximate photon flux density of 45–50 μmol m−2 s−1. Cells tolerated temperatures from 5 to 25 °C with optimum growth and mucilage aggregate production between 15 and 20 °C. Methanol extracts of this isolate examined by Liquid Chromatography-Mass Spectrometry (LC–MS) did not show the presence of the previously reported cooliatoxin. Toxic effects were assayed using two zebrafish bioassays, the Fish Embryo Toxicity (FET) assay and the General Behaviour and Toxicity (GBT) assay. The results of this study demonstrate a lack of toxicity in C. monotis from Nova Scotia, as has been reported for other genetically-confirmed isolates of this species. Conditions in which cell growth that could potentially degrade water quality and provide substrate and dispersal mechanisms for other harmful microorganisms via mucilage production are indicated.
Keywords: Coolia monotis; temperature; growth rate; toxicity; zebrafish bioassay

Characterization and optimization of spiral eddy current coils for in-situ crack detection - Mandache, Catalin; Shull, Peter J. (Nondestructive Characterization and Monitoring of Advanced Materials, Aerospace, Civil Infrastructure, and Transportation XII, 2018)
In-situ condition-based maintenance is making strides in the aerospace industry and it is seen as an alternative to scheduled, time-based maintenance. With fatigue cracks originating from fastener holes as the main reason for structural failures, embedded eddy current coils are a viable non-invasive solution for their timely detection. The development and potential broad use of these coils are motivated by a few consistent arguments: (i) inspection of structures of complicated geometries and hard to access areas, that often require disassembly, (ii) alternative to regular inspection actions that could introduce inadvertent damage, (iii) for structures that have short inspection intervals, and (iv) for repaired structures where fastener holes contain bushings and prevent further bolt-hole inspections. Since the spiral coils are aiming at detecting radial cracks emanating from the fastener holes, their design parameters should allow for high inductance, low ohmic losses and power requirements, as well as optimal size and high sensitivity to discontinuities. In this study, flexible, surface conformable, spiral eddy current coils are empirically investigated on mock-up specimens, while numerical analysis is performed for their optimization and design improvement.

High-temperature and low-threshold interband cascade lasers at wavelengths longer than 6 μm - Rassel, S. M. Shazzad; Li, Lu; Li, Yiyun; Yang, Rui Q.; Gupta, James A.; Wu, Xiaohua; Aers, Geof C. (Optical Engineering, 2018)
InAs-based interband cascade (IC) lasers with improved optical confinement have achieved high-temperature operation with a threshold current density as low as 333 A∕cm2 at 300 K for emission at 6003 nm. The threshold current density is the lowest ever reported among semiconductor midinfrared lasers at similar wavelengths. These InAs-based IC devices lased in pulsed mode at temperatures up to 357 K near 6.28 μm. A narrow-ridge device was able to operate in continuous-wave mode at temperatures up to 293 K at 6.01 μm.
Keywords: interband cascade laser; type-II quantum well; midinfrared; InAs

High-resolution synchrotron infrared spectroscopy of acrolein: the interacting 10⋀1 and 14⋀1 18⋀1 states and other vibrational levels between 1020 and 1200 cm⋀−1 - Mckellar, A. R. W.; Billinghurst, B. E.; Xu, Li-Hong; Lees, R. M. (Journal of Molecular Spectroscopy, 2018)
Vibrational states of trans-acrolein (propenal) between 1020 and 1200 cm−1 are analyzed using high-resolution infrared spectra obtained at the Canadian Light Source synchrotron radiation facility. The one fundamental in this range, ν10 (C-C stretch vibration) is found to be strongly mixed with a combination vibration ν14 + ν18 by a Fermi-type interaction. Five additional states are directly observed via hot, combination, and overtone bands: ν11 + ν18, ν16 + ν18, ν15 + ν18, 2ν12, and 2ν17. These seven vibrational states are analyzed in a large multi-state fit, along with nine more states which are not directly observed but which affect the observed states by means of many perturbations. Though this fit is cumbersome, incomplete, and not unique, it can account for 3668 out of 3835 assigned lines with an average error of less than 0.0004 cm−1.
Keywords: acrolein; propenal; infrared; synchrotron; coriolis; perturbation

High-resolution SMA imaging of bright submillimetre sources from the SCUBA-2 Cosmology Legacy Survey - Hill, Ryley; Chapman, Scott C.; Scott, Douglas; Petitpas, Glen; Smail, Ian; Chapin, Edward L.; Gurwell, Mark A.; Perry, Ryan; Blain, Andrew W.; Bremer, Malcolm N.; Chen, Chian-Chou; Dunlop, James S.; et al. (Monthly Notices of the Royal Astronomical Society, 2018)
We have used the Submillimeter Array (SMA) at 860 μm to observe the brightest sources in the Submillimeter Common User Bolometer Array-2 (SCUBA-2) Cosmology Legacy Survey (S2CLS). The goal of this survey is to exploit the large field of the S2CLS along with the resolution and sensitivity of the SMA to construct a large sample of these rare sources and to study their statistical properties. We have targeted 70 of the brightest single-dish SCUBA-2 850 μm sources down to S850 ≈ 8 mJy, achieving an average synthesized beam of 2.4 arcsec and an average rms of σ860 = 1.5mJy beam−1 in our primary beam-corrected maps. We searched our SMA maps for 4σ peaks, corresponding to S860 ≳ 6mJy sources, and detected 62, galaxies, including three pairs. We include in our study 35 archival observations, bringing our sample size to 105 bright single-dish submillimetre sources with interferometric followup. We compute the cumulative and differential number counts, finding them to overlap with previous single-dish survey number counts within the uncertainties, although our cumulative number count is systematically lower than the parent S2CLS cumulative number count by 14± 6 per cent between 11 and 15 mJy. We estimate the probability that a ≳10 mJy singledish submillimetre source resolves into two or more galaxies with similar flux densities to be less than 15 per cent. Assuming the remaining 85 per cent of the targets are ultraluminous starburst galaxies between z= 2 and 3, we find a likely volume density of ≳400M⊙ yr−1 sources to be ∼3+0.7−0.6 ×10−7 Mpc−3.We show that the descendants of these galaxies could be ≳4× 1011M⊙ local quiescent galaxies, and that about 10 per cent of their total stellar mass would have formed during these short bursts of star formation.
Keywords: galaxies: starburst; galaxies: statistics; submillimetre: galaxies

High-quality draft genome of the methanotroph Methylovulum psychrotolerans Str. HV10-M2 isolated from plant material at a high-altitude environment - Mateos-Rivera, Alejandro; Islam, Tajul; Marshall, Ian P. G.; Schreiber, Lars; Øvreås, Lise (Standards in Genomic Sciences, 2018)
Here we present the genome of Methylovulum psychrotolerans strain HV10-M2, a methanotroph isolated from Hardangervidda national park (Norway). This strain represents the second of the two validly published species genus with a sequenced genome. The other is M. miyakonense HT12, which is the type strain of the species and the type species of the genus Methylovulum. We present the genome of M. psychrotolerants str. HV10-M2 and discuss the differences between M. psychrotolerans and M. miyakonense. The genome size of M. psychrotolerans str. HV10-M2 is 4,923,400 bp and contains 4415 protein-coding genes, 50 RNA genes and an average GC content of 50.88%.
Keywords: methylovulum psychrotolerans HV10-M2; methylovulum; gammaproteobacteria; methanotroph; high-altitude

High performance InAs/InP quantum dot 34462-GHz C-band coherent comb laser module - Lu, Z. G.; Liu, J. R.; Song, C. Y.; Weber, J.; Mao, Y.; Chang, S. D.; Ding, H. P.; Poole, P. J.; Barrios, P. J.; Poitras, D.; Janz, S.; O’sullivan, M. (Optics Express, 2018)
We have developed an InAs/InP quantum dot (QD) C-band coherent comb laser (CCL) module with actively stabilized absolute wavelength and power, and channel spacing of 34.462 GHz with ± 100 ppm accuracy. The total output power is up to 46 mW. The integrated average relative intensity noise (RIN) values of the lasing spectrum and a filtered single channel at 1540.19 nm were −165.6 dB/Hz and −130.3 dB/Hz respectively in the frequency range from 10 MHz to 10 GHz. The optical linewidth of the 45 filtered individual channels between 1531.77 nm to 1543.77 nm ranged from 850 kHz to 2.16 MHz. We have also analyzed the noise behaviors of each individual channel.

HFF-DeepSpace photometric catalogs of the 12 Hubble frontier fields, clusters, and parallels: photometry, photometric redshifts, and stellar masses - Shipley, Heath V.; Lange-Vagle, Daniel; Marchesini, Danilo; Brammer, Gabriel B.; Ferrarese, Laura; Stefanon, Mauro; Kado-Fong, Erin; Whitaker, Katherine E.; Oesch, Pascal A.; Feinstein, Adina D.; Labbé, Ivo; Lundgren, Britt; et al. (The Astrophysical Journal Supplement Series, 2018)
We present Hubble multi-wavelength photometric catalogs, including (up to) 17 filters with the Advanced Camera for Surveys and Wide Field Camera 3 from the ultra-violet to near-infrared for the Hubble Frontier Fields and associated parallels. We have constructed homogeneous photometric catalogs for all six clusters and their parallels. To further expand these data catalogs, we have added ultra-deep K S -band imaging at 2.2 μm from the Very Large Telescope HAWK-I and Keck-I MOSFIRE instruments. We also add post-cryogenic Spitzer imaging at 3.6 and 4.5 μm with the Infrared Array Camera (IRAC), as well as archival IRAC 5.8 and 8.0 μm imaging when available. We introduce the public release of the multi-wavelength (0.2–8 μm) photometric catalogs, and we describe the unique steps applied for the construction of these catalogs. Particular emphasis is given to the source detection band, the contamination of light from the bright cluster galaxies (bCGs), and intra-cluster light (ICL). In addition to the photometric catalogs, we provide catalogs of photometric redshifts and stellar population properties. Furthermore, this includes all the images used in the construction of the catalogs, including the combined models of bCGs and ICL, the residual images, segmentation maps, and more. These catalogs are a robust data set of the Hubble Frontier Fields and will be an important aid in designing future surveys, as well as planning follow-up programs with current and future observatories to answer key questions remaining about first light, reionization, the assembly of galaxies, and many more topics, most notably by identifying high-redshift sources to target.

H2: the benchmark molecule for ultrafast science and technologies - Ibrahim, Heide; Lefebvre, Catherine; Bandrauk, André D.; Staudte, André; Légaré, François (Journal of Physics B: Atomic, Molecular and Optical Physics, 2018)
This review article focuses on imaging and controlling ultrafast dynamics of the hydrogen molecule and its cation, initiated by ultrashort laser pulses. We discuss the mechanisms underlying these dynamics and theoretical methods to describe them. A broad variety of defining and influencing theoretical and experimental results is presented. We put special emphasis on the required experimental techniques, many of which have been developed in view of imaging the fastest of all nuclear dynamics.

GPI Spectra of HR 8799 c, d, and e from 1.5 to 2.4 μm with KLIP Forward Modeling - Greenbaum, Alexandra Z.; Pueyo, Laurent; Ruffio, Jean-Baptiste; Wang, Jason J.; Rosa, Robert J. De; Aguilar, Jonathan; Rameau, Julien; Barman, Travis; Marois, Christian; Marley, Mark S.; Konopacky, Quinn; Rajan, Abhijith; et al. (The Astronomical Journal, 2018)
We explore KLIP forward modeling spectral extraction on Gemini Planet Imager coronagraphic data of HR 8799, using PyKLIP, and show algorithm stability with varying KLIP parameters. We report new and re-reduced spectrophotometry of HR 8799 c, d, and e in the H and K bands. We discuss a strategy for choosing optimal KLIP PSF subtraction parameters by injecting simulated sources and recovering them over a range of parameters. The K1/K2 spectra for HR 8799 c and d are similar to previously published results from the same data set. We also present a K-band spectrum of HR 8799 e for the first time and show that our H-band spectra agree well with previously published spectra from the VLT/SPHERE instrument. We show that HR 8799 c and d show significant differences in their H and K spectra, but do not find any conclusive differences between d and e, nor between c and e, likely due to large error bars in the recovered spectrum of e. Compared to M-, L-, and T-type field brown dwarfs, all three planets are most consistent with mid- and late-L spectral types. All objects are consistent with low gravity, but a lack of standard spectra for low gravity limit the ability to fit the best spectral type. We discuss how dedicated modeling efforts can better fit HR 8799 planets' near-IR flux, as well as how differences between the properties of these planets can be further explored.

Genome-wide prediction of cis-regulatory regions using supervised deep learning methods - Li, Yifeng; Shi, Wenqiang; Wasserman, Wyeth W. (BMC Bioinformatics, 2018)
Background: In the human genome, 98% of DNA sequences are non-protein-coding regions that were previously disregarded as junk DNA. In fact, non-coding regions host a variety of cis-regulatory regions which precisely control the expression of genes. Thus, Identifying active cis-regulatory regions in the human genome is critical for understanding gene regulation and assessing the impact of genetic variation on phenotype. The developments of high-throughput sequencing and machine learning technologies make it possible to predict cis-regulatory regions genome wide. Results: Based on rich data resources such as the Encyclopedia of DNA Elements (ENCODE) and the Functional Annotation of the Mammalian Genome (FANTOM) projects, we introduce DECRES based on supervised deep learning approaches for the identification of enhancer and promoter regions in the human genome. Due to their ability to discover patterns in large and complex data, the introduction of deep learning methods enables a significant advance in our knowledge of the genomic locations of cis-regulatory regions. Using models for well-characterized cell lines, we identify key experimental features that contribute to the predictive performance. Applying DECRES, we delineate locations of 300,000 candidate enhancers genome wide (6.8% of the genome, of which 40,000 are supported by bidirectional transcription data), and 26,000 candidate promoters (0.6% of the genome). Conclusion: The predicted annotations of cis-regulatory regions will provide broad utility for genome interpretation from functional genomics to clinical applications. The DECRES model demonstrates potentials of deep learning technologies when combined with high-throughput sequencing data, and inspires the development of other advanced neural network models for further improvement of genome annotations.
Keywords: cis-regulatory region; enhancer; promoter; deep learning

Genome re-sequencing and simple sequence repeat markers reveal the existence of divergent lineages in the Canadian Puccinia striiformis f. sp. tritici population with extensive DNA methylation - Brar, Gurcharn S.; Ali, Sajid; Qutob, Dinah; Ambrose, Stephen; Lou, Kun; Maclachlan, Ron; Pozniak, Curtis J.; Fu, Yong-Bi; Sharpe, Andrew G.; Kutcher, Hadley R. (Environmental Microbiology, 2018)
Wheat stripe rust, caused by Puccinia striiformis f. sp. tritici (Pst), is an important disease in Canada. The worldwide genetic structure of Pst populations have been characterized, excluding Canada. Here, we elucidated the genetic structure of the western Canadian Pst population using molecular markers, revealing the presence of four divergent lineages with predominantly clonal structure. In the worldwide context, two previously reported lineages were identified: PstS0 (22%), representing an old Northwestern‐European and PstS1 (35%), an invasive warm‐temperature adapted. Additionally, two new, unreported lineages, PstPr (9%) and PstS1‐related (35%), were detected, which produced more telia than other lineages and had double the number of unique recombination events. The PstPr was a recent invasion, and likely evolved in a diverse, recombinant population as it was closely related to the PstS5, PstS7/Warrior, PstS8/Kranich, and PstS9 lineages originating from sexually recombining populations in the centre of diversity. The DNA methylation analysis revealed DNA‐methyltransferase1‐homologs, providing compelling evidence for epigenetic regulation and as a first report, an average of ∼5%, 5hmC in the Puccinia epigenome merits further investigation. The divergent lineages in the Canadian Pst population with the potential for genetic recombination, as well as epigenetic regulation needs consideration in the context of pathogen adaptation and management.

Genetic algorithm and polynomial chaos modelling for performance optimization of photonic circuits under manufacturing variability - Melati, Daniele; Waqas, Abi; Xu, Dan-Xia; Melloni, Andrea (Optical Fiber Communication Conference, 2018)
We propose an efficient technique based on polynomial chaos expansion and genetic algorithms to enable constrained optimization of photonic integrated circuits subject to fabrication tolerances. Simulations on a realistic SOI design confirm its effectiveness.

Gene transfer of ZMapp antibodies mediated by recombinant adeno-associatedvVirus protects against Ebola infections - Robert, Marc-André; Nassoury, Nasha; Chahal, Parminder S.; Venne, Marie-Hélène; Racine, Trina; Qiu, Xiangguo; Kobinger, Gary; Kamen, Amine; Gilbert, Rénald; Gaillet, Bruno (Human Gene Therapy, 2018)
Vectored delivery of the ZMapp antibody cocktail (c2G4, c4G7, and c13C6) by using recombinant adeno-associated viruses (rAAVs) could be useful for preventive immunization against Ebola virus infections because rAAVs can generate long-term antibody expression. Three rAAVs (serotype 9) encoding chimeric ZMapp antibodies were produced by triple-plasmid transfection up to 10 L-scale in WAVE bioreactors using HEK293 cells grown in suspension/serum-free conditions. Efficacy of AAV-c2G4 via intravenous (i.v.), intramuscular (i.m.), and intranasal (i.n.) routes of administration was evaluated in mice with two different doses of 2.7 × 1010 and 13.0 × 1010 vector genomes (vg). The best protective efficacies after Ebola challenge were obtained with the i.v. and i.m. routes. Serum concentrations of ZMapp antibodies positively correlated with survivability. Efficacy of the rAAV-ZMapp cocktail was then evaluated at a higher dose of 30.0 × 1010 vg. It conferred a more robust protection (90% i.v. and 60% i.m.) than rAAV-c4G7 (30%) and rAAV-c13C6 (70%), both administered separately at the same dose. Delivery of rAAV-c2G4 alone achieved up to 100% protection (100% i.v. and 90% i.m.) at the same dose. In conclusion, the preventive treatment was effective in mice. However, no advantage was observed for using the rAAV-ZMapp cocktail in comparison to the utilization of the single rAAV-c2G4.

Further characterization of the capsule-like complex (CLC) produced by Francisella tularensis Subspecies tularensis: protective efficacy and similarity to outer membrane vesicles - Champion, Anna E.; Bandara, Aloka B.; Mohapatra, Nrusingh; Fulton, Kelly M.; Twine, Susan M.; Inzana, Thomas J. (Frontiers in Cellular and Infection Microbiology, 2018)
Francisella tularensis is the etiologic agent of tularemia, and subspecies tularensis (type A) is the most virulent subspecies. The live vaccine strain (LVS) of subspecies holarctica produces a capsule-like complex (CLC) that consists of a large variety of glycoproteins. Expression of the CLC is greatly enhanced when the bacteria are subcultured in and grown on chemically defined medium. Deletion of two genes responsible for CLC glycosylation in LVS results in an attenuated mutant that is protective against respiratory tularemia in a mouse model. We sought to further characterize the CLC composition and to determine if a type A CLC glycosylation mutant would be attenuated in mice. The CLCs isolated from LVS extracted with 0.5% phenol or 1 M urea were similar, as determined by gel electrophoresis and Western blotting, but the CLC extracted with urea was more water-soluble. The CLC extracted with either 0.5% phenol or 1 M urea from type A strains was also similar to the CLC of LVS in antigenic properties, electrophoretic profile, and by transmission electron microscopy (TEM). The solubility of the CLC could be further enhanced by fractionation with Triton X-114 followed by N-Lauroylsarcosine detergents; the largest (>250 kDa) molecular size component appeared to be an aggregate of smaller components. Outer membrane vesicles/tubules (OMV/T) isolated by differential centrifugation and micro-filtration appeared similar to the CLC by TEM, and many of the proteins present in the OMV/T were also identified in soluble and insoluble fractions of the CLC. Further investigation is warranted to assess the relationship between OMV/T and the CLC. The CLC conjugated to keyhole limpet hemocyanin or flagellin was highly protective against high-dose LVS intradermal challenge and partially protective against intranasal challenge. A protective response was associated with a significant rise in cytokines IL-12, IL-10, and IFN-γ. However, a type A CLC glycosylation mutant remained virulent in BALB/c mice, and immunization with the CLC did not protect mice against high dose respiratory challenge with type A strain SCHU S4.

Full-length glycosylated gag of murine leukemia virus can associate with the viral envelope as a type I integral membrane protein - Renner, Tyler Milston; Bélanger, Kasandra; Lam, Cindy; Gerpe, María Carla Rosales; Mcbane, Joanne Eileen; Langlois, Marc-André; Simon, Viviana (Journal of Virology, 2018)
The glycosylated Gag protein (gPr80) of murine leukemia viruses (MLVs) has been shown to exhibit multiple roles in facilitating retrovirus release, infection, and resistance to host-encoded retroviral restriction factors, such as APOBEC3, SERINC3, and SERINC5. One way in which gPr80 helps MLVs to escape host innate immune restriction is by increasing capsid stability, a feature that protects viral replication intermediates from being detected by cytosolic DNA sensors. gPr80 also increases the resistance of MLVs to deamination and restriction by mouse APOBEC3 (mA3). How the gPr80 accessory protein, with its three N-linked glycosylation sites, contributes to these resistance mechanisms is still not fully understood. Here we further characterized the function of gPr80 and, more specifically, revealed that the asparagines targeted for glycosylation in gPr80 also contribute to capsid stability through their parallel involvement in the Pr65 Gag structural polyprotein. In fact, we demonstrate that sensitivity to deamination by the mA3 and human A3 proteins is directly linked to capsid stability. We also show that full-length gPr80 is detected in purified viruses. However, our results suggest that gPr80 is inserted in the NexoCcyto orientation of a type I integral membrane protein. Additionally, our experiments have revealed the existence of a large population of Env-deficient virus-like particles (VLPs) harboring gPr80 inserted in the opposite (NcytoCexo) polarity, which is typical of type II integral membrane proteins. Overall this study provides new insight into the complex nature of the MLV gPr80 accessory protein.

Friction correction for model ship resistance and propulsion tests in ice at NRC's OCRE-RC - Lau, Michael (International Journal of Naval Architecture and Ocean Engineering, 2018)
This paper documents the result of a preliminary analysis on the influence of hull-ice friction coefficient on model resistance and power predictions and their correlation to full-scale measurements. The study is based on previous model-scale/full-scale correlations performed on the National Research Council - Ocean, Coastal, and River Engineering Research Center's (NRC/OCRE-RC) model test data. There are two objectives for the current study: (1) to validate NRC/OCRE-RC's modeling standards in regarding to its practice of specifying a CFC (Correlation Friction Coefficient) of 0.05 for all its ship models; and (2) to develop a correction methodology for its resistance and propulsion predictions when the model is prepared with an ice friction coefficient slightly deviated from the CFC of 0.05. The mean CFC of 0.056 and 0.050 for perfect correlation as computed from the resistance and power analysis, respectively, have justified NRC/OCRE-RC's selection of 0.05 for the CFC of all its models. Furthermore, a procedure for minor friction corrections is developed.
Keywords: model test; ice resistance; power; friction correction; correlation friction coefficient

Flame attachment and kinetics studies of laminar coflow CO/H2 diffusion flames burning in O2/H2O - Xu, Huanhuan; Liu, Fengshan; Sun, Shaozeng; Zhao, Yijun; Meng, Shun; Chen, Lei; Chen, Longfei (Combustion and Flame, 2018)
In this study, experimental and numerical investigations were conducted to study the attachment and oxidation process of laminar CO/H2 diffusion flames burning in coflow O2/H2O at 1 atm with an inlet temperature of 400 K for both the fuel and oxidizer streams. The effects of fuel composition were investigated by considering a wide range of CO/H2 mole ratio from 95%CO–5%H2 to 5%CO–95%H2 and also pure H2. The oxidizer has a fixed composition of 75%H2O–25%O2. The measured flame heights determined by OH*-chemiluminescence images were used to validate the flame model adopted in this work. Through numerical simulations using a two-dimensional flame code with the preheating effect, detailed reaction mechanism, and detailed thermal and transport properties, the details of flame attachment and flame structure were obtained and analysed. Although both CO and H2 diffuse over the burner rim and move upstream into the oxidizer stream, the attachment point of a H2-rich syngas flame is further upstream below the burner exit than that of a CO-rich flame. This is attributed to the high reactivity of H2 through reaction OH + H2 = H + H2O and the high diffusivity of H2. Reaction pathways for syngas burning in the oxidizer of O2/H2O based on a detailed kinetics analysis were revealed, not only inside the fuel tube and above the fuel exit, but also near the flame sheet and in the flame attachment zone. Significant consumption of H2O was observed in the flame core due to the reverse reaction of OH + H2 = H + H2O which shifts to proceed forward outside the flame in the radial direction also at higher streamwise locations if H2 in the fuel flow is rich, oxidizing unburned H2 to H2O.
Keywords: syngas; O2/H2O oxidizer; laminar coflow diffusion flame; flame attachment; oxidation process

Fertilizer usage and cadmium in soils, crops and food - Dharma-Wardana, M. W. C. (Environmental Geochemistry and Health, 2018)
Phosphate fertilizers were first implicated by Schroeder and Balassa (Science 140(3568):819–820, 1963) for increasing the Cd concentration in cultivated soils and crops. This suggestion has become a part of the accepted paradigm on soil toxicity. Consequently, stringent fertilizer control programs to monitor Cd have been launched. Attempts to link Cd toxicity and fertilizers to chronic diseases, sometimes with good evidence, but mostly on less certain data are frequent. A re-assessment of this “accepted” paradigm is timely, given the larger body of data available today. The data show that both the input and output of Cd per hectare from fertilizers are negligibly small compared to the total amount of Cd/hectare usually present in the soil itself. Calculations based on current agricultural practices are used to show that it will take centuries to double the ambient soil Cd level, even after neglecting leaching and other removal effects. The concern of long-term agriculture should be the depletion of available phosphate fertilizers, rather than the negligible contamination of the soil by trace metals from fertilizer inputs. This conclusion is confirmed by showing that the claimed correlations between fertilizer input and Cd accumulation in crops are not robust. Alternative scenarios that explain the data are presented. Thus, soil acidulation on fertilizer loading and the effect of Mg, Zn and F ions contained in fertilizers are considered using recent Cd2+, Mg2+ and F− ion-association theories. The protective role of ions like Zn, Se, Fe is emphasized, and the question of Cd toxicity in the presence of other ions is considered. These help to clarify difficulties in the standard point of view. This analysis does not modify the accepted views on Cd contamination by airborne delivery, smoking, and industrial activity, or algal blooms caused by phosphates.
Keywords: cadmium; metal toxins; phosphate; crops; fertilizers; soils; food

Femtosecond laser-inscribed fiber bragg gratings for sensing applications - Mihailov, Stephen J. (Opto-Mechanical Fiber Optic Sensors, 2018)
This chapter presents the state of the art of femtosecond laser–induced fiber Bragg gratings for sensing applications. It summarizes the laser-material processing mechanisms for dielectric modification with femtosecond pulse duration sources, techniques for grating inscription with said sources, and applications of femtosecond laser–induced gratings in waveguides for strain, temperature, and chemical sensing in harsh environments.
Keywords: fiber Bragg grating; fiber optic sensor; laser-material processing; nonlinear optics; ultrafast laser sources

Fatigue performances of FSW and GMAW aluminum alloys welded joints: competition between microstructural and structural-contact-fretting crack initiation - Texier, D.; Atmani, F.; Nadeau, F.; Chen, J.; Zedan, Y.; Vanderesse, N.; Demers, V. (International Journal of Fatigue, 2018)
The fatigue properties of gas metal arc welded and friction stir welded assemblies made of aluminum alloy AA6061-T6 structural extrusions were examined. The mechanical performances of welded joints were obtained using uniaxial tensile and force-controlled constant amplitude axial fatigue tests. Microstructural and fractographic analyses were conducted to document the influence of the process on microstructure evolution, fatigue crack initiation sites, and propagation mechanisms leading to the final rupture of the assemblies. Microhardness measurements and digital image correlation techniques paired with interrupted tensile tests were also used to investigate the complex heterogeneous local mechanical behavior and to highlight the fact that the crack initiation mechanism was driven by the microstructural state of the joint as well as by the structural-contact-fretting occurring at the notch root. The corresponding fatigue strengths at 2 million and 10 million cycles were evaluated respectively at 10% and 20% higher for friction stir welded assemblies versus gas metal arc welded assemblies. Fractographic analyses revealed that the fatigue cracks were initiated from microstructural features (pores for the GMAW configuration and banded structure on the crown side for the FSW configuration), or from large sub-surface grains in a shallow region below the structural-contact-fretting occurring at the notch root.

Fast detection of vascular plaque in optical coherence tomography images using a reduced feature set - Prakash, Ammu; Ocana, Mariano; Hewko, Mark; Sherif, Sherif S.; Sowa, Michael; Bang, Ole; Podoleanu, Adrian (2nd Canterbury Conference on OCT with Emphasis on Broadband Optical Sources, 2018)
Optical coherence tomography (OCT) images are capable of detecting vascular plaque by using the full set of 26 Haralick textural features and a standard K-means clustering algorithm. However, the use of the full set of 26 textural features is computationally expensive and may not be feasible for real time implementation. In this work, we identified a reduced set of 3 textural feature which characterizes vascular plaque and used a generalized Fuzzy C-means clustering algorithm. Our work involves three steps: 1) the reduction of a full set 26 textural feature to a reduced set of 3 textural features by using genetic algorithm (GA) optimization method 2) the implementation of an unsupervised generalized clustering algorithm (Fuzzy C-means) on the reduced feature space, and 3) the validation of our results using histology and actual photographic images of vascular plaque. Our results show an excellent match with histology and actual photographic images of vascular tissue. Therefore, our results could provide an efficient pre-clinical tool for the detection of vascular plaque in real time OCT imaging.

Fabrication of bragg gratings in random air-line clad microstructured optical fiber - Mihailov, Stephen J.; Hnatovsky, Cyril; Grobnic, Dan; Chen, Kevin; Li, Ming-Jun (IEEE Photonics Technology Letters, 2018)
Fiber Bragg gratings (FBGs) are written using an infrared (IR) femtosecond laser and a phase mask into pure silica microstructured optical fiber having a cladding region comprised of random air-lines (RAL). Scanning electron microscopy measurements of the IR irradiated RAL fiber samples shows the presence of subwavelength nanograting structures associated with thermally stable type II Bragg gratings. High temperature annealing testing shows that although the RAL FBGs have a high degree of stability even at 1000 °C, they are less stable than similar FBGs made in single mode telecom fiber (SMF-28).
Keywords: ultrafast optics; fiber Bragg gratings; microstructured optical fiber

Experimental observations of microstructure changes in the catalyst layers of proton exchange membrane fuel cells under wet-dry cycles - Zhao, Jian; Shahgaldi, Samaneh; Li, Xianguo; Liu, Zhongsheng (Simon) (Journal of The Electrochemical Society, 2018)
Microstructure changes of the catalyst layers in proton exchange membrane fuel cells (PEMFCs) lead to significant performance degradation and durability limitations, especially under dynamic loading condition; and they are investigated experimentally in this study simulating the effect of wet-dry cycles through water intrusion-evaporation and water flow-through-dehydration experiments, respectively. It is found that the cycling of water intrusion-evaporation processes significantly contributes to the growth of agglomerates as well as the formation of pinholes and cracks, causing irreversible losses of active surface areas and catalytic activity; in contrast, the cycling of water flow-through-dehydration experiments enlarges the large pores but changes very little the agglomerate sizes. This is because water tends to flow through the path of least resistance, that is, the large pores in the catalyst layers, leaving the other parts of the catalyst layers with relatively small pores less affected. These observations provide experimental evidence of microstructure changes and their forms for a better understanding of degradation in PEMFCs, especially under dynamic operating conditions.
Keywords: catalyst layer; microstructure changes; proton exchange membrane fuel cell

Experimental and numerical investigations of soot formation in laminar coflow ethylene flames burning in O2/N2 and O2/CO2 atmospheres at different O2 mole fractions - Zhang, Yindi; Liu, Fengshan; Lou, Chun (Energy & Fuels, 2018)
This paper presents an experimental and numerical study of the distributions of the temperature and soot volume fraction in laminar coflow ethylene diffusion flames burning in O2/N2 and O2/CO2 atmospheres with the O2 mole fraction varying from 21 to 50% in both atmospheres. The fuel flow rate was maintained constant in all of the experiments and simulations. The two-color flame emission method based on the response spectrum of R and G bands of a three-color charge-coupled device camera was applied to measure the temperature and soot volume fraction. Numerical calculations were conducted using the C2 chemistry model [Appel–Bockhorn–Frenklach (ABF), Appel, J.; Bockhorn, H.; Frenklach, M. Kinetic modeling of soot formation with detailed chemistry and physics: Laminar premixed flames of C2 hydrocarbons. Combust. Flame 2000, 121 (1–2), 122–136, DOI: 10.1016/S0010-2180(99)00135-2] with formation of polycyclic aromatic hydrocarbons (PAHs) up to pyrene and a soot model incorporating the dimerization of two pyrene molecules as the soot inception step and hydrogen-abstraction acetylene addition mechanism and PAH condensation as the surface growth processes. Numerical results are in qualitative agreement with the experimental measurements when the oxidizer stream is air. The numerical model predicts the temperature well but overpredicts the soot volume fraction in oxygen-enriched flames in both O2/N2 and O2/CO2 atmospheres. With the increase of the oxygen mole fraction in the oxidizer stream, the flame becomes brighter and shorter, the peak temperature zone shifts from the flame wing to the upper part, and the peak soot volume fraction moves from the flame wing to the flame center. The soot loading grows rapidly with increasing the oxygen mole fraction in the oxidizer stream. Under the same oxygen mole fraction, the temperature and soot volume fraction in the O2/N2 atmosphere are always higher than those in the O2/CO2 atmosphere as a result of the higher heat capacity of CO2 and soot formation suppression by CO2. The chemical effect of CO2 may promote O and OH, which enhance the oxidation of the critical soot formation species, including H, C2H2, C6H6, and C16H10. The primary pathway for the chemical effect of CO2 is its competition for the H radical to form CO and OH, i.e., CO2 + H ⇄ CO + OH. Soot formation in these flames is affected by two primary reactions: CO2 + H ⇄ CO + OH and H + O2 ⇄ O + OH.

Experimental and numerical investigation of wave induced motions of partially submerged bodies approaching a fixed structure - Sayeed, Tanvir; Colbourne, Bruce; Molyneux, David; Akinturk, Ayhan; Zaman, Hasanat (Ocean Engineering, 2018)
Estimation of iceberg impact load is an important design consideration for offshore structures in ice prone regions. Impact velocity is influenced by the complex hydrodynamic interaction between the iceberg or bergy bit and the offshore structure. In order to understand the phenomenon, a two phase, experimental and numerical, study has been conducted. In the first phase, the change in wave loads on different sized spherical model ice masses was investigated for different proximities to a fixed structure and the results published in Sayeed et al. (2017b). This paper describes the results of the second phase study where the change in wave induced motions of free floating ice masses, approaching a fixed structure, is investigated through physical experiments and numerical simulations. The experiments were carried out at the Ocean Engineering Research Center (OERC) of Memorial University of Newfoundland and the motions were measured using an optical tracking system, Qualysis©. The objective is to determine the velocity profiles of approaching ice masses and how that changes prior to impact. The experimental results of motion data show excellent correlation with the force data gathered in the first phase. Similar to previous studies, the separation distance to wavelength ratio is shown to dictate the corresponding wave induced motions. As the body gets close to the structure, the surge motion slows and at the same time the heave motion is increased. Some experiments have also been conducted to understand the effect of initial starting location on the resulting drift velocity. Numerical simulations of the experimental cases, using the commercial CFD software Flow3D©, show good agreement with the experimental data.
Keywords: iceberg; Bergy-bit; wave induced motion; hydrodynamic interaction; offshore structure; wave-body interaction

Experimental and numerical investigation of wave induced forces and motions of partially submerged bodies near a fixed structure in irregular waves - Sayeed, Tanvir; Colbourne, Bruce; Molyneux, David (Ocean Engineering, 2018)
This paper is the third of a series covering investigations of the wave induced force and motion behavior of ice masses near a fixed structure. The objective of this phase of the study was to determine whether the effects observed in regular waves (Sayeed et al. (2017b, 2018)) still held in irregular seas. In the present case, wave characteristics measured in front of the fixed structure showed that the significant wave heights follow a standing wave pattern generated by the superposition of the incident and reflected peak frequency wave. Thus it may be inferred that the significant surge and heave forces and motions will be increased or decreased at the node and antinode locations in front of the structure as previously observed for regular waves. Force spectra generated from regular wave force data (Sayeed et al. 2017b) and wave measurements from the present study showed that beyond the nodal location at D/λp=0.25, the significant surge force goes down and significant heave force goes up as the body gets close to the structure. Direct measurements of irregular wave forces on a fixed berg model at different proximity to the fixed structure demonstrate the change in significant wave forces based on the ratio of separation distance to peak wavelength. When the berg body is positioned closer to the fixed structure, the normalized significant forces in the horizontal direction decrease, and the normalized significant forces in the vertical direction increase. Significant differences were found between the directly measured force spectra and those produced by linear superposition of regular wave force transfer functions. This is attributed to non-linear effects arising from the iceberg profile and low freeboard. Free floating motion experiments showed smaller differences in the surge and heave velocity spectra due to the presence of the structure. This is because there is insufficient motion data at any specific location to capture the motion responses for all the frequencies in the spectrum. The proximity effect on wave loads and wave induced motions in the vertical direction is found to be more pronounced than the same in the horizontal direction. Numerical simulations using RANS based commercial CFD code Flow3D© are compared to the experimental results. Selected test cases from both force and motion experiments are simulated in irregular waves generated from selected experimental wave spectra. Numerical results for irregular waves demonstrate the ability to simulate random waves and resulting forces and motions with trends comparable to the experimental results.
Keywords: iceberg; bergy bit; irregular waves; Hydrodynamic interaction; offshore structure; wave-body interaction

Evaluation of the computer simulation model NTVPM for assessing military tracked vehicle cross-country mobility - Wong, Jo Y.; Jayakumar, Paramsothy; Preston-Thomas, Jon (Proceedings of the Institution of Mechanical Engineers, Part D: Journal of Automobile Engineering, 2018)
In the United States and some other NATO (North Atlantic Treaty Organization) countries, the NATO Reference Mobility Model is currently used to evaluate military ground vehicle mobility. The module of the NATO Reference Mobility Model for predicting the cross-country performance of military vehicles is empirically based and was developed using test data collected decades ago. The NATO Reference Mobility Model has inherent limitations, such as the uncertainty whether its empirical relations can be extrapolated beyond the test conditions upon which they were derived or whether it can be used for evaluating new-generation military vehicles. This suggests that there is a need for the development of a physics-based model that takes into account the advancements in terramechanics and modelling/simulation techniques. This paper describes the results of a detailed evaluation of a physics-based model – the Nepean Tracked Vehicle Performance Model – for assessing military tracked vehicle cross-country performance. The performance of a notional tracked vehicle (an armoured personnel carrier) predicted by the latest version of the Nepean Tracked Vehicle Performance Model is compared with test data obtained on sandy terrain, muskeg and snow-covered terrain. The correlations between the predicted and measured performance are evaluated using the coefficient of correlation, coefficient of determination, root mean square deviation and coefficient of variation. The applications of the Nepean Tracked Vehicle Performance Model to predicting the maximum possible vehicle speed (speed-made-good) on a given terrain, the sensitivity of vehicle performance to variations in the values of terrain parameters and the mean maximum pressure are demonstrated. The results of this study indicate that the Nepean Tracked Vehicle Performance Model has potential to form the basis for the development of the next-generation cross-country performance assessment methodology for military tracked vehicles.
Keywords: coefficient of correlation; coefficient of variation; root mean square deviation; computer simulation models; cross-country performance; mean maximum pressure; physics-based models; tracked vehicle mobility

Enhancement-mode two-channel triple quantum dot from an undoped Si/Si0.8Ge0.2 quantum well hetero-structure - Studenikin, S. A.; Gaudreau, L.; Kataoka, K.; Austing, D. G.; Sachrajda, A. S. (Applied Physics Letters, 2018)
We demonstrate coupled triple dot operation and charge sensing capability for the recently introduced quantum dot technology employing undoped Si/Si0.8Ge0.2 hetero-structures which also incorporate a single metal-gate layer to simplify fabrication [Lu et al., Appl. Phys. Lett. 109, 093102 (2016)]. Si/SiGe hetero-structures with a Ge concentration of 20% rather than the more usual 30% typically encountered offer higher electron mobility. The devices consist of two in-plane parallel electron channels that host a double dot in one channel and a single dot in the other channel. In a device where the channels are sufficiently close a triple dot in a triangular configuration is induced leading to regions in the charge stability diagram where three charge-addition lines of different slope approach each other and anti-cross. In a device where the channels are further apart, the single dot charge-senses the double dot with relative change of ∼2% in the sensor current.

Energy and comfort performance benefits of early detection of building sensor and actuator faults - Gunay, Burak; Shen, Weiming; Huchuk, Brent; Yang, Chunsheng; Bucking, Scott; O’Brien, William (Building Services Engineering Research and Technology, 2018)
This paper presents a building performance simulation-based investigation to better understand the energy and comfort performance benefits of early detection of common sensor and actuator faults. Five types of air-handling unit faults and four types of zone-level faults were implemented to the energy management system application of the building performance simulation tool EnergyPlus. During 50-year simulation periods, the faults were randomly permitted to affect 75 different components of an archetype medium-sized office building model. The sensitivity of the simulation results with respect to three variables was studied: fault recurrence period, fault repair period, and discomfort threshold for simulated complaints. The results indicate that the energy use intensity and the predicted percentage of dissatisfied exhibit a power–law relationship with time, in which most of the performance reductions occur in the first 10 years. If the work-orders are issued only upon occupant complaints, the faults were estimated to cause a 16–62% increase in the energy use intensity for heating, ventilation, and air-conditioning and a 11–38% increase in the predicted percentage of dissatisfied at the end of the 50-year simulation periods. The results indicate that if the faults can be detected within a month after their first appearance, almost all their detrimental effects on a building’s energy and comfort performance can be mitigated. Practical application: The methodology and results presented in this article are of practical use for those who study on-going commissioning, fault detection and diagnostics, and energy management systems in buildings. The simulation-based parametric analysis approach can be used to estimate the range of energy and comfort savings expected through early detection of common sensor and actuator faults in commercial buildings. Insights gathered from such an analysis can be used in planning the frequency of retro-commissioning and investments for automated fault detection and diagnostics systems.
Keywords: fault detection and diagnostics; building performance simulation; energy and comfort impact of sensor and actuator faults

Efficient solution of the electronic eigenvalue problem using wavepacket propagation - Neville, Simon P.; Schuurman, Michael S. (Journal of Chemical Theory and Computation, 2018)
We report how imaginary time wavepacket propagation may be used to efficiently calculate the lowest-lying eigenstates of the electronic Hamiltonian. This approach, known as the relaxation method in the quantum dynamics community, represents a fundamentally different approach to the solution of the electronic eigenvalue problem in comparison to traditional iterative subspace diagonalization schemes such as the Davidson and Lanczos methods. In order to render the relaxation method computationally competitive with existing iterative subspace methods, an extended short iterative Lanczos wavepacket propagation scheme is proposed and implemented. In the examples presented here, we show that by using an efficient wavepacket propagation algorithm the relaxation method is, at worst, as computationally expensive as the commonly used block Davidson–Liu algorithm, and in certain cases, significantly less so.

Effects of stem-injected gibberellins and 6-benzylaminopurine on phytohormone profiles and cone yield in two lodgepole pine genotypes - Kong, Lisheng; Von Aderkas, Patrick; Zaharia, L. Irina (Trees, 2018)
Effects of exogenously applied gibberellins (GAs) and 6-benzylaminopurine (BA) on profiles of phytohormones and some of their metabolites relative to controls in long-shoot buds of lodgepole pine (Pinus contorta Dougl. ex Loud. var. latifolia Engelm.) were analyzed during cone bud initiation and differentiation. Differential responses in phytohormones and in cone yield were observed in ramets of the two tested genotypes (478 and 276) to stem-injected mixtures of GA4 and GA7 (GA4/7) and /or BA. Injected GA4/7 affected bud concentrations of GA4 and GA7. Injected PGRs, with the exception of BA injection, decreased concentrations of abscisic acid (ABA) and ABA glucose-ester at week 5 and/or week 7. Internal concentrations of trans-zeatin riboside (t-ZR) increased in response to all treatments at week 3 in genotype 276. In genotype 478, t-ZR only increased with treatments of BA or GA4/7 plus BA. Dihydrozeatin riboside concentrations increased in response to GA4/7 plus BA treatment at week 7 in genotype 276. Concentrations of isopentenyl adenosine declined with treatments of GA4/7 and GA4/7 plus BA in genotype 276 at week 5. In genotype 478, a similar decrease was caused by GA4/7 plus BA treatment. For both genotypes, the highest ratio of zeatin-type cytokinins to isopentenyl-type cytokinins occurred at weeks 5 and 7 after injection with GA4/7 plus BA. Stem-injection of GA4/7, especially in combination with BA, increased female cone yields significantly in genotype 276, but not in genotype 478.
Keywords: lodgepole pine; phytohormone; gibberellins A4 + A7; 6-benzylaminopurine; stem-injection; female cone yield

Effects of interfacial interactions and interpenetrating brushes on the electrospinning of cellulose nanocrystals-polystyrene fibers - Kalantari, Mahsa; Du, Rongbing; Ayranci, Cagri; Boluk, Yaman (Journal of Colloid and Interface Science, 2018)
This study investigated the electrospinning of polystyrene solutions using added unmodified and modified (with grafted nitrobenzene and trifluoromethyl benzene functionalities and polystyrene brushes) cellulose nanocrystals (CNCs). A strong correlation existed between the formation of beads on the fibers and the degree of dispersion of CNC particles in the electrospinning mixtures. Agglomerates of CNC particles always concentrated in the form of beads. The best dispersion in N,N dimethylformamide (DMF) mixtures was obtained using CNC-2 surfaces that were modified using trifluoromethyl benzene functional groups. Using CNC-2 also resulted in both uniform and bead-free electrospun fibers. Despite good dispersion in DMF, the use of grafted polystyrene (PS) chains with CNC-g resulted in beads above a 1.0% concentration level. This result is attributed to more favorable interactions between the CNC-g brushes during the DMF solvent evaporation stage of electrospinning. The electrospinning of CNC/PS nanocomposites at very low CNC concentrations (<1.0%) showed strong adhesion bonds at the polymer-CNC interfaces. Excellent mechanical properties were also produced by using interpenetrating networks of surface brushes.
Keywords: electrospinning; cellulose nanocrystals; polystyrene; N,N dimethylformamide; dispersion; polymer brushes; tensile strength

Effects of global warming on precipitation extremes: dependence on storm characteristics - Gaur, Abhishek; Schardong, Andre; Simonovic, Slobodan (Water Resources Management, 2018)
This study investigates the relationship between historically observed changes in extreme precipitation magnitudes and temperature (Pex-T relationship) at multiple locations in Canada. The focus is on understanding the behavior of these relationships with regards to key storm characteristics such as its duration, season of occurrence, and location. To do so, three locations are chosen such that they have large amounts of moisture available near them whereas four locations are chosen such that they are located in the land-locked regions of Canada and subsequently have no nearby moisture source available on them. To investigate the effect of different storm durations on Pex-T relationship, storms of durations: 5, 10, 15, 30 min, 1, 2, 6, 12, 24 h are considered. Finally, Pex-T relationship is analyzed separately for summer and winter seasons to quantify the influence of seasons. Results indicate strong influences of storm duration, season of occurrence, and location on observed precipitation scaling rates. Drastic intensification of precipitation extremes with temperature is obtained for shorter duration precipitation events than for longer duration precipitation events, in summers than in the winters. Furthermore, in summertime, increases in the intensity of convection driven precipitation extremes is found highest at locations away from large waterbodies. On the other hand, in wintertime most drastic increases in extreme precipitation are obtained at locations near large waterbodies. These findings contribute towards increasing the current understanding of precipitation extremes in the context of rapidly increasing global temperatures.
Keywords: clausius-Clapeyron; precipitation extremes; temperature; storm duration; moisture availability

NFIRAOS adaptive optics for the Thirty Meter Telescope - Crane, Jeffrey; Andersen, David R.; Atwood, Jenny; Byrnes, Peter; Fitzsimmons, Joeleff; Lardière, Olivier; Densmore, Adam; Hardy, Tim; Herriot, Glen; Hoff, Brian; Kerley, Dan; Smith, Malcolm; et al. (Adaptive Optics Systems VI, 2018)
NFIRAOS (Narrow-Field InfraRed Adaptive Optics System) will be the first-light multi-conjugate adaptive optics system for the Thirty Meter Telescope (TMT). NFIRAOS houses all of its opto-mechanical sub-systems within an optics enclosure cooled to precisely -30°C in order to improve sensitivity in the near-infrared. It supports up to three client science instruments, including the first-light InfraRed Imaging Spectrograph (IRIS). Powering NFIRAOS is a Real Time Controller that will process the signals from six laser wavefront sensors, one natural guide star pyramid WFS, up to three low-order on-instrument WFS and up to four guide windows on the client instrument’s science detector in order to correct for atmospheric turbulence, windshake, optical errors and plate-scale distortion. NFIRAOS is currently preparing for its final design review in late June 2018 at NRC Herzberg in Victoria, British Columbia in partnership with Canadian industry and TMT.

ATP triggers a robust intracellular [Ca2+]-mediated signalling pathway in human synovial fibroblasts - Kondo, C.; Clark, R. B.; Kim, T. Y.; Belke, D.; Banderali, U.; Szerencsei, R. T.; Jalloul, A. H.; Schnetkamp, P. P. M.; Spitzer, K. W.; Giles, W. R. (Experimental Physiology, 2018)
In human articular joints, synovial fibroblasts (HSFs) have essential physiological functions that include synthesis and secretion of components of the extracellular matrix and essential articular joint lubricants, as well as release of paracrine substances such as ATP. Although the molecular and cellular processes that lead to a rheumatoid arthritis (RA) phenotype are not fully understood, HSF cells exhibit significant changes during this disease progression. The effects of ATP on HSFs were studied by monitoring changes in intracellular Ca2+ ([Ca2+]i), and measuring electrophysiological properties. ATP application to HSF cell populations that had been enzymatically released from 2‐D cell culture revealed that ATP (10–100 μm), or its analogues UTP or ADP, consistently produced a large transient increase in [Ca2+]i. These changes (i) were initiated by activation of the P2Y purinergic receptor family, (ii) required Gq‐mediated signal transduction, (iii) did not involve a transmembrane Ca2+ influx, but instead (iv) arose almost entirely from activation of endoplasmic reticulum (ER)‐localized inositol 1,4,5‐trisphosphate (IP3) receptors that triggered Ca2+ release from the ER. Corresponding single cell electrophysiological studies revealed that these ATP effects (i) were insensitive to [Ca2+]o removal, (ii) involved an IP3‐mediated intracellular Ca2+ release process, and (iii) strongly turned on Ca2+‐activated K+ current(s) that significantly hyperpolarized these cells. Application of histamine produced very similar effects in these HSF cells. Since ATP is a known paracrine agonist and histamine is released early in the inflammatory response, these findings may contribute to identification of early steps/defects in the initiation and progression of RA.

Dynamics of paralytic shellfish toxins and their metabolites during timecourse exposure of scallops Chlamys farreri and mussels Mytilus galloprovincialis to Alexandrium pacificum - Qiu, Jiangbing; Meng, Fanping; Ding, Ling; Che, Yijia; Mccarron, Pearse; Beach, Daniel G.; Li, Aifeng (Aquatic Toxicology, 2018)
New C-11 hydroxyl metabolites of paralytic shellfish toxins (PSTs) have been reported in shellfish. To gain further information on these metabolites, as well as the potential for formation of phase-II metabolites and acyl esters of PSTs, bivalves were fed with the PSTs-producing dinoflagellate Alexandrium pacificum (strain ATHK). Through independent experiments, scallops (Chlamys farreri) were fed for 9 days and mussels (Mytilus galloprovincialis) for 5 days plus an additional 5 days of depuration, with representative samples taken throughout. Several common PSTs (C1-4, GTX1-6 and NEO) and metabolites including M1, M3, M5, M7, M9, M2 and M8 were detected in the hepatopancreas of scallops during toxin accumulation and in the hepatopancreas of mussels during both toxin accumulation and elimination periods. The relative molar ratio of metabolites to precursor molecules was used to estimate relative metabolic conversion rates. Conversion rates of C1/2 and GTX2/3 were higher than those of C3/4 and GTX1/4, in scallops and mussels. The first metabolites observed in both bivalve species investigated were M1/3, which are formed from C1/2. However, the conversion of GTX2/3 to M2 was more complete than other biotransformation reactions in both mussels and scallops. In general, metabolic conversion of PSTs was observed after a shorter time and to a greater extent in mussels than in scallops in the exposure period. No acyl esters or conjugation products of PSTs with glucuronic acid, glutathione, cysteine and taurine were detected by liquid chromatography with high resolution tandem mass spectrometry in the samples investigated. Additionally, only GTX1/4 and GTX2/3 were detected in the kidney of scallops, which demonstrates that PSTs are mainly metabolized through the hepatic metabolism pathway in bivalves. This work improves the understanding of PST metabolism during toxin accumulation and depuration in commercially harvested shellfish.
Keywords: paralytic shellfish toxins; metabolites; chlamys farreri; mytilus galloprovincialis; Alexandrium pacificum; Alexandrium tamarense

Dynamics at conical intersections - Schuurman, Michael S.; Stolow, Albert (Annual Review of Physical Chemistry, 2018)
The nonadiabatic coupling of electronic and vibrational degrees of freedom is the defining feature of electronically excited states of polyatomic molecules. Once considered a theoretical curiosity, conical intersections (CIs) are now generally accepted as being the dominant source of coupled charge and vibrational energy flow in molecular excited states. Passage through CIs leads to the conversion of electronic to vibrational energy, which drives the ensuing photochemistry, isomerization being a canonical example. It has often been remarked that the CI may be thought of as a transition state in the excited state. As such, we expect that both the direction and the velocity of approach to the CI will matter. We explore this suggestion by looking for dynamical aspects of passage through CIs and for analogies with well-known concepts from ground-state reaction dynamics. Great progress has been made in the development of both experimental techniques and ab initio dynamics simulations, to a degree that direct comparisons may now be made. Here we compare time-resolved photoelectron spectroscopy results with on-the-fly ab initio multiple spawning calculations of the experimental observables, thereby validating each. We adopt a phenomenological approach and specifically concentrate on the excited-state dynamics of the C=C bond in unsaturated hydrocarbons. In particular, we make use of selective chemical substitution (such as replacing an H atom by a methyl group) so as to alter the inertia of certain vibrations relative to others, thus systematically varying (mass-weighted) directions and velocities of approach to a CI. Chemical substituents, however, may affect both the nuclear and electronic components of the total wave function. The former, which we call an inertial effect, influences the direction and velocity of approach. The latter, which we call a potential effect, modifies the electronic structure and therefore the energetic location and topography of the potential energy surfaces involved. Using a series of examples, we discuss both types of effects. We argue that there is a need for dynamical pictures and simple models of nonadiabatic dynamics at CIs and hope that the phenomenology presented here will help inspire such developments.
Keywords: conical intersection; molecular dynamics; nonadiabatic; ultrafast; spectroscopy; transition state; photochemistry; photoelectron; simulation; electronic structure

Dynamic mechanical characterization of aluminum: analysis of strain-rate-dependent behavior - Rahmat, Meysam (Mechanics of Time-Dependent Materials, 2018)
A significant number of materials show different mechanical behavior under dynamic loads compared to quasi-static (Salvado et al. in Prog. Mater. Sci. 88:186–231, 2017). Therefore, a comprehensive study of material dynamic behavior is essential for applications in which dynamic loads are dominant (Li et al. in J. Mater. Process. Technol. 255:373–386, 2018). In this work, aluminum 6061-T6, as an example of ductile alloys with numerous applications including in the aerospace industry, has been studied under quasi-static and dynamic tensile tests with strain rates of up to 156 s−1. Dogbone specimens were designed, instrumented and tested with a high speed servo-hydraulic load frame, and the results were validated with the literature. It was observed that at a strain rate of 156 s−1 the yield and ultimate strength increased by 31% and 33% from their quasi-static values, respectively. Moreover, the failure elongation and fracture energy per unit volume also increased by 18% and 52%, respectively. A Johnson–Cook model was used to capture the behavior of the material at different strain rates, and a modified version of this model was presented to enhance the capabilities of the original model, especially in predicting material properties close to the failure point. Finally, the fracture surfaces of specimens tested under quasi-static and dynamic loads were compared and conclusions about the differences were drawn.
Keywords: stress–strain; fracture; servo-hydraulic; tensile; aluminum 6061-T6

Draft whole-genome sequence of the fluorene-degrading sphingobium sp. strain LB126, isolated from polycyclic aromatic hydrocarbon-contaminated soil - Augelletti, Floriana; Tremblay, Julien; Agathos, Spiros N.; Stenuit, Ben (Genome Announcements, 2018)
We report here the draft whole-genome sequence of a fluorene-degrading bacterium, Sphingobium sp. strain LB126. The genes involved in the upper biodegradation pathway of fluorene are located on a plasmid, and the lower pathway that generates tricarboxylic acid cycle intermediates is initiated by the meta-cleavage of protocatechuic acid that is chromosomally encoded.

Dopant-modulated conjugated polymer enrichment of semiconducting SWCNTs - Li, Zhao; Ding, Jianfu; Lefebvre, Jacques; Malenfant, Patrick R. L. (ACS Omega, 2018)
Conjugated polymer extraction (CPE) is a low-cost, scalable process that can enrich single-walled carbon nanotube (SWCNT) materials in organic media. For other separation methods in aqueous phases, redox chemistry and/or pH control dramatically affect the sorting process of the SWCNTs. We have previously determined that the CPE process can be fine-tuned by adjusting the pH on the tube surface. Here, we systematically studied the effect of redox chemistry on the CPE process by adding organic p-/n-dopants. At a very strong p-/n-doping level, static repulsions dominated the interactions between the tubes and the CPE lost selectivity. When the doping level changed from a medium p-doping to a neutral state, the yield of CPE increased and the selectivity was compromised. We also observed chiral selectivity when a weak p-dopant was used. A photoluminescence excitation mapping under different titration conditions provided more insight into the doping level of the tubes relative to their diameters, chiralities, and redox potentials. We proposed a mechanism for the CPE process. The semiconducting and metallic tubes are separated because of their different solubilities, which are determined by the bundling energy between the tubes and are related to their doping level in polymer solutions.
Keywords: electron transfer; fluorescence; materials processing; nanoclusters; reaction mechanism; redox potential

Distinct amino acid residues confer one of three UDP-sugar substrate specificities in Acinetobacter baumannii PglC phosphoglycosyltransferases - Harding, Christian M.; Haurat, M florencia; Vinogradov, Evgeny; Feldman, Mario F. (Glycobiology, 2018)
Acinetobacter baumannii is an opportunistic human pathogen with the highest reported rates of multidrug resistance among Gram-negative pathogens. The capsular polysaccharide of A. baumannii is considered one of its most significant virulence factors providing resistance against complemented-mediated killing. Capsule synthesis in A. baumannii is usually initiated by the phosphoglycosyltransferase PglC. PglC transfers a phosphosugar from a nucleotide diphosphate-sugar to a polyprenol phosphate generating a polyprenol diphosphate-linked monosaccharide. Traditionally, PglC was thought to have stringent specificity towards UDP-N-N′-diacetylbacillosamine (UDP-diNAcBac). In this work we demonstrate that A. baumannii PglC has the ability to utilize three different UDP-sugar substrates: UDP-N-acetylglucosamine (UDP-GlcNAc), UDP-N-acetylgalactosamine (UDP-GalNAc) or UDP-diNAcBac. Using phylogenetic analyses, we first demonstrate that A. baumannii PglC orthologs separate into three distinct clades. Moreover, all members within a clade are predicted to have the same preference for one of the three possible sugar substrates. To experimentally determine the substrate specificity of each clade, we utilized in vivo complementation models and NMR analysis. We demonstrate that UDP-diNAcBac is accommodated by all PglC orthologs, but some orthologs evolved to utilize UDP-GlcNAc or UDP-GalNAc in a clade-dependent manner. Furthermore, we show that a single point mutation can modify the sugar specificity of a PglC ortholog specific for UDP-diNAcBac and that introduction of a non-native PglC ortholog into A. baumannii can generate a new capsule serotype. Collectively, these studies begin to explain why A. baumannii strains have such highly diverse glycan repertoires.
Keywords: acinetobacter baumannii; capsule; PglC; phosphoglycosyltransferase; serotype

Discrimination of uranium ore concentrates by chemometric data analysis to support provenance assessment for nuclear forensics applications - El haddad, Josette; Harhira, Aissa; Blouin, Alain; Sabsabi, Mohamad; Jovanovic, Slobodan; Kell, Tara; El-jaby, Ali (Journal of Radioanalytical and Nuclear Chemistry, 2018)
This work describes a method for the discrimination of uranium ore concentrates (UOCs) to support provenance assessment for nuclear forensics applications using samples representing twenty producers from around the world. The concentrations were measured using inductively coupled plasma mass spectrometry. UOCs were classified using the support vector machine method relying on 61 down to only 18 element concentrations without affecting the accuracy. New features are calculated from combination of elements from the selected 18 elements, and added to the selected elements improve the classification results. Reducing the number leads to the optimization of laboratory measurements of element signatures in support of nuclear safeguards and forensics applications.
Keywords: uranium ore concentrate (UOC); nuclear forensics; provenance assessment; chemometrics; support vector machine; discrimination

Differential mobility-mass spectrometry double spike isotope dilution study of release of β-methylaminoalanine and proteinogenic amino acids during biological sample hydrolysis - Beach, Daniel G.; Kerrin, Elliott S.; Giddings, Sabrina D.; Quilliam, Michael A.; Mccarron, Pearse (Scientific Reports, 2018)
The non-protein amino acid β-methylamino-L-alanine (BMAA) has been linked to neurodegenerative disease and reported throughout the environment. Proposed mechanisms of bioaccumulation, trophic transfer and chronic toxicity of BMAA rely on the hypothesis of protein misincorporation. Poorly selective methods for BMAA analysis have led to controversy. Here, a recently reported highly selective method for BMAA quantitation using hydrophilic interaction liquid chromatography-differential mobility spectrometry-tandem mass spectrometry (HILIC-DMS-MS/MS) is expanded to include proteinogenic amino acids from hydrolyzed biological samples. For BMAA quantitation, we present a double spiking isotope dilution approach using D3-BMAA and 13C15N2-BMAA. These methods were applied to study release of BMAA during acid hydrolysis under a variety of conditions, revealing that the majority of BMAA can be extracted along with only a small proportion of protein. A time course hydrolysis of BMAA from mussel tissue was carried out to assess the recovery of BMAA during sample preparation. The majority of BMAA measured by typical methods was released before a significant proportion of protein was hydrolyzed. Little change was observed in protein hydrolysis beyond typical hydrolysis times but the concentration of BMAA increased linearly. These findings demonstrate protein misincorporation is not the predominant form of BMAA in cycad and shellfish.

Development of wind load criteria for commercial roof edge metals - Baskaran, A.; Molleti, S.; Martins, N.; Martín-Pérez, B. (Journal of Architectural Engineering, 2018)
Edge metal covers the majority of commercial roofs to maintain waterproofing. It acts as the first line of defense against wind effects on commercial roofs. First, this article summarizes the in situ measurement site (the Canada Post building located in Vancouver, Canada) and compares the measured pressures with the existing wind standards. This study aimed to develop appropriate wind design pressure coefficients for roof edges, for incorporation in the National Building Code of Canada (NBCC). During this process, the following observations were made: (a) Comparison of the in situ measured pressures with existing wind standards suggested that design specifications on wind loads acting on roof edge metal systems in current building codes and standards are not adequate; (b) a systematic procedure to calculate code-comparable pressure coefficients from the in situ measured data is a challenging process; (c) correlation exists between edge metal design coefficients with those of the roof, to simplify the components and cladding design process.

Development of a multi-axis active seat mount to mitigate vibration transmission to helicopter aircrew - Hadj-Moussa, Firdous; Fereidooni, Amin; Chen, Yong; Wickramasinghe, Viresh K. (2018 AIAA/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference, 2018)
This paper presents the performance evaluation of a multi-axis active helicopter seat mount. By simultaneously counteracting vibrations in three orthogonal directions, the mount mitigates the transmission of helicopter vibrations from the floor to the seat before reaching to the human body. This design is tested independently in each direction and simultaneously in all three directions using shaker tables. The input vibration prole used in these tests are helicopter flight measurements collected on a Bell-412 research helicopter. To cancel the input vibration, the feedforward Filtered-x Least Mean Square (FxLMS) algorithm is employed as the adaptive control law. Signicant suppression of the harmonic components of the N/rev harmonics is achieved for both independent and simultaneous testing. In each case, the overall g-rms reduction level is more than 40 % along each axis. The experimental testing veried the effectiveness of the active seat mount as a means to attenuate multi-axis vibrations experienced by helicopter aircrew.

Determination of the cell wall polysaccharide and teichoic acid structures from Lactococcus lactis IL1403 - Vinogradov, Evgeny; Sadovskaya, Irina; Courtin, Pascal; Kulakauskas, Saulius; Grard, Thierry; Mahony, Jennifer; Van Sinderen, Douwe; Chapot-Chartier, Marie-Pierre (Carbohydrate Research, 2018)
In the lactic acid bacterium Lactococcus lactis, a cell wall polysaccharide (CWPS) is the bacterial receptor of the majority of infecting bacteriophages. The diversity of CWPS structures between strains explains, at least partially, the narrow host range of lactococcal phages. In the present work, we studied the polysaccharide components of the cell wall of the prototype L. lactis subsp. lactis strain IL1403. We identified a rhamnose-rich complex polysaccharide, carrying a glycerophosphate substitution, as the major component. Its structure was analyzed by 2D NMR spectroscopy, methylation analysis and MALDI-TOF MS and shown to be distinctly different from currently known lactococcal CWPS structures. It contains a linear backbone of repeated α-l-Rha disaccharide subunits, which is irregularly substituted with a trisaccharide occasionally bearing a glycerophosphate group. A poly (glycerol phosphate) teichoic acid, another important carbohydrate component of the IL1403 cell wall, was also isolated and structurally characterized.
Keywords: lactococcus lactis; cell-wall polysaccharide; rhamnose; structure; NMR spectroscopy

Determination of kfmsr,fref Qmsr,Q0 factors for ion chambers used in the calibration of Leksell Gamma Knife Perfexion model using EGSnrc and PENELOPE Monte Carlo codes - Mirzakhanian, Lalageh; Benmakhlouf, Hamza; Tessier, Frederic; Seuntjens, Jan (Medical Physics, 2018)
Purpose: To calculate the kfmsr,fref Qmsr,Q0 factors for nine common ionization chamber types following the small fields dosimetry formalism for the calibration of the Leksell Gamma Knife®(LGK) PerfexionTM using Monte Carlo simulation. This study also provides the first independent comparison of EGSnrc and PENELOPE for the calculation of kfmsr,fref Qmsr,Q0 correction factors and proposes a practical method to predict these factors based on chamber type, chamber orientation and phantom electron density. Methods: The ionization chambers are modeled using the EGSnrc and PENELOPE Monte Carlo codes based on the blueprints provided by the manufacturers. The chambers are placed in a half‐sphere water phantom and five spherical phantoms made of liquid water, solid water, ABS, polystyrene, and PMMA, respectively. Dose averaged over the air cavity of the chambers and a small water volume are calculated using EGSnrc and PENELOPE Monte Carlo codes for both conventional and machine specific reference (msr) setups. Using the calculated dose ratio, the kfmsr,fref Qmsr,Q0 factor is determined for all phantom materials and two possible orientations of chamber. The calculated kfmsr,fref Qmsr,Q0 factors are compared to a previous Monte Carlo study.1, 2 A relationship between the kfmsr,fref Qmsr,Q0 factor and the electron density of the phantom material is derived to predict the kfmsr,fref Qmsr,Q0 factor for any phantom material type. Applying the calculated kfmsr,fref Qmsr,Q0 factors to the measured dose rate of a recent round robin study3 improves consistency of reference dosimetry of the Leksell Gamma Knife®(LGK) PerfexionTM. Results: Agreement within uncertainty is observed between kfmsr,fref Qmsr,Q0 values determined in this study and the previous PEGASOS/PENELOPE study1, 2 in a liquid water phantom. The difference between kfmsr,fref Qmsr,Q0 values in parallel and perpendicular detector orientations is most significant for the PTW 31010 (1.8%) chamber. The percentage root‐mean‐square (%RMS) deviation between EGSnrc and PENELOPE calculated kfmsr,fref Qmsr,Q0 values for Exradin‐A1SL, A14 and A14SL chambers studies in this work was found to be 0.4%. The kfmsr,fref Qmsr,Q0 values increase linearly with electron density of the phantom material for all chamber types mainly due to the linear dependency of photon energy fluence ratios on electron density. The average percentage difference between the calculated and predicted kfmsr,fref Qmsr,Q0 values using two methods is found to be 0.15% and 0.16%. Previously measured dose rates corrected with the kfmsr,fref Qmsr,Q0 values determined in this work leads to absorbed dose values consistent to within 0.8%. Conclusions: The calculated kfmsr,fref Qmsr,Q0 values in this work will enable users to apply the appropriate correction for their own specific phantom material only knowing the electron density of the phantom material.

Detection of azaspiracids in mussels using electrochemical immunosensors for fast screening in monitoring programs - Leonardo, Sandra; Kilcoyne, Jane; Samdal, Ingunn A.; Miles, Christopher O.; O’sullivan, Ciara K.; Diogène, Jorge; Campàs, Mònica (Sensors and Actuators B: Chemical, 2018)
Given the widespread occurrence of azaspiracids (AZAs), it is clearly necessary to advance in simple and low-cost methods for the rapid detection of these marine toxins in order to protect seafood consumers. To address this need, electrochemical immunosensors for the detection of AZAs based on a competitive direct immunoassay using peroxidase-labelled AZA as a tracer were developed. An anti-AZA polyclonal antibody was immobilised in a controlled and stable manner on protein G or avidin-coated electrodes. Experimental conditions were first optimised using colorimetric immunoassays on microtitre plates, providing intermediate products already applicable to the accurate detection of AZAs. Then, transfer of the protein G and avidin–biotin interaction-based immunoassays to 8-electrode arrays provided compact and miniaturised devices for the high-throughput detection of AZAs. The low amounts of immunoreagents required as well as the potential for reusability of the avidin–biotin interaction-based immunosensors represented significant economic savings as well as a contribution to sustainability. The electrochemical immunosensors enabled the quantification of all regulated AZAs below the regulatory limit, as well as a broad range of other toxic AZA analogues (from 63 ± 3 to 2841 ± 247 μg AZA-1 equiv./kg for the protein G-based immunosensor and from 46 ± 2 to 3079 ± 358 μg AZA-1 equiv./kg for the avidin–biotin interaction-based immunosensor). The good agreement between the results obtained by the immunosensors and LC–MS/MS in the analysis of naturally contaminated mussel samples demonstrated the easy implementation of electrochemical immunosensors for routine analysis of AZAs in food safety monitoring programs.
Keywords: azaspiracid; antibody; electrochemical immunosensor; protein G; biotin; mussel

Design of narrowband Bragg spectral filters in subwavelength grating metamaterial waveguides - Čtyroký, Jiří; Gonzalo Wangüemert-Pérez, Juan; Kwiecien, Pavel; Richter, Ivan; Litvik, Ján; Schmid, Jens H.; Molina-Fernández, Íñigo; Ortega-Moñux, Alejandro; Dado, Milan; Cheben, Pavel (Optics Express, 2018)
Properties of reflection and transmission spectral filters based on Bragg gratings in subwavelength grating (SWG) metamaterial waveguides on silicon-on-insulator platform have been analyzed using proprietary 2D and 3D simulation tools based on Fourier modal method and the coupled-mode theory. We also demonstrate that the coupled Bloch mode theory can be advantageously applied to design of Bragg gratings in SWG waveguides. By combining different techniques, including judiciously positioning silicon loading segments within the evanescent field of the SWG waveguide and making use of its dispersion properties, it is possible to attain sub-nanometer spectral bandwidths for both reflection and transmission filters in the wavelength range of 1550 nm while keeping minimum structural features of the filters as large as 100 nm. Numerical simulations have also shown that a few nanometer jitter in the size and position of Si segments is well tolerated in our filter designs.

Derivatization chemistries for the determination of inorganic anions and structurally related compounds by gas chromatography: a review - Pagliano, Enea; Campanella, Beatrice; D'ulivo, Alessandro; Mester, Zoltán (Analytica Chimica Acta, 2018)
Gas chromatography (GC) methods for the determination of inorganic anions and structurally related compounds are reviewed. In their native form, such analytes are polar and non-volatile, therefore they require derivatization before GC analysis. Several chemistries have been employed to convert anions to volatile molecules with applications to a wide set of analytes: nitrite, nitrate, halides, azide, bromate, iodate, borate, carbonate, thiocyanate, cyanide, sulfide, silicates, phosphates, phosphonates, selenite, selenate, arsenite, arsenate, monomethylarsonic acid, and dimethylarsinic acid have been measured following GC separation. In this review, most derivatization chemistries employed for anions are discussed with attention to molecular aspects of the conversion, experimental conditions, applications to complex sample matrices, and figure of merits.
Keywords: inorganic anions; alkyl phosphates; phosphonates; gas chromatography; derivatization

Demonstration of analyzers for multimode photonic time-bin qubits - Jin, Jeongwan; Agne, Sascha; Bourgoin, Jean-Philippe; Zhang, Yanbao; Lütkenhaus, Norbert; Jennewein, Thomas (Physical Review A, 2018)
We demonstrate two approaches for unbalanced interferometers as time-bin qubit analyzers for quantum communication, robust against mode distortions and polarization effects as expected from free-space quantum communication systems including wavefront deformations, path fluctuations, pointing errors, and optical elements. Despite strong spatial and temporal distortions of the optical mode of a time-bin qubit, entangled with a separate polarization qubit, we verify entanglement using the Negative Partial Transpose, with the measured visibility of up to 0.85±0.01. The robustness of the analyzers is further demonstrated for various angles of incidence up to 0.2∘. The output of the interferometers is coupled into multimode fiber yielding a high system throughput of 0.74. Therefore, these analyzers are suitable and efficient for quantum communication over multimode optical channels.

Deconvolution in mass spectrometry based proteomics - Xu, Guang; Stupak, Jacek; Yang, Li; Hu, Luokai; Guo, Bo; Li, Jianjun (Rapid Communications in Mass Spectrometry, 2018)
Mass spectrometry (MS) has played a vital role across a broad range of fields and applications in proteomics. The development of high‐resolution MS has significantly advanced biology in areas such as protein structure, function, post‐translational modification and global protein dynamics. The two most widely used MS ionization techniques in proteomics are electrospray ionization (ESI) and matrix‐assisted laser desorption/ionization (MALDI). ESI typically yields multiple charge values for each molecular mass and an isotopic cluster for each nominal mass‐to‐charge (m/z) value. Although MALDI mass spectra typically contain only singly charged ions, overlapping isotope patterns can be problematic for accurate mass measurement. To overcome these challenges of overlapping isotope patterns associated with complex samples in MS‐based proteomics research, deconvolution strategies are being used. This manuscript describes a wide variety of deconvolution strategies, including de‐isotoping and de‐charging processes, deconvolution of co‐eluting isomers or peptides with different sequences in data‐dependent acquisition (DDA) and data‐independent acquisition (DIA) modes, and data analysis in intact protein mass determination, ion mobility MS, native MS, and hydrogen/deuterium exchange MS. It concludes with a discussion of future prospects in the development of bioinformatics and potential new applications in proteomics.
Keywords: Avogadro constant; Avogadro number; definition; IUPAC Physical and Biophysical Chemistry Division; mole; SI

Dark matter in ultra-diffuse galaxies in the virgo cluster from their globular cluster populations - Toloba, Elisa; Lim, Sungsoon; Peng, Eric; Sales, Laura V.; Guhathakurta, Puragra; Mihos, J. Christopher; Côté, Patrick; Boselli, Alessandro; Cuillandre, Jean-Charles; Ferrarese, Laura; Gwyn, Stephen; Lançon, Ariane; et al. (The Astrophysical Journal, 2018)
We present Keck/DEIMOS spectroscopy of globular clusters (GCs) around the ultra-diffuse galaxies (UDGs) VLSB−B, VLSB−D, and VCC615 located in the central regions of the Virgo cluster. We spectroscopically identify 4, 12, and 7 GC satellites of these UDGs, respectively. We find that the three UDGs have systemic velocities (V sys) consistent with being in the Virgo cluster, and that they span a wide range of velocity dispersions, from ~16 to ~47 km s−1, and high dynamical mass-to-light ratios within the radius that contains half the number of GCs (407^+916 -407, 21^+15 -11, 60^+65-38, respectively). VLSB−D shows possible evidence for rotation along the stellar major axis and its V sys is consistent with that of the massive galaxy M84 and the center of the Virgo cluster itself. These findings, in addition to having a dynamically and spatially (~1 kpc) off-centered nucleus and being extremely elongated, suggest that VLSB−D could be tidally perturbed. On the contrary, VLSB−B and VCC615 show no signs of tidal deformation. Whereas the dynamics of VLSB−D suggest that it has a less massive dark matter halo than expected for its stellar mass, VLSB−B and VCC615 are consistent with a ~1012 M ⊙ dark matter halo. Although our samples of galaxies and GCs are small, these results suggest that UDGs may be a diverse population, with their low surface brightnesses being the result of very early formation, tidal disruption, or a combination of the two.
Keywords: galaxies: clusters: individual (Virgo); galaxies: evolution; galaxies: formation; galaxies: individual (VLSB-B, VLSB-D, VCC615); galaxies: kinematics and dynamics

Cysteinyl leukotrienes C4 and D4 downregulate human mast cell expression of toll-like receptors 1 through 7 - Karpov, V.; Ilarraza, R.; Catalli, A.; Kulka, M. (Journal of Biological Regulators & Homeostatic Agents, 2018)
Cysteinyl leukotrienes (CysLT) are potent inflammatory lipid molecules that mediate some of the pathophysiological responses associated with asthma such as bronchoconstriction, vasodilation and increased microvascular permeability. As a result, CysLT receptor antagonists (LRA), such as montelukast, have been used to effectively treat patients with asthma. We have recently shown that mast cells are necessary modulators of innate immune responses to bacterial infection and an important component of this innate immune response may involve the production of CysLT. However, the effect of LRA on innate immune receptors, particularly on allergic effector cells, is unknown. This study determined the effect of CysLT on toll-like receptor (TLR) expression by the human mast cell line LAD2. Real-time PCR analysis determined that LTC4, LTD4 and LTE4 downregulated mRNA expression of several TLR. Specifically in human CD34+-derived human mast cells (HuMC), LTC4 inhibited expression of TLR1, 2, 4, 5, 6 and 7 while LTD4 inhibited expression of TLR1-7. Montelukast blocked LTC4-mediated downregulation of all TLR, suggesting that these effects were mediated by activation of the CysLT1 receptor (CysLT1R). Flow cytometry analysis confirmed that LTC4 downregulated surface expression of TLR2 which was blocked by montelukast. These data show that CysLT can modulate human mast cell expression of TLR and that montelukast may be beneficial for innate immune responses mediated by mast cells.

Cyclic loading testing of repaired SMA and steel reinforced concrete shear walls - Cortés-Puentes, Leonardo; Zaidi, Mohammed; Palermo, Dan; Dragomirescu, Elena (Engineering Structures, 2018)
This paper presents the results of reverse cyclic load testing of a repaired slender concrete shear wall reinforced internally with superelastic Shape Memory Alloys (SMAs) in the boundary zones within the plastic hinge region. In addition, a companion-repaired wall reinforced with deformed mild steel was also tested. Provided herein is an assessment of the performance of the repaired walls against the same set of walls previously tested in their original condition. The repair strategy included removing heavily damaged concrete within the plastic hinge region, replacing ruptured and buckled reinforcing steel, and shortening of the SMA bars in the boundary zones. High-strength, self-consolidating concrete replaced the removed concrete. The concrete above the plastic hinge region remained intact given the negligible damage (hairline cracking) of the original walls in this zone. The test results demonstrated that SMA-reinforced concrete structural components are self-centering, permitting repair of damaged areas. Furthermore, the SMA bars were re-usable for the repair application due to their capacity to reset to their original state within the range of inelastic strains of up to 6%. The repaired walls were capable of restoring the yield and ultimate lateral load capacities, but sustained lower drift capacities. The repaired SMA wall was capable of recovering the imposed lateral drifts up to 2%, after which residual displacements accumulated due to rupturing of the SMA bars in the boundary zone. The repaired walls dissipated up to 7.8% more energy than their original walls for a significant portion of the loading range. The length of the SMA bars and the presence of starter bars in the original walls were influencing factors in the location of failure of the SMA- and steel-reinforced walls.
Keywords: shape memory alloys; repair; reinforced concrete; slender shear walls; recovery capacity; energy dissipation

Current state and future prospects for liquid biofuels in Canada - Littlejohns, Jennifer; Rehmann, Lars; Murdy, Rachel; Oo, Aung; Neill, Stuart (Biofuel Research Journal, 2018)
The necessity to find renewable and low carbon fuels as a critical component of the strategy to reduce greenhouse gas emissions in Canada has caused the biofuels industry to rapidly expand. However, there is a higher capacity for the use of biofuels to replace conventional petroleum fuels in Canada than outlined by cur rent regulations and programs. A wide range of feedstocks, processes, and applications for liquid biofuels can be found in Canada at varying degrees of progress. To reach the full potential of the biofuels industry in Canada, it is important to understand the broad landscape of the biofuels industry and areas of promise. The objective of this paper is to provide a comprehensive overview of the current state of liquid biofuels in Canada. This includes national feedstock availability and conversion processes to produce liquid biofuels. Both biochemical and thermochemical processes over a wide range of technology readiness levels, from R&D to commercialization, will be included. Current industry, government, and/or academic support for these production activities will b e referenced where applicable. The transportation applications of commercially available liquid biofuels in Canada will be reviewed. Finally, comments on future prospects to boost environmental and economic competitiveness of the biofuels industry in Canada will be provided.
Keywords: biofuel feedstock; biochemical conversion; thermochemical conversion; biofuel applications; liquid biofuel; Canada

Crosslinked chitosan networks as binders for silicon/graphite composite electrodes in Li-oon batteries - Zhao, Xiuyun; Yim, Chae-Ho; Du, Naiying; Abu-Lebdeh, Yaser (Journal of The Electrochemical Society, 2018)
Silicon/graphite composites have the potential to improve the practical energy density of Li-ion batteries to enable mass-market penetration of electric vehicles. However, they require polymeric binders that are compatible with both silicon and graphite and can sustain alloying and intercalation reactions as well as the associated interfacial reactions. In this work, chitosan, a natural cellulose, is crosslinked with either molecular (citric acid) or polymeric (poly (acrylic acid), PAA) carboxylic acids to form networks with maximum interaction with the composite as evidenced by infrared spectroscopy. Li-ion half-cells of graphite-rich, silicon/graphite negative electrodes using crosslinked chitosan binders show higher initial Coulombic efficiency (ICE) and more stable cycling performance than pristine chitosan. This could be due to the polymeric network produced from the crosslinking reaction between chitosan and carboxyl acids as well as the strong interactions between polymeric network and surface of silicon and graphite as evidenced by adhesion tests. The crosslinked chitosan network can effectively accommodate large volume change of silicon particles and keep other electrode components connected during cycling as evidenced by scanning electron microscope (SEM) images leading to excellent cycling stability. This makes it very attractive for use as a binder in Si/graphite electrodes for Li-ion batteries.
Keywords: binders; Li-ion battery; silicon-graphite composite

Coupled electrochemical and thermal battery models for thermal management of prismatic automotive cells - Darcovich, K.; Macneil, D. D.; Recoskie, S.; Kenney, B. (Applied Thermal Engineering, 2018)
This study combines a two-dimensional Ohm’s law finite-volume approach determining the current distribution in prismatic battery cells with a simplified electrochemical model for the thermal state of automotive battery packs. The objective was to develop a simulation tool for assessing the effect of cooling effort applied to automotive battery packs under real-life usage conditions. The Ohm’s law model was enhanced by imparting a chemical and physical basis to source terms previously found empirically. This simulation was applied to 2D electrode sheets, determining thermal generation values that were mapped volumetrically into a thermal simulation, which in turn, updated the electrochemical simulation. Battery parameters, along with capacity fade kinetics were determined by fitting experimental data to simulated results. Dynamometer data from tests under reference drive cycles provided current demands on battery cells. Thermal profiles simulated for 30 A h prismatic cells at different cooling levels. Passive and forced air cooling simulations both gave endpoint temperatures upwards of 40 °C (313 K), considered excessive for preserving the battery life. A simulation scenario which reflected a liquid cooling system kept the temperature gain for a US06 drive cycle to about 2 K. With liquid cooling, an automotive battery is better protected against thermally driven degradation.
Keywords: battery simulation; prismatic cell; single-particle model; thermal model; drive cycles

Core–shell titanium dioxide–titanium nitride nanotube arrays with near-infrared plasmon resonances - Farsinezhad, Samira; Shanavas, Thariq; Mahdi, Najia; Askar, Abdelrahman M.; Kar, Piyush; Sharma, Himani; Shankar, Karthik (Nanotechnology, 2018)
Titanium nitride (TiN) is a ceramic with high electrical conductivity which in nanoparticle form, exhibits localized surface plasmon resonances (LSPRs) in the visible region of the solar spectrum. The ceramic nature of TiN coupled with its dielectric loss factor being comparable to that of gold, render it attractive for CMOS polarizers, refractory plasmonics, surface-enhanced Raman scattering and a whole host of sensing applications. We report core–shell TiO2–TiN nanotube arrays exhibiting LSPR peaks in the range 775–830 nm achieved by a simple, solution-based, low cost, large area-compatible fabrication route that does not involve laser-writing or lithography. Self-organized, highly ordered TiO2 nanotube arrays were grown by electrochemical anodization of Ti thin films on fluorine-doped tin oxide-coated glass substrates and then conformally coated with a thin layer of TiN using atomic layer deposition. The effects of varying the TiN layer thickness and thermal annealing on the LSPR profiles were also investigated. Modeling the TiO2–TiN core–shell nanotube structure using two different approaches, one employing effective medium approximations coupled with Fresnel coefficients, resulted in calculated optical spectra that closely matched the experimentally measured spectra. Modeling provided the insight that the observed near-infrared resonance was not collective in nature, and was mainly attributable to the longitudinal resonance of annular nanotube-like TiN particles redshifted due to the presence of the higher permittivity TiO2 matrix. The resulting TiO2–TiN core–shell nanotube structures also function as visible light responsive photocatalysts, as evidenced by their photoelectrochemical water-splitting performance under light emitting diode illumination using 400, 430 and 500 nm photons.

Cooling aerosols and changes in albedo counteract warming from CO2 and black carbon from forest bioenergy in Norway - Arvesen, Anders; Cherubini, Francesco; Del Alamo Serrano, Gonzalo; Astrup, Rasmus; Becidan, Michael; Belbo, Helmer; Goile, Franziska; Grytli, Tuva; Guest, Geoffrey; Lausselet, Carine; Rørstad, Per Kristian; Rydså, Line; et al. (Scientific Reports, 2018)
Climate impacts of forest bioenergy result from a multitude of warming and cooling effects and vary by location and technology. While past bioenergy studies have analysed a limited number of climate-altering pollutants and activities, no studies have jointly addressed supply chain greenhouse gas emissions, biogenic CO2 fluxes, aerosols and albedo changes at high spatial and process detail. Here, we present a national-level climate impact analysis of stationary bioenergy systems in Norway based on wood-burning stoves and wood biomass-based district heating. We find that cooling aerosols and albedo offset 60–70% of total warming, leaving a net warming of 340 or 69 kg CO2e MWh−1 for stoves or district heating, respectively. Large variations are observed over locations for albedo, and over technology alternatives for aerosols. By demonstrating both notable magnitudes and complexities of different climate warming and cooling effects of forest bioenergy in Norway, our study emphasizes the need to consider multiple forcing agents in climate impact analysis of forest bioenergy.

Controlling high harmonic generation in tailored semiconductors - Taucer, Marco; Sivis, Murat; Vampa, Giulio; Johnston, Kyle; Staudte, André; Naumov, Andrei Yu.; Villeneuve, David M.; Ropers, Claus; Corkum, Paul B. (Conference on Lasers and Electro-Optics, 2018)
The solid state opens new possibilities for the generation of high harmonics extending to the extreme ultraviolet. Additionally, an array of tools and techniques exists for straightforward fabrication of solid-state devices, with nanoscale precision. In this work, we explore new ways to control high-harmonic emission in semiconductors using nanofabrication. We measure high-harmonic emission from tailored silicon and zinc oxide targets, up to the ninth order of the fundamental driving frequency (corresponding to a wavelength of ~225 nm). Morphology and local composition can each localize and enhance emission. We utilize this control to demonstrate prototype devices which simultaneously emit and focus harmonic radiation.

Contribution of model predictive control in the integration of renewable energy sources within the built environment - Stadler, Paul; Girardin, Luc; Ashouri, Araz; Maréchal, François (Frontiers in Energy Research, 2018)
Integrating intermittent renewable energy sources has renders the power network operator task of balancing electricity generation and consumption increasingly challenging. Aside from heavily investing in additional storage capacities, an interesting solution might be the use predictive control methods to shift controllable loads toward production periods. Therefore, this article introduces a systematic approach to provide a preliminary evaluation of the thermoeconomic impact of model predictive control (MPC) when being applied to modern and complex building energy systems (BES). The proposed method applies an ϵ-constraint multi-objective optimization to generate a large panel of different BES configurations and their respective operating strategies. The problem formulation relies on a holistic BES framework to satisfy the different building service requirements using a mixed-integer linear programming technique. To illustrate the contribution of MPC, different applications on the single- and multi-dwelling level are presented and analyzed. The results suggest that MPC can facilitate the integration of renewable energy sources within the built environment by adjusting the heating and cooling demand to the fluctuating renewable generation, increasing the share of self-consumption by up to 27% while decreasing the operating expenses by up to 3% on the single-building level. Finally, a preliminary assessment of the national-wide potential is performed by means of an extended implementation on the Swiss building stock.

Concomitant reduction of lactate and ammonia accumulation in fed-batch cultures: impact on glycoprotein production and quality - Karengera, Eric; Robotham, Anna; Kelly, John; Durocher, Yves; De crescenzo, Gregory; Henry, Olivier (Biotechnology Progress, 2018)
Lactate and ammonia accumulation is a major factor limiting the performance of fed‐batch strategies for mammalian cell culture processes. In addition to the detrimental effects of these by‐products on production yield, ammonia also contributes to recombinant glycoprotein quality deterioration. In this study, we tackled the accumulation of these two inhibiting metabolic wastes by culturing in glutamine‐free fed‐batch cultures an engineered HEK293 cell line displaying an improved central carbon metabolism. Batch cultures highlighted the ability of PYC2‐overexpressing HEK293 cells to grow and sustain a relatively high viability in absence of glutamine without prior adaptation to the culture medium. In fed‐batch cultures designed to maintain glucose at high concentration by daily feeding a glutamine‐free concentrated nutrient feed, the maximum lactate and ammonia concentrations did not exceed 5 and 1 mM, respectively. In flask, this resulted in more than a 2.5‐fold increase in IFNα2b titer in comparison to the control glutamine‐supplied fed‐batch. In bioreactor, this strategy led to similar reductions in lactate and ammonia accumulation and an increase in IFNα2b production. Of utmost importance, this strategy did not affect IFNα2b quality with respect to sialylation and glycoform distribution as confirmed by surface plasmon resonance biosensing and LC‐MS, respectively. Our strategy thus offers an attractive and simple approach for the development of efficient cell culture processes for the mass production of high‐quality therapeutic glycoproteins.

Computational aeroelastic analysis using an enhanced OpenFOAM-based CFD-CSD solver - Fereidooni, Amin; Grewal, Anant K.; Seraj, Sabet; Grzeszczyk, Marcel (2018 AIAA/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference, 2018)
In this paper, the development of a coupled solver suitable for the simulation of unsteady transonic aerodynamicow is described. The OpenFOAM baseline segregated solver, rho-CentralFoam, is modied to produce an implicit Euler formulation where the conservation of mass, momentum and energy equations are solved in a coupled manner. The key modication centers on the construction of the convectiveux Jacobian matrix and the application of the Lower-Upper Symmetric Gauss-Seidel algorithm to solve the resultant matrix. The developed aerodynamic solver is then coupled with a modied OpenFOAM structural solver sixDoFRigidBodyMotion to formulate a full aeroelastic model. This model is veried through the simulation of two benchmark problems: a pitching and uttering 2D NACA64A010 airfoil, and the Benchmark Supercritical Wing (BSCW) from the second AIAA Aeroelastic Prediction Workshop (AePW-2). In all cases, the numerical solutions of the Euler equations show good agreement with the available numerical and experimental data.

Compositing doped-carbon with metals, non-metals, metal oxides, metal nitrides and other materials to form bifunctional electrocatalysts to enhance metal-air battery oxygen reduction and evolution reactions - Wang, Yan-Jie; Fan, Hongbo; Ignaszak, Anna; Zhang, Lei; Shao, Siqin; Wilkinson, David P.; Zhang, Jiujun (Chemical Engineering Journal, 2018)
Rechargeable metal-air batteries (MABs) have gained renewed attention because of their feasibility as electrochemical energy storage/conversion devices. Although MABs possess drastically higher theoretical energy densities than traditional aqueous or lithium-ion batteries, the development and commercialization of MABs have been challenged considerably due to the lack of efficient and robust air-electrode electrocatalysts which are used for both oxygen reduction reactions (ORR) and oxygen evolution reactions (OER). To improve the bifunctional activity and stability of these electrocatalysts, doped-carbon composite catalysts have been explored as one type of modified electrode and have demonstrated great potential toward MAB applications due to the synergistic interactions between the dopant(s), carbon, and other noncarbon component(s). This article reviews the progresses and advancements in the development of various doped-carbon composite bifunctional catalysts for MAB cathodes with an emphasis on material selection, structural characterization and electrochemical properties, as well as their applications in MABs. This review provides developmental details that will benefit readers from both academia and industry.
Keywords: rechargeable metal-air batteries; air-electrode electrocatalysts; oxygen reduction reactions; oxygen evolution reactions; bifunctional; doped-carbon

Complementary methods for the determination of the just-suspended speed and suspension state in a viscous solid–liquid mixing system - Bertrand, Olivier; Blais, Bruno; Bertrand, François; Fradette, Louis (Chemical Engineering Research and Design, 2018)
A poor understanding of mixing dynamics may lead to major economic losses in numerous industries due to poor yields and waste of raw materials. Then processes can be optimized through a better understanding of solid–liquid mixing dynamics. Previous studies have characterized the suspension of solid particles in a viscous medium using a standard high shear impeller (a pitched-blade turbine or PBT) and have measured the fraction of suspended particles using the pressure gauge technique (PGT). Since the PGT cannot be applied in a straightforward way to close-clearance impellers, we developed a novel technique based on the PGT to determine the fraction of suspended particles in a system using a close-clearance impeller such as a double helical ribbon (DHR). We studied a solid–liquid suspension in the laminar and transitional regimes with high particle loadings and a DHR. Since the dynamic pressure cannot be subtracted from the total pressure determined by the PGT, we developed two alternative methods. The first was the pressure difference method, which we used to determine a range of speeds where Njs is located. The second was the sedimentation-based method which we used to accurately quantify Njs and effectively eliminate the dynamic pressure. Their pertinence and applicability were demonstrated.
Keywords: solid–liquid mixing; viscous fluids; non-dilute suspensions; mechanically agitated vessel; just-suspended speed; sedimentation

Combined laser-induced breakdown spectroscopy and MIR quantum cascade laser reflectance spectroscopy for elemental and molecular characterization - Vanier, Francis; Padioleau, Christian; Sabsabi, Mohamad; Blouin, Alain (Conference on Lasers and Electro-Optics, 2018)
We combine laser-based mid-infrared reflectance measurements using tunable quantum cascade lasers and laser-induced breakdown spectroscopy to get both the elemental and molecular compositions of a sample. Results for mineral ore characterization are shown.

Cognitive biases within decision making during fire evacuations - Kinsey, M. J.; Gwynne, S. M. V.; Kuligowski, E. D.; Kinateder, M. (Fire Technology, 2018)
During a fire evacuation, once an individual perceives cues from a fire event, they must interpret them to assess the new situation and determine whether action is required. It is proposed that this assessment and action selection can employ either an automatic or reflective processing system depending on the nature of the situation and the experiences of the individual involved. This decision-making process is bounded in terms of the information available, the time available, and an individual’s resources to process such information that influences which processing mechanism is adopted. To compensate for such limitations and manage the uncertainty and complexity associated with the decision-making process, people may employ heuristics that reduce decision-making from a cognitively effortful problem-solving task requiring mental reflection, to a less effortful pattern-matching process, where stored conditions and expectations are quickly scanned to identify relevant responses. During this decision-making process cognitive biases may occur which cause an individual to neglect or be biased towards certain information: this may potentially lead to an inappropriate and/or unexpected response. Cognitive biases affect performance without the individual being directly aware of them. This paper identifies cognitive biases from existing literature that may influence a person’s decision-making process during a fire evacuation, along with how these align with general decision-making in the process. The purpose of the article is to promote consideration of cognitive biases in the modeling of evacuee behavior, as well as during the fire safety design of buildings and evacuation procedures.
Correction to: Cognitive Biases Within Decision Making During Fire Evacuations, at https://doi.org/10.1007/s10694-018-0722-2
Keywords: decision-making; evacuation; human factors; cognitive bias

Cloud access to interoperable IVOA-compliant VOSpace storage - Bertocco, S.; Dowler, P.; Gaudet, S.; Major, B.; Pasian, F.; Taffoni, G. (Astronomy and Computing, 2018)
Handling, processing and archiving the huge amount of data produced by the new generation of experiments and instruments in Astronomy and Astrophysics are among the more exciting challenges to address in designing the future data management infrastructures and computing services. We investigated the feasibility of a data management and computation infrastructure, available world-wide, with the aim of merging the FAIR1 data management provided by IVOA standards with the efficiency and reliability of a cloud approach. Our work involved the Canadian Advanced Network for Astronomy Research (CANFAR) infrastructure and the European EGI federated cloud (EFC). We designed and deployed a pilot data management and computation infrastructure that provides IVOA-compliant VOSpace storage resources and wide access to interoperable federated clouds. In this paper, we detail the main user requirements covered, the technical choices and the implemented solutions and we describe the resulting Hybrid cloud Worldwide infrastructure, its benefits and limitations.
Keywords: IVOA; Virtual observatory; cloud; interoperability; distributed services; VOSpace

CIPK9 is involved in seed oil regulation in Brassica napus L. and Arabidopsis thaliana (L.) Heynh. - Guo, Yanli; Huang, Yi; Gao, Jie; Pu, Yuanyuan; Wang, Nan; Shen, Wenyun; Wen, Jing; Yi, Bin; Ma, Chaozhi; Tu, Jinxing; Fu, Tingdong; Zou, Jitao; et al. (Biotechnology for Biofuels, 2018)
Background: Accumulation of storage compounds during seed development plays an important role in the life cycle of oilseed plants; these compounds provide carbon and energy resources to support the establishment of seedlings. Results: In this study, we show that BnCIPK9 has a broad expression pattern in Brassica napus L. tissues and that wounding stress strongly induces its expression. The overexpression of BnCIPK9 during seed development reduced oil synthesis in transgenic B. napus compared to that observed in wild-type (WT) plants. Functional analysis revealed that seed oil content (OC) of complementation lines was similar to that of WT plants, whereas OC in Arabidopsis thaliana (L.) Heynh. Atcipk9 knockout mutants (cipk9) was higher than that of WT plants. Seedling of cipk9 mutants failed to establish roots on a sugar-free medium, but root establishment could be rescued by supplementation of sucrose or glucose. The phenotype of complementation transgenic lines was similar to that of WT plants when grown on sugar-free medium. Mutants, cipk9, cbl2, and cbl3 presented similar phenotypes, suggesting that CIPK9, CBL2, and CBL3 might work together and play similar roles in root establishment under sugar-free condition. Conclusion: This study showed that BnCIPK9 and AtCIPK9 encode a protein kinase that is involved in sugar-related response and plays important roles in the regulation of energy reserves. Our results suggest that AtCIPK9 negatively regulates lipid accumulation and has a significant effect on early seedling establishment in A. thaliana. The functional characterization of CIPK9 provides insights into the regulation of OC, and might be used for improving OC in B. napus. We believe that our study makes a significant contribution to the literature because it provides information on how CIPKs coordinate stress regulation and energy signaling.
Keywords: brassica napus L.; seed oil content; CIPK9; sucrose; seedling establishment; arabidopsis thaliana

Characterizing bacterial glycoproteins with LC-MS - Fulton, Kelly M.; Li, Jianjun; Tomas, Juan M.; Smith, Jeffrey C.; Twine, Susan M. (Expert Review of Proteomics, 2018)
Introduction: Though eukaryotic glycoproteins have been studied since their discovery in the 1930s, the first bacterial glycoprotein was not identified until the 1970s. As a result, their role in bacterial pathogenesis is still not well understood and they remain an understudied component of bacterial virulence. In recent years, mass spectrometry has emerged as a leading technology for the study of bacterial glycoproteins, largely due to its sensitivity and versatility. Areas covered: Identification and comprehensive characterization of bacterial glycoproteins usually requires multiple complementary mass spectrometry approaches, including intact protein analysis, top-down analysis, and bottom-up methods used in combination with specialized liquid chromatography. This review provides an overview of liquid chromatography separation technologies, as well as current and emerging mass spectrometry approaches used specifically for bacterial glycoprotein identification and characterization. Expert commentary: Bacterial glycoproteins may have significant clinical utility as a result of their unique structures and exposure on the surface of the cells. Better understanding of these glycoconjugates is an essential first step towards that goal. These often unique structures, and by extension the key enzymes involved in their synthesis, represent promising targets for novel antimicrobials, while unique carbohydrate structures may be used as antigens in vaccines or as biomarkers.
Keywords: mass spectrometry; liquid chromatography; glycoprotein; glycopeptide; bacterial glycoprotein; glycan; host-pathogen interactions; antimicrobials; vaccines

Characterization of molecular attributes that influence LINE-1 restriction by all seven human APOBEC3 proteins - Renner, Tyler Milston; Bélanger, Kasandra; Goodwin, Laura Rose; Campbell, Mark; Langlois, Marc-André (Virology, 2018)
LINE-1 (L1) is a non-long terminal repeat (LTR) retrotransposon inserted throughout the human genome. APOBEC3 (A3) proteins are part of a network of host intrinsic defenses capable of restricting retroviruses and the replication of L1 retroelements. These enzymes inactivate retroviruses primarily through deamination of single-stranded viral DNA. In contrast, only A3A deaminates L1 DNA, while the other six A3 proteins restrict L1 to varying degrees through yet poorly defined mechanisms. Here we provide further insight into the molecular attributes of L1 restriction by A3 proteins. We specifically investigated the roles of A3 protein oligomerization, interactions with RNA and their binding to the various L1 proteins. Our results show that compromising the ability of A3 proteins to oligomerize or interact with a nucleic acid substrate diminished L1 restriction to varying degrees. However the efficiency of their binding to L1 proteins did not predict restriction or the potency of the restriction.
Keywords: APOBEC3; LINE-1; ORF0p; ORF1p; ORF2p; intrinsic immunity; retroviral restriction factors; retroelements

Characterization of machinability and environmental impact of cryogenic turning of Ti-6Al-4V - Damir, A.; Sadek, A.; Attia, H. (Procedia CIRP, 2018)
Titanium alloys are widely used in aerospace applications due to their physical and mechanical properties. However, their poor machinability remains the main challenge to improve the productivity and the surface quality. Cryogenic machining recently gained interest as a clean and economical cooling technique. It becomes a promising candidate for applications that involve aggressive metal removal, especially for hard-to-cut material. This research provides insight into the cryogenic machining performance compared to flood machining in terms of its effect on tool life, surface quality, cutting forces and environmental impact. For such analysis, turning tests of Ti-6Al-4V using cryogenic and flood technologies were conducted at different cutting conditions. Life cycle analysis was conducted using the Eco-indicator method to compare the environmental impact of each technology. The cryogenic technology significantly improved the process environmental performance in addition to enhancing the tool life and surface quality compared to flood, hence improved the process productivity.
Keywords: life Cycle analysis; cryogenic Machining; environmental impact; titanium alloy

Capillary electrophoresis–tandem mass spectrometry for multiclass analysis of polar marine toxins - Beach, Daniel G.; Kerrin, Elliott S.; Thomas, Krista; Quilliam, Michael A.; Mccarron, Pearse (Analytical and Bioanalytical Chemistry, 2018)
Polar marine toxins are more challenging to analyze by mass spectrometry-based methods than lipophilic marine toxins, which are now routinely measured in shellfish by multiclass reversed-phase liquid chromatography–tandem mass spectrometry (MS/MS) methods. Capillary electrophoresis (CE)–MS/MS is a technique that is well suited for the analysis of polar marine toxins, and has the potential of providing very high resolution separation. Here, we present a CE–MS/MS method developed, with use of a custom-built interface, for the sensitive multiclass analysis of paralytic shellfish toxins, tetrodotoxins, and domoic acid in seafood. A novel, highly acidic background electrolyte (5 M formic acid) was designed to maximize protonation of analytes and to allow a high degree of sample stacking to improve the limits of detection. The method was applied to a wide range of regulated and less common toxin analogues, and exhibited a high degree of selectivity between toxin isomers and matrix interference. The limits of detection in mussel tissue were 0.0052 mg/kg for tetrodotoxins, 0.160 mg/kg for domoic acid, and between 0.0018 and 0.120 mg/kg for paralytic shellfish toxins, all of which showed good linearity. Minimal ionization suppression was observed when the response from neat and mussel-matrix-matched standards was corrected with multiple internal standards. Analysis of shellfish matrix reference materials and spiked samples demonstrated good accuracy and precision. Finally, the method was transferred to a commercial CE–MS/MS system to demonstrate its widespread applicability for use in both R & D and routine regulatory settings. The approach of using a highly acidic background electrolyte is of broad interest, and can be considered generally applicable to simultaneous analysis of other classes of small, polar molecules with differing pKa values.
Keywords: biotoxins; tetrodotoxin; paralytic shellfish poisoning; domoic acid; harmful algal bloom; capillary electrophoresis

Canola root–associated microbiomes in the Canadian Prairies - Lay, Chih-Ying; Bell, Terrence H.; Hamel, Chantal; Harker, K. Neil; Mohr, Ramona; Greer, Charles W.; Yergeau, Étienne; St-Arnaud, Marc (Frontiers in Microbiology, 2018)
Canola is one of the most economically important crops in Canada, and the root and rhizosphere microbiomes of a canola plant likely impact its growth and nutrient uptake. The aim of this study was to determine whether canola has a core root microbiome (i.e., set of microbes that are consistently selected in the root environment), and whether this is distinct from the core microbiomes of other crops that are commonly grown in the Canadian Prairies, pea, and wheat. We also assessed whether selected agronomic treatments can modify the canola microbiome, and whether this was associated to enhanced yield. We used a field experiment with a randomized complete block design, which was repeated at three locations across the canola-growing zone of Canada. Roots and rhizosphere soil were harvested at the flowering stage of canola. We separately isolated total extractable DNA from plant roots and from adjacent rhizosphere soil, and constructed MiSeq amplicon libraries for each of 60 samples, targeting bacterial, and archaeal 16S rRNA genes and the fungal ITS region. We determined that the microbiome of the roots and rhizosphere of canola was consistently different from those of wheat and pea. These microbiomes comprise several putative plant-growth-promoting rhizobacteria, including Amycolatopsis sp., Serratia proteamaculans, Pedobacter sp., Arthrobacter sp., Stenotrophomonas sp., Fusarium merismoides, and Fusicolla sp., which correlated positively with canola yield. Crop species had a significant influence on bacterial and fungal assemblages, especially within the roots, while higher nutrient input or seeding density did not significantly alter the global composition of bacterial, fungal, or archaeal assemblages associated with canola roots. However, the relative abundance of Olpidium brassicae, a known pathogen of members of the Brassicaceae, was significantly reduced in the roots of canola planted at higher seeding density. Our results suggest that seeding density and plant nutrition management modified the abundance of other bacterial and fungal taxa forming the core microbiomes of canola that are expected to impact crop growth. This work helps us to understand the microbial assemblages associated with canola grown under common agronomic practices and indicates microorganisms that can potentially benefit or reduce the yield of canola.

Brown and black carbon emitted by a marine engine operated on heavy fuel oil and distillate fuels: optical properties, size distributions, and emission factors - Corbin, J. C.; Pieber, S. M.; Czech, H.; Zanatta, M.; Jakobi, G.; Massabò, D.; Orasche, J.; El haddad, I.; Mensah, A. A.; Stengel, B.; Drinovec, L.; Mocnik, G.; et al. (Journal of Geophysical Research: Atmospheres, 2018)
We characterized the chemical composition and optical properties of particulate matter (PM) emitted by a marine diesel engine operated on heavy fuel oil (HFO), marine gas oil (MGO), and diesel fuel (DF). For all three fuels, ∼80% of submicron PM was organic (and sulfate, for HFO at higher engine loads). Emission factors varied only slightly with engine load. Refractory black carbon (rBC) particles were not thickly coated for any fuel; rBC was therefore externally mixed from organic and sulfate PM. For MGO and DF PM, rBC particles were lognormally distributed in size (mode at drBC≈120 nm). For HFO, much larger rBC particles were present. Combining the rBC mass concentrations with in situ absorption measurements yielded an rBC mass absorption coefficient MACBC,780nm of 7.8 ± 1.8 m2/g at 780 nm for all three fuels. Using positive deviations of the absorption Ångström exponent (AAE) from unity to define brown carbon (brC), we found that brC absorption was negligible for MGO or DF PM (AAE(370,880 nm)≈1.0 ± 0.1) but typically 50% of total 370‐nm absorption for HFO PM. Even at 590 nm, ∼20  of the total absorption was due to brC. Using absorption at 880 nm as a reference for BC absorption and normalizing to organic PM mass, we obtained a MACOM,370nm of 0.4 m2/g at typical operating conditions. Furthermore, we calculated an imaginary refractive index of (0.045 ± 0.025)(λ/370nm)−3 for HFO PM at 370 nm>λ > 660 nm, more than twofold greater than previous recommendations. Climate models should account for this substantial brC absorption in HFO PM.

Bright single InAsP quantum dots at telecom wavelengths in position-controlled InP nanowires: the role of the photonic waveguide - Haffouz, Sofiane; Zeuner, Katharina D.; Dalacu, Dan; Poole, Philip J.; Lapointe, Jean; Poitras, Daniel; Mnaymneh, Khaled; Wu, Xiaohua; Couillard, Martin; Korkusinski, Marek; Schöll, Eva; Jöns, Klaus D.; et al. (Nano Letters, 2018)
We report on the site-selected growth of bright single InAsP quantum dots embedded within InP photonic nanowire waveguides emitting at telecom wavelengths. We demonstrate a dramatic dependence of the emission rate on both the emission wavelength and the nanowire diameter. With an appropriately designed waveguide, tailored to the emission wavelength of the dot, an increase in the count rate by nearly 2 orders of magnitude (0.4 to 35 kcps) is obtained for quantum dots emitting in the telecom O-band, showing high single-photon purity with multiphoton emission probabilities down to 2%. Using emission-wavelength-optimized waveguides, we demonstrate bright, narrow-line-width emission from single InAsP quantum dots with an unprecedented tuning range of 880 to 1550 nm. These results pave the way toward efficient single-photon sources at telecom wavelengths using deterministically grown InAsP/InP nanowire quantum dots.
Keywords: chemical beam epitaxy; epitaxial growth; nanowire; photoluminescence; quantum dot; selective growth; single-photon source; vapor−liquid−solid

Bibliometric analysis of global research trends on microbial fuel cells using Scopus database - Md Khudzari, Jauharah; Kurian, Jiby; Tartakovsky, Boris; Raghavan, G.S.Vijaya (Biochemical Engineering Journal, 2018)
The rising demand for sustainable energy and the availability of abundant wastes have stimulated research efforts around the world. As a newly emerging energy-based technology, microbial fuel cell (MFC) has received a significant attention due to its broad range of applications. Therefore, understanding the topics of interest and broadening collaboration networks are necessary to advance the research development towards integrated efforts. In this bibliometric study, our aim was to evaluate the global research trends in MFC area based on publication outputs, co-authorships among authors and affiliated countries, and co-occurrences of author keywords. Using the Scopus database, a total of 4126 journal articles published between 1962–2017 were retrieved. Results have shown that since 2008, the number of publications increased by 100 articles every two years, resulting in the steady increase in the cumulative total publications until present. About 60% of the global total publications were contributed by researchers from China and USA, leading the other 70 countries/territories. Also, among the most productive university from each of the 15 leading countries, four were amongst the world’s top 100 universities. In conclusion, recent progress in MFC research includes the following (but not limited to) (i) electrode materials incorporated nanotechnology, ceramic, and biochar; (ii) mathematical modeling (e.g. artificial neural network); and (iii) economic assessment and life cycle analysis.
Keywords: bibliometric analysis; author keyword co-occurrences; co-authorship; microbial fuel cell; VOSviewer; scopus database

Behavior of selenium hydride in heated quartz tube and dielectric barrier discharge atomizers - Kratzer, Jan; Musil, Stanislav; Marschner, Karel; Svoboda, Milan; Matoušek, Tomáš; Mester, Zoltán; Sturgeon, Ralph E.; Dědina, Jiří (Analytica Chimica Acta, 2018)
Atomization of SeH2 in an externally heated multiple microflame quartz tube atomizer (MMQTA) as well as planar dielectric barrier discharge (DBD) atomizer was investigated using a variety of probes. Deposits of Se on inner surfaces of the atomizers were quantified and their distribution visualized by autoradiography with 75Se radiotracer. The gas phase fraction of Se transported beyond the confines of the atomizers was also determined. In the MMQTA, a 15% mass fraction of Se was deposited in a narrow zone at both colder ends of the optical arm (100–400 °C). By contrast, a 25-40% mass fraction of Se was deposited homogeneously along the entire length of the optical arm of the DBD, depending on detection technique employed. The fraction of Se transported outside the MMQTA approached 90%, whereas it was 50–70% in the DBD. The presence of H2 was essential for atomization of selenium hydride in both atomizers. The gaseous effluent arising from the hydride generator as well as the atomizers was investigated by direct analysis in real time (DART) coupled to an Orbitrap-mass spectrometer, enabling identification of major gas phase species of Se.
Keywords: hydride generation; selenium; dielectric barrier discharge; quartz tube atomizer; atomization mechanism

Automated data processing architecture for the Gemini Planet Imager Exoplanet Survey - Wang, Jason J.; Perrin, Marshall D.; Savransky, Dmitry; Arriaga, Pauline; Chilcote, Jeffrey K.; De Rosa, Robert J.; Millar-Blanchaer, Maxwell A.; Marois, Christian; Rameau, Julien; Wolff, Schuyler G.; Shapiro, Jacob; Ruffio, Jean-Baptiste; et al. (Journal of Astronomical Telescopes, Instruments, and Systems, 2018)
The Gemini Planet Imager Exoplanet Survey (GPIES) is a multiyear direct imaging survey of 600 stars to discover and characterize young Jovian exoplanets and their environments. We have developed an automated data architecture to process and index all data related to the survey uniformly. An automated and flexible data processing framework, which we term the Data Cruncher, combines multiple data reduction pipelines (DRPs) together to process all spectroscopic, polarimetric, and calibration data taken with GPIES. With no human intervention, fully reduced and calibrated data products are available less than an hour after the data are taken to expedite follow up on potential objects of interest. The Data Cruncher can run on a supercomputer to reprocess all GPIES data in a single day as improvements are made to our DRPs. A backend MySQL database indexes all files, which are synced to the cloud, and a front-end web server allows for easy browsing of all files associated with GPIES. To help observers, quicklook displays show reduced data as they are processed in real time, and chatbots on Slack post observing information as well as reduced data products. Together, the GPIES automated data processing architecture reduces our workload, provides real-time data reduction, optimizes our observing strategy, and maintains a homogeneously reduced dataset to study planet occurrence and instrument performance.

A-type stellar abundances: a corollary to Herschel observations of debris disks - Draper, Zachary H.; Matthews, Brenda; Venn, Kim; Lambert, David; Kennedy, Grant; Sitnova, Tatyana (The Astrophysical Journal, 2018)
In order to assess the relationship between metallicity and exoplanetary systems, we compare the abundances of AF-type main-sequence stars with debris disk properties assessed using Herschel observations of an unbiased survey of nearby stars. Hot stars are not as commonly observed, given their unique constraints in data reduction, lack of metal lines, and "astrophysical noise" from rotation speed. Here, we address that deficiency using new and archival spectra of 83 AF-type stars. We measure the abundances of a few species in addition to Fe in order to classify the stars with Ap/Am or Lambda Boo signatures. Lambda Boo stars have a chemical signature of solar-abundant volatile species and sub-solar refractory abundances that is hypothesized to be altered by the pollution of volatiles. Overall, we see no correlation between debris disks and metallicity, primarily because the sample size is cut significantly when using only reliable fits to the spectroscopic data. The abundance measured from the Mg ii 4481 blend is a useful diagnostic because it can be reliably measured at large vcenterdotsin(i) and is found to be lower around stars with bright debris disks. We find that Lambda Boo stars have brighter debris disks compared to a bias-free sample of AF stars. The trend with disk brightness and Mg abundances suggests pollution effects can be significant and used as a marker for the stability of planetary systems. We explore trends with other species, such as with the C/O ratios, but are significantly limited by the low number of reliable detections.
Keywords: circumstellar matter; planet–disk interactions; stars: abundances

Attosecond science - Villeneuve, D. M. (Contemporary Physics, 2018)
Scientists have been developing sources of light with ever-shorter pulse durations, in order to study motion in systems ranging from a golfer’s swing to the motion of atoms within molecules. The shortest pulses produced to date are under 60 attoseconds, i.e. 60×10 −18 s. One attosecond is to one second as one second is to the age of the universe. For comparison, the classical orbital period of an electron in a hydrogen atom is 150 attoseconds. Attosecond pulses were first produced in 2001. This article describes how attosecond pulses are generated and how they are measured. Some applications of attosecond pulses are described, such as measuring the delay in photoionisation, or observing molecular dissociation dynamics.
Keywords: attosecond; femtosecond; high harmonic generation; photoionisation; transient absorption

Arabidopsis ICK/KRP cyclin-dependent kinase inhibitors function to ensure the formation of one megaspore mother cell and one functional megaspore per ovule - Cao, Ling; Wang, Sheng; Venglat, Prakash; Zhao, Lihua; Cheng, Yan; Ye, Shengjian; Qin, Yuan; Datla, Raju; Zhou, Yongming; Wang, Hong; Qu, Li-Jia (PLOS Genetics, 2018)
In most plants, the female germline starts with the differentiation of one megaspore mother cell (MMC) in each ovule that produces four megaspores through meiosis, one of which survives to become the functional megaspore (FM). The FM further develops into an embryo sac. Little is known regarding the control of MMC formation to one per ovule and the selective survival of the FM. The ICK/KRPs (interactor/inhibitor of cyclin-dependent kinase (CDK)/Kip-related proteins) are plant CDK inhibitors and cell cycle regulators. Here we report that in the ovules of Arabidopsis mutant with all seven ICK/KRP genes inactivated, supernumerary MMCs, FMs and embryo sacs were formed and the two embryo sacs could be fertilized to form two embryos with separate endosperm compartments. Twin seedlings were observed in about 2% seeds. Further, in the mutant ovules the number and position of surviving megaspores from one MMC were variable, indicating that the positional signal for determining the survival of megaspore was affected. Strikingly, ICK4 fusion protein with yellow fluorescence protein was strongly present in the degenerative megaspores but absent in the FM, suggesting an important role of ICKs in the degeneration of non-functional megaspores. The absence of or much weaker phenotypes in lower orders of mutants and complementation of the septuple mutant by ICK4 or ICK7 indicate that multiple ICK/KRPs function redundantly in restricting the formation of more than one MMC and in the selective survival of FM, which are critical to ensure the development of one embryo sac and one embryo per ovule.

Applications of the NRGsuite and the molecular docking software FlexAID in computational drug discovery and design - Morency, Louis-Philippe; Gaudreault, Francis; Najmanovich, Rafael (Computational Drug Discovery and Design, 2018)
Docking simulations help us understand molecular interactions. Here we present a hands-on tutorial to utilize FlexAID (Flexible Artificial Intelligence Docking), an open source molecular docking software between ligands such as small molecules or peptides and macromolecules such as proteins and nucleic acids. The tutorial uses the NRGsuite PyMOL plugin graphical user interface to set up and visualize docking simulations in real time as well as detect and refine target cavities. The ease of use of FlexAID and the NRGsuite combined with its superior performance relative to widely used docking software provides nonexperts with an important tool to understand molecular interactions with direct applications in structure-based drug design and virtual high-throughput screening.
Keywords: computer-aided drug design; binding mode prediction; lead identification; molecular docking; molecular flexibility; molecular recognition; protein–ligand complex

Application of CRISPR/Cas9 genome editing technology for the improvement of crops cultivated in tropical climates: recent progress, prospects, and challenges - Haque, Effi; Taniguchi, Hiroaki; Hassan, Md. Mahmudul; Bhowmik, Pankaj; Karim, M. Rezaul; Śmiech, Magdalena; Zhao, Kaijun; Rahman, Mahfuzur; Islam, Tofazzal (Frontiers in Plant Science, 2018)
The world population is expected to increase from 7.3 to 9.7 billion by 2050. Pest outbreak and increased abiotic stresses due to climate change pose a high risk to tropical crop production. Although conventional breeding techniques have significantly increased crop production and yield, new approaches are required to further improve crop production in order to meet the global growing demand for food. The Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/Cas9 (CRISPR-associated protein9) genome editing technology has shown great promise for quickly addressing emerging challenges in agriculture. It can be used to precisely modify genome sequence of any organism including plants to achieve the desired trait. Compared to other genome editing tools such as zinc finger nucleases (ZFNs) and transcriptional activator-like effector nucleases (TALENs), CRISPR/Cas9 is faster, cheaper, precise and highly efficient in editing genomes even at the multiplex level. Application of CRISPR/Cas9 technology in editing the plant genome is emerging rapidly. The CRISPR/Cas9 is becoming a user-friendly tool for development of non-transgenic genome edited crop plants to counteract harmful effects from climate change and ensure future food security of increasing population in tropical countries. This review updates current knowledge and potentials of CRISPR/Cas9 for improvement of crops cultivated in tropical climates to gain resiliency against emerging pests and abiotic stresses.

Another unprecedented Wieland mechanism confirmed: hydrogen formation from hydrogen peroxide, formaldehyde, and sodium hydroxide - Czochara, Robert; Litwinienko, Grzegorz; Korth, Hans-Gert; Ingold, Keith U. (Angewandte Chemie International Edition, 2018)
In 1923, Wieland and Wingler reported that in the molecular hydrogen producing reaction of hydrogen peroxide with formaldehyde in basic solution, free hydrogen atoms (H.) are not involved. They postulated that bis(hydroxymethyl)peroxide, HOCH2OOCH2OH, is the intermediate, which decomposes to yield H2 and formate, proposing a mechanism that would nowadays be considered as a “concerted process”. Since then, several other (conflicting) “mechanisms” have been suggested. Our NMR and Raman spectroscopic and kinetic studies, particularly the determination of the deuterium kinetic isotope effect (DKIE), now confirm that in this base‐dependent reaction, both H atoms of H2 derive from the CH2 hydrogen atoms of formaldehyde, and not from the OH groups of HOCH2OOCH2OH or from water. Quantum‐chemical CBS‐QB3 and W1BD computations show that H2 release proceeds through a concerted process, which is strongly accelerated by double deprotonation of HOCH2OOCH2OH, thereby ruling out a free radical pathway.

Analysis of MAPK and MAPKK gene families in wheat and related Triticeae species - Goyal, Ravinder K.; Tulpan, Dan; Chomistek, Nora; González-Peña Fundora, Dianevys; West, Connor; Ellis, Brian E.; Frick, Michele; Laroche, André; Foroud, Nora A. (BMC Genomics, 2018)
Background: The mitogen-activated protein kinase (MAPK) family is involved in signal transduction networks that underpin many different biological processes in plants, ranging from development to biotic and abiotic stress responses. To date this class of enzymes has received little attention in Triticeae species, which include important cereal crops (wheat, barley, rye and triticale) that represent over 20% of the total protein food-source worldwide. Results: The work presented here focuses on two subfamilies of Triticeae MAPKs, the MAP kinases (MPKs), and the MAPK kinases (MKKs) whose members phosphorylate the MPKs. In silico analysis of multiple Triticeae sequence databases led to the identification of 152 MAPKs belonging to these two sub-families. Some previously identified MAPKs were renamed to reflect the literature consensus on MAPK nomenclature. Two novel MPKs, MPK24 and MPK25, have been identified, including the first example of a plant MPK carrying the TGY activation loop sequence common to mammalian p38 MPKs. An EF-hand calcium-binding domain was found in members of the Triticeae MPK17 clade, a feature that appears to be specific to Triticeae species. New insights into the novel MEY activation loop identified in MPK11s are offered. When the exon-intron patterns for some MPKs and MKKs of wheat, barley and ancestors of wheat were assembled based on transcript data in GenBank, they showed deviations from the same sequence predicted in Ensembl. The functional relevance of MAPKs as derived from patterns of gene expression, MPK activation and MKK-MPK interaction is discussed. Conclusions: A comprehensive resource of accurately annotated and curated Triticeae MPK and MKK sequences has been created for wheat, barley, rye, triticale, and two ancestral wheat species, goat grass and red wild einkorn. The work we present here offers a central information resource that will resolve existing confusion in the literature and sustain expansion of MAPK research in the crucial Triticeae grains.
Keywords: mitogen-activated protein kinase (MAPK); wheat; triticale; rye; barley; cell signalling; protein interactions; gene expression; phylogenetics

An infrared-induced terahertz imaging modality for foreign insert detection in a glass fiber-skinned lightweight honeycomb composite panel - Zhang, Hai; Sfarra, Stefano; Osman, Ahmad; Szielasko, Klaus; Stumm, Christopher; Genest, Marc; Maldague, Xavier (IEEE Transactions on Industrial Informatics, 2018)
In this paper, terahertz time-domain spectroscopy (THz-TDS) is used for the first time to detect fabricated defects in a glass fiber-skinned lightweight honeycomb composite panel. A novel amplitude polynomial regression (APR) algorithm is proposed as a pre-processing method. This method segments the amplitude-frequency curves to simulate the heating and the cooling monotonic behavior as in infrared thermography. Then, the method of empirical orthogonal function (EOF) imaging is applied on the APR pre-processed data as a post-processing algorithm. Signal-to-noise ratio analysis is performed to verify the image improvement of the proposed APR-EOF modality from a quantitative point of view. Finally, the experimental results and the physical analysis show that THz is more suitable with respect to the detection of defects in glass fiber lightweight honeycomb composites.
Keywords: terahertz; polynomial fitting; fourier transform; empirical orthogonal function; lightweight honeycomb

An incremental machine learning algorithm for nuclear forensics - Drummond, Chris (Advances in Artificial Intelligence, 2018)
This paper presents an incremental machine learning algorithm that identifies the origin, or provenance, of samples of nuclear material. This is part of work being undertaken by the Canadian National Nuclear Forensics Library development program, which seeks to build a comprehensive database of signatures for radioactive and nuclear materials under Canadian regulatory control. One difficulty with this application is the small ratio of the number of examples over the number of classes. So, we introduce variants to a basic generative algorithm, based on ideas from the robust statistics literature and elsewhere, to address this issue and to improve robustness to attribute noise. We show experimentally the effectiveness of the approach, and the problems that arise, when adding new examples and classes.

An InAs/InP quantum dot C-band coherent comb laser - Lu, Z. G.; Liu, J. R.; Song, C. Y.; Weber, J.; Mao, Y.; Chang, S. D.; Ding, H. P.; Poole, P. J.; Barrios, P.; Poitras, D.; Janz, S.; O’sullivan, M. (Optical Fiber Communication Conference, 2018)
We have developed InAs/InP quantum-dot 34.462-GHz C-band coherent comb laser modules with low relative intensity and phase noises over its filtered 45 channels, which can be used for data center and coherent communication systems.

An extreme magneto-ionic environment associated with the fast radio burst source FRB 121102 - Michilli, D.; Seymour, A.; Hessels, J. W. T.; Spitler, L. G.; Gajjar, V.; Archibald, A. M.; Bower, G. C.; Chatterjee, S.; Cordes, J. M.; Gourdji, K.; Heald, G. H.; Kaspi, V. M.; et al. (Nature, 2018)
Fast radio bursts are millisecond-duration, extragalactic radio flashes of unknown physical origin1,2,3. The only known repeating fast radio burst source4,5,6—FRB 121102—has been localized to a star-forming region in a dwarf galaxy7,8,9 at redshift 0.193 and is spatially coincident with a compact, persistent radio source7,10. The origin of the bursts, the nature of the persistent source and the properties of the local environment are still unclear. Here we report observations of FRB 121102 that show almost 100 per cent linearly polarized emission at a very high and variable Faraday rotation measure in the source frame (varying from +1.46 × 105 radians per square metre to +1.33 × 105 radians per square metre at epochs separated by seven months) and narrow (below 30 microseconds) temporal structure. The large and variable rotation measure demonstrates that FRB 121102 is in an extreme and dynamic magneto-ionic environment, and the short durations of the bursts suggest a neutron star origin. Such large rotation measures have hitherto been observed11,12 only in the vicinities of massive black holes (larger than about 10,000 solar masses). Indeed, the properties of the persistent radio source are compatible with those of a low-luminosity, accreting massive black hole10. The bursts may therefore come from a neutron star in such an environment or could be explained by other models, such as a highly magnetized wind nebula13 or supernova remnant14 surrounding a young neutron star.

An experimental and computational study of OH formation in laminar coflow syngas diffusion flames - Xu, Huanhuan; Sun, Shaozeng; Liu, Fengshan; Zhao, Yijun; Liu, Yuying; Chen, Lei; Meng, Shun (Fuel, 2018)
This paper presents an experimental and numerical study to elucidate the suppressing influence of H2 content in syngas on OH formation in laminar syngas diffusion flames burning in coflow oxidizer of 25%O2/75%H2O. Such an influence was found different from the effect of H2 content in syngas on OH formation when the oxidizer stream consists of O2/N2. OH∗-chemiluminescence images were captured using an intensified CCD (ICCD) camera, the centerline temperatures were measured by a Pt-6%Rh/Pt-30%Rh thermocouple, while a two-dimensional flame code was adopted to simulate these laminar coflow diffusion flames using a detailed reaction mechanism. The different effects of H2O including chemical, thermal, transport, and radiative were examined and detailed kinetics analyses were conducted to gain insights into how H2O in the oxidizer stream alters the influence of H2 content in syngas on OH formation.
Keywords: H2 content in syngas; OH; O2/H2O atmosphere; Laminar coflow diffusion flame

An experimental and computational study of CO2 adsorption in the sodalite-type M-BTT (M = Cr, Mn, Fe, Cu) metal–organic frameworks featuring open metal sites - Asgari, Mehrdad; Jawahery, Sudi; Bloch, Eric D.; Hudson, Matthew R.; Flacau, Roxana; Vlaisavljevich, Bess; Long, Jeffrey R.; Brown, Craig M.; Queen, Wendy L. (Chemical Science, 2018)
We present a comprehensive investigation of the CO2 adsorption properties of an isostructural series of metal–organic frameworks, M-BTT (M = Cr, Mn, Fe, Cu; BTT3− = 1,3,5-benzenetristetrazolate), which exhibit a high density of open metal sites capable of polarizing and binding guest molecules. Coupling gas adsorption measurements with in situ neutron and X-ray diffraction experiments provides molecular-level insight into the adsorption process and enables rationalization of the observed adsorption isotherms. In particular, structural data confirms that the high initial isosteric heats of CO2 adsorption for the series are directly correlated with the presence of open metal sites and further reveals the positions and orientations of as many as three additional adsorption sites. Density functional theory calculations that include van der Waals dispersion corrections quantitatively support the observed structural features associated with the primary and secondary CO2 binding sites, including CO2 positions and orientations, as well as the experimentally determined isosteric heats of CO2 adsorption.

An excess of massive stars in the local 30 Doradus starburst - Schneider, F. R. N.; Sana, H.; Evans, C. J.; Bestenlehner, J. M.; Castro, N.; Fossati, L.; Gräfener, G.; Langer, N.; Ramírez-Agudelo, O. H.; Sabín-Sanjulián, C.; Simón-Díaz, S.; Tramper, F.; et al. (Science, 2018)
The 30 Doradus star-forming region in the Large Magellanic Cloud is a nearby analog of large star-formation events in the distant universe. We determined the recent formation history and the initial mass function (IMF) of massive stars in 30 Doradus on the basis of spectroscopic observations of 247 stars more massive than 15 solar masses (Embedded Image). The main episode of massive star formation began about 8 million years (My) ago, and the star-formation rate seems to have declined in the last 1 My. The IMF is densely sampled up to 200 Embedded Image and contains 32 ± 12% more stars above 30 Embedded Image than predicted by a standard Salpeter IMF. In the mass range of 15 to 200 Embedded Image, the IMF power-law exponent is Embedded Image, shallower than the Salpeter value of 2.35.

Amplified pilot head vibration and the effects of vibration mitigation on neck muscle strain - Wright Beatty, Heather E.; Law, Andrew J.; Thomas, J. Russell; Wickramasinghe, Viresh (Aerospace Medicine and Human Performance, 2018)
INTRODUCTION: Rotary wing pilot neck strain is increasing in prevalence due to the combined effects of head supported mass (e.g., Night Vision Goggles, head mounted displays) and whole-body vibration. This study examined the physiological responses of pilots during exposure to whole-body vibration (WBV) representative of the National Research Council’s Bell 412 helicopter in forward flight. WBV levels were measured and evaluated using the ISO-2631-1-1997 WBV standards. METHODS: Twelve pilots (aged 20–59 yr, 7 of the 12 with 20+ years flight experience) underwent six 15-min vibration trials on a human rated shaker platform. Participants were exposed to three vibration levels (-25%, normal, and +25% amplitude; Levels 1–3, respectively) while seated on an Original Equipment Manufacturer (OEM) or vibration mitigating (MIT) cushion. Upper back and neck electromyography (EMG) and acceleration were continuously recorded. RESULTS: Normalized EMG amplitude was higher using the OEM compared to the MIT during Level 2 (0.18 vs. -0.27) and Level 3 (0.24 vs. -0.14) for the anterior neck muscles. Health weighted vibration amplitude at the head (Mean of 3 levels: OEM = 1.19 and MIT = 1.11 m · s−2) was larger than the vibration amplitude at the seat (Mean of 3 levels: OEM = 0.77 and MIT = 0.70 m · s−2). DISCUSSION: The amplification of head vibration relative to the seat, and the significant effects of vibration level, as well as the vibration mitigation cushion, on neck EMG amplitude support the need for revisions to the ISO-2631-1 standard to account for the head and neck response to whole-body vibration.

All-electronic nanosecond-resolved scanning tunneling microscopy: facilitating the investigation of single dopant charge dynamics - Rashidi, Mohammad; Vine, Wyatt; Burgess, Jacob A.J.; Taucer, Marco; Achal, Roshan; Pitters, Jason L.; Loth, Sebastian; Wolkow, Robert A. (Journal of Visualized Experiments, 2018)
The miniaturization of semiconductor devices to scales where small numbers of dopants can control device properties requires the development of new techniques capable of characterizing their dynamics. Investigating single dopants requires sub-nanometer spatial resolution, which motivates the use of scanning tunneling microscopy (STM). However, conventional STM is limited to millisecond temporal resolution. Several methods have been developed to overcome this shortcoming, including all-electronic time-resolved STM, which is used in this study to examine dopant dynamics in silicon with nanosecond resolution. The methods presented here are widely accessible and allow for local measurement of a wide variety of dynamics at the atomic scale. A novel time-resolved scanning tunneling spectroscopy technique is presented and used to efficiently search for dynamics.

Aerodynamics of a stay cable with helical fillets - Part II: Fluctuating load and wake characteristics - Christiansen, H.; Jakobsen, J. B.; Macdonald, J. H. G.; Larose, G. L.; Bosch, H. R. (Journal of Wind Engineering and Industrial Aerodynamics, 2018)
This paper presents the fluctuating load and wake characteristics of a bridge stay cable model with helical fillets in smooth flow at high Reynolds numbers. Over the Reynolds numbers tested, the frequency content of the lift coefficient in individual pressure tap rings, was dominated by low frequencies. At lower Reynolds numbers, these were caused by single separation bubble instabilities. At smaller spectral magnitudes, a vortex shedding process was observed, with a local Strouhal number dependent on the angular position of the helical fillet nearly normal to flow. For the average over the four rings, the low frequencies cancelled out, and left a high frequency vortex shedding process with a Strouhal number of 0.19 as the prominent load. The Strouhal number was maintained throughout the Reynolds number range tested. In dynamic tests, the pressure distribution was found to periodically rotate relative to the cable circumference at the natural frequency of the cable. Also, when observing the velocity components in the wake, a periodic motion of the wake synchronized with the cable motion was revealed. In static tests, the wake field instantly displaced towards the same side as the lift force generated by the asymmetric pressure distribution during boundary layer instabilities.
Keywords: bridge cable; helical fillets; inclined circular cylinder; cable instability; fluctuating lift; wake characteristics

Aerodynamics of a stay cable with helical fillets - Part I: Stability and load characteristics - Christiansen, H.; Jakobsen, J. B.; Macdonald, J. H. G.; Larose, G. L.; Bosch, H. R. (Journal of Wind Engineering and Industrial Aerodynamics, 2018)
The aerodynamic behaviour of a bridge stay cable with helical fillets in smooth flow at high Reynolds numbers is presented in this paper. The cable response and related sectional load characteristics were studied experimentally on a 1:1 scale cable section model. The studies showed that a cable with helical fillets inclined 60° to the flow could experience large amplitude wind induced vibrations and that the occurrence of vibrations were highly dependent on cable surface irregularities. The ambition is not to explain fully the excitation mechanism, but to present global and local influences of the helical fillets on the flow field. It was revealed that the flow field around the cable shifted between semi-stable transition states which took place when the transition from laminar to turbulent flow propagated from the free shear layers to the boundary layer. The transitions would form locally and spread along the cable axis. The helical fillet appeared to dominate the local flow structures when located at an angular position between 40° and 130° from the stagnation region. In the stagnation and base regions, the surface irregularities appeared to dominate. Furthermore, the helical fillets displaced the mean stagnation line. The application of quasi-steady theory with the measurement data available appeared not to be able to explain the vibrations.
Keywords: bridge stay cable; helical fillets; inclined circular cylinder; cable instability; surface pressures; sectional loads; quasi-steady theory; reynolds number

A UV-to-NIR study of molecular gas in the dust cavity around RY Lupi - Arulanantham, N.; France, K.; Hoadley, K.; Manara, C. F.; Schneider, P. C.; Alcalá, J. M.; Banzatti, A.; Günther, H. M.; Miotello, A.; Marel, N. van der; Dishoeck, E. F. van; Walsh, C.; et al. (The Astrophysical Journal, 2018)
We present a study of molecular gas in the inner disk (r < 20au) around RY Lupi, with spectra from HST-COS, HST-STIS, and VLT-CRIRES. We model the radial distribution of flux from hot gas in a surface layer between r = 0.1–10 au, as traced by Lyα-pumped H2. The result shows H2 emission originating in a ring centered at ~3 au that declines within r < 0.1 au, which is consistent with the behavior of disks with dust cavities. An analysis of the H2 line shapes shows that a two-component Gaussian profile $(FWHM mathrm,H2=105 +- 15 km s ^-1; FWHM mathrm,H2=43 +- 13 km s^-1) is statistically preferred to a single-component Gaussian. We interpret this as tentative evidence for gas emitting from radially separated disk regions ({r broad,H2} ~0.4 +- 0.1 au; {r narrow,H2} ~ 3 +- 2 au). The 4.7 μm 12CO emission lines are also well fit by two-component profiles ({r broad,CO} =0.4 +- 0.1 au; {r narrow,CO} =15 +- 2 au). We combine these results with 10 μm observations to form a picture of gapped structure within the mm-imaged dust cavity, providing the first such overview of the inner regions of a young disk. The HST SED of RY Lupi is available online for use in modeling efforts.

A systematic methodology for design of retrofit actions with longevity - Morelli, Martin; Lacasse, Michael A. (Journal of Building Physics, 2018)
This article presents a method for the design of retrofit actions with focus on energy savings that permits a systematic and thorough assessment of potential failures, anticipated maintenance and the expected durability of the retrofit actions. The proposed method combines the use of failure mode and effect analysis (FMEA) to permit identifying likely failure modes from which maintenance actions could be planned and the limit states (LS) method to assess the durability of the given retrofit action. One case study was completed to illustrate the application of: (1) the FMEA and LS method and (2) the proposed method for a retrofit action of an internal insulated solid wall of masonry bonded with lightweight aggregate concrete and floor division of concrete. It was evident that FMEA is useful regarding failure-mode identification and maintenance planning, and the LS method has its strength in durability assessment. Combining the use of both the FMEA and LS methods allowed improved design of new energy-saving retrofit actions, given that a thorough risk assessment was possible that included a decision-making process on maintenance planning, durability assessment and decision on potential redesign of retrofit actions.
Dr. Michael A. Lacasse: https://orcid.org/0000-0001-7640-3701
Dr. Michael A. Lacasse: https://orcid.org/0000-0001-7640-3701
Keywords: failure mode and effect analysis; limit states; durability; maintenance; renovation

A system for the measurement of electron stopping powers: proof of principle using a pure β-emitting source - Roy, Timothy; Tessier, Frederic; Mcewen, Malcolm (Radiation Physics and Chemistry, 2018)
The accuracy of the electron stopping powers of elements and compounds is of great importance to medical dosimetry, radiation therapy, and radiation transport simulations. This paper summarises the commissioning of a new high purity Germanium (HPGe) detector and presents a feasibility study confirming the suitability of a method to determine electron stopping power data. A high-efficiency, HPGe detector was commissioned and found to match the manufacturer's performance specifications. A simple experiment was designed to obtain spectra acquired from a Sr-90/Y-90 radioactive check source with varying thicknesses of absorber (Al and Cu foils) placed between the source and the detector. The entire experimental arrangement was simulated using the EGSnrc radiation transport system. The Monte Carlo model of the detector accurately replicated the detector response to electrons and a quantitative analysis showed that the difference between the simulated and measured spectra was less than 1.5%, using the standard tabulated ICRU 37 stopping power data for the simulations. Based on the experiment with the low-energy Sr-90/Y-90 source, it is anticipated that this method can be used with a well-characterized quasi-monoenergetic electron beam, as available from a research linear accelerated to yield accurate measurements to validate current tabulated stopping power data.

A survey for dwarf galaxy remnants around 14 globular clusters in the outer halo - Sollima, A.; Martínez Delgado, D..; Muñoz, R. R.; Carballo-Bello, J. A.; Valls-Gabaud, D.; Grebel, E. K.; Santana, F. A.; Côté, P.; Djorgovski, S. G. (Monthly Notices of the Royal Astronomical Society, 2018)
We report the results of a systematic photometric survey of the peripheral regions of a sample of 14 globular clusters in the outer halo of the Milky Way at distances dGC > 25 kpc from the Galactic Centre. The survey is aimed at searching for the remnants of the host satellite galaxies where these clusters could originally have been formed before being accreted on to the Galactic halo. The limiting surface brightness varies within our sample, but reaches μV, lim = 30–32 mag arcsec−2. For only two globular clusters (NGC 7492 and Whiting 1; already suggested to be associated with the Sagittarius galaxy), we detect extended stellar populations that cannot be associated with either the clusters themselves or with the surrounding Galactic field population. We show that the lack of substructures around globular clusters at these Galactocentric distances is still compatible with the predictions of cosmological simulations whereby in the outer halo the Galactic globular cluster system is built up through hierarchical accretion at early epochs.
Keywords: methods: observational; techniques: photometric; stars: Population II; globular clusters: general; Galaxy: halo; Galaxy: structure

A solid state source of photon triplets based on quantum dot molecules - Khoshnegar, Milad; Huber, Tobias; Predojević, Ana; Dalacu, Dan; Prilmüller, Maximilian; Lapointe, Jean; Wu, Xiaohua; Tamarat, Philippe; Lounis, Brahim; Poole, Philip; Weihs, Gregor; Majedi, Hamed (Conference on Lasers and Electro-Optics, 2018)
Producing advanced quantum states of light is a priority in quantum information technologies. In this context, experimental realizations of multipartite photon states would enable improved tests of the foundations of quantum mechanics as well as implementations of complex quantum optical networks and protocols. It is favourable to directly generate these states using solid state systems, for simpler handling and the promise of reversible transfer of quantum information between stationary and flying qubits. Here we use the ground states of two optically active coupled quantum dots to directly produce photon triplets. The formation of a triexciton in these ground states leads to a triple cascade recombination and sequential emission of three photons with strong correlations. We record 65.62 photon triplets per minute under continuous-wave pumping, surpassing rates of earlier reported sources. Our structure and data pave the way towards implementing multipartite photon entanglement and multi-qubit readout schemes in solid state devices.

A rapid and simple single-stage method for Ca separation from geological and biological samples for isotopic analysis by MC-ICP-MS - Lanping, Feng; Zhou, Lian; Yang, Lu; Zhang, Wen; Wang, Qian; Shuoyun, Tong; Hu, Zhaochu (Journal of Analytical Atomic Spectrometry, 2018)
A new simple and rapid method was developed for the purification of Ca from geological and biological samples. The proposed separation protocol is based on DGA resin and consists of only three elution steps and two types of eluents (6.8 mL 4 mol L−1 HNO3 and 3 mL DI-water), which afford a straightforward separation of Ca with a high yield (95–99%), good purity and low blank level. Moreover, a vacuum box was employed which enables Ca purification for a batch of twelve samples within two hours, with greatly improved efficiency compared to conventional gravity flow separation methods. Ca isotopic ratios were measured by multi-collector inductively coupled plasma mass-spectrometry (MC-ICP-MS) using a standard–sample bracketing method. Based on repeated measurements of NIST SRM 915a and Alfa Ca, the long-term reproducibility was evaluated at ±0.07‰ (2SD) for δ44/42Ca. The validity of the proposed method was demonstrated by the analysis of thirteen international geological and biological reference materials with satisfactory results which are in good agreement with published values. Therefore, the proposed method can be used for a rapid and efficient determination of stable Ca isotopic ratios in geological and biological samples.

A radio continuum and polarization study of SNR G57.2+0.8 associated with magnetar SGR 1935+2154 - Kothes, R.; Sun, X.; Gaensler, B.; Reich, W. (The Astrophysical Journal, 2018)
We present a radio continuum and linear polarization study of the Galactic supernova remnant (SNR) G57.2+0.8, which may host the recently discovered magnetar SGR 1935+2154. The radio SNR shows the typical radio continuum spectrum of a mature supernova remnant with a spectral index of α=-0.55 ±0.02 and moderate polarized intensity. Magnetic field vectors indicate a tangential magnetic field, expected for an evolved SNR, in one part of the SNR, and a radial magnetic field in the other. The latter can be explained by an overlapping arc-like feature, perhaps a pulsar wind nebula, emanating from the magnetar. The presence of a pulsar wind nebula is supported by the low average braking index of 1.2, which we extrapolated for the magnetar, and the detection of diffuse X-ray emission around it. We found a distance of 12.5 kpc for the SNR, which identifies G57.2+0.8 as a resident of the Outer spiral arm of the Milky Way. The SNR has a radius of about 20 pc and could be as old as 41,000 yr. The SNR has already entered the radiative or pressure-driven snowplow phase of its evolution. We compare independently determined characteristics like age and distance for both the SNR and the soft gamma repeater SGR 1935+2154, and conclude that they are physically related.
Keywords: ISM: individual objects (G57.2+0.8, SGR1935+2154); ISM: magnetic fields; ISM: supernova remnants; stars: magnetars

A protocol for epigenetic imprinting analysis with RNA-Seq data - Zou, Jinfeng; Xiang, Daoquan; Datla, Raju; Wang, Edwin (Transcriptome Data Analysis, 2018)
Genomic imprinting is an epigenetic regulatory mechanism that operates through expression of certain genes from maternal or paternal in a parent-of-origin-specific manner. Imprinted genes have been identified in diverse biological systems that are implicated in some human diseases and in embryonic and seed developmental programs in plants. The molecular underpinning programs and mechanisms involved in imprinting are yet to be explored in depth in plants. The recent advances in RNA-Seq-based methods and technologies offer an opportunity to systematically analyze epigenetic imprinting that operates at the whole genome level in the model and crop plants. We are interested using Arabidopsis model system, to investigate gene expression patterns associated with parent of origin and their implications to imprinting during embryo and seed development. Toward this, we have generated early embryo development RNA-Seq-based transcriptome datasets in F1s from a genetic cross between two diverse Arabidopsis thaliana ecotypes Col-0 and Tsu-1. With the data, we developed a protocol for evaluating the maternal and paternal contributions of genes during the early stages of embryo development after fertilization. This protocol is also designed to consider the contamination from other potential seed tissues, sequencing quality, proper processing of sequenced reads and variant calling, and appropriate inference of the parental contributions based on the parent-of-origin-specific single-nucleotide polymorphisms within the expressed genes. The approach, methods and the protocol developed in this study can be used for evaluating the effects of epigenetic imprinting in plants.
Keywords: genomic imprinting; RNA-Seq; maternal and paternal contributions; Arabidopsis thaliana

A photometric study of globular clusters observed by the APOGEE survey - Mészáros, Szabolcs; García-Hernández, D. A.; Cassisi, Santi; Monelli, Matteo; Szigeti, László; Dell'agli, Flavia; Derekas, Alíz; Masseron, Thomas; Shetrone, Matthew; Stetson, Peter; Zamora, Olga (Monthly Notices of the Royal Astronomical Society, 2018)
In this paper, we describe the photometric and spectroscopic properties of multiple populations in seven northern globular clusters. In this study, we employ precise ground-based photometry from the private collection of Stetson, space photometry from the Hubble Space Telescope (HST), literature abundances of Na and O, and Apache Point Observatory Galactic Evolution Experiment (APOGEE) survey abundances for Mg, Al, C, and N. Multiple populations are identified by their position in the CU, B, I −Vpseudo colour–magnitude diagram (pseudo-CMD) and confirmed with their chemical composition determined using abundances. We confirm the expectation from previous studies that the red giant branches (RGBs) in all seven clusters are split and the different branches have different chemical compositions. The Mg–Al anticorrelations were well explored by the APOGEE and Gaia-ESO surveys for most globular clusters, some clusters showing bimodal distributions, while others continuous distributions. Even though the structure (i.e. bimodal versus continuous) of Mg–Al can greatly vary, the Al-rich and Al-poor populations do not seem to have very different photometric properties, agreeing with theoretical calculations. There is no one-to-one correspondence between the Mg–Al anticorrelation shape (bimodal versus continuous) and the structure of the RGB seen in the HST pseudo-CMDs, with the HST photometric information usually implying more complex formation/evolution histories than the spectroscopic ones. We report on finding two second-generation horizontal branch (HB) stars in M5, and five second-generation asymptotic giant branch (AGB) stars in M92, which is the most metal-poor cluster to date in which second-generation AGB stars have been observed.
Keywords: stars: abundances; stars: AGB and post-AGB; globular clusters: general

A numerical study on the chemical kinetics process during auto-ignition of n-heptane in a direct injection compression ignition engine - Li, Yu; Li, Hailin; Guo, Hongsheng; Wang, Hu; Yao, Mingfa (Applied Energy, 2018)
This paper presents a numerical analysis of the ignition process of an n-heptane spray in a compression ignition engine using a post-processing tool developed by West Virginia University. Such a tool is able to process the CFD simulation data for the examination of chemical reaction process without revising the CFD source code. The main functions of the post-processing tool include: (1) The calculation of the instantaneous rate of production (ROP) using CHEMKIN with the temperature, pressure and species concentration in each cell simulated using CFD; (2) the development of the representative destruction reaction (RDR) and destruction pathway of the key species involved in a specific area; and (3) the visualization of the analysis results. Such a tool was applied to examine the chemical reaction process during ignition delay of the n-heptane spray in a direct injection compression ignition engine. The H abstraction of n-heptane by O2, OH, HO2, and H radical during ignition period was further examined. The destruction pathway of key species in RDROH/RDRHO2 region and their development leading to the autoignition of n-heptane were studied. It is found that both the n-heptane/air mixture and bulk gas movement play an important role in the formation of RDRHO2 region. The RDRHO2 region featured with medium temperature (around 1000 K) produces more H2O2/HO2 radical before the auto-ignition of n-heptane than low-temperature combustion. The rapid dissociation of H2O2 provides a large amount of OH radical that enhances the chain branching reaction as well as heat release process which then initiates the autoignition of n-heptane. The reaction rates of nC7H16 + OH = C7H15 + H2O and nC7H16 + HO2 = C7H15 + H2O2 were examined to reveal their competition in destructing n-heptane. The H atom is also found to promote the chain branching during auto-ignition. Such a tool provides the convenience for commercial CFD research community to conveniently elaborate the CFD simulation results for better understanding of the fundamental aspects of the combustion and emissions phenomenon observed using CFD code.
Keywords: instantaneously ROP; CFD; n-Heptane auto-ignition; compression ignition engine

A numerical investigation on NO2 formation in a natural gas–diesel dual fuel engine - Li, Yu; Li, Hailin; Guo, Hongsheng; Li, Yongzhi; Yao, Mingfa (Journal of Engineering for Gas Turbines and Power, 2018)
This research numerically simulates the formation and destruction of nitrogen dioxide (NO2) in a natural gas (NG)–diesel dual fuel engine using commercial CFD software converge coupled with a reduced primary reference fuel (PRF) mechanism consisting of 45 species and 142 reactions. The model was validated by comparing the simulated cylinder pressure, heat release rate (HRR), and nitrogen oxide (NOx) emissions with experimental data. The validated model was used to simulate the formation and destruction of NO2 in a NG–diesel dual fuel engine. The formation of NO2 and its correlation with the local concentration of nitric oxide (NO), methane, and temperature were examined and discussed. It was revealed that NO2 was mainly formed in the interface region between the hot NO-containing combustion products and the relatively cool unburnt methane–air mixture. The NO2 formed at the early combustion stage is usually destructed to NO after the complete oxidation of methane and n-heptane, while NO2 formed during the postcombustion process survives through the expansion process and exits the engine. The increased NO2 emissions from NG–diesel dual fuel engines was formed during the post combustion process due to higher concentration of HO2 produced during the oxidation process of the unburned methane at low temperature. A detailed analysis of the chemical reactions occurring in the NO2 containing zone consisting of NO2, NO, O2, methane, etc., was conducted using a quasi-homogeneous constant volume (QHCV) model to identify the key reactions and species dominating NO2 formation and destruction. The HO2 produced during the postcombustion process of methane was identified as the primary species dominating the formation of NO2 during the post combustion expansion process. The simulation revealed the key reaction path for the formation of HO2 noted as CH4 → CH3 → CH2O → HCO → HO2, with conversion ratios of 98%, 74%, 90%, 98%, accordingly. The backward reaction of OH + NO2 = NO + HO2 consumed 34% of HO2 for the production of NO2.

A novel Gerstmann-Sträussler-Scheinker disease mutation defines a precursor for amyloidogenic 8 kDa PrP fragments and reveals N-terminal structural changes shared by other GSS alleles - Mercer, Robert C. C.; Daude, Nathalie; Dorosh, Lyudmyla; Fu, Ze-lin; Mays, Charles E.; Gapeshina, Hristina; Wohlgemuth, Serene L.; Acevedo-morantes, Claudia Y.; Yang, Jing; Cashman, Neil R.; Coulthart, Michael B.; Pearson, Dawn M.; et al. (PLOS Pathogens, 2018)
To explore pathogenesis in a young Gerstmann-Sträussler-Scheinker Disease (GSS) patient, the corresponding mutation, an eight-residue duplication in the hydrophobic region (HR), was inserted into the wild type mouse PrP gene. Transgenic (Tg) mouse lines expressing this mutation (Tg.HRdup) developed spontaneous neurologic syndromes and brain extracts hastened disease in low-expressor Tg.HRdup mice, suggesting de novo formation of prions. While Tg.HRdup mice exhibited spongiform change, PrP aggregates and the anticipated GSS hallmark of a proteinase K (PK)-resistant 8 kDa fragment deriving from the center of PrP, the LGGLGGYV insertion also imparted alterations in PrP's unstructured N-terminus, resulting in a 16 kDa species following thermolysin exposure. This species comprises a plausible precursor to the 8 kDa PK-resistant fragment and its detection in adolescent Tg.HRdup mice suggests that an early start to accumulation could account for early disease of the index case. A 16 kDa thermolysin-resistant signature was also found in GSS patients with P102L, A117V, H187R and F198S alleles and has coordinates similar to GSS stop codon mutations. Our data suggest a novel shared pathway of GSS pathogenesis that is fundamentally distinct from that producing structural alterations in the C-terminus of PrP, as observed in other prion diseases such as Creutzfeldt-Jakob Disease and scrapie.

A novel approach for real-time prediction and prevention of tool chipping in intermittent turning machining - Hassan, M.; Sadek, A.; Damir, A.; Attia, M. H.; Thomson, V. (CIRP Annals, 2018)
An integrated tool condition monitoring system, based on a novel signal processing approach, for online prediction and prevention of tool chipping in intermittent turning is presented. It identifies the unstable crack propagation features of the prefailure phase, independent of the cutting parameters and workpiece material. A correlation between the chipping size and these features was developed for decision making, to protect machined surfaces. Experimental validation results confirmed the accuracy of the proposed system. The time required for signal processing, decision making and communication with the machine controller allows stopping the operation before part damage. No such system is presently available.
Keywords: cutting; condition monitoring; prefailure prediction

A MegaCam survey of outer halo satellites. III. Photometric and structural parameters - Muñoz, Ricardo R.; Côté, Patrick; Santana, Felipe A.; Geha, Marla; Simon, Joshua D.; Oyarzún, Grecco A.; Stetson, Peter B.; Djorgovski, S. G. (The Astrophysical Journal, 2018)
We present structural parameters from a wide-field homogeneous imaging survey of Milky Way satellites carried out with the MegaCam imagers on the 3.6 m Canada–France–Hawaii Telescope and 6.5 m Magellan-Clay telescope. Our survey targets an unbiased sample of "outer halo" satellites (i.e., substructures having galactocentric distances greater than 25 kpc) and includes classical dSph galaxies, ultra-faint dwarfs, and remote globular clusters. We combine deep, panoramic gr imaging for 44 satellites and archival gr imaging for 14 additional objects (primarily obtained with the DECam instrument as part of the Dark Energy Survey) to measure photometric and structural parameters for 58 outer halo satellites. This is the largest and most uniform analysis of Milky Way satellites undertaken to date and represents roughly three-quarters (58/81 sime 72%) of all known outer halo satellites. We use a maximum-likelihood method to fit four density laws to each object in our survey: exponential, Plummer, King, and Sérsic models. We systematically examine the isodensity contour maps and color–magnitude diagrams for each of our program objects, present a comparison with previous results, and tabulate our best-fit photometric and structural parameters, including ellipticities, position angles, effective radii, Sérsic indices, absolute magnitudes, and surface brightness measurements. We investigate the distribution of outer halo satellites in the size–magnitude diagram and show that the current sample of outer halo substructures spans a wide range in effective radius, luminosity, and surface brightness, with little evidence for a clean separation into star cluster and galaxy populations at the faintest luminosities and surface brightnesses.

A MegaCam survey of outer halo satellites. I. Description of the survey - Muñoz, Ricardo R.; Côté, Patrick; Santana, Felipe A.; Geha, Marla; Simon, Joshua D.; Oyarzún, Grecco A.; Stetson, Peter B.; Djorgovski, S. G. (The Astrophysical Journal, 2018)
We describe a deep, systematic imaging study of satellites in the outer halo of the Milky Way. Our sample consists of 58 stellar overdensities—i.e., substructures classified as either globular clusters, classical dwarf galaxies, or ultra-faint dwarf galaxies—that are located at Galactocentric distances of R GC ≥ 25 kpc (outer halo) and out to ~400 kpc. This includes 44 objects for which we have acquired deep, wide-field, g- and r-band imaging with the MegaCam mosaic cameras on the 3.6 m Canada–France–Hawaii Telescope and the 6.5 m Magellan-Clay telescope. These data are supplemented by archival imaging, or published gr photometry, for an additional 14 objects, most of which were discovered recently in the Dark Energy Survey (DES). We describe the scientific motivation for our survey, including sample selection, observing strategy, data reduction pipeline, calibration procedures, and the depth and precision of the photometry. The typical 5σ point-source limiting magnitudes for our MegaCam imaging—which collectively covers an area of ≈52 deg2—are g lim sime 25.6 and r lim sime 25.3 AB mag. These limits are comparable to those from the coadded DES images and are roughly a half-magnitude deeper than will be reached in a single visit with the Large Synoptic Survey Telescope. Our photometric catalog thus provides the deepest and most uniform photometric database of Milky Way satellites available for the foreseeable future. In other papers in this series, we have used these data to explore the blue straggler populations in these objects, their density distributions, star formation histories, scaling relations, and possible foreground structures.

A massive core for a cluster of galaxies at a redshift of 4.3 - Miller, T. B.; Chapman, S. C.; Aravena, M.; Ashby, M. L. N.; Hayward, C. C.; Vieira, J. D.; Weiß, A.; Babul, A.; Béthermin, M.; Bradford, C. M.; Brodwin, M.; Carlstrom, J. E.; et al. (Nature, 2018)
Massive galaxy clusters have been found that date to times as early as three billion years after the Big Bang, containing stars that formed at even earlier epochs1,2,3. The high-redshift progenitors of these galaxy clusters—termed ‘protoclusters’—can be identified in cosmological simulations that have the highest overdensities (greater-than-average densities) of dark matter4,5,6. Protoclusters are expected to contain extremely massive galaxies that can be observed as luminous starbursts7. However, recent detections of possible protoclusters hosting such starbursts8,9,10,11 do not support the kind of rapid cluster-core formation expected from simulations12: the structures observed contain only a handful of starbursting galaxies spread throughout a broad region, with poor evidence for eventual collapse into a protocluster. Here we report observations of carbon monoxide and ionized carbon emission from the source SPT2349-56. We find that this source consists of at least 14 gas-rich galaxies, all lying at redshifts of 4.31. We demonstrate that each of these galaxies is forming stars between 50 and 1,000 times more quickly than our own Milky Way, and that all are located within a projected region that is only around 130 kiloparsecs in diameter. This galaxy surface density is more than ten times the average blank-field value (integrated over all redshifts), and more than 1,000 times the average field volume density. The velocity dispersion (approximately 410 kilometres per second) of these galaxies and the enormous gas and star-formation densities suggest that this system represents the core of a cluster of galaxies that was already at an advanced stage of formation when the Universe was only 1.4 billion years old. A comparison with other known protoclusters at high redshifts shows that SPT2349-56 could be building one of the most massive structures in the Universe today.

A Joint multi-feature and scale-adaptive correlation filter tracker - Yang, Xiaohui; Zhang, Hao; Yang, Lei; Yang, Chunsheng; Liu, Peter X. (IEEE Access, 2018)
Traditional tracking-by-detection trackers may fail to track targets owing to interferences, such as deformation, occlusion, fast or irregular motion, and background clutter. To improve the process of feature extraction, sample training, and the performance of the traditional kernelized correlation filter (KCF), this paper proposes a new joint multi-feature and scale-adaptive correlation filter tracking algorithm based on histogram of oriented gradients (HOG) and color-naming features. The new algorithm is composed of a position correlation filter tracker and a scale correlation filter tracker. It first uses a mask matrix to cut the training samples, obtains a higher proportion of real samples, and then trains the two correlation filter trackers. One is a position tracker that uses HOG and color-naming features to train two correlation filters, and then combines the results of the two correlation filters to calculate the target position. The second tracker is used to identify the scale with the maximum response size to select the target scale. The proposed algorithm achieves a competitive performance compared with algorithms, such as KCF, compressive tracking, and circulant structure kernel. The results show that this algorithm achieves a better performance when faced with occlusion, deformation, background clutter, and fast or irregular motion, and is able to track changes in target scale.
Keywords: feature fusion; scale-adaptive correlation filters; target tracking; mask matrix

A generic modeling and power-flow analysis approach for isochronous and droop-controlled microgrids - Allam, Mahmoud A.; Said, Amr; Kazerani, Mehrdad (IEEE Transactions on Power Systems, 2018)
This paper proposes a generic steady-state modeling and power-flow analysis approach for droop- and isochronously-controlled microgrids. The proposed framework adopts symmetrical sequence component models, rather than phase-coordinate models, of microgrid components. Such approach immensely reduces the power-flow execution time, as it breaks down the system model into independent equation sets with considerably reduced sizes. To render the proposed approach practical and generic, it incorporates unbalanced loads and feeders, transformer connections, different load characteristics and configurations, as well as microgrid droop features. Furthermore, it models and integrates different types and control schemes of distributed generation (DG), including synchronous generator-based DG (SGDG) and electronically-interfaced DG (EIDG) units. A novel power-flow algorithm based on a modified Newton-Raphson (NR) method is proposed to solve for the microgrid steady-state voltage magnitudes, angles, and frequency. The accuracy of the models and algorithm is verified through comparison with detailed time-domain simulations in MATALB/Simulink. Additionally, the proposed algorithm is shown to outperform the reported Newton-Trust Region (NTR) approach in accuracy and computational cost. Two case studies, incorporating IEEE 123-node test microgrid, are further performed to examine the effectiveness of the proposed approach in solving complicated droop-controlled microgrids, and to investigate the behavior of droop-controlled DGs in isochronous microgrids.

A fast jaw-tracking model for VMAT and IMRT Monte Carlo simulations - Townson, Reid; Egglestone, Hilary; Zavgorodni, Sergei (Journal of Applied Clinical Medical Physics, 2018)
Modern radiotherapy techniques involve routine use of volumetric arc therapy (VMAT) and intensity modulated radiotherapy (IMRT) with jaw-tracking - dynamic motion of the secondary collimators (jaws) in tandem with multi-leaf collimators (MLCs). These modalities require accurate dose calculations for the purposes of treatment planning and dose verification. Monte Carlo (MC) methods for radiotherapy dose calculation are widely accepted as capable of achieving high accuracy. This paper presents an efficiency-enhancement method for secondary collimator modeling, presented in the context of a tool for MC-based dose second checks. The model constitutes an accuracy trade-off in the source model for the sake of efficiency enhancement, but maintains the advantages of MC transport in patient heterogeneities. The secondary collimator model is called Flat-Absorbing-Jaw-Tracking (FAJT). Transmission through and scatter from the secondary collimators is neglected, and jaws are modeled as perfectly absorbing planes. To couple the motion of secondary collimators with MLCs for jaw-tracking, the FAJT model was built into the VCU-MLC model. Gamma-index analysis of the dose distributions from FAJT against the full BEAMnrc MC simulations showed over 99% pass rate for a range of open fields, two clinical IMRT, and one VMAT treatment plan, for 2%/2 mm criteria above 10%. Using FAJT, the simulation speed of the secondary collimators for open fields increased by a factor of 237, 1489, and 1395 for 4 × 4, 10 × 10, and 30 × 30 cm2, respectively. In general, clinically oriented simulation times are reduced from "hours" to "minutes" on identical hardware. Results for nine representative clinical cases (seven with jaw-tracking) are presented. The average 2%/2 mm γ-test success rate above the 80% isodose was 96.8% when tested against the EPIDose electronic portal image-based dose reconstruction method and 97.3% against the Eclipse analytical anisotropic algorithm.

A detailed observational analysis of V1324 Sco, the most gamma-ray-luminous classical nova to date - Finzell, Thomas; Chomiuk, Laura; Metzger, Brian D.; Walter, Frederick M.; Linford, Justin D.; Mukai, Koji; Nelson, Thomas; Weston, Jennifer H. S.; Zheng, Yong; Sokoloski, Jennifer L.; Mioduszewski, Amy; Rupen, Michael P.; et al. (The Astrophysical Journal, 2018)
It has recently been discovered that some, if not all, classical novae emit GeV gamma-rays during outburst, but the mechanisms involved in the production ofgamma-rays are still not well understood. We present here a comprehensive multiwavelength data set—from radio to X-rays—for the most gamma-ray-luminous classical nova to date, V1324 Sco. Using this data set, we show that V1324 Sco is a canonical dusty Fe ii-type nova, with a maximum ejecta velocity of 2600 km s−1 and an ejecta mass of a few x 10^-5 M⊙. There is also evidence for complex shock interactions, including a double-peaked radio light curve which shows high brightness temperatures at early times. To explore why V1324 Sco was so gamma-ray luminous, we present a model of the nova ejecta featuring strong internal shocks and find that higher gamma-ray luminosities result from higher ejecta velocities and/or mass-loss rates. Comparison of V1324 Sco with other gamma-ray-detected novae does not show clear signatures of either, and we conclude that a larger sample of similarly well-observed novae is needed to understand the origin and variation of gamma-rays in novae.
Keywords: gamma rays: stars; novae, cataclysmic variables; radio continuum: stars; stars: individual V1324 Sco)

A deeper look at the GD1 stream: density variations and wiggles - De boer, T. J. L.; Belokurov, V.; Koposov, S. E.; Ferrarese, L.; Erkal, D.; Côté, P.; Navarro, J. F. (Monthly Notices of the Royal Astronomical Society, 2018)
Using deep photometric data from Canada–France–Hawaii Telescope/Megacam, we study the morphology and density of the GD-1 stream, one of the longest and coldest stellar streams in the Milky Way. Our deep data recovers the lower main sequence of the stream with unprecedented quality, clearly separating it from Milky Way foreground and background stars. An analysis of the distance to different parts of the stream shows that GD-1 lies at a heliocentric distance between 8 and 10 kpc, with only a shallow gradient across 45° on the sky. Matched filter maps of the stream density show clear density variations, such as deviations from a single orbital track and tentative evidence for stream fanning. We also detect a clear underdensity in the middle of the stream track at φ1 = −45° surrounded by overdense stream segments on either side. This location is a promising candidate for the elusive missing progenitor of the GD-1 stream. We conclude that the GD-1 stream has clearly been disturbed by interactions with the Milky Way disc or other subhaloes.
Keywords: Galaxy: fundamental parameters; Galaxy: halo; Galaxy: structure

Influences on energy savings of heavy trucks using cooperative adaptive cruise control - Mcauliffe, Brian; Lammert, Michael; Lu, Xiao-Yun; Shladover, Steven; Surcel, Marius-Dorin; Kailas, Aravind (SAE Technical Papers, 2018)
An integrated adaptive cruise control (ACC) and cooperative ACC (CACC) was implemented and tested on three heavy-duty tractor-trailer trucks on a closed test track. The first truck was always in ACC mode, and the followers were in CACC mode using wireless vehicle-vehicle communication to augment their radar sensor data to enable safe and accurate vehicle following at short gaps. The fuel consumption for each truck in the CACC string was measured using the SAE J1321 procedure while travelling at 65 mph and loaded to a gross weight of 65,000 lb, demonstrating the effects of: inter-vehicle gaps (ranging from 3.0 s or 87 m to 0.14 s or 4 m, covering a much wider range than previously reported tests), cut-in and cut-out maneuvers by other vehicles, speed variations, the use of mismatched vehicles (standard trailers mixed with aerodynamic trailers with boat tails and side skirts), and the presence of a passenger vehicle ahead of the platoon.The results showed that energy savings generally increased in a non-linear fashion as the gap was reduced. The middle truck saved the most fuel at gaps shorter than 12 m and the trailing truck saved the most at longer gaps, while lead truck saved the least at all gaps. The cut-in and cut-out maneuvers had only a marginal effect on fuel consumption even when repeated every two miles. The presence of passenger-vehicle traffic had a measurable impact. The fuel-consumption savings on the curves was less than on the straight sections.

Thermo-mechanical fatigue testing of welded tubes for exhaust applications - Quan, Guangchun; Wu, Xijia; Lafleur, Luc; Zhang, Zhong (SAE Technical Papers, 2018)
Selected ferritic stainless steel sheets for exhaust applications were tested under thermo-mechanical fatigue (TMF) condition in the temperature range of 400-800 °C with partial constraint. Straight welded tubes were used as the testing coupons to withstand large compression without buckling, and to understand the effect of welding as well. Repeated tests confirmed the observed failure scenario for each material type. The hysteresis loop behaviors were also simulated using the mechanism-based integrated creep and fatigue theory (ICFT) model. Although more development work is needed, for quick material screening purpose this type of testing could be a very cost effective solution for materials and tube weld development for exhaust applications.

An integrated approach to constitutive modeling and life prediction for automotive materials - Wu, Xijia (SAE Technical Papers, 2018)
An integrated approach of constitutive modeling and life prediction is presented through introduction of the integrated creep-fatigue theory (ICFT). The ICFT is formulated based on participating deformation and damage mechanisms, which not only describes the cyclic deformation behavior, but also the life and fracture mode. Automotive exhaust system materials such as ductile cast iron and austenitic cast steel are used as example materials for demonstration in good agreement with experimental results and metallurgical examinations. This enlightens the understanding of the roles each mechanism plays in low cycle fatigue (LCF) and thermomechanical (TMF) processes, thus helping material and component design specifically targeting the most damaging mechanism(s) encountered in service.

Screening of cyclic imine and paralytic shellfish toxins in isolates of the genus Alexandrium (Dinophyceae) from Atlantic Canada - Qiu, Jiangbing; Rafuse, Cheryl; Lewis, Nancy I.; Li, Aifeng; Meng, Fanping; Beach, Daniel G.; Mccarron, Pearse (Harmful Algae, 2018)
The dinoflagellate genus Alexandrium Halim has frequently been associated with harmful algal blooms. Although a number of species from this genus are known to produce paralytic shellfish toxins (PST) and/or cyclic imines (CI), studies on comprehensive toxin profiling using techniques capable of detecting the full range of PST and CI analogues are limited. Isolates of Alexandrium spp. from Atlantic Canada were analyzed by targeted and untargeted liquid chromatography-tandem mass spectrometry (LC–MS). Results showed a number of distinct profiles and wide ranging cell quotas of PST and spirolides (SPX) in both A. catenella (Whedon & Kofoid) Balech and A. ostenfedii (Paulsen) Balech & Tangen. The concentration of PST in A. catenella ranged from 0.0029 to 54 fmol cell−1 with the major components being C2 and GTX4. In addition, putative PST metabolites were confirmed for the first time in A. catenella by high resolution MS/MS. By comparison, A. ostenfeldii isolates showed much lower concentrations of PST (<LOD to 2 fmol cell−1) and high total levels of SPX (14 to 43 fmol cell−1). The SPX profile of the A. ostenfeldii strains mainly included 13-desmethyl SPX-C, SPX-C and 20-methyl SPX-G, with low levels of other SPX and gymnodimine-like analogues detected by untargeted –high-resolution LC-MS. This work demonstrates the importance of using screening methods capable of detecting the full suite of PST and CI compounds when analyzing Alexandrium isolates for toxin production and adds further complexity to the known toxin profiles of this genus.
Keywords: Alexandrium catenella; Alexandrium tamarense; Alexandrium ostenfeldii; paralytic shellfish toxins; cyclic imine toxins; spirolides; gymnodimines; mass spectrometry

Further investigation of surface velocity measurements for material characterization in laser shockwave experiments - Smith, James A.; Lacy, Jeffrey M.; Scott, Clark L.; Benefiel, Bradley C.; Lévesque, Daniel; Monchalin, Jean-Pierre; Lord, Martin (AIP Conference Proceedings; no. 1949, 2018)
As part of the U.S. High Performance Research Reactor program, a laser shock test system is being developed by the Idaho National Laboratory (INL) to characterize interface strength in innovative plate fuel for research reactors around the world. The INL has been working with National Research Council Canada (NRC) on this project for the last five years. One of the concerns is the difficulty of calibrating and standardizing the laser shock technique. A recent analytical study and testing support the use of the Hugoniot Elastic Limit (HEL) in materials as a robust and simple benchmark to compare stresses generated by different laser shock systems. Using a non-contact laser velocimeter based on a solid Fabry-Perot etalon, the systems at NRC and INL show that the back-surface velocity reached at the HEL is consistent, and independent of the laser power used. In this work, the laser velocimeter of the NRC system is tested against a fast rotating wheel to verify accuracy and determine best operating conditions. A round robin test between the two laser shock systems on plates of different aluminum alloys is presented that shows the consistent characterization of the aluminum alloys based on the HEL velocities as well as determines the bias between the systems. The effects of setup parameters on other characteristics of the back-surface velocity trace and corresponding stress wave are also discussed.

Experimental life improvement quantification of shot peening and fastener modifications - Renaud, Guillaume; Martin, Pascal; Liao, Min; Hénaff, G. (MATEC Web of Conferences, 2018)
Two coupon test programs were recently carried out at the National Research Council of Canada to certify shot peening and fastener modifications that aim at extending the lives of military aircraft components that are short of their revised usage goals. The life improvement associated with each modification was experimentally quantified by comparing the lives resulting from variants of each modification with that of pre-modification baseline configurations. This approach allowed determining the effects of several parameters, such as the applied stress level, geometric configuration, and modification specifications, on the life extension.

Development of a recombinant murine tumour model using hepatoma cells expressing hepatitis C virus nonstructural antigens - Young, K. G.; Haq, K.; Maclean, S.; Dudani, R.; Elahi, S. M.; Gilbert, R.; Weeratna, R. D.; Krishnan, L. (Journal of Viral Hepatitis, 2018)
Hepatitis C virus (HCV) chronically infects 2%‐3% of the world's population, causing liver disease and cancer with prolonged infection. The narrow host range of the virus, being restricted largely to human hepatocytes, has made the development of relevant models to evaluate the efficacy of vaccines a challenge. We have developed a novel approach to accomplish this by generating a murine hepatoma cell line stably expressing nonstructural HCV antigens which can be used in vitro or in vivo to test HCV vaccine efficacies. These HCV‐recombinant hepatoma cells formed large solid‐mass tumours when implanted into syngeneic mice, allowing us to test candidate HCV vaccines to demonstrate the development of an HCV‐specific immune response that limited tumour growth. Using this model, we tested the therapeutic potential of recombinant anti‐HCV‐specific vaccines based on two fundamentally different attenuated pathogen vaccine systems—attenuated Salmonella and recombinant adenoviral vector based vaccine. While attenuated Salmonella that secreted HCV antigens limited growth of the HCV‐recombinant tumours when used in a therapeutic vaccination trial, replication‐competent but noninfectious adenovirus expressing nonstructural HCV antigens showed overall greater survival and reduced weight loss compared to non‐replicating nondisseminating adenovirus. Our results demonstrate a model with anti‐tumour responses to HCV nonstructural (NS) protein antigens and suggest that recombinant vaccine vectors should be explored as a therapeutic strategy for controlling HCV and HCV‐associated cancers.

Long-term in-situ assessment of vacuum insulation panels for integration into roofing systems: five years of field-performance - Molleti, Sudhakar; Lefebvre, Dominique; Van Reenen, David (Energy and Buildings, 2018)
The use of vacuum insulation panels (VIPs) is under investigation by the National Research Council for use as a complementary material for current insulation systems. VIP composites, consisting of VIPs sandwiched between polyiso panels, were constructed and incorporated into a modified bitumen roofing system in Ottawa, Canada. The VIP composite, as well as a conventional polyiso system, were monitored in-situ for a period of five years to observe their performance. It was found that the composite VIP insulation outperformed the conventional polyiso system for all months and years monitored, providing an increased barrier to heat flow, reduced temperature driving forces for energy loss, and R-values that were on average twice that of the conventional polyiso system. The long-term performance was also assessed for the five year period and it was found that the VIP composite performed within a 10% margin of its original value for consecutive years. This study successfully demonstrated the energy saving potential that can be achieved through incorporating VIPs into current roofing and building applications.
Keywords: vacuum insulation panel; VIP composite; modified bitumen roof insulation; VIP in-situ monitoring; VIP roof; VIP long-term performance; VIP long-term monitoring

PO-033 Identification and functional evaluation of monoclonal antibodies specifically targeting human carbonic anhydrase ix - Lenferink, A.; Baardsnes, J.; Sulea, T.; Wu, C.; Acchione, M.; Jaramillo, M.; Mcdonald, P.; Benard, F.; Dedhar, S. (New Therapies, 2018)
Introduction Poor vascularisation of solid tumours leads to inadequate nutrient and oxygen supplies which forces tumour cells to reprogram their metabolism. As a consequence the tumour cell’s environment becomes acidic and hypoxic. This, in turn, triggers signalling cascades involving for example heterodimeric hypoxia-inducible factor (HIF). Activation of this hypoxia-induced transcriptional program is crucial for the survival of tumour cells in their hostile microenvironment but also their ability to metastasize. One of the genes upregulated through the HIF pathway is carbonic anhydrase (CA)-IX (CAIX, gene G250/MN-encoded transmembrane protein). CA-IX catalyses carbon dioxide (CO2) thereby generating a proton (H+) and bicarbonate (HCO3-), the latter of which is transported back into the cell and utilised to help safeguard intracellular pH (pHi) stability. Except for the stomach and the gallbladder, CA-IX expression is negligible in normal tissues. In contrast, a broad range of tumours express high levels of CA-IX, where the protein can serve as a biomarker for the early stages of tumour development but also as tumour marker of hypoxia associated with resistance to chemotherapy and radiotherapy. Material and methods Preclinical and clinical studies have shown that CA-IX is a promising therapeutic target for detection and therapy for several cancer types. To date only a limited number of ant-CAIX monoclonal antibodies (mAbs) have been available for clinical testing as therapeutic and imaging agents. In the current study, we generated and functionally categorised a panel of 51 mouse mAbs that specifically bind to human CA-IX. Results and discussions Characterisation of the mAbs revealed that of the mAbs with the best biophysical characteristics, three3 mAbs are suitable as an antibody-drug conjugate (ADC), two2 mAbs inhibit the CA-IX enzyme activity, and one1 mAb that is suitable for CA-IX imaging purposes. Conclusion These preliminary data presented here could thus form the basis for the development of novel CA-IX targeted immunotherapies and diagnostic tools for the treatment of cancer.

Metrology and the elctric power grid modernization - Djokic, Branislav (Proceedings of the International Conference on Electronics, Telecommunications, Computers, Automation and Nuclear Enfineering (IcETRAN) 2018, 2018)
Metrology, as the science of measurement, is the very basis for acquiring scientific knowledge. In electric power systems, measurements of electrical and non-electrical quantities are necessary for monitoring, control, protection, and sage and reliable operation. Another significant application is revenue metering for industrial, commercial and residential customers. In today’s interdependent world, ensuring uniform metrology inside and across national boundaries is an important enabling factor of national and international trade, including the electrical energy trade. The introduction of distributed power generation, renewable energy resources, and deregulation of electric power utilities has in many countries, been transforming the electric power grids. We are witnessing exciting developments in metrology, on which the Smart Grid is based. This includes smart metering, synchro phasor and frequency measurements, wide-area protection, wide-area situational awareness, digital substations, energy storage and other evolving power system technologies. The proliferation of harmonics in the grid has been increasing over the last decades. With the prominent role of power electronics in new Smart Grid developments, this trend continues. The increased penetration of electric vehicles (EV) and the EV infrastructure emphasizes the necessity for wide frequency band measurements of distorted waveforms. New instrumentation and measurement methods for industrial applications at high-voltage and high-current levels are being developed. The digital measurements of voltage, current, phase, frequency, power and energy are continually improving. This is pushing the boundaries of the high accuracy measurements needed for calibrations. The role of National Measurements Institutes in providing the highest accuracy measurement standards and traceability to SI units is essential. The SI is undergoing profound changes, and the new revised SI is about to be adopted. Metrology has a key role in the research, development and innovation of evolving electric power grid. In the words of Lord Kelvin: “If you cannot measure it, you cannot improve it.”
Keywords: Smart grid; digital sustations; synchrophasor measurements; non-conventional instrument transformers; merging units; digital energy meters; harmonics; metrology; measurement standards; measurement uncertainty; traceability

Advances in the uncertainty evaluation of a 88sr+ single 10n optical clock - Dubé, Pierre; Jian, Bin; Vutha, Amar C. (2018 European Frequency and Time Forum (EFTF), 2018)
We report on recent progress in the evaluation and reduction of the systematic shifts of the strontium ion clock, addressing effects such as the collisional frequency shift, the servo tracking errors, and the blackbody radiation (BBR) shift. The total uncertainty is currently dominated by the BBR field evaluation. All the other known contributions are at least one order of magnitude smaller. Experiments are underway to improve the BBR field evaluation using thermal imaging of a dummy ion trap.
Keywords: single ion clock; optical atomic clock; collisional frequency shift; servo tracking error; blackbody radiation shift; uncertainty evaluation

Direct online quantitation of 2-methyl-3-methoxy-4-phenyl butanoic acid for total microcystin analysis by condensed phase membrane introduction tandem mass spectrometry - Duncan, Kyle D.; Beach, Daniel G.; Wright, Elliott J.; Barsby, Todd; Gill, Chris G.; Krogh, Erik T. (Analytical Methods, 2018)
Microcystins (MCs) are a potent class of hepatotoxins produced by several species of cyanobacteria, which have been responsible for illness and death in livestock and humans. Rapid detection and quantitation are important for the protection of human and environmental health. More than 200 MC variants have been reported, and nearly all release 2-methyl-3-methoxy-4-phenyl butanoic acid (MMPB) upon oxidation. The quantitation of MMPB directly in complex post-oxidation solutions is presented using online condensed phase membrane introduction mass spectrometry with a methanol acceptor phase and negative electrospray ionization. We observe a linear response over several orders of magnitude for MMPB standards, and have applied the technique to measuring total MC in algal suspensions with both positive and negative controls. Preliminary results are reported for the analysis of total microcystins after Lemieux oxidation, at detection limits relevant to regulatory levels in recreational and drinking waters, with no sample clean up. Good quantitative agreement was obtained between measurement of total MCs in an algal reference material by CP-MIMS-MS/MS and LC-MS/MS analysis of total and free MCs. The developed methodology is of interest as an important first step for further development as a rapid benchtop tool for quantitative analysis with future potential use in the field.

Solution to collision induced dissociation mass spectrometry challenge - Beach, Daniel G.; Gabryelski, Wojciech (Analytical and Bioanalytical Chemistry, 2018)

Collision induced dissociation mass spectrometry challenge - Beach, Daniel G.; Gabryelski, Wojciech (Analytical and Bioanalytical Chemistry, 2018)

Spectral retrieval techniques for high-resolution Fourier transform microspectrometers - Velasco, Aitor V.; Herrero-Bermello, Alaine; Podmore, Hugh; Cheben, Pavel; Schmid, Jens H.; Calvo, María L.; Janz, Siegfried; Xu, Dan-Xia; Scott, Alan; Lee, Regina; Taccheo, Stefano; Ferrari, Maurizio; et al. (Fiber Lasers and Glass Photonics: Materials through Applications, 2018)
Spatial heterodyne Fourier transform (SHFT) spectroscopy is based on simultaneous interferometric measurements implementing linearly increasing optical path differences, hence circumventing the need for mechanical components of traditional Fourier transform spectroscopy schemes. By taking advantage of the high mode confinement of the Siliconon-Insulator (SOI). platform, great interferometric lengths can be implemented in a reduced footprint, hence increasing the resolution of the device. However, as resolution increases, spectrometers become progressively more sensitive to environmental conditions, and new spectral retrieval techniques are required. In this work, we present several software techniques that enhance the operation of high-resolution SHFT micro-spectrometers. Firstly, we present two techniques for mitigating and correcting the effects of temperature drifts, based on a temperature-sensitive calibration and phase errors correction. Both techniques are demonstrated experimentally on a 32 Mach-Zehnder interferometers array fabricated in a Silicon-on-insulator chip with microphotonic spirals of linearly increasing length up to 3.779 cm. This configuration provides a resolution of 17 pm in a compact device footprint of 12 mm2. Secondly, we propose the application of compressive-sensing (CS) techniques to SHFT micro-spectrometers. By assuming spectrum sparsity, an undersampled discrete Fourier interferogram is inverted using l1-norm minimization to retrieve the input spectrum. We demonstrate this principle on a subwavelength-engineered SHFT with 32 MZIs and a 50 pm resolution. Correct retrieval of three sparse input signals was experimentally demonstrated using data from 14 or fewer MZIs and applying common CS reconstruction techniques to this data.

Shortly-branched, linear dextrans as efficient binders for silicon/graphite composite electrodes in Li-ion batteries - Zhao, Xiuyun; Yim, Chae-Ho; Du, Naiying; Abu-Lebdeh, Yaser (Industrial & Engineering Chemistry Research, 2018)
There is a need for new binders that are compatible with both silicon and graphite to enable high energy density silicon/graphite composites for Li-ion batteries. In this work, we have evaluated the shortly-branched, linear polysaccharide dextran with graphite-rich composite electrode and battery testing shows a reversible capacity of about 525 mAh g-1 and an excellent cycling stability unlike the conventional poly(vinylidenefluoride) binder. A study of the interface using Impedance Spectroscopy, X-ray Photoelectron Spectroscopy, and post-mortem Scanning Electron Microscopy analysis shows that the superior performance of Dextran is due to the formation of a solid electrolyte interface layer that completely covers the surfaces of silicon and graphite due to a strong interaction between dextran’s hydroxyl or ethereal groups and silicon surface as evidenced by Infrared spectroscopy. This along with its low cost and environmental friendly nature makes it an attractive binder material for Si/graphite composite electrodes in Li-ion batteries.

Identification of n-6 monounsaturated fatty acids in acer seed oils - Sun, Jin-Yue; Wang, Xin-Kun; Smith, Mark A. (Journal of the American Oil Chemists' Society, 2018)
Seed oils from Acer species are a potential source of the nutraceutical fatty acids, nervonic acid (cis‐15‐tetracosenoic acid, NA), and γ‐linolenic acid (cis‐6,9,12‐octadecatrienoic acid, GLA). To further characterize the genus, seed fatty acid content and composition were determined for 20 species of Acer. Fatty acid content ranged from 8.2% for Acer macrophyllum to over 36% for A. mono and A. negundo. The presence of very‐long‐chain fatty acids (VLCFA), with chain length of 20‐carbons or greater, and GLA were characteristic features of the seed oils. In all species, erucic acid (cis‐13‐docosenoic acid, EA) was the predominant VLCFA with the highest level of NA being only 8.6% in A. olivianum. Regioselective lipase digestion demonstrated that VLCFA are largely absent from the sn‐2 position of seed triacylglycerol, whereas GLA is primarily located at this position. Five Acer species contained low levels (<2%) of cis‐12‐octadecenoic acid and cis‐14‐eicosenoic acid, uncommon n‐6 fatty acids not previously reported from Acer.
Keywords: acer; seed oil; sn-2 MAG; very-long-chain fatty acids; n-6 monounsaturated fatty acids; Gamma-linolenic acid; nervonic acid

Very-long-chain fatty acid diversity in nine Heliophila seed oils - Smith, M. A.; Zhang, H. (South African Journal of Botany, 2018)
Heliophila is a genus of approximately 90 recognized plant species endemic to southern Africa and considered the most morphologically diverse genus in the family Brassicaceae. To begin to characterize chemical diversity in the genus, seed oil content and fatty acid composition were determined for 9 species, with representatives from the three major recognized clades. All species produced very-long-chain fatty acids (VLCFAs) as major components of the seed triacylglycerol (TAG) oil, with considerable diversity of fatty acid chain length. The 22-carbon (C22) monounsaturated fatty acid erucic acid (cis-13-docosenoic acid) was the dominant VLCFA in the oil of Heliophila coronopifolia at 47.6% of total seed fatty acids whereas the unusual C26 fatty acid ximenic acid (cis-17-hexacosenoic acid) dominated the VLCFA profile of oil from Heliophila scoparia at 35.8%. Heliophila africana oil was identified as a potential novel source of the nutraceutical fatty acid, nervonic acid (cis-15-tetracosenoic acid). Analysis of the oil of 3 species by sn-1,3 regioselective lipase digestion demonstrated the virtual exclusion of VLCFAs from the sn-2 position of TAG. Examination of the oil from H. scoparia by Matrix-Assisted Laser Desorption/Ionization Time-of-Flight (MALDI-TOF) Mass Spectrometry revealed the presence of high molecular weight TAGs and widespread distribution of VLCFAs among the TAG molecular species. Heliophila species have significant potential as sources of novel seed oil enriched in VLCFAs and as model species to study the mechanisms and evolution of VLCFA biosynthesis in plants.
Keywords: Heliophila; seed oil; very-long-chain fatty acids; nervonic acid; sn-2-MAG

Antioxidant properties and lipid composition of selected microalgae - Banskota, Arjun H.; Sperker, Sandra; Stefanova, Roumiana; Mcginn, Patrick J.; O’leary, Stephen J. B. (Journal of Applied Phycology, 2018)
Marine and freshwater microalgae were evaluated for their antioxidant properties and lipid composition. Both lipophilic (L) and hydrophilic (H) oxygen radical absorbance capacity (ORAC) values were measured. Among the tested microalgae, the marine microalga Nannochloropsis granulata showed the highest total ORAC value at 6948 μmol TE (100 g)−1, followed by the freshwater species Neochloris oleoabundans at 4508 μmol TE (100 g)−1 and Scenedesmus obliquus at 4406 μmol TE (100 g)−1 of algal biomass. Freeze-dried algal biomass was also examined for lipid content by the Folch method. Lipid content ranged from 30.9 to 49.3% and linear regression analysis revealed a statistically significant correlation between the lipid content and the ORAC values. Tested microalgae showed moderate and dose-dependent DPPH radical scavenging activity. The total phenol assay shows that marine microalga Tetraselmis chui had the highest phenolic content at 57.5 μmol GAE g−1 and N. oleoabundans had the lowest at 26.6 μmol GAE g−1 of MeOH extract. A statistically significant correlation was detected between DPPH radical scavenging activity and the phenolic content. Fatty acid analysis revealed that polyunsaturated fatty acids constituted > 45% of the total fatty acid content in N. oleoabundans, Phaeodactylum tricornutum, Porphyridium aerugineum, S. obliquus, and Scenedesmus sp. Total carotenoid concentration ranged from 1.1 to 29.5 mg g−1 of dry algal biomass. Lutein, zeaxanthin, and β-carotene are common carotenoids found in most of the algae tested. P. tricornutum contains significant amount of fucoxanthin at 24.3 mg g−1 algal biomass. These carotenoids also contributed to the overall antioxidative activity of microalgae.
Keywords: microalgae; ORAC; total phenolic; DPPH radical; fatty acids; carotenoids

Optimization of a high-cell-density Polyethylenimine transfection method for rapid protein production in cho-ebna1 cells - Stuible, Matthew; Burlacu, Alina; Perret, Sylvie; Brochu, Denis; Paul-Roc, Béatrice; Baardsnes, Jason; Loignon, Martin; Grazzini, Eric; Durocher, Yves (Journal of Biotechnology, 2018)
For pre-clinical evaluation of biotherapeutic candidates, protein production by transient gene expression (TGE) in Chinese Hamster Ovary (CHO) cells offers important advantages, including the capability of rapidly and cost-effectively generating recombinant proteins that are highly similar to those produced in stable CHO clones. We have established a novel CHO clone (CHO-3E7) expressing a form of the Epstein-Barr virus nuclear antigen-1 (EBNA-1) with improved TGE productivity relative to parental CHO cells. Taking advantage of a new transfection-compatible media formulation that permits prolonged, high-density culture, we optimized transfection parameters (cell density, plasmid vector and polyethylenimine concentrations) and post-transfection culture conditions to establish a new, high-performing process for rapid protein production. The growth media is chemically defined, and a single hydrolysate feed is added post-transfection, followed by periodic glucose supplementation. This method gave significantly higher yields than our standard low-cell density, F17-based CHO-3E7 TGE method, averaging several hundred mg/L for a panel of recombinant proteins and antibodies. Purified antibodies produced using the two methods had distinct glycosylation profiles but showed identical target binding kinetics by SPR. Key advantages of this new protein production platform include the cost-effectiveness of the transfection reagent, the commercial availability of the culture media and the ability to perform high-cell-density transfection without media change.

Intracellular sorting and transcytosis of the rat transferrin receptor antibody OX26 across the blood-brain barrier in vitro is dependent on its binding affinity - Haqqani, Arsalan S.; Thom, George; Burrell, Matthew; Delaney, Christie E.; Brunette, Eric; Baumann, Ewa; Sodja, Caroline; Jezierski, Anna; Webster, Carl; Stanimirovic, Danica B. (Journal of Neurochemistry, 2018)
The blood‐brain barrier (BBB) is a formidable obstacle to the delivery of therapeutics to the brain. Antibodies that bind transferrin receptor, which is enriched in brain endothelial cells, have been shown to cross the BBB and are being developed as fusion proteins to deliver therapeutic cargos to brain targets. Various antibodies have been developed for this purpose and their in vivo evaluation demonstrated that either low affinity or mono‐valent receptor binding re‐directs their transcellular trafficking away from lysosomal degradation and towards improved exocytosis on the abluminal side of the BBB. However, these studies have been performed with antibodies that recognize different TfR epitopes and have different binding characteristics, preventing inter‐study comparisons. In this study, the efficiency of transcytosis in vitro and intracellular trafficking in endosomal compartments were evaluated in an in vitro BBB model for affinity variants (Kd from 5 nM ‐174 nM) of the rat TfR‐binding antibody, OX26. Distribution in subcellular fractions of the rat brain endothelial cells was determined using both targeted quantitative proteomics (SRM) and fluorescent imaging with markers of early‐ and late endosomes. The OX26 variants with affinities of 76 nM and 108 nM showed improved trancytosis (Papp values) across the in vitro BBB model compared to a 5 nM OX26. Whereas ~40% of the 5 nM OX26 and ~35% of TfR co‐localized with late‐endosome/lysosome compartment, 76 nM and 108 nM affinity variants showed lower amounts in lysosomes and a predominant co‐localization with early endosome markers. The study links bi‐valent TfR antibody affinity to mechanisms of sorting and trafficking away from late endosomes and lysosomes, resulting in improvement in their transcytosis efficiency.
Keywords: blood-brain barrier; transferrin receptor antibody; intracellular trafficking; quantitative targeted proteomics; affinity optimization; analgesic peptides

Evaluation of a numerical wave modelling tool for studying the overtopping of rubblemound breakwaters - Pilechi, Abolghasem; Baker, Scott; Cornett, Andrew (Proceedings of the 7th International Conference on the Application of Physical Modelling in Coastal and Port Engineering and Science (Coastlab18), 2018)
Wave overtopping of rubblemound breakwaters is a complex physical process which influences the functional efficiency and structural stability of the structure. The mean overtopping discharge resulting from design wave and water level conditions is often an important consideration affecting the selection of breakwater profile and crest height. The volume of water which passes over the crest of a breakwater depends on the structure geometry and composition, the nearshore bathymetry, the water level, and the seastate conditions. Physical modelling at large scale has traditionally provided a robust and reliable means to support the design of rubblemound breakwaters. Recent advancements in computational fluid dynamics and computing power have led to increasing efforts to use numerical modelling as a complementary tool to physical modelling for breakwater design applications. This paper compares measurements from a physical model study of rubblemound breakwaters conducted by the National Research Council of Canada (NRC) with numerical simulations produced by the numerical model IH2VOF. The skill of the IH2VOF model in predicting free-surface elevations and mean wave overtopping discharges is assessed. The comparisons are conducted for a range of seastate conditions, water levels, and breakwater geometries. The findings demonstrate that IH2VOF offers a viable tool to complement physical model testing for rubblemound breakwater design applications.
Keywords: IH2VOF; overtopping; VOF; CFD; physical modelling; numerical modelling

Physical modelling of shoreline improvements in the Caribbean - Baker, Scott; Logan, Seth; Des Vignes, Terence; Macintosh, Kevin (Proceedings of the 7th International Conference on the Application of Physical Modelling in Coastal and Port Engineering and Science (Coastlab18), 2018)
This paper discusses a 3D physical modelling study that was commissioned to support shoreline improvements for a new resort development in the Caribbean. The model included a recreation of the complex foreshore and shoreline at the project site at a geometric scale of 1:25. Beach sediment was modelled using fine sand that deformed naturally in response to wave forcing. The model was outfitted with a directional wave machine to generate a wide range of realistic seastates, and was equipped with instrumentation to measure wave conditions, wave-induced nearshore currents, and changes in the plan and profile shape of the model beach. Nearly 150 individual tests were conducted to assess the impact of proposed coastal structures on the wave conditions and nearshore currents, as well as their effect on sediment transport processes and the response of the beach, for a range of prescribed wave conditions and water levels. These investigations generated a large quantity of valuable information which will be used to optimize and support the detailed design of the waterfront improvements and obtain the necessary permits required for construction.
Keywords: shoreline improvements; sediment transport; coastal processes; coastal structures; breakwaters

Special track on bioinformatics (BIO)(editorial) - Lecca, P.; Tulpan, D.; Corchado, J. M. (Proceedings of the ACM Symposium on Applied Computing, 2018)

Excited state non-adiabatic dynamics of the smallest polyene, trans 1,3-butadiene. I. Time-resolved photoelectron-photoion coincidence spectroscopy - Boguslavskiy, Andrey E.; Schalk, Oliver; Gador, Niklas; Glover, William J.; Mori, Toshifumi; Schultz, Thomas; Schuurman, Michael S.; Martínez, Todd J.; Stolow, Albert (The Journal of Chemical Physics, 2018)
The ultrafast excited state dynamics of the smallest polyene, trans-1,3-butadiene, were studied by femtosecond time-resolved photoelectron-photoion coincidence (TRPEPICO) spectroscopy. The evolution of the excited state wavepacket, created by pumping the bright 1Bu (ππ*) electronic state at its origin of 216 nm, is projected via one- and two-photon ionization at 267 nm onto several ionization continua. The results are interpreted in terms of Koopmans’ correlations and Franck-Condon factors for the excited and cationic states involved. The known predissociative character of the cation excited states is utilized to assign photoelectron bands to specific continua using TRPEPICO spectroscopy. This permits us to report the direct observation of the famously elusive S1(21Ag) dark electronic state during the internal conversion of trans 1,3-butadiene. Our phenomenological analysis permits the spectroscopic determination of several important time constants. We report the overall decay lifetimes of the 11Bu and 21Ag states and observe the re-appearance of the hot ground state molecule. We argue that the apparent dephasing time of the S2(11Bu) state, which leads to the extreme breadth of the absorption spectrum, is principally due to large amplitude torsional motion on the 1Bu surface in conjunction with strong non-adiabatic couplings via conical intersections, whereupon nuclear wavepacket revivals to the initial Franck-Condon region become effectively impossible. In Paper II [W. J. Glover et al., J. Chem. Phys. 148, 164303 (2018)], ab initio multiple spawning is used for on-the-fly computations of the excited state non-adiabatic wavepacket dynamics and their associated TRPEPICO observables, allowing for direct comparisons of experiment with theory.

Excited state non-adiabatic dynamics of the smallest polyene, trans 1,3-butadiene. II. Ab initio multiple spawning simulations - Glover, William J.; Mori, Toshifumi; Schuurman, Michael S.; Boguslavskiy, Andrey E.; Schalk, Oliver; Stolow, Albert; Martínez, Todd J. (The Journal of Chemical Physics, 2018)
The excited state non-adiabatic dynamics of the smallest polyene, trans 1,3-butadiene (BD), has long been the subject of controversy due to its strong coupling, ultrafast time scales and the difficulties that theory faces in describing the relevant electronic states in a balanced fashion. Here we apply Ab Initio Multiple Spawning (AIMS) using state-averaged complete active space multistate second order perturbation theory [SA-3-CAS(4/4)-MSPT2] which describes both static and dynamic electron correlation effects, providing a balanced description of both the initially prepared bright 11Bu (ππ*) state and non-adiabatically coupled dark 21Ag state of BD. Importantly, AIMS allows for on-the-fly calculations of experimental observables. We validate our approach by directly simulating the time resolved photoelectron-photoion coincidence spectroscopy results presented in Paper I [A. E. Boguslavskiy et al., J. Chem. Phys. 148, 164302 (2018)], demonstrating excellent agreement with experiment. Our simulations reveal that the initial excitation to the 11Bu state rapidly evolves via wavepacket dynamics that follow both bright- and dark-state pathways as well as mixtures of these. In order to test the sensitivity of the AIMS results to the relative ordering of states, we considered two hypothetical scenarios biased toward either the bright 1Bu or the dark 21Ag state. In contrast with AIMS/SA-3-CAS(4/4)-MSPT2 simulations, neither of these scenarios yields favorable agreement with experiment. Thus, we conclude that the excited state non-adiabatic dynamics in BD involves both of these ultrafast pathways.

Estimating peatland water table depth and net ecosystem exchange: a comparison between satellite and airborne imagery - Kalacska, Margaret; Arroyo-Mora, J.; Soffer, Raymond; Roulet, Nigel; Moore, Tim; Humphreys, Elyn; Leblanc, George; Lucanus, Oliver; Inamdar, Deep (Remote Sensing, 2018)
Peatlands play a fundamental role in climate regulation through their long-term accumulation of atmospheric carbon. Despite their resilience, peatlands are vulnerable to climate change. Remote sensing offers the opportunity to better understand these ecosystems at large spatial scales through time. In this study, we estimated water table depth from a 6-year time sequence of airborne shortwave infrared (SWIR) hyperspectral imagery. We found that the narrowband index NDWI1240 is a strong predictor of water table position. However, we illustrate the importance of considering peatland anisotropy on SWIR imagery from the summer months when the vascular plants are in full foliage, as not all illumination conditions are suitable for retrieving water table position. We also model net ecosystem exchange (NEE) from 10 years of Landsat TM5 imagery and from 4 years of Landsat OLI 8 imagery. Our results show the transferability of the model between imagery from sensors with similar spectral and radiometric properties such as Landsat 8 and Sentinel-2. NEE modeled from airborne hyperspectral imagery more closely correlated to eddy covariance tower measurements than did models based on satellite images. With fine spectral, spatial and radiometric resolutions, new generation satellite imagery and airborne hyperspectral imagery allow for monitoring the response of peatlands to both allogenic and autogenic factors.
Keywords: hyperspectral; Sentinel-2; Landsat TM5; Landsat 8 OLI; bog; CASI; SASI; northern peatland; hydrology; Mer Bleue

Deep neural networks for direct, featureless learning through observation: the case of two-dimensional spin models - Mills, Kyle; Tamblyn, Isaac (Physical Review E, 2018)
We demonstrate the capability of a convolutional deep neural network in predicting the nearest-neighbor energy of the 4×4 Ising model. Using its success at this task, we motivate the study of the larger 8×8 Ising model, showing that the deep neural network can learn the nearest-neighbor Ising Hamiltonian after only seeing a vanishingly small fraction of configuration space. Additionally, we show that the neural network has learned both the energy and magnetization operators with sufficient accuracy to replicate the low-temperature Ising phase transition. We then demonstrate the ability of the neural network to learn other spin models, teaching the convolutional deep neural network to accurately predict the long-range interaction of a screened Coulomb Hamiltonian, a sinusoidally attenuated screened Coulomb Hamiltonian, and a modified Potts model Hamiltonian. In the case of the long-range interaction, we demonstrate the ability of the neural network to recover the phase transition with equivalent accuracy to the numerically exact method. Furthermore, in the case of the long-range interaction, the benefits of the neural network become apparent; it is able to make predictions with a high degree of accuracy, and do so 1600 times faster than a CUDA-optimized exact calculation. Additionally, we demonstrate how the neural network succeeds at these tasks by looking at the weights learned in a simplified demonstration.

Convolutional neural networks for atomistic systems - Ryczko, Kevin; Mills, Kyle; Luchak, Iryna; Homenick, Christa; Tamblyn, Isaac (Computational Materials Science, 2018)
We introduce a new method, called CNNAS (convolutional neural networks for atomistic systems), for calculating the total energy of atomic systems which rivals the computational cost of empirical potentials while maintaining the accuracy of ab initio calculations. This method uses deep convolutional neural networks (CNNs), where the input to these networks are simple representations of the atomic structure. We use this approach to predict energies obtained using density functional theory (DFT) for 2D hexagonal lattices of various types. Using a dataset consisting of graphene, hexagonal boron nitride (hBN), and graphene-hBN heterostructures, with and without defects, we trained a deep CNN that is capable of predicting DFT energies to an extremely high accuracy, with a mean absolute error (MAE) of 0.198 meV/atom (maximum absolute error of 16.1 meV/atom). To explore our new methodology, we investigate the ability of a deep neural network (DNN) in predicting a Lennard-Jones energy and separation distance for a dataset of dimer molecules in both two and three dimensions. In addition, we systematically investigate the flexibility of the deep learning models by performing interpolation and extrapolation tests.
Keywords: dimer molecules; deep learning; convolutional neural networks; density functional theory; 2D materials

Permanent magnets produced by cold spray additive manufacturing - Lamarre, Jean-Michel; Bernier, Fabrice (Proceedings of International Forum on Magnetic Applications, Technologies and Materials (MAGNETICS 2017), 2018)

Printed UHF RFID reader antennas for potential retail applications - Xiao, Gaozhi; Aflaki, Pouya; Lang, Stephen; Zhang, Zhiyi; Tao, Ye; Py, Christophe; Lu, Philip; Martin, Cedric; Chang, Shoude (IEEE Journal of Radio Frequency Identification, 2018)
Automation of retail industry is calling for the low cost solution due to its sheer size and varied needs. Printed electronics offers a great potential in addressing the needs in point-of-sales, inventory management and self-service, in particular the RFID systems consisting of the printed components. Screen printed UHF RFID reader antennas have been investigated in this work for their application potentials in retails for achieving easy-implementation and low cost. The results obtained clearly demonstrated that the screen printed UHF RFID reader antennas are closely matching the performance of their circularly polarized patch antenna counterparts fabricated using the conventional chemical etching method in most critical specifications. The screen printed antennas have been explored for the monitoring of items on metal shelves targeting potential inventory management and point-of-sales applications. It has been found that all tagged items can be identified using a home developed UHF RFID system consisting of the printed antennas. The findings pave the way for the use of low cost printed antennas in the potential retail automation applications.
Keywords: UHF RFID system; antenna; printed electronics; screen printing; retail automation; smart shelf

Entanglement and co-tunneling of two equivalent protons in hydrogen bond pairs - Smedarchina, Zorka; Siebrand, Willem; Fernández-Ramos, Antonio (The Journal of Chemical Physics, 2018)
A theoretical study is reported of a system of two identical symmetric hydrogen bonds, weakly coupled such that the two mobile protons can move either separately (stepwise) or together (concerted). It is modeled by two equivalent quartic potentials interacting through dipolar and quadrupolar coupling terms. The tunneling Hamiltonian has two imaginary modes (reaction coordinates) and a potential with a single maximum that may turn into a saddle-point of second order and two sets of (inequivalent) minima. Diagonalization is achieved via a modified Jacobi-Davidson algorithm. From this Hamiltonian the mechanism of proton transfer is derived. To find out whether the two protons move stepwise or concerted, a new tool is introduced, based on the distribution of the probability flux in the dividing plane of the transfer mode. While stepwise transfer dominates for very weak coupling, it is found that concerted transfer (co-tunneling) always occurs, even when the coupling vanishes since the symmetry of the Hamiltonian imposes permanent entanglement on the motions of the two protons. We quantify this entanglement and show that, for a wide range of parameters of interest, the lowest pair of states of the Hamiltonian represents a perfect example of highly entangled quantum states in continuous variables. The method is applied to the molecule porphycene for which the observed tunneling splitting is calculated in satisfactory agreement with experiment, and the mechanism of double-proton tunneling is found to be predominantly concerted. We show that, under normal conditions, when they are in the ground state, the two porphycene protons are highly entangled, which may have interesting applications. The treatment also identifies the conditions under which such a system can be handled by conventional one-instanton techniques.

Airborne hyperspectral evaluation of maximum gross photosynthesis, gravimetric water content, and CO2 uptake efficiency of the Mer Bleue Ombrotrophic Peatland - Arroyo-Mora, J.; Kalacska, Margaret; Soffer, Raymond; Moore, Tim; Roulet, Nigel; Juutinen, Sari; Ifimov, Gabriela; Leblanc, George; Inamdar, Deep (Remote Sensing, 2018)
Peatlands cover a large area in Canada and globally (12% and 3% of the landmass, respectively). These ecosystems play an important role in climate regulation through the sequestration of carbon dioxide from, and the release of methane to, the atmosphere. Monitoring approaches, required to understand the response of peatlands to climate change at large spatial scales, are challenged by their unique vegetation characteristics, intrinsic hydrological complexity, and rapid changes over short periods of time (e.g., seasonality). In this study, we demonstrate the use of multitemporal, high spatial resolution (1 m2) hyperspectral airborne imagery (Compact Airborne Spectrographic Imager (CASI) and Shortwave Airborne Spectrographic Imager (SASI) sensors) for assessing maximum instantaneous gross photosynthesis (PGmax) in hummocks, and gravimetric water content (GWC) and carbon uptake efficiency in hollows, at the Mer Bleue ombrotrophic bog. We applied empirical models (i.e., in situ data and spectral indices) and we derived spatial and temporal trends for the aforementioned variables. Our findings revealed the distribution of hummocks (51.2%), hollows (12.7%), and tree cover (33.6%), which is the first high spatial resolution map of this nature at Mer Bleue. For hummocks, we found growing season PGmax values between 8 μmol m−2 s−1 and 12 μmol m−2 s−1 were predominant (86.3% of the total area). For hollows, our results revealed, for the first time, the spatial heterogeneity and seasonal trends for gravimetric water content and carbon uptake efficiency for the whole bog.
Keywords: airborne hyperspectral; Compact Airborne Spectrographic Imager (CASI); Shortwave Airborne Spectrographic Imager (SASI); peatlands; normalized difference water index (NDWI); gravimetric water content; carbon uptake; photosynthesis; bog; Mer Bleue

Design and synthesis of new fullerene derivatives for organic solar cells - Lu, Jianping; Alem, Salima; Dadvand, Afshin; Ding, Jianfu; Tao, Ye (Renewable Energy and Power Quality Journal, 2018)
Bulk heterojunction (BHJ) organic solar cells based on p-type polymers and n-type fullerene derivatives have attracted increasing attention due to their promising potential for providing low–cost solar electricity. In this paper, we will introduce our recent work on the development of new fullerene derivatives. Through Rh complex catalyzed coupling reactions and cycloaddition reactions, we attached several organic functional groups to the fullerene skeleton. It was found that the organic substituents had little impact on the fullerene energy levels. Instead, the organic substituents have huge impact on the other physical properties of the resulting fullerene derivatives, such as solubility, crystallinity, and electron mobility. We designed and synthesized a novel series of alkoxy substituted indene derivatives as solubilizing groups for fullerenes. Preliminary experimental results demonstrated that these 5-alkoxyindene modified C70 derivatives are superior to widely used PC71BM when blended with poly[N-heptadecanyl-2,7-carbazole-alt-5,5-(4',7'-di-2-thienyl-2',1',3'- benzothiadiazole)](PCDTBT) in BHJ solar cells. The device series resistance decreased from 10 cm2 for the PC71BM based device to 4 cm2 for the 5-methoxyindene-C70 monoadduct based device. As a result, the device fill factor increased from 0.60 to 0.69, and the overall EQE-calibrated power conversion efficiency was enhanced from 5.6% to 6.2%.
Keywords: fullerene derivatives; organic solar cells; 5-alkoxyindene; substituent effects

EGSnrc calculation of activity calibration factors for the Vinten ionization chamber - Townson, R.; Tessier, F.; Galea, R. (Applied Radiation and Isotopes, 2018)
The National Physical Laboratory Vinten 671 chamber was selected as a proving ground for a new radionuclide source model in the EGSnrc software. The computational Vinten model is validated against measurements of radionuclide artifacts whose activities were determined by absolute methods. The response of the Vinten chamber is first calculated as a function of gamma energy, but more strikingly, an explicit simulation of radionuclide decay was implemented and now permits the direct determination of a calibration factor, including additional effects due to all decay paths of the radionuclide. The Monte Carlo and experimental calibration factors are found to agree at the percent level, in absolute terms.
Keywords: ionization chambers; Monte Carlo simulation; EGSnrc

Characterization challenges for a cellulose nanocrystal reference material: dispersion and particle size distributions - Jakubek, Zygmunt J.; Chen, Maohui; Couillard, Martin; Leng, Tianyang; Liu, Leslie; Zou, Shan; Baxa, Ulrich; Clogston, Jeffrey D.; Hamad, Wadood Y.; Johnston, Linda J. (Journal of Nanoparticle Research, 2018)
Cellulose nanocrystals (CNCs) have high aspect ratios, polydisperse size distributions, and a strong propensity for aggregation, all of which make them a challenging material for detailed size and morphology characterization. A CNC reference material produced by sulfuric acid hydrolysis of softwood pulp was characterized using a combination of dynamic light scattering (DLS), atomic force microscopy (AFM), transmission electron microscopy, and X-ray diffraction. As a starting point, a dispersion protocol using ultrasonication was developed to provide CNC suspensions with reproducible size distributions as assessed by DLS. Tests of various methods for AFM sample preparation demonstrated that spin coating on a positively charged substrate maximizes the number of individual particles for size analysis, while minimizing the presence of agglomerates. The effects of sample-to-sample variability, analyst bias, and sonication on size distributions were assessed by AFM. The latter experiment indicated that dispersion of agglomerates by sonication did not significantly change the size distribution of individual CNCs in suspension. Comparison with TEM data demonstrated that the two microscopy methods provide similar results for CNC length (mean ~ 80 nm); however, the particle width as measured by TEM is approximately twice that of the CNC height (mean 3.5 nm) measured by AFM. The individual crystallite size measured by X-ray diffraction is intermediate between the two values, although closer to the AFM height, possibly indicating that laterally agglomerated CNCs contribute to the TEM width. Overall, this study provides detailed information that can be used to assess the factors that must be considered in measuring CNC size distributions, information that will be useful for benchmarking the performance of different industrially sourced materials.
Keywords: Cellulose nanocrystals; Dispersion; Particle size distribution; Atomic force microscopy; Transmission electron microscopy; Dynamic light scattering; Biopolymer

Ultra-broadband mode converter and multiplexer based on sub-wavelength structures - Gonzalez-Andrade, David; Wanguemert-Perez, Juan Gonzalo; Velasco, Aitor; Ortega-Monux, Alejandro; Herrero-Bermello, Alaine; Molina-Fernandez, Inigo; Halir, Robert; Cheben, Pavel (IEEE Photonics Journal, 2018)
Current bandwidth capacity provided by wavelength-division multiplexing and polarization-division multiplexing is insufficient to keep up with the increasing bandwidth demand required for new services. Mode-division multiplexing technology paves the way to further increase transmission and bandwidth capacities in photonic interconnects. In this work, we propose an ultra-broadband two-mode converter and de/multiplexer based on a sub-wavelength engineered multimode interference coupler, a 90° phase shifter and a symmetric Y-junction for the silicon on insulator platform. Sub-wavelength grating waveguides enable dispersion engineering to further increase the bandwidth operation of conventional multimode interference coupler and, subsequently, of mode de/multiplexer based on them. Full 3D simulations of the designed mode converter and de/multiplexer show insertion losses below than 0.84 dB and crosstalk lower than ± 20 dB over an unprecedented bandwidth of 300 nm (1.4 × 1.7 μm). The overall footprint of the proposed devices is only 36 μm × 3.7 μm.
Keywords: mode-division multiplexing; mode-converter; broadband; sub-wavelength grating waveguides; silicon-on-insulator

Development and validation of a stabilized immersed boundary CFD model for freezing and melting with natural convection - Blais, Bruno; Ilinca, Florin (Computers & Fluids, 2018)
Numerous processes in the automotive, additive manufacturing or energy storage industries require an accurate prediction of the solidification (freezing) and melting (thawing) dynamics of substances. The numerical modeling of these phase change is highly complex because it includes sharp moving interfaces and strong discontinuities in the material properties. This complexity is often exacerbated by the occurrence of natural convection, which induces a strong coupling between the motion of the liquid and the position of the solid-liquid interface. This leads to strongly coupled non-linear thermo-fluid problems which have to be solved in complex geometries. In this work, we introduce two novel stabilized finite element models to predict the phase change with natural convection. The first model uses a more classical viscosity approach to impose stasis in the solid region whereas the second one is based on an immersed boundary formulation to accurately describe the solid-fluid interface. The efficiency of the stabilized approach is first demonstrated by studying the Stefan problem. The two approaches to impose stasis are then compared using 2D test cases before they are both used to study melting in a rectangular (2D) and prismatic (3D) cavity. Significant differences are observed in the flow profiles and the solid-liquid interface between the 2D and the 3D simulations.
Keywords: multiphase flows; melting and freezing; selective catalytic reduction (SCR); computational fluid dynamics; finite element method; immersed boundary method

Copper ion assisted photochemical vapor generation of chlorine for its sensitive determination by sector field inductively coupled plasma mass spectrometry - Hu, Jing; Sturgeon, Ralph E.; Nadeau, Kenny; Hou, Xiandeng; Zheng, Chengbin; Yang, Lu (Analytical Chemistry, 2018)
A novel, reliable, and sensitive approach for the determination of chlorine by sector field inductively coupled plasma mass spectrometry (SF-ICPMS) using photochemical vapor generation for sample introduction is presented. Methyl chloride is generated from different chlorine species in a flow-through photochemical reactor using a 1% solution of acetic acid containing 7.5 μg g–1 of Cu2+. The volatile product is directed by an argon carrier gas to a gas–liquid separator and introduced into the instrument. A sample flow rate at 1.7 mL min–1 and a 45 s irradiation time provided a 74-fold enhancement in sensitivity compared to conventional nebulization. A blank-limited detection limit of 0.5 ng g–1 for chloride, suitable for quantitation at trace levels, was achieved. The proposed method was validated by analysis of two certified reference materials, NIST SRM 1568b rice flour and SRM 1571 orchard leaves, with satisfactory results, as well as three varieties of bottled water, achieving spike recoveries between 101% and 105%.
Keywords: chlorine; photochemical vapor generation; copper; ICP-MS

Optimal configuration of isolated hybrid AC/DC microgrids - Hamad, Amr A.; Nassar, Mohammed E.; El Saadany, Ehab F.; Salama, M. M. A. (IEEE Transactions on Smart Grid, 2018)
This paper proposes a model for planning isolated microgrids. The goal of the proposed model is to minimize the investment, operational, and total costs of an isolated microgrid through the full identification of the system configuration. The model designates the optimal type of microgrid, i.e., ac, dc, or hybrid ac/dc, and the optimal sizing of both the distributed energy resources (DERs) and the electronic power converters, if needed. To render this planning approach generic, the model accommodates a wide variety of DERs, including ac and dc generators, capacitors, and energy storage systems. The detailed operational criteria of each power apparatus are taken into account in order to provide reliable operational scenarios. As a means of guaranteeing active and reactive power adequacy in isolated microgrids, the stochastic nature of generation and demand are also considered. The proposed model was developed analytically as a mixed integer nonlinear problem so that obtaining solution optima is thus possible with the use of a deterministic branch-and-bound nonlinear solver. The validity and effectiveness of the new formulation have been demonstrated through several case studies involving varied load topologies.
Keywords: distributed energy resources (DER); hybrid ac/dc microgrids; isolated microgrids; planning model

The development of the advanced cryogenic radiometer facility at NRC - Gamouras, A; Todd, A. D. W.; Côté, É; Rowell, N. L. (Journal of Physics: Conference Series, 2018)
The National Research Council (NRC) of Canada has established a next generation facility for the primary realization of optical radiant power. The main feature of this facility is a new cryogenic electrical substitution radiometer with a closed-cycle helium cryocooler. A monochromator-based approach allows for detector calibrations at any desired wavelength. A custom-designed motion apparatus includes two transfer standard radiometer mounting ports which has increased our measurement capability by allowing the calibration of two photodetectors in one measurement cycle. Measurement uncertainties have been improved through several upgrades, including newly designed and constructed transimpedance amplifiers for the transfer standard radiometers, and a higher power broadband light source. The most significant improvements in uncertainty arise from the enhanced characteristics of the new cryogenic radiometer including its higher cavity absorptance and reduced non-equivalence effects.

Human serum albumin stabilizes aqueous silver nanoparticle suspensions and inhibits particle uptake by cells - Kennedy, D. C.; Qian, H.; Gies, V.; Yang, L. (Environmental Science: Nano, 2018)
Incubation of 20 nm silver nanoparticles with human serum albumin (HSA) stabilizes the nanoparticles against aggregation and dissolution and produces particles that can be lyophilized for longterm storage and redispersed in water consistently. Biological studies of this stabilized material showed reduced toxicity and cellular uptake compared to other 20 nm particles.

Nanoreinforced epoxy and adhesive joints incorporating boron nitride nanotubes - Jakubinek, Michael B.; Ashrafi, Behnam; Martinez-Rubi, Yadienka; Rahmat, Meysam; Yourdkhani, Mostafa; Kim, Keun Su; Laqua, Kurtis; Yousefpour, Ali; Simard, Benoit (International Journal of Adhesion and Adhesives, 2018)
Boron nitride nanotubes (BNNTs) offer complimentary properties to carbon nanotubes (CNTs) and interact more favorably with epoxies than do CNTs. This could make BNNTs the preferred nanotube for reinforcing epoxy when electrical conductivity is not required, and particularly where features such as transparency/color, neutron absorption or electrical insulation are advantageous. Here we report epoxy nanocomposites containing 1 to 7 wt% raw BNNTs. The elastic modulus and fracture toughness increased progressively with loading up to 5 wt% BNNTs. Adhesive joints (ASTM D1002) indicated average improvements of ~10% in joint strength at 2 wt% raw BNNTs, but substantially reduced strength for a 5 wt% BNNT adhesive joint. Observation of the failure surfaces suggests that BNNTs impede crack propagation leading to increased joint performance despite a mixed-mode failure with a substantial contribution from adhesive failure. BNNTs purified by removing the elemental boron impurity were more effective, yielding 15% joint strength improvements at 1 wt% loading. This nanocomposite is also semi-transparent, showing the potential for reinforced, electrically insulating, transparent adhesives based on BNNTs.
Keywords: nanocomposites; mechanical properties; adhesion; joints/joining

Final report of the SIM.QM-S7 supplementary comparison, trace metals in drinking water - Yang, Lu; Nadeau, Kenny; Pihillagawa, Indu Gedara; Meija, Juris; Grinberg, Patricia; Mester, Zoltan; Moya, Edith Valle; Solís González, Faviola Alejandra; Torres, María del Rocio Arvizu; Yañez Muñoz, Oscar; Lara-Manzano, Judith Velina; Mazzitello, Gisela; et al. (Metrologia, 2018)
SIM.QM-S7 was performed to assess the analytical capabilities of National Metrology Institutes (NMIs) and Designated Institutes (DIs) of SIM members (or other regions) for the accurate determination of trace metals in drinking water. The study was proposed by the coordinating laboratories National Research Council Canada (NRC) and Centro Nacional de Metrologia (CENAM) as an activity of Inorganic Analysis Working Group (IAWG) of Consultative Committee for Amount of Substance - Metrology in Chemistry and Biology (CCQM). Participants included 16 NMIs/DIs from 15 countries. No measurement method was prescribed by the coordinating laboratories. Therefore, NMIs used measurement methods of their choice. However, the majority of NMIs/DIs used ICP-MS. This SIM.QM-S7 Supplementary Comparison provides NMIs/DIs with the needed evidence for CMC claims for trace elements in fresh waters and similar matrices.

Radical-initiated and thermally induced hydrogermylation of alkenes on the surfaces of germanium nanosheets - Yu, Haoyang; Helbich, Tobias; Scherf, Lavinia M.; Chen, Jian; Cui, Kai; Fässler, Thomas F.; Rieger, Bernhard; Veinot, Jonathan G. C. (Chemistry of Materials, 2018)
The synthesis of germanium nanomaterials with well-defined surface chemistry is of considerable interest because of not only general scientific curiosity but also their vast potential in optoelectronics, energy storage, and the semiconductor industry. Herein, we report a straightforward preparative route that yields hydride-terminated germanium nanosheet (H-GeNS) monolayers via sonochemical exfoliation of hydride-terminated germanane flakes (HGe-flakes) derived from crystalline CaGe2. We subsequently show that these freestanding H-GeNSs are readily functionalized by radical-initiated and thermally induced hydrogermylation. Furthermore, we demonstrate that following functionalization the crystal structure of the GeNSs remains intact, and the introduction of organic moieties to the GeNS surfaces imparts improved thermal stability and solvent compatibility.

Application of Assisted Design of Antibody and Protein Therapeutics (ADAPT) improves efficacy of a Clostridium difficile toxin a single-domain antibody - Sulea, Traian; Hussack, Greg; Ryan, Shannon; Tanha, Jamshid; Purisima, Enrico O. (Scientific Reports, 2018)
Assisted Design of Antibody and Protein Therapeutics (ADAPT) is an affinity maturation platform interleaving predictions and testing that was previously validated on monoclonal antibodies (mAbs). This study expands the applicability of ADAPT to single-domain antibodies (sdAbs), a promising class of recombinant antibody-based biologics. As a test case, we used the camelid sdAb A26.8, a VHH that binds Clostridium difficile toxin A (TcdA) relatively weakly but displays a reasonable level of TcdA neutralization. ADAPT-guided A26.8 affinity maturation resulted in an improvement of one order of magnitude by point mutations only, reaching an equilibrium dissociation constant (KD) of 2 nM, with the best binding mutants having similar or improved stabilities relative to the parent sdAb. This affinity improvement generated a 6-fold enhancement of efficacy at the cellular level; the A26.8 double-mutant T56R,T103R neutralizes TcdA cytotoxicity with an IC50 of 12 nM. The designed mutants with increased affinities are predicted to establish novel electrostatic interactions with the antigen. Almost full additivity of mutation effects is observed, except for positively charged residues introduced at adjacent positions. Furthermore, analysis of false-positive predictions points to general directions for improving the ADAPT platform. ADAPT guided the efficacy enhancement of an anti-toxin sdAb, an alternative therapeutic modality for C. difficile.

Size and shape distributions of carbon black aggregates by transmission electron microscopy - Grulke, Eric A.; Rice, Stephen B.; Xiong, Jincheng; Yamamoto, Kazuhiro; Yoon, Tae Hyun; Thomson, Kevin; Saffaripour, Meghdad; Smallwood, Greg J.; Lambert, Joshua W.; Stromberg, Arnold J.; Macy, Ryan; Briot, Nicolas J.; et al. (Carbon, 2018)
Carbon black aggregate size and shape affects its performance in many applications. In this interlaboratory comparison, an industry reference carbon black, SRB8, was analysed with a protocol based on ASTM D3849-14a, a method for morphological characterization of carbon black aggregates using electron microscopy. Multiple descriptor types (size, elongation, ruggedness, plus those of ASTM D3849-14a) were assessed for repeatability, reproducibility, and measurement uncertainties. Carbon black aggregates have been characterized using descriptor correlations: two important such correlations are affinity coefficients and fractal exponents. SRB8 aggregates appear to be self-affine, i.e., their width and length descriptors scale anisotropically. ASTM D3849-14a derived descriptors have low interlaboratory reproducibilities and high measurement uncertainties. When these descriptors are used for projected area-based fractal analysis, the estimated fractal exponents do not have realistic values. However, the use of an average nodule diameter generated self-consistent values of fractal exponents with measurement uncertainties of about 9%. Carbon black aggregates can be categorized using shape descriptors into the categories: spheroidal, ellipsoidal, branched, and linear. These shape categories contribute non-uniformly to descriptor values across their data ranges and lead to multimodal distributions. These findings illustrate the importance of assessing data quality and measurement uncertainty for particle size and shape distributions.

The correlation coefficient as a simple tool for the localization of errors in spectroscopic imaging data - Inamdar, Deep; Leblanc, George; Soffer, Raymond; Kalacska, Margaret (Remote Sensing, 2018)
The correlation coefficient (CC) was substantiated as a simple, yet robust statistical tool in the quality assessment of hyperspectral imaging (HSI) data. The sensitivity of the metric was also characterized with respect to artificially-induced errors. The CC was found to be sensitive to spectral shifts and single feature modifications in hyperspectral ground data despite the high, artificially-induced, signal-to-noise ratio (SNR) of 100:1. The study evaluated eight airborne hyperspectral images that varied in acquisition spectrometer, acquisition date and processing methodology. For each image, we identified a uniform ground target region of interest (ROI) that was comprised of a single asphalt road pixel from each column within the sensor field-of-view (FOV). A CC was calculated between the spectra from each of the pixels in the ROI and the data from the center pixel. Potential errors were located by reductions in the CCs below a designated threshold, which was derived from the results of the sensitivity tests. The spectral range associated with each error was established using a windowing technique where the CCs were recalculated after removing the spectral data within various windows. Errors were isolated in the spectral window that removed the previously-identified reductions in the CCs. Finer errors were detected by calculating the CCs across the ROI in the spectral range surrounding various atmospheric absorption features. Despite only observing deviations in the CCs from the 3rd–6th decimal places, non-trivial errors were detected in the imagery. An error was detected within a single band of the shortwave infrared imagery. Errors were also observed throughout the visible-near-infrared imagery, especially in the blue end. With this methodology, it was possible to immediately gauge the spectral consistency of the HSI data across the FOV. Consequently, the effectiveness of various processing methodologies and the spectral consistency of the imaging spectrometers themselves could be studied. Overall, the research highlights the utility of the CC as a simple, low monetary cost, analytical tool for the localization of errors in spectroscopic imaging data.
Keywords: imaging spectroscopy; hyperspectral; correlation coefficient; error detection; data quality assessment

High-directionality L-shaped fiber-chip grating couplers realized in 300-mm silicon-on-insulator platform with deep-ultraviolet lithography (conference presentation) - Alonso-Ramos, Carlos A.; Benedikovich, Daniel; Pérez-Galacho, Diego; Guerber, Sylvain; Vakarin, Vladyslav; Marcaud, Guillaume; Le Roux, Xavier; Cassan, Eric; Marris-Morini, Delphine; Cheben, Pavel; Boeuf, Frédéric; Baudot, Charles; et al. (Integrated Optics: Devices, Materials, and Technologies XXII, 2018)
Fiber-chip grating couplers providing high-efficiency, robustness and cost-effectivity are recognized as a key building block for large-volume photonic applications. However, the efficiency of silicon-on-insulator (SOI) grating couplers is limited by the mismatch between the beam diffracted by the grating and the fiber mode, back-reflections at the grating-to-waveguide interface, and the power radiated towards the substrate. While the first two limitations can be overcome by grating apodization, the limited diffraction efficiency (directionality) towards the fiber remains a challenge. Typically, grating directionality is optimized by backside metallization, distributed Bragg mirrors, multi-level grating architectures or non-standard etching depths. However, these approaches yield comparatively complex structures, which in turn, come with the expense of extra fabrication costs, hindering the mass-scale development. Alternatively, the blazing effect has been exploited to provide remarkably high directionalities, relying on standard deep and shallow etch depths. Here, we report on the first experimental demonstration of an ultra-directional L-shaped fiber-chip grating coupler fabricated on 300 mm SOI wafer using 193-nm deep-ultraviolet lithography. The grating coupler is realized on a 300-nm-thick Si layer, combining standard full (300 nm) and shallow (150 nm) etch steps in an L-shaped arrangement. This approach yields a remarkably high grating directionality up to 98%. A single-step subwavelength-engineered transition provides an eight-fold reduction of the reflectivity, from ~8% to ~1%. We experimentally demonstrate a coupling efficiency of -2.7 dB, with a 3-dB bandwidth of 62 nm. These results open a new route towards exploiting the blazing effect for the large-volume realization of high-efficiency fiber-chip grating couplers in the low-cost 300 mm SOI photonic platform.

Silicon membrane Bragg filters for near- and mid-infrared applications (conference presentation) - Alonso-Ramos, Carlos A.; Le Roux, Xavier; Benedikovic, Daniel; Vakarin, Vladyslav; Durán-Valdeiglesias, Elena; Oser, Dorian; Pérez-Galacho, Diego; Cassan, Eric; Marris-Morini, Delphine; Cheben, Pavel; Vivien, Laurent (Integrated Optics: Devices, Materials, and Technologies XXII, 2018)
The large transparency window of silicon (1.1 - 8 µm wavelength range) makes it a promising material for the implementation of a wide range of applications, including datacom, nonlinear and quantum optics, or sensing in the near- and mid-infrared wavelength ranges. However, the implementation of the silicon-on-insulator (SOI) platform in the mid-infrared is restricted by the absorption of buried oxide layer for wavelengths above 4 µm. A promising solution is to combine silicon membranes and subwavelength nanostructuration to locally remove the buried oxide layer, thus allowing access to the full transparency window of silicon. Additionally, structuring silicon with features smaller than half of the wavelength releases new degrees of freedom to tailor material properties, allowing the realization of innovative high-performance Si devices. Implementing Si membrane waveguides providing simultaneous single-mode operation at both near-infrared and mid-infrared wavelengths is cumbersome. Due to the high index contrast between Si and air cladding, conventional strip waveguides with cross-sections large enough to guide a mode in the mid-infrared are multi-mode in the near-infrared. Here, we exploit periodic corrugation to engineer light propagation properties of Si membrane waveguides allowing effective single-mode operation in near- and mid-IR. Single-mode propagation in the mid-IR is allowed by choosing a 500-nm-thick and 1100-nm-wide silicon waveguide. A novel waveguide corrugation approach radiates out the higher order modes in the near-IR, resulting in an effectively single-mode operation in near-IR. Based on this concept, we demonstrated Bragg filters with 4 nm bandwidth and 40 dB rejection.

Amphiphilic quantum dots with asymmetric, mixed polymer brush layers: from single core-shell nanoparticles to salt-induced vesicle formation - Coleman, Brian R.; Moffitt, Matthew G. (Polymers, 2018)
A mixed micelle approach is used to produce amphiphilic brush nanoparticles (ABNPs) with cadmium sulfide quantum dot (QD) cores and surface layers of densely grafted (σ = ~1 chain/nm2) and asymmetric (fPS = 0.9) mixed polymer brushes that contain hydrophobic polystyrene (PS) and hydrophilic poly(methyl methacrylate) (PMAA) chains (PS/PMAA-CdS). In aqueous media, the mixed brushes undergo conformational rearrangements that depend strongly on prior salt addition, giving rise to one of two pathways to fluorescent and morphologically disparate QD-polymer colloids. (A) In the absence of salt, centrosymmetric condensation of PS chains forms individual core-shell QD-polymer colloids. (B) In the presence of salt, non-centrosymmetric condensation of PS chains forms Janus particles, which trigger anisotropic interactions and amphiphilic self-assembly into the QD-polymer vesicles. To our knowledge, this is the first example of an ABNP building block that can form either discrete core-shell colloids or self-assembled superstructures in water depending on simple changes to the chemical conditions (i.e., salt addition). Such dramatic and finely tuned morphological variation could inform numerous applications in sensing, biolabeling, photonics, and nanomedicine.
Keywords: quantum dots; self-assembly; mixed polymer brush nanoparticles; vesicles; core-shell nanoparticles; fluorescence

Evaluation of pack ice pressure approaches and engineering implications for offshore structure design - Charlebois, Lawrence; Frederking, Robert M.; Timco, Garry W.; Watson, David; Richard, Martin (Cold Regions Science and Technology, 2018)
A probabilistic model for ice forces on a caisson platform in the Beaufort Sea was used to evaluate two different approaches for describing pack ice pressure. The ridge-building equation in the ISO Arctic offshore structures standard was compared to a more recently derived exceedance curve (EC) approach. The results indicated that the EC approach yielded a wider range of pack ice pressures compared to ISO estimates; however, when these results were used to determine the ultimate ice force on the platform, the effect of the pack ice approach selected was minimal. The influence of floe size in affecting the pack ice pressure did not yield agreement amongst several data sets examined. Furthermore, the influence of adfreeze was examined but no definite relationship was quantified. The paper discusses the engineering implications of these results in the context of offshore structure design. When evaluating the ice loads at a candidate site for offshore development, relevant information on floe size distribution and pack ice thickness, concentration, and movement are required in order to assess the influence of pack ice pressure on design calculations.
Keywords: pack ice; offshore structures; ice loads; ice engineering; ice pressure

A diagnostic tool for competency-based program engineering - Durand, Guillaume; Goutte, Cyril; Belacel, Nabil; Bouslimani, Yassine; Léger, Serge (Proceedings of the 8th International Conference on Learning Analytics and Knowledge, LAK '18, 2018)
Competency based education (CBE) is seen by many as a way to optimize learning on cost, efficiency and flexibility. However, defining the required competencies, assigning them to specific courses and building the assessments evaluating student's proficiency can be tedious. More precisely, making sure that the assessments evaluate what they are supposed to evaluate requires a fair amount of psychometrics knowledge and time that can be difficult for teachers to acquire, maintain and use. Addressing assessment validity and more specifically competency frameworks mapping adequacy, we propose a rule-based tool to ease the building and the refinement of CBE courses and curricula. After introducing the context and briefly the related work, we present our set of rules before illustrating the capacity of the proposed diagnostic tool on an engineering curriculum. Experiments show that this tool can improve mapping adequacy in term of predictive accuracy and would require more efforts towards competency parameters reliability measurement.
Keywords: Competency based education; cognitive diagnostic model; diagnostic tool; competency framework reliability

Additive manufacturing powder feedstock characterization using X-ray tomography - Bernier, Fabrice; Tahara, Rui; Gendron, Mathieu (Metal Powder Report, 2018)
To answer the need for efficient quality control protocols for additive manufacturing processes and materials, specific testing methods for powder feedstocks should be developed. A powder feedstock may contain some defects, such as porosities, that will remain in the final parts after the building process. X-ray tomography combined with 3D image analysis offers unique advantages over other characterization methods, such as pycnometry and metallography, in respect to quantifying internal porosity in the individual particles of the feedstock. This paper presents the effect of X-ray tomography parameters on the quality of the obtained images and its impact on the image analysis. An automated image analysis routine was also developed to allow the visualization of the pores inside the particles but also, more importantly, to quantify this internal porosity contents, as well as to provide information on the morphological features of these pores, such a size distribution, number of particles containing pores and the volume fraction of a pore inside a particle.

A virgo environmental survey tracing ionised gas emission (VESTIGE).I. introduction to the survey - Boselli, A.; Fossati, M.; Ferrarese, L.; Boissier, S.; Consolandi, G.; Longobardi, A.; Amram, P.; Balogh, M. (Astronomy & Astrophysics, 2018)
The Virgo Environmental Survey Tracing Ionised Gas Emission (VESTIGE) is a blind narrow-band Halpha+[NII] imaging survey carried out with MegaCam at the Canada-France-Hawaii Telescope. The survey covers the whole Virgo cluster region from its core to one virial radius (104 deg^2). The sensitivity of the survey is of f(Halpha) ~ 4 x 10^-17 erg sec-1 cm^-2 (5 sigma detection limit) for point sources and Sigma (Halpha) ~ 2 x 10^-18 erg sec^-1 cm^-2 arcsec^-2 (1 sigma detection limit at 3 arcsec resolution) for extended sources, making VESTIGE the deepest and largest blind narrow-band survey of a nearby cluster. This paper presents the survey in all its technical aspects, including the survey design, the observing strategy, the achieved sensitivity in both the narrow-band Halpha+[NII] and in the broad-band r filter used for the stellar continuum subtraction, the data reduction, calibration, and products, as well as its status after the first observing semester. We briefly describe the Halpha properties of galaxies located in a 4x1 deg^2 strip in the core of the cluster north of M87, where several extended tails of ionised gas are detected. This paper also lists the main scientific motivations of VESTIGE, which include the study of the effects of the environment on galaxy evolution, the fate of the stripped gas in cluster objects, the star formation process in nearby galaxies of different type and stellar mass, the determination of the Halpha luminosity function and of the Halpha scaling relations down to ~ 10^6 Mo stellar mass objects, and the reconstruction of the dynamical structure of the Virgo cluster. This unique set of data will also be used to study the HII luminosity function in hundreds of galaxies, the diffuse Halpha+[NII] emission of the Milky Way at high Galactic latitude, and the properties of emission line galaxies at high redshift.

Analysis of the pharmacological properties of JWH-122 isomers and THJ-2201, RCS-4 and AB-CHMINACA in HEK293T cells and hippocampal neurons - Costain, Willard J.; Rasquinha, Ingrid; Comas, Tanya; Hewitt, Melissa; Aylsworth, Amy; Rouleau, Yanouchka; Marleau, Vincent; Soo, Evelyn C.; Tauskela, Joseph S. (European Journal of Pharmacology, 2018)
Synthetic cannabinoids are marketed as legal alternatives to Δ9-THC, and are a growing worldwide concern as these drugs are associated with severe adverse effects. Unfortunately, insufficient information regarding the physiological and pharmacological effects of emerging synthetic cannabinoids (ESCs) makes their regulation by government authorities difficult. One strategy used to evade regulation is to distribute isomers of regulated synthetic cannabinoids. This study characterized the pharmacological properties of a panel of ESCs in comparison to Δ9-THC, as well as six JWH-122 isomers relative to its parent compound (JWH-122-4). Two cell-based assays were used to determine the potency and efficacy of ESCs and a panel of reference cannabinoids. HEK293T cells were transfected with human cannabinoid receptor 1 (CB1) and pGloSensor-22F, and the inhibition of forskolin-stimulated cyclic adenosine monophosphate (cAMP) levels was monitored in live cells. All ESCs examined were classified as agonists, with the following rank order of potency: Win 55,212-2 > CP 55,940 > JWH-122-4 > Δ9-THC ≈ RCS-4 ≈ THJ-2201 > JWH-122-5 > JWH-122-7 > JWH-122-2 ≈ AB-CHMINACA > JWH-122-8 > JWH-122-6 > JWH-122-3. Evaluation of ESC-stimulated Ca2+ transients in cultured rat primary hippocampal neurons confirmed the efficacy of four of the most potent ESCs (JWH-122-4, JWH-122-5, JWH-122-7 and AB-CHMINACA). This work helps regulatory agencies make informed decisions concerning these poorly characterized recreational drugs.
Keywords: rebaudioside A; hepatoprotective; Nrf2; HO-1; NQO1

CO2 adsorption on PIMs studied with 13C NMR spectroscopy - Moore, Jeremy K.; Marti, Robert M.; Guiver, Michael D.; Du, Naiying; Conradi, Mark S.; Hayes, Sophia E. (The Journal of Physical Chemistry C, 2018)
Polymers of intrinsic microporosity (PIMs) can be functionalized with nitrogen-bearing groups, such as a nitrile group for PIM-1 and a methylated tetrazole group for MTZ-PIM, to physisorb CO2. Static 13C NMR spectroscopy was used to investigate CO2 dynamics by analysis of onedimensional spectra and T2 relaxation times at temperatures ranging from 6 to 295 K. Each polymer had two different loadings of CO2 to determine the dominating relaxation mechanism at lower temperatures and deduce the identity of the weaker secondary adsorption site on the rigid polymer backbone. Both polymers, with a high loading of CO2, experience a narrowing of the 13C NMR line width as the samples are warmed to 80 K, which is the onset of the weakly adsorbed CO2 hopping on and off the polymer backbone.

Localizing 3-D anatomical landmarks using deep convolutional neural networks - Xi, Pengcheng; Shu, Chang; Goubran, Rafik (2017 14th Conference on Computer and Robot Vision (CRV), 2018)
Anatomical landmarks on 3-D human body scans play key roles in shape-essential applications, including consistent parameterization, body measurement extraction, segmentation, and mesh re-targeting. Manually locating landmarks is tedious and time-consuming for large-scale 3-D anthropometric surveys. To automate the landmarking process, we propose a data-driven approach, which learns from landmark locations known on a dataset of 3-D scans and predicts their locations on new scans. More specifically, we adopt a coarse-to-fine approach by training a deep regression neural network to compute the locations of all landmarks and then for each landmark training an individual deep classification neural network to improve its accuracy. In regards to input images being fed into the neural networks, we compute from a frontal view three types of image renderings for comparison, i.e., gray-scale appearance images, range depth images, and curvature mapped images. Among these, curvature mapped images result in the best empirical accuracy from the deep regression network, whereas depth images lead to higher accuracy for locating most landmarks using the deep classification networks. In conclusion, the proposed approach performs better than state of the art on locating most landmarks. The simple yet effective approach can be extended to automatically locate landmarks in large scale 3-D scan datasets.
Keywords: Machine learning; multi-layer neural networks; feature extraction; machine vision

Re-evaluation of ice loads on the Molikpaq structure measured during the 1985–86 season - Jordaan, Ian; Hewitt, Kevin; Frederking, Robert (Canadian Journal of Civil Engineering, 2018)
The Molikpaq drilling platform, a steel annulus filled with sand, 90 m wide, was deployed at the Amauligak I-65 location in the Beaufort Sea during the 1985–1986 winter. It was heavily instrumented for measurement of ice loads, using strain gauges, extensometers, and Medof panels. The original calibrations of the Medof panels were used to estimate loads. Calibration was carried out using uniform pressures up to 1.86 MPa. The actual loading in the field of the Medof panels was extremely non-uniform spatially, particularly during ice crushing, and is very different from that in the original calibration. The resulting high pressures led to softening of the polyurethane buttons in the panels, including the Mullins effect. The panels were consequently reading too high. Extensometer readings, geotechnical measurements, and those pertaining to a decelerating floe impacting the structure, support the conclusion that actual ice loads were about half those obtained using the original Medof panel calibrations.
Keywords: ice engineering; ice mechanics; offshore technology; design; reliability analyses; steel structure; ingénierie dans les eaux englacées; mécanique des glaces; technologie de forage et de production en mer; conception; analyses de fiabilité; charpente métallique

Multi-wavelength brillouin random fiber laser via distributed feedback from a random fiber grating - Zhang, Liang; Xu, Yanping; Lu, Ping; Mihailov, Stephen; Chen, Liang; Bao, Xiaoyi (Journal of Lightwave Technology, 2018)
Multi-wavelength (MW) laser sources with high optical signal-to-noise ratios (OSNR) are of great interest for optical communications with ultrahigh data capacity as well as microwave and terahertz photonics. In this paper, we report the first demonstration of MW Brillouin random fiber laser in the telecom spectral window around 1.5 μm based on a unique random fiber grating (RFG). Random feedback by enhanced distributed Rayleigh scattering from the RFG basically enables a high-efficiency random lasing resonance of the Stokes wave via stimulated Brillouin scattering in optical fibers. A subfiber loop eventually delivers the cascading process for the high-efficiency generation of up to a 14-order Stokes’ comb with an ultrahigh OSNR of 41 dB and an optimized peak power discrepancy of 3.4 dB. Thanks to Rayleigh scattered random feedback from the RFG, single longitudinal mode operation of the Stokes laser emission is achieved.

WIVERN: a new satellite concept to provide global in-cloud winds, precipitation and cloud properties. - Illingworth, A. J.; Battaglia, A.; Bradford, J.; Forsythe, M.; Joe, P.; Kollias, P.; Lean, K.; Lori, M.; Mahfouf, J.-F.; Mello, S.; Midthassel, R.; Munro, Y.; et al. (Bulletin of the American Meteorological Society, 2018)
A new satellite concept with a conically scanning W-band Doppler radar to provide in-cloud winds, together with estimates of global rainfall, snowfall and cloud properties. This paper presents a conically scanning space-borne Dopplerized 94GHz radar Earth Science mission concept, WIVERN, ‘Wind VElocity Radar Nephoscope’. WIVERN aims to provide global measurements of in-cloud winds using the Doppler shifted radar returns from hydrometeors. The conically scanning radar could provide wind data with daily revisits poleward of 50°, 50-km horizontal resolution and approximately 1km vertical resolution. The measured winds, when assimilated into weather forecasts and provided they are representative of the larger scale mean flow, should lead to further improvements in the accuracy and effectiveness of forecasts of severe weather and better focusing of activities to limit damage and loss of life. It should also be possible to characterize the more variable winds associated with local convection. Polarization diversity would be used to enable high wind speeds to be unambiguously observed; analysis indicates that artifacts associated with polarization diversity are rare and can be identified. Winds should be measurable down to 1 km above the ocean surface and 2 km over land. The potential impact of the WIVERN winds on reducing forecast errors is estimated by comparison with the known positive impact of cloud motion and aircraft winds. The main thrust of WIVERN is observing in-cloud winds, but WIVERN should also provide global estimates of ice water content, cloud cover and vertical distribution continuing the data series started by CloudSat with the conical scan giving increased coverage. As with CloudSat, estimates of rainfall and snowfall rates should be possible. These non-wind products may also have a positive impact when assimilated into weather forecasts.

In-source reduction of disulfide-bonded peptides monitored by ion mobility mass spectrometry - Stocks, Bradley B.; Melanson, Jeremy E. (Journal of The American Society for Mass Spectrometry, 2018)
Many peptides with antimicrobial activity and/or therapeutic potential contain disulfide bonds as a means to enhance stability, and their quantitation is often performed using electrospray ionization mass spectrometry (ESI-MS). Disulfides can be reduced during ESI under commonly used instrument conditions, which has the potential to hinder accurate peptide quantitation. We demonstrate that this in-source reduction (ISR) is predominantly observed for peptides infused from acidic solutions and subjected to elevated ESI voltages (3-4 kV). ISR is readily apparent in the mass spectrum of oxytocin-a small, single disulfide-containing peptide. However, subtle m/z shifts due to partial ISR of highly charged (z ≥ 3) peptides with multiple disulfide linkages may proceed unnoticed. Ion mobility (IM)-MS separates ions on the basis of charge and shape in the gas phase, and using insulin as a model system, we show that IM-MS arrival time distributions (ATDs) are particularly sensitive to partial ISR of large peptides. Isotope modeling allows for the relative quantitation of disulfide-intact and partially reduced states of the mobility-separated peptide conformers. Interestingly, hepcidin peptides ionized from acidic solutions at elevated ESI voltages undergo gas-phase compaction, ostensibly due to partial disulfide ISR. Our IM-MS results lead us to propose that residual acid is the likely cause of disparate ATDs recently measured for hepcidin from different suppliers [Anal. Bioanal. Chem. 409, 2559-2567 (2017)]. Overall, our results demonstrate the utility of IM-MS to detect partial ISR of disulfide-bonded peptides and reinforce the notion that peptide/protein measurements should be carried out using minimally activating instrument conditions.

Colloidal CdSe 0-dimension nanocrystals and their self-assembled 2-dimension structures - Liu, Yuanyuan; Zhang, Baowei; Fan, Hongsong; Rowell, Nelson; Willis, Maureen; Zheng, Xiaotong; Che, Renchao; Han, Shuo; Yu, Kui (Chemistry of Materials, 2018)
We report on a particular type of CdSe nanocrystals (NCs) that exhibit a single optical absorption doublet. The two peaks in the doublet are relatively sharp with a full width half-maximum as narrow as 10 nm. The peak positions vary with passivation ligands (at ∼426 and ∼453 nm for amine ligand passivation and at ∼432 and ∼460 nm for carboxylate ligand passivation). To date, it has been generally concluded that these NCs have a two-dimension (2D) morphology with 1D quantum confinement. Here, we report that zero-dimension (0D) NCs with 3D quantum confinement can exhibit a very similar static optical feature consisting of a sharp absorption doublet. We show that our as-prepared CdSe NCs (without further purification) were mainly 0D NCs, as observed when they were deposited on transmission electron microscopy (TEM) grids directly from toluene or hexane dispersions. We further demonstrate that it was possible to alter this 0D morphology by using dispersion additives and/or purification solvents to result in the appearance of 2D NCs under TEM. Although the 0D and self-assembled 2D NCs displayed similar static optical features, the two morphologies behaved quite differently in polarized emission. The 2D NCs exhibited detection angle dependent polarized emission, whereas the 0D NCs do not. Our findings indicate that a well-like morphology can be induced by the presence of hexadecylamine (HDA) in the dispersion with sonication for amine-passivated 0D NCs or by the use of ethanol during purification with dispersion storage for carboxylate-passivated 0D NCs. In this way, it is possible to manipulate the NC morphology for a targeted application through the appropriate post-treatment. This study highlights that more sophisticated theoretical studies are required to account for the experimental observations in which both 0D NCs and their self-assembled 2D NC products display similar static optical features.

Evaluation of electron tomography reconstruction methods for interface roughness measurement - Hayashida, Misa; Ogawa, Shinichi; Malac, Marek; Verkade, Paul (Microscopy Research and Technique, 2018)
We evaluate the suitability of simultaneous iterative reconstruction technique (SIRT), filtered back projection, and simultaneous algebraic reconstruction technique methods for buried interface roughness measurements. We also investigate the effect of total electron dose distributed over the entire tilt series on measured roughness values. We investigate the applicability of the dose fractionation theorem by evaluating the effect of an increasing number of images, i.e., decreasing tilt increment size at fixed total electron irradiation dose on the quantitative measurement of buried interface roughness. The results indicate that SIRT is the most suitable method for reconstruction and a 3° to 5° angle is optimal for the roughness measurement.
Keywords: buried interface roughness; dose fractionation theorem; electron tomography; radiation damage; semiconductor devices

Reply to the ‘Comment on “Methanol dimer formation drastically enhances hydrogen abstraction from methanol by OH at low temperature”’ by W. Siebrand, Z. Smedarchina, E. Martínez-Núñez and A. Fernández-Ramos, Phys. Chem. Chem. Phys., 2016, 18, 22712 - Siebrand, W.; Smedarchina, Z.; Ferro-Costas, D.; Martínez-Núñez, E.; Fernández-Ramos, A. (Physical Chemistry Chemical Physics, 2018)

A polynomial-chaos-expansion-based building block approach for stochastic analysis of photonic circuits - Waqas, Abi; Melati, Daniele; Melloni, Andrea; Manfredi, Paolo; Grassi, Flavia; Osiński, Marek; Arakawa, Yasuhiko; Witzigmann, Bernd (Physics and Simulation of Optoelectronic Devices XXVI, 2018)
The Building Block (BB) approach has recently emerged in photonic as a suitable strategy for the analysis and design of complex circuits. Each BB can be foundry related and contains a mathematical macro-model of its functionality. As well known, statistical variations in fabrication processes can have a strong effect on their functionality and ultimately affect the yield. In order to predict the statistical behavior of the circuit, proper analysis of the uncertainties effects is crucial. This paper presents a method to build a novel class of Stochastic Process Design Kits for the analysis of photonic circuits. The proposed design kits directly store the information on the stochastic behavior of each building block in the form of a generalized-polynomial-chaos-based augmented macro-model obtained by properly exploiting stochastic collocation and Galerkin methods. Using this approach, we demonstrate that the augmented macro-models of the BBs can be calculated once and stored in a BB (foundry dependent) library and then used for the analysis of any desired circuit. The main advantage of this approach, shown here for the first time in photonics, is that the stochastic moments of an arbitrary photonic circuit can be evaluated by a single simulation only, without the need for repeated simulations. The accuracy and the significant speed-up with respect to the classical Monte Carlo analysis are verified by means of classical photonic circuit example with multiple uncertain variables.
Keywords: integrated photonic; building block; generalized polynomial chaos (gPC); stochastic process

Uncertainty quantification and stochastic modelling of photonic device from experimental data through polynomial chaos expansion - Waqas, Abi; Melati, Daniele; Mushtaq, Zarlish; Melloni, Andrea I.; García-Blanco, Sonia M.; Cheben, Pavel (Integrated Optics: Devices, Materials, and Technologies XXII, 2018)
Unavoidable statistical variations in fabrication processes have a strong effect on the functionality of fabricated photonic circuits and on fabrication yield. It is hence essential to measure and consider these uncertainties during the design in order to predict the statistical behavior of the realized circuits. Also, during the mass production of photonic integrated circuits, the experimental evaluation of circuits’ desired quantity of interest in the presence of fabrication error can be crucial. In this paper we proposed the use of generalized polynomial chaos method to estimate the statistical properties of a circuit from a reduced number of experimental data whilst achieving good accuracy comparable to those obtained by Monte Carlo.
Keywords: integrated photonic; generalized polynomial chaos (gPC); stochastic process

Thermal expansion coefficient measurement from electron diffraction of amorphous films in a TEM - Hayashida, Misa; Cui, Kai; Malac, Marek; Egerton, Ray (Ultramicroscopy, 2018)
We measured the linear thermal expansion coefficients of amorphous 5–30 nm thick SiN and 17 nm thick Formvar/Carbon (F/C) films using electron diffraction in a transmission electron microscope. Positive thermal expansion coefficient (TEC) was observed in SiN but negative coefficients in the F/C films. In case of amorphous carbon (aC) films, we could not measure TEC because the diffraction radii required several hours to stabilize at a fixed temperature.

Selective extraction and purification of Azaspiracids from blue mussels (Mytilus edulis) using boric acid gel - Miles, Christopher O.; Kilcoyne, Jane; Mccarron, Pearse; Giddings, Sabrina D.; Waaler, Thor; Rundberget, Thomas; Samdal, Ingunn A.; Løvberg, Kjersti E. (Journal of Agricultural and Food Chemistry, 2018)
Azaspiracids (AZAs) belong to a family of more than 50 polyether toxins originating from marine dinoflagellates such as Azadinium spinosum. All of the AZAs reported thus far contain a 21,22-dihydroxy group. Boric acid gel (BAG) can bind selectively to compounds containing vic-diols or α-hydroxycarboxylic acids via formation of reversible boronate complexes. Here we report use of BAG to selectively capture and release AZAs from extracts of blue mussels. Analysis of the extracts and BAG fractions by LC–MS showed that this procedure resulted in an excellent clean-up of the AZAs in the extract. Analysis by ELISA and LC–MS indicated that most AZA analogues were recovered in good yield by this procedure. The capacity of BAG for AZAs was at least 50 μg/g, making this procedure suitable for use in the early stages of preparative purification of AZAs. In addition to its potential for concentration of dilute samples, the extensive clean-up provided by BAG fractionation of AZAs in mussel samples almost eliminated matrix effects during subsequent LC–MS, and could be expected to reduce matrix effects during ELISA analysis. The method may therefore prove useful for quantitative analysis of AZAs as part of monitoring programs. Although LC-MS data showed that okadaic acid analogues also bound to BAG, this was much less efficient than for AZAs under the conditions used. The BAG methodology is potentially applicable to other important groups of natural toxins containing diols, including ciguatoxins, palytoxins, pectenotoxins,karlotoxins, tetrodotoxin, trichothecenes, and toxin glycosides.

Magnetic materials fabricated by cold spray additive manufacturing - Lamarre, Jean-Michel; Bernier, Fabrice (2018)
This presentation discusses the cost effective fabrication of soft and hard magnetic materials using cold spray additive manufacturing. This technique allows for 3D build-up of complex shapes permitting fabrication of high complexity motor designs for enhanced performance. Combination of sprayed soft and hard magnetic materials opens up synergetic design possibilities for additional performance gain and cost savings. Measured hard magnetic properties (coercivity and remanence), soft magnetic properties (permeability and losses) and mechanical properties (adhesion and cohesion) will be presented. Use of the materials for the realization of motor prototypes will be discussed.

Enhanced delivery of galanin conjugates to the brain through bioengineering of the anti-transferrin receptor antibody OX26 - Thom, George; Burrell, Matthew; Haqqani, Arsalan S.; Yogi, Alvaro; Lessard, Etienne; Brunette, Eric; Delany, Christie; Baumann, Ewa; Callaghan, Deborah; Rodrigo, Natalia; Webster, Carl I.; Stanimirovic, Danica B. (Molecular Pharmaceutics, 2018)
The blood-brain barrier (BBB) is a formidable obstacle for brain delivery of therapeutic antibodies. However, antibodies against the transferrin receptor (TfR), enriched in brain endothelial cells, have been developed as delivery carriers of therapeutic cargos into the brain via a receptor-mediated transcytosis pathway. In vitro and in vivo studies demonstrated that either a low-affinity or mono-valent binding of these antibodies to the TfR improves their release on the abluminal side of the BBB and target engagement in brain parenchyma. However, these studies have been performed with mouse-selective TfR antibodies that recognize different TfR epitopes and have varied binding characteristics. In this study, we evaluated serum pharmacokinetics, brain and CSF exposure of the rat TfR-binding antibody OX26 affinity variants, having Kds of 5 nM, 76 nM, 108 nM and 174 nM; all binding the same epitope in bi-valent format. Pharmacodynamic responses were tested in Hargreaves chronic pain model after conjugation of OX26 affinity variants with the analgesic and anti-epileptic peptide, galanin. OX26 variants with affinities of 76 nM and 108 nM showed enhanced brain and CSF exposure and higher potency in Hargreaves model, compared to a 5 nM affinity variant; lowering affinity to 174 nM resulted in prolonged serum pharmacokinetics, but reduced brain and CSF exposure. The study demonstrates that binding affinity optimization of TfR-binding antibodies could improve their brain and CSF exposure even in the absence of mono-valent TfR engagement.

Editorial: Single-domain antibodies: biology, engineering and emerging applications - Henry, Kevin A.; Mackenzie, C. Roger (Frontiers in Immunology, 2018)
Since the discovery of camelid heavy chain-only antibodies (HCAbs) in 1993 and shark immunoglobulin new antigen receptors (IgNARs) in 1995, and the subsequent recognition that the variable domains of these antibodies (VHHs and VNARs, respectively) function autonomously as single-domain antibodies (sdAbs), sdAbs have found many uses across diverse fields. Early work on naturally-occurring antibodies bearing single variable domains spurred renewed interest in the development of human sdAbs, namely, the light chain variable domains (VLs) and the heavy chain variable domains (VHs) of human conventional antibodies; the first reported sdAbs were actually VHs. Synthetic human sdAbs are expected to be less immunogenic than VHHs or VNARs but their development is more challenging, requiring steps to ensure the selection of molecules with good biophysical properties and appropriate affinity. There are several advantages offered by sdAbs over conventional antibodies in a wide variety of diagnostic, research, and therapeutic applications, most notably their ease of production in microbial systems, their potential ability to target cryptic epitopes that are inaccessible to larger molecules, and the fact that they can be readily formatted into more complex molecules. This collection brings together 26 reviews and original research articles that together provide extensive coverage of the developments, opportunities, and challenges associated with this unique class of molecules.

A review of carbon-composited materials as air-electrode bifunctional electrocatalysts for metal–air batteries - Wang, Yan-Jie; Fang, Baizeng; Zhang, Dan; Li, Aijun; Wilkinson, David P.; Ignaszak, Anna; Zhang, Lei; Zhang, Jiujun (Electrochemical Energy Reviews, 2018)
Metal–air batteries (MABs), particularly rechargeable MABs, have gained renewed interests as a potential energy storage/conversion solution due to their high specific energy, low cost, and safety. The development of MABs has, however, been considerably hampered by its relatively low rate capability and its lack of efficient and stable air catalysts in which the former stems mainly from the sluggish kinetics of the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) and the latter stems from the corrosion/oxidation of carbon materials in the presence of oxygen and high electrode potentials. In this review, various carbon-composited bifunctional electrocatalysts are reviewed to summarize progresses in the enhancement of ORR/OER and durability induced by the synergistic effects between carbon and other component(s). Catalyst mechanisms of the reaction processes and associated performance enhancements as well as technical challenges hindering commercialization are also analyzed. To facilitate further research and development, several research directions for overcoming these challenges are also proposed.
Keywords: metal–air batteries; oxygen reduction reaction; oxygen evolution reaction; carbon; bifunctional electrocatalysts; synergistic effect

Decomposable s-tetrazine copolymer enables single-walled carbon nanotube thin film transistors and sensors with improved sensitivity - Li, Zhao; Ding, Jianfu; Guo, Chang; Lefebvre, Jacques; Malenfant, Patrick R. L. (Advanced Functional Materials, 2018)
Semiconducting single-walled carbon nanotubes (sc-SWCNTs) enriched by a conjugated polymer extraction process have been actively studied for various applications in both electronics and optoelectronics. Although the resulting tube samples usually have high sc-purity and concentration, SWCNT networks from such dispersions typically contain residual conjugated polymer that may degrade device performance and its removal remains a challenge while maintaining uniform, dense SWCNT thin film networks. In this study, a novel polymer–SWCNT combination based on an alternating bisfuran-s-tetrazine and benzo[1,2-b:4,5-b′]dithiophene copolymer abbreviated as PBDTFTz is proposed. This polymer decomposes at >250 °C or under UV irradiation. In situ transistor characterization under laser irradiation confirms the polymer decomposition. The study of the tube network in the transistor channel at various channel lengths reveals significantly reduced contact resistance attributed to removal of the wrapping PBDTFTz polymer. In ammonia sensing experiments, sc-SWCNT networks demonstrate rapid and reversible responses, while the unwrapped nanotube networks prove superior in terms of signal to noise ratio and a detection limit of 2.5 ppb is calculated, almost four times better than polymer wrapped nanotubes.

Traumatic brain injury: classification, models and markers - Najem, Dema; Rennie, Kerry; Ribecco-Lutkiewicz, Maria; Ly, Dao; Haukenfrers, Julie; Liu, Qing; Nzau, Munyao; Fraser, Douglas; Bani, Mahmud (Biochemistry and Cell Biology, 2018)
Traumatic brain injury (TBI) is a leading cause of morbidity and mortality worldwide. Due to its high incidence rate and often long-term sequelae, TBI contributes significantly to increasing costs of medicare expenditures annually. Unfortunately, advances in the field have been stifled by patient and injury heterogeneity that pose a major challenge in TBI prevention, diagnosis and treatment. In this review, we briefly discuss the causes of TBI, followed by its prevalence, classification and pathophysiology. The current imaging detection methods and animal models used to study brain injury are examined. We discuss the potential use of molecular markers in detecting and monitoring the progression of TBI, with particular emphasis on microRNAs as a novel class of molecular modulators of injury and its repair in the neural tissue.

Coupled numerical approach for automotive battery pack lifetime estimates with thermal management - Darcovich, K.; Macneil, D. D.; Recoskie, S.; Cadic, Q.; Ilinca, F.; Kenney, B. (Journal of Electrochemical Energy Conversion and Storage, 2018)
This study combined a simple two-dimensional (2D) finite volume model (Kim model), which employs Ohm's law along with charge conservation over the electrodes and Butler–Volmer charge transfer kinetics for prismatic battery cells coupled with the single particle model (SPM) in order to model the thermal state of automotive battery packs. The objective here was to determine the effects of liquid cooling applied to the packs under standard driving cycles. A model developed by Kim provided a means for determining a nonuniform current distribution over the surface of the current collectors. The Kim model is based on the application of Ohm's law over a conducting medium, with empirical source terms representing current flowing into or out of an adjacent electrode layer. Here, a modeling advance is presented where empirical source terms in the Kim model were replaced with ones based on the chemistry and physics occurring inside the battery. As such, fundamental battery function was imparted to the model by integrating the SPM into the 2D finite volume Kim model. The 2D procedure described above was carried out on electrode sheets at different positions inside the cell, and determined thermal generation values that were mapped volumetrically into a heat transfer simulation, which, in turn, updated the electrochemical simulation. Capacity fade kinetics were determined by fitting experimental data to simulated results. With time-temperature profiles produced as described above for different pack cooling levels and varying degrees of cell degradation, a basic SPM simulation was then used with thermal overlays to estimate automotive cell life under various driving scenarios and various cooling levels. With these simulations, scenarios representing different thermal management regimes along with driving behavior were able to show the combined impact on automotive battery pack lifetimes.

A real time machining error compensation method based on dynamic features for cutting force induced elastic deformation in flank milling - Liu, Changqing; Li, Yingguang; Shen, Weiming (Machining Science and Technology, 2018)
During the machining process, cutting forces cause deformation of thin-walled parts and cutting tools because of their low rigidity. Such deformation can lead to undercut and may result in defective parts. Since there are various unexpected factors that affect cutting forces during the machining process, the error compensation of cutting force induced deformation is deemed to be a very difficult issue. In order to address this challenge, this article proposes a novel real time deformation error compensation method based on dynamic features. A dynamic feature model is established for the evaluation of feature rigidity as well as the association between geometric information and real time cutting force information. Then the deformations are calculated based on the dynamic feature model. Eventually, the machining error compensation for elastic deformation is realized based on Function Blocks. A thin-walled feature is used as an example to validate the proposed approach. Machining experiment results show that the errors of calculated deformation with the monitored deformation is less than 10%, and the thickness errors were between −0.05 mm and +0.06 mm, which can well satisfy the accuracy requirement of structural parts by NC (Numerical Control) machining.

Expanding paraphrase lexicons by exploiting generalities - Fujita, Atsushi; Isabelle, Pierre (ACM Transactions on Asian and Low-Resource Language Information Processing, 2018)
Techniques for generating and recognizing paraphrases, i.e., semantically equivalent expressions, play an important role in a wide range of natural language processing tasks. In the last decade, the task of automatic acquisition of subsentential paraphrases, i.e., words and phrases with (approximately) the same meaning, has been drawing much attention in the research community. The core problem is to obtain paraphrases of high quality in large quantity. This article presents a method for tackling this issue by systematically expanding an initial seed lexicon made up of high-quality paraphrases. This involves automatically capturing morpho-semantic and syntactic generalizations within the lexicon and using them to leverage the power of large-scale monolingual data. Given an input set of paraphrases, our method starts by inducing paraphrase patterns that constitute generalizations over corresponding pairs of lexical variants, such as “amending” and “amendment,” in a fully empirical way. It then searches large-scale monolingual data for new paraphrases matching those patterns. The results of our experiments on English, French, and Japanese demonstrate that our method manages to expand seed lexicons by a large multiple. Human evaluation based on paraphrase substitution tests reveals that the automatically acquired paraphrases are also of high quality.

Optimization of friction stir weld joint quality using a meshfree fully-coupled thermo-mechanics approach - Fraser, Kirk; Kiss, Laszlo; St-Georges, Lyne; Drolet, Dany (Metals, 2018)
There is currently a need for an efficient numerical optimization strategy for the quality of friction stir welded (FSW) joints. However, due to the computational complexity of the multi-physics problem, process parameter optimization has been a goal that is out of reach of the current state-of-the-art simulation codes. In this work, we describe an advanced meshfree computational framework that can be used to determine numerically optimized process parameters while minimizing defects in the friction stir weld zone. The simulation code, SPHriction-3D, uses an innovative parallelization strategy on the graphics processing unit (GPU). This approach allows determination of optimal parameters faster than is possible with costly laboratory testing. The meshfree strategy is firstly outlined. Then, a novel metric is proposed that automatically evaluates the presence and severity of defects in the weld zone. Next, the code is validated against a set of experimental results for ½” AA6061-T6 butt joint FSW joints. Finally, the code is used to determine the optimal advancing speed and rpm while minimizing defect volume based on the proposed defect metric.
Keywords: coupled thermal-mechanics; meshfree; optimization; graphics processing unit; large plastic deformation; Lagrangian framework; SPHriction-3D; defect prediction

Rapid determination of bitumen content in Athabasca oil sands by laser-induced breakdown spectroscopy - Harhira, Aissa; El haddad, Josette; Blouin, Alain; Sabsabi, Mohamad (Energy & Fuels, 2018)
Evaluation of bitumen content in oil sands feedstock is important to control the extraction process and improve the recovery efficiency. Current standard techniques for bitumen determination in oil sands ore suffer whether from their time-consuming labor intensive method of sample preparations or from requiring a high number of samples for calibration purposes. The analysis of bitumen ore samples is very challenging for the analytical chemist due to its nature of several phases of wet and dry particles and heterogeneous mixture of clay, bitumen, water, and solid contents. In this paper, we present a new enabling method using LIBS to determine rapidly and without sample preparation the bitumen content in oil sands ores. A qualitative study by principal component analysis was first done, and then a partial least-squares method was performed to assess the feasibility of determining bitumen by LIBS. The results show a good correlation between LIBS spectra and bitumen content and a prediction averaged absolute error around 0.7%. This method demonstrates that the LIBS is a promising tool for rapidly assessing oil sands ore grades either in the lab, at-line, or online. Elemental composition of solids is also investigated.

Real-time monitoring of a microbial electrolysis cell using an electrical equivalent circuit model - Hussain, S. A.; Perrier, M.; Tartakovsky, B. (Bioprocess and Biosystems Engineering, 2018)
Efforts in developing microbial electrolysis cells (MECs) resulted in several novel approaches for wastewater treatment and bioelectrosynthesis. Practical implementation of these approaches necessitates the development of an adequate system for real-time (on-line) monitoring and diagnostics of MEC performance. This study describes a simple MEC equivalent electrical circuit (EEC) model and a parameter estimation procedure, which enable such real-time monitoring. The proposed approach involves MEC voltage and current measurements during its operation with periodic power supply connection/disconnection (on/off operation) followed by parameter estimation using either numerical or analytical solution of the model. The proposed monitoring approach is demonstrated using a membraneless MEC with flow-through porous electrodes. Laboratory tests showed that changes in the influent carbon source concentration and composition significantly affect MEC total internal resistance and capacitance estimated by the model. Fast response of these EEC model parameters to changes in operating conditions enables the development of a model-based approach for real-time monitoring and fault detection.
Keywords: MEC; equivalent circuit model; parameter estimation; on-line monitoring

Identification of 21,22-Dehydroazaspiracids in mussels (Mytilus edulis) and in vitro toxicity of azaspiracid-26 - Kilcoyne, Jane; Mccarron, Pearse; Twiner, Michael J.; Rise, Frode; Hess, Philipp; Wilkins, Alistair L.; Miles, Christopher O. (Journal of Natural Products, 2018)
Azaspiracids (AZAs) are marine biotoxins produced by the genera Azadinium and Amphidoma, pelagic marine dinoflagellates that may accumulate in shellfish resulting in human illness following consumption. The complexity of these toxins has been well documented, with more than 40 structural variants reported that are produced by dinoflagellates, result from metabolism in shellfish, or are extraction artifacts. Approximately 34 μg of a new AZA with MW 823 Da (AZA26 (3)) was isolated from blue mussels (Mytilus edulis), and its structure determined by MS and NMR spectroscopy. AZA26, possibly a bioconversion product of AZA5, lacked the C-20–C-21 diol present in all AZAs reported thus far and had a 21,22-olefin and a keto group at C-23. Toxicological assessment of 3 using an in vitro model system based on Jurkat T lymphocyte cells showed the potency to be ∼30-fold lower than that of AZA1. The corresponding 21,22-dehydro-23-oxo-analogue of AZA10 (AZA28) and 21,22-dehydro analogues of AZA3, -4, -5, -6, -9, and -10 (AZA25, -48 (4), -60, -27, -49, and -61, respectively) were also identified by HRMS/MS, periodate cleavage reactivity, conversion from known analogues, and NMR (for 4 that was present in a partially purified sample of AZA7).

Validating Fricke dosimetry for the measurement of absorbed dose to water for HDR 192Ir brachytherapy: a comparison between primary standards of the LCR, Brazil, and the NRC, Canada - Salata, Camila; David, Mariano gazineu; De almeida, Carlos eduardo; El gamal, Islam; Cojocaru, Claudiu; Mainegra-hing, Ernesto; Mcewen, Malcolm r (Physics in Medicine and Biology, 2018)
Two Fricke-based absorbed dose to water standards for HDR Ir-192 dosimetry, developed independently by the LCR in Brazil and the NRC in Canada have been compared. The agreement in the determination of the dose rate from a HDR Ir-192 source at 1 cm in a water phantom was found to be within the k=1 combined measurement uncertainties of the two standards: DNRC/DLCR = 1.011, standard uncertainty = 2.2 %. The dose-based standards also agreed within the uncertainties with the manufacturer’s stated dose rate value, which is traceable to a national standard of air kerma. A number of possible influence quantities were investigated, including the specific method for producing the ferrous-sulphate Fricke solution, the geometry of the holder, and the Monte Carlo code used to determine correction factors. The comparison highlighted the lack of data on the determination of G(Fe3+) in this energy range and the possibilities for further development of the holders used to contain the Fricke solution. The comparison also confirmed the suitability of Fricke dosimetry for Ir-192 primary standard dose rate determinations at therapy dose levels.
Keywords: Fricke dosimetry; Ir-192 HDR brachytherapy; absorbed dose standards

Scalable fabrication of supercapacitors by nozzle-free electrospinning - Shi, Kaiyuan; Giapis, Konstantinos P. (ACS Applied Energy Materials, 2018)
Nozzle-free electrospinning was investigated as a facile technique for producing nanoscale materials for supercapacitors. MnO2 nanofibers and their composites with multiwalled carbon nanotubes (MWCNTs) were synthesized in a single step, using polyvinylpyrrolidone (PVP) and Mn(CH3COO)2·4H2O as starting materials, followed up by heat treatment in ambient air. Nanofibers of relatively uniform diameter were produced at high rates. The nanofibers exhibited good electrical contact between MnO2 and MWCNT without degradation, which was attributed to the improved stability of MWCNTs in PVP solutions. Electrochemical testing of the composites demonstrated a high capacitance of 1.43 F cm–2 at a scan rate of 100 mV s–1 in the three-electrode tests. Electrodes and devices produced by nozzle-free electrospinning are promising for practical energy storage applications.
Keywords: energy storage devices; MnO2; nanofibers; nozzle-free electrospinning; supercapacitors

Connection between phase diagram, structure and ion transport in liquid, aqueous electrolyte solutions of lithium chloride - Yim, Chae-Ho; Abu-Lebdeh, Yaser A. (Journal of The Electrochemical Society, 2018)
The nature of structure and ion transport in liquid electrolyte solutions are still not fully understood over the whole concentration range. In this work, we have studied aqueous solutions of lithium chloride as a model salt due to its very high solubility in water and ample knowledge of its structure and physiochemical properties. We have analyzed the ionic conductivity (κ) vs. concentration (C) plots based on free volume approach and our recently developed equation: κ = AC exp[ − BC] and conductivity vs. temperature plots based on Arrhenius equation. We find that the solutions show little variation in free volume with concentration, or even temperature, but a rapid increase in activation energy and pre-exponential factor. We relate the significant changes in conductivity to changes in structure and transport in the solutions and connect them to the binary LiCl/H2O phase diagram. We hypothesize that the changes are caused by a breakdown of the bulk water structure near the eutectic composition that causes a change in transport mechanism. We believe that this connection between solution structure, ion transport and phase diagram is common in most aqueous and non-aqueous electrolyte solutions and explains the origin of maximum in conductivity in isothermal conductivity vs. concentration plots.
Keywords: aqueous electrolyte; battery; solution structure

Linear friction welding of dissimilar materials 316L stainless steel to Zircaloy-4 - Wanjara, P.; Naik, B. S.; Yang, Q.; Cao, X.; Gholipour, J.; Chen, D. L. (Metallurgical and Materials Transactions A, 2018)
In the nuclear industry, there are a number of applications where the transition of stainless steel to Zircaloy is of technological importance. However, due to the differences in their properties there are considerable challenges associated with developing a joining process that will sufficiently limit the heat input and welding time—so as to minimize the extent of interaction at the joint interface and the resulting formation of intermetallic compounds—but still render a functional metallurgical bond between these two alloys. As such, linear friction welding, a solid-state joining technology, was selected in the present study to assess the feasibility of welding 316L stainless steel to Zircaloy-4. The dissimilar alloy welds were examined to evaluate their microstructural characteristics, microhardness evolution across the joint interface, static tensile properties, and fatigue behavior. Microstructural observations revealed a central intermixed region and, on the Zircaloy-4 side, dynamically recrystallized and thermomechanically affected zones were present. By contrast, deformation on the 316L stainless steel side was limited. In the intermixed region a drastic change in the composition was observed along with a local increase in hardness, which was attributed to the presence of intermetallic compounds, such as FeZr3 and Cr2Zr. The average yield (316 MPa) and ultimate tensile (421 MPa) strengths met the minimum strength properties of Zircaloy-4, but the elongation was relatively low (~ 2 pct). The tensile and fatigue fracture of the welds always occurred at the interface in the mode of partial cohesive failure.

Splitting-merging clustering algorithm for collaborative filtering recommendation system - Belacel, Nabil; Durand, Guillaume; Leger, Serge; Bouchard, Cajetan (Proceedings of the 10th International Conference on Agents and Artificial Intelligence, 2018)
Collaborative filtering (CF) is a well-known and successful filtering technique that has its own limits, especially in dealing with highly sparse and large-scale data. To address this scalability issue, some researchers propose to use clustering methods like K-means that has the shortcomings of having its performances highly dependent on the manual definition of its number of clusters and on the selection of the initial centroids, which leads in case of ill-defined values to inaccurate recommendations and an increase in computation time. In this paper, we will show how the Merging and Splitting clustering algorithm can improve the performances of recommendation with reasonable computation time by comparing it with K-means based approach. Our experiment results demonstrate that the performances of our system are independent on the initial partition by considering the statistical nature of data. More specially, results in this paper provide significant evidences that the proposed splitting-merging clustering based CF is more scalable than the well-known K-means clustering based CF.
Keywords: information filtering; recommender systems; collaborative filtering; clustering; splitting-merging clustering

Bottom-up, robust graphene ribbon electronics in all-carbon molecular junctions - Supur, Mustafa; Van Dyck, Colin; Bergren, Adam J.; McCreery, Richard L. (ACS Applied Materials and Interfaces, 2018)
Large-area molecular electronic junctions consisting of 5-carbon wide graphene ribbons (GR) with lengths of 2–12 nm between carbon electrodes were fabricated by electrochemical reduction of diazotized 1,8-diaminonaphthalene. Their conductance greatly exceeds that observed for other molecular junctions of similar thicknesses, by a factor of >1 × 104 compared to polyphenylenes and >1 × 107 compared to alkane chains. The remarkable increase of conductance of the GR nanolayer results from (i) uninterrupted planarity of fused-arene structure affording extensive π-electron delocalization and (ii) enhanced electronic coupling of molecular layer with the carbon bottom contact by two-point covalent bonding, in agreement with DFT-based simulations.
Keywords: electron transport; graphene electronics; graphene ribbons; molecular electronics; molecular junction

Self-assembled vertically aligned Au nanorod arrays for surface-enhanced Raman Scattering (SERS) detection of Cannabinol - Milliken, Sarah; Fraser, Jeff; Poirier, Shawn; Hulse, John; Tay, Li-Lin (Spectrochimica Acta Part A: Molecular and Biomolecular Spectroscopy, 2018)
Self-assembled multi-layered vertically aligned gold nanorod (AuNR) arrays have been fabricated by a simple preparation process that requires a balance between the particle concentration and the ionic strength of the solvent. An experimentally determined critical AuNR concentration of 2.0 nM and 50 mM NaCl produces well-ordered vertically aligned hexagonally close-packed AuNR arrays. We demonstrate surface treatment via UV Ozone cleaning of such samples to allow introduction of analyte molecules (benzenethiol and cannabinol) for effective surface enhanced Raman scattering detection. This is the first demonstration of the SERS analysis of cannabinol. This approach demonstrates a cost-effective, high-yield and simple fabrication route to SERS sensors with application in the screening for the cannabinoids.
Keywords: SERS; Self-assembly; Au NR; Raman; Cannabinol; Plasmonics; Sensors; Cannabis

Estimate of scattering truncation in the cavity attenuated phase shift PMSSA monitor using the radiative transfer theory - Liu, Fengshan; Snelling, David; Thomson, Kevin; Smallwood, Gregory J. (Aerosol Science and Technology, 2018)
The recently developed cavity attenuated phase shift particulate matter single scattering albedo (CAPS PMssA) monitor has been shown to be fairly accurate and robust for real-time aerosol optical properties measurements. The scattering component of the measurement undergoes a truncation error due to the loss of scattered light from the sample tube in both the forward and backward directions. Previous studies estimated the loss of scattered light typically using the Mie theory for spherical particles, assuming particles are present only on the sampling tube centerline, and without accounting for the effects of sampling tube surface reflection. This study overcomes these limitations by solving the radiative transfer equation in an axisymmetric absorbing and scattering medium using the discrete ordinates method to estimate the scattering truncation error. The present mode! predicted larger scattering loss than the simplified theoretical estimate in the literature. The effects of absorption coefficient, scattering coefficient, asymmetry parameter of the scattering phase function, and the reflection coefficient at the sampling tube inner surface were investigated . Under typical conditions of CAPS PMssA operation of low extinction coefficients below about 5000 Mm- 1 the scattering loss remains independent of the absorption and scattering coefficients but is dependent on the asymmetry parameter of the scattering phase function and the reflection coefficient of the sampling glass tube inner surface. The scattering loss increases with increasing bath the asymmetry parameter and the surface reflection coefficient.
Keywords: aerosol optical properties; radiative transfer equation; scattering loss; cavity attenuated phase shift

Genetic characterization of type II Fusarium head blight resistance derived from transgressive segregation in a cross between Eastern and Western Canadian spring wheat - Zhang, Wentao; Francis, Tammy; Gao, Peng; Boyle, Kerry; Jiang, Fengying; Eudes, François; Cuthbert, Richard; Sharpe, Andrew (Molecular Breeding, 2018)
Fusarium head blight (FHB) caused by Fusarium graminearum is a devastating disease affecting global wheat production, causing significant losses to yield and grain quality. The Eastern Canadian line FL62R1 was developed using a systemic breeding approach and boasts high levels of FHB resistance with good yield, desirable agronomics, and end-use quality traits. The objective of this study was to identify genetic determinants of type II resistance in a cross between FL62R1 and cv. Stettler, a Canada Western Red Spring variety rated moderately susceptible to FHB. Although neither parent displayed strong resistance to FHB spread within spikes following point inoculation (type II resistance) in greenhouses, strong type II resistance was observed in a large number of progeny, including 6% with resistance comparable to the best check line, Sumai 3. Quantitative trait locus (QTL) mapping identified a locus from chromosome 2BL of Stettler which provides Sumai 3 level type II resistance when combined with favorable FHB resistance QTLs with minor effects from FL62R1. This study provides insight into transgressive segregation for FHB, which despite its importance is poorly understood, rare, and difficult to predict. It also begins to dissect the genetic architecture of FHB resistance in wheat derived from the systemic breeding approach.
Keywords: QTL; SNP; transgressive segregation; triticum aestivum L.; linkage; systemic breeding

A novel human induced pluripotent stem cell blood-brain barrier model: applicability to study antibody-triggered receptor-mediated transcytosis - Ribecco-Lutkiewicz, Maria; Sodja, Caroline; Haukenfrers, Julie; Haqqani, Arsalan S.; Ly, Dao; Zachar, Peter; Baumann, Ewa; Ball, Marguerite; Huang, Jez; Rukhlova, Marina; Martina, Marzia; Liu, Qing; et al. (Scientific Reports, 2018)
We have developed a renewable, scalable and transgene free human blood-brain barrier model, composed of brain endothelial cells (BECs), generated from human amniotic fluid derived induced pluripotent stem cells (AF-iPSC), which can also give rise to syngeneic neural cells of the neurovascular unit. These AF-iPSC-derived BECs (i-BEC) exhibited high transendothelial electrical resistance (up to 1500 Ω cm2) inducible by astrocyte-derived molecular cues and retinoic acid treatment, polarized expression of functional efflux transporters and receptor mediated transcytosis triggered by antibodies against specific receptors. In vitro human BBB models enable pre-clinical screening of central nervous system (CNS)-targeting drugs and are of particular importance for assessing species-specific/selective transport mechanisms. This i-BEC human BBB model discriminates species-selective antibody- mediated transcytosis mechanisms, is predictive of in vivo CNS exposure of rodent cross-reactive antibodies and can be implemented into pre-clinical CNS drug discovery and development processes.

Machine learning methods for analysis of metabolic data and metabolic pathway modeling - Cuperlovic-Culf, Miroslava (Metabolites, 2018)
Machine learning uses experimental data to optimize clustering or classification of samples or features, or to develop, augment or verify models that can be used to predict behavior or properties of systems. It is expected that machine learning will help provide actionable knowledge from a variety of big data including metabolomics data, as well as results of metabolism models. A variety of machine learning methods has been applied in bioinformatics and metabolism analyses including self-organizing maps, support vector machines, the kernel machine, Bayesian networks or fuzzy logic. To a lesser extent, machine learning has also been utilized to take advantage of the increasing availability of genomics and metabolomics data for the optimization of metabolic network models and their analysis. In this context, machine learning has aided the development of metabolic networks, the calculation of parameters for stoichiometric and kinetic models, as well as the analysis of major features in the model for the optimal application of bioreactors. Examples of this very interesting, albeit highly complex, application of machine learning for metabolism modeling will be the primary focus of this review presenting several different types of applications for model optimization, parameter determination or system analysis using models, as well as the utilization of several different types of machine learning technologies.
Keywords: system biology; metabolomics; metabolism modeling; machine learning; genomics

Establishing comparability and compatibility in the purity assessment of high purity zinc as demonstrated by the CCQM-P149 intercomparison - Vogl, Jochen; Kipphardt, Heinrich; Richter, Silke; Bremser, Wolfram; Arvizu, Maria del Rocio; Lara, Judith Velina; Buzoianu, Mirella; Hill, Sarah; Petrov, Panayot; Goenaga-Infante, Heidi; Sargent, Mike; Fisicaro, Paola; et al. (Metrologia, 2018)
For the first time, an international comparison was conducted on the determination of the purity of a high purity element. Participants were free to choose any analytical approach appropriate for their institute's applications and services. The material tested was a high purity zinc, which had earlier been assessed for homogeneity and previously used in CCQM-K72 for the determination of six defined metallic impurities. Either a direct metal assay of the Zn mass fraction was undertaken by EDTA titrimetry, or an indirect approach was used wherein all impurities, or at least the major ones, were determined and their sum subtracted from ideal purity of 100 %, or 1 kg/kg. Impurity assessment techniques included glow discharge mass spectrometry, inductively coupled plasma mass spectrometry and carrier gas hot extraction/combustion analysis. Up to 91 elemental impurities covering metals, non-metals and semi-metals/metalloids were quantified. Due to the lack of internal experience or experimental capabilities, some participants contracted external laboratories for specific analytical tasks, mainly for the analysis of non-metals. The reported purity, expressed as zinc mass fraction in the high purity zinc material, showed excellent agreement for all participants, with a relative standard deviation of 0.011 %. The calculated reference value, w(Zn) = 0.999 873 kg/kg, was assigned an asymmetric combined uncertainty of + 0.000025 kg/kg and – 0.000028 kg/kg. Comparability amongst participating metrology institutes is thus demonstrated for the purity determination of high purity metals which have no particular difficulties with their decomposition / dissolution process when solution-based analytical methods are used, or which do not have specific difficulties when direct analysis approaches are used. Nevertheless, further development is required in terms of uncertainty assessment, quantification of non-metals and the determination of purity of less pure elements and/or for those elements suffering difficulties with the decomposition process.

Multifunctional skin materials based on tailorable, carbon-nanotube-polyurethane composite sheets - Jakubinek, Michael; Ashrafi, Behnam; Rubi, Yadienka Martinez; Laqua, Kurtis; Palardy-Sim, Marc; Roy, Steven; Rahmat, Meysam; Sunesara, Amanul; Denommee, Stephane; Simard, Benoit (AIAA, 2018)

Evaluation of novel solutions for lightning strike protection of composites using current carrying capacity - Ashrafi, Behnam; Crodua, Josee; Jakubinek, Michael; Yang, Qi; Pankov, Vladimir; Rubi, Yadienka Martinez; Laqua, Kurtis; Park, Daesun; Baradari, Javad Gholipour; Simard, Benoit; Yousefpour, Ali (AIAA, 2018)

Correlation of alternative jet fuel physical properties to engine ignition at altitude conditions - Canteenwalla, Pervez; Corber, Andrew; Chishty, Wajid A. (AIAA, 2018)

A study on the effect of inorganic fillers on the dryband arcing erosion of silicone rubber composites - Ghunem, Refat Atef; El-Hag, Ayman H.; Hadjadj, Yazid; Chemey, Edward A. (2017 IEEE Conference on Electrical Insulation and Dielectric Phenomenon, 2018)
This paper investigates the erosion of silicone rubber composites filled with various fillers. The fillers under study are alumina tri-hydrate, magnesium hydroxide and silica in a liquid silicone ru bber. The inclined plane tracking and erosion test was used to compare the erosion of the composite materials at 50 wt% filler level and at 4.5 kV. Simultaneous thermogravimetric and differential thermal analyses are reported which shows various mechanisms by which the fillers can su ppress the dry band arcing erosion. The effect of water of hydration in the alumina tri-hyd rate and magnesium hydroxide is investigated and its effect on the suppression of the dry-band arcing erosion is reported for the composites filled with alumina tri-hydrate and magnesiu m hydroxide.

Stable isotope methodology for MC-ICPMS - Yang, Lu (2018)
Since its commercialization in 1992, the multicollector inductively coupled plasma mass spectrometry (MC-ICPMS) has quickly become a powerful research tool for the detennination of isotope amount ratios for its applications in a wide range of fields and disciplines Attributed to its inherited high sample throughput, publications of MC-ICPMS have grown exponentially over the last two decades. lt has reached a total of 12000 by March 2017, with 1400 publications in the year of 20 16 alone. This de/uge, however, has also created significant confusion and inconsistencies as to how to obtain highly accurate and precise isotope amount ratios using MC-ICPMS. Compared to the conventional therma l ionization mass spectrometry (TIMS), MC-ICPMS suffers much larger mass bias. In addition to mass-dependent fractionation (MDF), mass-independent fractionation (MIF) has also been reported in MC-ICPMS for many multi-isotopic elements. Consequently, proper choice of methodologies for correcting mass bias is of paramount importance when MC-ICPMS is used for the detennination of absolute isotope amount ratios. Current methodologies for the accurate isotope amount ratios measurements by MC-ICPMS will be reviewed and discussed in details. In particular, the latest developments in the regression mass bias correction method for the accurate isotope amount ratio measurements by MC-ICPMS and results obtained from our laboratory will be discussed in details in this lecture.

Dielectric measurements on polypropylene nanocomposites filled with natural and synthetic Nanoclay - Hadjadj, Y.; Ghunem, R. A. (2017 IEEE Conference on Electrical Insulation and Dielectric Phenomenon (CEIDP), 2018)
The Effect of the type, size and level of organoclay nanoparticles on the dielectric properties of polypropylene nanocomposites is investigated at different temperatures. Two types of nanoclay, synthetic and natural, are added to polypropylene at different levels. The incorporation of nanoclay into polypropylene is shown to increase the dielectric losses. Unlike the unfilled polypropylene, both real and imaginary part of the permittivity increases at low frequencies with the increase in the clay level. Such a finding can be related to the effect of the interface between the nanoclays and the host PP matrix. The effect of compatibilizer added, i.e maleic anhydride, on the losses at very low frequencies is more recognizable at 80 °C. This could be due the conductive nature of the maleic anhydride at higher temperatures. Lower losses were measured for the polypropylene filled with 2 wt% synthetic nanoclay as compared to polypropylene filled with 2 wt% of natural nano clay. This finding can be attributed to the effect of the size (aspect ratio) of the platelets.

Solution to the pink tea challenge - D'Ulivo, Lucia (Analytical and Bioanalytical Chemistry, 2018)

3D physical modelling and revetment design for the Billy Bishop Toronto City Airport extension - Baker, Scott; Cornett, Andrew; Glodowski, Chris (Coasts, Marine Structures and Breakwaters 2017: Realising the Potential, 2018)
As part of a planned development for Billy Bishop Toronto City Airport, new land reclamation and related marine works are required to extend both ends of the main runway into Lake Ontario. Wave conditions at the eastern end of the runway are relatively mild, as the site is sheltered inside Toronto Harbour. However, an extension at the western end of the runway will be directly exposed to strong winds, energetic wave conditions, high water levels, and winter ice conditions. An engineered revetment is required to prevent erosion, preserve stability, and protect the exposed western reclamation from attack by waves and ice. The design challenge was compounded by the requirement to minimize the frequency and extent of wave run-up and overtopping during storms as much as possible in order to avoid frequent inundation of the runway. At the same time, the crest elevation of the perimeter revetment was limited by the elevation of the existing runway and various other requirements for safe operations at the airport. A large-scale 3D physical modelling study was undertaken which played a crucial role in developing, testing, and optimizing the design of the perimeter revetment and for costing the marine works. In order to accommodate the stringent design requirements, several innovative revetment design concepts (featuring lower crest elevations, milder slopes, thicker filter layers, and thicker armour layers than normally seen in conventional designs) were tested in a wide range of harsh wave, wind, and water level conditions.

Laser-induced breakdown spectroscopy of molten matte - Moreau, André; Hamel, André; Bouchard, Paul; Sabsabi, Mohamad (CIM Journal, 2018)
Laser-induced breakdown spectroscopy (LIBS) is an atomic emission spectroscopy technique suitable for in-situ and in-line measurements during pyrometallurgy. A mobile prototype system was developed to measure elemental compositions of molten metals. An inert gas flows through a tube with its end immersed in molten metal and the gas bubbles out below the melt surface. The LIBS measurement is made through the tube and onto the bubble’s surface. This avoids measuring surface contaminants and slag. This paper presents the simultaneous measurement of Cu, Ni, Fe, Co, and S concentrations in molten matte at 1,125°C.
Keywords: LIBS; laser-induced breakdown spectroscopy; matte; copper; nickel; sensor